Baseline associations of office and ambulatory blood pressure monitoring with cognitive function and dementia prevalence. - Melgarejo, Jesus D; Patil, Dhrumil; Charisis, Sokratis; Vatcheva, Kristina P; Mejia-Arango, Silvia; Mena, Luis J; Satizabal, Claudia L; Gaona, Ciro; Silva, Egle; Manusov, Eron; Lee, Joseph H; Terwilliger, Joseph D; et al. (J Alzheimers Dis, 2025)
BackgroundHigh blood pressure has been associated with dementia prevalence and incident. However, it is unclear the relationship of office and ambulatory BP monitoring with cognitive function and dementia and in particular, it remains unknown whether ambulatory BP variability relates to dementia.ObjectiveTo investigate the associations of office and 24-h blood pressure (BP) with cognitive function and dementia prevalence.MethodsCross-sectional population-based study of 1435 participants aged ≥40 years with office BP/24-h BP, and cognitive assessments (Mini-Mental State Examination [MMSE] and Selective Reminding Test [SRT]). Dementia was diagnosed with a clinical dementia rating ≥1.0. Statistics included logistic and linear regression models.ResultsThe mean age was 63.8 ± 10.3 years old and 995 (69.3%) were women. Out of the 1435 participants, 46 (3.20%) had dementia at baseline. Office and 24-h BP levels were not associated with dementia but with one SRT. Increasing 24-h systolic BP variability was associated with lower MMSE (adjusted mean, -0.08; 95% confidence interval [CI], -0.13, -0.03), and SRT (adjusted means ranged from -0.13 to -0.06; 95% CI ranging from -0.19 to -0.01) scores and 1.48-fold greater odds of dementia (95% CI, 1.09-2.02) regardless of BP level.ConclusionsElevated 24-h BP variability, not the BP level, seems to have a stronger association with lower cognitive function and dementia prevalence. Prospective studies are needed to address whether 24-h BP variability relates to cognitive decline and dementia incidence.

Cost-effectiveness of diagnosing and treating patients with early Alzheimer's disease with anti-amyloid treatment in a clinical setting. - Wimo, Anders; Handels, Ron; Blennow, Kaj; Kirsebom, K Bjørn-Eivind; Selnes, Per; Bon, Jaka; Emersic, Andreja; Gonzalez-Ortiz, Fernando; Gregoric Kramberger, Milica; Sköldunger, Anders; Speh, Andreja; Timón-Reina, Santiago; et al. (J Alzheimers Dis, 2025)
BackgroundThe introduction of anti-amyloid treatments (AAT) for Alzheimer's disease (AD) has put the cost-effectiveness into focus.ObjectiveEstimate the potential cost-effectiveness of diagnostic pathways combined with AAT for early AD.MethodsDiagnostic accuracy of blood-based (BBM) and cerebrospinal fluid (CSF) biomarkers was obtained from Norwegian memory clinics using positron emission tomography (PET) as reference standard. In a health-economic model, the cost-effectiveness of three diagnostic strategies was estimated relying either on BBM (p-tau 217), CSF (Aβ ratio), and BBM with CSF confirmatory testing and compared with standard of care (SoC) and compared with CSF-AAT. The model consisted of a decision tree reflecting the diagnostic process and a subsequent Markov cohort model starting at mild cognitive impairment due to AD. All strategies except SoC were combined with AAT including costs of treatment (assumed €5000/year), infusions and monitoring.ResultsCompared with SoC all three strategies (CSF-AAT, BBM-AAT, and BBM-CSF-AAT) resulted in QALY gains at higher costs, with an incremental cost-effectiveness ratio (ICER) of 110k€, 141k€ and 110k€ respectively. Compared with CSF-AAT both BBM-AAT and BBM-CSF-AAT strategies resulted in QALYs lost at lower costs, with an ICER of 27k€ and 109k€ respectively. Results were particularly sensitive to the price of AAT and possible subcutaneous administration.ConclusionsCompared with SoC all three strategies are potentially not cost-effective as they exceeded the Swedish maximum willingness to pay threshold of €94,800 per QALY gained. BBM-CSF-AAT versus CSF-AAT is potentially cost-effective if willing to accept its QALY loss. Discussions on budget impact on different payers are needed after introducing AAT.

Dynamic PET imaging in patients with unilateral carotid occlusion shows lateralized cerebral hypoperfusion, but no amyloid binding. - Starmans, Naomi Lp; Leeuwis, Anna E; Bennink, Edwin; Meyer Viol, Sebastiaan L; Golla, Sandeep Sv; Dankbaar, Jan Willem; Bron, Esther E; Biessels, Geert Jan; Kappelle, L Jaap; van der Flier, Wiesje M; Tolboom, Nelleke (J Alzheimers Dis, 2025)
BackgroundCarotid occlusive disease is a risk factor for cognitive decline. A possible underlying etiology is that hemodynamic impairment results in decreased cerebral perfusion, exacerbated amyloid-β accumulation (Aβ) and poorer cognitive performance.ObjectiveWe aimed to determine whether patients with unilateral internal carotid artery (ICA) occlusion have less cerebral perfusion and more Aβ in the ipsilateral than in the contralateral hemisphere, and whether perfusion and Aβ are associated with cognitive functioning.MethodsWe included 20 patients (age 67.2 ± 7.0 years, 8 females, MMSE 29 [27-29]) with unilateral ICA occlusion, which underwent neuropsychological assessment and dynamic F-Florbetaben positron emission tomography (PET). Global and regional relative perfusion (R) and binding potential (BP) were obtained from the PET-images using a simplified reference tissue model. We performed Wilcoxon signed-rank tests to examine differences between hemispheres within subjects and linear regression to investigate associations with cognitive functioning.ResultsMedian global R was 0.911 (0.883-0.950) and global BP was 0.172 (0.129-0.187). R was lower in the hemisphere ipsilateral to the ICA occlusion than in the contralateral hemisphere (0.899 [0.876-0.921] versus 0.935 [0.889-0.970]). BP did not differ significantly between hemispheres (ipsilateral 0.172 [0.124-0.181] versus contralateral 0.168 [0.137-0.191]). Neither cerebral perfusion nor Aβ burden were associated with cognitive functioning.ConclusionsPatients with unilateral ICA occlusion did not have more Aβ in the ipsilateral hemisphere than in the contralateral hemisphere despite ipsilateral hypoperfusion. Perfusion and Aβ were unrelated to cognitive functioning. This indicates that cognitive impairment in patients with ICA occlusion is not due to exacerbated Aβ accumulation.

Interactive effects of ɛ4 status and vascular burden on white matter microstructural integrity in aging with and without neurocognitive decline. - Konwar, Srijan; Manca, Riccardo; De Marco, Matteo; Soininen, Hilkka; Venneri, Annalena (J Alzheimers Dis, 2025)
BackgroundCarrying the Apolipoprotein () ε4 allele lowers age of onset and increases Alzheimer's disease (AD) risk. Neuropathological findings suggest a mixed etiology in many AD patients, and vascular pathology is common.ObjectiveThis study tested the interactive effect of status and multiple vascular comorbidities on white matter (WM) microstructure in aging and early AD.Methods195 participants from the VPH-DARE@IT dataset were stratified in low/high vascular burden based on the Framingham Risk Score (BMI version). Tract-based spatial statistics was used for WM analyses.ResultsThere was a main effect of , with ɛ4 carriers having higher fractional anisotropy (FA) and lower axial diffusivity (AxD), mean diffusivity (MD), and radial diffusivity (RD) than non-carriers. There was a main effect of vascular burden with lower FA and higher AxD, MD, and RD in the high-burden than the low-burden group. A significant interaction between genotype and vascular burden was also found for all diffusion indices. comparisons revealed lower left hemisphere WM integrity when comparing the low risk group (i.e., non-carriers low burden) to intermediate risk groups (i.e., non-carriers high burden or ɛ4 carriers low burden). The contrasts between the two intermediate risk groups showed altered WM integrity bilaterally. Only the non-carriers high burden showed greater alterations in WM integrity when compared with the high risk group (i.e., ɛ4 carriers high burden) mainly in right hemisphere tracts.ConclusionsThese findings indicate an interactive effect of a risk gene and vascular comorbidities on WM integrity in aging and early AD.

Performance of a smell identification test versus the Mini-Mental Status Exam for the detection of dementia and cognitive impairment among persons with cognitive concerns in primary care. - Luchsinger, Jose A; Teresi, Jeanne A; Valdez, Lenfis; Rosario, Dahiana; de Miguel, Maria; Taylor, Delphine; Singer, Jessica; Chang, Nancy; Fuller, William S; Boquín, Cyrus; Silver, Stephanie; Eimicke, Joseph P; et al. (J Alzheimers Dis, 2025)
BackgroundOdor identification deficits predict Alzheimer's disease (AD) in epidemiological studies.ObjectiveTo compare the accuracy of a short odor identification test with a short cognitive screening test for the detection of dementia and cognitive impairment in elderly persons with cognitive concerns.MethodsThis was a cross-sectional study of 600 participants 65 years and older, without known mild cognitive impairment (MCI) or dementia, with cognitive concerns, attending primary care practices in New York City. The odor identification test was the Brief Smell Identification Test (BSIT). The comparator test was the Mini Mental Status Exam II (MMSE). Cognitive diagnoses were made using the National Alzheimer's Coordinating Center Uniform Data set (NACC-UDS) version 3 forms with slight modifications. Test performance was compared using Receiver Operating Characteristic analyses.ResultsThe mean age was 72.65 ± 6.31 years, 73.3% were female, 63.3% were Hispanic, 13.5% non-Hispanic Black, and 20.8% non-Hispanic White; 23.5% were classified as normal cognition, 27.7% as cognitive impairment-not mild cognitive impairment (MCI), 31.2% as amnestic MCI, 5.7% as non-amnestic MCI, and 12% as dementia. The MMSE was superior to the BSIT in detecting dementia and any cognitive impairment. Combining abnormal scores in the BSIT (≤8) to MMSE (≤24) improved the MMSE's specificity and positive predictive value (PPV) in detecting cognitive impairment.ConclusionsThe MMSE was superior to the BSIT in detecting dementia and cognitive impairment in primary care but using both tests improved specificity and PPV for identifying persons with subjective complaints needing further cognitive and biomarker evaluation.

African Ancestry Individuals with Higher Educational Attainment Are Resilient to Alzheimer's Disease Measured by pTau181. - Rajabli, Farid; Seixas, Azizi A; Akgun, Bilcag; Adams, Larry D; Inciute, Jovita; Hamilton, Kara L; Whithead, Patrice G; Konidari, Ioanna; Gu, Tianjie; Arvizu, Jamie; Golightly, Charles G; Starks, Takiyah D; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive and functional abilities in individuals with Alzheimer's disease (AD) pathology (ADP) are highly variable. Factors contributing to this variability are not well understood. Previous research indicates that higher educational attainment (EA) correlates with reduced cognitive impairments among those with ADP. While cognitive and functional impairments are correlated, they are distinguishable in their manifestations. OBJECTIVE: To investigate whether levels of education are associated with functional impairments among those with ADP. METHODS: This research involved 410 African American (AA) individuals (Institutional Review Boards 20070307, 01/27/2023) to ascertain whether EA correlates with functional resilience and if this effect varies between APOE ɛ4 carriers and non-carriers. Utilizing EA as a cognitive reserve proxy, CDR-FUNC as a functional difficulties measure, and blood pTau181 as an ADP proxy, the non-parametric Mann-Whitney U test assessed the relationship between EA and CDR-FUNC in individuals with advanced pTau181 levels. RESULTS: The results showed that EA correlated with functional difficulties in AA individuals with high levels of pTau181, such that individuals with high EA are more likely to have better functional ability compared to those with lower EA (W = 730.5, p = 0.0007). Additionally, we found that the effect of high EA on functional resilience was stronger in ɛ4 non-carriers compared to ɛ4 carriers (W = 555.5, p = 0.022). CONCLUSION: This study extends the role of cognitive reserve and EA to functional performance showing that cognitive reserve influences the association between ADP burden and functional difficulties. Interestingly, this protective effect seems less pronounced in carriers of the strong genetic risk allele ɛ4.
Keywords: Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Educational Status; Humans; Resilience, Psychological

Alzheimer's Disease and Cognitive Decline in Patients with Cardiovascular Diseases Along the Heart-Brain Axis. - Trieu, Calvin; Van Harten, Argonde C; Leeuwis, Anna E; Exalto, Lieza G; Hooghiemstra, Astrid M; Verberk, Inge M W; Allaart, Cor P; Brunner-La Rocca, Hans-Peter; Kappelle, L Jaap; van Oostenbrugge, Robert J; Biessels, Geert-Jan; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2024)
BACKGROUND: We hypothesize that Alzheimer's disease (AD)-related pathology may accelerate cognitive decline in patients with cardiovascular diseases. OBJECTIVE: To investigate the association between blood-based biomarkers of AD, astrocyte activation, and neurodegeneration and cognitive decline. METHODS: From the multi-center Heart-Brain study, we included 412 patients with heart failure, carotid occlusive disease or vascular cognitive impairment (age:68.6±9.0) and 128 reference participants (65.7±7.5). Baseline amyloid-β42/40 (Aβ42/40), phosphorylated-tau181 (pTau181), glial fibrillary acidic protein (GFAP), and neurofilament light (NfL) were determined using SiMoA (Quanterix). Memory, attention, language, and executive functioning were evaluated (follow-up:2.1±0.3 years). We applied linear mixed models with terms for biomarker, time and biomarker*time interactions, adjusted for age, sex, education, and site, to assess associations between biomarkers and cognitive decline. RESULTS: Among patients, Aβ42/40 was not associated with cognitive performance at baseline. However, lower Aβ42/40 was associated with steeper decline in global cognition (β±SE:0.04±0.02). Higher pTau181 was associated with worse baseline performance on global cognition (-0.14±0.04) and memory (-0.31±0.09) and with steeper decline in global cognition (-0.07±0.02), memory (-0.09±0.04), attention (-0.05±0.02), and language (-0.10±0.03). Higher GFAP was associated with worse baseline performance on global cognition (-0.22±0.05), memory (-0.43±0.10), attention (-0.14±0.06), language (-0.15±0.05), and executive functioning (-0.15±0.05) and steeper decline in global cognition (-0.05±0.01). Higher NfL was associated with worse baseline performance on global cognition (-0.16±0.04), memory (-0.28±0.09), attention (-0.20±0.06), and executive functioning (-0.10±0.04), but was not associated with performance over time. In reference participants, no associations were found. CONCLUSIONS: Our findings suggest that blood-based biomarkers of AD-related pathology predict cognitive decline in patients with cardiovascular diseases.

The Association Between Neuropathological Lesions and Body Mass Index Is Independent of Cognitive Abilities. - Ururahy, Raul Dos Reis; do Val, Marina Scott; Ciciliati, Aline Maria Macagnan; Leite, Renata Elaine Paraizo; Paes, Vitor Ribeiro; Rodrigues, Roberta Diehl; Grinberg, Lea Tenenholz; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Suemoto, Claudia Kimie (J Alzheimers Dis, 2024)
BACKGROUND: The association of moderate and severe dementia with low body mass index (BMI) is well described, but weight decline seems to also occur in individuals with preclinical neuropathologies. Considering that up to one-fifth of individuals with normal cognition meet the criteria for a dementia-related neuropathological diagnosis, autopsy studies are key to detecting preclinical neurodegenerative and cerebrovascular diseases that could be underlying weight changes. OBJECTIVE: We investigated the association between dementia-related brain lesions and BMI and evaluated whether the cognitive function was a mediator of this association. METHODS: In 1,170 participants, sociodemographic data, clinical history, and cognitive post-mortem evaluation were assessed with an informant. Neuropathological evaluation was performed in all cases. Linear regression models were used to investigate the association between neuropathological lesions (exposure variable) and BMI (outcome) adjusted for demographic, clinical, and cognitive variables in the whole sample, and in only those with normal cognition. Corrections for multiple comparisons were performed. In addition, a mediation analysis was performed to investigate the direct and indirect effects of cognitive abilities on the association between neuropathology and BMI. RESULTS: Individuals with lower BMI had a higher burden of neuropathological lesions and poorer cognitive abilities. Only neurofibrillary tangles (NFT) and neuropathological comorbidity were associated with low BMI, while other neurodegenerative and cerebrovascular lesions were not. NFT were indirectly associated with BMI through cognitive abilities, and also directly, even in participants with normal cognition. CONCLUSIONS: Neurofibrillary tangles were directly associated with low BMI even in individuals with preclinical Alzheimer's disease.

Circulating adipokines and MRI markers of brain aging in middle-aged adults from the community. - Satizabal, Claudia L; Himali, Jayandra Jung; Conner, Sarah C; Beiser, Alexa S; Maillard, Pauline; Vasan, Ramachandran S; DeCarli, Charles; Seshadri, Sudha (J Alzheimers Dis, 2024)
BACKGROUND: Midlife obesity is related to late-onset dementia. Studying adipose tissue-secreted adipokines in the context of brain aging may help us understand this association. OBJECTIVE: To investigate associations between adipokines and brain MRI markers in middle-aged adults from the Third-Generation cohort of the Framingham Heart Study. METHODS: Serum adiponectin, retinol-binding protein 4 (RBP4), fetuin-A, and Fatty Acid-Binding Protein 4 (FABP4) concentrations were measured by enzymatic immunoassays. MRI measures included total brain, cortical gray matter, hippocampal (total and anterior), lateral ventricular, and white matter hyperintensity volumes. We used linear regression models to separately relate adipokine concentrations to MRI measures, adjusting for potential confounders. RESULTS: We included 1882 participants (mean age of 48 ± 8 years, 54% women). Higher RBP4 concentrations were related to markers of brain atrophy, including smaller total (Beta ± standard error, -0.05 ± 0.02; p = 0.014) and cortical gray brain volumes (-0.06 ± 0.02; p = 0.004), and larger lateral ventricular volumes (0.06 ± 0.02; p = 0.006). Additionally, higher RBP4 (-0.06 ± 0.03; p = 0.042), Fetuin-A (-0.06 ± 0.03; p = 0.039), and FABP4 (-0.09 ± 0.03; p = 0.008) concentrations were associated with smaller anterior hippocampal volumes. Most associations remained after additional adjustment for vascular risk factors. In exploratory analyses, higher FABP4 was related to larger total brain in non-obese participants, and to smaller anterior hippocampal volumes in obese participants. Finally, higher adiponectin concentrations were related to smaller cortical gray, only in non-obese participants. CONCLUSIONS: Our results suggest that adipokines are associated with markers of brain atrophy during midlife. Further studies are needed to replicate these findings and elucidate any potential mechanisms contributing to abnormal brain aging.
Keywords: Adipokines; Adiponectin; Adult; Aging; alpha-2-HS-Glycoprotein; Atrophy; Biomarkers; Brain; Cohort Studies; Fatty Acid-Binding Proteins; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Retinol-Binding Proteins, Plasma

Cognitive Outcomes in Autosomal-Dominant Alzheimer's Disease: A Comprehensive Review from a Colombian Kindred with the Presenilin-1 E280A Mutation. - Giudicessi, Averi; McDowell, Celina Pluim; Martinez, Jairo E; Baena, Ana; Vila-Castelar, Clara; Norton, Daniel; Aguirre-Acevedo, Daniel C; Tirado, Victoria; Bocanegra, Yamile; Guzmán-Vélez, Edmarie; Lopera, Francisco; Cronin-Golomb, Alice; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The largest identified kindred worldwide with a single mutation causing autosomal-dominant Alzheimer's disease (ADAD) is a family from Antioquia, Colombia, carrying the Presenilin-1 (PSEN1) E280A (Paisa) mutation. The majority of mutation carriers develop dementia, typically commencing in their late 30 s, with a median onset age of 49 years. Cognitive decline is a hallmark feature. OBJECTIVE: This review synthesizes the existing literature on neuropsychological assessments in PSEN1 E280A mutation carriers throughout their lifespan. We provide a comprehensive overview of cognitive outcomes in this unique population. METHODS: We reviewed and integrated the published research, analyzing studies on neuropsychological assessments in PSEN1 E280A carriers. Our focus was on measures of verbal, semantic, episodic, and spatial memory, and encompassed other cognitive domains such as language, attention, visuospatial memory, and executive functioning. RESULTS: Verbal, semantic, episodic, and spatial memory emerged as the most sensitive indicators of preclinical changes in PSEN1 E280A carriers. Inconsistencies were noted in findings from tests assessing language, attention, visuospatial memory, and executive functioning, suggesting potential limitations in detecting early cognitive changes in PSEN1 mutation carriers. Specific cognitive tasks developed for this population proved effective but underutilized. CONCLUSIONS: The review underscores the importance of continued test development tailored to detect early cognitive changes in PSEN1 E280A carriers, potentially enhancing ADAD screening. Furthermore, investigating ADAD mutations in children may identify early changes in AD and enhance our understanding of neuropsychological functioning across the lifespan. This synthesis provides valuable insights for researchers, clinicians, and policymakers engaged in the study and management of ADAD.

Creating an Unprotected Class: Addressing Legal Risks in the Era of Biologically-Defined Alzheimer's Disease. - Vaishnav, Neil; Gonzalez, Rosa; Karunungan, Krystal; Tyler, Ana; Zheng, William; Arias, Jalayne J (J Alzheimers Dis, 2024)
BACKGROUND: Documentation of preclinical biomarker tests for Alzheimer's disease (AD) in the medical record may expose patients to employment and insurance discrimination risks. There is a gap in research describing clinicians' approaches to documenting biomarker results. OBJECTIVE: To evaluate discrimination risks faced by patients undergoing biomarker testing for AD through a qualitative analysis of clinician documentation practices. METHODS: Semi-structured interviews using hypothetical patient scenarios. The qualitative analysis focused on interviewees' responses related to documentation and disclosure of results. RESULTS: We collected and analyzed 17 interviews with dementia experts; and identified three approaches to documenting biomarkers as: an association with active AD, noninformative, and an increased susceptibility for AD. Those who associated biomarkers with active disease were more likely to favor disclosure to employers and insurers, which could increase discrimination risks. CONCLUSIONS: This study demonstrates the variety of documentation and disclosure practices likely to emerge for preclinical AD biomarker tests and highlights a need for guidelines in this area.
Keywords: Alzheimer Disease; Biomarkers; Disclosure; Humans

FACEmemory®, an Innovative Online Platform for Episodic Memory Pre-Screening: Findings from the First 3,000 Participants. - Alegret, Montserrat; García-Gutiérrez, Fernando; Muñoz, Nathalia; Espinosa, Ana; Ortega, Gemma; Lleonart, Núria; Rodríguez, Isabel; Rosende-Roca, Maitee; Pytel, Vanesa; Cantero-Fortiz, Yahveth; Rentz, Dorene M; Marquié, Marta; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The FACEmemory® online platform comprises a complex memory test and sociodemographic, medical, and family questions. This is the first study of a completely self-administered memory test with voice recognition, pre-tested in a memory clinic, sensitive to Alzheimer's disease, using information and communication technologies, and offered freely worldwide. OBJECTIVE: To investigate the demographic and clinical variables associated with the total FACEmemory score, and to identify distinct patterns of memory performance on FACEmemory. METHODS: Data from the first 3,000 subjects who completed the FACEmemory test were analyzed. Descriptive analyses were applied to demographic, FACEmemory, and medical and family variables; t-test and chi-square analyses were used to compare participants with preserved versus impaired performance on FACEmemory (cut-off = 32); multiple linear regression was used to identify variables that modulate FACEmemory performance; and machine learning techniques were applied to identify different memory patterns. RESULTS: Participants had a mean age of 50.57 years and 13.65 years of schooling; 64.07% were women, and 82.10% reported memory complaints with worries. The group with impaired FACEmemory performance (20.40%) was older, had less schooling, and had a higher prevalence of hypertension, diabetes, dyslipidemia, and family history of neurodegenerative disease than the group with preserved performance. Age, schooling, sex, country, and completion of the medical and family history questionnaire were associated with the FACEmemory score. Finally, machine learning techniques identified four patterns of FACEmemory performance: normal, dysexecutive, storage, and completely impaired. CONCLUSIONS: FACEmemory is a promising tool for assessing memory in people with subjective memory complaints and for raising awareness about cognitive decline in the community.

Herpes Simplex Viral Infection Doubles the Risk of Dementia in a Contemporary Cohort of Older Adults: A Prospective Study. - Vestin, Erika; Boström, Gustaf; Olsson, Jan; Elgh, Fredrik; Lind, Lars; Kilander, Lena; Lövheim, Hugo; Weidung, Bodil (J Alzheimers Dis, 2024)
BACKGROUND: Evidence indicates that herpes simplex virus (HSV) participates in the pathogenesis of Alzheimer's disease (AD). OBJECTIVE: We investigated AD and dementia risks according to the presence of herpesvirus antibodies in relation to anti-herpesvirus treatment and potential APOE ɛ4 carriership interaction. METHODS: This study was conducted with 1002 dementia-free 70-year-olds living in Sweden in 2001-2005 who were followed for 15 years. Serum samples were analyzed to detect anti-HSV and anti-HSV-1 immunoglobulin (Ig) G, anti-cytomegalovirus (CMV) IgG, anti-HSV IgM, and anti-HSV and anti-CMV IgG levels. Diagnoses and drug prescriptions were collected from medical records. Cox proportional-hazards regression models were applied. RESULTS: Cumulative AD and all-cause dementia incidences were 4% and 7%, respectively. Eighty-two percent of participants were anti-HSV IgG carriers, of whom 6% received anti-herpesvirus treatment. Anti-HSV IgG was associated with a more than doubled dementia risk (fully adjusted hazard ratio = 2.26, p = 0.031). No significant association was found with AD, but the hazard ratio was of the same magnitude as for dementia. Anti-HSV IgM and anti-CMV IgG prevalence, anti-herpesvirus treatment, and anti-HSV and -CMV IgG levels were not associated with AD or dementia, nor were interactions between anti-HSV IgG and APOE ɛ4 or anti-CMV IgG. Similar results were obtained for HSV-1. CONCLUSIONS: HSV (but not CMV) infection may be indicative of doubled dementia risk. The low AD incidence in this cohort may have impaired the statistical power to detect associations with AD.

High-Fat Diets in Animal Models of Alzheimer's Disease: How Can Eating Too Much Fat Increase Alzheimer's Disease Risk? - Valentin-Escalera, Josue; Leclerc, Manon; Calon, Frederic (J Alzheimers Dis, 2024)
High dietary intake of saturated fatty acids is a suspected risk factor for neurodegenerative diseases, including Alzheimer's disease (AD). To decipher the causal link behind these associations, high-fat diets (HFD) have been repeatedly investigated in animal models. Preclinical studies allow full control over dietary composition, avoiding ethical concerns in clinical trials. The goal of the present article is to provide a narrative review of reports on HFD in animal models of AD. Eligibility criteria included mouse models of AD fed a HFD defined as > 35% of fat/weight and western diets containing > 1% cholesterol or > 15% sugar. MEDLINE and Embase databases were searched from 1946 to August 2022, and 32 preclinical studies were included in the review. HFD-induced obesity and metabolic disturbances such as insulin resistance and glucose intolerance have been replicated in most studies, but with methodological variability. Most studies have found an aggravating effect of HFD on brain Aβ pathology, whereas tau pathology has been much less studied, and results are more equivocal. While most reports show HFD-induced impairment on cognitive behavior, confounding factors may blur their interpretation. In summary, despite conflicting results, exposing rodents to diets highly enriched in saturated fat induces not only metabolic defects, but also cognitive impairment often accompanied by aggravated neuropathological markers, most notably Aβ burden. Although there are important variations between methods, particularly the lack of diet characterization, these studies collectively suggest that excessive intake of saturated fat should be avoided in order to lower the incidence of AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Diet, High-Fat; Disease Models, Animal; Fatty Acids; Mice; Mice, Transgenic

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Interaction Between Arteriosclerosis and Amyloid-β on Cognitive Function. - Frentz, Ingeborg; van Arendonk, Joyce; Leeuwis, Anna E; Vernooij, Meike W; van der Flier, Wiesje M; Bos, Daniel; De Deyn, Peter Paul; Wolters, Frank J; Ikram, M Arfan (J Alzheimers Dis, 2024)
BACKGROUND: Dementia is a multifactorial disease, with Alzheimer's disease (AD) and vascular pathology often co-occurring in many individuals with dementia. Yet, the interplay between AD and vascular pathology in cognitive decline is largely undetermined. OBJECTIVE: The aim of the present study was to examine the joint effect of arteriosclerosis and AD pathology on cognition in the general population without dementia. METHODS: We determined the interaction between blood-based AD biomarkers and CT-defined arteriosclerosis on cognition in 2,229 dementia-free participants of the population-based Rotterdam Study (mean age: 68.9 years, 52% women) cross-sectionally. RESULTS: Amyloid-β (Aβ)42 and arterial calcification were associated with cognitive performance. After further adjustment for confounders in a model that combined all biomarkers, only arterial calcification remained independently associated with cognition. There was a significant interaction between arterial calcification and Aβ42 and between arterial calcification and the ratio of Aβ42/40. Yet, estimates attenuated, and interactions were no longer statistically significant after adjustment for cardio metabolic risk factors. CONCLUSIONS: Arteriosclerosis and AD display additive interaction-effects on cognition in the general population, that are due in part to cardio metabolic risk factors. These findings suggest that joint assessment of arteriosclerosis and AD pathology is important for understanding of disease etiology in individuals with cognitive impairment.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Arteriosclerosis; Biomarkers; Cognition; Cognitive Dysfunction; Female; Humans; Male; tau Proteins

Long Non-Coding RNA Profile in Genetic Symptomatic and Presymptomatic Frontotemporal Dementia: A GENFI Study. - Serpente, Maria; Fenoglio, Chiara; Arcaro, Marina; Carandini, Tiziana; Sacchi, Luca; Pintus, Manuela; Rotondo, Emanuela; Borracci, Vittoria; Ghezzi, Laura; Bouzigues, Arabella; Russell, Lucy L; Foster, Phoebe H; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Long non-coding RNAs (lncRNAs) play crucial roles in gene regulation and are implicated in neurodegenerative diseases, including frontotemporal dementia (FTD). However, their expression patterns and potential as biomarkers in genetic FTD involving Chromosome 9 Open Reading Frame (C9ORF72), Microtubule Associated Protein Tau (MAPT), and Progranulin (GRN) genes are not well understood. OBJECTIVE: This study aimed to profile the expression levels of lncRNAs in peripheral blood mononuclear cells collected within the GENetic Frontotemporal dementia Initiative (GENFI). METHODS: Fifty-three lncRNAs were analyzed with the OpenArray Custom panel, in 131 patients with mutations in C9ORF72, MAPT, and GRN, including 68 symptomatic mutation carriers (SMC) and 63 presymptomatic mutation carriers (PMC), compared with 40 non-carrier controls (NC). RESULTS: Thirty-eight lncRNAs were detectable; the relative expression of NEAT1 and NORAD was significantly higher in C9ORF72 SMC as compared with NC. GAS5 expression was instead significantly lower in the GRN group versus NC. MAPT carriers showed no significant deregulations. No significant differences were observed in PMC. Disease duration did not correlate with lncRNA expression. CONCLUSIONS: NEAT1 and NORAD are upregulated in C9ORF72 SMC and GAS5 levels are downregulated in GRN SMC, underlining lncRNAs' relevance in FTD and their potential for biomarker development. Further validation and mechanistic studies are crucial for clinical implications.

Markers of amyloid-β deposition and burden of enlarged perivascular spaces in patients with cognitive impairment and small vessel disease. - Costa, Ana Sofia; Exalto, Lieza G; van der Flier, Wiesje M; Teunissen, Charlotte E; Barkhof, Frederik; Kuijf, Hugo J; Biessels, Geert Jan (J Alzheimers Dis, 2024)
MRI-visible enlarged perivascular spaces (EPVS) are common in patients with cognitive impairment and possibly linked to Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA). In a study of memory clinic patients (n = 450; mean age 66.5 ± 7.45, 45.8% female), we investigated CSF amyloid-β (Aβ) (AD biomarker) and strictly lobar microbleeds (CAA marker) in relation to centrum semiovale EPVS (CSO-EPVS). Age-controlled analyses showed that severe CSO-EPVS associated with Aβ status (odds ratio [OR] = 1.51, 95%CI = 1.02-2.24), but not strictly lobar microbleeds (OR = 1.39, 95%CI = 0.92-2.11), with no significant Aβ status and microbleeds interaction. This implies that in this setting, severe CSO-EPVS is not a specific indicator of CAA.

Mayo Normative Studies: Amyloid and Neurodegeneration Negative Normative Data for the Auditory Verbal Learning Test and Sex-Specific Sensitivity to Mild Cognitive Impairment/Dementia. - Stricker, Nikki H; Christianson, Teresa J; Pudumjee, Shehroo B; Polsinelli, Angelina J; Lundt, Emily S; Frank, Ryan D; Kremers, Walter K; Machulda, Mary M; Fields, Julie A; Jack, Clifford R; Knopman, David S; Graff-Radford, Jonathan; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Conventional normative samples include individuals with undetected Alzheimer's disease neuropathology, lowering test sensitivity for cognitive impairment. OBJECTIVE: We developed Mayo Normative Studies (MNS) norms limited to individuals without elevated amyloid or neurodegeneration (A-N-) for Rey's Auditory Verbal Learning Test (AVLT). We compared these MNS A-N- norms in female, male, and total samples to conventional MNS norms with varying levels of demographic adjustments. METHODS: The A-N- sample included 1,059 Mayo Clinic Study of Aging cognitively unimpaired (CU) participants living in Olmsted County, MN, who are predominantly non-Hispanic White. Using a regression-based approach correcting for age, sex, and education, we derived fully-adjusted T-score formulas for AVLT variables. We validated these A-N- norms in two independent samples of CU (n = 261) and mild cognitive impairment (MCI)/dementia participants (n = 392) > 55 years of age. RESULTS: Variability associated with age decreased by almost half in the A-N- norm sample relative to the conventional norm sample. Fully-adjusted MNS A-N- norms showed approximately 7- 9% higher sensitivity to MCI/dementia compared to fully-adjusted MNS conventional norms for trials 1- 5 total and sum of trials. Among women, sensitivity to MCI/dementia increased with each normative data refinement. In contrast, age-adjusted conventional MNS norms showed greatest sensitivity to MCI/dementia in men. CONCLUSIONS: A-N- norms show some benefits over conventional normative approaches to MCI/dementia sensitivity, especially for women. We recommend using these MNS A-N- norms alongside MNS conventional norms. Future work is needed to determine if normative samples that are not well characterized clinically show greater benefit from biomarker-refined approaches.

Optimizing the Implementation of a Lifestyle Dementia Prevention Intervention for Older Patients in an Academic Healthcare System. - Mace, Ryan A; Lyons, Christopher; Cohen, Joshua E; Ritchie, Christine; Bartels, Stephen; Okereke, Olivia I; Hoeppner, Bettina B; Brewer, Judson A; Vranceanu, Ana-Maria (J Alzheimers Dis, 2024)
BACKGROUND: Interventions that promote healthy lifestyles are critical for the prevention of Alzheimer's disease and Alzheimer's disease related dementias (AD/ADRD). However, knowledge of the best practices for implementing AD/ADRD prevention in healthcare settings remains limited. OBJECTIVE: We aimed to qualitatively identify barriers and facilitators to implementing a clinical trial of a novel lifestyle intervention (My Healthy Brain) in our medical center for older patients with subjective cognitive decline who are at-risk for AD/ADRD. METHODS: We conducted focus groups with 26 healthcare professionals (e.g., physicians, psychology, nursing) from 5 clinics that treat older patients (e.g., memory care, psychiatry). Our qualitative analysis integrated two implementation frameworks to systematically capture barriers and facilitators to AD/ADRD prevention (Consolidated Framework for Implementation Science Research) that impact implementation outcomes of acceptability, appropriateness, and feasibility (Proctor's framework). RESULTS: We found widespread support for an RCT of My Healthy Brain and AD/ADRD prevention. Participants identified barriers related to patients (stigma, technological skills), providers (dismissiveness of "worried well," doubting capacity for behavior change), clinics (limited time and resources), and the larger healthcare system (underemphasis on prevention). Implementation strategies guided by Expert Recommendations for Implementing Change (ERIC) included: developing tailored materials, training staff, obtaining buy-in from leadership, addressing stigmatized language and practices, identifying "champions," and integrating with workflows and resources. CONCLUSIONS: The results will inform our recruitment, enrollment, and retention procedures to implement the first randomized clinical trial of My Healthy Brain. Our study provides a blueprint for addressing multi-level barriers to the implementation of AD/ADRD prevention for older patients in medical settings.
Keywords: Academic Medical Centers; Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Focus Groups; Health Personnel; Humans; Life Style; Male

Palliative Care in Nursing Home Residents with Young-Onset Dementia: Professional and Family Caregiver Perspectives. - Maters, Jasper; van der Steen, Jenny T; de Vugt, Marjolein E; Bakker, Christian; Koopmans, Raymond T C M (J Alzheimers Dis, 2024)
BACKGROUND: The evidence underpinning palliative care in dementia is mostly based on research in older populations. Little is known about the palliative care needs of people with young-onset dementia (YOD). OBJECTIVE: To describe palliative care practices including advance care planning (ACP) in people with YOD residing in Dutch nursing homes. METHODS: The study presents baseline questionnaire data from an observational cohort study. Physicians, family caregivers, and nursing staff completed questionnaires about 185 residents with YOD. The questionnaires included items on sociodemographics, quality of life measured with the quality of life in late-stage dementia (QUALID) scale, dementia-related somatic health problems, symptoms, pain medication, psychotropic drugs, and ACP. RESULTS: The mean age was 63.9 (SD 5.8) years. Half (50.3%) of them were female. Alzheimer's disease dementia (42.2%) was the most prevalent subtype. The mean QUALID score was 24.0 (SD 7.9) as assessed by family caregivers, and 25.3 (SD 8.6) as assessed by the nursing staff. Swallowing problems were the most prevalent dementia-related health problem (11.4%). Agitation was often reported by physicians (42.0%) and nursing staff (40.5%). Psychotropics were prescribed frequently (72.3%). A minority had written advance directives (5.4%) or documentation on treatment preferences by the former general practitioner (27.2%). Global care goals most often focused on comfort (73.9%). Proportions of do-not-treat orders were higher than do-treat orders for all interventions except for hospitalization and antibiotics. CONCLUSIONS: ACP must be initiated earlier, before nursing home admission. A palliative approach seems appropriate even though residents are relatively young and experience few dementia-related health problems.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Nursing Homes; Palliative Care; Quality of Life

Parkinson's Disease and Other Alzheimer's Disease and Related Dementia Pathologies and the Progression of Parkinsonism in Older Adults. - Buchman, Aron S; Yu, Lei; Oveisgharan, Shahram; Zammit, Andrea R; Wang, Tianhao; Shulman, Joshua M; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2024)
BACKGROUND: The interrelationship of parkinsonism, Parkinson's disease (PD) and other Alzheimer's disease (AD) and Alzheimer's disease and related dementias (ADRD) pathologies is unclear. OBJECTIVE: We examined the progression of parkinsonian signs in adults with and without parkinsonism, and their underlying brain pathologies. METHODS: Annual parkinsonian signs were based on a modified Unified Parkinson's Disease Rating Scale. We used linear mixed effects models to compare the progression of parkinsonian signs in 3 groups categorized based on all available clinical evaluations: Group1 (never parkinsonism or clinical PD), Group2 (ever parkinsonism, but never clinical PD), Group3 (ever clinical PD). In decedents, we examined the progression of parkinsonian signs with PD and eight other AD/ADRD pathologies. RESULTS: During average follow-up of 8 years, parkinsonian signs on average increased by 7.3% SD/year (N = 3,807). The progression of parkinsonian signs was slowest in Group1 (never parkinsonism or clinical PD), intermediate in Group2, and fastest in Group3. In decedents (n = 1,717) pathologic PD and cerebrovascular (CVD) pathologies were associated with a faster rate of progressive parkinsonian signs (all p values <0.05). However, pathologic PD was rare in adults without clinical PD (Group1, 5%; Group2, 7% versus Group3, 55%). Yet, 70% of adults in Group2 without pathologic PD showed one or more CVD pathologies. In Group2, adults with pathologic PD showed faster progression of parkinsonian signs compared with those without evidence of pathologic PD and their rate of progression was indistinguishable from adults with clinical PD. CONCLUSIONS: Parkinsonism in old age is more commonly related to cerebrovascular pathologies relative to pathologic PD and only a minority manifest prodromal PD.

Psychosis in Neurodegenerative Dementias: A Systematic Comparative Review. - Cressot, Coralie; Vrillon, Agathe; Lilamand, Matthieu; Francisque, Hélène; Méauzoone, Aurélie; Hourregue, Claire; Dumurgier, Julien; Marlinge, Emeline; Paquet, Claire; Cognat, Emmanuel (J Alzheimers Dis, 2024)
BACKGROUND: Psychosis, characterized by delusions and/or hallucinations, is frequently observed during the progression of Alzheimer's disease (AD) and other neurodegenerative dementias (ND) (i.e., dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD)) and cause diagnostic and management difficulties. OBJECTIVE: This review aims at presenting a concise and up-to-date overview of psychotic symptoms that occur in patients with ND with a comparative approach. METHODS: A systematic review was conducted following the PRISMA guidelines. 98 original studies investigating psychosis phenotypes in neurodegenerative dementias were identified (40 cohort studies, 57 case reports). RESULTS: Psychosis is a frequently observed phenomenon during the course of ND, with reported prevalence ranging from 22.5% to 54.1% in AD, 55.9% to 73.9% in DLB, and 18% to 42% in FTD. Throughout all stages of these diseases, noticeable patterns emerge depending on their underlying causes. Misidentification delusions (16.6-78.3%) and visual hallucinations (50-69.6%) are frequently observed in DLB, while paranoid ideas and somatic preoccupations seem to be particularly common in AD and FTD, (respectively 9.1-60.3% and 3.10-41.5%). Limited data were found regarding psychosis in the early stages of these disorders. CONCLUSIONS: Literature data suggest that different ND are associated with noticeable variations in psychotic phenotypes, reflecting disease-specific tendencies. Further studies focusing on the early stages of these disorders are necessary to enhance our understanding of early psychotic manifestations associated with ND and help in differential diagnosis issues.
Keywords: Alzheimer Disease; Delusions; Dementia; Frontotemporal Dementia; Humans; Lewy Body Disease; Neurodegenerative Diseases; Psychotic Disorders

Recent Advances in Drug Delivery Systems Targeting Insulin Signalling for the Treatment of Alzheimer's Disease. - Sachdeva, Punya; Narayanan, Kannan Badri; Sinha, Jitendra Kumar; Gupta, Saurabh; Ghosh, Shampa; Singh, Krishna Kumar; Bhaskar, Rakesh; Almutary, Abdulmajeed G; Zothantluanga, James H; Kotta, Kranthi Kumar; Nelson, Vinod Kumar; Paiva-Santos, Ana Cláudia; et al. (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by the accumulation of neurofibrillary tangles and amyloid-β plaques. Recent research has unveiled the pivotal role of insulin signaling dysfunction in the pathogenesis of AD. Insulin, once thought to be unrelated to brain function, has emerged as a crucial factor in neuronal survival, synaptic plasticity, and cognitive processes. Insulin and the downstream insulin signaling molecules are found mainly in the hippocampus and cortex. Some molecules responsible for dysfunction in insulin signaling are GSK-3β, Akt, PI3K, and IRS. Irregularities in insulin signaling or insulin resistance may arise from changes in the phosphorylation levels of key molecules, which can be influenced by both stimulation and inactivity. This, in turn, is believed to be a crucial factor contributing to the development of AD, which is characterized by oxidative stress, neuroinflammation, and other pathological hallmarks. Furthermore, this route is known to be indirectly influenced by Nrf2, NF-κB, and the caspases. This mini-review delves into the intricate relationship between insulin signaling and AD, exploring how disruptions in this pathway contribute to disease progression. Moreover, we examine recent advances in drug delivery systems designed to target insulin signaling for AD treatment. From oral insulin delivery to innovative nanoparticle approaches and intranasal administration, these strategies hold promise in mitigating the impact of insulin resistance on AD. This review consolidates current knowledge to shed light on the potential of these interventions as targeted therapeutic options for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Drug Delivery Systems; Glycogen Synthase Kinase 3 beta; Humans; Insulin; Insulin Resistance

Serial Cerebrospinal Fluid Sampling Reveals Trajectories of Potential Synaptic Biomarkers in Early Stages of Alzheimer's Disease. - Duits, Flora H; Nilsson, Johanna; Zetterberg, Henrik; Blennow, Kaj; van der Flier, Wiesje M; Teunissen, Charlotte E; Brinkmalm, Ann (J Alzheimers Dis, 2024)
BACKGROUND: Synaptic dysfunction is closely associated with cognitive function in Alzheimer's disease (AD), and is present already in an early stage of the disease. OBJECTIVE: Using serial cerebrospinal fluid (CSF) sampling, we aimed to investigate slopes of CSF synaptic proteins, and their relation with cognition along the AD continuum. METHODS: We included subjects with subjective cognitive decline (SCD) or mild cognitive impairment (MCI) (n = 50 amyloid-β+ [A +], n = 50 A-) and 50 patients with AD dementia from the Amsterdam dementia cohort, with CSF at two time points (median[IQR] 2.1[1.4-2.7] years). We analyzed 17 synaptic proteins and neurofilament light (NfL). Using linear mixed models we assessed trajectories of protein levels, and associations with cognitive decline (repeated Mini-Mental State Examination). We used Cox regression models to assess predictive value of protein levels for progression to AD dementia. RESULTS: At baseline most proteins showed increased levels in AD dementia compared to the other groups. In contrast NPTX2 levels were lower in AD dementia. Higher baseline levels of SNAP25, β-syn, and 14-3-3 proteins were associated with faster cognitive decline (St.B[SE] -0.27[0.12] to -0.61[0.12]). Longitudinal analyses showed that SYT1 and NPTX levels decreased over time in AD dementia (st.B[SE] -0.10[0.04] to -0.15[0.05]) and SCD/MCI-A+ (St.B[SE] -0.07[0.03] to -0.12[0.03]), but not in SCD/MCI-A- (pinteraction < 0.05). Increase over time in NfL levels was associated with faster cognitive decline in AD dementia (St.B[SE] -1.75[0.58]), but not in the other groups (pinteraction < 0.05). CONCLUSIONS: CSF synaptic proteins showed different slopes over time, suggesting complex synaptic dynamics. High levels of especially SNAP-25 may have value for prediction of cognitive decline in early AD stages, while increase in NfL over time correlates better with cognitive decline in later stages.

Social Activity and Cognitive Decline in Older Residents of Long-Term Care Facilities: A Cohort Study. - Angevaare, Milou J; Pieters, Jack A; Twisk, Jos W R; Van Hout, Hein P J (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive decline is a major reason for dependence and resource use in long-term care. OBJECTIVE: We explored whether social activities may prevent cognitive decline of older residents of long-term care facilities. METHODS: In a routine care cohort, 3,603 residents of long-term care facilities were assessed on average 4.4 times using the interRAI-Long-Term-Care-Facilities instrument which includes frequency of participation in social activities of long standing interest over the last 30 days and the Cognitive Performance Scale. Linear mixed models repeated measures analyses were performed corrected for age, sex, physical activity, Activities of Daily Living, mood, and health indicators. RESULTS: Social activity was associated with cognitive preservation over time. This association was stronger in those with no or mild cognitive impairment at baseline, relative to those with moderate to severe impairment. Participation in specific social activities such as conversing and helping others showed a similar positive association. The relation between social activity and cognitive impairment appeared to be bi-directional. CONCLUSIONS: The protective effects of social activity offer a window of opportunity to preserve cognitive functioning in long-term care residents.

Voluntary wheel running decreases amyloidogenic pathway and rescues cognition and mitochondrial energy metabolism in middle-aged female 3xTg-AD mouse model of Alzheimer's disease. - Dos Santos, Jonathas Rodrigo; Catalão, Carlos Henrique Rocha; Vulczak, Anderson; Azzolini, Ana Elisa Caleiro Seixas; Alberici, Luciane Carla (J Alzheimers Dis, 2024)
BACKGROUND: Evidence supports the neuroprotective effects of physical activity, either in experimental animal models or humans. However, the biological mechanisms by which physical exercise modulates dementia and Alzheimer's disease (AD) progression are still unclear. OBJECTIVE: This study investigated whether long-term (6 months) of voluntary wheel running induces neuroprotective effects in the pathogenesis of AD in middle-aged (8 months) female mice, focusing on energy metabolism. METHODS: A genetic mice model of AD (3xTg-AD) that performed wheel running presented changes in body metabolism and muscle oxidative profile, as well as restored discriminative and non-associative retention memories, evaluated by novel object recognition and open field tasks, respectively. RESULTS: In the hippocampus, these mice exhibited reduced levels of amyloidogenic AβPPβ fragment, phospho-Tau protein and phospho-Akt (activated form), without changes in phospho-AMPK (activated form). In addition, hippocampal mitochondria presented a restored respiratory function, characterized by lower coupling degree and weak contribution from complex I found in 3xTg-AD mice. CONCLUSIONS: The results demonstrated that voluntary exercise improves cognitive parameters and biochemical hallmarks of AD, modulates Akt activation and enhances mitochondrial energy metabolism in hippocampus of middle-aged 3xTg-AD female mice, thereby reinforcing the neuroprotective role of physical exercise and the involvement of mitochondria in the etiology of the AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognition; Disease Models, Animal; Energy Metabolism; Female; Hippocampus; Mice; Mice, Transgenic; Mitochondria; Physical Conditioning, Animal; tau Proteins

Activation of TNF Receptor 2 Improves Synaptic Plasticity and Enhances Amyloid-β Clearance in an Alzheimer's Disease Mouse Model with Humanized TNF Receptor 2. - Ortí-Casañ, Natalia; Wajant, Harald; Kuiperij, H Bea; Hooijsma, Annelien; Tromp, Leon; Poortman, Isabelle L; Tadema, Norick; de Lange, Julia H E; Verbeek, Marcel M; De Deyn, Peter P; Naudé, Petrus J W; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
BACKGROUND: Tumor necrosis factor-alpha (TNF-α) is a master cytokine involved in a variety of inflammatory and neurological diseases, including Alzheimer's disease (AD). Therapies that block TNF-α proved ineffective as therapeutic for neurodegenerative diseases, which might be explained by the opposing functions of the two receptors of TNF (TNFRs): while TNFR1 stimulation mediates inflammatory and apoptotic pathways, activation of TNFR2 is related to neuroprotection. Despite the success of targeting TNFR2 in a transgenic AD mouse model, research that better mimics the human context is lacking. OBJECTIVE: The aim of this study is to investigate whether stimulation of TNFR2 with a TNFR2 agonist is effective in activating human TNFR2 and attenuating AD neuropathology in the J20xhuTNFR2-k/i mouse model. METHODS: Transgenic amyloid-β (Aβ)-overexpressing mice containing a human extracellular TNFR2 domain (J20xhuTNFR2-k/i) were treated with a TNFR2 agonist (NewStar2). After treatment, different behavioral tests and immunohistochemical analysis were performed to assess different parameters, such as cognitive functions, plaque deposition, synaptic plasticity, or microglial phagocytosis. RESULTS: Treatment with NewStar2 in J20xhuTNFR2-k/i mice resulted in a drastic decrease in plaque load and beta-secretase 1 (BACE-1) compared to controls. Moreover, TNFR2 stimulation increased microglial phagocytic activity, leading to enhanced Aβ clearance. Finally, activation of TNFR2 rescued cognitive impairments and improved synaptic plasticity. CONCLUSION: Our findings demonstrate that activation of human TNFR2 ameliorates neuropathology and improves cognitive functions in an AD mouse model. Moreover, our study confirms that the J20xhuTNFR2-k/i mouse model is suitable for testing human TNFR2-specific compounds.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Mice; Mice, Transgenic; Neuronal Plasticity; Receptors, Tumor Necrosis Factor, Type II; Tumor Necrosis Factor-alpha

Alzheimer's Disease: A Systems View Provides a Unifying Explanation of Its Development. - Grobler, Corlia; van Tongeren, Marvi; Gettemans, Jan; Kell, Douglas B; Pretorius, Etheresia (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a debilitating neurodegenerative disorder affecting 50 million people globally. It is characterized by the presence of extracellular senile plaques and intracellular neurofibrillary tangles, consisting of amyloid-β and hyperphosphorylated tau proteins, respectively. Despite global research efforts, there is currently no cure available, due in part to an incomplete understanding of the disease pathogenesis. Numerous possible mechanisms, or hypotheses, explaining the origins of sporadic or late-onset AD have been proposed, including the amyloid-β, inflammatory, vascular, and infectious hypotheses. However, despite ample evidence, the failure of multiple trial drugs at the clinical stage illuminates the possible pitfalls of these hypotheses. Systems biology is a strategy which aims to elucidate the interactions between parts of a whole. Using this approach, the current paper shows how the four previously mentioned hypotheses of AD pathogenesis can be intricately connected. This approach allows for seemingly contradictory evidence to be unified in a system-focused explanation of sporadic AD development. Within this view, it is seen that infectious agents, such as P. gingivalis, may play a central role. The data presented here shows that when present, P. gingivalis or its virulence factors, such as gingipains, may induce or exacerbate pathologies underlying sporadic AD. This evidence supports the view that infectious agents, and specifically P. gingivalis, may be suitable treatment targets in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurofibrillary Tangles; Plaque, Amyloid; tau Proteins

Alzheimer's Disease and Neurosyphilis: Meaningful Commonalities and Differences of Clinical Phenotype and Pathophysiological Biomarkers. - Milano, Chiara; Hoxhaj, Domeniko; Del Chicca, Marta; Pascazio, Alessia; Paoli, Davide; Tommasini, Luca; Vergallo, Andrea; Pizzanelli, Chiara; Tognoni, Gloria; Nuti, Angelo; Ceravolo, Roberto; Siciliano, Gabriele; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neurosyphilis-associated cognitive and behavioral impairment- historically coined as "general paralysis of the insane"- share clinical and neuroradiological features with the neurodegenerative disease spectrum, in particular Alzheimer's disease (AD). Anatomopathological similarities have been extensively documented, i.e., neuronal loss, fibrillary alterations, and local amyloid-β deposition. Consequently, accurate classification and timely differential diagnosis may be challenging. OBJECTIVE: To describe clinical, bio-humoral, brain MRI, FDG-PET, and amyloid-PET features in cases of neurosyphilis with an AD-like phenotypical presentation, as well as clinical outcome in terms of response to antibiotic therapy. METHODS: We selected the studies comparing patients with AD and with neurosyphilis associated cognitive impairment, to investigate candidate biomarkers classifying the two neurological diseases. RESULTS: The neuropsychological phenotype of general paralysis, characterized by episodic memory impairment and executive disfunction, substantially mimics clinical AD features. Neuroimaging often shows diffuse or medial temporal cortical atrophy, thus contributing to a high rate of misdiagnosis. Cerebrospinal fluid (CSF)-based analysis may provide supportive diagnostic value, since increased proteins or cells are often found in neurosyphilis, while published data on pathophysiological AD candidate biomarkers are controversial. Finally, psychometric testing using cross-domain cognitive tests, may highlight a wider range of compromised functions in neurosyphilis, involving language, attention, executive function, and spatial ability, which are atypical for AD. CONCLUSION: Neurosyphilis should be considered a potential etiological differential diagnosis of cognitive impairment whenever imaging, neuropsychological or CSF features are atypical for AD, in order to promptly start antibiotic therapy and delay or halt cognitive decline and disease progression.

Alzheimer's Disease Pathology Outside of the Cerebrum Is Related to a Higher Odds of Dementia. - Buchman, Aron S; Leurgans, Sue E; Kim, Namhee; Agrawal, Sonal; Oveisgharan, Shahram; Zammit, Andrea R; VanderHorst, Veronique; Nag, Sukrit; Bennett, David A (J Alzheimers Dis, 2023)
BACKGROUND: Assessments of Alzheimer's disease pathology do not routinely include lower brainstem, olfactory bulb, and spinal cord. OBJECTIVE: Test if amyloid-β (Aβ) and paired helical filament (PHF) tau-tangles outside the cerebrum are associated with the odds of dementia. METHODS: Autopsies were obtained in decedents with cognitive testing (n = 300). Aβ plaques and PHF tau-tangles were assessed in 24 sites: cerebrum (n = 14), brainstem (n = 5), olfactory bulb, and four spinal cord levels. Since spinal Aβ were absent in the first 165 cases, it was not assessed in the remaining cases. RESULTS: Age at death was 91 years old. About 90% had Aβ in cerebrum and of these, half had Aβ in the brainstem. Of the latter, 85% showed Aβ in the olfactory bulb. All but one participant had tau-tangles in the cerebrum and 86% had brainstem tau-tangles. Of the latter, 80% had tau-tangles in olfactory bulb and 36% tau-tangles in one or more spinal cord levels. About 90% of adults with tau-tangles also had Aβ in one or more regions. In a logistic model controlling for demographics, Aβ and tau-tangles within the cerebrum, the presence of Aβ in olfactory bulb [OR, 1.74(1.00, 3.05)]; tau-tangles in brainstem [OR, 4.00(1.1.57,10.21)]; and spinal cord [OR, 1.87 (1.21,3.11)] were independently associated with higher odds of dementia. CONCLUSION: Regional differences in Aβ and tau-tangle accumulation extend beyond cerebrum to spinal cord and their presence outside the cerebrum are associated with a higher odds of dementia. Further studies are needed to clarify the extent, burden, and consequences of AD pathology outside of cerebrum.

The Anti-Amyloid Monoclonal Antibody Lecanemab: 16 Cautionary Notes. - Kepp, Kasper P; Sensi, Stefano L; Johnsen, Kasper B; Barrio, Jorge R; Høilund-Carlsen, Poul F; Neve, Rachael L; Alavi, Abass; Herrup, Karl; Perry, George; Robakis, Nikolaos K; Vissel, Bryce; Espay, Alberto J (J Alzheimers Dis, 2023)
After the CLARITY-AD clinical trial results of lecanemab were interpreted as positive, and supporting the amyloid hypothesis, the drug received accelerated Food and Drug Administration approval. However, we argue that benefits of lecanemab treatment are uncertain and may yield net harm for some patients, and that the data do not support the amyloid hypothesis. We note potential biases from inclusion, unblinding, dropouts, and other issues. Given substantial adverse effects and subgroup heterogeneity, we conclude that lecanemab's efficacy is not clinically meaningful, consistent with numerous analyses suggesting that amyloid-β and its derivatives are not the main causative agents of Alzheimer's disease dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidogenic Proteins; Antibodies, Monoclonal; Humans; United States

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

Cerebrospinal Fluid Panel of Synaptic Proteins in Cerebral Amyloid Angiopathy and Alzheimer's Disease. - van den Berg, Emma; Nilsson, Johanna; Kersten, Iris; Brinkmalm, Gunnar; de Kort, Anna M; Klijn, Catharina J M; Schreuder, Floris H B M; Jäkel, Lieke; Gobom, Johan; Portelius, Erik; Zetterberg, Henrik; Brinkmalm, Ann; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA) share pathogenic pathways related to amyloid-β deposition. Whereas AD is known to affect synaptic function, such an association for CAA remains yet unknown. OBJECTIVE: We therefore aimed to investigate synaptic dysfunction in CAA. METHODS: Multiple reaction monitoring mass spectrometry was used to quantify cerebrospinal fluid (CSF) concentrations of 15 synaptic proteins in CAA and AD patients, and age- and sex-matched cognitively unimpaired controls. RESULTS: We included 25 patients with CAA, 49 patients with AD, and 25 controls. Only neuronal pentraxin-2 levels were decreased in the CSF of CAA patients compared with controls (p = 0.04). CSF concentrations of 12 other synaptic proteins were all increased in AD compared with CAA or controls (all p≤0.01) and were unchanged between CAA and controls. Synaptic protein concentrations in the subgroup of CAA patients positive for AD biomarkers (CAA/ATN+; n = 6) were similar to AD patients, while levels in CAA/ATN- (n = 19) were comparable with those in controls. A regression model including all synaptic proteins differentiated CAA from AD at high accuracy levels (area under the curve 0.987). CONCLUSION: In contrast to AD, synaptic CSF biomarkers were found to be largely unchanged in CAA. Moreover, concomitant AD pathology in CAA is associated with abnormal synaptic protein levels. Impaired synaptic function in AD was confirmed in this independent cohort. Our findings support an apparent differential involvement of synaptic dysfunction in CAA and AD and may reflect distinct pathological mechanisms.

Characterizing Performance Gaps of a Code-Based Dementia Algorithm in a Population-Based Cohort of Cognitive Aging. - Vassilaki, Maria; Fu, Sunyang; Christenson, Luke R; Garg, Muskan; Petersen, Ronald C; St Sauver, Jennifer; Sohn, Sunghwan (J Alzheimers Dis, 2023)
BACKGROUND: Multiple algorithms with variable performance have been developed to identify dementia using combinations of billing codes and medication data that are widely available from electronic health records (EHR). If the characteristics of misclassified patients are clearly identified, modifying existing algorithms to improve performance may be possible. OBJECTIVE: To examine the performance of a code-based algorithm to identify dementia cases in the population-based Mayo Clinic Study of Aging (MCSA) where dementia diagnosis (i.e., reference standard) is actively assessed through routine follow-up and describe the characteristics of persons incorrectly categorized. METHODS: There were 5,316 participants (age at baseline (mean (SD)): 73.3 (9.68) years; 50.7% male) without dementia at baseline and available EHR data. ICD-9/10 codes and prescription medications for dementia were extracted between baseline and one year after an MCSA dementia diagnosis or last follow-up. Fisher's exact or Kruskal-Wallis tests were used to compare characteristics between groups. RESULTS: Algorithm sensitivity and specificity were 0.70 (95% CI: 0.67, 0.74) and 0.95 (95% CI: 0.95, 0.96). False positives (i.e., participants falsely diagnosed with dementia by the algorithm) were older, with higher Charlson comorbidity index, more likely to have mild cognitive impairment (MCI), and longer follow-up (versus true negatives). False negatives (versus true positives) were older, more likely to have MCI, or have more functional limitations. CONCLUSIONS: We observed a moderate-high performance of the code-based diagnosis method against the population-based MCSA reference standard dementia diagnosis. Older participants and those with MCI at baseline were more likely to be misclassified.
Keywords: Alzheimer Disease; Cognitive Aging; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Male

Coexistence of Amyotrophic Lateral Sclerosis and Alzheimer's Disease: Case Report and Review of the Literature. - Verde, Federico; Aiello, Edoardo Nicolò; Adobbati, Laura; Poletti, Barbara; Solca, Federica; Tiloca, Cinzia; Sangalli, Davide; Maranzano, Alessio; Muscio, Cristina; Ratti, Antonia; Zago, Stefano; Ticozzi, Nicola; et al. (J Alzheimers Dis, 2023)
We describe a case of amyotrophic lateral sclerosis (ALS) associated with Alzheimer's disease (AD) and review the literature about the coexistence of the two entities, highlighting the following: mean age at onset is 63.8 years, with slight female predominance; ALS tends to manifest after cognitive impairment and often begins in the bulbar region; average disease duration is 3 years; cognitive phenotype is mostly amnestic; the pattern of brain involvement is, in most cases, consistent with AD. Our case and the reviewed ones suggest that patients with ALS and dementia lacking unequivocal features of FTD should undergo additional examinations in order to recognize AD.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Brain; Cognitive Dysfunction; Female; Frontotemporal Dementia; Humans; Male

The Complexity of Nutritional Problems in Persons with Dementia: Expanding a Theoretical Model. - van Buuren, Cornelia Pieternella; van der Steen, Jenny Theodora; Olthof-Nefkens, Maria; Bakker, Christian; Koopmans, Raymond Theodorus Catherina Maria; Perry, Marieke; Kalf, Johanna Gezina (J Alzheimers Dis, 2023)
BACKGROUND: Persons with dementia are at risk of developing nutritional problems. Theoretical models on nutritional problems have been developed, but have not been evaluated with healthcare professionals. OBJECTIVE: This study aimed to explore the comprehensiveness and applicability of a theoretical model of nutritional problems in persons with dementia for daily nursing home practice. METHODS: A qualitative design employing a combined deductive and inductive approach was used. Healthcare professionals were eligible to participate if they 1) had expert knowledge of and experience with nutritional problems related to dementia, and 2) worked in a nursing home affiliated with an academic network covering the east and south of the Netherlands. Three focus group interviews with 20 healthcare professionals from seven professions were held. We conducted thematic analysis and we compared themes with existing theoretical models from the literature. RESULTS: We identified six themes, four of which corresponded with the existing models (observing and analysing nutritional problems; consequences of nutritional problems; functioning of the person with dementia; environmental factors). Interprofessional collaboration and ethical factors were identified as new themes. The analyses indicated interactions within each theme, between themes, and a bidirectional connection between themes. CONCLUSIONS: This study demonstrated the relevance of interprofessional collaboration and ethical considerations in nutritional problems related to dementia. It uncovered complex bidirectional relations within and between factors regarding nutritional problems. All aspects should be taken into account to minimize the consequences of nutritional problems for persons with dementia.
Keywords: Attitude of Health Personnel; Dementia; Focus Groups; Health Personnel; Humans; Nursing Homes

Early Depressive Symptoms Predict Faster Dementia Progression in Autosomal-Dominant AD - Acosta-Baena, Natalia; Lopera-Gómez, Carlos M; Jaramillo-Elorza, Mario C; Velilla-Jiménez, Lina; Villegas-Lanau, Carlos Andrés; Sepúlveda-Falla, Diego; Arcos-Burgos, Mauricio; Lopera, Francisco (J Alzheimers Dis, 2023)
BACKGROUND: Depression is associated with Alzheimer's disease (AD). OBJECTIVE: To evaluate the association between depressive symptoms and age of onset of cognitive decline in autosomal dominant AD, and to determine possible factors associated to early depressive symptoms in this population. METHODS: We conducted a retrospective study to identify depressive symptoms among 190 presenilin 1 (PSEN1) E280A mutation carriers, subjected to comprehensive clinical evaluations in up to a 20-year longitudinal follow-up. We controlled for the following potential confounders: APOE, sex, hypothyroidism, education, marital status, residence, tobacco, alcohol, and drug abuse. RESULTS: PSEN1 E280A carriers with depressive symptoms before mild cognitive impairment (MCI) develop dementia faster than E280A carriers without depressive symptoms (Hazard Ratio, HR = 1.95; 95% CI, 1.15-3.31). Not having a stable partner accelerated the onset of MCI (HR = 1.60; 95 % CI, 1.03-2.47) and dementia (HR = 1.68; 95 % CI, 1.09-2.60). E280A carriers with controlled hypothyroidism had later age of onset of depressive symptoms (HR = 0.48; 95 % CI, 0.25-0.92), dementia (HR = 0.43; 95 % CI, 0.21-0.84), and death (HR = 0.35; 95 % CI, 0.13-0.95). APOEɛ2 significantly affected AD progression in all stages. APOE polymorphisms were not associate to depressive symptoms. Women had a higher frequency and developed earlier depressive symptoms than men throughout the illness (HR = 1.63; 95 % CI, 1.14-2.32). CONCLUSION: Depressive symptoms accelerated progress and faster cognitive decline of autosomal dominant AD. Not having a stable partner and factors associated with early depressive symptoms (e.g., in females and individuals with untreated hypothyroidism), could impact prognosis, burden, and costs.

Effect of Lecanemab in Early Alzheimer's Disease: Mechanistic Interpretation in the Amyloid Cascade Hypothesis 2.0 Perspective. - Volloch, Vladimir; Rits-Volloch, Sophia (J Alzheimers Dis, 2023)
In clinical trials, lecanemab and donanemab showed statistically significant yet marginal slowdown of Alzheimer's disease (AD)-associated cognitive decline. This could be due to their sub-optimal design and/or deployment; alternatively, their limited efficiency could be intrinsic. Distinguishing between the two is of great importance considering the acute need of efficient AD therapy and tremendous resources being invested in its pursuit. The present study analyzes the mode of operation of lecanemab and donanemab within the framework of recently proposed Amyloid Cascade Hypothesis 2.0 and concludes that the second possibility is correct. It suggests that substantial improvement of the efficiency of these drugs in symptomatic AD is unlikely and proposes the alternative therapeutic strategy.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Humans

Effect of Metabolic Syndrome Risk Factors on Processing Speed and Executive Function in Three Racialized Groups. - Bouges, Shenikqua; Fischer, Barbara; Norton, Derek L; Wyman, Mary F; Lambrou, Nickolas; Zuelsdorff, Megan; Van Hulle, Carol A; Ennis, Gilda E; James, Taryn T; Johnson, Adrienne L; Chin, Nathaniel; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Metabolic syndrome (MetS) has been associated with increased risk for Alzheimer's disease and related dementias (ADRD). Understanding the association of MetS risk factors to processing speed and executive function in the pre-clinical stages of ADRD in under-represented groups would offer insight on potential mechanisms through which MetS associates with ADRD risk. OBJECTIVE: Examine association of MetS features and processing speed and executive function across three racial groups. METHODS: Cognitively unimpaired adults from the Wisconsin Alzheimer's Disease Research Center and the Wisconsin Registry for Alzheimer's Disease Prevention completed blood-draws and neuropsychological testing. Six cognitive outcomes were assessed in association to MetS risk factors: Trailmaking Tests A and B, Animal Fluency, Digit Symbol, and composite scores for Processing Speed and Executive Function. Linear mixed effect models were used to assess the relationship between MetS risk factor count and longitudinal cognitive performance across three racialized groups. RESULTS: Participant sample sizes varied by outcome analyzed (N = 714-1,088). African American and Native American groups exhibited higher rates of MetS than non-Hispanic Whites. MetS was associated with processing speed and executive function across all racialized groups. Three-way interaction by racialized group was limited to one cognitive outcome: Trailmaking Test A. CONCLUSION: Metabolic dysfunction incrementally affects cognitive trajectory, with generally similar associations across racial groups. Since racialized groups exhibit higher levels of both MetS and ADRD, MetS may represent a driving factor for increased ADRD risk experience by racialized group and an important and modifiable target through which to reduce risk of ADRD.

Effect of Pathway-Specific Polygenic Risk Scores for Alzheimer's Disease (AD) on Rate of Change in Cognitive Function and AD-Related Biomarkers Among Asymptomatic Individuals. - Xu, Yuexuan; Vasiljevic, Eva; Deming, Yuetiva K; Jonaitis, Erin M; Koscik, Rebecca L; Van Hulle, Carol A; Lu, Qiongshi; Carboni, Margherita; Kollmorgen, Gwendlyn; Wild, Norbert; Carlsson, Cynthia M; Johnson, Sterling C; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Genetic scores for late-onset Alzheimer's disease (LOAD) have been associated with preclinical cognitive decline and biomarker variations. Compared with an overall polygenic risk score (PRS), a pathway-specific PRS (p-PRS) may be more appropriate in predicting a specific biomarker or cognitive component underlying LOAD pathology earlier in the lifespan. OBJECTIVE: In this study, we leveraged longitudinal data from the Wisconsin Registry for Alzheimer's Prevention and explored changing patterns in cognition and biomarkers at various age points along six biological pathways. METHODS: PRS and p-PRSs with and without APOE were constructed separately based on the significant SNPs associated with LOAD in a recent genome-wide association study meta-analysis and compared to APOE alone. We used a linear mixed-effects model to assess the association between PRS/p-PRSs and cognitive trajectories among 1,175 individuals. We also applied the model to the outcomes of cerebrospinal fluid biomarkers in a subset. Replication analyses were performed in an independent sample. RESULTS: We found p-PRSs and the overall PRS can predict preclinical changes in cognition and biomarkers. The effects of PRS/p-PRSs on rate of change in cognition, amyloid-β, and tau outcomes are dependent on age and appear earlier in the lifespan when APOE is included in these risk scores compared to when APOE is excluded. CONCLUSION: In addition to APOE, the p-PRSs can predict age-dependent changes in amyloid-β, tau, and cognition. Once validated, they could be used to identify individuals with an elevated genetic risk of accumulating amyloid-β and tau, long before the onset of clinical symptoms.

Effects of Brain Pathologies on Spatiotemporal Gait Parameters in Patients with Mild Cognitive Impairment. - Lindh-Rengifo, Magnus; Jonasson, Stina B; Ullén, Susann; Palmqvist, Sebastian; van Westen, Danielle; Stomrud, Erik; Mattsson-Carlgren, Niklas; Nilsson, Maria H; Hansson, Oskar (J Alzheimers Dis, 2023)
BACKGROUND: Impaired gait can precede dementia. The associations between gait parameters and brain pathologies are therefore of interest. OBJECTIVE: To explore how different brain pathologies (i.e., vascular and Alzheimer's) are associated with specific gait parameters from various gait components in persons with mild cognitive impairment (MCI), who have an increased risk of developing dementia. METHODS: This cross-sectional study included 96 patients with MCI (mean 72, ±7.5 years; 52% women). Gait was evaluated by using an electronic walkway, GAITRite®. Four gait parameters (step velocity variability; step length; step time; stance time asymmetry) were used as dependent variables in multivariable linear regression analyses. Independent variables included Alzheimer's disease pathologies (amyloid-β and tau) by using PET imaging and white matter hyperintensities (WMH) by using MRI. Covariates included age, sex, comorbidities (and intracranial volume in analyses that includedWMH). RESULTS: Increased tau-PET (Braak I-IV region of interest [ROI]) was associated with step velocity variability (standardized regression coefficient, β= 0.383, p < 0.001) and step length (β= 0.336, p < 0.001), which remained significant when using different Braak ROIs (I-II, III-IV, V-VI). The associations remained significant when adjusting for WMH (p < 0.001). When also controlling for gait speed, tau was no longer significantly (p = 0.168) associated with an increased step length. No significant associations between gait and Aβ-PET load or WMH were identified. CONCLUSIONS: The results indicate that one should pay specific attention to assess step velocity variability when targeting single task gait in patients with MCI. Future studies should address additional gait variability measures and dual tasking in larger cohorts.

Impaired Early Insulin Response to Glucose Load Predicts Episodic Memory Decline: A 10-Year Population-Based Cohort Follow-Up of 45-74-Year-Old Men and Women. - Toppala, Sini; Ekblad, Laura L; Viitanen, Matti; Rinne, Juha O; Jula, Antti (J Alzheimers Dis, 2023)
BACKGROUND: Diabetes increases the risk for cognitive decline, but the mechanisms behind this association remain unknown. Impaired early insulin secretion in elderly men and insulin resistance, both of which are pathophysiological features of type 2 diabetes, have previously been linked to Alzheimer's disease. OBJECTIVE: To examine if the early insulin response to oral glucose load predicts cognitive performance after 10 years in men and women aged 45-74 years. METHODS: This study was based on a subpopulation of the Health 2000 Survey, a Finnish nationwide, population-based health examination study, and its follow-up, the Health 2011 Study. In total, 961 45-74-year-old individuals (mean age at baseline 55.6 years, 55.8% women) were examined. An oral glucose tolerance test was performed in 2001-2002, and early insulin response was defined as the ratio of the 30-min increment in insulin concentration to that of glucose concentration. Cognitive function was evaluated at baseline and follow-up with categorical verbal fluency, word-list learning, and word-list delayed recall. Statistical analyses were performed using multivariable linear models adjusted for age, sex, education, APOE&z.epsi;4 genotype, vascular risk factors including diabetes, and depressive symptoms. RESULTS: A lower early insulin response to glucose load predicted lower performance (β: 0.21, p = 0.03) and greater decline (β: 0.19, p = 0.03) in the word-list delayed recall test. Baseline early insulin response did not predict verbal fluency or word-list learning (all p-values≥0.13). CONCLUSION: Our results suggest that decreased early insulin secretion predicts episodic memory decline in middle-aged to elderly men and women.

Klotho Gene Expression Is Decreased in Peripheral Blood Mononuclear Cells in Patients with Alzheimer's Disease and Frontotemporal Dementia. - Sorrentino, Federica; Fenoglio, Chiara; Sacchi, Luca; Serpente, Maria; Arighi, Andrea; Carandini, Tiziana; Arosio, Beatrice; Ferri, Evelyn; Arcaro, Marina; Visconte, Caterina; Rotondo, Emanuela; Scarpini, Elio; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The longevity gene Klotho (KL) was recently associated with neurodegenerative diseases including Alzheimer's disease (AD). Its role in the brain has not been completely elucidated, although evidence suggests that KL-VS heterozygosity is associated with a reduced risk of AD in Apolipoprotein E ɛ4 carriers. Conversely, no data about genetic association with frontotemporal dementia (FTD) are available so far. OBJECTIVE: To investigate the involvement of KL in AD and FTD by the determination of the genetic frequency of KL-VS variant and the expression analysis of KL gene. METHODS: A population consisting of 438 patients and 240 age-matched controls was enrolled for the study. KL-VS and APOE genotypes were assessed by allelic discrimination through a QuantStudio 12K system. KL gene expression analysis was performed in a restricted cohort of patients consisting of 43 AD patients, 41 FTD patients and 19 controls. KL gene expression was assessed in peripheral blood mononuclear cells with specific TaqMan assay. Statistical analysis was performed using GraphPad 9 Prims software. RESULTS: KL-VS frequency was comparable to the ones found in literature and no differences were found in both allelic and genotypic frequencies between patients and controls were found. Conversely, KL expression levels were significantly lower in AD and FTD patients compared with controls (mean fold regulation - 4.286 and - 6.561 versus controls in AD and FTD, respectively, p = 0.0037). CONCLUSION: This is the first study investigating KL in FTD. We showed a decreased expression of the gene in AD and FTD, independent of the genotype, suggesting a role of Klotho in common steps during neurodegeneration.

Linking Air Pollution Exposure to Blood-Based Metabolic Features in a Community-Based Aging Cohort with and without Dementia. - Kalia, Vrinda; Kulick, Erin R; Vardarajan, Badri; Gu, Yian; Manly, Jennifer J; Elkind, Mitchell S V; Kaufman, Joel D; Jones, Dean P; Baccarelli, Andrea A; Mayeux, Richard; Kioumourtzoglou, Marianthi-Anna; Miller, Gary W (J Alzheimers Dis, 2023)
BACKGROUND: Long-term exposure to air pollution has been associated with changes in levels of metabolites measured in the peripheral blood. However, most research has been conducted in ethnically homogenous, young or middle-aged populations. OBJECTIVE: To study the relationship between the plasma metabolome and long-term exposure to three air pollutants: particulate matter (PM) less than 2.5μm in aerodynamic diameter (PM2.5), PM less than 10μm in aerodynamic diameter (PM10), and nitrogen dioxide (NO2) in an ethnically diverse, older population. METHODS: Plasma metabolomic profiles of 107 participants of the Washington Heights and Inwood Community Aging Project in New York City, collected from 1995-2015, including non-Hispanic white, Caribbean Hispanic, and non-Hispanic Black older adults were used. We estimated the association between each metabolic feature and predicted annual mean exposure to the air pollutants using three approaches: 1) A metabolome wide association study framework; 2) Feature selection using elastic net regression; and 3) A multivariate approach using partial-least squares discriminant analysis. RESULTS: 79 features associated with exposure to PM2.5 but none associated with PM10 or NO2. PM2.5 exposure was associated with altered amino acid metabolism, energy production, and oxidative stress response, pathways also associated with Alzheimer's disease. Three metabolites were associated with PM2.5 exposure through all three approaches: cysteinylglycine disulfide, a diglyceride, and a dicarboxylic acid. The relationship between several features and PM2.5 exposure was modified by diet and metabolic diseases. CONCLUSIONS: These relationships uncover the mechanisms through which PM2.5 exposure can lead to altered metabolic outcomes in an older population.
Keywords: Aged; Aging; Air Pollutants; Air Pollution; Dementia; Environmental Exposure; Humans; Nitrogen Dioxide; Particulate Matter

Mediation of Reduced Hippocampal Volume by Cerebral Amyloid Angiopathy in Pathologically Confirmed Patients with Alzheimer's Disease. - Nagaraja, Nandakumar; Wang, Wei-En; Duara, Ranjan; DeKosky, Steven T; Vaillancourt, David (J Alzheimers Dis, 2023)
BACKGROUND: Hippocampal atrophy in cerebral amyloid angiopathy (CAA) has been reported to be similar to that in Alzheimer's disease (AD). OBJECTIVE: To evaluate if CAA pathology partly mediates reduced hippocampal volume in patients with AD. METHODS: Patients with a clinical diagnosis of AD and neuropathological confirmation of AD+/-CAA in the National Alzheimer's Coordinating Center database were included in the study. The volumes of temporal lobe structures were calculated on T1-weighted imaging (T1-MRI) using automated FreeSurfer software, from images acquired on average 5 years prior to death. Multivariate regression analysis was performed to compare brain volumes in four CAA groups. The hippocampal volume on T1-MRI was correlated with Clinical Dementia Rating sum of boxes (CDRsb) score, apolipoprotein E (APOE) genotype, and hippocampal atrophy at autopsy. RESULTS: The study included 231 patients with no (n = 45), mild (n = 70), moderate (n = 67), and severe (n = 49) CAA. Among the four CAA groups, patients with severe CAA had a smaller mean left hippocampal volume (p = 0.023) but this was not significant when adjusted for APOE ɛ4 (p = 0.07). The left hippocampal volume on MRI correlated significantly with the hippocampal atrophy grading on neuropathology (p = 0.0003). Among patients with severe CAA, the left hippocampal volume on T1-MRI: (a) decreased with an increase in the number of APOE ɛ4 alleles (p = 0.04); but (b) had no evidence of correlation with CDRsb score (p = 0.57). CONCLUSION: Severe CAA was associated with smaller left hippocampal volume on T1-MRI up to five years prior to death among patients with neuropathologically confirmed AD. This relationship was dependent on APOE ɛ4 genotype.

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

Preventing Neurocognitive Decline in Adults Aging with HIV: Implications for Practice and Research. - Cody, Shameka L; Miller, Gabe H; Fazeli, Pariya L; Wang, Ge; Li, Wei; Goodin, Burel R; Vance, David E (J Alzheimers Dis, 2023)
Mild to moderate forms of neurocognitive impairment persist among people living with HIV (PLWH), despite being virally suppressed on antiretroviral therapy. PLWH are disproportionally impacted by physiological and psychosocial comorbidities compared to those without HIV. As adults live longer with HIV, the neurocognitive burden of physiological and psychosocial stressors can impair everyday functioning and may contribute to the development of neurodegenerative diseases such as Alzheimer's disease. This article outlines neurocognitive consequences of everyday stressors in PLWH. While some lifestyle factors can exacerbate inflammatory processes and promote negative neurocognitive health, novel interventions including the use of cannabinoids may be neuroprotective for aging PLWH who are at risk for elevated levels of inflammation from comorbidities. Studies of integrated neurocognitive rehabilitation strategies targeting lifestyle factors are promising for improving neurocognitive health, and may over time, reduce the risk of Alzheimer's disease in PLWH.
Keywords: Aging; Alzheimer Disease; Comorbidity; HIV Infections; Humans

Progression from Prodromal Alzheimer's Disease to Mild Alzheimer's Disease Dementia in the Verubecestat APECS Study: Adjudicating Diagnostic Transitions. - Voss, Tiffini; Kost, James; Mercer, Swati Pal; Furtek, Christine; Randolph, Christopher; Lines, Christopher; Egan, Michael F; Cummings, Jeffrey L (J Alzheimers Dis, 2023)
BACKGROUND: Delay of progression from prodromal Alzheimer's disease (AD) to dementia is an important outcome in AD trials. Centralized adjudication is intended to improve the consistency of dementia diagnosis but has not been scrutinized. OBJECTIVE: To evaluate centralized adjudication for determining progression to dementia compared with Site Investigator opinion or change in Clinical Dementia Rating (CDR). METHODS: We used data from the 2-year APECS trial of verubecestat versus placebo in 1,451 prodromal AD participants. Cases were triggered for central adjudication if: 1) the Site Investigator judged the participant had progressed to dementia, or 2) the participant's CDR sum-of-boxes score increased ≥2 points from baseline. Post-hoc analyses were performed on pooled treatment-group data to compare methods of assessing progression. RESULTS: 581/1,451 (40% ) participants had changes triggering adjudication and most (83% ) were confirmed as progression to dementia. Only 66% of those who met CDR criteria (regardless of whether they also met Site Investigator criteria) were adjudicated to have progressed to dementia and just 15% of those who met only CDR criteria were adjudicated to have progressed, representing 5% of progressors. In contrast, 99% of those who met Site Investigator criteria (regardless of whether they also met CDR criteria) were adjudicated to have progressed, and the same was true for those who met only Site Investigator criteria. CONCLUSION: A positive Site Investigator opinion is an excellent predictor for a positive adjudication decision regarding onset of dementia. Conversely, sole use of CDR sum-of-boxes change ≥2 is inadequate. The benefit of centralized adjudication appears doubtful.

Proteome Network Analysis Identifies Potential Biomarkers for Brain Aging. - Short, Meghan I; Fohner, Alison E; Skjellegrind, Håvard K; Beiser, Alexa; Gonzales, Mitzi M; Satizabal, Claudia L; Austin, Thomas R; Longstreth, W T; Bis, Joshua C; Lopez, Oscar; Hveem, Kristian; Selbæk, Geir; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease and related dementias (ADRD) involve biological processes that begin years to decades before onset of clinical symptoms. The plasma proteome can offer insight into brain aging and risk of incident dementia among cognitively healthy adults. OBJECTIVE: To identify biomarkers and biological pathways associated with neuroimaging measures and incident dementia in two large community-based cohorts by applying a correlation-based network analysis to the plasma proteome. METHODS: Weighted co-expression network analysis of 1,305 plasma proteins identified four modules of co-expressed proteins, which were related to MRI brain volumes and risk of incident dementia over a median 20-year follow-up in Framingham Heart Study (FHS) Offspring cohort participants (n = 1,861). Analyses were replicated in the Cardiovascular Health Study (CHS) (n = 2,117, mean 6-year follow-up). RESULTS: Two proteomic modules, one related to protein clearance and synaptic maintenance (M2) and a second to inflammation (M4), were associated with total brain volume in FHS (M2: p = 0.014; M4: p = 4.2×10-5). These modules were not significantly associated with hippocampal volume, white matter hyperintensities, or incident all-cause or AD dementia. Associations with TCBV did not replicate in CHS, an older cohort with a greater burden of comorbidities. CONCLUSIONS: Proteome networks implicate an early role for biological pathways involving inflammation and synaptic function in preclinical brain atrophy, with implications for clinical dementia.

Reliability and Validity of Self-Reported Vascular Risk Factors: Hypertension, Diabetes, and Heart Disease, in a Multi-Ethnic Community Based Study of Aging and Dementia. - Lee, Annie J; Sanchez, Didi; Reyes-Dumeyer, Dolly; Brickman, Adam M; Lantigua, Rafael A; Vardarajan, Badri N; Mayeux, Richard (J Alzheimers Dis, 2023)
BACKGROUND: Queries for the presence of cardiovascular and cerebrovascular risk factors are typically assessed through self-report. However, the reliability and validity of self-reported cardiovascular and cerebrovascular risk factors remains inconsistent in aging research. OBJECTIVE: To determine the reliability and validity of the most frequently self-reported vascular risk factors: hypertension, diabetes, and heart disease. METHODS: 1,870 individuals aged 65 years or older among African Americans, Caribbean Hispanics, and white non-Hispanic individuals were recruited as part of a community study of aging and dementia. We assessed the reliability, validity, sensitivity, specificity, and percent agreement of self-reported hypertension, diabetes, and heart disease, in comparison with direct measures of blood pressure, hemoglobin A1c (HbA1c), and medication use. The analyses were subsequently stratified by age, sex, education, and ethnic group. RESULTS: Reliability of self-reported for hypertension, diabetes, and heart disease was excellent. Agreement between self-reports and clinical measures was moderate for hypertension (kappa: 0.58), good for diabetes (kappa: 0.76-0.79), and moderate for heart disease (kappa: 0.45) differing slightly by age, sex, education, and ethnic group. Sensitivity and specificity for hypertension was 88.6% -78.1%, for diabetes was 87.7% -92.0% (HbA1c ≥6.5%) or 92.7% -92.8% (HbA1c ≥7%), and for heart disease was 85.8% -75.5%. Percent agreement of self-reported was 87.0% for hypertension, 91.6% -92.6% for diabetes, and 77.4% for heart disease. CONCLUSION: Ascertainment of self-reported histories of hypertension, diabetes, and heart disease are reliable and valid compared to direct measurements or medication use.

Retinal Functional and Structural Neural Indices: Potential Biomarkers for the Monitoring of Cerebral Neurodegeneration: The Maastricht Study. - van der Heide, Frank C T; Mokhtar, Sara; Khanna, Anjani; Said, Mozhda; Henry, Ronald M A; Kroon, Abraham A; Dagnelie, Pieter C; Eussen, Simone J P M; Berendschot, Tos T J M; Schouten, Jan S A G; Schram, Miranda T; van der Kallen, Carla J H; et al. (J Alzheimers Dis, 2023)
BACKGROUND: If retinal indices of neurodegeneration are to be biomarkers for the monitoring of cerebral neurodegeneration, it is important to establish whether potentially modifiable risk factors for dementia are associated with retinal neurodegenerative changes. OBJECTIVE: To study associations of dementia risk factors with retinal sensitivity, an index of retinal neural function, and retinal nerve fiber layer (RNFL) thickness, an index of retinal neural structure. METHODS: We used cross-sectional data from The Maastricht Study (up to 5,666 participants, 50.5% men, mean age 59.7), and investigated associations with regression analyses (adjusted for potential confounders). RESULTS: Most risk factors under study (i.e., hyperglycemia, unhealthy diet, lower cardiorespiratory fitness, smoking, alcohol consumption, and hypertension) were significantly associated with lower retinal sensitivity and lower RNFL thickness. CONCLUSION: Findings of this population-based study support the concept that retinal neural indices may be biomarkers for the monitoring of therapeutic strategies that aim to prevent early-stage cerebral neurodegeneration and, ultimately, dementia.

Two-Year Changes in Physical Activity and Concurrent Changes in Cognitive Function in a Cohort of Adults with Metabolic Syndrome. - Rognoni, Teresa; Fernández-Matarrubia, Marta; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Castañer, Olga; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Gómez-Gracia, Enrique; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: It has been proposed that physical activity (PA) could prevent cognitive decline. OBJECTIVE: To evaluate the association between changes in PA and changes in cognitive function in a cohort of adults with metabolic syndrome. METHODS: Longitudinal observational study including 5,500 adults (mean age 65 years, SD = 5; women = 49.3%) with metabolic syndrome. Participants underwent physical activity measurements and cognitive evaluation at baseline and at two-years of follow-up. PA was quantified using the Minnesota questionnaire-shortened version. Cognitive function was evaluated using a battery of tests: Mini-Mental Test Examination, Clock Drawing Test, Trail Making Test A and B, Verbal Fluency Test, and Digit Span. The primary outcome was change in cognition at two-year follow-up, as measured through the Global Composite Score (GCS) of all neuropsychological tests. Multivariable-adjusted linear regression models were fitted with baseline PA and their changes as the main exposures and changes in cognitive function as the outcome. RESULTS: No significant association was found between PA levels (or their changes) and changes in cognitive function, as measured by the GCS. A greater increase in PA levels was associated with a more favorable two-year change in performance on the Trail Making Test A (Q4 versus Q1: b = -2.15, 95% CI -4.25 to -0.05; p-trend = 0.024). No significant association was found for other neuropsychological test. CONCLUSION: Our results do not support an association between increases in PA and the evolution of the global cognitive function at two-year follow-up, but they suggested a possible beneficial effect of PA on attentional function in older adults.

APOEɛ4 Allele Moderates the Association Between Basal Forebrain Nuclei Volumes and Allocentric Navigation in Older Adults Without Dementia. - Lerch, Ondřej; Pařízková, Martina; Vyhnálek, Martin; Nedelska, Zuzana; Hort, Jakub; Laczó, Jan (J Alzheimers Dis, 2022)
BACKGROUND: Cholinergic deficit and medial temporal lobe (MTL) atrophy are hallmarks of Alzheimer's disease (AD) leading to early allocentric spatial navigation (aSN) impairment. APOEɛ4 allele (E4) is a major genetic risk factor for late-onset AD and contributes to cholinergic dysfunction. Basal forebrain (BF) nuclei, the major source of acetylcholine, project into multiple brain regions and, along with MTL and prefrontal cortex (PFC), are involved in aSN processing. OBJECTIVE: We aimed to determine different contributions of individual BF nuclei atrophy to aSN in E4 positive and E4 negative older adults without dementia and assess whether they operate on aSN through MTL and PFC or independently from these structures. METHODS: 120 participants (60 E4 positive, 60 E4 negative) from the Czech Brain Aging Study underwent structural MRI and aSN testing in real-space arena setting. Hippocampal and BF nuclei volumes and entorhinal cortex and PFC thickness were obtained. Associations between brain regions involved in aSN were assessed using MANOVA and complex model of mutual relationships was built using structural equation modelling (SEM). RESULTS: Path analysis based on SEM modeling revealed that BF Ch1-2, Ch4p, and Ch4ai nuclei volumes were indirectly associated with aSN performance through MTL (pch1 - 2 = 0.039; pch4p = 0.042) and PFC (pch4ai = 0.044). In the E4 negative group, aSN was indirectly associated with Ch1-2 nuclei volumes (p = 0.015), while in the E4 positive group, there was indirect effect of Ch4p nucleus (p = 0.035). CONCLUSION: Our findings suggest that in older adults without dementia, BF nuclei affect aSN processing indirectly, through MTL and PFC, and that APOE E4 moderates these associations.

Association Between Plasma Biomarkers of Amyloid, Tau, and Neurodegeneration with Cerebral Microbleeds. - McCarter, Stuart J; Lesnick, Timothy G; Lowe, Val J; Rabinstein, Alejandro A; Przybelski, Scott A; Algeciras-Schimnich, Alicia; Ramanan, Vijay K; Jack, Clifford R; Petersen, Ronald C; Knopman, David S; Boeve, Bradley F; Kantarci, Kejal; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Cerebral microbleeds (CMBs) are a common vascular pathology associated with future intracerebral hemorrhage. Plasma biomarkers of amyloid, tau, and neurodegeneration may provide a screening avenue to identify those with CMBs, but evidence is conflicting. OBJECTIVE: To determine the association between plasma biomarkers (Aβ40, Aβ42, t-tau, p-tau181, p-tau217, neurofilament light chain (NfL)) and CMBs in a population-based study of aging and whether these biomarkers predict higher signal on Aβ-PET imaging in patients with multiple CMBs. METHODS: 712 participants from the Mayo Clinic Study of Aging with T2 * GRE MRI and plasma biomarkers were included. Biomarkers were analyzed utilizing Simoa (Aβ40, Aβ42, t-tau, NfL) or Meso Scale Discovery (p-tau181, p-tau217) platforms. Cross-sectional associations between CMBs, plasma biomarkers and Aβ-PET were evaluated using hurdle models and multivariable regression models. RESULTS: Among the 188 (26%) individuals with≥1 CMB, a lower plasma Aβ42/Aβ40 ratio was associated with more CMBs after adjusting for covariables (IRR 568.5 95% CI 2.8-116,127). No other biomarkers were associated with risk or number CMBs. In 81 individuals with≥2 CMBs, higher plasma t-tau, p-tau181, and p-tau217 all were associated with higher Aβ-PET signal, with plasma p-tau217 having the strongest predictive value (r2 0.603, AIC -53.0). CONCLUSION: Lower plasma Aβ42/Aβ40 ratio and higher plasma p-tau217 were associated with brain amyloidosis in individuals with CMBs from the general population. Our results suggest that in individuals with multiple CMBs and/or lobar intracranial hemorrhage that a lower plasma Aβ42/Aβ40 ratio or elevated p-tau217 may indicate underlying cerebral amyloid angiopathy.

Association of Brain Volume and Retinal Thickness in the Early Stages of Alzheimer's Disease. - Mathew, Sunu; WuDunn, Darrell; Mackay, Devin D; Vosmeier, Aaron; Tallman, Eileen F; Deardorff, Rachael; Harris, Alon; Farlow, Martin R; Brosch, Jared R; Gao, Sujuan; Apostolova, Liana G; Saykin, Andrew J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The eye has been considered a 'window to the brain,' and several neurological diseases including neurodegenerative conditions like Alzheimer's disease (AD) also show changes in the retina. OBJECTIVE: To investigate retinal nerve fiber layer (RNFL) thickness and its association with brain volume via magnetic resonance imaging (MRI) in older adults with subjective or objective cognitive decline. METHODS: 75 participants underwent ophthalmological and neurological evaluation including optical coherence tomography and MRI (28 cognitively normal subjects, 26 with subjective cognitive decline, 17 patients diagnosed with mild cognitive impairment, and 4 with AD). Differences in demographics, thickness of RNFL, and brain volume were assessed using ANCOVA, while partial Pearson correlations, covaried for age and sex, were used to compare thickness of the peripapillary RNFL with brain volumes, with p < 0.05 considered statistically significant. RESULTS: Mean RNFL thickness was significantly correlated with brain volumes, including global volume (right eye r = 0.235 p = 0.046, left eye r = 0.244, p = 0.037), temporal lobe (right eye r = 0.242 p = 0.039, left eye r = 0.290, p = 0.013), hippocampal (right eye r = 0.320 p = 0.005, left eye r = 0.306, p = 0.008), amygdala (left eye r = 0.332, p = 0.004), and occipital lobe (right eye r = 0.264 p = 0.024) volumes. CONCLUSION: RNFL thickness in both eyes was positively associated with brain volumes in subjects with subjective and objective cognitive decline. The RNFL, however, did not correlate with the disease, but the small sample number makes it important to conduct larger studies. RNFL thickness may be a useful non-invasive and inexpensive tool for detection of brain neurodegeneration and may assist with diagnosis and monitoring of progression and treatment in AD.

Association of COVID-19 with New-Onset Alzheimer's Disease. - Wang, Lindsey; Davis, Pamela B; Volkow, Nora D; Berger, Nathan A; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
An infectious etiology of Alzheimer's disease has been postulated for decades. It remains unknown whether SARS-CoV-2 viral infection is associated with increased risk for Alzheimer's disease. In this retrospective cohort study of 6,245,282 older adults (age ≥65 years) who had medical encounters between 2/2020-5/2021, we show that people with COVID-19 were at significantly increased risk for new diagnosis of Alzheimer's disease within 360 days after the initial COVID-19 diagnosis (hazard ratio or HR:1.69, 95% CI: 1.53-1.72), especially in people age ≥85 years and in women. Our findings call for research to understand the underlying mechanisms and for continuous surveillance of long-term impacts of COVID-19 on Alzheimer's disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; COVID-19; COVID-19 Testing; Female; Humans; Retrospective Studies; SARS-CoV-2

Associations Between Intrathecal Levels of Vitamin D, Cytokines, and Core Biomarkers of Alzheimer's Disease: A Cross-Sectional Study. - Soares, Jelena Zugic; Valeur, Jørgen; Šaltytė Benth, Jūratė; Knapskog, Anne-Brita; Selbæk, Geir; Bogdanovic, Nenad; Pettersen, Renate (J Alzheimers Dis, 2022)
BACKGROUND: Several studies have examined association between vitamin D levels in serum and cognition, but little is known of vitamin D levels in cerebrospinal fluid (CSF) and association with Alzheimer's disease (AD). OBJECTIVE: In this cross-sectional, explorative study we investigated possible associations of vitamin D in CSF with biomarkers for AD, amyloid-β, tau protein/phosphorylated tau protein in CSF, and with the cytokines IL-6, IL-8, and TNF-α in CSF in patients with cognitive impairment and cognitively healthy controls. METHODS: We included 100 outpatients ≥65 years referred for assessment of cognitive impairment and 76 age- and sex-matched cognitively healthy controls. Levels of 25-hydroxyvitamin D (25(OH)D), amyloid-β, tau protein and phosphorylated tau protein, as well as IL-6, IL-8, and TNF-α, were analyzed in CSF in both groups. RESULTS: Higher levels of 25(OH)D in CSF in all groups together were associated with lower levels of tau protein (p = 0.01) and phosphorylated tau protein (p = 0.005). We found no association between 25(OH)D levels in CSF and pathological levels of amyloid-β in CSF nor levels of IL-6 or TNF-α in CSF. Higher levels of 25(OH)D in CSF were associated with higher levels of IL-8 in CSF (p = 0.002). However, vitamin D explained only 6% of variance in IL-8. There was no significant difference between the patient groups and the control group regarding the association between 25(OH)D in CSF and any of the three cytokines in CSF. CONCLUSION: Participants with higher CSF levels of 25(OH)D exhibited reduced CSF levels of tau protein and phosphorylated tau protein.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Can Diet Supplements of Macular Pigment of Lutein, Zeaxanthin, and Meso-zeaxanthin Affect Cognition? - Wang, Hongwei; Wang, Ge; Billings, Rebecca; Li, Daniel; Haase, Shakaye R; Wheeler, Pariya F; Vance, David E; Li, Wei (J Alzheimers Dis, 2022)
BACKGROUND: Lutein (L), zeaxanthin (Z), and meso-zeaxanthin (MZ) are collectively called macular pigment. MZ can be converted from L in the macula. In the recent decade, many studies have been performed to investigate the effects for taking carotenoids, especially L and Z or L, Z, and MZ, as diet supplements on human health. OBJECTIVE: We examined if diet supplements of L + Z or L + Z + MZ have effects on cognitive function in adults. METHODS: A systemic literature search was performed in March 2021 with the following keywords: lutein, zeaxanthin, meso-zeaxanthin, cognition, cognitive, and macular pigment. The searched databases included Medline EBSCOhost, Scopus, Elsevier, Cochrane Library, ProQuest, and ClinicalTrials.gov. Findings from eight clinical trials were presented as the strongest evidence on the studied topic. RESULTS: Most studies have found that macular pigments (L + Z) in blood or macula are positively correlated with cognitive performance. As an index of the amount of macular pigments in the brain, macular pigment optical density is related to cognitive performance in adults. In addition, there is an inverse relationship between a higher amount of macular pigment in the blood and lower risk of mild cognitive impairments or Alzheimer's disease. Based on the findings from the clinical trials, diet supplements of L + Z or L + Z + MZ are associated with improved cognition in adults. CONCLUSION: The diet supplements of L + Z or L + Z+MZ are associated with better cognitive functioning, which may be via their beneficial effects on the vision.

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Cerebral Volumetric Correlates of Apathy in Alzheimer's Disease and Cognitively Normal Older Adults: Meta-Analysis, Label-Based Review, and Study of an Independent Cohort. - Chaudhary, Shefali; Zhornitsky, Simon; Chao, Herta H; van Dyck, Christopher H; Li, Chiang-Shan R (J Alzheimers Dis, 2022)
BACKGROUND: Affecting nearly half of the patients with Alzheimer's disease (AD), apathy is associated with higher morbidity and reduced quality of life. Basal ganglia and cortical atrophy have been implicated in apathy. However, the findings have varied across studies and left unclear whether subdomains of apathy may involve distinct neuroanatomical correlates. OBJECTIVE: To identify neuroanatomical correlates of AD-associated apathy. METHODS: We performed a meta-analysis and label-based review of the literature. Further, following published routines of voxel-based morphometry, we aimed to confirm the findings in an independent cohort of 19 patients with AD/mild cognitive impairment and 25 healthy controls assessed with the Apathy Evaluation Scale. RESULTS: Meta-analysis of 167 AD and 56 healthy controls showed convergence toward smaller basal ganglia gray matter volume (GMV) in apathy. Label-based review showed anterior cingulate, putamen, insula, inferior frontal gyrus (IFG) and middle temporal gyrus (MTG) atrophy in AD apathy. In the independent cohort, with small-volume-correction, right putamen and MTG showed GMVs in negative correlation with Apathy Evaluation Scale total, behavioral, and emotional scores, and right IFG with emotional score (p < 0.05 family-wise error (FWE)-corrected), controlling for age, education, intracranial volume, and depression. With the Mini-Mental State Examination scores included as an additional covariate, the correlation of right putamen GMV with behavioral and emotional score, right MTG GMV with total and emotional score, and right IFG GMV with emotional score were significant. CONCLUSION: The findings implicate putamen, MTG and IFG atrophy in AD associated apathy, potentially independent of cognitive impairment and depression, and suggest potentially distinct volumetric correlates of apathy.
Keywords: Aged; Alzheimer Disease; Apathy; Atrophy; Basal Ganglia; Brain; Cognitive Dysfunction; Cohort Studies; Gray Matter; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Prefrontal Cortex

Cerebrospinal Fluid Sphingomyelins in Alzheimer's Disease, Neurodegeneration, and Neuroinflammation. - Morrow, Autumn; Panyard, Daniel J; Deming, Yuetiva K; Jonaitis, Erin; Dong, Ruocheng; Vasiljevic, Eva; Betthauser, Tobey J; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Bayfield, Anna; Van Hulle, Carol A; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Sphingomyelin (SM) levels have been associated with Alzheimer's disease (AD), but the association direction has been inconsistent and research on cerebrospinal fluid (CSF) SMs has been limited by sample size, breadth of SMs examined, and diversity of biomarkers available. OBJECTIVE: Here, we seek to build on our understanding of the role of SM metabolites in AD by studying a broad range of CSF SMs and biomarkers of AD, neurodegeneration, and neuroinflammation. METHODS: Leveraging two longitudinal AD cohorts with metabolome-wide CSF metabolomics data (n = 502), we analyzed the relationship between the levels of 12 CSF SMs, and AD diagnosis and biomarkers of pathology, neurodegeneration, and neuroinflammation using logistic, linear, and linear mixed effects models. RESULTS: No SMs were significantly associated with AD diagnosis, mild cognitive impairment, or amyloid biomarkers. Phosphorylated tau, neurofilament light, α-synuclein, neurogranin, soluble triggering receptor expressed on myeloid cells 2, and chitinase-3-like-protein 1 were each significantly, positively associated with at least 5 of the SMs. CONCLUSION: The associations between SMs and biomarkers of neurodegeneration and neuroinflammation, but not biomarkers of amyloid or diagnosis of AD, point to SMs as potential biomarkers for neurodegeneration and neuroinflammation that may not be AD-specific.

Cognitive Decline Risk Stratification in People with Late-Onset Epilepsy of Unknown Etiology: An Electroencephalographic Connectivity and Graph Theory Pilot Study. - Costa, Cinzia; Vecchio, Fabrizio; Romoli, Michele; Miraglia, Francesca; Nardi Cesarini, Elena; Alù, Francesca; Calabresi, Paolo; Rossini, Paolo Maria (J Alzheimers Dis, 2022)
BACKGROUND: Although people with late onset epilepsy of unknown etiology (LOEU) are at higher risk of cognitive decline compared to the general population, we still lack affordable tools to predict and stratify their risk of dementia. OBJECTIVE: This pilot-study investigates the potential application of electroencephalography (EEG) network small-world (SW) properties in predicting cognitive decline among patients with LOEU. METHODS: People diagnosed with LOEU and normal cognitive examination at the time of epilepsy diagnosis were included. Cerebrospinal fluid biomarkers, brain imaging, and neuropsychological assessment were performed at the time of epilepsy diagnosis. Baseline EEG was analyzed for SW properties. Patients were followed-up over time with neuropsychological testing to define the trajectory of cognitive decline. RESULTS: Over 5.1 years of follow-up, among 24 patients diagnosed with LOEU, 62.5% were female, mean age was 65.3 years, thirteen developed mild cognitive impairment (MCI), and four developed dementia. Patients with LOEU developing MCI had lower values of SW coefficients in the delta (p = 0.03) band and higher SW values in the alpha frequency bands (p = 0.02) compared to patients having normal cognition at last follow-up. The two separate ANOVAs, for low and alpha bands, confirmed an interaction between SW and cognitive decline at follow-up. A similar gradient was confirmed for patients developing dementia compared to those with normal cognitive function as well as to those developing MCI. CONCLUSION: Baseline EEG analysis through SW is worth investigating as an affordable, widely available tool to stratify LOEU patients for their risk of cognitive decline.
Keywords: Aged; Cognitive Dysfunction; Dementia; Electroencephalography; Epilepsy; Female; Humans; Male; Neuropsychological Tests; Pilot Projects; Risk Assessment

Cognitive, Functional, and Emotional Changes During the COVID-19 Pandemic in Greek Patients with Neurocognitive Disorders. - Tsiakiri, Anna; Vlotinou, Pinelopi; Terzoudi, Aikaterini; Heliopoulos, Ioannis; Vadikolias, Konstantinos (J Alzheimers Dis, 2022)
BACKGROUND: Prolonged periods of social deprivation, such as COVID-19-related lockdowns, are associated with deleterious effects on cognitive functions. OBJECTIVE: The aim of this study was to gauge the effect of prolonged social isolation on the cognitive function of older adults with neurocognitive disorders. METHODS: We recruited 125 older adults with minor or major neurocognitive disorders divided into two groups. The control group was tested at the first period of the study (October 2018-May 2019), whereas the experimental group was evaluated at the second chronological period of the study (October 2020-May 2021) during the second wave of COVID-19. Neuropsychological tests were performed at baseline and six months after baseline. RESULTS: In the control group, significant changes in the scores from the Montreal Cognitive Assessment (MoCA; p = 0.049) and the Functional Rating Scale for Symptoms of Dementia (FRSSD; p = 0.005) were found between baseline and follow-up assessments, whereas no changes were identified in Mini-Mental State Examination (MMSE; p = 0.229) and Geriatric Depression Scale (GDS; p = 0.619) scores. In the experimental group, the scores from all neuropsychological tests (MoCA, MMSE, GDS, and FRSSD; p < 0.001 for all) were significantly different at follow-up when compared with those at baseline measurements. Moreover, significant deterioration of specific functions assessed in MMSE and FRSSD was detected, especially in the experimental group. CONCLUSION: This study highlights cognitive functions directly affected by social deprivation of individuals with neurocognitive disorders. The findings can be used in the rehabilitation from confinement and its negative consequences.
Keywords: Aged; Cognition; Cognitive Dysfunction; Communicable Disease Control; COVID-19; Greece; Humans; Neurocognitive Disorders; Neuropsychological Tests; Pandemics

A Comparison of Well-Being of Carers of People with Dementia and Their Ability to Manage Before and During the COVID-19 Pandemic: Findings from the IDEAL Study. - Gamble, Laura D; Parker, Sophie; Quinn, Catherine; Bennett, Holly Q; Martyr, Anthony; Sabatini, Serena; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Allan, Louise; Burns, Alistair; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Social restriction measures imposed to curb the spread of COVID-19 in the United Kingdom impacted on carers of people with dementia, limiting access to support services and increasing perceived burden of caring. Few studies have compared data collected both during and before the pandemic to examine the effect of these changes. OBJECTIVE: To explore whether the COVID-19 pandemic affected the well-being of carers of people with dementia living in the community, and their ability to cope with their caring responsibilities. METHODS: Analysis was conducted on two groups of carers who were enrolled in the IDEAL programme; the 'pre-pandemic group' (n = 312), assessed at two time points prior to the pandemic, and the 'pandemic group', assessed prior to and several months into the pandemic (n = 156). For the pre-pandemic group, carers were matched 2:1 to carers in the pandemic group on certain characteristics. Differences in change over time between the two groups on self-reported well-being, quality of life, coping, perceived competence, and role captivity, were investigated using mixed effect modelling. RESULTS: Compared to the pre-pandemic group, those in the pandemic group appeared to cope better and had more stable self-rated competency and role captivity. They did not differ in terms of well-being or quality of life. CONCLUSIONS: Despite reports of negative impacts on carers early in the pandemic, the findings suggest the pandemic had little negative longer-term impact on carers of people with dementia, and in fact they appeared to have a more positive attitude towards coping several months into the pandemic.
Keywords: Adaptation, Psychological; Caregivers; COVID-19; Dementia; Humans; Pandemics; Quality of Life

Does Loss of Integrity of the Cingulum Bundle Link Amyloid-β Accumulation and Neurodegeneration in Alzheimer's Disease? - Vlegels, Naomi; Ossenkoppele, Rik; van der Flier, Wiesje M; Koek, Huiberdina L; Reijmer, Yael D; Wisse, Laura Em; Biessels, Geert Jan (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease is characterized by the accumulation of amyloid-β (Aβ) into plaques, aggregation of tau into neurofibrillary tangles, and neurodegenerative processes including atrophy. However, there is a poorly understood spatial discordance between initial Aβ deposition and local neurodegeneration. OBJECTIVE: Here, we test the hypothesis that the cingulum bundle links Aβ deposition in the cingulate cortex to medial temporal lobe (MTL) atrophy. METHODS: 21 participants with mild cognitive impairment (MCI) from the UMC Utrecht memory clinic (UMCU, discovery sample) and 37 participants with MCI from Alzheimer's Disease Neuroimaging Initiative (ADNI, replication sample) with available Aβ-PET scan, T1-weighted and diffusion-weighted MRI were included. Aβ load of the cingulate cortex was measured by the standardized uptake value ratio (SUVR), white matter integrity of the cingulum bundle was assessed by mean diffusivity and atrophy of the MTL by normalized MTL volume. Relationships were tested with linear mixed models, to accommodate multiple measures for each participant. RESULTS: We found at most a weak association between cingulate Aβ and MTL volume (added R2 <0.06), primarily for the posterior hippocampus. In neither sample, white matter integrity of the cingulum bundle was associated with cingulate Aβ or MTL volume (added R2 <0.01). Various sensitivity analyses (Aβ-positive individuals only, posterior cingulate SUVR, MTL sub region volume) provided similar results. CONCLUSION: These findings, consistent in two independent cohorts, do not support our hypothesis that loss of white matter integrity of the cingulum is a connecting factor between cingulate gyrus Aβ deposition and MTL atrophy.

The Effectiveness of GRADIOR: A Neuropsychological Rehabilitation Program for People with Mild Cognitive Impairment and Mild Dementia. Results of a Randomized Controlled Trial After 4 and 12 Months of Treatment. - Diaz Baquero, Angie A; Franco-Martín, Manuel A; Parra Vidales, Esther; Toribio-Guzmán, José Miguel; Bueno-Aguado, Yolanda; Martínez Abad, Fernando; Perea Bartolomé, María V; Asl, Aysan Mahmoudi; van der Roest, Henriëtte G (J Alzheimers Dis, 2022)
BACKGROUND: Computer-based cognitive training programs have been developed with promising results on the maintenance/improvement of cognitive performance in people with dementia. OBJECTIVE: The objective was to evaluate the effectiveness of the cognitive rehabilitation program "GRADIOR" in people with mild cognitive impairment and mild dementia. METHOD: This study was a single-blind multicenter randomized clinical trial. Participants were recruited from hospitals/day centers. The experimental group (EG) and control group (CG) received computer-based cognitive training (CCT) and routine daily care, respectively. Outcome measures at T0: baseline, T1: at 4 months, T2: at 12 months were compared within and between-groups. RESULTS: Significant differences or important effect sizes were detected at the intragroup and intergroup level for most variables, observing a trend of improvement and/or maintenance at 4 months by Visual Reasoning of Cambridge Cognitive Examination (CAMCOG), Digit and Arithmetic of WAIS-III, Semantic Verbal Fluency, Mini-Mental State Exam (MMSE), Trail Making Test (TMT)-A-Mistakes and at 12 months by Visual Reasoning of CAMCOG, Digit Symbol of WAIS-III, TMT-B-mistakes, Visual Memory of Rivermead Behavioural Memory Test, Lexical Verbal Fluency-P, Yesavage's Geriatric Depression Scale (GDS), TMT-A-time scales whose objective was to evaluate some executive functions and/or the memory. The CG presented a worsening trend for most of the measures towards 12 months. There was also a significant interaction between "time and group" for MMSE (F = 8.971; p = 0.03; η 2 = 0.019) and the GDS (F = 3.414; p = 0.04; η 2 = 0.041), as well as small effect sizes for TMT-A-time (F = 1.641; p = 0.21; η 2 = 0.021) and TMT-A-mistakes (F = 0.908; p = 0.41; η 2 = 0.019). CONCLUSION: CCT with GRADIOR has been proved to benefit cognitive functions (ISRCTN:15742788).

Impact of COVID-19 on 'Living Well' with Mild-to-Moderate Dementia in the Community: Findings from the IDEAL Cohort. - Clare, Linda; Martyr, Anthony; Gamble, Laura D; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Parker, Sophie; Allan, Louise; Burns, Alistair; Hillman, Alexandra; Litherland, Rachael; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Negative impacts of the COVID-19 pandemic on people with dementia have been widely-documented, but most studies have relied on carer reports and few have compared responses to information collected before the pandemic. OBJECTIVE: We aimed to explore the impact of the pandemic on community-dwelling individuals with mild-to-moderate dementia and compare responses with pre-pandemic data. METHODS: During the second wave of the pandemic, we conducted structured telephone interviews with 173 people with dementia and 242 carers acting as informants, all of whom had previously participated in the IDEAL cohort. Where possible, we benchmarked responses against pre-pandemic data. RESULTS: Significant perceived negative impacts were identified in cognitive and functional skills and ability to engage in self-care and manage everyday activities, along with increased levels of loneliness and discontinuity in sense of self and a decline in perceived capability to 'live well'. Compared to pre-pandemic data, there were lower levels of pain, depression, and anxiety, higher levels of optimism, and better satisfaction with family support. There was little impact on physical health, mood, social connections and relationships, or perceptions of neighborhood characteristics. CONCLUSION: Efforts to mitigate negative impacts of pandemic-related restrictions and restore quality of life could focus on reablement to address the effects on participation in everyday activities, creating opportunities for social contact to reduce loneliness, and personalized planning to reconnect people with their pre-COVID selves. Such efforts may build on the resilience demonstrated by people with dementia and carers in coping with the pandemic.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Caregivers; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Neighborhood Characteristics; Quality of Life; SARS-CoV-2

Improved Alzheimer's Disease versus Frontotemporal Lobar Degeneration Differential Diagnosis Combining EEG and Neurochemical Biomarkers: A Pilot Study. - Laton, Jorne; Van Schependom, Jeroen; Goossens, Joery; Wiels, Wietse; Sieben, Anne; De Deyn, Peter Paul; Goeman, Johan; Streffer, Johannes; van der Zee, Julie; Martin, Jean-Jacques; Van Broeckhoven, Christine; De Vos, Maarten; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Distinguishing between Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) results in poor diagnostic accuracy. OBJECTIVE: To investigate the utility of electroencephalography (EEG)-based biomarkers in comparison and in addition to established cerebrospinal fluid (CSF) biomarkers in the AD versus FTLD differential diagnosis. METHODS: The study cohort comprised 37 AD and 30 FTLD patients, of which 17 AD and 9 FTLD patients had definite diagnoses. All participants had CSF neurochemical (NCM) biomarker analyses (Aβ1-42, T-tau, P-tau181, and Nf-L) and underwent 19-channel resting-state EEG. From the EEG spectra, dominant frequency peaks were extracted in four regions resulting in four dominant frequencies. This produced eight features (4 NCM + 4 EEG). RESULTS: When NCM and EEG markers were combined, the diagnostic accuracy increased significantly. In the whole group, the accuracy went up from 79% (NCM) to almost 82%, while in the definite group only, it went up from around 85% to almost 95% . Two differences in the occurrence of the dominant EEG frequency were discovered: people lacking a clear dominant peak almost all had definite AD, while people with two peaks more often had FTLD. CONCLUSION: Combining EEG with NCM biomarkers resulted in differential diagnostic accuracies of 82% in clinically diagnosed AD and FTD patients and of 95% in patients having a definite diagnosis, which was significantly better than with EEG or NCM biomarkers alone. This suggests that NCM and EEG markers are complementary, revealing different aspects of the disease and therefore confirms again their relevance in developing additional diagnosis tools.

Increased Functional Connectivity of the Precuneus in Individuals with a Family History of Alzheimer's Disease. - Green, Zachary D; Vidoni, Eric D; Swerdlow, Russell H; Burns, Jeffrey M; Morris, Jill K; Honea, Robyn A (J Alzheimers Dis, 2022)
BACKGROUND: First-degree relatives of individuals with late-onset Alzheimer's disease (AD) have increased risk for AD, with children of affected parents at an especially high risk. OBJECTIVE: We aimed to investigate default mode network connectivity, medial temporal cortex volume, and cognition in cognitively healthy (CH) individuals with (FH+) and without (FH-) a family history of AD, alongside amnestic mild cognitive impairment (aMCI) and AD individuals, to determine the context and directionality of dysfunction in at-risk individuals. Our primary hypothesis was that there would be a linear decline (CH FH- > CH FH+ > aMCI > AD) within the risk groups on all measures of AD risk. METHODS: We used MRI and fMRI to study cognitively healthy individuals (n = 28) with and without AD family history (FH+ and FH-, respectively), those with aMCI (n = 31) and early-stage AD (n = 25). We tested connectivity within the default mode network, as well as measures of volume and thickness within the medial temporal cortex and selected seed regions. RESULTS: As expected, we identified decreased medial temporal cortex volumes in the aMCI and AD groups compared to cognitively healthy groups. We also observed patterns of connectivity across risk groups that suggest a nonlinear relationship of change, such that the FH+ group showed increased connectivity compared to the FH- and AD groups (CH FH+ > CH FH- > aMCI > AD). This pattern emerged primarily in connectivity between the precuneus and frontal regions. CONCLUSION: These results add to a growing literature that suggests compensatory brain function in otherwise cognitively healthy individuals with a family history of AD.

Insulin-Like Growth Factor, Inflammation, and MRI Markers of Alzheimer's Disease in Predominantly Middle-Aged Adults. - Wittfeld, Katharina; Raman, Mekala R; Conner, Sarah C; Aslam, Asra; Teumer, Alexander; Nauck, Matthias; Hosten, Norbert; Habes, Mohamad; DeCarli, Charles; Vasan, Ramachandran S; Beiser, Alexa S; Himali, Jayandra J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Insulin-like growth factor 1 (IGF-1) signaling has been implicated in Alzheimer's disease pathogenesis, and further evidence suggests inflammation can be a moderator of this association. However, most research to date has been conducted on older adults. OBJECTIVE: To investigate the association of serum IGF-1 and IGF binding protein 3 (IGFBP-3) concentrations with MRI markers of Alzheimer's disease in predominantly middle-aged adults, and further assess moderation by chronic inflammation. METHODS: We included participants from the Framingham Heart Study (n = 1,852, mean age 46±8, 46% men) and the Study of Health in Pomerania (n = 674, mean age 50±13, 42% men) with available serum IGF-1, IFGBP-3, as well as brain MRI. IGF-1 and IFGBP-3 were related to MRI outcomes (i.e., total brain, cortical gray matter, white matter, white matter hyperintensities (WMH), and hippocampal volumes) using multivariable regression models adjusting for potential confounders. Subgroup analyses by C-reactive protein (CRP) concentrations were also performed. Cohort-specific summary statistics were meta-analyzed using random-effects models and corrected for multiple comparisons. RESULTS: Meta-analysis results revealed that higher IGF-1 concentrations were associated with lower WMH (estimate [β] [95% CI], -0.05 [-0.09, -0.02], p = 0.006) and larger hippocampal volumes (0.07 [0.02, 0.12], p = 0.01), independent of vascular risk factors. These associations occurred predominantly in individuals with CRP concentrations < 75th percentile. We did not observe associations between IGFBP-3 and MRI outcomes. CONCLUSION: Our findings suggest that IGF-1-related signaling may be implicated in brain health as early as midlife.

Interaction Between Diet and Microbiota in the Pathophysiology of Alzheimer's Disease: Focus on Polyphenols and Dietary Fibers. - Ticinesi, Andrea; Mancabelli, Leonardo; Carnevali, Luca; Nouvenne, Antonio; Meschi, Tiziana; Del Rio, Daniele; Ventura, Marco; Sgoifo, Andrea; Angelino, Donato (J Alzheimers Dis, 2022)
Animal studies increasingly indicate that the gut microbiota composition and function can be involved in the pathophysiology and progression of Alzheimer's disease (AD) at multiple levels. However, few studies have investigated this putative gut-brain axis in human beings, and none of them considered diet as a determinant of intestinal microbiota composition. Epidemiological studies highlight that a high intake of fruit and vegetables, such as that typical of the Mediterranean diet, can modulate AD progression. Thus, nutritional interventions are being increasingly studied as a possible non-pharmacological strategy to slow down the progression of AD. In particular, polyphenols and fibers represent the nutritional compounds with the higher potential of counterbalancing the pathophysiological mechanisms of dementia due to their antioxidant, anti-inflammatory, and anti-apoptotic properties. These actions are mediated by the gut microbiota, that can transform polyphenols and fibers into biologically active compounds including, among others, phenyl-γ-valerolactones, urolithins, butyrate, and other short-chain fatty acids. In this review, the complex mechanisms linking nutrition, gut microbiota composition, and pathophysiology of cognitive decline in AD are discussed, with a particular focus on the role of polyphenols and fibers. The gaps between pre-clinical and clinical studies are particularly emphasized, as well as the urgent need for studies comprehensively evaluating the link between nutrition, microbiome, and clinical aspects of AD.
Keywords: Alzheimer Disease; Animals; Diet; Diet, Mediterranean; Dietary Fiber; Humans; Microbiota; Polyphenols

A Novel Panel of Plasma Proteins Predicts Progression in Prodromal Alzheimer's Disease. - Araújo, Daniella Castro; Veloso, Adriano Alonso; Gomes, Karina Braga; de Souza, Leonardo Cruz; Ziviani, Nivio; Caramelli, Paulo (J Alzheimers Dis, 2022)
BACKGROUND: A cheap and minimum-invasive method for early identification of Alzheimer's disease (AD) pathogenesis is key to disease management and the success of emerging treatments targeting the prodromal phases of the disease. OBJECTIVE: To develop a machine learning-based blood panel to predict the progression from mild cognitive impairment (MCI) to dementia due to AD within a four-year time-to-conversion horizon. METHODS: We created over one billion models to predict the probability of conversion from MCI to dementia due to AD and chose the best-performing one. We used Alzheimer's Disease Neuroimaging Initiative (ADNI) data of 379 MCI individuals in the baseline visit, from which 176 converted to AD dementia. RESULTS: We developed a machine learning-based panel composed of 12 plasma proteins (ApoB, Calcitonin, C-peptide, CRP, IGFBP-2, Interleukin-3, Interleukin-8, PARC, Serotransferrin, THP, TLSP 1-309, and TN-C), and which yielded an AUC of 0.91, accuracy of 0.91, sensitivity of 0.84, and specificity of 0.98 for predicting the risk of MCI patients converting to dementia due to AD in a horizon of up to four years. CONCLUSION: The proposed machine learning model was able to accurately predict the risk of MCI patients converting to dementia due to AD in a horizon of up to four years, suggesting that this model could be used as a minimum-invasive tool for clinical decision support. Further studies are needed to better clarify the possible pathophysiological links with the reported proteins.

Obesity-Associated Neurodegeneration Pattern Mimics Alzheimer's Disease in an Observational Cohort Study. - Morys, Filip; Potvin, Olivier; Zeighami, Yashar; Vogel, Jacob; Lamontagne-Caron, Rémi; Duchesne, Simon; Dagher, Alain (J Alzheimers Dis, 2022)
BACKGROUND: Excess weight in adulthood leads to health complications such as diabetes, hypertension, or dyslipidemia. Recently, excess weight has also been related to brain atrophy and cognitive decline. Reports show that obesity is linked with Alzheimer's disease (AD)-related changes, such as cerebrovascular damage or amyloid-β accumulation. However, to date no research has conducted a direct comparison between brain atrophy patterns in AD and obesity. OBJECTIVE: Here, we compared patterns of brain atrophy and amyloid-β/tau protein accumulation in obesity and AD using a sample of over 1,300 individuals from four groups: AD patients, healthy controls, obese otherwise healthy individuals, and lean individuals. METHODS: We age- and sex-matched all groups to the AD-patients group and created cortical thickness maps of AD and obesity. This was done by comparing AD patients with healthy controls, and obese individuals with lean individuals. We then compared the AD and obesity maps using correlation analyses and permutation-based tests that account for spatial autocorrelation. Similarly, we compared obesity and AD brain maps with amyloid-β and tau protein maps from other studies. RESULTS: Obesity maps were highly correlated with AD maps but were not correlated with amyloid-β/tau protein maps. This effect was not accounted for by the presence of obesity in the AD group. CONCLUSION: Our research confirms that obesity-related grey matter atrophy resembles that of AD. Excess weight management could lead to improved health outcomes, slow down cognitive decline in aging, and lower the risk for AD.

Polygenic Scores of Alzheimer's Disease Risk Genes Add Only Modestly to APOE in Explaining Variation in Amyloid PET Burden. - Ramanan, Vijay K; Heckman, Michael G; Przybelski, Scott A; Lesnick, Timothy G; Lowe, Val J; Graff-Radford, Jonathan; Mielke, M; Jack, Clifford R; Knopman, David S; Petersen, Ronald C; Ross, Owen A; Vemuri, Prashanthi (J Alzheimers Dis, 2022)
BACKGROUND: Brain accumulation of amyloid-β is a hallmark event in Alzheimer's disease (AD) whose underlying mechanisms are incompletely understood. Case-control genome-wide association studies have implicated numerous genetic variants in risk of clinically diagnosed AD dementia. OBJECTIVE: To test for associations between case-control AD risk variants and amyloid PET burden in older adults, and to assess whether a polygenic measure encompassing these factors would account for a large proportion of the unexplained variance in amyloid PET levels in the wider population. METHODS: We analyzed data from the Mayo Clinic Study of Aging (MCSA) and the Alzheimer's Disease Neuroimaging Initiative (ADNI). Global cortical amyloid PET burden was the primary outcome. The 38 gene variants from Wightman et al. (2021) were analyzed as predictors, with PRSice-2 used to assess the collective phenotypic variance explained. RESULTS: Known AD risk variants in APOE, PICALM, CR1, and CLU were associated with amyloid PET levels. In aggregate, the AD risk variants were strongly associated with amyloid PET levels in the MCSA (p = 1.51×10-50) and ADNI (p = 3.21×10-64). However, in both cohorts the non-APOE variants uniquely contributed only modestly (MCSA = 2.1%, ADNI = 4.4%) to explaining variation in amyloid PET levels. CONCLUSION: Additional case-control AD risk variants added only modestly to APOE in accounting for individual variation in amyloid PET burden, results which were consistent across independent cohorts with distinct recruitment strategies and subject characteristics. Our findings suggest that advancing precision medicine for dementia may require integration of strategies complementing case-control approaches, including biomarker-specific genetic associations, gene-by-environment interactions, and markers of disease progression and heterogeneity.

Potential Mechanisms Underlying Resistance to Dementia in Non-Demented Individuals with Alzheimer's Disease Neuropathology. - Kok, Frédérique K; van Leerdam, Suzanne L; de Lange, Elizabeth C M (J Alzheimers Dis, 2022)
Alzheimer's disease (AD) is the most common form of dementia and typically characterized by the accumulation of amyloid-β plaques and tau tangles. Intriguingly, there also exists a group of elderly which do not develop dementia during their life, despite the AD neuropathology, the so-called non-demented individuals with AD neuropathology (NDAN). In this review, we provide extensive background on AD pathology and normal aging and discuss potential mechanisms that enable these NDAN individuals to remain cognitively intact. Studies presented in this review show that NDAN subjects are generally higher educated and have a larger cognitive reserve. Furthermore, enhanced neural hypertrophy could compensate for hippocampal and cingulate neural atrophy in NDAN individuals. On a cellular level, these individuals show increased levels of neural stem cells and 'von Economo neurons'. Furthermore, in NDAN brains, binding of Aβ oligomers to synapses is prevented, resulting in decreased glial activation and reduced neuroinflammation. Overall, the evidence stated here strengthens the idea that some individuals are more resistant to AD pathology, or at least show an elongation of the asymptomatic state of the disease compared to others. Insights into the mechanisms underlying this resistance could provide new insight in understanding normal aging and AD itself. Further research should focus on factors and mechanisms that govern the NDAN cognitive resilience in order to find clues on novel biomarkers, targets, and better treatments of AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Hippocampus; Humans; Plaque, Amyloid; Synapses

Pre-Diagnostic Symptoms of Young-Onset Dementia in the General Practice up to Five Years Before Diagnosis. - Hendriks, Stevie; Peetoom, Kirsten; Tange, Huibert; van Bokhoven, Marloes A; van der Flier, Wiesje M; Bakker, Christian; Papma, Janne M; Koopmans, Raymond; Verhey, Frans; Köhler, Sebastian; de Vugt, Marjolein (J Alzheimers Dis, 2022)
BACKGROUND: Young-onset dementia (YOD) has many underlying etiologies, leading to a large heterogeneity in first symptoms. This makes it difficult for general practitioners (GPs) to recognize YOD. OBJECTIVE: Identify early symptoms that are more common in the pre-diagnostic phase of YOD. METHODS: We performed a case-control study nested in a primary-care registry on 89 cases and 162 matched controls, where we compared symptoms of people with YOD up to 5 years before diagnosis to their matched control group without YOD. The variables included in this study were International Classification of Primary Care codes and symptoms extracted from written GP notes and categorized in groups. We used Generalized Equation Estimation to analyze symptom's time-trajectories and logistic regression and ROC-curves to analyze differences in number of symptom categories reported. RESULTS: Cognitive symptoms were more common in people with YOD 5 years before diagnosis, affective symptoms 4 years before diagnosis, social symptoms 3 years, behavioral symptoms 2 years, and daily functioning disturbances 1 year before diagnosis. The ROC-curve suggested that reporting two or more symptom categories at the GP gave the best trade-off between sensitivity (85%) and specificity (77% ), for the highest percentage of correctly diagnosed persons. CONCLUSION: This study showed people with YOD present differently than people without YOD. However, it may still be difficult for GPs to use these symptom categories to distinguish people with YOD, since the symptoms also occur in people with other diseases. A combination of reported symptom categories increases the probability of an underlying cause of YOD.

Progression from Subjective Cognitive Decline to Mild Cognitive Impairment or Dementia: The Role of Baseline Cognitive Performance. - Jester, Dylan J; Vyhnálek, Martin; Andel, Ross; Marková, Hana; Nikolai, Tomas; Laczó, Jan; Matuskova, Veronika; Cechova, Katerina; Sheardova, Katerina; Hort, Jakub (J Alzheimers Dis, 2022)
BACKGROUND: Older adults with subjective cognitive decline (SCD) are at an increased risk of progression to mild cognitive impairment (MCI) or dementia. However, few have examined the specific cognitive tests that are associated with progression. OBJECTIVE: This study examined performance on 18 neuropsychological tests among participants with SCD who later progressed to MCI or dementia. METHODS: We included 131 participants from the Czech Brain Aging Study that had SCD at baseline. They completed a comprehensive neuropsychological battery including cognitive tests from the Uniform Data Set 2.0 enriched by the verbal memory test Rey Auditory Verbal Learning Test (RAVLT) and Rey-Osterrieth Complex Figure Test (ROCFT). RESULTS: Fifty-five participants progressed: 53% to non-amnestic MCI (naMCI), 44% to amnestic MCI (aMCI), and 4% to dementia. Scoring one SD below the mean at baseline on the RAVLT 1 and RAVLT 1-5 was associated with 133% (RAVLT 1; HR: 2.33 [1.50, 3.62]) and 122% (RAVLT 1-5; HR: 2.22 [1.55, 3.16]) greater risk of progression to MCI or dementia over 3.84 years on average. Worse performance on the RAVLT 5, RAVLT 1-5, RAVLT 30, and ROCFT-Recall was associated with progression to aMCI whereas worse performance on the RAVLT 1, TMT B, and Boston Naming Test was associated with progression to naMCI. CONCLUSION: At baseline, lower verbal memory performance was most strongly associated with progression to aMCI whereas lower executive or language performance was most strongly associated with progression to naMCI.

Proteomic Profiles of Neurodegeneration Among Mexican Americans and Non-Hispanic Whites in the HABS-HD Study. - O'Bryant, Sid E; Zhang, Fan; Petersen, Melissa; Hall, James R; Johnson, Leigh A; Yaffe, Kristine; Braskie, Meredith; Vig, Rocky; Toga, Arthur W; Rissman, Robert A (J Alzheimers Dis, 2022)
BACKGROUND: Hispanics are expected to experience the largest increase in Alzheimer's disease (AD) and AD related dementias over the next several decades. However, few studies have examined biomarkers of AD among Mexican Americans, the largest segment of the U.S. Hispanic population. OBJECTIVE: We sought to examine proteomic profiles of an MRI-based marker of neurodegeneration from the AT(N) framework among a multi-ethnic, community-dwelling cohort. METHODS: Community-dwelling Mexican Americans and non-Hispanic white adults and elders were recruited. All participants underwent comprehensive assessments including an interview, functional exam, clinical labs, informant interview, neuropsychological testing, and 3T MRI of the brain. A neurodegeneration MRI meta-ROI biomarker for the AT(N) framework was calculated. RESULTS: Data was examined from n = 1,291 participants. Proteomic profiles were highly accurate for detecting neurodegeneration (i.e., N+) among both Mexican Americans (AUC = 1.0) and non-Hispanic whites (AUC = 0.98). The proteomic profile of N + was different between ethnic groups. Further analyses revealed that the proteomic profiles of N + varied by diagnostic status (control, MCI, dementia) and ethnicity (Mexican American versus non-Hispanic whites) though diagnostic accuracy was high for all classifications. CONCLUSION: A proteomic profile of neurodegeneration has tremendous value and point towards novel diagnostic and intervention opportunities. The current findings demonstrate that the underlying biological factors associated with neurodegeneration are different between Mexican Americans versus non-Hispanic whites as well as at different levels of disease progression.

Relationship Between the Gut Microbiota and Alzheimer's Disease: A Systematic Review. - González Cordero, Elisa Marina; Cuevas-Budhart, Miguel Angel; Pérez Morán, Diana; Trejo Villeda, Miguel Angel; Gomez-Del-Pulgar Gª-Madrid, Mercedes (J Alzheimers Dis, 2022)
BACKGROUND: In recent years, scientific research on the gut microbiota and their relationship with some diseases, including neurological ones, has notably increased. As a result of these investigations, the so-called gut-brain axis arises. Despite its influence on the evolution and development of cognitive impairment, the gut-brain axis is little defined and demonstrated. OBJECTIVE: To provide the best scientific evidence available on the relationship between the gut microbiota and Alzheimer's disease. METHOD: Systematic and narrative review of the information generated in the last 5 years in national and international databases, in English and Spanish. RESULTS: Eight observational studies were selected, carried out in humans and, therefore, suitable for inclusion in this review. CONCLUSION: The results of these studies support the hypothesis that there is a relationship between the gut microbiota and cognitive disorders through the gut-brain axis. However, today, there is a substantial lack of human studies, especially clinical trials, which makes it difficult to formulate clinical recommendations on this topic.
Keywords: Alzheimer Disease; Brain; Brain-Gut Axis; Cognitive Dysfunction; Gastrointestinal Microbiome; Humans

Rheumatoid Arthritis, Cognitive Impairment, and Neuroimaging Biomarkers: Results from the Mayo Clinic Study of Aging. - Vassilaki, Maria; Crowson, Cynthia S; Davis Iii, John M; Duong, Stephanie Q; Jones, David T; Nguyen, Aivi; Mielke, Michelle M; Vemuri, Prashanthi; Myasoedova, Elena (J Alzheimers Dis, 2022)
BACKGROUND: Observational studies suggested that dementia risk in patients with rheumatoid arthritis (RA) is higher than in the general population. OBJECTIVE: To examine the associations of RA with cognitive decline and dementia, and neuroimaging biomarkers of aging, Alzheimer's disease, and vascular pathology in adult participants in the Mayo Clinic Study of Aging (MCSA). METHODS: Participants with RA were matched 1:3 on age, sex, education, and baseline cognitive diagnosis to participants without RA. RA cases with MRI were also matched with non-cases with available MRI. All available imaging studies (i.e., amyloid and FDG PET, sMRI, and FLAIR) were included. The study included 104 participants with RA and 312 without RA (mean age (standard deviation, SD) 75.0 (10.4) years, 33% male and average follow-up (SD) 4.2 (3.8) years). RESULTS: Groups were similar in cognitive decline and risk of incident dementia. Among participants with neuroimaging, participants with RA (n = 33) and without RA (n = 98) had similar amyloid burden and neurodegeneration measures, including regions sensitive to aging and dementia, but greater mean white matter hyperintensity volume relative to the total intracranial volume (mean (SD)% : 1.12 (0.57)% versus 0.76 (0.69)% of TIV, p = 0.01), and had higher mean (SD) number of cortical infarctions (0.24 (0.44) versus 0.05 (0.33), p = 0.02). CONCLUSION: Although cognitive decline and dementia risk were similar in participants with and without RA, participants with RA had more abnormal cerebrovascular pathology on neuroimaging. Future studies should examine the mechanisms underlying these changes and potential implications for prognostication and prevention of cognitive decline in RA.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidosis; Arthritis, Rheumatoid; Biomarkers; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Positron-Emission Tomography

Safety and Efficacy of Monoclonal Antibodies for Alzheimer's Disease: A Systematic Review and Meta-Analysis of Published and Unpublished Clinical Trials. - Lacorte, Eleonora; Ancidoni, Antonio; Zaccaria, Valerio; Remoli, Giulia; Tariciotti, Leonardo; Bellomo, Guido; Sciancalepore, Francesco; Corbo, Massimo; Lombardo, Flavia L; Bacigalupo, Ilaria; Canevelli, Marco; Piscopo, Paola; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Monoclonal antibodies (mAbs) are currently among the most investigated targets for potential disease-modifying therapies in Alzheimer's disease (AD). OBJECTIVE: Our objectives were to identify all registered trials investigating mAbs in MCI due to AD or AD at any stage, retrieve available published and unpublished data from all registered trials, and analyze data on safety and efficacy outcomes. METHODS: A systematic search of all registered trials on ClinicalTrials.gov and EUCT was performed. Available results were searched on both platforms and on PubMed, ISI Web of Knowledge, and The Cochrane Library. RESULTS: Overall, 101 studies were identified on 27 mAbs. Results were available for 50 trials investigating 12 mAbs. For 18 trials, data were available from both published and unpublished sources, for 21 trials only from published sources, and for 11 trials only from unpublished sources. Meta-analyses of amyloid-related imaging abnormalities (ARIA) events showed overall risk ratios of 10.65 for ARIA-E and of 1.75 for ARIA-H. The meta-analysis of PET-SUVR showed an overall significant effect of mAbs in reducing amyloid (SMD -0.88), but when considering clinical efficacy, data on CDR-SB showed that treated patients had a statistically significant but clinically non-relevant lower worsening (MD -0.15). CONCLUSION: Our results suggest that the risk-benefit profile of mAbs remains unclear. Research should focus on clarifying the effect of amyloid on cognitive decline, providing data on treatment response rate, and accounting for minimal clinically important difference. Research on mAbs should also investigate the possible long-term impact of ARIA events, including potential factors predicting their onset.
Keywords: Alzheimer Disease; Amyloid; Amyloidogenic Proteins; Amyloidosis; Antibodies, Monoclonal; Cognitive Dysfunction; Humans

Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Positive Modulator of HGF/MET, Fosgonimeton, in Healthy Volunteers and Subjects with Alzheimer's Disease: Randomized, Placebo-Controlled, Double-Blind, Phase I Clinical Trial. - Hua, Xue; Church, Kevin; Walker, William; L'Hostis, Philippe; Viardot, Geoffrey; Danjou, Philippe; Hendrix, Suzanne; Moebius, Hans J (J Alzheimers Dis, 2022)
BACKGROUND: Fosgonimeton (ATH-1017) is being developed as a first-in-class regenerative therapy for people with Alzheimer's disease (AD) and dementia; potentially improving dementia symptoms and altering disease progression by reversing synaptic disconnection and neuronal loss. OBJECTIVE: This randomized, double-blind, placebo-controlled phase I trial (NCT03298672) evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of fosgonimeton. METHODS: Fosgonimeton was administered once daily via subcutaneous injection to 88 subjects. The single ascending dose study enrolled healthy young male subjects (n = 48; age, 33.4±6.3 years; dose, 2, 6, 20, 40, 60, or 90 mg); the multiple ascending dose study enrolled healthy elderly subjects (n = 29; age, 63.8±4.0 years; dose, 20, 40, 60, or 80 mg; 9-day duration); and the fixed-dose study enrolled AD subjects (n = 11; age, 69.2±7.1 years; dose, 40 mg; 9-day duration). Quantitative electroencephalogram (qEEG) and event-related potential (ERP) P300 measured neurophysiological signals following fosgonimeton treatment, supporting brain penetration and target engagement. RESULTS: Fosgonimeton and placebo were shown to be safe and well-tolerated across all doses. Pharmacokinetic results for fosgonimeton were dose-proportional, with no sex effect or accumulation over 9 days. The main effect of fosgonimeton on qEEG was acute and sustained gamma power induction. In AD subjects, there was a significant effect toward ERP P300 latency normalization compared with placebo (p = 0.027; n = 7 at 40 mg fosgonimeton versus n = 4 placebo). CONCLUSION: These results support the continued development of fosgonimeton as a novel therapeutic for people with AD and dementia. The fast-onset normalization of ERP P300 latency in AD subjects suggests enhancement of synaptic function and potential procognitive effects.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Dose-Response Relationship, Drug; Double-Blind Method; Healthy Volunteers; Hepatocyte Growth Factor; Humans; Male

Systemic Injection of Aged Blood Plasma in Adult C57BL/6 Mice Induces Neurophysiological Impairments in the Hippocampal CA1. - Huffels, Christiaan F M; van Dijk, Roland E; Karst, Henk; Meye, Frank J; Hol, Elly M; Middeldorp, Jinte (J Alzheimers Dis, 2022)
BACKGROUND: Aging is characterized by systemic alterations and forms an important risk factor for Alzheimer's disease. Recently, it has been indicated that blood-borne factors present in the systemic milieu contribute to the aging process. Exposing young mice to aged blood plasma results in impaired neurogenesis and synaptic plasticity in the dentate gyrus, as well as impaired cognition. Vice versa, treating aged mice with young blood plasma rescues impairments associated with aging. OBJECTIVE: Whether blood-borne factors are sufficient to drive impairments outside the dentate gyrus, how they impact neurophysiology, and how the functional outcome compares to impairments found in mouse models for AD is still unclear. METHODS: Here, we treated adult mice with blood plasma from aged mice and assessed neurophysiological parameters in the hippocampal CA1. RESULTS: Mice treated with aged blood plasma show significantly impaired levels of long-term potentiation (LTP), similar to those present in APP/PS1 mice. These impaired levels of LTP in plasma-treated mice are associated with alterations in basic properties of glutamatergic transmission and the enhanced activity of voltage-gated Ca2 + channels. CONCLUSION: Together, the data presented in this study show that blood-borne factors are sufficient to drive neurophysiological impairments in the hippocampal CA1.

Visually Identified Tau 18F-MK6240 PET Patterns in Symptomatic Alzheimer's Disease. - Krishnadas, Natasha; Huang, Kun; Schultz, Stephanie A; Doré, Vincent; Bourgeat, Pierrick; Goh, Anita M Y; Lamb, Fiona; Bozinovski, Svetlana; Burnham, Samantha C; Robertson, Joanne S; Laws, Simon M; Maruff, Paul; et al. (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease, heterogeneity has been observed in the postmortem distribution of tau neurofibrillary tangles. Visualizing the topography of tau in vivo may facilitate clinical trials and clinical practice. OBJECTIVE: This study aimed to investigate whether tau distribution patterns that are limited to mesial temporal lobe (MTL)/limbic regions, and those that spare MTL regions, can be visually identified using 18F-MK6240, and whether these patterns are associated with different demographic and cognitive profiles. METHODS: Tau 18F-MK6240 PET images of 151 amyloid-β positive participants with mild cognitive impairment (MCI) and dementia were visually rated as: tau negative, limbic predominant (LP), MTL-sparing, and Typical by two readers. Groups were evaluated for differences in age, APOE ɛ4 carriage, hippocampal volumes, and cognition (MMSE, composite memory and non-memory scores). Voxel-wise contrasts were also performed. RESULTS: Visual rating resulted in 59.6% classified as Typical, 17.9% as MTL-sparing, 9.9% LP, and 12.6% as tau negative. Intra-rater and inter-rater reliability was strong (Cohen's kappa values of 0.89 and 0.86 respectively). Tracer retention in a "hook"-like distribution on sagittal sequences was observed in the LP and Typical groups. The visually classified MTL-sparing group had lower APOE ɛ4 carriage and relatively preserved hippocampal volumes. Higher MTL tau was associated with greater amnestic cognitive impairment. High cortical tau was associated with greater impairments on non-memory domains of cognition, and individuals with high cortical tau were more likely to have dementia than MCI. CONCLUSION: Tau distribution patterns can be visually identified using 18F-MK6240 PET and are associated with differences in APOE ɛ4 carriage, hippocampal volumes, and cognition.

Accelerometer-Measured, Habitual Physical Activity and Circulating Brain-Derived Neurotrophic Factor: A Cross-Sectional Study. - Spartano, Nicole L; Himali, Jayandra J; Trinquart, Ludovic; Yang, Qiong; Weinstein, Galit; Satizabal, Claudia L; Dukes, Kimberly A; Beiser, Alexa S; Murabito, Joanne M; Vasan, Ramachandran S; Seshadri, Sudha (J Alzheimers Dis, 2021)
BACKGROUND: One of the mechanisms suggested to link physical activity (PA) to favorable brain health is through stimulation of neural growth factors such as brain-derived neurotrophic factor (BDNF). Acute bouts of PA stimulate circulating BDNF levels. OBJECTIVE: In this investigation, we assessed whether habitual, accelerometer-measured PA levels were related to circulating BDNF levels in a middle-aged cohort. METHODS: In the Framingham Heart Study Third Generation cohort, 1,769 participants provided reliable accelerometry data and were not missing BDNF measurement and platelet counts. In a cross-sectional analysis, using multivariable regression, we related PA measures to serum BDNF levels, adjusting for age, sex, smoking status, platelet count, depression status, and accelerometer wear time. RESULTS: Our study participants (mean age 47±9 years, 50.8% women) spent an average of 22.3 mins/day moderate-to-vigorous (MV)PA. Most PA variables (steps, MVPA, light activity, and sedentary time) were not related to BDNF levels (p > 0.05). We observed a non-linear trend, where 15-50 mins/week vigorous activity was associated with lower BDNF compared to those with 0 min vigorous activity (β= -0.049±0.024, p = 0.05), but with no significant associations at lower or higher vigorous activity levels. In smokers, MVPA was also associated with lower BDNF levels (β= -0.216±0.079, p = 0.01). CONCLUSION: Our study reveals that circulating BDNF is not chronically elevated in individuals with higher levels of habitual PA in middle-aged adults from the community and may even be chronically suppressed with higher PA in subgroups, including current smokers. These results do not contradict previous studies demonstrating that circulating BDNF rises acutely after PA.

Anti-Aβ Antibody Aducanumab Regulates the Proteome of Senile Plaques and Closely Surrounding Tissue in a Transgenic Mouse Model of Alzheimer's Disease. - Bastrup, Joakim; Hansen, Kathrine H; Poulsen, Thomas B G; Kastaniegaard, Kenneth; Asuni, Ayodeji A; Christensen, Søren; Belling, Dorthe; Helboe, Lone; Stensballe, Allan; Volbracht, Christiane (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by accumulation of amyloid-β (Aβ) species and deposition of senile plaques (SPs). Clinical trials with the anti-Aβ antibody aducanumab have been completed recently. OBJECTIVE: To characterize the proteomic profile of SPs and surrounding tissue in a mouse model of AD in 10-month-old tgAPPPS1-21 mice after chronic treatment with aducanumab for four months with weekly dosing (10 mg/kg). METHODS: After observing significant reduction of SP numbers in hippocampi of aducanumab-treated mice, we applied a localized proteomic analysis by combining laser microdissection and liquid chromatography-tandem mass spectrometry (LC-MS/MS) of the remaining SPs in hippocampi. We microdissected three subregions, containing SPs, SP penumbra level 1, and an additional penumbra level 2 to follow the proteomic profile as gradient. RESULTS: In the aducanumab-treated mice, we identified 17 significantly regulated proteins that were associated with 1) mitochondria and metabolism (ACAT2, ATP5J, ETFA, EXOG, HK1, NDUFA4, NDUFS7, PLCB1, PPP2R4), 2) cytoskeleton and axons (ADD1, CAPZB, DPYSL3, MAG), 3) stress response (HIST1H1C/HIST1H1D, HSPA12A), and 4) AβPP trafficking/processing (CD81, GDI2). These pathways and some of the identified proteins are implicated in AD pathogenesis. Proteins associated with mitochondria and metabolism were mainly upregulated while proteins associated with AβPP trafficking/processing and stress response pathways were mainly downregulated, suggesting that aducanumab could lead to a beneficial proteomic profile around SPs in tgAPPPS1-21 mice. CONCLUSION: We identified novel proteomic patterns of SPs and surrounding tissue indicating that chronic treatment with aducanumab could inhibit Aβ toxicity and increase phagocytosis and cell viability.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Antibodies, Monoclonal, Humanized; Brain; Chromatography, Liquid; Cytoskeletal Proteins; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Mitochondrial Proteins; Plaque, Amyloid; Presenilin-1; Protein Transport; Proteome; Proteomics; Stress, Physiological; Tandem Mass Spectrometry

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Apolipoprotein E ɛ4 (APOE ɛ4) Allele is Associated with Long Sleep Duration Among Elderly with Cognitive Impairment. - Basta, Maria; Zaganas, Ioannis; Simos, Panagiotis; Koutentaki, Eirini; Dimovasili, Christina; Mathioudakis, Lambros; Bourbouli, Mara; Panagiotakis, Symeon; Kapetanaki, Stefania; Vgontzas, Alexandros (J Alzheimers Dis, 2021)
BACKGROUND: Apolipoprotein E gene (APOE) ɛ4 allele increases the risk for Alzheimer's disease (AD). Furthermore, among patients with cognitive impairment, longer sleep duration is associated with worse cognitive performance. To date, literature examining the associations between APOE ɛ4 allele and objective sleep duration is limited. OBJECTIVE: Our aim was to assess the association between APOE ɛ4 and objective sleep duration, among patients with mild cognitive impairment (MCI) and AD. A sub-sample of 89 patients with AD (n = 49) and MCI (n = 40) were recruited from a large, population-based cohort of 3,140 elders (>60 years) residing on Crete, Greece. METHODS: All participants underwent medical history/physical examination, extensive neuropsychiatric and neuropsychological evaluation, 3-day 24 h actigraphy and APOE ɛ4 allele genotyping. Comparisons of sleep duration variables between APOE ɛ4 allele carriers and non-carriers were assessed using ANCOVA, controlling for confounders. RESULTS: The sample included 18 APOE ɛ4 carriers and 71 non-carriers, aged 78.6±6.6 and 78.2±6.5 years, respectively. Comparisons between the APOE ɛ4 carriers and non-carriers revealed no significant differences in terms of demographic and clinical variables. In terms of objective sleep duration across the two groups, APOE ɛ4 carriers compared to non-carriers had significantly longer nighttime Total Sleep Time (nTST) (7.7±1.4 versus 7.2±1.3  h, respectively, p = 0.011), as well as 24 h TST (8.5±1.6 versus 7.8±1.5  h, respectively, p = 0.012). CONCLUSION: Among patients with MCI and AD, APOE ɛ4 carriers have longer objective nighttime and 24 h sleep duration compared to non-carriers. These findings further support that objective long sleep duration is a genetically-driven pre-clinical marker associated with worse prognosis in elderly with cognitive impairment.

The Association Between Homocysteine and Memory in Older Adults. - Nelson, Monica E; Andel, Ross; Nedelska, Zuzana; Martinkova, Julie; Cechova, Katerina; Marková, Hana; Matuskova, Veronika; Nikolai, Tomas; Lerch, Ondřej; Pařízková, Martina; Laczó, Jan; Vyhnálek, Martin; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Identifying modifiable risk factors for cognitive decline can reduce burden of dementia. OBJECTIVE: We examined whether homocysteine was associated with memory performance, mediated by entorhinal volume, hippocampal volume, total gray matter volume, or white matter lesions, and moderated by APOE ɛ4 allele, B vitamins, creatinine, total cholesterol, or triglycerides. METHODS: All 204 members of the Czech Brain Aging Study with subjective cognitive decline (SCD; n = 60) or amnestic mild cognitive impairment (aMCI; n = 144) who had valid data were included. Linear regression was used, followed by conditional process modeling to examine mediation and moderation. RESULTS: Controlling for age, sex, and education, higher homocysteine was related to poorer memory performance overall (b = -0.03, SE = 0.01, p = 0.017) and in participants with SCD (b = -0.06, SE = 0.03, p = 0.029), but less so in aMCI (b = -0.03, SE = 0.02, p = 0.074); though sensitivity analyses revealed a significant association when sample was reduced to aMCI patients with more complete cognitive data (who were also better functioning; b = -0.04, SE = 0.02, p = 0.022). Results were unchanged in fully adjusted models. Neither mediation by markers of brain integrity nor moderation by APOE ɛ4, B vitamins, creatinine, and cardiovascular factors were significant. Memory sub-analyses revealed that results for SCD were likely driven by non-verbal memory. The homocysteine-memory relationship was significant when hippocampal volume was below the median (b = -0.04, SE = 0.02, p = 0.046), but not at/above the median (p = 0.247). CONCLUSION: Higher homocysteine levels may adversely influence memory performance, particularly in those without cognitive impairment. Results appear to be independent of brain health, suggesting that homocysteine may represent a good target for intervention.

The Association of Essential Metals with APOE Genotype in Alzheimer's Disease. - Babić Leko, Mirjana; Jurasović, Jasna; Nikolac Perković, Matea; Španić, Ena; Sekovanić, Ankica; Orct, Tatjana; Lukinović Škudar, Vesna; Bačić Baronica, Koraljka; Kiđemet-Piskač, Spomenka; Vogrinc, Željka; Pivac, Nela; Borovečki, Fran; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The major confirmed genetic risk factor for late-onset, sporadic Alzheimer's disease (AD) is variant ɛ4 of apolipoprotein E gene (APOE). It is proposed that ApoE, a protein involved in transport of cholesterol to neurons can cause neurodegeneration in AD through interaction with metals. Previous studies mostly associated copper, iron, zinc, and calcium with ApoE4-mediated toxicity. OBJECTIVE: To test the association of essential metals with APOE genotype. METHODS: We compared plasma and cerebrospinal fluid (CSF) levels of copper, zinc, iron, sodium, magnesium, calcium, cobalt, molybdenum, manganese, boron, and chromium, and CSF ferritin levels among AD, mild cognitive impairment (MCI) patients, and healthy controls (HC) with different APOE genotype. RESULTS: Sodium, copper, and magnesium levels were increased in carriers of ɛ4 allele. Additionally, the increase in sodium, calcium and cobalt plasma levels was observed in carriers of ɛ4/ɛx genotype. The decrease in boron plasma levels was observed in carriers of ɛ4 allele and ɛ4/ɛ4 genotype. Additionally, CSF zinc levels as well as plasma sodium levels were increased in AD patients compared to HC. CONCLUSION: These results indicate that the molecular underpinnings of association of essential metals and metalloids with APOE should be further tested and clarified in vivo and in vitro.

Association of Malnutrition with Functional and Cognitive Trajectories in People Living with Dementia: A Five-Year Follow-Up Study. - Borda, Miguel Germán; Ayala Copete, Ana María; Tovar-Rios, Diego Alejandro; Jaramillo-Jimenez, Alberto; Giil, Lasse Melvær; Soennesyn, Hogne; Gómez-Arteaga, Camilo; Venegas-Sanabria, Luis Carlos; Kristiansen, Ida; Chavarro-Carvajal, Diego Andrés; Caicedo, Sandra; Cano-Gutierrez, Carlos Alberto; et al. (J Alzheimers Dis, 2021)
BACKGROUND: In dementia, functional status depends on multiple factors in addition to cognition. Nutritional status is a potentially modifiable factor related to homeostasis and proper functioning of body systems and may contribute to cognitive and functional decline. OBJECTIVE: This paper aims to analyze the association of malnutrition with the course of cognitive and functional decline in people living with dementia. METHODS: This is an analysis of a longitudinal cohort study, the Dementia Study of Western Norway. Data of 202 patients diagnosed with mild dementia were analyzed; Alzheimer's disease (AD) (n = 103), Lewy body dementia (LBD) (n = 74), and other dementias (OD) (n = 25). Cognition was assessed with the Mini-Mental State Examination and functional decline through the activities of daily living included in the Rapid Disability Rating Scale. The Global Leadership Initiative on Malnutrition Index was used to determine nutritional status. Associations of nutritional status with cognitive and functional decline were evaluated through adjusted linear mixed models. RESULTS: At baseline, the prevalence of general malnutrition was 28.7%; 17.32% were classified as moderate malnutrition and 11.38% as severe malnutrition (there were no significant differences between AD and LBD). Malnutrition at diagnosis and over follow-up was a significant predictor of functional-decline, but not of cognitive decline. CONCLUSION: According to our results malnutrition was associated with faster functional loss but, not cognitive decline in older adults with dementia. A more comprehensive dementia approach including nutritional assessments could improve prognosis.

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Bispecific Tau Antibodies with Additional Binding to C1q or Alpha-Synuclein. - Quint, Wim Hendricus; Matečko-Burmann, Irena; Schilcher, Irene; Löffler, Tina; Schöll, Michael; Burmann, Björn Marcus; Vogels, Thomas (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) and other tauopathies are neurodegenerative disorders characterized by cellular accumulation of aggregated tau protein. Tau pathology within these disorders is accompanied by chronic neuroinflammation, such as activation of the classical complement pathway by complement initiation factor C1q. Additionally, about half of the AD cases present with inclusions composed of aggregated alpha-synuclein called Lewy bodies. Lewy bodies in disorders such as Parkinson's disease and Lewy body dementia also frequently occur together with tau pathology. OBJECTIVE: Immunotherapy is currently the most promising treatment strategy for tauopathies. However, the presence of multiple pathological processes within tauopathies makes it desirable to simultaneously target more than one disease pathway. METHODS: Herein, we have developed three bispecific antibodies based on published antibody binding region sequences. One bispecific antibody binds to tau plus alpha-synuclein and two bispecific antibodies bind to tau plus C1q. RESULTS: Affinity of the bispecific antibodies to their targets compared to their monospecific counterparts ranged from nearly identical to one order of magnitude lower. All bispecific antibodies retained binding to aggregated protein in patient-derived brain sections. The bispecific antibodies also retained their ability to inhibit aggregation of recombinant tau, regardless of whether the tau binding sites were in IgG or scFv format. Mono- and bispecific antibodies inhibited cellular seeding induced by AD-derived pathological tau with similar efficacy. Finally, both Tau-C1q bispecific antibodies completely inhibited the classical complement pathway. CONCLUSION: Bispecific antibodies that bind to multiple pathological targets may therefore present a promising approach to treat tauopathies and other neurodegenerative disorders.

Body Mass Index and Mild Cognitive Impairment Among Middle-Aged and Older Adults from Low- and Middle-Income Countries. - Smith, Lee; Shin, Jae Il; Oh, Hans; Carmichael, Christina; Jacob, Louis; Stefanac, Sinisa; Lindsay, Rosie K; Soysal, Pinar; Veronese, Nicola; Tully, Mark A; Butler, Laurie; Barnett, Yvonne; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The effect of weight modification on future dementia risk is currently a subject of debate and may be modified by age. OBJECTIVE: The aim of the present study was to investigate the association between body mass index (BMI) status with mild cognitive impairment (MCI) (a preclinical stage of dementia) in middle-aged and older adults residing in six low- and middle-income countries using nationally representative data. METHODS: Cross-sectional data from the Study on Global Ageing and Adult Health (SAGE) were analyzed. MCI was defined using the National Institute on Aging-Alzheimer's Association criteria. BMI (kg/m2) was based on measured weight and height and categorized as: underweight (<18.5), normal (18.5-24.9), overweight (25.0-29.9), and obese (≥30.0). Multivariable logistic regression analysis and meta-analysis were conducted to assess associations. RESULTS: Data on 32,715 individuals aged ≥50 years with preservation in functional abilities were analyzed [mean (SD) age 62.1 (15.6) years; 51.7% females]. Among those aged 50-64 years, compared to normal weight, underweight (OR = 1.44; 95% CI = 1.14-1.81), overweight (OR = 1.17; 95% CI = 1.002-1.37), and obesity (OR = 1.46; 95% CI = 1.09-1.94) were all significantly associated with higher odds for MCI. In those aged ≥65 years, underweight (OR = 0.71; 95% CI = 0.54-0.95) and overweight (OR = 0.72; 95% CI = 0.55-0.94) were associated with significantly lower odds for MCI, while obesity was not significantly associated with MCI. CONCLUSION: The results of the study suggest that the association between BMI and MCI is likely moderated by age. Future longitudinal studies are required to confirm or refute the present findings before recommendations for policy and practice can be made.

Broader Insights into Understanding Tumor Necrosis Factor and Neurodegenerative Disease Pathogenesis Infer New Therapeutic Approaches. - Clark, I A; Vissel, B (J Alzheimers Dis, 2021)
Proinflammatory cytokines such as tumor necrosis factor (TNF), with its now appreciated key roles in neurophysiology as well as neuropathophysiology, are sufficiently well-documented to be useful tools for enquiry into the natural history of neurodegenerative diseases. We review the broader literature on TNF to rationalize why abruptly-acquired neurodegenerative states do not exhibit the remorseless clinical progression seen in those states with gradual onsets. We propose that the three typically non-worsening neurodegenerative syndromes, post-stroke, post-traumatic brain injury (TBI), and post cardiac arrest, usually become and remain static because of excess cerebral TNF induced by the initial dramatic peak keeping microglia chronically activated through an autocrine loop of microglial activation through excess cerebral TNF. The existence of this autocrine loop rationalizes post-damage repair with perispinal etanercept and proposes a treatment for cerebral aspects of COVID-19 chronicity. Another insufficiently considered aspect of cerebral proinflammatory cytokines is the fitness of the endogenous cerebral anti-TNF system provided by norepinephrine (NE), generated and distributed throughout the brain from the locus coeruleus (LC). We propose that an intact LC, and therefore an intact NE-mediated endogenous anti-cerebral TNF system, plus the DAMP (damage or danger-associated molecular pattern) input having diminished, is what allows post-stroke, post-TBI, and post cardiac arrest patients a strong long-term survival advantage over Alzheimer's disease and Parkinson's disease sufferers. In contrast, Alzheimer's disease and Parkinson's disease patients remorselessly worsen, being handicapped by sustained, accumulating, DAMP and PAMP (pathogen-associated molecular patterns) input, as well as loss of the LC-origin, NE-mediated, endogenous anti-cerebral TNF system. Adrenergic receptor agonists may counter this.
Keywords: Alzheimer Disease; Anti-Inflammatory Agents, Non-Steroidal; Brain; Brain Injuries; COVID-19; Disease Progression; Etanercept; Heart Arrest; Humans; Locus Coeruleus; Neurodegenerative Diseases; Norepinephrine; Parkinson Disease; Risk Factors; SARS-CoV-2; Stroke; Survivors; Tumor Necrosis Factor-alpha

Cannabidiol Ameliorates Cognitive Function via Regulation of IL-33 and TREM2 Upregulation in a Murine Model of Alzheimer's Disease. - Khodadadi, Hesam; Salles, Évila Lopes; Jarrahi, Abbas; Costigliola, Vincenzo; Khan, M B; Yu, Jack C; Morgan, John C; Hess, David C; Vaibhav, Kumar; Dhandapani, Krishnan M; Baban, Babak (J Alzheimers Dis, 2021)
There is a dire need for due innovative therapeutic modalities to improve outcomes of AD patients. In this study, we tested whether cannabidiol (CBD) improves outcomes in a translational model of familial AD and to investigate if CBD regulates interleukin (IL)-33 and triggering receptor expressed on myeloid cells 2 (TREM2), which are associated with improved cognitive function. CBD was administered to 5xFAD mice, which recapitulate early onset, familial AD. Behavioral tests and immunoassays were used to evaluate cognitive and motor outcomes. Our findings suggest that CBD treatment enhanced IL-33 and TREM2 expression, ameliorated the symptoms of AD, and retarded cognitive decline.
Keywords: Alzheimer Disease; Animals; Cannabidiol; Cognition; Disease Models, Animal; Humans; Interleukin-33; Male; Membrane Glycoproteins; Mice; Mice, Transgenic; Receptors, Immunologic; Up-Regulation

Cerebrospinal Fluid Proteome Changes in Older Non-Cardiac Surgical Patients with Postoperative Cognitive Dysfunction. - VanDusen, Keith W; Li, Yi-Ju; Cai, Victor; Hall, Ashley; Hiles, Sarah; Thompson, J Will; Moseley, M Arthur; Cooter, Mary; Acker, Leah; Levy, Jerrold H; Ghadimi, Kamrouz; Quiñones, Quintin J; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Postoperative cognitive dysfunction (POCD), a syndrome of cognitive deficits occurring 1-12 months after surgery primarily in older patients, is associated with poor postoperative outcomes. POCD is hypothesized to result from neuroinflammation; however, the pathways involved remain unclear. Unbiased proteomic analyses have been used to identify neuroinflammatory pathways in multiple neurologic diseases and syndromes but have not yet been applied to POCD. OBJECTIVE: To utilize unbiased mass spectrometry-based proteomics to identify potential neuroinflammatory pathways underlying POCD. METHODS: Unbiased LC-MS/MS proteomics was performed on immunodepleted cerebrospinal fluid (CSF) samples obtained before, 24 hours after, and 6 weeks after major non-cardiac surgery in older adults who did (n = 8) or did not develop POCD (n = 6). Linear mixed models were used to select peptides and proteins with intensity differences for pathway analysis. RESULTS: Mass spectrometry quantified 8,258 peptides from 1,222 proteins in > 50%of patient samples at all three time points. Twelve peptides from 11 proteins showed differences in expression over time between patients with versus withoutPOCD (q < 0.05), including proteins previously implicated in neurodegenerative disease pathophysiology. Additionally, 283 peptides from 182 proteins were identified with trend-level differences (q < 0.25) in expression over time between these groups. Among these, pathway analysis revealed that 50 were from 17 proteins mapping to complement and coagulation pathways (q = 2.44*10-13). CONCLUSION: These data demonstrate the feasibility of performing unbiased mass spectrometry on perioperative CSF samples to identify pathways associated with POCD. Additionally, they provide hypothesis-generating evidence for CSF complement and coagulation pathway changes in patients with POCD.

Cognitive Effects of Aerobic Exercise in Alzheimer's Disease: A Pilot Randomized Controlled Trial. - Yu, Fang; Vock, David M; Zhang, Lin; Salisbury, Dereck; Nelson, Nathaniel W; Chow, Lisa S; Smith, Glenn; Barclay, Terry R; Dysken, Maurice; Wyman, Jean F (J Alzheimers Dis, 2021)
BACKGROUND: Aerobic exercise has shown inconsistent cognitive effects in older adults with Alzheimer's disease (AD) dementia. OBJECTIVE: To examine the immediate and longitudinal effects of 6-month cycling on cognition in older adults with AD dementia. METHODS: This randomized controlled trial randomized 96 participants (64 to cycling and 32 to stretching for six months) and followed them for another six months. The intervention was supervised, moderate-intensity cycling for 20-50 minutes, 3 times a week for six months. The control was light-intensity stretching. Cognition was assessed at baseline, 3, 6, 9, and 12 months using the AD Assessment Scale-Cognition (ADAS-Cog). Discrete cognitive domains were measured using the AD Uniform Data Set battery. RESULTS: The participants were 77.4±6.8 years old with 15.6±2.9 years of education, and 55%were male. The 6-month change in ADAS-Cog was 1.0±4.6 (cycling) and 0.1±4.1 (stretching), which were both significantly less than the natural 3.2±6.3-point increase observed naturally with disease progression. The 12-month change was 2.4±5.2 (cycling) and 2.2±5.7 (control). ADAS-Cog did not differ between groups at 6 (p = 0.386) and 12 months (p = 0.856). There were no differences in the 12-month rate of change in ADAS-Cog (0.192 versus 0.197, p = 0.967), memory (-0.012 versus -0.019, p = 0.373), executive function (-0.020 versus -0.012, p = 0.383), attention (-0.035 versus -0.033, p = 0.908), or language (-0.028 versus -0.026, p = 0.756). CONCLUSION: Exercise may reduce decline in global cognition in older adults with mild-to-moderate AD dementia. Aerobic exercise did not show superior cognitive effects to stretching in our pilot trial, possibly due to the lack of power.

A Cost-Consequence Analysis of Different Screening Procedures in Alzheimer's Disease: Results from the MOPEAD Project. - Wimo, Anders; Belger, Mark; Bon, Jaka; Jessen, Frank; Dumas, Annette; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo Salas, Adrián; Rodríguez Gómez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al. (J Alzheimers Dis, 2021)
BACKGROUND: For care planning and support, under-detection and late diagnosis of Alzheimer's disease (AD) is a great challenge. Models of Patient-Engagement for Alzheimer's Disease (MOPEAD) is an EU-funded project aiming at testing different strategies to improve this situation. OBJECTIVE: To make a cost-consequence analysis of MOPEAD. METHODS: Four screening strategies were tested in five countries (Germany, the Netherlands, Slovenia, Spain, and Sweden): 1) a web-approach; 2) Open-House initiative; 3) in primary care; and 4) by diabetes specialists. Persons-at-risk of AD in all strategies were offered referral to a hospital-based specialist. The primary health-economic outcome was the cost per true-positive case (TP) of AD from the screened population. RESULTS: Of 2,847 screened persons, 1,121 screened positive (39%), 402 were evaluated at memory clinics (14%), and 236 got an AD diagnosis (8%). The cost per TP of those screened was 3,115€ with the web-approach, 2,722€ with the Open-House, 1,530€ in primary care, and 1,190€ by diabetes specialists. Sensitivity analyses that more likely reflect the real-world situation confirmed the results. The number-needed-to-screen was 30 with the web-approach, 8 with the Open-House and primary care, and 6 with the diabetes specialists.There were country differences in terms of screening rates, referrals to memory clinics, staff-types involved, and costs per TP. CONCLUSION: In primary care and by the diabetes specialist, the costs per TP/screened population were lowest, but the capacity of such settings to identify cases with AD-risk must be discussed. Hence new diagnostic strategies such as web-solutions and Open-House initiatives may be valuable after modifications.

Current Status and Challenges of Stem Cell Treatment for Alzheimer's Disease. - Pacheco-Herrero, Mar; Soto-Rojas, Luis O; Reyes-Sabater, Heidy; Garcés-Ramirez, Linda; de la Cruz López, Fidel; Villanueva-Fierro, Ignacio; Luna-Muñoz, José (J Alzheimers Dis, 2021)
Neurodegenerative diseases called tauopathies, such as Alzheimer's disease (AD), frontotemporal dementia, progressive supranuclear palsy, and Parkinson's disease, among others, are characterized by the pathological processing and accumulation of tau protein. AD is the most prevalent neurodegenerative disease and is characterized by two lesions: neurofibrillary tangles (NFTs) and neuritic plaques. The presence of NFTs in the hippocampus and neocortex in early and advanced stages, respectively, correlates with the patient's cognitive deterioration. So far, no drugs can prevent, decrease, or limit neuronal death due to abnormal pathological tau accumulation. Among potential non-pharmacological treatments, physical exercise has been shown to stimulate the development of stem cells (SCs) and may be useful in early stages. However, this does not prevent neuronal death from the massive accumulation of NFTs. In recent years, SCs therapies have emerged as a promising tool to repopulate areas involved in cognition in neurodegenerative diseases. Unfortunately, protocols for SCs therapy are still being developed and the mechanism of action of such therapy remains unclear. In this review, we show the advances and limitations of SCs therapy. Finally, we provide a critical analysis of its clinical use for AD.
Keywords: Alzheimer Disease; Amyloid; Government Regulation; Hippocampus; Humans; Neocortex; Neurofibrillary Tangles; Plaque, Amyloid; Stem Cells; tau Proteins

Dementia and Parkinson's Disease: Risk Factors for 30-Day Mortality in Nursing Home Residents with COVID-19. - Rutten, Jeanine J S; van Kooten, Janine; van Loon, Anouk M; van Buul, Laura W; Joling, Karlijn J; Smalbrugge, Martin; Hertogh, Cees M P M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic has led to high mortality rates in nursing homes (NHs) in Europe. For adequate risk management and good prognostications, it is essential to identify mortality risk factors. OBJECTIVE: This study aimed to determine whether previously identified risk factors for 30-day mortality in Dutch NH residents with COVID-19 are unique to COVID-19. METHODS: In this cohort study, we included 1,294 NH residents with COVID-19 (cases) and 17,999 NH residents without COVID-19 (controls, from the pre-COVID-19 period). We used descriptive statistics and Cox proportional hazard models to compare mortality rates in residents with and without COVID-19, categorized by risk factors. RESULTS: Cases had a more than 18 times higher hazard of death within 30 days compared to controls (HR 18, 95%CI: 16-20). For residents with COVID-19, being male, having dementia, and having Parkinson's disease (PD) were all associated with a higher 30-day mortality (HR 1.8 versus 1.3 versus 1.7). Being male was also associated with a higher mortality (HR 1.7) in the control group, whereas having dementia and PD were not. COVID-19 symptomatology was very similar for residents with and without dementia or PD, except for delirium and malaise which was more frequent in residents with dementia. CONCLUSION: Dementia and PD were significant additional risk factors for mortality in Dutch NH residents with COVID-19, whereas male gender was not unique to residents with COVID-19. The frailty of PD and dementia in NH residents with COVID-19 are relevant to consider in prognostication, communication, and care planning with residents and their families.

Depressive Symptoms Imputed Across the Life Course Are Associated with Cognitive Impairment and Cognitive Decline. - Brenowitz, Willa D; Zeki Al Hazzouri, Adina; Vittinghoff, Eric; Golden, Sherita H; Fitzpatrick, Annette L; Yaffe, Kristine (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms may increase risk for dementia, but findings are controversial because late-life depression may be a prodromal dementia symptom. Life course data on depression and dementia risk may clarify this association; however, data is limited. OBJECTIVE: To impute adult depressive symptoms trajectories across adult life stages and estimate the association with cognitive impairment and decline. METHODS: Using a pooled study of 4 prospective cohorts (ages 20-89), we imputed adult life course depressive symptoms trajectories based on Center for Epidemiologic Studies Depression Scale-10 (CESD-10) and calculated time-weighted averages for early adulthood (ages 20-49), mid-life (ages 50-69), and late-life (ages 70-89) for 6,122 older participants. Adjusted pooled logistic and mixed-effects models estimated associations of imputed depressive symptoms with two cognitive outcomes: cognitive impairment defined by established criteria and a composite cognitive score. RESULTS: In separate models, elevated depressive symptoms in each life stage were associated with cognitive outcomes: early adulthood OR for cognitive impairment = 1.59 (95%CI: 1.35,1.87); mid-life OR = 1.94 (95%CI:1.16, 3.26); and late-life OR = 1.77 (95%CI:1.42, 2.21). When adjusted for depressive symptoms in the other life-stages, elevated depressive symptoms in early adulthood (OR = 1.73; 95%CI: 1.42,2.11) and late-life (OR = 1.43; 95%CI: 1.08,1.89) remained associated with cognitive impairment and were also associated with faster rates of cognitive decline (p <  0.05). CONCLUSION: Imputing depressive symptom trajectories from pooled cohorts may help expand data across the life course. Our findings suggest early adulthood depressive symptoms may be a risk factor for cognitive impairment independent of mid- or late-life depressive symptoms.

Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Elevated Norepinephrine Metabolism Gauges Alzheimer's Disease-Related Pathology and Memory Decline. - Riphagen, Joost M; van Egroo, Maxime; Jacobs, Heidi I L (J Alzheimers Dis, 2021)
The noradrenergic (NE) locus coeruleus (LC) is vulnerable to hyperphosphorylated tau, and dysregulated NE-metabolism is linked to greater tau and disease progression. We investigated whether elevated NE-metabolism alone predicts memory decline or whether concomitant presence of tau and amyloid-β is required. Among 114 memory clinic participants, time trends (max. six years) showed dose-response declines in learning across groups with elevated NE-metabolite 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) with no, one, or two Alzheimer's disease biomarkers; and no decline in the low MHPG group. Elevated MHPG is required and sufficient to detect learning declines, supporting a pathophysiologic model including the LC-NE system contributing to initial Alzheimer's disease-related processes.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Humans; Learning; Locus Coeruleus; Male; Memory Disorders; Methoxyhydroxyphenylglycol; Middle Aged; Neuropsychological Tests; Norepinephrine; Predictive Value of Tests; tau Proteins

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Life Course Air Pollution Exposure and Cognitive Decline: Modelled Historical Air Pollution Data and the Lothian Birth Cohort 1936. - Russ, Tom C; Cherrie, Mark P C; Dibben, Chris; Tomlinson, Sam; Reis, Stefan; Dragosits, Ulrike; Vieno, Massimo; Beck, Rachel; Carnell, Ed; Shortt, Niamh K; Muniz-Terrera, Graciela; Redmond, Paul; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution has been consistently linked with dementia and cognitive decline. However, it is unclear whether risk is accumulated through long-term exposure or whether there are sensitive/critical periods. A key barrier to clarifying this relationship is the dearth of historical air pollution data. OBJECTIVE: To demonstrate the feasibility of modelling historical air pollution data and using them in epidemiologicalmodels. METHODS: Using the EMEP4UK atmospheric chemistry transport model, we modelled historical fine particulate matter (PM2.5) concentrations for the years 1935, 1950, 1970, 1980, and 1990 and combined these with contemporary modelled data from 2001 to estimate life course exposure in 572 participants in the Lothian Birth Cohort 1936 with lifetime residential history recorded. Linear regression and latent growth models were constructed using cognitive ability (IQ) measured by the Moray House Test at the ages of 11, 70, 76, and 79 years to explore the effects of historical air pollution exposure. Covariates included sex, IQ at age 11 years, social class, and smoking. RESULTS: Higher air pollution modelled for 1935 (when participants would have been in utero) was associated with worse change in IQ from age 11-70 years (β = -0.006, SE = 0.002, p = 0.03) but not cognitive trajectories from age 70-79 years (p > 0.05). There was no support for other critical/sensitive periods of exposure or an accumulation of risk (all p > 0.05). CONCLUSION: The life course paradigm is essential in understanding cognitive decline and this is the first study to examine life course air pollution exposure in relation to cognitive health.
Keywords: Adolescent; Adult; Aged; Air Pollution; Child; Cognitive Dysfunction; Environmental Exposure; Female; History, 20th Century; Humans; Linear Models; Male; Middle Aged; Particulate Matter; Scotland; Young Adult

Lipidomic Network of Mild Cognitive Impairment from the Mayo Clinic Study of Aging. - Wang, Xuewei; Bui, Hai; Vemuri, Prashanthi; Graff-Radford, Jonathan; Jack, Clifford R; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2021)
BACKGROUND: Lipid alterations contribute to Alzheimer's disease (AD) pathogenesis. Lipidomics studies could help systematically characterize such alterations and identify potential biomarkers. OBJECTIVE: To identify lipids associated with mild cognitive impairment and amyloid-β deposition, and to examine lipid correlation patterns within phenotype groupsMethods:Eighty plasma lipids were measured using mass spectrometry for 1,255 non-demented participants enrolled in the Mayo Clinic Study of Aging. Individual lipids associated with mild cognitive impairment (MCI) were first identified. Correlation network analysis was then performed to identify lipid species with stable correlations across conditions. Finally, differential correlation network analysis was used to determine lipids with altered correlations between phenotype groups, specifically cognitively unimpaired versus MCI, and with elevated brain amyloid versus without. RESULTS: Seven lipids were associated with MCI after adjustment for age, sex, and APOE4. Lipid correlation network analysis revealed that lipids from a few species correlated well with each other, demonstrated by subnetworks of these lipids. 177 lipid pairs differently correlated between cognitively unimpaired and MCI patients, whereas 337 pairs of lipids exhibited altered correlation between patients with and without elevated brain amyloid. In particular, 51 lipid pairs showed correlation alterations by both cognitive status and brain amyloid. Interestingly, the lipids central to the network of these 51 lipid pairs were not significantly associated with either MCI or amyloid, suggesting network-based approaches could provide biological insights complementary to traditional association analyses. CONCLUSION: Our attempt to characterize the alterations of lipids at network-level provides additional insights beyond individual lipids, as shown by differential correlations in our study.

Loneliness, Not Social Support, Is Associated with Cognitive Decline and Dementia Across Two Longitudinal Population-Based Cohorts. - Freak-Poli, Rosanne; Wagemaker, Nina; Wang, Rui; Lysen, Thom S; Ikram, M Arfan; Vernooij, Meike W; Dintica, Christina S; Vernooij-Dassen, Myrra; Melis, Rene J M; Laukka, Erica J; Fratiglioni, Laura; Xu, Weili; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Poor social health is likely associated with cognitive decline and risk of dementia; however, studies show inconsistent results. Additionally, few studies separate social health components or control for mental health. OBJECTIVE: To investigate whether loneliness and social support are independently associated with cognitive decline and risk of dementia, and whether depressive symptoms confound the association. METHODS: We included 4,514 participants from the population-based Rotterdam Study (RS; aged 71±7SD years) followed up to 14 years (median 10.8, interquartile range 7.4-11.6), and 2,112 participants from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K; aged 72±10SD years) followed up to 10 years (mean 5.9±1.6SD). At baseline, participants were free of major depression and scored on the Mini-Mental State Examination (MMSE) ≥26 for RS and ≥25 for SNAC-K. We investigated loneliness, perceived social support, and structural social support (specifically marital status and number of children). In both cohorts, dementia was diagnosed and cognitive function was repeatedly assessed with MMSE and a global cognitive factor (g-factor). RESULTS: Loneliness was prospectively associated with a decline in the MMSE in both cohorts. Consistently, persons who were lonely had an increased risk of developing dementia (RS: HR 1.34, 95%CI 1.08-1.67; SNAC-K: HR 2.16, 95%CI 1.12-4.17). Adjustment for depressive symptoms and exclusion of the first 5 years of follow-up did not alter results. Neither perceived or structural social support was associated with cognitive decline or dementia risk. CONCLUSION: Loneliness, not social support, predicted cognitive decline and incident dementia independently of depressive symptoms.

Longitudinally Increasing Elevated Asymmetric Flortaucipir Binding in a Cognitively Unimpaired Amyloid-Negative Older Individual. - Schwarz, Christopher G; Knopman, David S; Ramanan, Vijay K; Lowe, Val J; Wiste, Heather J; Cogswell, Petrice M; Utianski, Rene L; Senjem, Matthew L; Gunter, Jeffrey R; Vemuri, Prashanthi; Petersen, Ronald C; Jack, Clifford R (J Alzheimers Dis, 2021)
We present the case of a cognitively unimpaired 77-year-old man with elevated, asymmetric, and longitudinally increasing Flortaucipir tau PET despite normal (visually negative) amyloid PET. His atypical tau PET signal persisted and globally increased in a follow-up scan five years later. Across eight years of observations, temporoparietal atrophy was observed consistent with tau PET patterns, but he retained the cognitively unimpaired classification. Altogether, his atypical tau PET signal is not explained by any known risk factors or alternative pathologies, and other imaging findings were not remarkable. He remains enrolled for further observation.

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

New Frontiers in the Prevention, Diagnosis, and Treatment of Alzheimer's Disease. - Guzmán-Martínez, Leonardo; Calfío, Camila; Farías, Gonzalo A; Vilches, Cristian; Prieto, Raul; Maccioni, Ricardo B (J Alzheimers Dis, 2021)
One of the major puzzles in medical research and public health systems worldwide is Alzheimer's disease (AD), reaching nowadays a prevalence near 50 million people. This is a multifactorial brain disorder characterized by progressive cognitive impairment, apathy, and mood and neuropsychiatric disorders. The main risk of AD is aging; a normal biological process associated with a continuum dynamic involving a gradual loss of people's physical capacities, but with a sound experienced view of life. Studies suggest that AD is a break from normal aging with changes in the powerful functional capacities of neurons as well as in the mechanisms of neuronal protection. In this context, an important path has been opened toward AD prevention considering that there are elements of nutrition, daily exercise, avoidance of toxic substances and drugs, an active social life, meditation, and control of stress, to achieve healthy aging. Here, we analyze the involvement of such factors and how to control environmental risk factors for a better quality of life. Prevention as well as innovative screening programs for early detection of the disease using reliable biomarkers are becoming critical to control the disease. In addition, the failure of traditional pharmacological treatments and search for new drugs has stimulated the emergence of nutraceutical compounds in the context of a "multitarget" therapy, as well as mindfulness approaches shown to be effective in the aging, and applied to the control of AD. An integrated approach involving all these preventive factors combined with novel pharmacological approaches should pave the way for the future control of the disease.
Keywords: Acupuncture Therapy; Aging; Alzheimer Disease; Biomarkers; Dietary Supplements; Early Diagnosis; Humans; Medicine, Chinese Traditional; Meditation; Quality of Life; Treatment Outcome

Niemann-Pick Type C 1 (NPC1) and NPC2 Gene Variability in Demented Patients with Evidence of Brain Amyloid Deposition. - Sorrentino, Federica; Arighi, Andrea; Serpente, Maria; Arosio, Beatrice; Arcaro, Marina; Visconte, Caterina; Rotondo, Emanuela; Vimercati, Roberto; Ferri, Evelyn; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variants in Niemann-Pick Type C genes (NPC1 and NPC2) have been suggested to play a role as risk or disease modifying factors for Alzheimer's disease (AD). OBJECTIVE: The aim of this study was to analyze NPC1 and NPC2 variability in demented patients with evidence of brain amyloid-β 1-42 (Aβ) deposition and to correlate genetic data with clinical phenotypes. METHODS: A targeted Next Generation Sequencing panel was customized to screen NPC1, NPC2, and main genes related to neurodegenerative dementias in a cohort of 136 demented patients with cerebrospinal fluid (CSF) low Aβ levels or positive PET with Aβ tracer and 200 non-demented geriatric subjects. RESULTS: Seven patients were carriers of NPC variants in heterozygosis. Four of them displayed pathogenic variants previously found in NPC patients and one AD patient had a novel variant. The latter was absent in 200 non-demented elderly subjects. Five of seven patients (70%) exhibited psychiatric symptoms at onset or later as compared with 43%in non-carriers (p >  0.05). CONCLUSION: The frequency of NPC1 and NPC2 heterozygous variants in patients with CSF evidence of Aβ deposition is higher than in the general population.

NLRP3 Inflammasome: A Starring Role in Amyloid-β- and Tau-Driven Pathological Events in Alzheimer's Disease. - Van Zeller, Mariana; Dias, Diogo; Sebastião, Ana M; Valente, Cláudia A (J Alzheimers Dis, 2021)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disease commonly diagnosed among the elderly population. AD is characterized by the loss of synaptic connections, neuronal death, and progressive cognitive impairment, attributed to the extracellular accumulation of senile plaques, composed by insoluble aggregates of amyloid-β (Aβ) peptides, and to the intraneuronal formation of neurofibrillary tangles shaped by hyperphosphorylated filaments of the microtubule-associated protein tau. However, evidence showed that chronic inflammatory responses, with long-lasting exacerbated release of proinflammatory cytokines by reactive glial cells, contribute to the pathophysiology of the disease. NLRP3 inflammasome (NLRP3), a cytosolic multiprotein complex sensor of a wide range of stimuli, was implicated in multiple neurological diseases, including AD. Herein, we review the most recent findings regarding the involvement of NLRP3 in the pathogenesis of AD. We address the mechanisms of NLRP3 priming and activation in glial cells by Aβ species and the potential role of neurofibrillary tangles and extracellular vesicles in disease progression. Neuronal death by NLRP3-mediated pyroptosis, driven by the interneuronal tau propagation, is also discussed. We present considerable evidence to claim that NLRP3 inhibition, is undoubtfully a potential therapeutic strategy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Astrocytes; Humans; Inflammasomes; Inflammation; Microglia; NLR Family, Pyrin Domain-Containing 3 Protein; Tauopathies

Pharmacological Strategies to Improve Dendritic Spines in Alzheimer's Disease. - Ettcheto, Miren; Busquets, Oriol; Cano, Amanda; Sánchez-López, Elena; Manzine, Patricia R; Espinosa-Jimenez, Triana; Verdaguer, Ester; Sureda, Francesc X; Olloquequi, Jordi; Castro-Torres, Ruben D; Auladell, Carme; Folch, Jaume; et al. (J Alzheimers Dis, 2021)
To deeply understand late onset Alzheimer's disease (LOAD), it may be necessary to change the concept that it is a disease exclusively driven by aging processes. The onset of LOAD could be associated with a previous peripheral stress at the level of the gut (changes in the gut microbiota), obesity (metabolic stress), and infections, among other systemic/environmental stressors. The onset of LOAD, then, may result from the generation of mild peripheral inflammatory processes involving cytokine production associated with peripheral stressors that in a second step enter the brain and spread out the process causing a neuroinflammatory brain disease. This hypothesis could explain the potential efficacy of Sodium Oligomannate (GV-971), a mixture of acidic linear oligosaccharides that have shown to remodel gut microbiota and slowdown LOAD. However, regardless of the origin of the disease, the end goal of LOAD-related preventative or disease modifying therapies is to preserve dendritic spines and synaptic plasticity that underlay and support healthy cognition. Here we discuss how systemic/environmental stressors impact pathways associated with the regulation of spine morphogenesis and synaptic maintenance, including insulin receptor and the brain derived neurotrophic factor signaling. Spine structure remodeling is a plausible mechanism to maintain synapses and provide cognitive resilience in LOAD patients. Importantly, we also propose a combination of drugs targeting such stressors that may be able to modify the course of LOAD by acting on preventing dendritic spines and synapsis loss.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Dendritic Spines; Diet, Healthy; Exercise; Gastrointestinal Microbiome; Humans; Mannose; Oligosaccharides; Synapses

Physical Activity and Trajectory of Cognitive Change in Older Persons: Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Syrjanen, Jeremy A; Bezold, Jelena; Trautwein, Sandra; Barisch-Fritz, Bettina; Boes, Klaus; Woll, Alexander; Forzani, Erica; Kremers, Walter K; Machulda, Mary M; Mielke, Michelle M; Knopman, David S; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Little is known about the association between physical activity (PA) and cognitive trajectories in older adults. OBJECTIVE: To examine the association between PA and change in memory, language, attention, visuospatial skills, and global cognition, and a potential impact of sex or Apolipoprotein E (APOE) ɛ4 status. METHODS: Longitudinal study derived from the population-based Mayo Clinic Study of Aging, including 2,060 cognitively unimpaired males and females aged ≥70 years. Engagement in midlife (ages 50-65) and late-life (last year) PA was assessed using a questionnaire. Neuropsychological testing was done every 15 months (mean follow-up 5.8 years). We ran linear mixed-effect models to examine whether mid- or late-life PA at three intensities (mild, moderate, vigorous) was associated with cognitive z-scores. RESULTS: Light intensity midlife PA was associated with less decline in memory function compared to the no-PA reference group (time x light PA; estimate [standard error] 0.047 [0.016], p = 0.004). Vigorous late-life PA was associated with less decline in language (0.033 [0.015], p = 0.030), attention (0.032 [0.017], p = 0.050), and global cognition (0.039 [0.016], p = 0.012). Females who were physically inactive in midlife experienced more pronounced cognitive decline than females physically active in midlife and males regardless of PA (p-values for time interaction terms with midlife PA levels and sex were all p <  0.05 for global cognition). APOE ɛ4 carriership did not moderate the association between PA and cognition. CONCLUSION: Engaging in PA, particularly of vigorous intensity in late-life, was associated with less pronounced decline in global and domain-specific cognition. This association may differ by sex.

Plasma EFEMP1 Is Associated with Brain Aging and Dementia: The Framingham Heart Study. - McGrath, Emer R; Himali, Jayandra J; Levy, Daniel; Yang, Qiong; DeCarli, Charles S; Courchesne, Paul; Satizabal, Claudia L; Finney, Rebecca; Vasan, Ramachandran S; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2021)
BACKGROUND: Epidermal growth factor containing fibulin extracellular matrix protein-1 (EFEMP1) has been associated with increased white matter hyperintensities (WMH) burden and disorders of premature aging and may have a shared pathophysiological role in the development of WMH and dementia. OBJECTIVE: To determine the association between plasma EFEMP1 levels and MRI markers of vascular brain injury and incident all-cause and Alzheimer's disease (AD) dementia. METHODS: We measured plasma EFEMP1 levels in 1597 [53% women, mean age 68.7 (SD 5.7) years] dementia-free Framingham Offspring cohort participants between 1998-2001 and subsequently followed them for incident dementia. Secondary outcomes included stroke, structural MRI brain measures and neurocognitive test performance. RESULTS: During a median 11.8 [Q1, Q3 : 7.1, 13.3] year follow-up, 131 participants developed dementia. The highest quintile of plasma EFEMP1, compared to the bottom four quintiles, was associated with an increased risk of time to incident all-cause dementia (HR 1.77, 95% CI 1.18-2.64) and AD dementia (HR 1.76, 95% CI 1.11-2.81) but not with markers of vascular brain injury (WMH, covert brain infarcts or stroke). Higher circulating EFEMP1 concentrations were also cross-sectionally associated with lower total brain (β±SE, -0.28±0.11, p = 0.01) and hippocampal volumes (-0.006±0.003, p = 0.04) and impaired abstract reasoning (Similarities test, -0.18±0.08, p = 0.018 per standard deviation increment in EFEMP1). CONCLUSION: Elevated circulating EFEMP1 is associated with an increased risk of all-cause and AD dementia, smaller hippocampal and total brain volumes, and poorer cognitive performance. EFEMP1 may play an important biological role in the development of AD dementia. Further studies to validate these findings are warranted.

Relevance of a Truncated PRESENILIN 2 Transcript to Alzheimer's Disease and Neurodegeneration. - Moussavi Nik, Seyyed Hani; Porter, Tenielle; Newman, Morgan; Bartlett, Benjamin; Khan, Imran; Sabale, Miheer; Eccles, Melissa; Woodfield, Amy; Groth, David; Doré, Vincent; Villemagne, Victor L; Masters, Colin L; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The PRESENILIN genes (PSEN1, PSEN2) encoding for their respective proteins have critical roles in many aspects of Alzheimer's disease (AD) pathogenesis. The PS2V transcript of PSEN2 encodes a truncated protein and is upregulated in AD brains; however, its relevance to AD and disease progression remains to be determined. OBJECTIVE: Assess transcript levels in postmortem AD and non-AD brain tissue and in lymphocytes collected under the Australian Imaging Biomarker and Lifestyle (AIBL) study. METHODS: Full length PSEN2 and PS2V transcript levels were assessed by quantitative digital PCR in postmortem brain tissue (frontal cortex and hippocampus) from control, AD, frontotemporal dementia (FTD), and Lewy body dementia (LBD). Transcript levels were also assessed in lymphocytes obtained from the Perth subset of the AIBL study (n = 160). Linear regression analysis was used to assess correlations between transcript copy number and brain volume and neocortical amyloid load. RESULTS: PS2V levels increased in AD postmortem brain but PS2V was also present at significant levels in FTD and LBD brains. PS2V transcript was detected in lymphocytes and PS2V/PSEN2 ratios were increased in mild cognitive impairment (p = 0.024) and AD (p = 0.019) groups compared to control group. Increased ratios were significantly correlated with hippocampal volumes only (n = 62, β= -0.269, p = 0.03). CONCLUSION: Taken together, these results suggest that PS2V may be a marker of overall neurodegeneration.

Research Attitudes and Interest Among Elderly Latinxs: The Impact of a Collaborative Video and Community Peers. - Sewell, Margaret C; Neugroschl, Judith; Umpierre, Mari; Chin, Shehan; Zhu, Carolyn W; Velasco, Nelly; Gonzalez, Sabrina; Acabá-Berrocal, Alexandra; Bianchetti, Luca; Silva, Gabriela; Collazo, Alma; Sano, Mary (J Alzheimers Dis, 2021)
BACKGROUND: Latinx elders are underrepresented in dementia research. In a previous study we assessed research attitudes in urban minority elders and found a significant minority expressed neutral to negative attitudes relating to trust, safety, and personal responsibility to help research. OBJECTIVE: To assess the impact of a composite intervention on attitudes toward research and research participation among elderly Latinx. The intervention was a collaboratively produced research participation video shown during presentations with our elderly community advisory board (CAB) as co-presenters. METHODS: The video was created by the ADRC and CAB. All senior center attendees were eligible to participate. Afterwards, the Research Attitudes Questionnaire (RAQ) and a brief questionnaire on the impact of the video were administered. Using Wilcoxon Rank Sum Tests, Chi Square, and OLS regressions, RAQ responses were compared to those from a historical cohort from similar centers. RESULTS: 74 in the "Historical Cohort 1" and 104 in "Intervention Cohort 2" were included. RAQ total score was higher in Cohort 2 than Cohort 1 (28.5 versus 26.1, p <  0.05) after controlling for age, education, and country of origin. In response to the question "Has the video influenced your willingness and interest to participate in research", 88.7%of the participants in Cohort 2 reported being "more" or "much more" interested in research. CONCLUSION: Tailoring community research recruitment programs to include relatable peers using novel recruitment techniques may have positive implications for improving enrollment of diverse elderly individuals in research.

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

Selective Impairment of Long-Range Default Mode Network Functional Connectivity as a Biomarker for Preclinical Alzheimer's Disease in People with Down Syndrome. - DiProspero, Natalie D; Keator, David B; Phelan, Michael; van Erp, Theo G M; Doran, Eric; Powell, David K; Van Pelt, Kathryn L; Schmitt, Frederick A; Head, Elizabeth; Lott, Ira T; Yassa, Michael A (J Alzheimers Dis, 2021)
BACKGROUND: Down syndrome (DS) is associated with increased risk for Alzheimer's disease (AD). In neurotypical individuals, clinical AD is preceded by reduced resting state functional connectivity in the default mode network (DMN), but it is unknown whether changes in DMN connectivity predict clinical onset of AD in DS. OBJECTIVE: Does lower DMN functional connectivity predict clinical onset of AD and cognitive decline in people with DS? METHODS: Resting state functional MRI (rsfMRI), longitudinal neuropsychological, and clinical assessment data were collected on 15 nondemented people with DS (mean age = 51.66 years, SD = 5.34 years, range = 42-59 years) over four years, during which 4 transitioned to dementia. Amyloid-β (Aβ) PET data were acquired on 13 of the 15 participants. Resting state fMRI, neuropsychological, and clinical assessment data were also acquired on an independent, slightly younger unimpaired sample of 14 nondemented people with DS (mean age = 44.63 years, SD = 7.99 years, range = 38-61 years). RESULTS: Lower functional connectivity between long-range but not short-range DMN regions predicts AD diagnosis and cognitive decline in people with DS. Aβ accumulation in the inferior parietal cortex is associated with lower regional DMN functional connectivity. CONCLUSION: Reduction of long-range DMN connectivity is a potential biomarker for AD in people with DS that precedes and predicts clinical conversion.

Substance Use-Related Cognitive Decline in Families with Autosomal Dominant Alzheimer's Disease: A Cohort Study. - Ramos, Claudia; Villalba, Camilo; García, Jenny; Lanata, Serggio; López, Hugo; Aguillón, David; Cordano, Christian; Madrigal, Lucía; Aguirre-Acevedo, Daniel C; Lopera, Francisco (J Alzheimers Dis, 2021)
BACKGROUND: Cigarette smoking is a known risk factor for Alzheimer's disease (AD). However, the association between neurodegeneration and other substances has not been fully determined. It is of vital importance to evaluate this relationship in populations at high risk of dementia. Since substance use possibly modifies the progression rate of cognitive decline, we studied this association in a unique and well-phenotyped cohort from the University of Antioquia: carriers of the PSEN1-E280A genetic variant. OBJECTIVE: To determine the association between substance use and cognitive decline in carriers of the PSEN1-E280A genetic variant. METHODS: A retrospective cohort study was conducted with 94 carriers and 69 noncarriers recruited between January 2019 and April 2020. A psychiatrist interviewed the participants using the Consumption of Alcohol, Cigarettes and other Substances questionnaire. The participants were also submitted to cognitive evaluation. The relationship between cognitive decline and substance use was explored through a mixed effects regression model. RESULTS: There was an association between cigarettes and better performance on tasks related to perceptual organization, verbal fluency, and memory in carriers. Alcohol had a positive or negative effect on memory according to the type of alcoholic beverage. Results on marijuana use were no conclusive. Coffee was associated with progressive improvements in executive function and verbal fluency. CONCLUSION: Cigarette and alcohol were associated with an improvement of some cognitive assessments, possibly by a survival bias. In addition, coffee was related to improvements in executive function and language; therefore, its short-term neuroprotective potential should be studied.

Time Trends of Cerebrospinal Fluid Biomarkers of Neurodegeneration in Idiopathic Normal Pressure Hydrocephalus. - Lukkarinen, Heikki; Tesseur, Ina; Pemberton, Darrel; van der Ark, Peter; Timmers, Maarten; Slemmon, Randy; Janssens, Luc; Streffer, Johannes; Van Nueten, Luc; Bottelbergs, Astrid; Rauramaa, Tuomas; Koivisto, Anne M; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Longitudinal changes in cerebrospinal fluid (CSF) biomarkers are seldom studied. Furthermore, data on biomarker gradient between lumbar (L-) and ventricular (V-) compartments seems to be discordant. OBJECTIVE: To examine alteration of CSF biomarkers reflecting Alzheimer's disease (AD)-related amyloid-β (Aβ) aggregation, tau pathology, neurodegeneration, and early synaptic degeneration by CSF shunt surgery in idiopathic normal pressure hydrocephalus (iNPH) in relation to AD-related changes in brain biopsy. In addition, biomarker levels in L- and V-CSF were compared. METHODS: L-CSF was collected prior to shunt placement and, together with V-CSF, 3-73 months after surgery. Thereafter, additional CSF sampling took place at 3, 6, and 18 months after the baseline sample from 26 iNPH patients with confirmed Aβ plaques in frontal cortical brain biopsy and 13 iNPH patients without Aβ pathology. CSF Amyloid-β42 (Aβ42), total tau (T-tau), phosphorylated tau (P-tau181), neurofilament light (NFL), and neurogranin (NRGN) were analyzed with customized ELISAs. RESULTS: All biomarkers but Aβ42 increased notably by 140-810% in L-CSF after CSF diversion and then stabilized. Aβ42 instead showed divergent longitudinal decrease between Aβ-positive and -negative patients in L-CSF, and thereafter increase in Aβ-negative iNPH patients in both L- and V-CSF. All five biomarkers correlated highly between V-CSF and L-CSF (Aβ42 R = 0.87, T-tau R = 0.83, P-tau R = 0.92, NFL R = 0.94, NRGN R = 0.9; all p <  0.0001) but were systematically lower in V-CSF (Aβ42 14 %, T-tau 22%, P-tau 20%, NFL 32%, NRGN 19%). With APOE genotype-grouping, only Aβ42 showed higher concentration in non-carriers of allele ɛ4. CONCLUSION: Longitudinal follow up shows that after an initial post-surgery increase, T-tau, P-tau, and NRGN are stable in iNPH patients regardless of brain biopsy Aβ pathology, while NFL normalized toward its pre-shunt levels. Aβ42 as biomarker seems to be the least affected by the surgical procedure or shunt and may be the best predictor of AD risk in iNPH patients. All biomarker concentrations were lower in V- than L-CSF yet showing strong correlations.

Upregulation of Cortical A2A Adenosine Receptors Is Reflected in Platelets of Patients with Alzheimer's Disease. - Merighi, Stefania; Battistello, Enrica; Casetta, Ilaria; Gragnaniello, Daniela; Poloni, Tino Emanuele; Medici, Valentina; Cirrincione, Alice; Varani, Katia; Vincenzi, Fabrizio; Borea, Pier Andrea; Gessi, Stefania (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative pathology covering about 70%of all cases of dementia. Adenosine, a ubiquitous nucleoside, plays a key role in neurodegeneration, through interaction with four receptor subtypes. The A2A receptor is upregulated in peripheral blood cells of patients affected by Parkinson's and Huntington's diseases, reflecting the same alteration found in brain tissues. However, whether these changes are also present in AD pathology has not been determined. OBJECTIVE: In this study we verified any significant difference between AD cases and controls in both brain and platelets and we evaluated whether peripheral A2A receptors may reflect the status of neuronal A2A receptors. METHODS: We evaluated the expression of A2A receptors in frontal white matter, frontal gray matter, and hippocampus/entorhinal cortex, in postmortem AD patients and control subjects, through [3H]ZM 241385 binding experiments. The same analysis was performed in peripheral platelets from AD patients versus controls. RESULTS: The expression of A2A receptors in frontal white matter, frontal gray matter, and hippocampus/entorhinal cortex, revealed a density (Bmax) of 174±29, 219±33, and 358±84 fmol/mg of proteins, respectively, in postmortem AD patients in comparison to 104±16, 103±19, and 121±20 fmol/mg of proteins in controls (p < 0.01). The same trend was observed in peripheral platelets from AD patients versus controls (Bmax of 214±17 versus 95±4 fmol/mg of proteins, respectively, p < 0.01). CONCLUSION: AD subjects show significantly higher A2A receptor density than controls. Values on platelets seem to correlate with those in the brain supporting a role for A2A receptor as a possible marker of AD pathology and drug target for novel therapies able to modify the progression of dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Platelets; Cerebral Cortex; Female; Humans; Male; Receptor, Adenosine A2A; Up-Regulation

Age of Migration and Cognitive Function Among Older Latinos in the United States. - Garcia, Marc A; Ortiz, Kasim; Arévalo, Sandra P; Diminich, Erica D; Briceño, Emily; Vega, Irving E; Tarraf, Wassim (J Alzheimers Dis, 2020)
BACKGROUND: Age of migration has been shown to have a robust association with Latino immigrant health outcomes; however, the relationship between timing of migration and cognition is less understood. OBJECTIVE: To examine associations between race/ethnicity, nativity, age of migration, and cognitive aging among US-born (USB) non-Latino Whites (NLW) and USB and foreign-born Latinos 50 years and older. METHODS: We used longitudinal biennial data from the Health and Retirement Study (HRS; 2006-2014) to fit generalized linear and linear latent growth curve models for: 1) global cognition (Modified Telephone Interview for Cognitive Status; TICS-M); 2) memory and attention subdomains of TICS-M; and 3) cognitive dysfunction. We also tested for sex modifications. RESULTS: In age and sex adjusted models, all Latino subgroups, independent of nativity and age of migration, had lower global and domain-specific cognitive scores and higher propensity of cognitive impairment classification compared to USB-NLWs. Differences between USB Latinos, but not other Latino subgroups, and USB-NLWs remained after full covariate adjustment. Latinas, independent of nativity or age of migration, had poorer cognitive scores relative to NLW females. Differences between all Latinos and USB-NLWs were principally expressed at baseline. Racial/ethnic, nativity, and age of migration grouping was not associated with slope (nor explained variance) of cognitive decline. CONCLUSION: Older US-born Latinos, regardless of sex exhibit poorer cognitive function than older USB-NLWs and foreign-born Latinos. Social determinants that differentially affect cognitive function, particularly those that compensate for education and sex differences among US-born Latinos and foreign-born Latinos, require further exploration.

Aluminum and Amyloid-β in Familial Alzheimer's Disease. - Mold, Matthew; Linhart, Caroline; Gómez-Ramírez, Johana; Villegas-Lanau, Andrés; Exley, Christopher (J Alzheimers Dis, 2020)
Genetic predispositions associated with metabolism of the amyloid-β protein precursor underlie familial Alzheimer's disease; a form of dementia characterized by early disease onset and elevated levels of cortical amyloid-β. Human exposure to aluminum is linked to the etiology of Alzheimer's disease and recent research measured a high content of aluminum in brain tissue in familial Alzheimer's disease. To elaborate upon this finding, we have obtained brain tissues from a Colombian cohort of donors with familial Alzheimer's disease. We have used established methods to measure the aluminum content of these tissues and we have compared the data with a recently measured dataset for control brain tissues. We report significantly higher levels of aluminum in brain tissues in donors with familial Alzheimer's disease than in control tissues from donors without neurological impairment or neurodegeneration. We have used aluminum-specific fluorescence microscopy along with complementary imaging for amyloid-β to demonstrate a very high degree of co-localization of these two risk factors in brain tissue in familial Alzheimer's disease. Aluminum and amyloid-β were co-located in senile plaques as well as vasculature, the latter resembling cerebral amyloid angiopathy. Aluminum was also found separately from amyloid-β in intracellular compartments including glia and neuronal axons. The research has identified an arguably unique association between high brain aluminum content and amyloid-β and allows postulation that genetic predispositions defining familial Alzheimer's disease underlie this relationship.

Angiotensin II Blood Levels Are Associated with Smaller Hippocampal and Cortical Volumes in Cognitively Normal Older Adults. - Yasar, Sevil; Moored, Kyle D; Adam, Atif; Zabel, Fiona; Chuang, Yi-Fang; Varma, Vijay R; Carlson, Michelle C (J Alzheimers Dis, 2020)
BACKGROUND: There is emerging evidence about possible involvement of the renin-angiotensin system (RAS) in the pathogenesis of Alzheimer's disease (AD) and decline of cognitive function. However, little is known about associations with brain biomarkers. OBJECTIVE: Our study aimed to examine associations between blood ACE-1 and ANG II levels and brain MRI based volumes in non-demented participants, and whether these associations were mediated by blood pressure. METHODS: This cross-sectional study was conducted in 34 older participants from the Baltimore Experience Corps Trial (BECT) Brain Health Sub-study (BHS). Blood ANGII and ACE-1 levels were measured by ELISA and brain MRI volumes were generated using FreeSurfer 6.0. Multiple linear regression analysis, adjusting for intracranial volume and confounders, was used to determine associations between log transformed ANGII and ACE-1 levels and MRI volumes (mm3). RESULTS: Participants were predominantly female (76%), African-American (94%), with mean age of 66.9 and education of 14.4 years. In the fully adjusted model we observed significant inverse associations between log ANGII levels and total grey matter (β=Angiotensin II associated with smaller hippocampus14,935.50, ±7,444.83, p = 0.05), total hippocampus (β=-129.97, ±105.27, p = 0.03), rostral middle frontal (β= -1580.40, ±584.74, p = 0.02), and supramarginal parietal (β= -978.90, ±365.54, p = 0.02) volumes. There were no associations between ANGII levels and total white matter or entorhinal cortex volumes, or ACE-1 levels and any brain volumes. CONCLUSION: We observed that increased blood ANGII levels were associated with lower total grey matter, hippocampal, rostral middle frontal, and supramarginal parietal volumes, which are associated with cognitive domains that decline in preclinical AD.

APOEɛ4-TOMM40L Haplotype Increases the Risk of Mild Cognitive Impairment Conversion to Alzheimer's Disease. - Cardoso, Remy; Lemos, Carolina; Oliveiros, Bárbara; Rosário Almeida, Maria; Baldeiras, Ines; Fragão Pereira, Cláudia; Santos, Ana; Duro, Diana; Vieira, Daniela; Santana, Isabel; Resende Oliveira, Catarina (J Alzheimers Dis, 2020)
BACKGROUND: Mild cognitive impairment (MCI) has been considered as a pre-dementia stage, although the factors leading to Alzheimer's disease (AD) conversion remain controversial. OBJECTIVE: Evaluate whether TOMM40 poly-T (TOMM40' 523) polymorphism is associated with the risk and conversion time from MCI to AD and secondly with AD cerebrospinal fluid (CSF) biomarkers, disentangling the APOE genotype. METHODS: 147 AD patients, 102 MCI patients, and 105 cognitively normal controls were genotyped for poly-T polymorphism. MCI patients were subdivided into two groups, the group of patients that converted to AD (MCI-AD) and the group of those that remained stable (MCI-S). RESULTS: TOMM40' 523 L allele was significantly more frequent in the MCI-AD group and having at least one L allele significantly increased the risk of conversion from MCI to AD (OR = 8.346, p <  0.001, 95% CI: 2.830 to 24.617). However, when adjusted for the presence of APOEɛ4 allele, both the L allele and ɛ4 allele lost significance in the model (p >  0.05). We then analyzed the APOEɛ4-TOMM40' 523 haplotype and observed that patients carrying this haplotype had significantly higher risk (OR = 5.83; 95% CI = 2.30-14.83) and mean lower times of conversion to AD (p = 0.003). This haplotype was also significantly associated with a biomarker profile compatible with AD (p = 0.007). CONCLUSION: This study shows that the APOEɛ4-TOMM40' 523 haplotype is associated with a higher risk and shorter times of conversion from MCI to AD, possibly driven by CSF biomarkers and mitochondrial dysfunction.

Cognitive Impairment Is a Common Comorbidity in Deceased COVID-19 Patients: A Hospital-Based Retrospective Cohort Study. - Martín-Jiménez, Paloma; Muñoz-García, Mariana I; Seoane, David; Roca-Rodríguez, Lucas; García-Reyne, Ana; Lalueza, Antonio; Maestro, Guillermo; Folgueira, Dolores; Blanco-Palmero, Víctor A; Herrero-San Martín, Alejandro; Llamas-Velasco, Sara; Pérez-Martínez, David A; et al. (J Alzheimers Dis, 2020)
We analyzed the frequency of cognitive impairment (CI) in deceased COVID-19 patients at a tertiary hospital in Spain. Among the 477 adult cases who died after admission from March 1 to March 31, 2020, 281 had confirmed COVID-19. CI (21.1% dementia and 8.9% mild cognitive impairment) was a common comorbidity. Subjects with CI were older, tended to live in nursing homes, had shorter time from symptom onset to death, and were rarely admitted to the ICU, receiving palliative care more often. CI is a frequent comorbidity in deceased COVID-19 subjects and is associated with differences in care.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Cognitive Dysfunction; Comorbidity; COVID-19; Female; Hospital Mortality; Hospitals; Humans; Male; Middle Aged; Palliative Care; Patient Admission; Retrospective Studies; Spain; Young Adult

Comorbidity of Cerebrovascular and Alzheimer's Disease in Aging. - Xia, Ying; Yassi, Nawaf; Raniga, Parnesh; Bourgeat, Pierrick; Desmond, Patricia; Doecke, James; Ames, David; Laws, Simon M; Fowler, Christopher; Rainey-Smith, Stephanie R; Martins, Ralph; Maruff, Paul; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrovascular disease often coexists with Alzheimer's disease (AD). While both diseases share common risk factors, their interrelationship remains unclear. Increasing the understanding of how cerebrovascular changes interact with AD is essential to develop therapeutic strategies and refine biomarkers for early diagnosis. OBJECTIVE: We investigate the prevalence and risk factors for the comorbidity of amyloid-β (Aβ) and cerebrovascular disease in the Australian Imaging, Biomarkers and Lifestyle Study of Ageing, and further examine their cross-sectional association. METHODS: A total of 598 participants (422 cognitively normal, 89 with mild cognitive impairment, 87 with AD) underwent positron emission tomography and structural magnetic resonance imaging for assessment of Aβ deposition and cerebrovascular disease. Individuals were categorized based on the comorbidity status of Aβ and cerebrovascular disease (V) as Aβ-V-, Aβ-V+, Aβ+V-, or Aβ+V+. RESULTS: Advancing age was associated with greater likelihood of cerebrovascular disease, high Aβ load and their comorbidity. Apolipoprotein E ɛ4 carriage was only associated with Aβ positivity. Greater total and regional WMH burden were observed in participants with AD. However, no association were observed between Aβ and WMH measures after stratification by clinical classification, suggesting that the observed association between AD and cerebrovascular disease was driven by the common risk factor of age. CONCLUSION: Our observations demonstrate common comorbid condition of Aβ and cerebrovascular disease in later life. While our study did not demonstrate a convincing cross-sectional association between Aβ and WMH burden, future longitudinal studies are required to further confirm this.

Concentration-Dependent Activity of Hydromethylthionine on Clinical Decline and Brain Atrophy in a Randomized Controlled Trial in Behavioral Variant Frontotemporal Dementia. - Shiells, Helen; Schelter, Bjoern O; Bentham, Peter; Baddeley, Thomas C; Rubino, Christopher M; Ganesan, Harish; Hammel, Jeffrey; Vuksanovic, Vesna; Staff, Roger T; Murray, Alison D; Bracoud, Luc; Wischik, Damon J; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Hydromethylthionine is a potent inhibitor of pathological aggregation of tau and TDP-43 proteins. OBJECTIVE: To compare hydromethylthionine treatment effects at two doses and to determine how drug exposure is related to treatment response in bvFTD. METHODS: We undertook a 52-week Phase III study in 220 bvFTD patients randomized to compare hydromethylthionine at 200 mg/day and 8 mg/day (intended as a control). The principal outcomes were change on the Addenbrookes Cognitive Examination - Revised (ACE-R), the Functional Activities Questionnaire (FAQ), and whole brain volume. Secondary outcomes included Modified Clinical Global Impression of Change (Modified-CGIC). A population pharmacokinetic exposure-response analysis was undertaken in 175 of the patients with available blood samples and outcome data using a discriminatory plasma assay for the parent drug. RESULTS: There were no significant differences between the two doses as randomized. There were steep concentration-response relationships for plasma levels in the range 0.3-0.6 ng/ml at the 8 mg/day dose on clinical and MRI outcomes. There were significant exposure-dependent differences at 8 mg/day for FAQ, Modified-CGIC, and whole brain atrophy comparing patients with plasma levels greater than 0.346 ng/ml with having minimal drug exposure. The exposure-response is biphasic with worse outcomes at the high concentrations produced by 200 mg/day. CONCLUSIONS: Hydromethylthionine has a similar concentration-response profile for effects on clinical decline and brain atrophy at the 8 mg/day dose in bvFTD as recently reported in AD. Treatment responses in bvFTD are predicted to be maximal at doses in the range 20-60 mg/day. A confirmatory placebo-controlled trial is now planned.

Day-to-Day Home Blood Pressure Variability is Associated with Cerebral Small Vessel Disease Burden in a Memory Clinic Population. - de Heus, Rianne A A; Reumers, Stacha F I; van der Have, Alba; Tumelaire, Maxime; Tully, Phillip J; Claassen, Jurgen A H R (J Alzheimers Dis, 2020)
BACKGROUND: High visit-to-visit blood pressure variability (BPV) has been associated with cognitive decline and cerebral small vessel disease (cSVD), in particular cerebrovascular lesions. Whether day-to-day BPV also relates to cSVD has not been investigated. OBJECTIVE: To investigate the cross-sectional association between day-to-day BPV and total cSVD MRI burden in older memory clinic patients. METHODS: We included outpatients referred to our memory clinic, who underwent cerebral MRI as part of their diagnostic assessment. We determined the validated total cSVD score (ranging from 0-4) by combining four markers of cSVD that were visually rated. Home blood pressure (BP) measurements were performed for one week, twice a day, according to international guidelines. BPV was defined as the within-subject coefficient of variation (CV; standard deviation/mean BP*100). We used multivariable ordinal logistic regression analyses adjusted for age, sex, smoking, diabetes, antihypertensive medication, history of cardiovascular disease, and mean BP. RESULTS: For 82 patients (aged 71.2±7.9 years), mean home BP was 140/79±15/9 mmHg. Dementia and mild cognitive impairment were diagnosed in 46% and 34%, respectively. 78% had one or more markers of cSVD. Systolic CV was associated with cSVD burden (adjusted odds ratio per point increase in CV = 1.29, 95% confidence interval = 1.04-1.60, p = 0.022). There were no differences in diastolic CV and mean BP between the cSVD groups. When we differentiated between morning and evening BP, only evening BPV remained significantly associated with total cSVD burden. CONCLUSION: Day-to-day systolic BPV is associated with cSVD burden in memory clinic patients. Future research should indicate whether lowering BPV should be included in BP management in older people with memory complaints.

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain. - Benaque, Alba; Gurruchaga, Miren Jone; Abdelnour, Carla; Hernandez, Isabel; Cañabate, Pilar; Alegret, Montserrat; Rodríguez, Isabel; Rosende-Roca, Maitee; Tartari, Juan Pablo; Esteban, Ester; López, Rogelio; Gil, Silvia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. OBJECTIVE: To share our experience in adapting our model of care to the new situation to ensure continuity of care. METHODS: We detail the sequence of events and the actions taken within Fundació ACE to swiftly adapt our face-to-face model of care to one based on telemedicine consultations. We characterize individuals under follow-up by the Memory Unit from 2017 to 2019 and compare the number of weekly visits in 2020 performed before and after the lockdown was imposed. RESULTS: The total number of individuals being actively followed by Fundació ACE Memory Unit grew from 6,928 in 2017 to 8,147 in 2019. Among those newly diagnosed in 2019, most patients had mild cognitive impairment or mild dementia (42% and 25%, respectively). Weekly visits dropped by 60% following the suspension of face-to-face activity. However, by April 24 we were able to perform 78% of the visits we averaged in the weeks before confinement began. DISCUSSION: We have shown that Fundació ACE model of care has been able to successfully adapt to a health and social critical situation as COVID-19 pandemic. Overall, we were able to guarantee the continuity of care while preserving the safety of patients, families, and professionals. We also seized the opportunity to improve our model of care.
Keywords: Aged; Aged, 80 and over; Betacoronavirus; Coronavirus Infections; COVID-19; Dementia; Female; Follow-Up Studies; Holistic Health; Humans; Male; Pandemics; Patient-Centered Care; Pneumonia, Viral; SARS-CoV-2; Spain; Telemedicine

Detection of Mild Cognitive Impairment in an At-Risk Group of Older Adults: Can a Novel Self-Administered Serious Game-Based Screening Test Improve Diagnostic Accuracy? - Zygouris, Stelios; Iliadou, Paraskevi; Lazarou, Eftychia; Giakoumis, Dimitrios; Votis, Konstantinos; Alexiadis, Anastasios; Triantafyllidis, Andreas; Segkouli, Sofia; Tzovaras, Dimitrios; Tsiatsos, Thrasyvoulos; Papagianopoulos, Sotirios; Tsolaki, Magda (J Alzheimers Dis, 2020)
BACKGROUND: Literature supports the use of serious games and virtual environments to assess cognitive functions and detect cognitive decline. This promising assessment method, however, has not yet been translated into self-administered screening instruments for pre-clinical dementia. OBJECTIVE: The aim of this study is to assess the performance of a novel self-administered serious game-based test, namely the Virtual Supermarket Test (VST), in detecting mild cognitive impairment (MCI) in a sample of older adults with subjective memory complaints (SMC), in comparison with two well-established screening instruments, the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE). METHODS: Two groups, one of healthy older adults with SMC (N = 48) and one of MCI patients (N = 47) were recruited from day centers for cognitive disorders and administered the VST, the MoCA, the MMSE, and an extended pencil and paper neuropsychological test battery. RESULTS: The VST displayed a correct classification rate (CCR) of 81.91% when differentiating between MCI patients and older adults with SMC, while the MoCA displayed of CCR of 72.04% and the MMSE displayed a CCR of 64.89%. CONCLUSION: The three instruments assessed in this study displayed significantly different performances in differentiating between healthy older adults with SMC and MCI patients. The VST displayed a good CCR, while the MoCA displayed an average CCR and the MMSE displayed a poor CCR. The VST appears to be a robust tool for detecting MCI in a population of older adults with SMC.

Development and Validation of a High Sensitivity Assay for Measuring p217 + tau in Cerebrospinal Fluid. - Triana-Baltzer, Gallen; Van Kolen, Kristof; Theunis, Clara; Moughadam, Setareh; Slemmon, Randy; Mercken, Marc; Galpern, Wendy; Sun, Hong; Kolb, Hartmuth (J Alzheimers Dis, 2020)
BACKGROUND: Early and accurate detection and staging is critical to managing Alzheimer's disease (AD) and supporting clinical trials. Cerebrospinal fluid (CSF) biomarkers for amyloid-β peptides, tau species, and various neurodegenerative and inflammatory analytes are leading the way in this regard, yet there is room for improved sensitivity and specificity. In particular tau is known to be present in many different fragments, conformations, and post-translationally modified forms. While the exact tau species that might best reflect AD pathology is unknown, a growing body of evidence suggests that forms with high levels of phosphorylation in the mid-region may be especially enriched in AD. OBJECTIVE: Develop an assay for measuring p217tau in CSF. METHODS: Here we describe the development and validation of a novel sELISA for measuring CSF tau species containing phosphorylation at threonines 212 & 217, aka p217 + tau, using the PT3 antibody. RESULTS: While the analyte is present at extremely low levels the assay is sufficiently sensitive and specific to quantitate p217 + tau with excellent precision, accuracy, and dilution linearity, allowing good differentiation between diagnostic subgroups. The p217 + tau measurements appear to track AD pathology better than the commonly used p181tau epitope, suggesting superior diagnostic and staging performance. Finally, the assay can also be configured to differentiate antibody-bound versus antibody-free tau, and therefore can be used to measure target engagement by p217 + tau-targeting immunotherapeutics. CONCLUSION: The assay for measuring p217 + tau described here is highly sensitive, accurate, precise, dilution linear, and shows good potential for identifying and staging AD.

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Epilepsy in Neurodegenerative Dementias: A Clinical, Epidemiological, and EEG Study. - Arnaldi, Dario; Donniaquio, Andrea; Mattioli, Pietro; Massa, Federico; Grazzini, Matteo; Meli, Riccardo; Filippi, Laura; Grisanti, Stefano; Famá, Francesco; Terzaghi, Michele; Girtler, Nicola; Brugnolo, Andrea; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Seizures are common in patients with dementia but precise epidemiologic data of epilepsy in neurodegenerative dementia is lacking. OBJECTIVE: The first aim of the study was to investigate prevalence and clinical characteristics of epilepsy in a large cohort of patients with neurodegenerative dementias. Subsequently, we explored clinical, neuropsychological, and quantitative electroencephalogram (qEEG) data of Alzheimer's disease (AD) patients with epilepsy (AD-EPI) as compared to AD patients without epilepsy (AD-CTR). METHODS: We retrospectively evaluated consecutive patients with a diagnosis of a neurodegenerative dementia and a clinically diagnosed epilepsy that required antiepileptic drugs (AED). All patients underwent baseline comprehensive neuropsychological assessment. A follow-up of at least one year was requested to confirm the dementia diagnosis. In AD patients, qEEG power band analysis was performed. AD-CTR and AD-EPI patients were matched for age, Mini-Mental State Examination score, and gender. RESULTS: Thirty-eight out of 2,054 neurodegenerative dementia patients had epilepsy requiring AED. The prevalence of epilepsy was 1.82% for AD, 1.28% for the behavioral variant of frontotemporal dementia (bvFTD), 2.47% for dementia with Lewy bodies (DLB), and 12% for primary progressive aphasia. Epilepsy were more drug-responsive in AD than in non-AD dementias. Finally, no significant differences were found in neuropsychological and qEEG data between AD-EPI and AD-CTR patients. CONCLUSION: In our cohort, AD, FTD, and DLB dementias have similar prevalence of epilepsy, even if AD patients were more responsive to AED. Moreover, AD-EPI patients did not have significant clinical, neuropsychological qEEG differences compared with AD-CTR patients.

Estrogens Inhibit Amyloid-β-Mediated Paired Helical Filament-Like Conformation of Tau Through Antioxidant Activity and miRNA 218 Regulation in hTau Mice. - Guglielmotto, Michela; Manassero, Giusi; Vasciaveo, Valeria; Venezia, Marika; Tabaton, Massimo; Tamagno, Elena (J Alzheimers Dis, 2020)
BACKGROUND: The risk of developing Alzheimer's disease as well as its progression and severity are known to be different in men and women, and cognitive decline is greater in women than in men at the same stage of disease and could be correlated at least in part on estradiol levels. OBJECTIVE: In our work we found that biological sex influences the effect of amyloid-β42 (Aβ42) monomers on pathological tau conformational change. METHODS: In this study we used transgenic mice expressing the wild-type human tau (hTau) which were subjected to intraventricular (ICV) injections of Aβ peptides in nanomolar concentration. RESULTS: We found that Aβ42 produces pathological conformational changes and hyperphosphorylation of tau protein in male or ovariectomized female mice but not in control females. The treatment of ovariectomized females with estradiol replacement protects against the pathological conformation of tau and seems to be mediated by antioxidant activity as well as the ability to modulate the expression of miRNA 218 linked to tau phosphorylation. CONCLUSION: Our study indicates that factors as age, reproductive stage, hormone levels, and the interplay with other risk factors should be considered in women, in order to identify the best appropriate therapeutic approach in prevention of cognitive impairment.

Gait Disturbances are Associated with Increased Cognitive Impairment and Cerebrospinal Fluid Tau Levels in a Memory Clinic Cohort. - Muurling, Marijn; Rhodius-Meester, Hanneke F M; Pärkkä, Juha; van Gils, Mark; Frederiksen, Kristian S; Bruun, Marie; Hasselbalch, Steen G; Soininen, Hilkka; Herukka, Sanna-Kaisa; Hallikainen, Merja; Teunissen, Charlotte E; Visser, Pieter Jelle; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Gait analysis with accelerometers is a relatively inexpensive and easy to use method to potentially support clinical diagnoses of Alzheimer's disease and other dementias. It is not clear, however, which gait features are most informative and how these measures relate to Alzheimer's disease pathology. OBJECTIVE: In this study, we tested if calculated features of gait 1) differ between cognitively normal subjects (CN), mild cognitive impairment (MCI) patients, and dementia patients, 2) are correlated with cerebrospinal fluid (CSF) biomarkers related to Alzheimer's disease, and 3) predict cognitive decline. METHODS: Gait was measured using tri-axial accelerometers attached to the fifth lumbar vertebra (L5) in 58 CN, 58 MCI, and 26 dementia participants, while performing a walk and dual task. Ten gait features were calculated from the vertical L5 accelerations, following principal component analysis clustered in four domains, namely pace, rhythm, time variability, and length variability. Cognitive decline over time was measured using MMSE, and CSF biomarkers were available in a sub-group. RESULTS: Linear mixed models showed that dementia patients had lower pace scores than MCI patients and CN subjects (p < 0.05). In addition, we found associations between the rhythm domain and CSF-tau, especially in the dual task. Gait was not associated with CSF Aβ42 levels and cognitive decline over time as measured with the MMSE. CONCLUSION: These findings suggest that gait-particularly measures related to pace and rhythm-are altered in dementia and have a direct link with measures of neurodegeneration.

Heavy Metals Exposure and Alzheimer's Disease and Related Dementias. - Bakulski, Kelly M; Seo, Young Ah; Hickman, Ruby C; Brandt, Daniel; Vadari, Harita S; Hu, Howard; Park, Sung Kyun (J Alzheimers Dis, 2020)
Alzheimer's disease and related dementias lack effective treatment or cures and are major public health challenges. Risk for Alzheimer's disease and related dementias is partially attributable to environmental factors. The heavy metals lead, cadmium, and manganese are widespread and persistent in our environments. Once persons are exposed to these metals, they are adept at entering cells and reaching the brain. Lead and cadmium are associated with numerous health outcomes even at low levels of exposure. Although manganese is an essential metal, deficiency or environmental exposure or high levels of the metal can be toxic. In cell and animal model systems, lead, cadmium, and manganese are well documented neurotoxicants that contribute to canonical Alzheimer's disease pathologies. Adult human epidemiologic studies have consistently shown lead, cadmium, and manganese are associated with impaired cognitive function and cognitive decline. No longitudinal human epidemiology study has assessed lead or manganese exposure on Alzheimer's disease specifically though two studies have reported a link between cadmium and Alzheimer's disease mortality. More longitudinal epidemiologic studies with high-quality time course exposure data and incident cases of Alzheimer's disease and related dementias are warranted to confirm and estimate the proportion of risk attributable to these exposures. Given the widespread and global exposure to lead, cadmium, and manganese, even small increases in the risks of Alzheimer's disease and related dementias would have a major population impact on the burden on disease. This article reviews the experimental and epidemiologic literature of the associations between lead, cadmium, and manganese on Alzheimer's disease and related dementias and makes recommendations of critical areas of future investment.

Impact of APOE and BDNF Val66Met Gene Polymorphisms on Cognitive Functions in Patients with Amnestic Mild Cognitive Impairment. - Cechova, Katerina; Andel, Ross; Angelucci, Francesco; Chmatalova, Zuzana; Marková, Hana; Laczó, Jan; Vyhnálek, Martin; Matoska, Vaclav; Kaplan, Vojtech; Nedelska, Zuzana; Ward, David D; Hort, Jakub (J Alzheimers Dis, 2020)
Apolipoprotein (APOE) ɛ4 is a well-known risk factor for late-onset Alzheimer's disease (AD), but other AD-related gene polymorphisms might also be important, such as the polymorphism within the brain-derived neurotrophic factor (BDNF) gene. Carriage of BDNF Val66Met has been associated with faster cognitive decline and greater hippocampal atrophy in cognitively normal elderly. Thus, we examined the effects of the concurrent presence of APOE and BDNF polymorphisms on cognitive functions and brain morphometry in amnestic mild cognitive impairment (aMCI) patients. 107 aMCI patients (mean age = 72.2) were recruited from the Czech Brain Aging Study and, based on APOE and BDNF genes polymorphisms, were divided into four groups: ɛ4-BDNFVal/Val (n = 37), ɛ4-BDNFMet (n = 19), ɛ4+BDNFVal/Val (n = 35), and ɛ4+BDNFMet (n = 16). All patients underwent clinical examination, magnetic resonance imaging, and complex neuropsychological battery. The combination of APOEɛ4+ and BDNF Met was associated with significantly worse memory performance in immediate and delayed recall compared to other polymorphism groups. We did not observe increased atrophy in areas related to memory function in the ɛ4+BDNFMet group. Our findings suggest that carriage of ɛ4+BDNFMet is associated with more pronounced memory dysfunction, a typical feature of early AD, but not with structural brain changes in aMCI patients. These findings suggest that in APOEɛ4/BDNF Met carriers, synaptic dysfunction affecting memory may precede pronounced structural changes.

Influence of Comorbidity of Cerebrovascular Disease and Amyloid-β on Alzheimer's Disease. - Yassi, Nawaf; Hilal, Saima; Xia, Ying; Lim, Yen Ying; Watson, Rosie; Kuijf, Hugo; Fowler, Christopher; Yates, Paul; Maruff, Paul; Martins, Ralph; Ames, David; Chen, Christopher; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Quantifying the contribution of cerebrovascular disease to the clinical and pathological profile of Alzheimer's disease is challenging. OBJECTIVE: We aimed to determine the influence of cerebrovascular disease, amyloid-β (Aβ), and their comorbidity on cognitive decline, hippocampal atrophy, and Aβ deposition, by evaluating data from the Australian Imaging, Biomarker and Lifestyle Study of Ageing. METHODS: Two-hundred and eighteen participants underwent Aβ PET, MRI, and cognitive assessment at 18-month intervals for up to 90 months. Aβ status was determined on baseline PET. Participants were also classified as V + on baseline MRI if they had≥1 large cortical infarcts, subcortical infarcts, or cortical cerebral microinfarcts; or white matter hyperintensity volume greater than the 90th percentile of healthy controls. Linear mixed models were conducted comparing slopes of change in cognition, hippocampal volume, and Aβ load between the four resultant groups. RESULTS: Mean age at baseline was 74 years (range 59-96). One-hundred and fifteen participants were cognitively normal, 54 had mild cognitive impairment, and 49 had Alzheimer's disease. Compared to the Aβ-/V- group, the Aβ+/V- and Aβ+/V+groups showed significantly faster cognitive decline and hippocampal atrophy over 90 months. V + status was associated with greater cognitive decline (Cohen's d = 0.85, p < 0.001) and hippocampal atrophy (d = 2.05, p < 0.001) in the Aβ+group but not in the Aβ- group. V + status was not associated with Aβ accumulation in any group. CONCLUSION: Comorbidity of cerebrovascular disease and Aβ was associated with cognitive decline and neurodegeneration. Cerebrovascular disease was not associated with the rate of Aβ accumulation.

Metabolic Profiles Help Discriminate Mild Cognitive Impairment from Dementia Stage in Alzheimer's Disease. - Jääskeläinen, Olli; Hall, Anette; Tiainen, Mika; van Gils, Mark; Lötjönen, Jyrki; Kangas, Antti J; Helisalmi, Seppo; Pikkarainen, Maria; Hallikainen, Merja; Koivisto, Anne; Hartikainen, Päivi; Hiltunen, Mikko; et al. (J Alzheimers Dis, 2020)
Accurate differentiation between neurodegenerative diseases is developing quickly and has reached an effective level in disease recognition. However, there has been less focus on effectively distinguishing the prodromal state from later dementia stages due to a lack of suitable biomarkers. We utilized the Disease State Index (DSI) machine learning classifier to see how well quantified metabolomics data compares to clinically used cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD). The metabolic profiles were quantified for 498 serum and CSF samples using proton nuclear magnetic resonance spectroscopy. The patient cohorts in this study were dementia (with a clinical AD diagnosis) (N = 359), mild cognitive impairment (MCI) (N = 96), and control patients with subjective memory complaints (N = 43). DSI classification was conducted for MCI (N = 51) and dementia (N = 214) patients with low CSF amyloid-β levels indicating AD pathology and controls without such amyloid pathology (N = 36). We saw that the conventional CSF markers of AD were better at classifying controls from both dementia and MCI patients. However, quantified metabolic subclasses were more effective in classifying MCI from dementia. Our results show the consistent effectiveness of traditional CSF biomarkers in AD diagnostics. However, these markers are relatively ineffective in differentiating between MCI and the dementia stage, where the quantified metabolomics data provided significant benefit.

Multi-Target Effects of the Cannabinoid CP55940 on Familial Alzheimer's Disease PSEN1 E280A Cholinergic-Like Neurons: Role of CB1 Receptor. - Soto-Mercado, Viviana; Mendivil-Perez, Miguel; Jimenez-Del-Rio, Marlene; Velez-Pardo, Carlos (J Alzheimers Dis, 2020)
BACKGROUND: Alzheimer's disease (AD) is characterized by structural damage, death, and functional disruption of cholinergic neurons (ChNs) as a result of intracellular amyloid-β (Aβ) aggregation, extracellular neuritic plaques, and hyperphosphorylation of protein tau (p-Tau) overtime. OBJECTIVE: To evaluate the effect of the synthetic cannabinoid CP55940 (CP) on PSEN1 E280A cholinergic-like nerve cells (PSEN1 ChLNs)-a natural model of familial AD. METHODS: Wild type (WT) and PSEN1 ChLNs were exposed to CP (1μM) only or in the presence of the CB1 and CB2 receptors (CB1Rs, CB2Rs) inverse agonist SR141716 (1μM) and SR144528 (1μM) respectively, for 24 h. Untreated or treated neurons were assessed for biochemical and functional analysis. RESULTS: CP in the presence of both inverse agonists (hereafter SR) almost completely inhibits the aggregation of intracellular sAβPPβf and p-Tau, increases ΔΨm, decreases oxidation of DJ-1Cys106-SH residue, and blocks the activation of c-Jun, p53, PUMA, and caspase-3 independently of CB1Rs signaling in mutant ChLNs. CP also inhibits the generation of reactive oxygen species partially dependent on CB1Rs. Although CP reduced extracellular Aβ 42, it was unable to reverse the Ca2 + influx dysregulation as a response to acetylcholine stimuli in mutant ChLNs. Exposure to anti-Aβ antibody 6E10 (1:300) in the absence or presence of SR plus CP completely recovered transient [Ca2 +]i signal as a response to acetylcholine in mutant ChLNs. CONCLUSION: Taken together our findings suggest that the combination of cannabinoids, CB1Rs inverse agonists, and anti-Aβ antibodies might be a promising therapeutic approach for the treatment of familial AD.

Neuropathologic Correlates of White Matter Hyperintensities in a Community-Based Cohort of Older Adults. - Arfanakis, Konstantinos; Evia, Arnold M; Leurgans, Sue E; Cardoso, Luis F C; Kulkarni, Arman; Alqam, Nabil; Lopes, Lucas F; Vieira, Diego; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2020)
BACKGROUND: The association of white matter hyperintensities (WMH) with age-related vascular and neurodegenerative pathologies remains incompletely understood. OBJECTIVE: The objective of this work was to elucidate the neuropathologic correlates of WMH in a large community-based cohort of older adults. METHODS: Cerebral hemispheres from 603 community-based older adults were imaged with MRI ex vivo. All participants underwent annual clinical evaluation, cognitive assessment, and neuropathologic examination. WMH burden was assessed using a modified Fazekas rating scale. Multiple ordinal logistic regression was used to test the association of WMH burden with an array of age-related neuropathologies, adjusting for demographics. Mixed effects models of cognition controlling for neuropathologies and demographics were used to determine whether WMH burden contributes to cognitive decline beyond measured pathologies. RESULTS: WMH burden in the whole group was associated with both vascular and Alzheimer's disease (AD) pathologies: arteriolosclerosis (p < 10-4), gross (p < 10-4), and microscopic infarcts (p = 0.04), and amyloid-β plaques (p = 0.028). In non-demented participants (mild or no cognitive impairment) (N = 332), WMH burden was related to gross infarcts (p = 10-4) and arteriolosclerosis (p < 10-4), but not to AD pathology. Similarly, in those with no cognitive impairment (N = 178), WMH burden was related to gross infarcts (p = 8×10-4) and arteriolosclerosis (p = 0.014). WMH burden was associated with faster decline in perceptual speed in both the whole (p = 0.038) and non-demented (p = 0.006) groups. CONCLUSION: WMH burden has independent associations with vascular pathologies in older adults regardless of clinical status, and with AD pathology later in the progression of AD. Moreover, WMH burden may reflect additional tissue injury not captured with traditional neuropathologic indices.

Non-Coding RNAs Based Molecular Links in Type 2 Diabetes, Ischemic Stroke, and Vascular Dementia. - Vijayan, Murali; Reddy, P Hemachandra (J Alzheimers Dis, 2020)
This article reviews recent advances in the study of microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and their functions in type 2 diabetes mellitus (T2DM), ischemic stroke (IS), and vascular dementia (VaD). miRNAs and lncRNAs are gene regulation markers that both regulate translational aspects of a wide range of proteins and biological processes in healthy and disease states. Recent studies from our laboratory and others have revealed that miRNAs and lncRNAs expressed differently are potential therapeutic targets for neurological diseases, especially T2DM, IS, VaD, and Alzheimer's disease (AD). Currently, the effect of aging in T2DM, IS, and VaD and the cellular and molecular pathways are largely unknown. In this article, we highlight results from the works on the molecular connections between T2DM and IS, and IS and VaD. In each disease, we also summarize the pathophysiology and the differential expressions of miRNAs and lncRNAs. Based on current research findings, we hypothesize that 1) T2DM bi-directionally and age-dependently induces IS and VaD, and 2) these changes are precursors to the onset of dementia in elderly people. Research into these hypotheses is required to examine further whether research efforts on reducing T2DM, IS, and VaD may affect dementia and/or delay the AD disease process in the aged population.

Plasma High Density Lipoprotein Small Subclass is Reduced in Alzheimer's Disease Patients and Correlates with Cognitive Performance. - Pedrini, Steve; Hone, Eugene; Gupta, Veer B; James, Ian; Teimouri, Elham; Bush, Ashley I; Rowe, Christopher C; Villemagne, Victor L; Ames, David; Masters, Colin L; Rainey-Smith, Stephanie; Verdile, Giuseppe; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The link between cholesterol and Alzheimer's disease (AD) has received much attention, as evidence suggests high levels of cholesterol might be an AD risk factor. The carriage of cholesterol and lipids through the body is mediated via lipoproteins, some of which, particularly apolipoprotein E (ApoE), are intimately linked with AD. In humans, high density lipoprotein (HDL) is regarded as a "good" lipid complex due to its ability to enable clearance of excess cholesterol via 'cholesterol reverse transport', although its activities in the pathogenesis of AD are poorly understood. There are several subclasses of HDL; these range from the newly formed small HDL, to much larger HDL. OBJECTIVE: We examined the major subclasses of HDL in healthy controls, mild cognitively impaired, and AD patients who were not taking statins to determine whether there were HDL profile differences between the groups, and whether HDL subclass levels correlated with plasma amyloid-β (Aβ) levels or brain Aβ deposition. METHODS: Samples from AIBL cohort were used in this study. HDL subclass levels were assessed by Lipoprint while Aβ1-42 levels were assessed by ELISA. Brain Aβ deposition was assessed by PET scan. Statistical analysis was performed using parametric and non-parametric tests. RESULTS: We found that small HDL subclass is reduced in AD patients and it correlates with cognitive performance while plasma Aβ concentrations do not correlate with lipid profile or HDL subfraction levels. CONCLUSION: Our data indicate that AD patients exhibit altered plasma HDL profile and that HDL subclasses correlate with cognitive performances.

Potential of FTIR Spectroscopy Applied to Exosomes for Alzheimer's Disease Discrimination: A Pilot Study. - Martins, Tânia Soares; Magalhães, Sandra; Rosa, Ilka Martins; Vogelgsang, Jonathan; Wiltfang, Jens; Delgadillo, Ivonne; Catita, José; da Cruz E Silva, Odete A B; Nunes, Alexandra; Henriques, Ana Gabriela (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) diagnosis is based on psychological and imaging tests but can also include monitoring cerebrospinal fluid (CSF) biomarkers. However, CSF based-neurochemical approaches are expensive and invasive, limiting their use to well-equipped settings. In contrast, blood-based biomarkers are minimally invasive, cost-effective, and a widely accessible alternative. Blood-derived exosomes have recently emerged as a reliable AD biomarker source, carrying disease-specific cargo. Fourier-transformed infrared (FTIR) spectroscopy meets the criteria for an ideal diagnostic methodology since it is rapid, easy to implement, and has high reproducibility. This metabolome-based technique is useful for diagnosing a broad range of diseases, although to our knowledge, no reports for FTIR spectroscopy applied to exosomes in AD exist. In this ground-breaking pilot study, FTIR spectra of serum and serum-derived exosomes from two independent cohorts were acquired and analyzed using multivariate analysis. The regional UA-cohort includes 9 individuals, clinically diagnosed with AD, mean age of 78.7 years old; and the UMG-cohort comprises 12 individuals, clinically diagnosed with AD (based on molecular and/or imaging data), mean age of 73.2 years old. Unsupervised principal component analysis of FTIR spectra of serum-derived exosomes revealed higher discriminatory value for AD cases when compared to serum as a whole. Consistently, the partial least-squares analysis revealed that serum-derived exosomes present higher correlations than serum. In addition, the second derivative peak area calculation also revealed significant differences among Controls and AD cases. The results obtained suggest that this methodology can discriminate cases from Controls and thus be potential useful to assist in AD clinical diagnosis.

Revised Framingham Stroke Risk Profile: Association with Cognitive Status and MRI-Derived Volumetric Measures. - Pelcher, Isabelle; Puzo, Christian; Tripodis, Yorghos; Aparicio, Hugo J; Steinberg, Eric G; Phelps, Alyssa; Martin, Brett; Palmisano, Joseph N; Vassey, Elizabeth; Lindbergh, Cutter; McKee, Ann C; Stein, Thor D; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The Framingham Stroke Risk Profile (FSRP) was created in 1991 to estimate 10-year risk of stroke. It was revised in 2017 (rFSRP) to reflect the modern data on vascular risk factors and stroke risk. OBJECTIVE: This study examined the association between the rFSRP and cognitive and brain aging outcomes among participants from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS). METHODS: Cross-sectional rFSRP was computed at baseline for 19,309 participants (mean age = 72.84, SD = 8.48) from the NACC-UDS [9,697 (50.2%) normal cognition, 4,705 (24.4%) MCI, 4,907 (25.4%) dementia]. Multivariable linear, logistic, or ordinal regressions examined the association between the rFSRP and diagnostic status, neuropsychological test performance, CDR® Sum of Boxes, as well as total brain volume (TBV), hippocampal volume (HCV), and log-transformed white matter hyperintensities (WMH) for an MRI subset (n = 1,196). Models controlled for age, sex, education, racial identity, APOEɛ4 status, and estimated intracranial volume for MRI models. RESULTS: The mean rFSRP probability was 10.42% (min = 0.50%, max = 95.71%). Higher rFSRP scores corresponded to greater CDR Sum of Boxes (β= 0.02, p = 0.028) and worse performance on: Trail Making Test A (β= 0.05, p <  0.001) and B (β= 0.057, p <  0.001), and Digit Symbol (β= -0.058, p <  0.001). Higher rFSRP scores were associated with increased odds for a greater volume of log-transformed WMH (OR = 1.02 per quartile, p = 0.015). No associations were observed for diagnosis, episodic memory or language test scores, HCV, or TBV. CONCLUSION: These results support the rFSRP as a useful metric to facilitate clinical research on the associations between cerebrovascular disease and cognitive and brain aging.

Structural Brain Magnetic Resonance Imaging to Rule Out Comorbid Pathology in the Assessment of Alzheimer's Disease Dementia: Findings from the Ontario Neurodegenerative Disease Research Initiative (ONDRI) Study and Clinical Trials Over the Past 10 Years. - Kapoor, Arunima; Bartha, Robert; Black, Sandra E; Borrie, Michael; Freedman, Morris; Gao, Fuqiang; Herrmann, Nathan; Mandzia, Jennifer; Ozzoude, Miracle; Ramirez, Joel; Scott, Christopher J M; Symons, Sean; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Structural brain magnetic resonance imaging (MRI) is not mandatory in Alzheimer's disease (AD) research or clinical guidelines. We aimed to explore the use of structural brain MRI in AD/mild cognitive impairment (MCI) trials over the past 10 years and determine the frequency with which inclusion of standardized structural MRI acquisitions detects comorbid vascular and non-vascular pathologies. METHODS: We systematically searched ClinicalTrials.gov for AD clinical trials to determine their neuroimaging criteria and then used data from an AD/MCI cohort who underwent standardized MRI protocols, to determine type and incidence of clinically relevant comorbid pathologies. RESULTS: Of 210 AD clinical trials, 105 (50%) included structural brain imaging in their eligibility criteria. Only 58 (27.6%) required MRI. 16,479 of 53,755 (30.7%) AD participants were in trials requiring MRI. In the observational AD/MCI cohort, 141 patients met clinical criteria; 22 (15.6%) had relevant MRI findings, of which 15 (10.6%) were exclusionary for the study. DISCUSSION: In AD clinical trials over the last 10 years, over two-thirds of participants could have been enrolled without brain MRI and half without even a brain CT. In a study sample, relevant comorbid pathology was found in 15% of participants, despite careful screening. Standardized structural MRI should be incorporated into NIA-AA diagnostic guidelines (when available) and research frameworks routinely to reduce diagnostic heterogeneity.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Alzheimer's and Parkinson's Diseases and the Risk of Cancer: A Cohort Study. - Ording, Anne G; Veres, Katalin; Horváth-Puhó, Erzsébet; Glymour, M Maria; Rørth, Mikael; Henderson, Victor W; Sørensen, Henrik T (J Alzheimers Dis, 2019)
Observational studies have shown inverse associations between neurological diseases, particularly dementia, and subsequent cancer risk, but is unknown whether this association is valid or arises from bias. We conducted a Danish nationwide cohort study using population-based health registries (1980-2012). The study included patients with dementia (n = 173,434) and with Parkinson's disease (n = 28,835). We followed patients for 10 years to assess subsequent cancer diagnoses. We computed absolute reduction in cancer risk attributable to dementia or Parkinson's disease (expected minus the observed number of cancer cases divided by the person time) and standardized incidence rate ratios (SIRs) as the observed to expected number of cancers, based on sex-, age-, and calendar year-standardized national incidence rates. During 10 years, the reduction in cancer cases were 79.9 per 10,000 person-years for Alzheimer's disease [SIR = 0.68 (95% CI: 0.66, 0.70)], 74.4 per 10,000 person-years for vascular dementia [SIR = 0.71 (95% CI: 0.67, 0.74)], 55.8 per 10,000 person-years [SIR = 0.77 (95% CI: 0.75, 0.78)] for all-cause dementia, and 4.0 per 10,000 person-years [SIR = 0.98 (95% CI: 0.95, 1.02) for Parkinson's disease. Associations were nearly similar for solid tumors diagnosed at localized, regional, or distant stages. We found an inverse association between dementia and cancer risk, with similar associations when considering only cancers diagnosed at distant stage. The cancer risk varied by type of dementia, with a gradient toward a stronger protective effect associated with Alzheimer's disease and vascular dementia, which may favor a biological explanation. Overall results do not show an inverse association between Parkinson's disease and cancer.

Amyloidogenic Nanoplaques in Blood Serum of Patients with Alzheimer's Disease Revealed by Time-Resolved Thioflavin T Fluorescence Intensity Fluctuation Analysis. - Tiiman, Ann; Jelic, Vesna; Jarvet, Jüri; Järemo, Petter; Bogdanovic, Nenad; Rigler, Rudolf; Terenius, Lars; Gräslund, Astrid; Vukojević, Vladana (J Alzheimers Dis, 2019)
BACKGROUND: Biomarkers are central to current research on molecular mechanisms underlying Alzheimer's disease (AD). Their further development is of paramount importance for understanding pathophysiological processes that eventually lead to disease onset. Biomarkers are also crucial for early disease detection, before clinical manifestation, and for development of new disease modifying therapies. OBJECTIVE: The overall aim of this work is to develop a minimally invasive method for fast, ultra-sensitive and cost-effective detection of structurally modified peptide/protein self-assemblies in the peripheral blood and in other biological fluids. Specifically, we focus here on using this method to detect structured amyloidogenic oligomeric aggregates in the blood serum of apparently healthy individuals and patients in early AD stage, and measure their concentration and size. METHODS: Time-resolved detection of Thioflavin T (ThT) fluorescence intensity fluctuations in a sub-femtoliter observation volume element was used to identify in blood serum ThT-active structured amyloidogenic oligomeric aggregates, hereafter called nanoplaques, and measure with single-particle sensitivity their concentration and size. RESULTS: The concentration and size of structured amyloidogenic nanoplaques are significantly higher in the blood serum of individuals diagnosed with AD than in control subjects. CONCLUSION: A new method with the ultimate, single-particle sensitivity was successfully developed. The proposed approach neither relies on the use of immune-based probes, nor on the use of radiotracers, signal-amplification or protein separation techniques, and provides a minimally invasive test for fast and cost-effective early determination of structurally modified peptides/proteins in the peripheral blood, as shown here, but also in other biological fluids.

APOE ɛ4 Carriers Show Delayed Recovery of Verbal Memory and Smaller Entorhinal Volume in the First Year After Ischemic Stroke. - Werden, Emilio; Khlif, Mohamed Salah; Bird, Laura J; Cumming, Toby; Bradshaw, Jennifer; Khan, Wasim; Pase, Matthew; Restrepo, Carolina; Veldsman, Michele; Egorova, Natalia; Patel, Sheila K; Gottlieb, Elie; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The apolipoprotein E (APOE) gene ɛ4 allele is a risk factor for Alzheimer's disease and cardiovascular disease. However, its relationship with cognition and brain volume after stroke is not clear. OBJECTIVE: We compared cognition and medial temporal lobe volumes in APOEɛ4 carriers and non-carriers in the first year after ischemic stroke. METHODS: We sampled 20 APOEɛ4 carriers and 20 non-carriers from a larger cohort of 135 ischemic stroke participants in the longitudinal CANVAS study. Participants were matched on a range of demographic and stroke characteristics. We used linear mixed-effect models to compare cognitive domain z-scores (attention, processing speed, executive function, verbal and visual memory, language, visuospatial function) and regional medial temporal lobe volumes (hippocampal, entorhinal cortex) between groups at each time-point (three, 12-months post-stroke), and within groups across time-points. APOE gene single nucleotide polymorphisms (SNPs; rs7412, rs429358) were genotyped on venous blood. RESULTS: APOEɛ4 carriers and non-carriers did not differ on any demographic, clinical, or stroke variable. Carriers performed worse than non-carriers in verbal memory at three months post-stroke (p = 0.046), but were better in executive function at 12 months (p = 0.035). Carriers demonstrated a significant improvement in verbal memory (p = 0.012) and executive function (p = 0.015) between time-points. Non-carriers demonstrated a significant improvement in visual memory (p = 0.0005). Carriers had smaller bilateral entorhinal cortex volumes (p <  0.05), and larger-right-sided and contralesional hippocampal volumes, at both time-points (p <  0.05). CONCLUSION: APOE ɛ4 is associated with delayed recovery of verbal memory function and reduced entorhinal cortex volumes in the first year after ischemic stroke.

Choroid Plexus Acts as Gatekeeper for TREM2, Abnormal Accumulation of ApoE, and Fibrillary Tau in Alzheimer's Disease and in Down Syndrome Dementia. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Vuono, Romina; Bickerton, Anastasia; Jones, Elizabeth; Fincham, Robert; Allinson, Kieren; Holland, Anthony; Zaman, Shahid H (J Alzheimers Dis, 2019)
BACKGROUND: Genetic factors that influence Alzheimer's disease (AD) risk include mutations in TREM2 and allelic variants of Apolipoprotein E, influencing AD pathology in the general population and in Down syndrome (DS). Evidence shows that dysfunction of the choroid plexus may compromise the blood-cerebrospinal fluid (CSF) barrier, altering secretary, transport and immune function that can affect AD pathology. OBJECTIVE: To investigate the genotype and phenotype of DS individuals in relation to choroid plexus damage and blood-CSF barrier leakage to identify markers that could facilitate early diagnosis of AD in DS. METHODS: To assess allele frequency and haplotype associations ApoE, Tau, TREM2, and HLA-DR were analyzed by SNP analysis in DS participants (n = 47) and controls (n = 50). The corresponding plasma protein levels were measured by ELISA. Postmortem brains from DS, AD, and age-matched controls were analyzed by immunohistochemistry. RESULTS: Haplotype analysis showed that individuals with Tau H1/H1 and ApoEɛ4 genotypes were more prevalent among DS participants with an earlier diagnosis of dementia (17%) compared to H1/H2 haplotypes (6%). Plasma TREM2 levels decreased whereas phospho-tau levels increased with age in DS. In AD and DS brain, insoluble tau and ApoE were found to accumulate in the choroid plexus. CONCLUSION: Accumulation of tau and ApoE in the choroid plexus may increase the oligomerization rate of Aβ42 and impair tau trafficking, leading to AD pathology. We have identified a high-risk haplotype: ApoEɛ4, Tau/H1, and TREM2/T, that manifests age-related changes potentially opening a window for treatment many years prior to the manifestation of the AD dementia.

The Clinical Phenotype of Vascular Cognitive Impairment in Patients with Type 2 Diabetes Mellitus. - Groeneveld, Onno N; Moneti, Costanza; Heinen, Rutger; de Bresser, Jeroen; Kuijf, Hugo J; Exalto, Lieza G; Boomsma, Jooske M F; Kappelle, L Jaap; Barkhof, Frederik; Prins, Niels D; Scheltens, Philip; van der Flier, Wiesje M; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes mellitus (T2DM) increases the risk of vascular cognitive impairment (VCI). It is unknown which type of vascular lesions and co-morbid etiologies, in particular Alzheimer's disease pathology, are associated with T2DM in patients with VCI, and how this relates to cognition and prognosis. OBJECTIVE: To compare brain MRI and cerebrospinal fluid (CSF) markers, cognition, and prognosis in patients with possible VCI with and without T2DM. METHODS: We included 851 memory clinic patients with vascular brain injury on MRI (i.e., possible VCI) from a prospective cohort study (T2DM: n = 147, 68.4±7.9 years, 63% men; no T2DM: n = 704, 67.6±8.5 years, 52% men). At baseline, we assessed between-group differences in brain MRI abnormalities, CSF markers of Alzheimer's disease, and cognitive profile. After two years follow-up, we compared occurrence of cognitive decline, stroke, and death. RESULTS: The distribution of clinical diagnoses did not differ between patients with and without T2DM. T2DM patients had more pronounced brain atrophy (total and white matter volume), and more lacunar infarcts, whereas microbleeds were less common (all p <  0.05). CSF amyloid-β levels were similar between the groups. T2DM patients performed worse on working memory (effect size: - 0.17, p = 0.03) than those without, whereas performance on other domains was similar. During follow-up, risk of further cognitive decline was not increased in T2DM.∥Conclusion: In patients with possible VCI, presence of T2DM is related to more pronounced brain atrophy and a higher burden of lacunar infarcts, but T2DM does not have a major impact on cognitive profile or prognosis.∥.

A Comparison of Partial Volume Correction Techniques for Measuring Change in Serial Amyloid PET SUVR. - Schwarz, Christopher G; Gunter, Jeffrey L; Lowe, Val J; Weigand, Stephen; Vemuri, Prashanthi; Senjem, Matthew L; Petersen, Ronald C; Knopman, David S; Jack, Clifford R (J Alzheimers Dis, 2019)
Longitudinal PET studies in aging and Alzheimer's disease populations rely on accurate and precise measurements of change over time from serial PET scans. Various methods for partial volume correction (PVC) are commonly applied to such studies, but existing comparisons and validations of these PVC methods have focused on cross-sectional measurements. Rate of change measurements inherently have smaller magnitudes than cross-sectional measurements, so levels of noise amplification due to PVC must be smaller, and it is necessary to re-evaluate methods in this context. Here we compare the relative precision in longitudinal measurements from serial amyloid PET scans when using geometric transfer matrix (GTM) PVC versus the traditional two-compartment (Meltzer-style), three-compartment (Müller-Gärtner-style), and no-PVC approaches. We used two independent implementations of standardized uptake value ratio (SUVR) measurement and PVC (one in-house pipeline based on SPM12 and ANTs, and one using FreeSurfer 6.0). For each approach, we also tested longitudinal-specific variants. Overall, we found that measurements using GTM PVC had significantly worse relative precision (unexplained within-subject variability ≈4-8%) than those using two-compartment, three-compartment, or no PVC (≈2-4%). Longitudinally-stabilized approaches did not improve these properties. This data suggests that GTM PVC methods may be less suitable than traditional approaches when measuring within-person change over time in longitudinal amyloid PET.

Education Moderates the Relation Between APOE ɛ4 and Memory in Nondemented Non-Hispanic Black Older Adults. - Vonk, Jet M J; Rentería, Miguel Arce; Medina, Valerie M; Pericak-Vance, Margaret A; Byrd, Goldie S; Haines, Jonathan; Brickman, Adam M; Manly, Jennifer J (J Alzheimers Dis, 2019)
BACKGROUND: The APOEɛ4 allele is a well-known risk factor for Alzheimer's disease (AD). Previous research argues that higher education helps to preserve cognition in older adults with AD pathology because of its key role in cognitive reserve and resilience. OBJECTIVE: To test if higher educational level buffers the effect of APOEɛ4 on cognition among older non-Hispanic Blacks. METHODS: Participants were 849 non-demented older non-Hispanic Blacks (38.3% APOEɛ4+), who underwent a comprehensive neuropsychological evaluation. Multiple linear regression models tested the relationship between APOEɛ4 status and twelve cognitive measures with education (up to high school and beyond high school) as a moderator. RESULTS: Education buffered the effects of the APOEɛ4 allele, such that there was no impact of APOEɛ4 status on word-list memory retention and working memory among participants with more than a high school degree. This pattern was not observed for ten other cognitive measures of verbal and visual episodic memory, semantic memory, executive function, and processing speed-although a similar trend was observed for switching ability in executive functioning. The buffering effect of education was stronger among women than men. CONCLUSION: Our findings suggest that genetic effects on late-life cognition may be modified by environmental factors such as educational attainment. These results are consistent with the framework of cognitive reserve such that engaging in cognitively enriching activities and acquiring skills and knowledge with more years of education may increase the capacity to maintain cognitive function despite high genetic risk for impairment.

Evaluation of Associations of Alzheimer's Disease Risk Variants that Are Highly Expressed in Microglia with Neuropathological Outcome Measures. - Sakae, Nobutaka; Heckman, Michael G; Vargas, Emily R; Carrasquillo, Minerva M; Murray, Melissa E; Kasanuki, Koji; Ertekin-Taner, Nilufer; Younkin, Steven G; Dickson, Dennis W (J Alzheimers Dis, 2019)
A number of Alzheimer's disease (AD) susceptibility loci are expressed abundantly in microglia. We examined associations between AD risk variants in genes that are highly expressed in microglia and neuropathological outcomes, including cerebral amyloid angiopathy (CAA) and microglial activation, in 93 AD patients. We observed significant associations of CAA pathology with APOEɛ4 and PTK2B rs28834970. Nominally significant associations with measures of microglial activation in white matter were observed for variants in PTK2B, PICALM, and CR1. Our findings suggest that several AD risk variants may also function as disease modifiers through amyloid-β metabolism and white matter microglial activity.

Gender and Educational Differences in the Association between Lifestyle and Cognitive Decline over 10 Years: The Doetinchem Cohort Study. - Deckers, Kay; Nooyens, Astrid; van Boxtel, Martin; Verhey, Frans; Verschuren, Monique; Köhler, Sebastian (J Alzheimers Dis, 2019)
BACKGROUND: Several modifiable risk factors for cognitive decline have been identified, but whether differences by gender and educational level exist is unclear. OBJECTIVE: The present study aims to clarify this by prospectively investigating the relationship between health and lifestyle factors and cognitive functioning in different subgroups defined by gender and educational level. METHODS: 2,347 cognitive healthy individuals (mean age = 54.8, SD = 6.8, range: 41-71; 51.8% female; 26.2% low education) from the Doetinchem Cohort Study were examined for cognitive function at baseline, and at 5- and 10-year follow-up. Health- and lifestyle factors were captured by a poly-environmental risk score labelled 'LIfestyle for BRAin Health' (LIBRA). This score consists of 12 modifiable risk and protective factors for cognitive decline and dementia, with higher scores indicating greater risk (range: -2.7 to +12.7). Heterogeneity in associations between LIBRA and decline in verbal memory, cognitive flexibility, and mental speed between males and females and individuals with different levels of education were assessed in linear mixed models. RESULTS: Overall, higher LIBRA scores predicted faster decline in verbal memory, cognitive flexibility, and mental speed over 10 years. Higher LIBRA scores were further associated with increased risk for incident cognitive impairment (one-point increase in LIBRA: HR = 1.09, 1.04-1.14, p = 0.001). In general, these effects were similar across gender and educational level. CONCLUSION: A composite risk score comprising unhealthy lifestyle and relatively poor health in midlife is significantly associated with a worse course of cognition 10 years later. These associations were for the most part unrelated to gender or educational differences.

Glial Fibrillary Acidic Protein in Serum is Increased in Alzheimer's Disease and Correlates with Cognitive Impairment. - Oeckl, Patrick; Halbgebauer, Steffen; Anderl-Straub, Sarah; Steinacker, Petra; Huss, André M; Neugebauer, Hermann; von Arnim, Christine A F; Diehl-Schmid, Janine; Grimmer, Timo; Kornhuber, Johannes; Lewczuk, Piotr; Danek, Adrian; et al. (J Alzheimers Dis, 2019)
Reliable blood biomarkers for Alzheimer's disease (AD) are missing. We measured astroglial GFAP in patients with AD (n = 28), frontotemporal dementia (bvFTD, n = 35), Parkinson's disease (n = 11), Lewy body dementias (n = 19), and controls (n = 34). Serum GFAP was increased in AD (p < 0.001) and DLB/PDD (p < 0.01), and cerebrospinal fluid GFAP was increased in all neurodegenerative diseases (p < 0.001). Serum GFAP correlated with the Mini-Mental State Examination score (r= -0.42, p < 0.001) and might be a follow-up marker in clinical trials. Sensitivity and specificity of serum GFAP for AD versus bvFTD was 89% and 79% and might be the first blood biomarker in the differential diagnosis of AD and bvFTD.

Inferring the Molecular Mechanisms of Noncoding Alzheimer's Disease-Associated Genetic Variants. - Amlie-Wolf, Alexandre; Tang, Mitchell; Way, Jessica; Dombroski, Beth; Jiang, Ming; Vrettos, Nicholas; Chou, Yi-Fan; Zhao, Yi; Kuzma, Amanda; Mlynarski, Elisabeth E; Leung, Yuk Yee; Brown, Christopher D; et al. (J Alzheimers Dis, 2019)
Most of the loci identified by genome-wide association studies (GWAS) for late-onset Alzheimer's disease (LOAD) are in strong linkage disequilibrium (LD) with nearby variants all of which could be the actual functional variants, often in non-protein-coding regions and implicating underlying gene regulatory mechanisms. We set out to characterize the causal variants, regulatory mechanisms, tissue contexts, and target genes underlying these associations. We applied our INFERNO algorithm to the top 19 non-APOE loci from the IGAP GWAS study. INFERNO annotated all LD-expanded variants at each locus with tissue-specific regulatory activity. Bayesian co-localization analysis of summary statistics and eQTL data was performed to identify tissue-specific target genes. INFERNO identified enhancer dysregulation in all 19 tag regions analyzed, significant enrichments of enhancer overlaps in the immune-related blood category, and co-localized eQTL signals overlapping enhancers from the matching tissue class in ten regions (ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, EPHA1, FERMT2, ZCWPW1). In several cases, we identified dysregulation of long noncoding RNA (lncRNA) transcripts and applied the lncRNA target identification algorithm from INFERNO to characterize their downstream biological effects. We also validated the allele-specific effects of several variants on enhancer function using luciferase expression assays. By integrating functional genomics with GWAS signals, our analysis yielded insights into the regulatory mechanisms, tissue contexts, genes, and biological processes affected by noncoding genetic variation associated with LOAD risk.

Long-Term Trazodone Use and Cognition: A Potential Therapeutic Role for Slow-Wave Sleep Enhancers. - La, Alice L; Walsh, Christine M; Neylan, Thomas C; Vossel, Keith A; Yaffe, Kristine; Krystal, Andrew D; Miller, Bruce L; Karageorgiou, Elissaios (J Alzheimers Dis, 2019)
BACKGROUND: Recent studies reveal an association between slow-wave sleep (SWS), amyloid-β aggregation, and cognition. OBJECTIVE: This retrospective study examines whether long-term use of trazodone, an SWS enhancer, is associated with delayed cognitive decline. METHODS: We identified 25 regular trazodone users (mean age 75.4±7.5; 9 women, 16 men) who carried a diagnosis of Alzheimer's dementia, mild cognitive impairment, or normal cognition, and 25 propensity-matched trazodone non-users (mean age 74.5±8.0; 13 women, 12 men), accounting for age, sex, education, type of sleep deficit (hypersomnia, insomnia, parasomnia), diagnosis, and baseline Mini-Mental State Examination (MMSE). Longitudinal group differences in cognitive testing were evaluated through repeated measures tests over an average inter-evaluation interval of four years. RESULTS: Trazodone non-users had 2.6-fold faster decline MMSE (primary outcome) compared to trazodone users, 0.27 (95% confidence interval [CI]: 0.07-0.48) versus 0.70 (95% CI: 0.50-0.90) points per year (p = 0.023). The observed effects were especially associated with subjective improvement of sleep complaints in post-hoc analyses (p = 0.0006). Secondary outcomes of other cognitive and functional scores had variable worsening in non-users and varied in significance when accounting for co-administered medications and multiple comparisons. Trazodone effects on MMSE remained significant within participants with AD-predicted pathology, with 2.4-fold faster decline in non-users (p = 0.038). CONCLUSIONS: These results suggest an association between trazodone use and delayed cognitive decline, adding support for a potentially attractive and cost-effective intervention in dementia. Whether the observed relationship of trazodone to cognitive function is causal or an indirect marker of other effects, such as treated sleep disruption, and if such effects are mediated through SWS enhancement requires confirmation through prospective studies.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

The MemTrax Test Compared to the Montreal Cognitive Assessment Estimation of Mild Cognitive Impairment. - van der Hoek, Marjanne D; Nieuwenhuizen, Arie; Keijer, Jaap; Ashford, J Wesson (J Alzheimers Dis, 2019)
Cognitive impairment is a leading cause of dysfunction in the elderly. When mild cognitive impairment (MCI) occurs in elderly, it is frequently a prodromal condition to dementia. The Montreal Cognitive Assessment (MoCA) is a commonly used tool to screen for MCI. However, this test requires a face-to-face administration and is composed of an assortment of questions whose responses are added together by the rater to provide a score whose precise meaning has been controversial. This study was designed to evaluate the performance of a computerized memory test (MemTrax), which is an adaptation of a continuous recognition task, with respect to the MoCA. Two outcome measures are generated from the MemTrax test: MemTraxspeed and MemTraxcorrect. Subjects were administered the MoCA and the MemTrax test. Based on the results of the MoCA, subjects were divided in two groups of cognitive status: normal cognition (n = 45) and MCI (n = 37). Mean MemTrax scores were significantly lower in the MCI than in the normal cognition group. All MemTrax outcome variables were positively associated with the MoCA. Two methods, computing the average MTX score and linear regression were used to estimate the cutoff values of the MemTrax test to detect MCI. These methods showed that for the outcome MemTraxspeed a score below the range of 0.87 - 91 s-1 is an indication of MCI, and for the outcome MemTraxcorrect a score below the range of 85 - 90% is an indication for MCI.

Midlife Insulin Resistance as a Predictor for Late-Life Cognitive Function and Cerebrovascular Lesions. - Toppala, Sini; Ekblad, Laura L; Lötjönen, Jyrki; Helin, Semi; Hurme, Saija; Johansson, Jarkko; Jula, Antti; Karrasch, Mira; Koikkalainen, Juha; Laine, Hanna; Parkkola, Riitta; Viitanen, Matti; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes (T2DM) increases the risk for Alzheimer's disease (AD) but not for AD neuropathology. The association between T2DM and AD is assumed to be mediated through vascular mechanisms. However, insulin resistance (IR), the hallmark of T2DM, has been shown to associate with AD neuropathology and cognitive decline. OBJECTIVE: To evaluate if midlife IR predicts late-life cognitive performance and cerebrovascular lesions (white matter hyperintensities and total vascular burden), and whether cerebrovascular lesions and brain amyloid load are associated with cognitive functioning. METHODS: This exposure-to-control follow-up study examined 60 volunteers without dementia (mean age 70.9 years) with neurocognitive testing, brain 3T-MRI and amyloid-PET imaging. The volunteers were recruited from the Finnish Health 2000 survey (n = 6062) to attend follow-up examinations in 2014-2016 according to their insulin sensitivity in 2000 and their APOE genotype. The exposure group (n = 30) had IR in 2000 and the 30 controls had normal insulin sensitivity. There were 15 APOEɛ4 carriers per group. Statistical analyses were performed with multivariable linear models. RESULTS: At follow-up the IR+group performed worse on executive functions (p = 0.02) and processing speed (p = 0.007) than the IR- group. The groups did not differ in cerebrovascular lesions. No associations were found between cerebrovascular lesions and neurocognitive test scores. Brain amyloid deposition associated with slower processing speed. CONCLUSION: Midlife IR predicted poorer executive functions and slower processing speed, but not cerebrovascular lesions. Brain amyloid deposition was associated with slower processing speed. The association between midlife IR and late-life cognition might not be mediated through cerebrovascular lesions measured here.

Mild Cognitive Impairment and Dementia Involving Multiple Cognitive Domains in Mexican Urbanites. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Kulesza, Randy J; Torres-Jardón, Ricardo; Hernández-Luna, Jacqueline; Ávila-Cervantes, Rodrigo; Macías-Escobedo, Edgar; González-González, Oscar; González-Maciel, Angelica; García-Hernández, Kevin; Hernández-Castillo, Ariatna; Villarreal-Ríos, Rodolfo (J Alzheimers Dis, 2019)
Exposures to fine particulate matter PM2.5 and ozone O3 are associated with Alzheimer's disease (AD) risk. Mexico City residents have lifetime exposures to PM2.5 and O3 above annual USEPA standards and their brains contain high redox, combustion, and friction-derived magnetite nanoparticles. AD pathological changes with subcortical pre-tangle stages in infancy and cortical tau pre-tangles, NFT Stages I-II, and amyloid phases 1-2 are identified by the 2nd decade. Given their AD continuum, a reliable identification of cognitive impairment is of utmost importance. The Montreal Cognitive Assessment (MoCA) was administered to 517 urbanites, age 21.60±5.88 years, with 13.69±1.28 formal education years, in Mexican PM2.5 polluted cities. MoCA score was 23.92±2.82, and 24.7% and 30.3% scored ≤24 and ≤22, respectively (MCI≤24, AD≤22). Cognitive deficits progressively targeted Visuospatial, Executive, Language, and Memory domains, body mass index (BMI) impacting total scores negatively (p = 0.0008), aging driving down Executive, Visuospatial, and Language index scores (p <  0.0001, 0.0037, and 0.0045), and males performing better in Executive tasks. Average age for AD MoCA scores was 22.38±7.7 years. Residency in polluted cities is associated with progression of multi-domain cognitive impairment affecting 55% of Mexican seemingly healthy youth. Normal BMI ought to be a neuroprotection goal. MoCA provides guidance for further mandatory neuropsychological testing in young populations. Identifying and lowering key neurotoxicants impacting neural risk trajectories in the developing brain and monitoring cognitive performance would greatly facilitate multidisciplinary early diagnosis and prevention of AD in high risk young populations. Cognitive deficits hinder development of those representing the force moving the country in future years.

Preliminary Report on the Feasibility and Efficacy of the Modified Atkins Diet for Treatment of Mild Cognitive Impairment and Early Alzheimer's Disease. - Brandt, Jason; Buchholz, Alison; Henry-Barron, Bobbie; Vizthum, Diane; Avramopoulos, Dimitrios; Cervenka, Mackenzie C (J Alzheimers Dis, 2019)
Ketone bodies, the products of fat metabolism, are a source of energy for the brain and are available even when glucose supplies are inadequate (such as with severe carbohydrate deprivation) or its metabolism is faulty (as it is in Alzheimer's disease). This phase I/II randomized clinical trial examined the feasibility of using a modified Atkins diet (MAD) to induce ketogenesis in persons with mild cognitive impairment (MCI) or early AD, and the effect of this diet on memory and other clinical outcomes. In the first 2.5 years of active recruitment, only 27 eligible and willing patients enrolled. After extensive assessment and education, they and their study partners were randomly assigned for 12 weeks to either the MAD or the National Institute on Aging (NIA) recommended diet for seniors. As of April 2018, 9 patients in the MAD arm and 5 in the NIA arm have completed the trial. In spite of extensive teaching, coaching, and monitoring, adherence to both diets was only fair. Among those in the MAD arm who generated at least trace amounts of urinary ketones, there was a large (effect size = 0.53) and statistically significant (p = 0.03) increase in Memory Composite Score between the baseline and week-6 assessment. MAD participants also reported increased energy between baseline and week-6 assessment. Despite challenges to implementing this trial, resulting in a small sample, our preliminary data suggest that the generation of even trace ketones might enhance episodic memory and patient-reported vitality in very early AD.

Risk Factors for and Clinical Relevance of Incident and Progression of Cerebral Small Vessel Disease Markers in an Asian Memory Clinic Population. - Gyanwali, Bibek; Shaik, Muhammad Amin; Tan, Boon Yeow; Venketasubramanian, Narayanaswamy; Chen, Christopher; Hilal, Saima (J Alzheimers Dis, 2019)
BACKGROUND: Cerebral small vessel disease (SVD) is one of the major contributors to cognitive impairment and dementia. However, data on the incidence and progression of SVD in an Asian population are lacking. OBJECTIVE: The present study aims to investigate the incidence, progression, associated risk factors, and clinical relevance of SVD in a memory clinic setting. METHODS: A prospective case-control study, where 346 patients underwent repeated brain MRI with a mean interval of 24.5 months, accessing white matter hyperintensities (WMH), lacunes and cerebral microbleeds (CMBs). Severity of cognitive impairment was assessed using Clinical Dementia Rating scale and change in clinical diagnosis. Data on demographics, vascular risk factors, and clinical history were collected at baseline. RESULTS: The prevalence of significant WMH (Fazekas ≥2) was 56.6% at baseline which progressed to 59.0% at follow-up. Overall prevalence of CMBs increased from 42.2% to 47.4% (9% new cases) and lacunes increased from 31.8% to 33.2% (2.1% new cases). Hypertension was associated with WMH progression (OR: 1.78, 95% CI: 1.01, 2.99) and increasing age was associated with incident CMBs (OR: 1.04, 95% CI: 1.01, 1.08). Moreover, the use of lipid-lowering medications decreased the incidence of lacunes (OR: 0.15, 95% CI: 0.04, 0.61). The major risk factor for incident SVD was baseline SVD lesion load. WMH progression was associated with increased severity of cognitive impairment (OR: 1.95, 95% CI: 1.16, 3.23). CONCLUSION: Vascular risk factors and baseline severity of SVD lesion load were associated with progression of SVD. Furthermore, WMH progression was linked with increased severity of cognitive impairment. Future studies should be aimed to slow cognitive deterioration by preventing SVD related brain damage by targeting vascular risk factors.

Self and Informant Memory Reports in FINGER: Associations with Two-Year Cognitive Change. - Vaskivuo, Laura; Hokkanen, Laura; Hänninen, Tuomo; Antikainen, Riitta; Bäckman, Lars; Laatikainen, Tiina; Paajanen, Teemu; Stigsdotter-Neely, Anna; Strandberg, Timo; Tuomilehto, Jaakko; Soininen, Hilkka; Kivipelto, Miia; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Subjective memory complaints (SMCs) may be the first sign of cognitive decline in aging. OBJECTIVE: To examine whether SMCs reported by oneself and informant predict cognitive change over 2 years among at-risk elderly people, and to determine the relationship of different types of SMCs (prospective and retrospective memory complaints) and change in cognitive function. METHODS: This investigation is part of the FINGER project, which is a multicenter randomized controlled trial aiming at preventing cognitive decline in cognitively healthy older adults with increased risk of dementia. A subsample of 303 control-group participants (aged 60-80 years) and their informants (n = 261) rated the frequency of SMCs, using the Prospective and Retrospective Memory Questionnaire (PRMQ). Cognitive performance was measured at baseline and at 1- and 2-year follow-up visits using a neuropsychological test battery. RESULTS: Participants who reported more SMCs improved less in global cognition, executive function, and memory during the subsequent 2 years in the fully-adjusted analyses. Self-reported retrospective memory problems predicted less improvement in all cognitive domains, whereas prospective memory problems did not. Informant-reported memory problems were not linked to subsequent change in cognition. CONCLUSION: Our results indicate that self-reported SMCs, measured with PRMQ, predict future cognitive change in several cognitive domains. By contrast, reports by informants were not linked to changes in cognition. Among cognitively healthy at-risk elderly individuals, the persons themselves observe more easily problems relevant for their future cognitive trajectories than their informants.

Small Molecule Amyloid-β Protein Precursor Processing Modulators Lower Amyloid-β Peptide Levels via cKit Signaling. - Chen, Ci-Di; Zeldich, Ella; Khodr, Christina; Camara, Kaddy; Tung, Tze Yu; Lauder, Emma C; Mullen, Patrick; Polanco, Taryn J; Liu, Yen-Yu; Zeldich, Dean; Xia, Weiming; Van Nostrand, William E; et al. (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is characterized by the accumulation of neurotoxic amyloid-β (Aβ) peptides consisting of 39-43 amino acids, proteolytically derived fragments of the amyloid-β protein precursor (AβPP), and the accumulation of the hyperphosphorylated microtubule-associated protein tau. Inhibiting Aβ production may reduce neurodegeneration and cognitive dysfunction associated with AD. We have previously used an AβPP-firefly luciferase enzyme complementation assay to conduct a high throughput screen of a compound library for inhibitors of AβPP dimerization, and identified a compound that reduces Aβ levels. In the present study, we have identified an analog, compound Y10, which also reduced Aβ. Initial kinase profiling assays identified the receptor tyrosine kinase cKit as a putative Y10 target. To elucidate the precise mechanism involved, AβPP phosphorylation was examined by IP-western blotting. We found that Y10 inhibits cKit phosphorylation and increases AβPP phosphorylation mainly on tyrosine residue Y743, according to AβPP751 numbering. A known cKit inhibitor and siRNA specific to cKit were also found to increase AβPP phosphorylation and lower Aβ levels. We also investigated a cKit downstream signaling molecule, the Shp2 phosphatase, and found that known Shp2 inhibitors and siRNA specific to Shp2 also increase AβPP phosphorylation, suggesting that the cKit signaling pathway is also involved in AβPP phosphorylation and Aβ production. We further found that inhibitors of both cKit and Shp2 enhance AβPP surface localization. Thus, regulation of AβPP phosphorylation by small molecules should be considered as a novel therapeutic intervention for AD.

Subjective Cognitive Decline May Be a Stronger Predictor of Incident Dementia in Women than in Men. - Heser, Kathrin; Kleineidam, Luca; Wiese, Birgitt; Oey, Anke; Roehr, Susanne; Pabst, Alexander; Kaduszkiewicz, Hanna; van den Bussche, Hendrik; Brettschneider, Christian; König, Hans-Helmut; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: Subjective cognitive decline (SCD) has often been associated with an increased risk for subsequent dementia. However, sex-specific associations are understudied until now. METHODS: Cross-sectional and longitudinal associations over a follow-up period of up to 13 years were investigated in a sample of participants without objective cognitive impairment at baseline (n = 2,422, mean age = 79.63 years). Logistic regression and Cox proportional hazards models were conducted. RESULTS: Women less frequently reported SCD without worries (p <  0.001), but tended to report more often SCD with worries (p = 0.082) at baseline compared to men. In models adjusted for age, education, cognitive status, and depressive symptoms, SCD at baseline increased the risk for subsequent dementia (p <  0.001), and this effect was less pronounced in males (interaction sex×SCD: p = 0.022). Stratified analyses showed that SCD increased the risk for subsequent dementia in women (HR = 1.77, p <  0.001), but not in men (HR = 1.07, p = 0.682). Similar results were found in analyses with SCD without and with worries, except that SCD with worries also predicted subsequent Alzheimer's disease (AD) in men (p = 0.037). CONCLUSION: At baseline, men reported more SCD without worries and women tended to report more SCD with worries. SCD in women was more strongly associated with subsequent dementia. SCD without and with worries was related to incident dementia and AD in women, whereas in men only SCD with worries increased the risk for AD, but not for all-cause dementia.

Telomere Length and the Risk of Alzheimer's Disease: The Rotterdam Study. - Fani, Lana; Hilal, Saima; Sedaghat, Sanaz; Broer, Linda; Licher, Silvan; Arp, Pascal P; van Meurs, Joyce B J; Ikram, M Kamran; Ikram, M Arfan (J Alzheimers Dis, 2019)
There is a wide interest in biomarkers that capture the burden of detrimental factors as these accumulate with the passage of time, i.e., increasing age. Telomere length has received considerable attention as such a marker, because it is easily quantified and it may aid in disentangling the etiology of dementia or serve as predictive marker. We determined the association of telomere length with risk of Alzheimer's disease and all-cause dementia in a population-based setting. Within the Rotterdam Study, we performed quantitative PCR to measure mean leukocyte telomere length in blood. We determined the association of telomere length with risk of Alzheimer's disease until 2016, using Cox regression models. Of 1,961 participants (mean age 71.4±9.3 years, 57.1% women) with a median follow-up of 8.3 years, 237 individuals were diagnosed with Alzheimer's disease. We found a U-shaped association between telomere length and risk of Alzheimer's disease: compared to the middle tertile the adjusted hazard ratio was 1.59 (95% confidence interval (CI), 1.13-2.23) for the lowest tertile and 1.47 (1.03-2.10) for the highest tertile. Results were similarly U-shaped but slightly attenuated for all-cause dementia. In conclusion, shorter and longer telomere length are both associated with an increased risk of Alzheimer's disease in the general population.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

Ultrasensitive Detection of Plasma Amyloid-β as a Biomarker for Cognitively Normal Elderly Individuals at Risk of Alzheimer's Disease. - Chatterjee, Pratishtha; Elmi, Mitra; Goozee, Kathryn; Shah, Tejal; Sohrabi, Hamid R; Dias, Cintia B; Pedrini, Steve; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Taddei, Kevin; Vanderstichele, Hugo; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Aberrant amyloid-β (Aβ) deposition in the brain occurs two decades prior to the manifestation of Alzheimer's disease (AD) clinical symptoms and therefore brain Aβ load measured using PET serves as a gold standard biomarker for the early diagnosis of AD. However, the uneconomical nature of PET makes blood markers, that reflect brain Aβ deposition, attractive candidates for investigation as surrogate markers. OBJECTIVE: Investigation of plasma Aβ as a surrogate marker for brain Aβ deposition in cognitively normal elderly individuals. METHODS: Plasma Aβ40 and Aβ42 concentrations were measured using the ultrasensitive Single Molecule Array (Simoa) assay in 95 cognitively normal elderly individuals, who have all undergone PET to assess brain Aβ deposition. Based on the standard uptake value ratios (SUVR) obtained from PET imaging, using the tracer 18F-Florbetaben, plasma Aβ was compared between 32 participants assessed to have low brain Aβ load (Aβ-, SUVR <1.35) and 63 assessed to have high brain Aβ load (Aβ+, SUVR ≥1.35). RESULTS: Plasma Aβ42/Aβ40 ratios were lower in the Aβ+ group compared to the Aβ-group. Plasma Aβ40 and Aβ42 levels were not significantly different between Aβ-and Aβ+ groups, although a trend of higher plasma Aβ40 was observed in the Aβ+ group. Additionally, plasma Aβ42/Aβ40 ratios along with the known AD risk factors, age and APOEɛ4 status, resulted in Aβ+ participants being distinguished from Aβ-participants based on an area under the receiver operating characteristic curve shown to be 78%. CONCLUSION: Plasma Aβ ratios in this study are a potential biomarker for brain Aβ deposition and therefore, for preclinical AD. However, this method to measure plasma Aβ needs further development to increase the accuracy of this promising AD blood biomarker.

Vascular Burden Score Impacts Cognition Independent of Amyloid PET and MRI Measures of Alzheimer's Disease and Vascular Brain Injury. - DeCarli, Charles; Villeneuve, Sylvia; Maillard, Pauline; Harvey, Danielle; Singh, Baljeet; Carmichael, Owen; Fletcher, Evan; Olichney, John; Farias, Sarah; Jagust, William; Reed, Bruce; Mungas, Dan (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: To determine the impact of vascular burden on rates of decline in episodic memory and executive function. We hypothesize that greater vascular burden will have an additive negative impact on cognition after accounting for baseline cognitive impairment, positron emission tomography (PET) amyloid burden, and magnetic resonance imaging (MRI) measures. METHODS: Individuals were followed an average of 5 years with serial cognitive assessments. Predictor variables include vascular burden score (VBS), quantitative brain MRI assessment, and amyloid imaging. Subjects consisted of 65 individuals, 53% of whom were male, aged 73.2±7.2 years on average with an average of 15.5±3.3 years of educational achievement. RESULTS: Baseline cognitive impairment was significantly associated poorer episodic memory (p < 0.0001), smaller hippocampal volume (p < 0.0001), smaller brain volume (p = 0.0026), and greater global Pittsburg Imaging Compound B (PiB) index (p = 0.0008). Greater amyloid burden was associated with greater decline in episodic memory over time (β= -0.20±0.07, p < 0.005). VBS was significantly associated with the level of executive function performance (β= -0.14±0.05, p < 0.005) and there was a significant negative interaction between VBS, cognitive impairment, and PiB index (β= -0.065±0.03, p = 0.03). CONCLUSIONS: Our results find a significant influence of VBS independent of standard MRI measures and cerebral amyloid burden on executive function. In addition, VBS reduced the amount of cerebral amyloid burden needed to result in cognitive impairment. We conclude that the systemic effects of vascular disease as reflected by the VBS independently influence cognitive ability.

Why Is Amyloid-β PET Requested After Performing Cerebrospinal Fluid Biomarkers? - Reimand, Juhan; Groot, Colin; Teunissen, Charlotte E; Windhorst, Albert D; Boellaard, Ronald; Barkhof, Frederik; Nazarenko, Sergei; van der Flier, Wiesje M; van Berckel, Bart N M; Scheltens, Philip; Ossenkoppele, Rik; Bouwman, Femke (J Alzheimers Dis, 2019)
BACKGROUND: Amyloid-β PET and cerebrospinal fluid (CSF) Aβ42 are considered interchangeable for clinical diagnosis of Alzheimer's disease. OBJECTIVE: To explore the clinical reasoning for requesting additional amyloid-β PET after performing CSF biomarkers. METHODS: We retrospectively identified 72 memory clinic patients who underwent amyloid-β PET after CSF biomarkers analysis for clinical diagnostic evaluation between 2011 and 2019. We performed patient chart reviews to identify factors which led to additional amyloid-β PET. Additionally, we assessed accordance with appropriate-use-criteria (AUC) for amyloid-β PET. RESULTS: Mean patient age was 62.0 (SD = 8.1) and mean Mini-Mental State Exam score was 23.6 (SD = 3.8). CSF analysis conflicting with the clinical diagnosis was the most frequent reason for requesting an amyloid-β PET scan (n = 53, 74%), followed by incongruent MRI (n = 16, 22%), unusual clinical presentation (n = 11, 15%) and young age (n = 8, 11%). An amyloid-β PET scan was rarely (n = 5, 7%) requested in patients with a CSF Aβ+/tau+ status. Fifteen (47%) patients with a post-PET diagnosis of AD had a predominantly non-amnestic presentation. In n = 11 (15%) cases, the reason that the clinician requested amyloid-β was not covered by AUC. This happened most often (n = 7) when previous CSF analysis did not support current clinical diagnosis, which led to requesting amyloid-β PET. CONCLUSION: In this single-center study, the main reason for requesting an amyloid-β PET scan after performing CSF biomarkers was the occurrence of a mismatch between the primary clinical diagnosis and CSF Aβ/tau results.

Abnormalities of Resting State Cortical EEG Rhythms in Subjects with Mild Cognitive Impairment Due to Alzheimer's and Lewy Body Diseases. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Catania, Valentina; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2018)
The present study tested the hypothesis that cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and dementia with Lewy bodies (DLBMCI) as compared to cognitively normal elderly (Nold) subjects. Clinical and rsEEG data in 30 ADMCI, 23 DLBMCI, and 30 Nold subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) score was matched between the ADMCI and DLBMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROCC) classified these sources across individuals. Compared to Nold, IAF showed marked slowing in DLBMCI and moderate in ADMCI. Furthermore, the posterior alpha 2 and alpha 3 source activities were more abnormal in the ADMCI than the DLBMCI group, while widespread delta source activities were more abnormal in the DLBMCI than the ADMCI group. The posterior delta and alpha sources correlated with the MMSE score and correctly classified the Nold and MCI individuals (area under the ROCC >0.85). In conclusion, the ADMCI and DLBMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test the clinical validity of these rsEEG markers.

Accuracy of Inferred APOE Genotypes for a Range of Genotyping Arrays and Imputation Reference Panels. - Lupton, Michelle K; Medland, Sarah E; Gordon, Scott D; Goncalves, Tabatha; MacGregor, Stuart; Mackey, David A; Young, Terri L; Duffy, David L; Visscher, Peter M; Wray, Naomi R; Nyholt, Dale R; Bain, Lisa; et al. (J Alzheimers Dis, 2018)
Cohort studies investigating aging and dementia require APOE genotyping. We compared directly measured APOE genotypes to 'hard-call' genotypes derived from imputing genome-wide genotyping data from a range of platforms using several imputation panels. Older GWAS arrays imputed to 1000 Genomes Project (1KGP) phases and the Haplotype Reference Consortium (HRC) reference panels were able to achieve concordance rates of over 98% with stringent quality control (hard-call-threshold 0.8). However, this resulted in high levels of missingness (>12% with 1KGP and 5% with HRC). With recent GWAS arrays, concordance of 99% could be obtained with relatively lenient QC, resulting in no missingness.

Acute Stroke Care in Dementia: A Cohort Study from the Swedish Dementia and Stroke Registries. - Zupanic, Eva; Kåreholt, Ingemar; Norrving, Bo; Secnik, Juraj; von Euler, Mia; Winblad, Bengt; Religa, Dorota; Kramberger, Milica Gregoric; Johnell, Kristina; Eriksdotter, Maria; Garcia-Ptacek, Sara (J Alzheimers Dis, 2018)
BACKGROUND: Previous studies have shown that patients with dementia receive less testing and treatment for stroke. OBJECTIVES: Our aim was to investigate hospital management of acute ischemic stroke in patients with and without dementia. METHODS: Retrospective analysis of prospectively collected data 2010-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who suffered an acute ischemic stroke (AIS) (n = 1,356) were compared with matched non-dementia AIS patients (n = 6,755). Outcomes included length of stay in a stroke unit, total length of hospitalization, and utilization of diagnostic tests and assessments. RESULTS: The median age at stroke onset was 83 years. While patients with dementia were equally likely to be directly admitted to a stroke unit as their non-dementia counterparts, their stroke unit and total hospitalization length were shorter (10.5 versus 11.2 days and 11.6 versus 13.5, respectively, p < 0.001). Dementia patients were less likely to receive carotid ultrasound (OR 0.36, 95% CI [0.30-0.42]) or undergo assessments by the interdisciplinary team members (physiotherapists, speech therapists, occupational therapists; p < 0.05 for all adjusted models). However, a similar proportion of patients received CT imaging (97.4% versus 98.6%, p = 0.001) and a swallowing assessment (90.7% versus 91.8%, p = 0.218). CONCLUSIONS: Patients with dementia who suffer an ischemic stroke have equal access to direct stroke unit care compared to non-dementia patients; however, on average, their stay in a stroke unit and total hospitalization are shorter. Dementia patients are also less likely to receive specific diagnostic tests and assessments by the interdisciplinary stroke team.

Age-Dependent Decrease of Mitochondrial Complex II Activity in a Familial Mouse Model for Alzheimer's Disease. - Emmerzaal, Tim L; Rodenburg, Richard J; Tanila, Heikki; Verweij, Vivienne; Kiliaan, Amanda J; Kozicz, Tamas (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a severe neurodegenerative disorder for which the exact etiology is largely unknown. An increasingly recognized and investigated notion is the pathogenic role of mitochondrial dysfunction in AD. We assessed mitochondrial oxidative-phosphorylation (OXPHOS) enzyme activities in the APPswe/PS1ΔE9 mouse model from 4.5 to 14 months of age. We show an age-dependent decrease in mitochondrial complex-II activity starting at 9 months in APP/PS1 mice. Other enzymes of the OXPHOS do not show any alterations. Since amyloid-β (Aβ) plaques are already present from 4 months of age, mitochondrial dysfunction likely occurs downstream of Aβ pathology in this mouse model.

Albuminuria and Microalbuminuria as Predictors of Cognitive Performance in a General Population: An 11-Year Follow-Up Study. - Ekblad, Laura L; Toppala, Sini; Johansson, Jouni K; Koskinen, Seppo; Sundvall, Jouko; Rinne, Juha O; Puukka, Pauli; Viitanen, Matti; Jula, Antti (J Alzheimers Dis, 2018)
Microalbuminuria, defined as urine albumin-to-creatinine ratio (UACR)>3.0 mg/mmol and ≤ 30 mg/mmol, is an early marker of endothelial damage of the renal glomeruli. Recent research suggests an association among microalbuminuria, albuminuria (UACR > 3.0 mg/mmol), and cognitive impairment. Previous studies on microalbuminuria, albuminuria, and cognition in the middle-aged have not provided repeated cognitive testing at different time-points. We hypothesized that albuminuria (micro- plus macroalbuminuria) and microalbuminuria would predict cognitive decline independently of previously reported risk factors for cognitive decline, including cardiovascular risk factors. In addition, we hypothesized that UACR levels even below the cut-off for microalbuminuria might be associated with cognitive functioning. These hypotheses were tested in the Finnish nationwide, population-based Health 2000 Survey (n = 5,921, mean age 52.6, 55.0% women), and its follow-up, Health 2011 (n = 3,687, mean age at baseline 49.3, 55.6% women). Linear regression analysis was used to determine the associations between measures of albuminuria and cognitive performance. Cognitive functions were assessed with verbal fluency, word-list learning, word-list delayed recall (at baseline and at follow-up), and with simple and visual choice reaction time tests (at baseline only). Here, we show that micro- plus macroalbuminuria associated with poorer word-list learning and a slower reaction time at baseline, with poorer word-list learning at follow-up, and with a steeper decline in word-list learning during 11 years after multivariate adjustments. Also, higher continuous UACR consistently associated with poorer verbal fluency at levels below microalbuminuria. These results suggest that UACR might have value in evaluating the risk for cognitive decline.
Keywords: Adult; Aged; Albuminuria; Cognition; Cognitive Dysfunction; Creatinine; Cross-Sectional Studies; Female; Finland; Follow-Up Studies; Humans; Kidney; Linear Models; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Risk Factors

Alzheimer's Disease: A Journey from Amyloid Peptides and Oxidative Stress, to Biomarker Technologies and Disease Prevention Strategies-Gains from AIBL and DIAN Cohort Studies. - Martins, Ralph N; Villemagne, Victor; Sohrabi, Hamid R; Chatterjee, Pratishtha; Shah, Tejal M; Verdile, Giuseppe; Fraser, Paul; Taddei, Kevin; Gupta, Veer B; Rainey-Smith, Stephanie R; Hone, Eugene; Pedrini, Steve; et al. (J Alzheimers Dis, 2018)
Worldwide there are over 46 million people living with dementia, and this number is expected to double every 20 years reaching about 131 million by 2050. The cost to the community and government health systems, as well as the stress on families and carers is incalculable. Over three decades of research into this disease have been undertaken by several research groups in Australia, including work by our original research group in Western Australia which was involved in the discovery and sequencing of the amyloid-β peptide (also known as Aβ or A4 peptide) extracted from cerebral amyloid plaques. This review discusses the journey from the discovery of the Aβ peptide in Alzheimer's disease (AD) brain to the establishment of pre-clinical AD using PET amyloid tracers, a method now serving as the gold standard for developing peripheral diagnostic approaches in the blood and the eye. The latter developments for early diagnosis have been largely achieved through the establishment of the Australian Imaging Biomarker and Lifestyle research group that has followed 1,100 Australians for 11 years. AIBL has also been instrumental in providing insight into the role of the major genetic risk factor apolipoprotein E ɛ4, as well as better understanding the role of lifestyle factors particularly diet, physical activity and sleep to cognitive decline and the accumulation of cerebral Aβ.

Alzheimer's Disease Biomarkers Have Distinct Associations with Specific Hippocampal Subfield Volumes. - Müller-Ehrenberg, Lisa; Riphagen, Joost M; Verhey, Frans R J; Sack, Alexander T; Jacobs, Heidi I L (J Alzheimers Dis, 2018)
Measures of amyloid-β (Aβ) and phosphorylated tau (p-tau) concentrations in cerebrospinal fluid are extensively used for diagnostic and research purposes in Alzheimer's disease (AD) as correlates of cortical thinning and cognitive outcomes. The present study investigated the relationship of Aβ and p-tau with hippocampal subfield volumes Cornu Ammonis (CA) 1-4, dentate gyrus (DG), and subiculum. Subfields were segmented from T1-weighted images from the ADNI-population using FreeSurfer v6. Linear and polynomial regression models revealed distinct associations of Aβ and p-tau with subfield volumes. Aβ had a quadratic relationship with all hippocampal subfield volumes and the inflection point was higher than the validated cut-off for Aβ. For p-tau the relationships were linear, except for CA3, in which it was quadratic. For the CA1 and CA3, these quadratic relationships with Aβ were only observed when p-tau was low. Amyloid and p-tau contributed equally to the explained variance in CA4 and DG volume. Subicular volume was best explained by Aβ alone. These biomarker relationships with hippocampal subfield volumes seem to mirror the hippocampal-specific topography of Aβ and tau reported in neuropathological staging models. In addition, using continuous values of Aβ reveals positive patterns with imaging markers for individuals around the positivity threshold that would be masked when using dichotomized biomarker groups, which can be important for early detection and accurate inclusion of potential participants at risk for AD in clinical trials.

Alzheimer's Disease: Recent Concepts on the Relation of Mitochondrial Disturbances, Excitotoxicity, Neuroinflammation, and Kynurenines. - Zádori, Dénes; Veres, Gábor; Szalárdy, Levente; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2018)
The pathomechanism of Alzheimer's disease (AD) certainly involves mitochondrial disturbances, glutamate excitotoxicity, and neuroinflammation. The three main aspects of mitochondrial dysfunction in AD, i.e., the defects in dynamics, altered bioenergetics, and the deficient transport, act synergistically. In addition, glutamatergic neurotransmission is affected in several ways. The balance between synaptic and extrasynaptic glutamatergic transmission is shifted toward the extrasynaptic site contributing to glutamate excitotoxicity, a phenomenon augmented by increased glutamate release and decreased glutamate uptake. Neuroinflammation in AD is predominantly linked to central players of the innate immune system, with central nervous system (CNS)-resident microglia, astroglia, and perivascular macrophages having been implicated at the cellular level. Several abnormalities have been described regarding the activation of certain steps of the kynurenine (KYN) pathway of tryptophan metabolism in AD. First of all, the activation of indolamine 2,3-dioxygenase, the first and rate-limiting step of the pathway, is well-demonstrated. 3-Hydroxy-L-KYN and its metabolite, 3-hydroxy-anthranilic acid have pro-oxidant, antioxidant, and potent immunomodulatory features, giving relevance to their alterations in AD. Another metabolite, quinolinic acid, has been demonstrated to be neurotoxic, promoting glutamate excitotoxicity, reactive oxygen species production, lipid peroxidation, and microglial neuroinflammation, and its abundant presence in AD pathologies has been demonstrated. Finally, the neuroprotective metabolite, kynurenic acid, has been associated with antagonistic effects at glutamate receptors, free radical scavenging, and immunomodulation, giving rise to potential therapeutic implications. This review presents the multiple connections of KYN pathway-related alterations to three main domains of AD pathomechanism, such as mitochondrial dysfunction, excitotoxicity, and neuroinflammation, implicating possible therapeutic options.
Keywords: Alzheimer Disease; Animals; Central Nervous System; Disease Models, Animal; Energy Metabolism; Glutamic Acid; Humans; Immunity, Innate; Inflammation; Kynurenine; Mitochondria; Quinolinic Acid; Reactive Oxygen Species; Receptors, Glutamate; Signal Transduction

Amsterdam Dementia Cohort: Performing Research to Optimize Care. - van der Flier, Wiesje M; Scheltens, Philip (J Alzheimers Dis, 2018)
The Alzheimer center of the VU University Medical Center opened in 2000 and was initiated to combine both patient care and research. Together, to date, all patients forming the Amsterdam Dementia Cohort number almost 6,000 individuals. In this cohort profile, we provide an overview of the results produced based on the Amsterdam Dementia Cohort. We describe the main results over the years in each of these research lines: 1) early diagnosis, 2) heterogeneity, and 3) vascular factors. Among the most important research efforts that have also impacted patients' lives and/or the research field, we count the development of novel, easy to use diagnostic measures such as visual rating scales for MRI and the Amsterdam IADL Questionnaire, insight in different subgroups of AD, and findings on incidence and clinical sequelae of microbleeds. Finally, we describe in the outlook how our research endeavors have improved the lives of our patients.

The Amyloid-β Oligomer Hypothesis: Beginning of the Third Decade. - Cline, Erika N; Bicca, Maíra Assunção; Viola, Kirsten L; Klein, William L (J Alzheimers Dis, 2018)
The amyloid-β oligomer (AβO) hypothesis was introduced in 1998. It proposed that the brain damage leading to Alzheimer's disease (AD) was instigated by soluble, ligand-like AβOs. This hypothesis was based on the discovery that fibril-free synthetic preparations of AβOs were potent CNS neurotoxins that rapidly inhibited long-term potentiation and, with time, caused selective nerve cell death (Lambert et al., 1998). The mechanism was attributed to disrupted signaling involving the tyrosine-protein kinase Fyn, mediated by an unknown toxin receptor. Over 4,000 articles concerning AβOs have been published since then, including more than 400 reviews. AβOs have been shown to accumulate in an AD-dependent manner in human and animal model brain tissue and, experimentally, to impair learning and memory and instigate major facets of AD neuropathology, including tau pathology, synapse deterioration and loss, inflammation, and oxidative damage. As reviewed by Hayden and Teplow in 2013, the AβO hypothesis "has all but supplanted the amyloid cascade." Despite the emerging understanding of the role played by AβOs in AD pathogenesis, AβOs have not yet received the clinical attention given to amyloid plaques, which have been at the core of major attempts at therapeutics and diagnostics but are no longer regarded as the most pathogenic form of Aβ. However, if the momentum of AβO research continues, particularly efforts to elucidate key aspects of structure, a clear path to a successful disease modifying therapy can be envisioned. Ensuring that lessons learned from recent, late-stage clinical failures are applied appropriately throughout therapeutic development will further enable the likelihood of a successful therapy in the near-term.

Antibodies to Multiple Receptors are Associated with Neuropsychiatric Symptoms and Mortality in Alzheimer's Disease: A Longitudinal Study. - Giil, Lasse M; Aarsland, Dag; Hellton, Kristoffer; Lund, Anders; Heidecke, Harald; Schulze-Forster, Kai; Riemekasten, Gabriela; Vik-Mo, Audun Osland; Kristoffersen, Einar K; Vedeler, Christian A; Nordrehaug, Jan Erik (J Alzheimers Dis, 2018)
BACKGROUND: Endogenous antibodies to signaling molecules and receptors (Abs) are associated with Alzheimer's disease (AD). OBJECTIVES: To investigate the association of 33 Abs to dopaminergic, serotoninergic, muscarinic, adrenergic, vascular, and immune receptors with cognitive, neuropsychiatric, and mortality outcomes. METHODS: Ninety-one patients with mild AD were followed annually for 5 years with the Mini-Mental State Examination (MMSE) and the Neuropsychiatric Inventory (NPI; composite outcomes: "psychosis" (item 1 + 2), "mood" (item 4 + 5 + 7), and "agitation" (item 3 + 8 + 9)). Abs were quantified in sera obtained at baseline by ELISA and reduced to principal components (PCs). Associations between Abs and outcomes were assessed by a mixed model (MMSE decline), zero-inflated fixed effects count models (composite NPI scores), and Cox regression (mortality). The resulting p-values were adjusted for multiple testing according to a false discovery rate of 0.05 (Benjamini-Hochberg). RESULTS: The measured levels of the 33 Abs formed four PCs. PC1 (dopaminergic and serotonergic Abs) was associated with increased mortality (Hazard ratio 2.57, p < 0.001), PC2 (serotonergic, immune, and vascular Abs) with decreased agitation symptoms (β - 0.19, p < 0.001), and PC3 (cholinergic receptor Abs) with increased mood symptoms (β 0.04, p = 0.002), over time. There were no associations between Abs and MMSE decline. CONCLUSION: The associations between Abs, mortality, and neuropsychiatric symptoms reported in this cohort are intriguing. They cannot, however, be generalized. Validation in independent sample sets is required.

Anti-Tau Monoclonal Antibodies Derived from Soluble and Filamentous Tau Show Diverse Functional Properties in vitro and in vivo. - Vandermeeren, Marc; Borgers, Marianne; Van Kolen, Kristof; Theunis, Clara; Vasconcelos, Bruno; Bottelbergs, Astrid; Wintmolders, Cindy; Daneels, Guy; Willems, Roland; Dockx, Koen; Delbroek, Lore; Marreiro, André; et al. (J Alzheimers Dis, 2018)
The tau spreading hypothesis provides rationale for passive immunization with an anti-tau monoclonal antibody to block seeding by extracellular tau aggregates as a disease-modifying strategy for the treatment of Alzheimer's disease (AD) and potentially other tauopathies. As the biochemical and biophysical properties of the tau species responsible for the spatio-temporal sequences of seeding events are poorly defined, it is not yet clear which epitope is preferred for obtaining optimal therapeutic efficacy. Our internal tau antibody collection has been generated by immunizations with different tau species: aggregated- and non-aggregated tau and human postmortem AD brain-derived tau fibrils. In this communication, we describe and characterize a set of these anti-tau antibodies for their biochemical and biophysical properties, including binding, tissue staining by immunohistochemistry, and epitope. The antibodies bound to different domains of the tau protein and some were demonstrated to be isoform-selective (PT18 and hTau56) or phospho-selective (PT84). Evaluation of the antibodies in cellular- and in vivo seeding assays revealed clear differences in maximal efficacy. Limited proteolysis experiments support the hypothesis that some epitopes are more exposed than others in the tau seeds. Moreover, antibody efficacy seems to depend on the structural properties of fibrils purified from tau Tg mice- and postmortem human AD brain.

Association between Alzheimer's Disease and Oral and Gut Microbiota: Are Pore Forming Proteins the Missing Link? - Aguayo, Sebastian; Schuh, Christina Maria Anna Pia; Vicente, Benjamin; Aguayo, Luis Gerardo (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative condition affecting millions of people worldwide. It is associated with cerebral amyloid-β (Aβ) plaque deposition in the brain, synaptic disconnection, and subsequent progressive neuronal death. Although considerable progress has been made to elucidate the pathogenesis of AD, the specific causes of the disease remain highly unknown. Recent research has suggested a potential association between certain infectious diseases and dementia, either directly due to bacterial brain invasion and toxin production, or indirectly by modulating the immune response. Therefore, in the present review we focus on the emerging issues of bacterial infection and AD, including the existence of antimicrobial peptides having pore-forming properties that act in a similar way to pores formed by Aβ in a variety of cell membranes. Special focus is placed on oral bacteria and biofilms, and on the potential mechanisms associating bacterial infection and toxin production in AD. The role of bacterial outer membrane vesicles on the transport and delivery of toxins as well as porins to the brain is also discussed. Aβ has shown to possess antimicrobial activity against several bacteria, and therefore could be upregulated as a response to bacteria and bacterial toxins in the brain. Although further research is needed, we believe that the control of biofilm-mediated diseases could be an important potential prevention mechanism for AD development.

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

Associations of Angiotensin Converting Enzyme-1 and Angiotensin II Blood Levels and Cognitive Function. - Yasar, Sevil; Varma, Vijay R; Harris, Gregory C; Carlson, Michelle C (J Alzheimers Dis, 2018)
BACKGROUND: Emerging evidence suggests a possible role of the renin angiotensin system in the pathophysiologic process of Alzheimer's disease, of which angiotensin converting enzyme-1 (ACE-1) and angiotensin II (ANGII) are important proteins. Few studies evaluated associations between blood ACE-1 and none between ANGII levels, and cognition. OBJECTIVE: Our pilot study was aimed to examine associations between blood ACE-1 and ANG II levels and cognitive function in non-demented participants at baseline and over a 1-year period. METHODS: 56 participants were included from the Brain Health Substudy of the Baltimore Experience Corps Study. Linear regression analysis, adjusting for confounders, was used to determine associations between baseline ACE-1 and ANGII, and baseline and 1-year follow-up measures of psychomotor and processing speed, executive function, verbal learning memory and working memory, and whether these associations were mediated by blood pressure. RESULTS: Participants were predominantly female (75%), African-American (93%), with mean age of 67.8 years and education of 14.3 years. There were no associations between baseline ACE-1 or ANGII levels and cognitive function; however, there were significant association between baseline ACE-1 levels and 1-year follow-up Trail Making Test, Part A (β= 0.003, p = 0.04) and Digit Span (β= -0.001, p = 0.02). CONCLUSIONS: In this cognitively intact sample, elevated ACE-1 levels were associated with worse processing speed and working memory after 1 year. Findings from this pilot study suggest that changes in the RAS are associated with alterations in cognitive function warranting further assessment of the role of RAS in neurodegenerative disorders.

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) Scale: Comprehensive Assessment of Psychopathology in Down Syndrome. - Dekker, Alain D; Sacco, Silvia; Carfi, Angelo; Benejam, Bessy; Vermeiren, Yannick; Beugelsdijk, Gonny; Schippers, Mieke; Hassefras, Lyanne; Eleveld, José; Grefelman, Sharina; Fopma, Roelie; Bomer-Veenboer, Monique; et al. (J Alzheimers Dis, 2018)
People with Down syndrome (DS) are prone to develop Alzheimer's disease (AD). Behavioral and psychological symptoms of dementia (BPSD) are core features, but have not been comprehensively evaluated in DS. In a European multidisciplinary study, the novel Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) scale was developed to identify frequency and severity of behavioral changes taking account of life-long characteristic behavior. 83 behavioral items in 12 clinically defined sections were evaluated. The central aim was to identify items that change in relation to the dementia status, and thus may differentiate between diagnostic groups. Structured interviews were conducted with informants of persons with DS without dementia (DS, n = 149), with questionable dementia (DS+Q, n = 65), and with diagnosed dementia (DS+AD, n = 67). First exploratory data suggest promising interrater, test-retest, and internal consistency reliability measures. Concerning item relevance, group comparisons revealed pronounced increases in frequency and severity in items of anxiety, sleep disturbances, agitation & stereotypical behavior, aggression, apathy, depressive symptoms, and eating/drinking behavior. The proportion of individuals presenting an increase was highest in DS+AD, intermediate in DS+Q, and lowest in DS. Interestingly, among DS+Q individuals, a substantial proportion already presented increased anxiety, sleep disturbances, apathy, and depressive symptoms, suggesting that these changes occur early in the course of AD. Future efforts should optimize the scale based on current results and clinical experiences, and further study applicability, reliability, and validity. Future application of the scale in daily care may aid caregivers to understand changes, and contribute to timely interventions and adaptation of caregiving.

Behavioral Variant Frontotemporal Dementia Performance on a Range of Saccadic Tasks. - Douglass, Amanda; Walterfang, Mark; Velakoulis, Dennis; Abel, Larry (J Alzheimers Dis, 2018)
BACKGROUND: Saccadic paradigms display changes across a number of degenerative conditions reflecting changes in the oculomotor pathway which in some conditions have been linked to disease presentation. OBJECTIVE: To examine a novel range of saccadic paradigms in behavioral variant frontotemporal dementia (bvFTD). METHODS: Prosaccade, predictive, self-paced, memory-guided, and anti-saccade tasks were examined in bvFTD patients and controls. RESULTS: A significant increase in latency for the bvFTD group was seen in all tasks. Self-paced saccades are reduced in number, memory-guided saccades display an increase in errors. Predictive saccades show an increased latency that does not remain when prosaccade latency changes are accounted for. While changes were seen across a range of paradigms, no individual task completely separated bvFTD from control participants. CONCLUSION: bvFTD patients as a group display a number of changes on saccadic testing which may reflect the frontal lobe changes seen in this condition.

A Blood Test for Alzheimer's Disease: Progress, Challenges, and Recommendations. - Kiddle, Steven J; Voyle, Nicola; Dobson, Richard J B (J Alzheimers Dis, 2018)
Ever since the discovery of APOEɛ4 around 25 years ago, researchers have been excited about the potential of a blood test for Alzheimer's disease (AD). Since then researchers have looked for genetic, protein, metabolite, and/or gene expression markers of AD and related phenotypes. However, no blood test for AD is yet being used in the clinical setting. We first review the trends and challenges in AD blood biomarker research, before giving our personal recommendations to help researchers overcome these challenges. While some degree of consistency and replication has been seen across independent studies, several high-profile studies have seemingly failed to replicate. Partly due to academic incentives, there is a reluctance in the field to report predictive ability, to publish negative findings, and to independently replicate the work of others. If this can be addressed, then we will know sooner whether a blood test for AD or related phenotypes with clinical utility can be developed.

Can 11C-PiB-PET Relative Delivery R1 or 11C-PiB-PET Perfusion Replace 18F-FDG-PET in the Assessment of Brain Neurodegeneration? - Oliveira, Francisco P M; Moreira, Ana Paula; de Mendonça, Alexandre; Verdelho, Ana; Xavier, Carolina; Barroca, Dalila; Rio, Joana; Cardoso, Eva; Cruz, Ângela; Abrunhosa, Antero; Castelo-Branco, Miguel (J Alzheimers Dis, 2018)
BACKGROUND: Pittsburgh Compound B (PiB) positron emission tomography (PET) is used to visualize in vivo amyloid plaques in the brain. Frequently the PiB examinations are complemented with a fluorodeoxyglucose (FDG) PET scan to further assess neurodegeneration. OBJECTIVE: Our goal is to identify alternative correlates of FDG images by assessing which kinetic methods originate PiB derived relative delivery ratio (R1) images that can be correlated with the FDG images, and to compare them with PiB perfusion (pPiB) images obtained from the early-phase of PiB acquisition. METHODS: We selected 52 patients with cognitive impairment who underwent a dynamic PiB and FDG acquisitions. To compute the R1 images, two simplified reference tissue models (SRTM and SRTM2) and two multi-linear reference tissue models (MRTM and MRTM2) were used. The pPiB images were obtained in two different time intervals. RESULTS: All six types of images were of good quality and highly correlated with the FDG images (mean voxelwise within-subjects r > 0.92). The higher correlation was found for FDG-R1(MRTM). Regarding the voxelwise regional correlation, the higher mean all brain correlations was r = 0.825 for FDG-R1(MRTM) and statistically significant in the whole brain analysis. CONCLUSION: All R1 and pPiB images here tested have potential to assess the metabolic impact of neurodegeneration almost as reliably as the FDG images. However, this is not enough to validate these images for a single-subject analysis compared with the FDG image, and thus they cannot yet be used clinically to replace the FDG image before such evaluation.

Cardiorespiratory Fitness and Cognitive Function are Positively Related Among Participants with Mild and Subjective Cognitive Impairment. - Stuckenschneider, Tim; Askew, Christopher David; Rüdiger, Stefanie; Polidori, Maria Cristina; Abeln, Vera; Vogt, Tobias; Krome, Andreas; Olde Rikkert, Marcel; Lawlor, Brian; Schneider, Stefan (J Alzheimers Dis, 2018)
BACKGROUND: By 2030, about 74 million people will be diagnosed with dementia, and many more will experience subjective (SCI) or mild cognitive impairment (MCI). As physical inactivity has been identified to be a strong modifiable risk factor for dementia, exercise and physical activity (PA) may be important parameters to predict the progression from MCI to dementia, but might also represent disease trajectory modifying strategies for SCI and MCI. OBJECTIVE: A better understanding of the relationship between activity, fitness, and cognitive function across the spectrum of MCI and SCI would provide an insight into the potential utility of PA and fitness as early markers, and treatment targets to prevent cognitive decline. METHODS: 121 participants were stratified into three groups, late MCI (LMCI), early MCI (EMCI), and SCI based on the Montreal Cognitive Assessment (MoCA). Cognitive function assessments also included the Trail Making Test A+B, and a verbal fluency test. PA levels were evaluated with an interviewer-administered questionnaire (LAPAQ) and an activity monitor. An incremental exercise test was performed to estimate cardiorespiratory fitness and to determine exercise capacity relative to population normative data. RESULTS: ANCOVA revealed that LMCI subjects had the lowest PA levels (LAPAQ, p = 0.018; activity monitor, p = 0.041), and the lowest exercise capacity in relation to normative values (p = 0.041). Moreover, a modest correlation between MoCA and cardiorespiratory fitness (r = 0.25; p < 0.05) was found. CONCLUSION: These findings suggest that during the earliest stages of cognitive impairment PA and exercise capacity might present a marker for the risk of further cognitive decline. This finding warrants further investigation using longitudinal cohort studies.

Caregiving and Caregiver Burden in Dementia Home Care: Results from the Prospective Dementia Registry (PRODEM) of the Austrian Alzheimer Society. - Ransmayr, Gerhard; Hermann, Philipp; Sallinger, Katharina; Benke, Thomas; Seiler, Stephan; Dal-Bianco, Peter; Marksteiner, Josef; Defrancesco, Michaela; Sanin, Günter; Struhal, Walter; Guger, Michael; Vosko, Milan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Comprehensive studies on caregiver burden (CB) of persons caring for dementia patients differ methodologically and show variable results. OBJECTIVE: Analysis of known and hypothesized factors of CB in home care of dementia patients. METHODS: Multicenter longitudinal study comprising 585 persons caring mostly for Alzheimer's disease patients (age median 77.25 years, Mini-Mental State Examination raw score median 23) using the Zarit Caregiver Burden Interview (CBI). Known patient-related determinants of CB were studied, such as dementia severity (Clinical Dementia Rating, CDR), neuropsychological deficits (CERAD-Plus), neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI), disability (Disability Assessment for Dementia, DAD), dependency (Dependency Scale, DS), and moreover, unclarified potential factors (age, sex, education of patients; age, sex, occupational status of the caregivers; family relationship). Psychological and somatic effects of CB were analyzed (factor analysis). RESULTS: Caregiver age was median 61. Female caregivers prevailed (67.8%). Median CBI sum score (CBIss) was 16 at baseline. After two years, CBIss was 22 and 37% of the caregivers reported mild to moderate (CBIss 21-40), 16.8% moderate to severe or severe (≥41), and 46.2% absent to little CB (CBIss ≤ 20). CB correlated positively with NPI, CDR, DS scores, disability (DAD), years of education of the patients, and proximity of patient and caregiver sex (female), and negatively with caregiver age. Caregivers reported restrictions of time, health problems, and negative emotions. CONCLUSION: The findings are applicable to identify persons at risk for substantial CB and its consequences. There is demand for personal, psychological, and medical support of caregivers and increasing male participation.

Cerebrospinal Fluid Biomarkers are Differentially Related to Structural and Functional Changes in Dementia of the Alzheimer's Type. - Malpas, Charles B; Saling, Michael M; Velakoulis, Dennis; Desmond, Patricia; Hicks, Rodney J; Zetterberg, Henrik; Blennow, Kaj; O'Brien, Terence J (J Alzheimers Dis, 2018)
The two cardinal pathologies of Alzheimer's disease (AD) develop according to distinct anatomical trajectories. Cerebral tau-related pathology first accumulates in the mesial temporal region, while amyloid-related pathology first appears in neocortex. The eventual distributions of these pathologies reflect their anatomical origins. An implication is that the cardinal pathologies might exert preferential effects on the structurofunctional brain changes observed in AD. We investigated this hypothesis in 39 patients with dementia of the Alzheimer's type. Interrelationships were analyzed between cerebrospinal fluid biomarkers of the cardinal pathologies, volumetric brain changes using magnetic resonance imaging, and brain metabolism using [18F]-FDG-PET. Amyloid-related pathology was preferentially associated with structurofunctional changes in the precuneus and lateral temporal regions. Tau-related pathology was not associated with changes in these regions. These findings support the hypothesis that tau- and amyloid-pathology exert differential effects on structurofunctional changes in the AD brain. These findings have implications for future therapeutic trials and hint at a more complex relationship between the cardinal pathologies and disruption of brain networks.

Cerebrovascular Disease and Neurodegeneration in Alzheimer's Disease with and without a Strong Family History: A Pilot Magnetic Resonance Imaging Study in Dominican Republic. - Piriz, Angel; Reyes, Dolly; Narkhede, Atul; Guzman, Vanessa A; Viqar, Fawad; Meier, Irene B; Budge, Mariana; Mena, Pedro; Dashnaw, Stephen; Lee, Joseph; Reitz, Christiane; Gutierrez, Jose; et al. (J Alzheimers Dis, 2018)
The incidence and prevalence of Alzheimer's disease (AD) dementia are higher among Caribbean Hispanics than among non-Hispanic Whites. The causes of this health disparity remain elusive, partially because of the relative limited capacity for biomedical research in the developing countries that comprise Caribbean Latin America. To begin to address this issue, we were awarded a Development Research Award from the US NIH and Fogarty International Center in order to establish the local capacity to integrate magnetic resonance imaging (MRI) into studies of cognitive aging and dementia in Dominican Republic, establish collaborations with Dominican investigators, and conduct a pilot study on the role of cerebrovascular markers in the clinical expression of AD. Ninety older adult participants with and without AD dementia and with and without a strong family history of AD dementia received MRI scans and clinical evaluation. We quantified markers of cerebrovascular disease (white matter hyperintensities [WMH], presence of infarct, and presence of microbleed) and neurodegeneration (entorhinal cortex volume) and compared them across groups. Patients with AD dementia had smaller entorhinal cortex and greater WMH volumes compared with controls, regardless of family history status. This study provides evidence for the capacity to conduct MRI studies of cognitive aging and dementia in Dominican Republic. The results are consistent with the hypothesis that small vessel cerebrovascular disease represents a core feature of AD dementia, as affected participants had elevated WMH volumes irrespective of family history status.

Change in Fitness and the Relation to Change in Cognition and Neuropsychiatric Symptoms After Aerobic Exercise in Patients with Mild Alzheimer's Disease. - Sobol, Nanna A; Dall, Christian Have; Høgh, Peter; Hoffmann, Kristine; Frederiksen, Kristian Steen; Vogel, Asmus; Siersma, Volkert; Waldemar, Gunhild; Hasselbalch, Steen G; Beyer, Nina (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity has the potential to improve physical function in patients with Alzheimer's disease (AD) and may contribute to modify disease processes and cognitive function. OBJECTIVE: The aim of this study was to investigate 1) the effect of moderate-high-intensity aerobic exercise on cardiorespiratory fitness, i.e., peak oxygen uptake (VO2peak) determined by direct breath-by-breath cardiopulmonary exercise test, and 2) the association between changes in VO2peak and changes in cognition and neuropsychiatric symptoms in patients with mild AD. METHODS: The study is based on secondary outcome analyses from the large single-blinded multi-center study ADEX (Preserving Cognition, Quality of Life, Physical Health and Functional Ability in Alzheimer's Disease: The Effect of Physical Exercise). A preselected sub-group of 55 participants (age 52-83 years), 29 from the intervention group (IG) and 26 from the control group (CG), was included. IG performed 16 weeks of supervised moderate-to-high intensity aerobic exercise. Assessments of VO2peak, mental speed and attention (Symbol Digit Modalities Test, SDMT), and neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI) were performed at baseline and at 16 weeks. RESULT: VO2peak increased 13% in the IG and a between-group difference in mean change (3.92 ml/kg/min, 95% CI 6.34-1.51, p = 0.003) was present in favor of the IG. Combined data from IG and CG showed positive associations between changes in VO2peak and changes in NPI (Rho = - 0.41, p = 0.042) and changes in SDMT (Rho = 0.36, p = 0.010), respectively. CONCLUSION: Aerobic exercise improves VO2peak in community-dwelling patients with mild AD. Furthermore, changes in VO2peak appear to be associated to changes in cognition and neuropsychiatric symptoms.

Comparison between FCSRT and LASSI-L to Detect Early Stage Alzheimer's Disease. - Matías-Guiu, Jordi A; Cabrera-Martín, María Nieves; Curiel, Rosie E; Valles-Salgado, María; Rognoni, Teresa; Moreno-Ramos, Teresa; Carreras, José Luis; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2018)
BACKGROUND: The Free and Cued Selective Reminding Test (FCSRT) is the most accurate test for the diagnosis of prodromal Alzheimer's disease (AD). Recently, a novel cognitive test, the Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L), has been developed in order to provide an early diagnosis. OBJECTIVE: To compare the diagnostic accuracy of the FCSRT and the LASSI-L for the diagnosis of AD in its preclinical and prodromal stages using 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) as a reference. METHODS: Fifty patients consulting for subjective memory complaints without functional impairment and at risk for AD were enrolled and evaluated using FCSRT, LASSI-L, and FDG-PET. Participants were evaluated using a comprehensive neurological and neuropsychological protocol and were assessed with the FCSRT and LASSI-L. FDG-PET was acquired concomitantly and used for classification of patients as AD or non-AD according to brain metabolism using both visual and semi-quantitative methods. RESULTS: LASSI-L scores allowed a better classification of patients as AD/non-AD in comparison to FCSRT. Logistic regression analysis showed delayed recall and failure to recovery from proactive semantic interference from LASSI-L as independent statistically significant predictors, obtaining an area under the curve of 0.894. This area under the curve provided a better discrimination than the best FCSRT score (total delayed recall, area under the curve 0.708, p = 0.029). CONCLUSIONS: The LASSI-L, a cognitive stress test, was superior to FCSRT in the prediction of AD features on FDG-PET. This emphasizes the possibility to advance toward an earlier diagnosis of AD from a clinical perspective.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; ROC Curve; Semantics

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

Crosstalk between Peripheral Small Vessel Properties and Anxious-like Profiles: Sex, Genotype, and Interaction Effects in Mice with Normal Aging and 3×Tg-AD mice at Advanced Stages of Disease. - Jiménez-Altayó, Francesc; Sánchez-Ventura, Judith; Vila, Elisabet; Giménez-Llort, Lydia (J Alzheimers Dis, 2018)
Cardiovascular disease resulting from oxidative stress and inflammation can exacerbate Alzheimer's disease. This brief report provides the first evidence of compromised small peripheral mesenteric resistance artery (MRA) properties in 15-month-old 3xTg-AD mice. Females showed worse physiologically relevant MRA structural (increased passive external and internal diameters, cross sectional area) and functional (increased active internal diameters) alterations suggesting sex-dependent dysfunctions. At both physiological and high intraluminal pressures, vascular alterations correlated with the anxious-like behavioral profile, in a sex-dependent manner. Finally, the results unveil a crosstalk between peripheral small vessel properties and behavior in both 3xTg-AD mice and age-matched counterparts with normal aging.

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Diagnostic Value of Diffusion Tensor Imaging and Positron Emission Tomography in Early Stages of Frontotemporal Dementia. - Krämer, Julia; Lueg, Gero; Schiffler, Patrick; Vrachimis, Alexis; Weckesser, Matthias; Wenning, Christian; Pawlowski, Matthias; Johnen, Andreas; Teuber, Anja; Wersching, Heike; Meuth, Sven G; Duning, Thomas (J Alzheimers Dis, 2018)
BACKGROUND: Due to suboptimal sensitivity and specificity of structural and molecular neuroimaging tools, the diagnosis of behavioral variant frontotemporal dementia (bvFTD) remains challenging. OBJECTIVE: Investigation of the sensitivity of diffusion tensor imaging (DTI) and fluorodeoxyglucose positron emission tomography (FDG-PET) to detect cerebral alterations in early stages of bvFTD despite inconspicuous conventional MRI. METHODS: Thirty patients with early stages of bvFTD underwent a detailed neuropsychological examination, cerebral 3T MRI with DTI analysis, and FDG-PET. After 12 months of follow-up, all patients finally fulfilled the diagnosis of bvFTD. Individual FDG-PET data analyses showed that 20 patients exhibited a "typical" pattern for bvFTD with bifrontal and/or temporal hypometabolism (bvFTD/PET+), and that 10 patients showed a "non-typical"/normal pattern (bvFTD/PET-). DTI data were compared with 42 healthy controls in an individual and voxel-based group analysis. To examine the clinical relevance of the findings, associations between pathologically altered voxels of DTI or FDG-PET results and behavioral symptoms were estimated by linear regression analyses. RESULTS: DTI voxel-based group analyses revealed microstructural degeneration in bifrontal and bitemporal areas in bvFTD/PET+ and bvFTD/PET- groups. However, when comparing the sensitivity of individual DTI data analysis with FDG-PET, DTI appeared to be less sensitive. Neuropsychological symptoms were considerably related to neurodegeneration within frontotemporal areas identified by DTI and FDG-PET. CONCLUSION: DTI seems to be an interesting tool for detection of functionally relevant neurodegenerative alterations in early stages of bvFTD, even in bvFTD/PET- patients. However, at a single subject level, it seems to be less sensitive than FDG-PET. Thus, improvement of individual DTI analysis is necessary.

Different Abnormalities of Cortical Neural Synchronization Mechanisms in Patients with Mild Cognitive Impairment due to Alzheimer's and Chronic Kidney Diseases: An EEG Study. - Lizio, Roberta; Babiloni, Claudio; Del Percio, Claudio; Losurdo, Antonia; Vernò, Lucia; De Tommaso, Marina; Montemurno, Anna; Dalfino, Giuseppe; Cirillo, Pietro; Soricelli, Andrea; Ferri, Raffaele; Noce, Giuseppe; et al. (J Alzheimers Dis, 2018)
This study tested whether resting state alpha rhythms (8-13 Hz) may characterize mild cognitive impairment due to Alzheimer's disease (ADMCI) compared with MCI due to chronic kidney disease (CKDMCI). Clinical and resting state eyes-closed electroencephalographic (rsEEG) rhythms from 40 ADMCI, 29 CKDMCI, and 45 cognitively normal elderly (Nold) subjects were available in a national archive. Age, gender, and education were matched in the three groups, and Mini-Mental State Evaluation (MMSE) score was paired in the ADMCI and CKDMCI groups. Delta (<4 Hz), theta (4-8 Hz), alpha 1 (8-10.5 Hz), alpha 2 (10.5-13 Hz), beta 1 (13-20 Hz), beta 2 (20-30 Hz), and gamma (30-40 Hz) cortical sources were estimated by eLORETA freeware and classified across individuals by area under the receiver operating characteristic curve (AUROCC). Compared with Nold group, posterior alpha 1 source activities were more reduced in ADMCI than CKDMCI group. In contrast, widespread delta source activities were greater in CKDMCI than ADMCI group. These source activities correlated with the MMSE score and correctly classified between Nold and all MCI individuals (AUROCC = 0.8-0.85) and between ADMCI and CKDMCI subjects (AUROCC = 0.75). These results suggest that early AD affects cortical neural synchronization at alpha frequencies underpinning brain arousal and low vigilance in the quiet wakefulness. In contrast, CKD may principally affect cortical neural synchronization at the delta frequencies. Future prospective cross-validation studies will have to test these candidate rsEEG markers for clinical applications and drug discovery.

Differential Pattern of Phospholipid Profile in the Temporal Cortex from E280A-Familiar and Sporadic Alzheimer's Disease Brains. - Villamil-Ortiz, Javier Gustavo; Barrera-Ocampo, Alvaro; Arias-Londoño, Julián David; Villegas, Andrés; Lopera, Francisco; Cardona-Gómez, Gloria Patricia (J Alzheimers Dis, 2018)
Lipids are considered important factors in the pathogenesis of Alzheimer's disease (AD). In this study, we realized a comparative analysis of the phospholipid profile and phospholipid composition of the temporal cortex from E280A-familiar AD (FAD), sporadic AD (SAD), and healthy human brains. Findings showed a significant decrease of lysophosphatidylcholine and phosphatidylethanolamine formed by low levels of polyunsaturated fatty acids (20 : 4, 22 : 6) in AD brains. However, phosphatidylethanolamine-ceramide and phosphoglycerol were significantly increased in SAD, conformed by high levels of (18 : 0/18 : 1) and (30/32/36 : 0/1/2), respectively. Together, the findings suggest a deficiency in lysophosphacholine and phosphatidylethanolamine, and alteration in the balance between poly- and unsaturated fatty acids in both types of AD, and a differential pattern of phospholipid profile and fatty acid composition between E280A FAD and SAD human brains.
Keywords: Adult; Aged; Aged, 80 and over; Alanine; Alzheimer Disease; Analysis of Variance; Fatty Acids; Female; Gene Expression Regulation; Glutamic Acid; Humans; Lysophosphatidylcholines; Male; Mass Spectrometry; Middle Aged; Mutation; Phosphatidylethanolamines; Phospholipids; Presenilin-1; Temporal Lobe

Diffuse Amyloid-β Plaques, Neurofibrillary Tangles, and the Impact of APOE in Elderly Persons' Brains Lacking Neuritic Amyloid Plaques. - Abner, Erin L; Neltner, Janna H; Jicha, Gregory A; Patel, Ela; Anderson, Sonya L; Wilcock, Donna M; Van Eldik, Linda J; Nelson, Peter T (J Alzheimers Dis, 2018)
Data from a large autopsy series were analyzed to address questions pertinent to primary age-related tauopathy (PART) and Alzheimer's disease (AD): what factors are associated with increased severity of neurofibrillary degeneration in brains that lack neuritic amyloid plaques?; is there an association between Apolipoprotein E (APOE) alleles and PART pathologic severity independent of amyloid-β (Aβ) deposits?; and, how do the stains used to detect plaques and tangles impact the experimental results? Neuropathologic data were evaluated from elderly research volunteers whose brain autopsies were performed at University of Kentucky Alzheimer's Disease Center (UK-ADC; N = 145 subjects). All of the included subjects' brains lacked neuritic amyloid plaques according to the CERAD diagnostic criteria and the average final MMSE score before death was 26.8±4.6 stdev. The study incorporated evaluation of tissue with both silver histochemical stains and immunohistochemical stains to compare results; the immunohistochemical stains (Aβ and phospho-tau) were scanned and quantified using digital pathologic methods. Immunohistochemical stains provided important advantages over histochemical stains due to sensitivity and detectability via digital methods. When AD-type pathology was in its presumed earliest phases, neocortical parenchymal Aβ deposits were associated with increased medial temporal lobe neurofibrillary tangles. The observation supports the NIA-AA consensus recommendation for neuropathologic diagnoses, because even these "diffuse" Aβ deposits signal that AD pathobiologic mechanisms are occurring. Further, the data were most compatible with the hypothesis that the APOEɛ4 allele exerts its effect(s) via driving Aβ deposition, i.e., an "upstream" influence, rather than being associated directly with Aβ- independent PART pathology.

Disease Course Varies According to Age and Symptom Length in Alzheimer's Disease. - Barnes, Josephine; Bartlett, Jonathan W; Wolk, David A; van der Flier, Wiesje M; Frost, Chris (J Alzheimers Dis, 2018)
Health-care professionals, patients, and families seek as much information as possible about prognosis for patients with Alzheimer's disease (AD); however, we do not yet have a robust understanding of how demographic factors predict prognosis. We evaluated associations between age at presentation, age of onset, and symptom length with cognitive decline as measured using the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating sum-of-boxes (CDR-SOB) in a large dataset of AD patients. Age at presentation was associated with post-presentation decline in MMSE (p < 0.001), with younger patients showing faster decline. There was little evidence of an association with change in CDR-SOB. Symptom length, rather than age, was the strongest predictor of MMSE and CDR-SOB at presentation, with increasing symptom length associated with worse outcomes. The evidence that younger AD patients have a more aggressive disease course implies that early diagnosis is essential.

Distinct Neuroanatomical Correlates of Neuropsychiatric Symptoms in the Three Main Forms of Genetic Frontotemporal Dementia in the GENFI Cohort. - Sellami, Leila; Bocchetta, Martina; Masellis, Mario; Cash, David M; Dick, Katrina M; van Swieten, John; Borroni, Barbara; Galimberti, Daniela; Tartaglia, Maria Carmela; Rowe, James B; Graff, Caroline; Tagliavini, Fabrizio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The overlap between frontotemporal dementia (FTD) and primary psychiatric disorders has been brought to light by reports of prominent neuropsychiatric symptoms (NPS) in FTD-related genetic mutations, particularly among C9orf72 and GRN carriers. It has been recently demonstrated that early neuroanatomical changes in genetic FTD may be different across the major disease-causing mutations. OBJECTIVE: We aimed to identify whether NPS could be driven by distinct structural correlates. METHODS: One hundred and sixty-seven mutation carriers (75 GRN, 60 C9orf72, and 32 MAPT) were included from the Genetic FTD Initiative (GENFI) study, a large international cohort of genetic FTD. Neuropsychiatric symptoms including delusions, hallucinations (visual, auditory, and tactile), depression, and anxiety were investigated using a structured interview. Voxel-based morphometry was performed to identify neuroanatomical correlates of NPS. RESULTS: Psychotic symptoms correlated mainly with grey matter (GM) atrophy in the anterior insula, left thalamus, cerebellum, and cortical regions including frontal, parietal, and occipital lobes in GRN mutations carriers. GM atrophy in posterior structures of the default-mode network was associated with anxiety in the GRN group. Delusions in C9orf72 expansion carriers were mainly associated with left frontal cortical atrophy. Cerebellar atrophy was found to be correlated only with anxiety in C9orf72 carriers. NPS in the MAPT group were mainly associated with volume loss in the temporal lobe. CONCLUSION: Neuroanatomical correlates of NPS appear to be distinct across the main forms of genetic FTD. Overall, our findings support overlapping brain structural changes between FTD and primary psychiatric disorders.

Distribution of Cerebrospinal Fluid Biomarker Profiles in Patients Explored for Cognitive Disorders. - Paquet, Claire; Bouaziz-Amar, Elodie; Cognat, Emmanuel; Volpe-Gillot, Lisette; Haddad, Victor; Mahieux, Florence; Dekimeche, Siham; Defontaines, Benedicte; Chabriat, Hugues; Belin, Catherine; Texeira, Antonio; Goutagny, Stephane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: CSF Alzheimer's disease (AD) biomarkers allow classifying individuals based on their levels of amyloid and neurodegeneration pathologies. OBJECTIVE: To investigate the distribution of AD biomarker profiles from patients suffering from cognitive disorders. METHODS: We analyzed 3001 patients with cognitive disorders and referred by 18 French memory clinics located in and around Paris. Patients were classified as normal, amyloidosis (A+/N-), amyloidosis and neurodegeneration (A+/N+) or suspected non-AD pathophysiology (SNAP), according to their CSF levels of biomarkers. Analysis were performed for the overall population and stratified by gender, age quintiles, and Mini-Mental State Examination (MMSE) score quintiles. Results were compared to previous findings in cohorts of healthy elderly adults. RESULTS: 37% of the sample were classified as A+/N+, 22% were classified A+/N-, and 15% as SNAP. The A+/N+ profile was associated with female gender, advanced age, and lower MMSE score, while the A+/N-profile was observed more frequently in men and the distribution was stable across age and MMSE. The SNAP profile showed no association with gender or age, was less frequent in patients with lower MMSE, and had a lower repartition than the one previously reported in asymptomatic populations. CONCLUSIONS: While A+/N+ patients had the clinical characteristics typically observed in AD, A+/N-patients had a different epidemiological pattern (higher frequency in men, no association with advanced age or lower MMSE). The SNAP profile was less frequent than previously reported in the general elderly population, suggesting that this profile is not a frequent cause of memory impairment in this population.

Does Fatty Acid Composition in Subcutaneous Adipose Tissue Differ between Patients with Alzheimer's Disease and Cohabiting Proxies? - Faxen-Irving, Gerd; Falahati, Farshad; Basun, Hans; Eriksdotter, Maria; Vedin, Inger; Wahlund, Lars-Olof; Schultzberg, Marianne; Hjorth, Erik; Palmblad, Jan; Cederholm, Tommy; Freund-Levi, Yvonne (J Alzheimers Dis, 2018)
Low tissue levels of the major marine ω3 fatty acids (FAs) DHA and EPA are found in Alzheimer's disease (AD). We investigated if healthy proxies to AD patients have higher levels of these ω3 FAs. We observed lower levels of EPA and DHA in subcutaneous adipose tissue biopsies from 64 AD patients compared with 16 cognitively healthy proxies. No significant difference was observed when pairwise comparisons were made between a subset of 16 AD patients and their co-habiting proxies. Larger studies are needed to replicate these findings and to determine if they could depend on FA intake or differences in metabolism.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Dietary Supplements; Fatty Acids, Omega-3; Female; Humans; Male; Regression Analysis; Subcutaneous Fat

Dual Time-Point [18F]Florbetaben PET Delivers Dual Biomarker Information in Mild Cognitive Impairment and Alzheimer's Disease. - Florek, Lisa; Tiepolt, Solveig; Schroeter, Matthias L; Berrouschot, Jörg; Saur, Dorothee; Hesse, Swen; Jochimsen, Thies; Luthardt, Julia; Sattler, Bernhard; Patt, Marianne; Hoffmann, Karl-Titus; Villringer, Arno; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Current research diagnostic criteria for Alzheimer's disease (AD) and mild cognitive impairment (MCI) due to AD include biomarkers to supplement clinical testing. Recently, we demonstrated that dual time-point [18F]FBB PET is able to deliver both blood flow and amyloid-β (Aβ) load surrogates. OBJECTIVE: The aim of this study was to investigate whether these surrogates can be utilized as AD biomarkers. METHODS: 112 subjects (41 with MCI, 50 with probable/possible AD, 21 with other dementias) underwent dual time-point [18F]FBB PET. Data were visually and relative quantitatively (Herholz scores for the early and composite SUVRs for the late PET data) analyzed. RESULTS: In the early images AD-typical patterns were present in 42% /27% /33% of probable/possible AD/MCI/other dementia cases. In late [18F]FBB PET, 42% /29% /38% of probable/possible AD/ MCI/other dementia cases were Aβ-positive. 17% of the MCIs were categorized as "MCI due to AD-high likelihood", 44% of the probable ADs as "probable AD with high evidence of AD pathophysiological process" and 28% of the possible ADs as "possible AD with evidence of AD pathophysiological process". 27% of all subjects showed a positive diagnostic and progression biomarker. Herholz scores were lower (0.85±0.05 versus 0.88±0.04, p = 0.015) for probable/possible AD versus MCI. Composite late phase SUVRs were significantly higher (1.65±0.23 versus 1.15±0.17, p < 0.005) in Aβ-positive versus Aβ-negative patients. Herholz and MMSE scores were positively correlated (R = 0.30 p = 0.006). CONCLUSION: Dual time-point [18F]FBB PET provides dual biomarker information which enables to categorize MCI and AD dementia patients according to established diagnostic criteria. Thus, dual time-point [18F]FBB PET has great potential to supplement diagnostic dementia workups.

Early and Persistent O-GlcNAc Protein Modification in the Streptozotocin Model of Alzheimer's Disease. - Dos Santos, João Paulo Almeida; Vizuete, Adriana; Hansen, Fernanda; Biasibetti, Regina; Gonçalves, Carlos-Alberto (J Alzheimers Dis, 2018)
O-GlcNAc transferase (OGT), an enzyme highly expressed in brain tissue, catalyzes the addition of N-acetyl-glucosamine (GlcNAc) to hydroxyl residues of serine and threonine of proteins. Brain protein O-GlcNAcylation is diminished in Alzheimer's disease (AD), and OGT targets include proteins of the insulin-signaling pathway (e.g., insulin receptor susbtrate-1, IRS-1). We hypothesized that ICV streptozotocin (STZ) also affects O-GlcNAc protein modification. We investigated hippocampal metabolic changes in Wistar rats, particularly OGT levels and insulin resistance, as well as related astroglial activities, immediately after ICV STZ administration (first week) and later on (fourth week). We found an early (at one week) and persistent (at fourth week) decrease in OGT in the ICV STZ model of AD, characterized by a spatial cognitive deficit. Consistent with this observation, we observed a decrease in protein O-GlnNAc modification at both times. Increased phosphorylation at serine-307 of IRS-1, which is related to insulin resistance, was observed on the fourth week. The decrease in OGT and consequent protein O-GlnNAc modifications appear to precede the decrease in glucose uptake and increment of the glyoxalase system observed in the hippocampus. Changes in glial fibrillary acidic protein and S100B in the hippocampus, as well as the alterations in cerebrospinal fluid S100B, confirm the astrogliosis. Moreover, decreases in glutamine synthetase and glutathione content suggest astroglial dysfunction, which are likely implicated in the neurodegenerative cascade triggered in this model. Together, these data contribute to the understanding of neurochemical changes in the ICV STZ model of sporadic AD, and may explain the decreases in protein O-GlcNAc levels and insulin resistance observed in AD.
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Antibiotics, Antineoplastic; Brain; Disease Models, Animal; Glial Fibrillary Acidic Protein; Glucose; Glutathione; Insulin Receptor Substrate Proteins; Lactoylglutathione Lyase; Male; Maze Learning; N-Acetylglucosaminyltransferases; Rats; Rats, Wistar; S100 Calcium Binding Protein beta Subunit; Streptozocin; Time Factors

Effects of a 3-Year Multi-Domain Intervention with or without Omega-3 Supplementation on Cognitive Functions in Older Subjects with Increased CAIDE Dementia Scores. - Chhetri, Jagadish K; de Souto Barreto, Philipe; Cantet, Christelle; Pothier, Kristell; Cesari, Matteo; Andrieu, Sandrine; Coley, Nicola; Vellas, Bruno (J Alzheimers Dis, 2018)
Findings from recent Alzheimer's disease prevention trials have shown subjects with increased dementia score based upon mid-life cardiovascular risk factors, to benefit from multi-domain intervention strategies to some extent. The effects of such interventions on cognitive functions remains yet to be well-established. This study is a secondary analysis of the MAPT study, 1,293 older subjects (mean age 75 years) with high CAIDE score (i.e., ≥6) were classified according to the four intervention groups: 1) multi-domain intervention plus placebo, 2) isolated supplementation with Omega-3 polyunsaturated fatty acid (n-3 PUFA), 3) combination of the two interventions, and 4) placebo alone. Linear mixed-model repeated-measures analyses were used to assess the cognitive changes according to various neuropsychological test scores between intervention groups compared to the placebo at 36 months from baseline. Compared to the placebo, group with multi-domain intervention in combination withn-3PUFA was found to show significant improvement in the delayed total recall test of the free and cued selective reminding test (FCSRT) (mean±standard error(SE) = 0.20±0.10) and MMSE orientation test (mean±SE = 0.15±0.06) at 36 months. Isolated multi-domain intervention group showed significant less decline in the MMSE orientation test (mean±SE = 0.12±0.06) compared to the placebo. There was significant less improvement (mean±SE = - 1.01±0.46) in the FCSRT free recall test in the n-3 PUFA intervention group compared to the placebo at 36 months. Our findings show high-risk subjects for dementia screened with CAIDE dementia score might benefit from multi-domain intervention strategies as in the MAPT study, particularly in the orientation and delayed recall domain.

Effects of Exergaming in People with Dementia: Results of a Systematic Literature Review. - van Santen, Joeke; Dröes, Rose-Marie; Holstege, Marije; Henkemans, Olivier Blanson; van Rijn, Annelies; de Vries, Ralph; van Straten, Annemieke; Meiland, Franka (J Alzheimers Dis, 2018)
BACKGROUND: Physical exercise benefits functioning, health, and well-being. However, people living with dementia in particular hardly engage in exercise. Exergaming (exercise and gaming) is an innovative, fun, and relatively safe way of exercising in a virtual reality or gaming environment. It may help people living with dementia overcome barriers they can experience regarding regular exercise activities. OBJECTIVE: This systematic literature review aims to provide an overview of the cost-effectiveness of exergaming and its effects on physical, cognitive, emotional, and social functioning, as well as the quality of life in people living with dementia. METHODS: PubMed, Embase, Cinahl, PsycINFO, the Cochrane Library, and the Web of Science Core Collection were searched. Selection of studies was carried out by at least two independent researchers. RESULTS: Three studies were found to be eligible and were included in this review. Two of these showed some statistically significant effects of exergaming on physical, cognitive, and emotional functioning in people living with dementia, although based on a very small sample. No articles were found about the cost-effectiveness of exergaming. CONCLUSIONS: Only a few controlled studies have been conducted into the effectiveness of exergaming, and these show very little significant benefits. More well-designed studies are necessary to examine the effects of exergaming.

Endocytosis and Transcytosis of Amyloid-β Peptides by Astrocytes: A Possible Mechanism for Amyloid-β Clearance in Alzheimer's Disease. - Domínguez-Prieto, Marta; Velasco, Ana; Tabernero, Arantxa; Medina, José M (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) peptides, Aβ40, Aβ42, and recently Aβ25 - 35, have been directly implicated in the pathogenesis of Alzheimer's disease (AD). We have previously shown that all three peptides decrease neuronal viability, but Aβ40 also promotes synaptic disassembling. In this work, we have studied the effects of these peptides on astrocytes in primary culture and found that the three Aβ peptides were internalized by astrocytes and significantly decreased astrocyte viability, while increasing ROS production. Aβ peptide internalization is temperature-dependent, a fact that supports the idea that Aβ peptides are actively endocytosed by astrocytes. However, inhibiting caveolae formation by methyl-beta-cyclodextrin or by silencing caveolin-1 with RNA interference did not prevent Aβ endocytosis, which suggests that Aβ peptides do not use caveolae to enter astrocytes. Conversely, inhibition of clathrin-coated vesicle formation by chlorpromazine or by silencing clathrin with RNA interference significantly decreased Aβ internalization and partially reverted the decrease of astrocyte viability caused by the presence of Aβ. These results suggest that Aβ is endocytosed by clathrin-coated vesicles in astrocytes. Aβ-loaded astrocytes, when co-incubated with non-treated astrocytes in separate wells but with the same incubation medium, promoted cell death in non-treated astrocytes; a fact that was associated with the presence of Aβ inside previously unloaded astrocytes. This phenomenon was inhibited by the presence of chlorpromazine in the co-incubation medium. These results suggest that astrocyte may perform Aβ transcytosis, a process that could play a role in the clearance of Aβ peptides from the brain to cerebrospinal fluid.

Endogenous Murine Amyloid-β Peptide Assembles into Aggregates in the Aged C57BL/6J Mouse Suggesting These Animals as a Model to Study Pathogenesis of Amyloid-β Plaque Formation. - Ahlemeyer, Barbara; Halupczok, Sascha; Rodenberg-Frank, Elke; Valerius, Klaus-Peter; Baumgart-Vogt, Eveline (J Alzheimers Dis, 2018)
Amyloid-β peptide (Aβ), paired helical filament-tau (PHF-tau), and α-synuclein are in the focus of neuroscience research because they aggregate in brains of patients with Alzheimer's and Parkinson's diseases. For this purpose, transgenic mouse models were used containing the human genes for AβPP/presenilin/tau or α-synuclein with the most frequent mutations. This is not ideal because most patients develop sporadic forms of the diseases with no causative single gene defect and furthermore the aggregation of human proteins in man is not necessarily the same in rodents. We hypothesized that for such cases the aged mouse could be an alternative model and analyzed the distribution of endogenous Aβ, PHF-tau, and α-synuclein in mouse brains at different ages. Whereas Aβ was below detectable levels at birth, it was present at high levels in the 15-month-old mouse. Aβ was found in the cytosol and lysosomes of neurons of the temporal cortex, cingulate area, pons, and cerebellum as well as extracellularly in the periventricular zone. Contrary to Aβ, mouse brain was devoid of PHF-tau-positive neurofibrillary tangles. α-Synuclein was detectable in the newborn mouse with highest levels in the marginal zone of the lateral cortex and average levels in the hippocampus, pons, and cerebellum. Brain-area specific differences in the α-synuclein level persisted up to 15 months of age, but increased 3-fold in all areas over time. α-Synuclein resided in the neuropil, but not in intracellular aggregates even in the aged mouse. We suggest the aged mouse as a model to study Aβ plaque formation.
Keywords: Age Factors; Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurofibrillary Tangles; Neurons; Plaque, Amyloid; tau Proteins

Episodic Memory and Learning Dysfunction Over an 18-Month Period in Preclinical and Prodromal Alzheimer's Disease. - Baker, Jenalle E; Lim, Yen Ying; Jaeger, Judith; Ames, David; Lautenschlager, Nicola T; Robertson, Joanne; Pietrzak, Robert H; Snyder, Peter J; Villemagne, Victor L; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2018)
Recent meta-analyses suggest that episodic memory impairment associated with preclinical Alzheimer's disease (AD) equates to 0.15-0.24 standard deviations below that of cognitively healthy older adults. The current study aimed to characterize impairments in verbal acquisition and recall detectable at a single assessment, and investigate how verbal learning and episodic memory deteriorates in preclinical AD. A verbal list-learning task, the International Shopping List Test (ISLT), was administered multiple times over an 18-month period, to three groups of participants: amyloid-beta negative healthy older adults (Aβ- CN; n = 50); Aβ+ positive healthy older adults (preclinical AD; n = 25); and Aβ+ positive individuals diagnosed with mild cognitive impairment (prodromal AD; n = 22). At baseline, there was no significant difference between the preclinical AD and control groups rate of acquisition, or total and delayed recall, however all indices were impaired in prodromal AD. Performance on ISLT total score improved in the control group over the 18-month period, but showed a moderate magnitude decline in the preclinical AD group (Cohen's d = - 0.63, [- 1.12, - 0.14]) and the prodromal AD group (Cohen's d = - 0.36, [- 0.94, 0.22]). No significant impairment in acquisition associated with preclinical AD was seen at baseline. Individuals with preclinical AD showed a significantly different performance on the ISLT total score over an 18-month period, compared to those without abnormal Aβ. Individuals with prodromal AD showed substantial impairment on the ISLT at baseline and declined to a greater extent over time.

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

The Ethyl Acetate Extract of Leaves of Ugni molinae Turcz. Improves Neuropathological Hallmarks of Alzheimer's Disease in Female APPswe/PS1dE9 Mice Fed with a High Fat Diet. - Jara-Moreno, Daniela; Castro-Torres, Rubn D; Ettcheto, Miren; Auladell, Carme; Kogan, Marcelo J; Folch, Jaume; Verdaguer, Ester; Cano, Amanda; Busquets, Oriol; Delporte, Carla; Camins, Antoni (J Alzheimers Dis, 2018)
The most common type of dementia is Alzheimer's disease (AD), a progressive neurodegenerative disease characterized by impairment in cognitive performance in aged individuals. Currently, there is no effective pharmacological treatment that cures the disease due to the lack of knowledge on the actual mechanisms involved in its pathogenesis. In the last decades, the amyloidogenic hypothesis has been the most studied theory trying to explain the origin of AD, yet it does not address all the concerns relating to its development. In the present study, a possible new preclinical treatment of AD was evaluated using the ethyl acetate extract (EAE) of leaves of Ugni molinae Turcz. (synonym Myrtus ugni Molina Family Myrtacea). The effects were assessed on female transgenic mice from a preclinical model of familial AD (APPswe/PS1dE9) combined with a high fat diet. This preclinical model was selected due to the already available experimental and observational data proving the relationship between obesity, gender, metabolic stress, and cognitive dysfunction; related to characteristics of sporadic AD. According to chemical analyses, EAE would contain polyphenols such as tannins, flavonoid derivatives, and phenolic acids, as well as pentacyclic triterpenoids that exhibit neuroprotective, anti-inflammatory, and antioxidant effects. In addition, the treatment evidenced its capacity to prevent deterioration of memory capacity and reduction of progression speed of AD neuropathology.

Executive and Language Subjective Cognitive Decline Complaints Discriminate Preclinical Alzheimer's Disease from Normal Aging. - Valech, Natalia; Tort-Merino, Adrià; Coll-Padrós, Nina; Olives, Jaume; León, María; Rami, Lorena; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to specify the profile of subjective cognitive decline in preclinical Alzheimer's disease (preAD). OBJECTIVES: To explore specific items of the Subjective Cognitive Decline Questionnaire (SCD-Q) that discriminate preAD from normal aging. METHODS: 68 cognitively normal older adults were classified as controls (n = 52) or preAD (n = 16) according to amyloid-β (Aβ) levels. An exploratory factor analysis and item analysis of the SCD-Q were performed. Informant reports of the SCD-Q were used to corroborate the findings of self-reports. One-year neuropsychological follow-up was available. RESULTS: Four SCD-Q factors were extracted: EM-factor (episodic memory), A-factor (attention), O-factor (organization), and L-factor (language). PreAD reported a significantly higher decline in L-factor (F(1) = 6.49; p = 0.014) and A-factor (F(1) = 4.04; p = 0.049) compared to controls, and showed a higher frequency of perceived decline in SCD-Q items related with language and executive tasks (Sig-items.) Significant discriminative powers for Aβ-positivity were found for L-factor (AUC = 0.75; p = 0.003) and A-factor (AUC = 0.74; p = 0.004). Informants in the preAD group confirmed significantly higher scores in L-factor and Sig-items. A significant time×group interaction was found in the Semantic Fluency and Stroop tests, with the preAD group showing a decrease in performance at one-year. CONCLUSIONS: Our results suggest that SCD-Q items related with language and executive decline may help in prediction algorithms to detect preAD. Validation in an independent population is needed.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Executive Function; Factor Analysis, Statistical; Female; Humans; Language; Male; Middle Aged; Neuropsychological Tests; Self Report

Exercise Training on Locomotion in Patients with Alzheimer's Disease: A Feasibility Study. - Pedrinolla, Anna; Venturelli, Massimo; Fonte, Cristina; Munari, Daniele; Benetti, Maria Vittoria; Rudi, Doriana; Tamburin, Stefano; Muti, Ettore; Zanolla, Luisa; Smania, Nicola; Schena, Federico (J Alzheimers Dis, 2018)
BACKGROUND: Although current literature has shown that patients with Alzheimer's disease (AD) have worse locomotion compared with healthy counterparts, no studies have focused on the efficacy of exercise training in improving gait abnormalities including biomechanics and metabolic aspects, in this population. OBJECTIVE: To verify the effectiveness of exercise training (ET) on gait parameters (i.e., speed, step and stride length, single and double support, and energy cost of walking (Cw)) in patients with AD with respect to a standard cognitive treatment (CT). METHODS: In this study, we included a small portion of data belonging to a larger study (ClinicalTrials.gov number, NCT03034746). Patients with AD (Mini-Mental State Examination 22±5) were included in the study. Gait parameters and Cw were assessed at baseline and after 6 months (72 treatment sessions) of treatment. ET included 90 min of aerobic and strength training. CT included 90 min of cognitive stimuli. RESULTS: The 16 patients assigned to ET exhibited significant improvement of Cw (-0.9±0.1 J/kg·m-1), while differences in gait parameters were negligible. The effect on gait parameters were undetectable in the 18 patients assigned to CT (-0.2±0.5 J/kg·m-1). CONCLUSIONS: Data from this study showed that ET program seems effective in improving Cw in patients with AD. Interestingly, the positive effect of ET on Cw was not coupled with ameliorations of patient's gait parameters, suggesting that the gain of metabolic aspects of locomotion were the main factors responsible for this positive result.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomechanical Phenomena; Exercise Test; Exercise Therapy; Feasibility Studies; Female; Gait; Humans; Italy; Male; Single-Blind Method

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

Growth Hormone-Releasing Hormone Modulation of Neuronal Exosome Biomarkers in Mild Cognitive Impairment. - Winston, Charisse N; Goetzl, Edward J; Baker, Laura D; Vitiello, Michael V; Rissman, Robert A (J Alzheimers Dis, 2018)
Age-related changes in cognition are linked to decreased expression of somatotropins, GHRH and IGF-1. Mild cognitive impairment (MCI) and Alzheimer's disease (AD) are heterogeneous conditions. The loss of GHRH signaling in the brain may be mechanistically involved in AD pathogenesis. The consequent need to identify AD at an early and perhaps more treatable stage has fueled research into blood-based, exosome biomarkers. Plasma exosomes from participants enrolled in a randomized, double-blind, placebo-controlled 20-week trial of GHRH administration, were isolated, precipitated, and enriched by immuno-absorption with anti-L1CAM antibody (neural adhesion protein) from adults with MCI and age-matched, cognitively normal controls (CNC). Extracted protein cargo from neuronally-derived exosomes (NDEs) were assessed by ELISAs for protein levels implicated in AD neuropathology and for synaptic proteins altered by AD. Plasma NDE concentrations of Aβ1-42 were significantly increased while plasma NDE concentrations of NRGN, synaptophysin, synaptotagmin, and synaptopodin were significantly decreased in patients with MCI, independent of GHRH treatment. Plasma NDE concentrations of ptau-S396 and GAP43 were not affected by cognitive status (CNC versus MCI) or by GHRH treatment. Aβ1-42, neurogranin (NRGN), synaptophysin, synaptotagmin, and synaptopodin demonstrated the highest diagnostic accuracy for distinguishing between CNC and MCI patients, while synaptophysin and synaptotagmin demonstrated moderate accuracy in distinguishing between placebo-treated and GHRH-treated, MCI patients.

Homocysteine and Cerebral Atrophy: The Epidemiology of Dementia in Singapore Study. - Tan, Bryce; Venketasubramanian, Narayanaswamy; Vrooman, Henri; Cheng, Ching-Yu; Wong, Tien Yin; Ikram, Mohammad Kamran; Chen, Christopher; Hilal, Saima (J Alzheimers Dis, 2018)
BACKGROUND: Plasma homocysteine levels are increasingly studied as a potential risk factor for dementia. Elevated homocysteine levels have been linked with gray and white matter volume reduction among individuals with mild cognitive impairment and Alzheimer's disease. However, the effects of homocysteine on brain changes in preclinical stages of dementia remain unexplored. OBJECTIVE: To examine the association of elevated homocysteine levels with markers of neurodegeneration, i.e., white and gray matter volume in an elderly population. METHODS: The study included 768 participants (mean age: 69.6±6.5 years, 51.3% women) from the Epidemiology of Dementia In Singapore study. Participants underwent a brain MRI scan and blood tests. Serum homocysteine was measured using competitive immunoassay. Cortical thickness and subcortical structural volume were quantified using FreeSurfer whereas white matter volume was quantified using a previous validated method. RESULTS: Higher homocysteine levels were significantly associated with decreased global white matter volume [mean difference (β) in volume (ml) per micromole per liter (μmol/l) increase in homocysteine levels: - 0.555, 95% Confidence Interval (CI): - 0.873; - 0.237], decreased parietal cortical thickness [β in thickness (μm) per μmol/l increase in homocysteine levels:- 1.429, 95% CI: - 2.781; - 0.077], and smaller volumes of the thalamus [β: - 0.017, 95% CI: - 0.026; - 0.008], brainstem [β: - 0.037, 95% CI: - 0.058; - 0.016], and accumbens [β: - 0.004, 95% CI: - 0.006; - 0.002]. CONCLUSION: Higher homocysteine levels were associated with cerebral atrophy. Further studies are required to assess whether lowering plasma homocysteine levels may prevent neurodegenerative changes or delay progression of clinical symptoms before the development of dementia.
Keywords: Aged; Atrophy; Biomarkers; Dementia; Female; Homocysteine; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Organ Size; Risk Factors; Singapore; White Matter

Hypercapnic and Hypoxic Respiratory Response During Wakefulness and Sleep in a Streptozotocin Model of Alzheimer's Disease in Rats. - Vicente, Mariane C; Almeida, Maria C; Bícego, Kênia C; Carrettiero, Daniel C; Gargaglioni, Luciane H (J Alzheimers Dis, 2018)
Besides the typical cognitive decline, patients with Alzheimer's disease (AD) develop disorders of the respiratory system, such as sleep apnea, shortness of breath, and arrhythmias. These symptoms are aggravated with the progression of the disease. However, the cause and nature of these disturbances are not well understood. Here, we treated animals with intracerebroventricular streptozotocin (STZ, 2 mg/kg), a drug that has been described to cause Alzheimer-like behavioral and histopathological impairments. We measured ventilation (V̇E), electroencephalography, and electromyography during normocapnia, hypercapnia, and hypoxia in Wistar rats. In addition, we performed western blot analyses for phosphorylated tau, total tau, and amyloid-β (Aβ) peptide in the locus coeruleus (LC), retrotrapezoid nucleus, medullary raphe, pre-Bötzinger/Bötzinger complex, and hippocampus, and evaluated memory and learning acquisition using the Barnes maze. STZ treatment promoted memory and learning deficits and increased the percentage of total wakefulness during normocapnia and hypercapnia due to a reduction in the length of episodes of wakefulness. CO2-drive to breathe during wakefulness was increased by 26% in STZ-treated rats due to an enhanced tidal volume, but no changes in V̇E were observed in room air or hypoxic conditions. The STZ group also showed a 70% increase of Aβ in the LC and no change in tau protein phosphorylation. In addition, no alteration in body temperature was observed. Our findings suggest that AD animals present an increased sensitivity to CO2 during wakefulness, enhanced Aβ in the LC, and sleep disruption.

The Impact of a Shared Decision-Making Training Program on Dementia Care Planning in Long-Term Care. - Mariani, Elena; Chattat, Rabih; Ottoboni, Giovanni; Koopmans, Raymond; Vernooij-Dassen, Myrra; Engels, Yvonne (J Alzheimers Dis, 2018)
BACKGROUND: Shared decision-making (SDM) can be a way for staff to adopt international recommendations advocating the involvement of nursing home residents and their family members in care planning and the development of personalized care plans. OBJECTIVE: The main aim was to analyze the effects of training nursing home staff in the implementation of SDM on agreement of residents' 'life-and-care plans' with the recommendations (primary outcome) and on family caregivers' quality of life and sense of competence, and staff's job satisfaction (secondary outcomes). METHODS: In the intervention condition, staff attended a training program on the use of SDM with residents and family caregivers in the care planning process. In the control condition, care planning as usual took place. For the primary outcome, in-depth qualitative and quantitative analyses of the care plans were performed. Multivariate Permutation Tests were applied to assess the impact on secondary outcomes. RESULTS: Forty-nine residents and family caregivers and 34 professionals were involved. Overall, many of the care plans developed during the intervention showed a high level of agreement with the care planning recommendations. Both Italian and Dutch care plans showed improvement in the number of clear problem statements (p < 0.001). In Italy, significant improvements (p < 0.05) were also found regarding specific care objectives, documentation of objectives met, and of residents and families' involvement. No impact was found on secondary outcomes. CONCLUSION: The involvement of residents and family caregivers in care planning contributed to an improvement of the residents' care plans, but it did not have an effect on family caregivers and staff outcomes.

The Impact of Creative Arts in Alzheimer's Disease and Dementia Public Health Education. - Burns, Nicole C; Watts, Amber; Perales, Jaime; Montgomery, Robert Neal; Morris, Jill K; Mahnken, Jonathan D; Lowther, Johnna; Vidoni, Eric D (J Alzheimers Dis, 2018)
Previous research involving dramatic performances about Alzheimer's disease and dementia perception have targeted health care workers or caretakers. We examined the influence of a theater performance on the emotional affect of a general audience to determine the utility of this type of theater in large-scale public health education efforts. Our study included 147 participants that attended a self-revelatory theater performance based on the social/relationship experiences of those with dementia and those who care for them. This type of theater engages the audience and actors in a dual transformative process, supporting the emotional growth of all involved. Participants completed pre- and post-performance questionnaires regarding their beliefs and feelings surrounding the topic of dementia and the importance of the Arts for educating on issues surrounding dementia care. We tested for change in emotional affect pre- and post-performance using sensitivity and center of gravity statistical analyses. We found a significant change in emotional affect from an initial strong negative affect to slightly more positive/relaxed view after viewing the performance. Findings support self-revelatory theater as a resource to destigmatize preconceived notions of dementia. Large-scale community health education efforts could benefit from using this style of theater to elicit a change in audience perception of disease realities.

Impact of Untimely Access to Formal Care on Costs and Quality of Life in Community Dwelling People with Dementia. - Janssen, Niels; Handels, Ron L; Sköldunger, Anders; Woods, Bob; Jelley, Hannah; Edwards, Rhiannon Tudor; Orrell, Martin; Selbæk, Geir; Røsvik, Janne; Gonçalves-Pereira, Manuel; Marques, Maria J; Zanetti, Orazio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Access to formal care is not always timely and a better understanding on the impact of untimely access is needed. OBJECTIVE: To examine, from a societal perspective, the impact of untimely access to formal care in terms of total costs and quality of life over one year in community dwelling people with dementia. METHODS: Within the Actifcare study, needs, resource use, and quality of life were observed for one year in a cohort of 451 community dwelling people with dementia in 8 European countries. Untimely access to care was operationalized as having at least one unmet need for care identified by the Camberwell Assessment of Need for the Elderly (CANE) instrument. Two regression models were built for both total costs and quality of life measured by the EQ-5D-5L, one using sum of unmet needs and one using a predefined selection of need items. RESULTS: Unmet needs were not associated with higher total costs but they were associated with a lower quality of life of people with dementia. Of all CANE items, only an unmet need for "company" was significantly related to lower total costs. CONCLUSION: Total costs did not seem to differ between participants with unmet and met needs. Only few associations between specific unmet needs and costs and quality of life were found. Furthermore, quality of life of people with dementia decreases when multiple unmet needs are experienced, indicating that assessing and meeting needs is important to improve quality of life.

Impaired IL-17 Production in Gut-Residing Immune Cells of 5xFAD Mice with Alzheimer's Disease Pathology. - Saksida, Tamara; Koprivica, Ivan; Vujičić, Milica; Stošić-Grujičić, Stanislava; Perović, Milka; Kanazir, Selma; Stojanović, Ivana (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by accumulation of amyloid-β plaques that further promotes microglia-mediated neuroinflammatory responses and inflammation in the brain. Emerging data are revealing the relation between gut-associated lymphoid tissue (GALT) cells and CNS, as effector cells primed in the gut might home to the brain. This study aimed to determine cell composition of GALT in 5xFAD mice, an established model for AD. Immune cells isolated from Peyer's patches (PP) and mesenteric lymph nodes (MLN) were stained with surface and intracellular markers for T helper (Th) subpopulations, B lymphocytes and macrophages and analyzed cytofluorimetrically, while cytokine expression and production were determined by qPCR and ELISA, respectively. Inflammation was detected in GALT of 5xFAD mice with established AD pathology. Although the production of IFN-γ, IL-4, and IL-10 was comparable between the strains, lower IL-17 production was observed in PP and MLN cells. This phenomenon could not be attributed to a lower abundance of Th17 cells, or cytokines that initiate their formation or propagation (TGF-β, IL-6, and IL-23). Also, reduced IL-17 production was not a consequence of altered Il-17 mRNA transcription or deficiency of Rorγt, a key transcription factor for IL-17. However, the expression of miR-155 (a non-coding micro RNA that promotes the development of Th17 cells), was significantly lower in MLN cells of 5xFAD mice. In contrast, mice without AD neuropathology did not have inflammation in GALT or altered Th17 numbers, nor decreased IL-17 production. In conclusion, the observed changes in GALT of 5xFAD mice mirror the disease progression and might reflect inadequate immune surveillance in the gut and lead to enhanced AD pathology.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; B-Lymphocytes; Disease Models, Animal; Female; Interleukin-17; Lymph Nodes; Male; Mice; Mice, Transgenic; MicroRNAs; Peyer's Patches; Th17 Cells

An Inducible Alpha-Synuclein Expressing Neuronal Cell Line Model for Parkinson's Disease1. - Vasquez, Velmarini; Mitra, Joy; Perry, George; Rao, K S; Hegde, Muralidhar L (J Alzheimers Dis, 2018)
Altered expression of α-synuclein is linked to Parkinson's disease (PD). A major challenge to explore how the increased α-synuclein affect neurotoxicity is the lack of a suitable human neuronal cell model that mimics this scenario. Its expression in neural precursors affects their differentiation process, in addition to the neuronal adaptability and variability in maintaining a constant level of expression across passages. Here, we describe an SH-SY5Y line harboring Tet-ON SNCA cDNA cassette that allows for induction of controlled α-synuclein expression after neuronal differentiation, which can be an important tool for PD research.

Induction of Amyloid-β42 Production by Fipronil and Other Pyrazole Insecticides. - Cam, Morgane; Durieu, Emilie; Bodin, Marion; Manousopoulou, Antigoni; Koslowski, Svenja; Vasylieva, Natalia; Barnych, Bogdan; Hammock, Bruce D; Bohl, Bettina; Koch, Philipp; Omori, Chiori; Yamamoto, Kazuo; et al. (J Alzheimers Dis, 2018)
Generation of amyloid-β peptides (Aβs) by proteolytic cleavage of the amyloid-β protein precursor (AβPP), especially increased production of Aβ42/Aβ43 over Aβ40, and their aggregation as oligomers and plaques, represent a characteristic feature of Alzheimer's disease (AD). In familial AD (FAD), altered Aβ production originates from specific mutations of AβPP or presenilins 1/2 (PS1/PS2), the catalytic subunits of γ-secretase. In sporadic AD, the origin of altered production of Aβs remains unknown. We hypothesize that the 'human chemical exposome' contains products able to favor the production of Aβ42/Aβ43 over Aβ40 and shorter Aβs. To detect such products, we screened a library of 3500 + compounds in a cell-based assay for enhanced Aβ42/Aβ43 production. Nine pyrazole insecticides were found to induce a β- and γ-secretase-dependent, 3-10-fold increase in the production of extracellular Aβ42 in various cell lines and neurons differentiated from induced pluripotent stem cells derived from healthy and FAD patients. Immunoprecipitation/mass spectrometry analyses showed increased production of Aβs cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and shorter. Strongly supporting a direct effect on γ-secretase activity, pyrazoles shifted the cleavage pattern of another γ-secretase substrate, alcadeinα, and shifted the cleavage of AβPP by highly purified γ-secretase toward Aβ42/Aβ43. Focusing on fipronil, we showed that some of its metabolites, in particular the persistent fipronil sulfone, also favor the production of Aβ42/Aβ43 in both cell-based and cell-free systems. Fipronil administered orally to mice and rats is known to be metabolized rapidly, mostly to fipronil sulfone, which stably accumulates in adipose tissue and brain. In conclusion, several widely used pyrazole insecticides enhance the production of toxic, aggregation prone Aβ42/Aβ43 peptides, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in sporadic AD.

Influence of Butyrylcholinesterase in Progression of Mild Cognitive Impairment to Alzheimer's Disease. - Gabriel, António José; Almeida, Maria Rosário; Ribeiro, Maria Helena; Carneiro, Diogo; Valério, Daniela; Pinheiro, Ana Cristina; Pascoal, Rui; Santana, Isabel; Baldeiras, Ines (J Alzheimers Dis, 2018)
BACKGROUND: Several demographic and genetic prognostic factors of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD) have been recognized so far. The most frequent polymorphism of butyrylcholinesterase (BuChE), the K-variant, has been proposed as a risk factor for AD, but data regarding its influence on early disease progression is still limited. OBJECTIVE: To investigate the influence of the BuChE-K variant in MCI progression to AD. METHODS: 96 MCI patients were included in the study and were genotyped for BuChE-K variant and Apolipoprotein E (ApoE). Cerebrospinal fluid (CSF) BuChE activity, as well as the levels of AD biomarkers amyloid-β 42 (Aβ42), total and hyperphosphorylated tau (t-tau and p-tau) were also determined. RESULTS: No significant differences were found in either BuChE-K variant or BuChE activity between MCI patients that progressed to AD (MCI-AD) and patients that remained stable during clinical follow-up (MCI-St). As expected, baseline CSF levels of Aβ42 were significantly lower and t-Tau, p-Tau, and ApoE ɛ4 allele frequency were significantly higher in MCI-AD patients. An association between the ApoE ɛ4 allele and the BuChE-K variant in MCI-AD, but not in MCI-St patients, was found with patients carrying both alleles presenting the highest incidence of progression and the lowest estimated time of progression to AD. CONCLUSION: Although BuChE-K alone does not seem to play a major role in progression to AD in MCI patients, a synergistic effect with the ApoE ɛ4 allele was found, highlighting the importance of assessing these combined genotypes for evaluating risk progression in MCI patients.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Biomarkers; Butyrylcholinesterase; Cognitive Dysfunction; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Risk Factors; tau Proteins

The Influence of Polypharmacy on the Initiation of Anti-Dementia Therapy in Germany. - Bohlken, Jens; Jacob, Louis; van den Bussche, Hendrik; Kostev, Karel (J Alzheimers Dis, 2018)
The goal of the present retrospective study was to focus on the potential influence of polypharmacy on the initiation of antidementia therapy in patients diagnosed with dementia in general practices in Germany. The current study sample included patients diagnosed with dementia in 1,217 general practices in Germany between 2014 and 2016 (index date). The primary outcome measure was the rate of prescription of anti-dementia drugs within one year following the index date. The explanatory variable was the number of different drugs prescribed at baseline per patient. Independent variables included age, sex, and type of dementia. Logistic regression analyses were conducted to study the impact of the number of different drugs prescribed at baseline per participant on the odds of receiving anti-dementia therapy (in all patients and in patients diagnosed with Alzheimer's disease). The study included 21,888 patients with all-cause dementia. Mean age was 80.2 years (SD = 7.3 years) and 61.4% of the study population were women. Individuals receiving six drugs or more at baseline were significantly less likely to be prescribed anti-dementia treatment when compared to those without any drug at baseline (6- 9 drugs: odds ratio [OR] = 0.75;≥10 drugs: OR = 0.58). In the subgroup of patients with Alzheimer's disease, the odds of being prescribed anti-dementia therapy were lower in individuals with four drugs or more, compared to patients who had not been prescribed any drugs at baseline (4- 5 drugs: OR = 0.60; 6- 9 drugs: OR = 0.49;≥10 drugs: OR = 0.36). There is a negative association between polypharmacy and antidementia therapy initiation in general practices in Germany.

Interactions between Atrial Fibrillation, Cardiovascular Risk Factors, and ApoE Genotype in Promoting Cognitive Decline in Patients with Alzheimer's Disease: A Prospective Cohort Study. - Falsetti, Lorenzo; Viticchi, Giovanna; Buratti, Laura; Grigioni, Francesco; Capucci, Alessandro; Silvestrini, Mauro (J Alzheimers Dis, 2018)
BACKGROUND: An association between non-valvular atrial fibrillation (NVAF) and cognitive impairment has been hypothesized. OBJECTIVE: We sought to evaluate whether and how permanent NVAF (pNVAF) is associated with progression of cognitive impairment in patients with Alzheimer's disease (AD) in the presence of vascular or genetic risk factors. METHODS: 310 consecutive patients affected by mild-moderate AD were included and followed for a 24-month period. At the end of the follow-up, based on the results of the neuropsychological evaluation patients were classified as stable or deteriorated to severe AD. Clinical history, therapy, time in therapeutic range for anticoagulation, Framingham cardiovascular risk profile (FCRP), CHA2DS2-VASc score, Mini-Mental State Examination (MMSE), ApoE genotype, brain CT-scan, carotid ultrasound, and ECG were collected. Binary logistic and path analysis were adopted to assess relationships between pNVAF, ApoE, and cognitive outcome. RESULTS: Despite anticoagulant therapy, pNVAF was associated with lower entry MMSE, higher mean intima-media thickness (mIMT) and higher FCRP. Among patients carrying ApoE ɛ4 allele and affected by pNVAF, the lowest MMSE (14.90±7.62) and the highest mIMT (1.16±0.17 mm) and FCRP (26.24±3.96) values were detected. In this group, the risk of cognitive deterioration reached the highest probability. pNVAF was associated with an increased cognitive deterioration in subjects with high FCRP, CHA2DS2-VASc, or mIMT. CONCLUSIONS: pNVAF seems to identify AD patients with a significant atherosclerotic burden and reduced cognitive performances. The interaction between pNVAF and ApoE ɛ4 genotype, especially with aggregated risk factors and an advanced stage of vascular damage is associated with higher risk of fast cognitive deterioration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Atherosclerosis; Atrial Fibrillation; Carotid Intima-Media Thickness; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prospective Studies; Risk Factors; Tomography, X-Ray Computed

Intracranial Transplantation of Pancreatic Islets Attenuates Cognitive and Peripheral Metabolic Dysfunctions in a Rat Model of Sporadic Alzheimer's Disease. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Taler, Michal; Dar, Shira; Azarov, Dmitry; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is often associated with brain insulin resistance and peripheral metabolic dysfunctions. Recently, we developed a model of sporadic AD associated with obesity-related peripheral metabolic abnormalities in Lewis rats using intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to assess the effect of intracranially grafted pancreatic islets on cognitive and peripheral metabolic dysfunctions in the icv-STZ Lewis rats. METHODS: AD-like dementia associated with obesity was induced in inbred Lewis rats using a single icv-STZ. Two months after icv-STZ, syngeneic islets (100 islets per recipient) were implanted in the cranial subarachnoid cavity of icv-STZ rats. Morris water maze and marble burying tests were used for studying cognitive and behavioral functions. Central and peripheral metabolic alterations were assessed by histological and biochemical assays. RESULTS: The icv-STZ induced increases in food intake, body weight, and blood levels of insulin and leptin without alteration of glucose homeostasis. Grafted islets reduced body weight gain, food consumption, peripheral insulin resistance, and hyperleptinemia. Biochemical and histological analysis of the brain revealed viable grafted islets expressing insulin and glucagon. The grafted islets did not affect expression of brain insulin receptors and peripheral glucose homeostasis. Two months after islet transplantation, cognitive and behavioral functioning in transplanted rats were significantly better than the sham-operated icv-STZ rats. No significant differences in the locomotor activity between transplanted and non-transplanted icv-STZ rats were found. CONCLUSIONS: Intracranial islet transplantation attenuates cognitive decline and peripheral metabolic dysfunctions providing a novel therapeutic approach for sporadic AD associated with peripheral metabolic dysfunctions.

Learning Processes and Brain Connectivity in A Cognitive-Motor Task in Neurodegeneration: Evidence from EEG Network Analysis. - Vecchio, Fabrizio; Miraglia, Francesca; Quaranta, Davide; Lacidogna, Giordano; Marra, Camillo; Rossini, Paolo Maria (J Alzheimers Dis, 2018)
Electroencephalographic (EEG) rhythms are linked to any kind of learning and cognitive performance including motor tasks. The brain is a complex network consisting of spatially distributed networks dedicated to different functions including cognitive domains where dynamic interactions of several brain areas play a pivotal role. Brain connectome could be a useful approach not only to mechanisms underlying brain cognitive functions, but also to those supporting different mental states. This goal was approached via a learning task providing the possibility to predict performance and learning along physiological and pathological brain aging. Eighty-six subjects (22 healthy, 47 amnesic mild cognitive impairment, 17 Alzheimer's disease) were recruited reflecting the whole spectrum of normal and abnormal brain connectivity scenarios. EEG recordings were performed at rest, with closed eyes, both before and after the task (Sensory Motor Learning task consisting of a visual rotation paradigm). Brain network properties were described by Small World index (SW), representing a combination of segregation and integration properties. Correlation analyses showed that alpha 2 SW in pre-task significantly predict learning (r  =  -0.2592, p < 0.0342): lower alpha 2 SW (higher possibility to increase during task and better the learning of this task), higher the learning as measured by the number of reached targets. These results suggest that, by means of an innovative analysis applied to a low-cost and widely available techniques (SW applied to EEG), the functional connectome approach as well as conventional biomarkers would be effective methods for monitoring learning progress during training both in normal and abnormal conditions.

Low Accuracy of Brief Cognitive Tests in Tracking Longitudinal Cognitive Decline in an Asian Elderly Cohort. - Phua, April Ka Sin; Hiu, Shaun Kuan Wei; Goh, Win King; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Tan, Boon Yeow; Chen, Christopher Li-Hsian; Xu, Xin (J Alzheimers Dis, 2018)
BACKGROUND: Researchers have questioned the utility of brief cognitive tests such as the Mini-Mental Status Examination (MMSE) and the Montreal Cognitive Assessment (MoCA) in serial administration and suggested that brief cognitive tests may not accurately track changes in Global Cognition. OBJECTIVE: To examine the accuracy of longitudinal changes on brief cognitive tests in reflecting progression in Global Cognition measured using comprehensive neuropsychological assessments. METHODS: Two hundred and seven participants were assessed with the MMSE, MoCA, and a validated comprehensive neuropsychological battery. Global z-scores on the battery were derived and used to assess overall and significant (≥0.5 standard deviation) decline on Global Cognition. Different patterns of decline on MMSE/MoCA were classified. Accuracy was examined using receiver operating characteristic curve, and sensitivity, specificity, positive (PPV) and negative (NPV) predictive values were reported. RESULTS: The overall ability of MMSE/MoCA change scores to discriminate participants who did and did not decline on Global Cognition was fair-to-moderate (AUC [95% CI] = 0.71 [0.64-0.78] & 0.73 [0.66-0.80] for overall decline; 0.78 [0.70-0.85] & 0.80 [0.73-0.86] for significant decline, respectively). Changes in MMSE/MoCA had low accuracy in identifying significant Global Cognitive Decline (PPV = 0.41 & 0.46, respectively) but high accuracy in ruling out significant decline and identifying cognitively stable participants (NPV = 0.89 & 0.88, respectively). CONCLUSION: There is limited utility in brief cognitive tests for tracking cognitive decline. Instead, they should be used for identifying participants who remain cognitively stable on follow up. These results accentuate the importance of acknowledging the limitations of brief cognitive tests when assessing cognitive change.

Medical and Research Consent Decision-Making Capacity in Patients with Alzheimer's Disease: A Systematic Review. - van Duinkerken, Eelco; Farme, Juliana; Landeira-Fernandez, Jesus; Dourado, Marcia C; Laks, Jerson; Mograbi, Daniel C (J Alzheimers Dis, 2018)
The capacity to make decisions is an important feature of daily living, which is closely linked to proper cognitive functioning. In conditions in which cognitive functioning becomes compromised, such as in Alzheimer's disease (AD), decision-making capacity can also get affected. Especially in AD, this has important implications, since over the course of the condition many important clinical decisions have to be made. For caregivers as well as physicians, it is sometimes difficult to determine how and when to intervene in the decision-making process. The aim of this systematic literature review was to identify studies that have evaluated medical and research consent decision-making capacity in patients with AD. Studies consistently show that decision-making capabilities are impaired in patients with AD. The cognitive and neuronal correlates of this process are, however, poorly studied. The few studies that investigated correlations have shown worse cognitive performance, mainly on the MMSE, to be related to poorer decision-making capacity. As most of these correlations have been performed in groups combining patients and controls, it remains unknown if these associations are disease specific. There is a need to study more systematically the decision-making process in relation to cognitive functioning and neural correlates to be able to develop a framework of decision-making capacity in AD, ultimately aiding clinicians and caregivers to understand and evaluate those capabilities in patients.

Mediterranean Diet, Its Components, and Amyloid Imaging Biomarkers. - Vassilaki, Maria; Aakre, Jeremiah A; Syrjanen, Jeremy A; Mielke, Michelle M; Geda, Yonas E; Kremers, Walter K; Machulda, Mary M; Alhurani, Rabe E; Staubo, Sara C; Knopman, David S; Petersen, Ronald C; Lowe, Val J; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is accumulating evidence suggesting that diet may play a role in preventing or delaying cognitive decline and dementia, but the underlying biological mechanisms are not well understood. OBJECTIVES: To examine the cross-sectional associations of the Mediterranean diet (MeDi) and its components with 11C-PiB-PET scan measures of amyloid-β (Aβ) deposition. METHODS: The study consisted of 278 Mayo Clinic Study of Aging participants 70+ years old, who were cognitively unimpaired (CU) at the time of completion of the Food Frequency Questionnaire (FFQ) and when they underwent PET imaging. Adherence to the MeDi was assessed by computing the MeDi score for each participant. All scans were performed after the FFQ completion; median [IQR] time between FFQ and Aβ PET was 3.5 (1.4) years. Z-scores were created for component, macro- and micronutrients measured. Linear and logistic regression models were adjusted for age, sex, education, apolipoprotein E (APOE) ɛ4 allele carrier status, time interval between the FFQ completion and PET scan, and total energy intake. RESULTS: Participants' median age at FFQ was 77.7 years (55.8% men; 26.6% with an APOE ɛ4 allele). Higher MeDi score (linear regression slope (beta):-0.035, p = 0.012; per standard deviation increase), vegetable intake (beta:-0.043, p = 0.002), intake of vitamin A (beta:-0.041, p = 0.003) or β-carotene (beta: -0.039, p = 0.005) from food sources and moderate alcohol consumption (beta: -0.074, p = 0.03) were associated with lower 11C-PiB standardized uptake value ratio. CONCLUSION: Findings are consistent with previous studies suggesting that higher adherence to a MeDi pattern and higher vegetable consumption are associated with better neuroimaging biomarker profile. Prospective studies are needed to validate current findings.

Memantine for the Treatment of Dementia: A Review on its Current and Future Applications. - Folch, Jaume; Busquets, Oriol; Ettcheto, Miren; Sánchez-López, Elena; Castro-Torres, Ruben Dario; Verdaguer, Ester; Garcia, Maria Luisa; Olloquequi, Jordi; Casadesus, Gemma; Beas-Zarate, Carlos; Pelegri, Carme; Vilaplana, Jordi; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the presence in the brain of extracellular amyloid-β protein (Aβ) and intracellular neurofibrillary tangles composed of hyperphosphorylated tau protein. The N-Methyl-D-aspartate receptors (NMDAR), ionotropic glutamate receptor, are essential for processes like learning and memory. An excessive activation of NMDARs has been associated with neuronal loss. The discovery of extrasynaptic NMDARs provided a rational and physiological explanation between physiological and excitotoxic actions of glutamate. Memantine (MEM), an antagonist of extrasynaptic NMDAR, is currently used for the treatment of AD jointly with acetylcholinesterase inhibitors. It has been demonstrated that MEM preferentially prevents the excessive continuous extrasynaptic NMDAR disease activation and therefore prevents neuronal cell death induced by excitotoxicity without disrupting physiological synaptic activity. The problem is that MEM has shown no clear positive effects in clinical applications while, in preclinical stages, had very promising results. The data in preclinical studies suggests that MEM has a positive impact on improving AD brain neuropathology, as well as in preventing Aβ production, aggregation, or downstream neurotoxic consequences, in part through the blockade of extrasynaptic NMDAR. Thus, the focus of this review is primarily to discuss the efficacy of MEM in preclinical models of AD, consider possible combinations of this drug with others, and then evaluate possible reasons for its lack of efficacy in clinical trials. Finally, applications in other pathologies are also considered.

microRNA 221 Targets ADAM10 mRNA and is Downregulated in Alzheimer's Disease. - Manzine, Patricia R; Pelucchi, Silvia; Horst, Maria A; Vale, Francisco A C; Pavarini, Sofia C I; Audano, Matteo; Mitro, Nico; Di Luca, Monica; Marcello, Elena; Cominetti, Márcia R (J Alzheimers Dis, 2018)
ADAM10 is the α-secretase that cleaves amyloid-β protein precursor in the non-amyloidogenic pathway in Alzheimer's disease (AD) and is known to be regulated by different microRNAs (miRNAs), which are post-transcriptional regulators related to several biological and pathological processes, including AD. Here we proposed to explore and validate miRNAs that have direct or indirect relations to the AD pathophysiology and ADAM10 gene. Approximately 700 miRNAs were analyzed and 21 differentially expressed miRNAs were validated in a sample of 21 AD subjects and 17 cognitively healthy matched controls. SH-SY5Y cells were transfected with miR-144-5p, miR-221, and miR-374 mimics and inhibitors, and ADAM10 protein levels were evaluated. miR-144-5p, miR-221, and miR-374 were downregulated in AD. The overexpression of miR-221 in SH-SY5Y cells resulted in ADAM10 reduction and its inhibition in ADAM10 increased. These findings show that miR-221 can be a new potential therapeutic target for increasing ADAM10 levels in AD. In addition, these results can contribute to the better understanding of ADAM10 post-transcriptional regulation.
Keywords: ADAM10 Protein; Aged; Aged, 80 and over; Alzheimer Disease; Cell Line, Tumor; Cohort Studies; Down-Regulation; Female; Humans; Male; MicroRNAs; Middle Aged; Neuroblastoma; Psychiatric Status Rating Scales; RNA, Messenger; ROC Curve; Transfection

Mitochondrial Dysfunction as a Predictor and Driver of Alzheimer's Disease-Like Pathology in OXYS Rats. - Tyumentsev, Mikhail A; Stefanova, Natalia A; Muraleva, Natalia A; Rumyantseva, Yulia V; Kiseleva, Elena; Vavilin, Valentin A; Kolosova, Nataliya G (J Alzheimers Dis, 2018)
Growing evidence suggests that mitochondrial dysfunction is an early event in sporadic Alzheimer's disease (AD), but the impact of mitochondrial dysfunction on the transition from healthy aging to AD remains elusive. Here we estimated the influence of mitochondrial dysfunction on the initiation of AD signs in OXYS rats, which simulate key characteristics of sporadic AD. We assessed the mitochondrial ultrastructure of pyramidal neurons of the hippocampus at the age preceding the development (age 20 days), during manifestation (4-5 months), and at the well-pronounced stages (18-24 months) of the AD-like pathology in OXYS rats. Ultrastructural alterations were collated with the amounts of proteins mediating mitochondrial dynamics [mitofusins (MFN1 and MFN2) and dynamin-1-like protein (DRP1)]; with activity of respiratory chain complexes I, IV, and V in the hippocampal mitochondria; with reactive oxygen species (ROS) production; and with expression of uncoupling protein 2 (UCP2) regulating ROS production. Already at the preclinical stage, OXYS rats showed some characteristic changes in hippocampal mitochondria, which increased in size with the manifestation and progression of AD-like pathology, including decreased activity of respiratory complexes against the background of greater fusion and formation of larger mitochondria. Signs of AD developed simultaneously with increasing dysfunction of mitochondria, with a dramatic decrease in their number, and with increased fission but without upregulation of ROS production (observed only in 20-day-old OXYS rats). Summarizing the data from our present and previous studies, we conclude that mitochondrial dysfunction appears to mediate or possibly even initiate pathological molecular cascades of AD-like pathology in OXYS rats and can be considered a predictor of the early development of the late-onset form of AD in humans.

MRI-Based Screening of Preclinical Alzheimer's Disease for Prevention Clinical Trials. - Casamitjana, Adrià; Petrone, Paula; Tucholka, Alan; Falcon, Carles; Skouras, Stavros; Molinuevo, José Luis; Vilaplana, Verónica; Gispert, Juan Domingo (J Alzheimers Dis, 2018)
The identification of healthy individuals harboring amyloid pathology represents one important challenge for secondary prevention clinical trials in Alzheimer's disease (AD). Consequently, noninvasive and cost-efficient techniques to detect preclinical AD constitute an unmet need of critical importance. In this manuscript, we apply machine learning to structural MRI (T1 and DTI) of 96 cognitively normal subjects to identify amyloid-positive ones. Models were trained on public ADNI data and validated on an independent local cohort. Used for subject classification in a simulated clinical trial setting, the proposed method is able to save 60% of unnecessary CSF/PET tests and to reduce 47% of the cost of recruitment. This recruitment strategy capitalizes on available MR scans to reduce the overall amount of invasive PET/CSF tests in prevention trials, demonstrating a potential value as a tool for preclinical AD screening. This protocol could foster the development of secondary prevention strategies for AD.

Neuropsychiatric Symptoms Complicating the Diagnosis of Alzheimer's Disease: A Case Report. - Eikelboom, Willem S; van Rooij, Jeroen G J; van den Berg, Esther; Coesmans, Michiel; Jiskoot, Lize C; Singleton, Ellen; Ossenkoppele, Rik; van Swieten, John C; Seelaar, Harro; Papma, Janne M (J Alzheimers Dis, 2018)
Neuropsychiatric symptoms (NPS) are increasingly recognized as a core element of Alzheimer's disease (AD); however, clinicians still consider AD primarily as a cognitive disorder. We describe a case in which the underrecognition of NPS as part of AD resulted in substantial delay of an AD diagnosis, a wrong psychiatric diagnosis, and the organization of inappropriate care. The aim of this paper is to acknowledge NPS as an (early) manifestation of AD and to suggest features that may point toward underlying AD in older adults with late-life behavioral changes.

Neurotoxic Effects of Aβ6-42 Peptides Mimicking Putative Products Formed by the Angiotensin Converting Enzyme. - Medvedev, Alexei E; Radko, Sergey P; Yurinskaya, Marina M; Vinokurov, Maxim G; Buneeva, Olga A; Kopylov, Arthur T; Kozin, Sergey A; Mitkevich, Vladimir A; Makarov, Alexander A (J Alzheimers Dis, 2018)
Angiotensin converting enzyme (ACE) is involved in proteolytic processing of the amyloid-β(Aβ) peptide implicated in the development of Alzheimer's disease (AD) and known products of ACE-based processing of Aβ42 are characterized by reduced aggregability and cytotoxicity. Recently it has been demonstrated that ACE can act as an arginine specific endopeptidase cleaving the N-terminal pentapeptide (Aβ1-5) from synthetic Aβ peptide analogues. In the context of proteolytic processing of full length Aβ42, this suggests possible formation of Aβ6-42 species. The aim of this study was to test a hypothesis that some N-terminally truncated Aβ peptide(s) could retain aggregability and neurotoxic properties typical for Aβ42. We have investigated aggregability of two amyloid-β peptides, Aβ6-42 and isoD7-Aβ6-42, mimicking potential proteolytic products of Aβ42 and isoD7-Aβ42, and evaluated their effects on the repertoire of brain Aβ binding proteins, and cytotoxicity towards neuroblastoma SH-SY5Y cells. Aggregability of isoD7-Aβ6-42 and Aβ6-42 was higher than that of full-length peptides Aβ42 and isoD7-Aβ42, while the repertoire of mouse brain Aβ binding proteins dramatically decreased. Aβ6-42 and isoD7-Aβ6-42 exhibited higher neurotoxicity towards SH-SY5Y cells than Aβ42 and isoD7-Aβ42, respectively. They effectively stimulated production of ROS and NO, and also TNFα secretion by cells. Thus, our results suggest that ACE-dependent processing of full-length Aβs could result in formation of more pathogenic peptides.

Nutritional Intervention as a Preventive Approach for Cognitive-Related Outcomes in Cognitively Healthy Older Adults: A Systematic Review. - Solfrizzi, Vincenzo; Agosti, Pasquale; Lozupone, Madia; Custodero, Carlo; Schilardi, Andrea; Valiani, Vincenzo; Sardone, Rodolfo; Dibello, Vittorio; Di Lena, Luca; Lamanna, Angela; Stallone, Roberta; Bellomo, Antonello; et al. (J Alzheimers Dis, 2018)
The link diet-cognitive function/dementia has been largely investigated in observational studies; however, there was a lack of evidence from randomized clinical trials (RCTs) on the prevention of late-life cognitive disorders though dietary intervention in cognitively healthy older adults. In the present article, we systematically reviewed RCTs published in the last four years (2014-2017) exploring nutritional intervention efficacy in preventing the onset of late-life cognitive disorders and dementia in cognitively healthy subjects aged 60 years and older using different levels of investigation (i.e., dietary pattern changes/medical food/nutraceutical supplementation/multidomain approach and dietary macro- and micronutrient approaches) as well as possible underlying mechanisms of nutritional prevention. From the 35 included RCTs, there was moderate evidence that intervention through dietary pattern changes, medical food/nutraceutical supplementation, and multidomain approach improved specific cognitive domains or cognitive-related blood biomarkers. There was high evidence that protein supplementation improved specific cognitive domains or functional status in prefrail older adults without effect.

An Objective Method to Accurately Measure Cardiorespiratory Fitness in Older Adults Who Cannot Satisfy Widely Used Oxygen Consumption Criteria. - Dougherty, Ryan J; Lindheimer, Jacob B; Stegner, Aaron J; Van Riper, Stephanie; Okonkwo, Ozioma C; Cook, Dane B (J Alzheimers Dis, 2018)
Cardiorespiratory fitness (CRF) is routinely investigated in older adults; however, the most appropriate CRF measure to use for this population has received inadequate attention. This study aimed to 1) evaluate the reliability and validity of the oxygen uptake efficiency slope (OUES) as a sub-maximal measurement of CRF; 2) examine demographic, risk-factor, and exercise testing differences in older adults who satisfied standardized criteria for a peak oxygen consumption (V̇O2peak) test compared to those who did not; and 3) determine the difference between directly measured V̇O2peak values and OUES-predicted V̇O2peak values. One hundred ten enrollees from the Wisconsin Registry for Alzheimer's Prevention participated in this study. Participants performed a graded maximal exercise test and wore an accelerometer for 7 days. For each participant, the OUES was calculated at 75%, 90%, and 100% of exercise duration. V̇O2peak was recorded at peak effort, and one week of physical activity behavior was measured. OUES values calculated at separate relative exercise durations displayed excellent reliability (ICC = 0.995; p < 0.001), and were strongly correlated with V̇O2peak (rrange = 0.801-0.909; p < 0.001). As hypothesized, participants who did not satisfy V̇O2peak criteria were significantly older than those who satisfied criteria (p = 0.049) and attained a directly measured V̇O2peak that was 2.31 mL·kg·min-1 less than the value that was predicted by OUES V̇O2peak (p = 0.003). Older adults are less likely to satisfy V̇O2peak criteria, which results in an underestimation of their CRF. Without adhering to standardized criteria, V̇O2peak measurement error may lead to misinterpretation of CRF and age-related associations. Here, we conclude that OUES is a reliable, valid measurement of CRF which does not require achievement of standardized criteria.
Keywords: Aged; Cardiorespiratory Fitness; Exercise Test; Female; Humans; Male; Middle Aged; Oxygen Consumption; Reproducibility of Results; Wisconsin

Odor Identification Ability Predicts PET Amyloid Status and Memory Decline in Older Adults. - Kreisl, William Charles; Jin, Peng; Lee, Seonjoo; Dayan, Ezra R; Vallabhajosula, Shankar; Pelton, Gregory; Luchsinger, Jose A; Pradhaban, Gnanavalli; Devanand, D P (J Alzheimers Dis, 2018)
BACKGROUND: Odor identification deficits occur in Alzheimer's disease (AD), as measured by the 40-item University of Pennsylvania Smell Identification Test (UPSIT). OBJECTIVE: To determine if UPSIT scores predict amyloid-β (Aβ) status, determined by 11C-Pittsburgh Compound B PET. We also compared UPSIT scores to Aβ status in predicting future memory decline. METHODS: Subjects were recruited into a longitudinal clinical prediction study. We analyzed data from those who had UPSIT, cognitive testing, PIB PET, and at least 12 months' clinical follow-up. Forty-six amnestic mild cognitive impairment patients and 25 cognitively normal controls were included. Amyloid-positivity was defined as composite PIB standardized uptake value ratio >1.5. Logistic regression and Receiver Operating Characteristic Curve analyses tested the predictive utility of impaired olfaction (defined as UPSIT score <35) and amyloid-positivity for memory decline. RESULTS: High UPSIT scores predicted absence of amyloidosis on PET, with negative predictive value of 100%. Positive predictive value of low UPSIT scores on positive Aβ status was only 41%. Both low UPSIT score (OR = 4.301, 95% CI = 1.248, 14.821, p = 0.021) and positive PET scan (OR = 20.898, 95% CI = 2.222, 196.581, p = 0.008) predicted memory decline. CONCLUSION: Individuals with high UPSIT scores are less likely to have cerebral amyloidosis or experience memory decline. Therefore, UPSIT has potential as a screening tool to determine utility of Aβ PET in clinical practice or enrollment in clinical trials. Low UPSIT score is a non-specific marker of neurodegeneration that could indicate further workup in patients with memory complaints.

PICALM Gene Methylation in Blood of Alzheimer's Disease Patients Is Associated with Cognitive Decline. - Mercorio, Roberta; Pergoli, Laura; Galimberti, Daniela; Favero, Chiara; Carugno, Michele; Dalla Valle, Elisabetta; Barretta, Francesco; Cortini, Francesca; Scarpini, Elio; Valentina, Valentina Bollati; Pesatori, Angela Cecilia (J Alzheimers Dis, 2018)
Epigenetic mechanisms might be involved in Alzheimer's disease (AD). Genetic polymorphisms in several genes, including APOE (Apolipoprotein E), PSEN1 (Presenilin 1), CR1 (Complement receptor 1), and PICALM (Phosphatidylinositol binding clathrin assembly protein), have been associated to an increased AD risk. However, data regarding methylation of these specific genes are lacking. We evaluated DNA methylation measured by quantitative bisulfite-PCR pyrosequencing in 43 AD patients and 38 healthy subjects (HS). In a multivariate age- and gender-adjusted model, PICALM methylation was decreased in AD compared to HS (mean = 3.54 and 4.63, respectively, p = 0.007). In AD, PICALM methylation level was also positively associated to Mini-Mental Scale Examination (MMSE) score (percent change 3.48%, p = 0.008). Moreover, a negative association between PICALM methylation and age was observed only in HS (percent change - 2.29%, p = 0.002). In conclusion, our data suggest a possible role of PICALM methylation in AD, particularly related to cognitive function. Given the small study sample and the associative nature of our study, further prospective investigations are required to assess the dynamics of DNA methylation in the early stages of AD development.

Possible Role of Chitin-Like Proteins in the Etiology of Alzheimer's Disease. - Lomiguen, Christine; Vidal, Luis; Kozlowski, Piotr; Prancan, Arthur; Stern, Robert (J Alzheimers Dis, 2018)
Chitin is a β-linked straight chain carbohydrate matrix monopolymer prominent in invertebrates, from fungi to arthropods. Surprisingly, chitin is now documented in vertebrates, including humans, a component of vertebrate physiology that has been neglected until now. Chitin levels are elevated in Alzheimer's disease (AD) patients, not only in the central nervous system but also in the cerebrospinal fluid and plasma. Elevated levels of chitin lectin have been reported in patients with AD. Chitinase activity varies widely in the human population. Chitin levels can increase in individuals with intrinsically low chitinase activity. Elevated amounts of chitin can reflect accumulation of the small chitin fragments that remain wherever rapid hyaluronan synthesis occurs. Another source of chitin may be from remote fungal infections. Chitin can be toxic for neurons, and its accumulation may lead to the development of AD. We present new suggestions for animal models and treatment modalities that could prove useful in future research endeavors. An unexpected connection with Gaucher's disease patients and their heterozygote relatives is also identified. These chitin-related mechanisms are novel approaches to AD whose etiology until now has defied explication.

Post Traumatic Stress Disorder Heralding the Onset of Semantic Frontotemporal Dementia. - Bonanni, Laura; Franciotti, Raffaella; Martinotti, Giovanni; Vellante, Federica; Flacco, Maria Elena; Di Giannantonio, Massimo; Thomas, Astrid; Onofrj, Marco (J Alzheimers Dis, 2018)
BACKGROUND: Post traumatic stress disorder (PTSD) is associated with cognitive decline. The dementia type following PTSD is unclear. OBJECTIVE: To assess whether PTSD is associated with a specific dementia. METHODS: Prospective study: 46 PTSD patients (DSM-IV-TR) were followed for 6-10 years with clinical, neuropsychological, imaging evaluations for possible development of dementia.Retrospective study:849 dementia patients followed during 1999-2014 (509 Alzheimer's disease, AD; 207 dementia with Lewy bodies, DLB; 90 vascular dementia, VaD; 43 frontotemporal dementia, FTD) and 287 patients with any neurological condition (including patients with/without dementia) were evaluated for the presence of PTSD in their history. RESULTS: Prospective study: 8 patients developed dementia; 1 AD, 1 DLB, 6 semantic FTD (13.0% of the PTSD population). Retrospective study: 38 patients (4.5%) had a history of PTSD; 3.5% of AD, 4.3% of DLB, 14.0% of FTD, 5.6% of VaD. The percentage was higher in FTD than in AD or DLB (χ2 = 10, p = 0.001, and χ2 = 6, p = 0.02). At difference with AD, DLB, or VaD, FTD incidence among dementia patients with PTSD history (38 patients) was higher than in the dementia population overall (16% versus 5%, χ2 = 8, p = 0.005). The impact of possible demographical/clinical confounders (age, gender, MMSE) was excluded by Poisson regression. PTSD prevalence in the comparative group without dementia matched the prevalence in the Italian general population (1.1%). PTSD prevalence in the demented comparative group matched the prevalence in our dementia retrospective cohort, 3.7%). DISCUSSION: PTSD was associated with the development of semantic FTD.

Postmortem T2*- Weighted MRI Imaging of Cortical Iron Reflects Severity of Alzheimer's Disease. - Bulk, Marjolein; Kenkhuis, Boyd; Graaf, Linda M van der; Goeman, Jelle J; Natté, Remco; Weerd, Louise van der (J Alzheimers Dis, 2018)
The value of iron-based MRI changes for the diagnosis and staging of Alzheimer's disease (AD) depends on an association between cortical iron accumulation and AD pathology. Therefore, this study determined the cortical distribution pattern of MRI contrast changes in cortical regions selected based on the known distribution pattern of tau pathology and investigated whether MRI contrast changes reflect the underlying AD pathology in the different lobes. T2*-weighted MRI was performed on postmortem cortical tissue of controls, late-onset AD (LOAD), and early-onset AD (EOAD) followed by histology and correlation analyses. Combining ex vivo high-resolution MRI and histopathology revealed that: 1) LOAD and EOAD have a different distribution pattern of AD pathological hallmarks and MRI contrast changes over the cortex, with EOAD showing more severe MRI changes; 2) per lobe, severity of AD pathological hallmarks correlates with iron accumulation, and hence with MRI. Therefore, iron-sensitive MRI sequences allow detection of the cortical distribution pattern of AD pathology ex vivo.

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Preclinical Alzheimer's Disease: Implications for Refinement of the Concept. - Vos, Stephanie J B; Visser, Pieter Jelle (J Alzheimers Dis, 2018)
Increasing interest in clinical trials and clinical research settings to identify Alzheimer's disease (AD) in the earliest stages of the disease has led to the concept of preclinical AD. Individuals with preclinical AD have AD pathology without clinical symptoms yet. Accumulating evidence has shown that biomarkers can identify preclinical AD and that preclinical AD is associated with a poor clinical outcome. Little is known yet about the role of vascular and lifestyle risk factors in the development of preclinical AD. In order to better understand preclinical AD pathology and clinical progression rates, there is a need to refine the concept of preclinical AD. This will be of great value for advancements in future research, clinical trials, and eventually clinical practice.

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Prodromal Alzheimer's Disease Demonstrates Increased Errors at a Simple and Automated Anti-Saccade Task. - Holden, John G; Cosnard, Alexandre; Laurens, Brice; Asselineau, Julien; Biotti, Damien; Cubizolle, Stéphanie; Dupouy, Sandrine; Formaglio, Maıté; Koric, Lejla; Seassau, Magali; Tilikete, Caroline; Vighetto, Alain; et al. (J Alzheimers Dis, 2018)
Saccade alterations are potential early signs of Alzheimer's disease. However, uncertainty persists in how early and reliably automated saccade recording systems detect impairments. This multicenter pathophysiological case-control transversal study explored saccade execution in carefully diagnosed amnestic mild cognitive impairment patients fulfilling research criteria for prodromal Alzheimer's disease (n = 29), as compared to both aged-matched mild Alzheimer's disease patients (n = 23) and controls (n = 27). Auto-coded saccades from horizontal (gap) vertical (step) stimulus elicited pro-saccades, and anti-saccade (gap) tasks were compared across the 3 groups. Mild cognitive impairment patients committed significantly more anti-saccade errors compared to controls (46.9 versus 24.3%, p < 0.001). Conventional analyses of the auto-coded stimulus elicited saccades parameters did not distinguish the amnestic mild cognitive impairment from controls or the mild Alzheimer's disease group. However, an offline analysis of manually coded saccade latencies, using resampling statistics did reveal subtle differences among the groups. Analysis of the manually coded data revealed that the mild Alzheimer's disease group had a reliably larger self-corrected error-rate than in amnestic mild cognitive impairment and controls (p = 0.003). Analysis of the manually coded saccade latencies, using more sensitive lognormal bootstrap analysis revealed a continuum, from amnestic mild cognitive impairment to mild Alzheimer's disease, of an increased severity of impaired inhibition of stimulus elicited saccades and correct voluntary saccade initiation. Anti-saccade error rates and psychometric measures of executive and several other cognitive functions were moderately and negatively correlated. Overall, inhibitory impairments in stimulus elicited saccades, characteristic of Alzheimer's disease, may be detected early in presumed prodromal patients using a simple, automated anti-saccade task.

The Progression of Dementia and Cognitive Decline in a Dutch 2-Year Cohort Study of People with Young-Onset Dementia. - Gerritsen, Adrie A J; Bakker, Christian; Verhey, Frans R J; Bor, Hans; Pijnenburg, Yolande A L; de Vugt, Marjolein E; Koopmans, Raymond T C M (J Alzheimers Dis, 2018)
BACKGROUND: The progression of dementia in people with young-onset dementia (YOD) is relatively unknown. OBJECTIVE: To investigate the progression of dementia and cognitive decline in the three most common subtypes in YOD and to explore which factors are associated with this course. METHODS: The course of dementia was examined in 198 people with YOD. The primary outcomes were cognitive function, as assessed by the Mini-Mental State Examination (MMSE) and dementia severity, as assessed by the Global Deterioration Scale (GDS). Mixed-model analyses were used to explore factors associated with the course of dementia of the diagnostic sub-types. RESULTS: The mean overall two-year progression of dementia severity was 0.9 GDS points, this was a statistically significant change (p = 0.012) and was not significant different for the three dementia subtypes. The mean overall two-year decline in cognitive function was 1.6 points on the MMSE. The differences in cognitive decline were statistically significant (p = 0.046) among the three diagnosis groups, AD participants showed the greatest decline, of 2.3 points. In addition to lower education (p = 0.010), higher scores on the Neuropsychiatric Inventory (NPI) sub-syndromes psychosis (p < 0.001) and hyperactivity (p = 0.002) were associated with higher rates of cognitive decline. In contrast, higher scores on the NPI affect cluster were associated with lower levels of cognitive decline (p < 0.001). CONCLUSION: Different YOD subtypes show different rates of decline in cognitive functioning, and this decline seems less progressive compared to those observed in studies in late-onset AD. Further research is needed to evaluate whether managing neuropsychiatric symptoms can positively influence the decline of cognitive function.

The Progression of Neuropsychiatric Symptoms in Alzheimer's Disease During a Five-Year Follow-Up: Kuopio ALSOVA Study. - Hallikainen, Ilona; Hongisto, Kristiina; Välimäki, Tarja; Hänninen, Tuomo; Martikainen, Janne; Koivisto, Anne M (J Alzheimers Dis, 2018)
BACKGROUND: An improved understanding of the role of neuropsychiatric symptoms (NPS) in the course of Alzheimer's disease (AD) has recently emerged. NPS lead to hospitalization and caregiver stress, but are more variable during the course of the disease than other symptoms. Knowledge about the role of specific NPS in disease progression and prognosis is especially limited. OBJECTIVES: To examine the relationship between specific NPS and AD severity during a 5-year follow-up period, and to determine which baseline NPS predict AD progression. METHODS: 236 persons with very mild (CDR 0.5) or mild (CDR 1) AD at baseline and their caregivers were followed up for five years as part of the ALSOVA study. The Neuropsychiatric Inventory was used to assess NPS, and AD severity progression was measured with the Clinical Dementia Rating Sum of Boxes. Data was analyzed with Generalized Estimated Equations and Linear Mixed Models. RESULTS: The baseline NPS that best predicted AD progression were delusions, agitation, and aberrant motor behavior, while AD severity during follow-up was associated with hallucinations, delusions, agitation, apathy, aberrant motor behavior, and sleep and appetite disturbances. CONCLUSIONS: Persons with mild AD presenting delusions, agitation, and aberrant motor behavior at the time of diagnosis could have a more rapidly progressing disease, and some NPS are associated with AD severity. These results highlight the importance of evaluating NPS at the time of AD diagnosis, and the need to offer additional support to persons presenting delusions, agitation and aberrant motor behavior, and their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety; Caregivers; Delusions; Disease Progression; Female; Finland; Hallucinations; Humans; Linear Models; Male; Motor Activity; Multivariate Analysis; Neuropsychological Tests; Severity of Illness Index

Prominent Non-Memory Deficits in Alzheimer's Disease Are Associated with Faster Disease Progression. - Scheltens, Nienke M E; Tijms, Betty M; Heymans, Martijn W; Rabinovici, Gil D; Cohn-Sheehy, Brendan I; Miller, Bruce L; Kramer, Joel H; Wolfsgruber, Steffen; Wagner, Michael; Kornhuber, Johannes; Peters, Oliver; Scheltens, Philip; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a heterogeneous disorder. OBJECTIVE: To investigate whether cognitive AD subtypes are associated with different rates of disease progression. METHODS: We included 1,066 probable AD patients from the Amsterdam Dementia Cohort (n = 290), Alzheimer's Disease Neuroimaging Initiative (n = 268), Dementia Competence Network (n = 226), and University of California, San Francisco (n = 282) with available follow-up data. Patients were previously clustered into two subtypes based on their neuropsychological test results: one with most prominent memory impairment (n = 663) and one with most prominent non-memory impairment (n = 403). We examined associations between cognitive subtype and disease progression, as measured with repeated Mini-Mental State Examination (MMSE) and Clinical Dementia Rating scale sum of boxes (CDR sob), using linear mixed models. Furthermore, we investigated mortality risk associated with subtypes using Cox proportional hazard analyses. RESULTS: Patients were 71±9 years old; 541 (51%) were female. At baseline, pooled non-memory patients had worse MMSE scores (23.1±0.1) and slightly worse CDR sob (4.4±0.1) than memory patients (MMSE 24.0±0.1; p < 0.001; CDR sob 4.1±0.1; p < 0.001). During follow-up, pooled non-memory patients showed steeper annual decline in MMSE (-2.8±0.1) and steeper annual increase in CDR sob (1.8±0.1) than memory patients (MMSE - 1.9±0.1; pinteraction<0.001; CDR sob 1.3±0.1; pinteraction<0.001). Furthermore, the non-memory subtype was associated with an increased risk of mortality compared with the memory subtype at trend level (HR = 1.36, CI = 1.00-1.85, p = 0.05). CONCLUSIONS: AD patients with most prominently non-memory impairment show faster disease progression and higher risk of mortality than patients with most prominently memory impairment.

Protective Effects of Indian Spice Curcumin Against Amyloid-β in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Grady, Mary Catherine; Mitchell, Andrew; Tonk, Sahil; Kuruva, Chandra Sekhar; Bhatti, Jasvinder Singh; Kandimalla, Ramesh; Vijayan, Murali; Kumar, Subodh; Wang, Rui; et al. (J Alzheimers Dis, 2018)
The purpose of our article is to assess the current understanding of Indian spice, curcumin, against amyloid-β (Aβ)-induced toxicity in Alzheimer's disease (AD) pathogenesis. Natural products, such as ginger, curcumin, and gingko biloba have been used as diets and dietary supplements to treat human diseases, including cancer, cardiovascular, respiratory, infectious, diabetes, obesity, metabolic syndromes, and neurological disorders. Products derived from plants are known to have protective effects, including anti-inflammatory, antioxidant, anti-arthritis, pro-healing, and boosting memory cognitive functions. In the last decade, several groups have designed and synthesized curcumin and its derivatives and extensively tested using cell and mouse models of AD. Recent research on Aβ and curcumin has revealed that curcumin prevents Aβ aggregation and crosses the blood-brain barrier, reach brain cells, and protect neurons from various toxic insults of aging and Aβ in humans. Recent research has also reported that curcumin ameliorates cognitive decline and improves synaptic functions in mouse models of AD. Further, recent groups have initiated studies on elderly individuals and patients with AD and the outcome of these studies is currently being assessed. This article highlights the beneficial effects of curcumin on AD. This article also critically assesses the current limitations of curcumin's bioavailability and urgent need for new formulations to increase its brain levels to treat patients with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blood-Brain Barrier; Curcumin; Disease Models, Animal; Humans; Mice; Neuroprotective Agents; Randomized Controlled Trials as Topic; Spices

Quality of Life, Care Resource Use, and Costs of Dementia in 8 European Countries in a Cross-Sectional Cohort of the Actifcare Study. - Handels, Ron L H; Sköldunger, Anders; Bieber, Anja; Edwards, Rhiannon Tudor; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Marques, Maria J; Meyer, Gabriele; Michelet, Mona; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With 10.5 million people with dementia in Europe and $301 billion associated costs, governments face challenges organizing access to care. OBJECTIVE: To examine the costs related to formal and informal care use and quality of life for people with dementia in eight European countries, and explore the association with unmet needs. METHODS: Cross-sectional data from 451 persons with dementia and their informal caregivers of the Actifcare cohort study were obtained. Formal and informal care use was multiplied by country specific unit prices of services. Needs were measured using the CANE and health-related quality of life (HRQOL) of the person with dementia (both self- and proxy-rated) and informal caregiver's quality of life using EQ-5D-5L, ICECAP-O, DEMQOL-U, and CarerQol utility scores. The association between costs and country, European region, and unmet needs was assessed using multi-level linear regression. RESULTS: Self-rated EQ-5D-5L utility score was higher than proxy-rated (0.84 and 0.71, respectively). Informal caregivers' utility score was 0.84. Across eight countries annual mean costs of formal and informal care were approximately € 17,000. Unmet needs were not associated with annual costs of care, nor with proxy-rated HRQOL, but were associated with self-rated HRQOL. CONCLUSION: We found varying relationships between unmet needs and quality of life, and no association between unmet needs and care costs, although the results were sensitive to various factors. Future research should further investigate the relation between unmet needs, quality of life and costs to generate a better understanding of the effects of (un)timely access to care.

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

Quantitative PET and Histology of Brain Biopsy Reveal Lack of Selective Pittsburgh Compound-B Binding to Intracerebral Amyloidoma. - Groot, Colin; Tolboom, Nelleke; Ikonomovic, Milos D; Lammertsma, Adriaan A; Boon, Baayla D C; Barkhof, Frederik; Scheltens, Philip; Klunk, William E; Rozemuller, Annemieke J M; Ossenkoppele, Rik; van Berckel, Bart N M (J Alzheimers Dis, 2018)
This single case study examines selective Pittsburgh compound-B (PiB) binding to an intracerebral light-chain amyloidoma using a 90-minute dynamic [11C]PiB-PET scan and brain biopsy tissue. Parametric non-displaceable binding potential (BPND) images showed low specific binding in the amyloidoma (BPND = 0.23), while relative tracer delivery was adequate (R1 = 0.44). Histology of the tissue revealed strong coloring with Congo-red, thioflavin-S, and X-34, indicating presence of amyloid. However, immunological staining with 6F/3D revealed absence of amyloid-β and histofluorescence of 6-CN-PiB, a highly fluorescent derivative of PiB, was at background levels. Our results suggest that PiB does not detect the atypical amyloid pathology associated with an intracerebral light-chain amyloidoma. These findings are of interest to clinicians and researchers applying [11C]PiB-PET to detect atypical forms of amyloid pathology.

Rationale and Design of the Mechanistic Potential of Antihypertensives in Preclinical Alzheimer's (HEART) Trial. - Wharton, Whitney; Goldstein, Felicia C; Tansey, Malú G; Brown, Alexandra L; Tharwani, Sonum D; Verble, Danielle D; Cintron, Amarallys; Kehoe, Patrick G (J Alzheimers Dis, 2018)
Research indicates that certain antihypertensive medications alter Alzheimer's disease (AD) biomarkers in Caucasians. The renin angiotensin system (RAS) regulates blood pressure (BP) in the body and the brain and may directly influence AD biomarkers, including amyloid-β (Aβ) neuropathology, cerebral blood flow (CBF), and inflammatory markers. This hypothesis is supported by studies, including ours, showing that antihypertensives targeting the RAS reduce the risk and slow the progression of AD in Caucasians. While mounting evidence supports a protective role of RAS medications in Caucasians, this mechanism has not been explored in African Americans. To assess the mechanism by which RAS medications modify the brain RAS, cerebrospinal fluid (CSF) Aβ, CBF, and inflammatory markers in African Americans, we are conducting an eight month, Phase Ib randomized, placebo controlled trial, enrolling 60 middle-aged (45-70 years), non-demented individuals, at risk for AD by virtue of a parental history. Participants include normotensive and treated hypertensives that have never been exposed to a RAS medication. Participants are randomized (1 : 1:1) by gender and BP medication use (yes/no) to one of three groups: placebo, or 20 mg, or 40 mg telmisartan (Micardis), to determine the dose required to penetrate the CNS. Our overarching hypothesis is that, compared to placebo, both doses of telmisartan will penetrate the CNS and produce salutary, dose dependent effects on the brain RAS as well as CSF Aβ, CBF, and CSF inflammatory markers in African Americans, over eight months. This manuscript describes the trial rationale and design.
Keywords: African Americans; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antihypertensive Agents; Biomarkers; Blood Pressure; Brain; Clinical Trials, Phase I as Topic; Female; Georgia; Humans; Linear Models; Male; Middle Aged; Randomized Controlled Trials as Topic; Renin-Angiotensin System; Telmisartan

Reaction of Amyloid-β Peptide Antibody with Different Infectious Agents Involved in Alzheimer's Disease. - Vojdani, Aristo; Vojdani, Elroy; Saidara, Evan; Kharrazian, Datis (J Alzheimers Dis, 2018)
As early as the 1980s, molecular virologist Ruth Itzhaki began to investigate if there was a causal connection between infections and neurodegenerative disorder. Although the theory has yet to be universally embraced, in 2016 Itzhaki and 33 other scientists from all over the world published a review article in this very journal presenting evidence for the causal role of pathogens in Alzheimer's disease (AD). Exactly how and in what way pathogens affect the induction of AD has yet to be determined, but one possible answer may involve the cross-reactivity of different pathogens with amyloid-β (Aβ). Aβ autoantibodies have been detected in the serum and cerebrospinal fluid of AD patients and in some healthy individuals. In the present study our major goal was to investigate whether antibodies made against Aβ would react both with other brain proteins as well as pathogens associated with AD as a result of molecular mimicry or the binding of bacterial toxins to Aβ42. Our study used a specific monoclonal antibody made against Aβ42, which not only reacted strongly with Aβ42, tau protein, and α-synuclein, but also had from weak to strong reactions with 25 different pathogens or their molecules, some of which have been associated with AD. The homology between peptide stretches of microbial origin and proteins involved in AD could be a mechanism by which antibodies to homologous peptides mount attacks against autoantigens in AD. We concluded that bacterial molecules bind to Aβ protein, forming small oligomers, then encasing pathogens and their molecules to form amyloid plaques, the tell-tale markers of AD. Conversely, these same Aβ peptides induce the production of antibodies to both Aβ42 and bacterial molecules, which may inhibit bacterial pathogenesis, but in the process may promote amyloid plaque formation.

Reduced Cerebrovascular Reserve Capacity as a Biomarker of Microangiopathy in Alzheimer's Disease and Mild Cognitive Impairment. - Urbanova, Barbora Soukupova; Schwabova, Jaroslava Paulasova; Magerova, Hana; Jansky, Petr; Marková, Hana; Vyhnálek, Martin; Laczó, Jan; Hort, Jakub; Tomek, Ales (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral microangiopathy in Alzheimer's disease (AD) causes chronic hypoperfusion and probably accelerates neurodegenerative changes. OBJECTIVE: We hypothesize microvascular impairment could be present already in mild cognitive impairment (MCI) and can be revealed using transcranial color-coded sonography (TCCS) and the breath-holding maneuver. METHODS: Three groups of subjects (AD in the stage of dementia, MCI, and cognitively normal controls) with detailed neuropsychological testing and low cerebrovascular burden (no history of stroke, no intra- or extracranial artery stenoses, and no severe vascular lesions on brain MRI), underwent a TCCS assessment of peak systolic (PSV), mean flow (MFV), and end diastolic velocities (EDV) and resistance and pulsatility indices (RI, PI) in large intracranial vessels bilaterally. Cerebrovascular reserve capacity was assessed using the breath-holding index (BHI) in middle cerebral artery (MCA) bilaterally. The ultrasound parameters were compared between the groups, correlated with neuropsychological tests, and compared between amnestic and non-amnestic MCI subtypes. RESULTS: Fourteen AD (3 males, 67.9±11.1 years, MMSE 18.0±4.6), 24 MCI (13 males, 71.9±7.3 years, MMSE 28.0±1.6), and 24 risk factor-matched controls (14 males, 67.8±6.4 years, MMSE 29.1±1.2) were enrolled. Significant differences were found between AD and controls in MFV, EDV, RI, PI in right MCA after breath holding, in PSV, MFV, EDV in left MCA after breath holding, and in BHI on the left side. The left BHI correlated positively with verbal memory test. CONCLUSION: Results show decreased cerebrovascular reserve capacity in AD as a sign of impaired cerebral hemodynamic status without severe underlying atherosclerosis. This can be identified using TCCS and BHI.

Regional White Matter Hyperintensity Influences Grey Matter Atrophy in Mild Cognitive Impairment. - Vipin, Ashwati; Foo, Heidi Jing Ling; Lim, Joseph Kai Wei; Chander, Russell Jude; Yong, Ting Ting; Ng, Adeline Su Lyn; Hameed, Shahul; Ting, Simon Kang Seng; Zhou, Juan; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
The association between cerebrovascular disease pathology (measured by white matter hyperintensities, WMH) and brain atrophy in early Alzheimer's disease (AD) remain to be elucidated. Thus, we investigated how WMH influence neurodegeneration and cognition in prodromal and clinical AD. We examined 51 healthy controls, 35 subjects with mild cognitive impairment (MCI), and 30 AD patients. We tested how total and regional WMH is related to specific grey matter volume (GMV) reductions in MCI and AD compared to controls. Stepwise regression analysis was further performed to investigate the association of GMV and regional WMH volume with global cognition. We found that total WMH volume was highest in AD but showed the strongest association with lower GMV in MCI. Frontal and parietal WMH had the most extensive influence on GMV loss in MCI. Additionally, parietal lobe WMH volume (but not hippocampal atrophy) was significantly associated with global cognition in MCI while smaller hippocampal volume (but not WMH volume) was associated with lower global cognition in AD. Thus, although WMH volume was highest in AD subjects, it had a more pervasive influence on brain structure and cognitive impairment in MCI. Our study thus highlights the importance of early detection of cerebrovascular disease, as its intervention at the MCI stage might potentially slow down neurodegeneration.

Relationship Between Amyloid-β Positivity and Progression to Mild Cognitive Impairment or Dementia over 8 Years in Cognitively Normal Older Adults. - Dang, Christa; Harrington, Karra D; Lim, Yen Ying; Ames, David; Hassenstab, Jason; Laws, Simon M; Yassi, Nawaf; Hickey, Martha; Rainey-Smith, Stephanie; Robertson, Joanne; Sohrabi, Hamid R; Salvado, Olivier; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Preclinical Alzheimer's disease (AD) is defined by cerebral amyloid-β positivity (Aβ+) in cognitively normal (CN) older adults. OBJECTIVE: To estimate the risk of progression to the symptomatic stages of AD due to PET Aβ+ and the extent that progression was influenced by other demographic, genetic, and clinical characteristics in a large prospective study. METHODS: Fine-Gray subdistribution modeling was used to examine the risk of progression from CN to MCI/dementia due to Aβ+, APOEɛ4 carriage, and their interaction in the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging CN cohort (n = 599) over 8 years. RESULTS: 17.7% Aβ+ and 8.1% Aβ-progressed over 8 years (OR: 2.43). Risk of progression for Aβ+ was 65-104% greater than Aβ-. Aβ+ APOEɛ4 carriers were at 348% greater risk than all other participants. Significant risk factors of progression in Aβ+ were age (HR: 1.05), PET SUVR (HR: 2.49) and APOE ɛ4 carriage (HR: 2.63); only age was a significant risk factor in Aβ-(HR: 1.09). Aβ-progressors were not near the threshold for Aβ+. These relationships were not moderated by hypertension, diabetes, obesity, or stroke/TIA. CONCLUSION: Aβ+ is an important prognostic marker for progression from CN to MCI/dementia in older adults and APOEɛ4 carriage provides further predictive value in the presence of Aβ+. These data suggest that Aβ-associated clinical progression is consistent with clinical-pathological models of AD, whereas progression in the absence of elevated Aβ deposition may be the result of neuropathological processes other than AD that accumulate with age.

Relationship Between Body Mass Index, ApoE4 Status, and PET-Based Amyloid and Neurodegeneration Markers in Amyloid-Positive Subjects with Normal Cognition or Mild Cognitive Impairment. - Blautzik, Janusch; Kotz, Sebastian; Brendel, Matthias; Sauerbeck, Julia; Vettermann, Franziska; Winter, Yaroslav; Bartenstein, Peter; Ishii, Kazunari; Rominger, Axel (J Alzheimers Dis, 2018)
Body weight loss in late-life is known to occur at a very early stage of Alzheimer's disease (AD). Apolipoprotein E4 (ApoE4) represents a major genetic risk factor for AD and is linked to an increased cortical amyloid-β (Aβ) accumulation. Since the relationship between body weight, ApoE4, and AD pathology is poorly investigated, we aimed to evaluate whether ApoE4 allelic status modifies the association of body mass index (BMI) with markers of AD pathology. A total of 368 Aβ-positive cognitively healthy or mild cognitive impaired subjects had undergone [18F]-AV45-PET, [18F]-FDG-PET, and T1w-MRI examinations. Composite cortical [18F]-AV45 uptake and [18F]-FDG uptake in posterior cingulate cortex were calculated as surrogates of cortical Aβ load and glucose metabolism, respectively. Multiple linear regressions were performed to assess the relationships between these PET biomarkers with BMI, present cognitive performance, and cognitive changes over time. Multivariate analysis of covariance was conducted to test for statistical differences between ApoE4/BMI categories on the PET markers and cognitive scores. In carriers of the ApoE4 allele only, BMI was inversely associated with cortical amlyoid load (β= -0.193, p < 0.005) and recent cognitive decline (β= -0.209, p < 0.05), and positively associated with cortical glucose metabolism in an AD-vulnerable region (β= 0.145, p < 0.05). ApoE4/BMI category analyses demonstrated lower Aβ load, higher posterior cingulate glucose metabolism, improved cognitive performance, and lower progression of cognitive decline in obese ApoE4 carriers. The effect of ApoE4 in promoting the accumulation of cortical amyoid, which may itself be a driver for weight loss, may be moderated by altering leptin signaling in the hypothalamus.

The Relationship between Obstructive Sleep Apnea and Alzheimer's Disease. - Andrade, Andreia G; Bubu, Omonigho M; Varga, Andrew W; Osorio, Ricardo S (J Alzheimers Dis, 2018)
Obstructive sleep apnea (OSA) and Alzheimer's disease (AD) are highly prevalent conditions with growing impact on our aging society. While the causes of OSA are now better characterized, the mechanisms underlying AD are still largely unknown, challenging the development of effective treatments. Cognitive impairment, especially affecting attention and executive functions, is a recognized clinical consequence of OSA. A deeper contribution of OSA to AD pathogenesis is now gaining support from several lines of research. OSA is intrinsically associated with disruptions of sleep architecture, intermittent hypoxia and oxidative stress, intrathoracic and hemodynamic changes as well as cardiovascular comorbidities. All of these could increase the risk for AD, rendering OSA as a potential modifiable target for AD prevention. Evidence supporting the relevance of each of these mechanisms for AD risk, as well as a possible effect of AD in OSA expression, will be explored in this review.

Relationships Between Lower Olfaction and Brain White Matter Lesions in Elderly Subjects with Mild Cognitive Impairment. - Heinrich, Juliette; Vidal, Jean-Sébastien; Simon, Axelle; Rigaud, Anne-Sophie; Hanon, Olivier; Epelbaum, Jacques; Viollet, Cécile; Duron, Emmanuelle (J Alzheimers Dis, 2018)
BACKGROUND: Olfactory impairment is reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD) and is associated with hippocampal atrophy. In elderly people, dementia with AD neuropathology and white matter lesions (WML) is common. In this context, olfactory impairment could also depend on the presence of WML. OBJECTIVE: To assess the cross-sectional relationship between olfaction and WML in elderly subjects with MCI. METHODS: Consecutive subjects, >65 years old, diagnosed as MCI after a comprehensive neuropsychological assessment in an expert memory center, with a brain MRI performed within a year and without major depressive state, were included. Olfaction was assessed by the Brief Smell Identification Test (BSIT). Two trained neuroradiologists, blind to cognitive and olfaction status, visually assessed hippocampal atrophy according to Scheltens' scale and WML according to Fazekas criteria. RESULTS: Seventy-five MCI subjects (mean age (SD) = 77.1 (6.2) years, 74.7% of women) were included. After adjustment for age and sex, factors associated with low BSIT scores were older age (p = 0.007), lower BMI (p = 0.08), lower MMSE score (p = 0.05), lower FCRST (p = 0.008), hippocampal atrophy (p = 0.04), periventricular WML (p = 0.007), and deep WML burden (p = 0.005). In multivariate analysis, severe deep WML (OR (95% CI) = 6.29 (1.4-35.13), p = 0.02) remained associated with low BSIT score independently from hippocampal atrophy. CONCLUSION: In elderly MCI subjects, low olfactory performances are associated with WML, whose progression may be slowed by vascular treatments. A longitudinal study to evaluate whether the progression of WML, hippocampal atrophy and low olfactory function, can predict accurately conversion from MCI to dementia is ongoing.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Neuropsychological Tests; Olfaction Disorders; Severity of Illness Index; White Matter

Reproducibility of Alzheimer's Disease Cerebrospinal Fluid-Biomarker Measurements under Clinical Routine Conditions. - Vogelgsang, Jonathan; Wedekind, Dirk; Bouter, Caroline; Klafki, Hans-W; Wiltfang, Jens (J Alzheimers Dis, 2018)
Analysis of cerebrospinal fluid (CSF) is one of the key tools for the state-of-the-art differential diagnosis of dementias. Dementia due to Alzheimer's disease (AD) is characterized by elevated CSF levels of total Tau (tTau) and phospho-181-Tau (pTau) and low CSF amyloid-β42 (Aβ42). Discrepancies in the laboratory analysis of human materials are well known and much effort has been put into harmonization procedures. In this study, we measured CSF biomarkers of more than 100 patients obtained under clinical routine conditions in two different clinical laboratories. The CSF biomarker levels obtained from the two different sites were significantly correlated: R2 = 0.7129 (tTau, p < 0.001), 0.7914 (pTau, p < 0.001), 0.5078 (Aβ42, p < 0.001), 0.5739 (Aβ40, p < 0.001), and 0.4308 (Aβ42/40, p < 0.001). However, the diagnostic classifications of the Aβ42, tTau, and pTau levels of identical subjects into normal versus pathological range made by the two different sites showed substantial discrepancies (31.5%, 29.6%, and 25.0% discordant cases, respectively). Applying Aβ42/40, instead of CSF Aβ42 alone, lead to a reduction of the discordant cases to 16.8%. Our findings suggest that CSF Aβ42/40 can outperform Aβ42 as a biomarker for AD neuropathology, not only under well-controlled study conditions but also in real life clinical routine. Thus, we recommend the inclusion of Aβ42/40 as a CSF biomarker in the diagnostic procedure.

A Retrospective Belgian Multi-Center MRI Biomarker Study in Alzheimer's Disease (REMEMBER). - Niemantsverdriet, Ellis; Ribbens, Annemie; Bastin, Christine; Benoit, Florence; Bergmans, Bruno; Bier, Jean-Christophe; Bladt, Roxanne; Claes, Lene; De Deyn, Peter Paul; Deryck, Olivier; Hanseeuw, Bernard; Ivanoiu, Adrian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Magnetic resonance imaging (MRI) acquisition/processing techniques assess brain volumes to explore neurodegeneration in Alzheimer's disease (AD). OBJECTIVE: We examined the clinical utility of MSmetrix and investigated if automated MRI volumes could discriminate between groups covering the AD continuum and could be used as a predictor for clinical progression. METHODS: The Belgian Dementia Council initiated a retrospective, multi-center study and analyzed whole brain (WB), grey matter (GM), white matter (WM), cerebrospinal fluid (CSF), cortical GM (CGM) volumes, and WM hyperintensities (WMH) using MSmetrix in the AD continuum. Baseline (n = 887) and follow-up (FU, n = 95) T1-weighted brain MRIs and time-linked neuropsychological data were available. RESULTS: The cohort consisted of cognitively healthy controls (HC, n = 93), subjective cognitive decline (n = 102), mild cognitive impairment (MCI, n = 379), and AD dementia (n = 313). Baseline WB and GM volumes could accurately discriminate between clinical diagnostic groups and were significantly decreased with increasing cognitive impairment. MCI patients had a significantly larger change in WB, GM, and CGM volumes based on two MRIs (n = 95) compared to HC (FU>24months, p = 0.020). Linear regression models showed that baseline atrophy of WB, GM, CGM, and increased CSF volumes predicted cognitive impairment. CONCLUSION: WB and GM volumes extracted by MSmetrix could be used to define the clinical spectrum of AD accurately and along with CGM, they are able to predict cognitive impairment based on (decline in) MMSE scores. Therefore, MSmetrix can support clinicians in their diagnostic decisions, is able to detect clinical disease progression, and is of help to stratify populations for clinical trials.

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Risk of Alzheimer's Disease in Obstructive Sleep Apnea Syndrome: Amyloid-β and Tau Imaging. - Elias, Alby; Cummins, Tia; Tyrrell, Regan; Lamb, Fiona; Doré, Vincent; Williams, Robert; Rosenfeld, J V; Hopwood, Malcolm; Villemagne, Victor L; Rowe, Christopher C (J Alzheimers Dis, 2018)
BACKGROUND: An association between obstructive sleep apnea (OSA) and Alzheimer's disease has been suggested but little is known about amyloid-β and tau deposition in this syndrome. OBJECTIVE: To determine amyloid and tau burden and cognitive function in OSA in comparison with those without a diagnosis of OSA. METHODS: The status of OSA was determined by asking participants about history of polysomnographic diagnosis of OSA and the use of Continuous Positive Airway Pressure (CPAP). A comprehensive neuropsychological battery measured cognitive function. Positron emission tomography (PET) was used to measure standardized uptake value ratio (SUVR) of 18F-florbetaben and 18F-AV1451, to quantify amyloid and tau burden. RESULTS: 119 male Vietnam veterans completed assessment. Impairment in visual attention and processing speed and increased body mass index (BMI) were seen in subjects with OSA compared with those without a diagnosis OSA. The cortical uptake of 18F-florbetaben was higher in the OSA group than in the control group (SUVR: 1.35±0.21 versus 1.27±0.16, p = 0.04). There were more apolipoprotein E ɛ4 allele (APOE ɛ4) carriers in the OSA group than in the control group. In multilinear regression analysis, the significance of OSA in predicting 18F-florbetaben uptake remained independent of age and vascular risk factors but not when BMI or APOE ɛ4 was adjusted. The reported use of CPAP (n = 14) had no effect on cognitive or amyloid PET findings. There was no significant difference in 18F-AV1451 uptake between the two groups. CONCLUSIONS: Obstructive sleep apnea is associated with Alzheimer's disease pathology, but this relationship is moderated by APOE ɛ4 and BMI.

The Role of Verb Fluency in the Detection of Early Cognitive Impairment in Alzheimer's Disease. - Alegret, Montserrat; Peretó, Mar; Pérez, Alba; Valero, Sergi; Espinosa, Ana; Ortega, Gemma; Hernandez, Isabel; Mauleón, Ana; Rosende-Roca, Maitee; Vargas, Liliana; Rodríguez-Gómez, Octavio; Abdelnour, Carla; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Verb fluency (VF) is the less commonly used fluency test, despite several studies suggesting its potential as a neuropsychological assessment tool. OBJECTIVE: To investigate the presence of VF deficits in mild cognitive impairment (MCI) and mild Alzheimer's disease (AD) dementia; to assess the usefulness of VF in the detection of cognitively healthy (CH) people who will convert to MCI, and from MCI to dementia; and to establish the VF cut-offs useful in the cognitive assessment of Spanish population. METHODS: 568 CH, 885 MCI, and 367 mild AD dementia individuals were administered the VF test and a complete neuropsychological battery. Longitudinal analyses were performed in 231 CH and 667 MCI subjects to search for VF predictors of diagnosis conversion. RESULTS: A worsening on VF performance from CH, MCI to AD dementia groups was found. Lower performances on VF were significantly related to conversion from CH to MCI/MCI to dementia. When the effect of time to conversion was analyzed, a significant effect of VF was found on the faster conversion from CH to MCI, but not from MCI to dementia. Moreover, VF cut-off scores and sensitivity/specificity values were calculated for 6 conditions (3 age ranges by 2 educational levels). CONCLUSION: The VF test may be a useful tool for the differential diagnosis of cognitive failure in the elderly. Since VF deficits seem to take place in early stages of the disease, it is a suitable neuropsychological tool for the detection not only of CH people who will convert to MCI, but also from MCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Early Diagnosis; Executive Function; Female; Humans; Language Tests; Logistic Models; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Sensitivity and Specificity; Spain

S-[18F]THK-5117-PET and [11C]PIB-PET Imaging in Idiopathic Normal Pressure Hydrocephalus in Relation to Confirmed Amyloid-β Plaques and Tau in Brain Biopsies. - Leinonen, Ville; Rauramaa, Tuomas; Johansson, Jarkko; Bottelbergs, Astrid; Tesseur, Ina; van der Ark, Peter; Pemberton, Darrel; Koivisto, Anne M; Jääskeläinen, Juha E; Hiltunen, Mikko; Herukka, Sanna-Kaisa; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Detection of pathological tau aggregates could facilitate clinical diagnosis of Alzheimer's disease (AD) and monitor drug effects in clinical trials. S-[18F]THK-5117 could be a potential tracer to detect pathological tau deposits in brain. However, no previous study have correlated S-[18F]THK-5117 uptake in PET with brain biopsy verified tau pathology in vivo. OBJECTIVE: Here we aim to evaluate the association between cerebrospinal fluid (CSF) AD biomarkers, S-[18F]THK-5117, and [11C]PIB PET against tau and amyloid lesions in brain biopsy. METHODS: Fourteen patients with idiopathic normal pressure hydrocephalus (iNPH) with previous shunt surgery including right frontal cortical brain biopsy and CSF Aβ1 - 42, total tau, and P-tau181 measures, underwent brain MRI, [11C]PIB PET, and S-[18F]THK-5117 PET imaging. RESULTS: Seven patients had amyloid-β (Aβ, 4G8) plaques, two both Aβ and phosphorylated tau (Pτ, AT8) and one only Pτ in biopsy. As expected, increased brain biopsy Aβ was well associated with higher [11C]PIB uptake in PET. However, S-[18F]THK-5117 uptake did not show any statistically significant correlation with either brain biopsy Pτ or CSF P-tau181 or total tau. CONCLUSIONS: S-[18F]THK-5117 lacked clear association with neuropathologically verified tau pathology in brain biopsy probably, at least partially, due to off-target binding. Further studies with larger samples of patients with different tau tracers are urgently needed. The detection of simultaneous Aβ and tau pathology in iNPH is important since that may indicate poorer and especially shorter response for CSF shunt surgery compared with no pathology.

Self-Reported Physical Activity is Associated with Tau Burden Measured by Positron Emission Tomography. - Brown, Belinda M; Rainey-Smith, Stephanie R; Doré, Vincent; Peiffer, Jeremiah J; Burnham, Samantha C; Laws, Simon M; Taddei, Kevin; Ames, David; Masters, Colin L; Rowe, Christopher C; Martins, Ralph N; Villemagne, Victor L (J Alzheimers Dis, 2018)
Numerous animal studies have reported exercise reduces the accumulation of Alzheimer's disease pathology, including amyloid-β (Aβ) and tau. Furthermore, we previously reported a relationship between higher levels of physical activity (PA) and lower brain Aβ burden in a human population. The recent advent of tau positron emission tomography (PET) tracers enables us to extend our investigations into the evaluation of the relationship between PA and brain tau burden. Utilizing data from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, we have examined the cross-sectional relationship between habitual PA and PET-quantified tau burden. Forty-three cognitively healthy older adults were categorized into low-moderate PA (LMPA; n = 16) or high PA (HPA; n = 27), based on self-reported PA levels. Tau PET imaging with the AV1451 tracer was conducted on all participants. The LMPA group had significantly higher neocortical tau burden (presented as a z-score; 1.22±1.98), compared to the HPA group (z-score: - 0.28±1.18). The difference between the LMPA and HPA groups was also evident when examining regional tau burden in the temporoparietal cortex and the prefrontal cortex. Our results suggest an association between self-reported PA level and brain tau burden. Future longitudinal and interventional studies utilizing larger samples sizes are vital to further investigate the nature of the relationship between tau and PA.

Separating Symptomatic Alzheimer's Disease from Depression based on Structural MRI. - Klöppel, Stefan; Kotschi, Maria; Peter, Jessica; Egger, Karl; Hausner, Lucrezia; Frölich, Lutz; Förster, Alex; Heimbach, Bernhard; Normann, Claus; Vach, Werner; Urbach, Horst; Abdulkadir, Ahmed (J Alzheimers Dis, 2018)
Older patients with depression or Alzheimer's disease (AD) at the stage of early dementia or mild cognitive impairment may present with objective cognitive impairment, although the pathology and thus therapy and prognosis differ substantially. In this study, we assessed the potential of an automated algorithm to categorize a test set of 65 T1-weighted structural magnetic resonance images (MRI). A convenience sample of elderly individuals fulfilling clinical criteria of either AD (n = 28) or moderate and severe depression (n = 37) was recruited from different settings to assess the potential of the pattern recognition method to assist in the differential diagnosis of AD versus depression. We found that our algorithm learned discriminative patterns in the subject's grey matter distribution reflected by an area under the receiver operator characteristics curve of up to 0.83 (confidence interval ranged from 0.67 to 0.92) and a balanced accuracy of 0.79 for the separation of depression from AD, evaluated by leave-one-out cross validation. The algorithm also identified consistent structural differences in a clinically more relevant scenario where the data used during training were independent from the data used for evaluation and, critically, which included five possible diagnoses (specifically AD, frontotemporal dementia, Lewy body dementia, depression, and healthy aging). While the output was insufficiently accurate to use it directly as a means for classification when multiple classes are possible, the continuous output computed by the machine learning algorithm differed between the two groups that were investigated. The automated analysis thus could complement, but not replace clinical assessments.

Single Subject Classification of Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia Using Anatomical, Diffusion Tensor, and Resting-State Functional Magnetic Resonance Imaging. - Bouts, Mark J R J; Möller, Christiane; Hafkemeijer, Anne; van Swieten, John C; Dopper, Elise; van der Flier, Wiesje M; Vrenken, Hugo; Wink, Alle Meije; Pijnenburg, Yolande A L; Scheltens, Philip; Barkhof, Frederik; Schouten, Tijn M; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: Overlapping clinical symptoms often complicate differential diagnosis between patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD). Magnetic resonance imaging (MRI) reveals disease specific structural and functional differences that aid in differentiating AD from bvFTD patients. However, the benefit of combining structural and functional connectivity measures to-on a subject-basis-differentiate these dementia-types is not yet known. METHODS: Anatomical, diffusion tensor (DTI), and resting-state functional MRI (rs-fMRI) of 30 patients with early stage AD, 23 with bvFTD, and 35 control subjects were collected and used to calculate measures of structural and functional tissue status. All measures were used separately or selectively combined as predictors for training an elastic net regression classifier. Each classifier's ability to accurately distinguish dementia-types was quantified by calculating the area under the receiver operating characteristic curves (AUC). RESULTS: Highest AUC values for AD and bvFTD discrimination were obtained when mean diffusivity, full correlations between rs-fMRI-derived independent components, and fractional anisotropy (FA) were combined (0.811). Similarly, combining gray matter density (GMD), FA, and rs-fMRI correlations resulted in highest AUC of 0.922 for control and bvFTD classifications. This, however, was not observed for control and AD differentiations. Classifications with GMD (0.940) and a GMD and DTI combination (0.941) resulted in similar AUC values (p = 0.41). CONCLUSION: Combining functional and structural connectivity measures improve dementia-type differentiations and may contribute to more accurate and substantiated differential diagnosis of AD and bvFTD patients. Imaging protocols for differential diagnosis may benefit from also including DTI and rs-fMRI.

A Small Molecule Inhibitor of Plasminogen Activator Inhibitor-1 Reduces Brain Amyloid-β Load and Improves Memory in an Animal Model of Alzheimer's Disease. - Akhter, Hasina; Huang, Wen-Tan; van Groen, Thomas; Kuo, Hui-Chien; Miyata, Toshio; Liu, Rui-Ming (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a major cause of dementia in the elderly with no effective treatment. Accumulation of amyloid-β peptide (Aβ) in the brain is a pathological hallmark of AD and is believed to be a central disease-causing and disease-promoting event. In a previous study, we showed that deletion of plasminogen activator inhibitor 1 (PAI-1), a primary inhibitor of tissue type and urokinase type plasminogen activators (tPA and uPA), significantly reduced brain Aβ load in APP/PS1 mice, an animal model of familial AD. In this study, we further show that oral administration of TM5275, a small molecule inhibitor of PAI-1, for a period of 6 weeks, inhibits the activity of PAI-1 and increases the activities of tPA and uPA as well as plasmin, which is associated with a reduction of Aβ load in the hippocampus and cortex and improvement of learning/memory function in APP/PS1 mice. Protein abundance of low density lipoprotein related protein-1 (LRP-1), a multi ligand endocytotic receptor involved in transporting Aβ out of the brain, as well as plasma Aβ42 are increased, whereas the expression and processing of full-length amyloid-β protein precursor is not affected by TM5275 treatment in APP/PS1 mice. In vitro studies further show that PAI-1 increases, whereas TM5275 reduces, Aβ40 level in the culture medium of SHSY5Y-APP neuroblastoma cells. Collectively, our data suggest that TM5275 improves memory function of APP/PS1 mice, probably by reducing brain Aβ accumulation through increasing plasmin-mediated degradation and LRP-1-mediated efflux of Aβ in the brain.

SORL1 Variants in Familial Alzheimer's Disease. - Gómez-Tortosa, Estrella; Ruggiero, María; Sainz, Ma José; Villarejo-Galende, Alberto; Prieto-Jurczynska, Cristina; Venegas Pérez, Begoña; Ordás, Carlos; Agüero, Pablo; Guerrero-López, Rosa; Pérez-Pérez, Julián (J Alzheimers Dis, 2018)
The SORL1 gene encodes a protein involved in the amyloidogenic process, and its variants have been associated with Alzheimer's disease (AD) physiopathology. We screened for SORL1 variants in 124 familial (44 early- and 80 late-onset) dementia of Alzheimer type (DAT) cases. Nine potentially pathogenic changes (three not previously reported and six rare variants) were found in nine probands (7%). After screening the control population and siblings (presence in at least 1/200 controls and/or absence of segregation pattern), a causal relationship with the disease was considered unlikely in six variants and uncertain in one. The change Trp848Ter and a splice-site variant remained likely correlated with the disease. SORL1 mutations are present in 7% of our familial DAT cohort, though in most cases cannot be considered the direct cause of the disease.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Siblings; Spain

SPARCL1 Accelerates Symptom Onset in Alzheimer's Disease and Influences Brain Structure and Function During Aging. - Seddighi, Sahba; Varma, Vijay R; An, Yang; Varma, Sudhir; Beason-Held, Lori L; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Kraut, Michael A; Davatzikos, Christos; Thambisetty, Madhav (J Alzheimers Dis, 2018)
We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer's disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression Project, we first identified two single nucleotide polymorphisms (SNPs), rs9998212 and rs7695558, associated with lower brain SPARCL1 gene expression. We then analyzed longitudinal trajectories of cognitive performance in 591 participants who remained cognitively normal (average follow-up interval: 11.8 years) and 129 subjects who eventually developed MCI or AD (average follow-up interval: 9.4 years). Cognitively normal minor allele carriers of rs7695558 who developed incident AD showed accelerated memory loss prior to disease onset. Next, we compared longitudinal changes in brain volumes (MRI; n = 120 participants; follow-up = 6.4 years; 826 scans) and resting-state cerebral blood flow (rCBF; 15O-water PET; n = 81 participants; follow-up = 7.7 years; 664 scans) in cognitively normal participants. Cognitively normal minor allele carriers of rs9998212 showed accelerated atrophy in several global, lobar, and regional brain volumes. Minor allele carriers of both SNPs showed longitudinal changes in rCBF in several brain regions, including those vulnerable to AD pathology. Our findings suggest that SPARCL1 accelerates AD pathogenesis and thus link neuroinflammation with widespread changes in brain structure and function during aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Calcium-Binding Proteins; Cerebrovascular Circulation; Cognition Disorders; Extracellular Matrix Proteins; Female; Humans; Independent Living; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Positron-Emission Tomography

Statins and Brain Health: Alzheimer's Disease and Cerebrovascular Disease Biomarkers in Older Adults. - Ramanan, Vijay K; Przybelski, Scott A; Graff-Radford, Jonathan; Castillo, Anna M; Lowe, Val J; Mielke, Michelle M; Roberts, Rosebud O; Reid, Robert I; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Vemuri, Prashanthi (J Alzheimers Dis, 2018)
BACKGROUND: Statins have been proposed to reduce the risk of Alzheimer's disease (AD). OBJECTIVE: Assess whether long-term statin use was associated with neuroimaging biomarkers of aging and dementia. METHODS: Methods: We analyzed neuroimaging biomarkers in 1,160 individuals aged 65+ from the Mayo Clinic Study of Aging, a population-based prospective longitudinal study of cognitive aging. RESULTS: Statin-treated (5+ years of therapy) individuals had greater burden of mid-and late-life cardiovascular disease (p < 0.001) than statin-untreated (≤3 months) individuals. Lower fractional anisotropy in the genu of the corpus callosum, an early marker of cerebrovascular disease, was associated with long-term statin exposure (p < 0.035). No significant associations were identified between long-term statin exposure and cerebral amyloid or tau burden, AD pattern neurodegeneration, or white matter hyperintensity burden. CONCLUSIONS: Long-term statin therapy was not associated with differences in AD biomarkers. Individuals with long-term statin exposure had worse white matter integrity in the genu of the corpus callosum, consistent with the coexistence of higher cerebrovascular risk factor burden in this group.

Subjective Cognitive Decline Is Associated with Greater White Matter Hyperintensity Volume. - van Rooden, Sanneke; van den Berg-Huysmans, Annette A; Croll, Pauline H; Labadie, Gerda; Hayes, Jessica M; Viviano, Raymond; van der Grond, Jeroen; Rombouts, Serge A R B; Damoiseaux, Jessica S (J Alzheimers Dis, 2018)
BACKGROUND: Research in older adults with subjective cognitive decline (SCD) has mainly focused on Alzheimer's disease (AD)-related MRI markers, such as hippocampal volume. However, small vessel disease (SVD) is currently established as serious comorbidity in dementia and its preliminary stages. It is therefore important to examine SVD markers in addition to AD markers in older adults presenting with SCD. OBJECTIVE: The aim of our study was to elucidate the role of SVD markers in late middle-aged to older adults with and without SCD in addition to the commonly found role of AD markers (hippocampal volume). METHODS: 67 healthy late middle-aged to older adults participated in this study (mean age 68 years); 25 participants with SCD and 42 participants without SCD. We evaluated quantitative as well as qualitative AD markers (i.e., hippocampal volume and medial temporal lobe atrophy (MTA) scale) and SVD markers (i.e., white matter hyperintensities (WMH) volume, Fazekas scale, microbleeds, and lacunar infarcts), and neuropsychological function and amount of memory complaints. RESULTS: We found a significant effect of SCD on hippocampal atrophy, as assessed using the MTA scale, but not on hippocampal volume. In addition, we found a significant effect of SCD, and amount of memory complaints, on WMH volume and Fazekas score, suggesting larger WMH volumes in participants with SCD. CONCLUSION: SVD MRI markers are related to amount of memory complaints, in addition to the commonly observed AD MRI markers, as demonstrated by the greater WMHs in healthy late middle-aged to older adults with SCD.

Synthetic Fragment of Receptor for Advanced Glycation End Products Prevents Memory Loss and Protects Brain Neurons in Olfactory Bulbectomized Mice. - Volpina, Olga M; Samokhin, Alexandr N; Koroev, Dmitriy O; Nesterova, Inna V; Volkova, Tatyana D; Medvinskaya, Natalia I; Nekrasov, Pavel V; Tatarnikova, Olga G; Kamynina, Anna V; Balasanyants, Samson M; Voronina, Tamara A; Kulikov, Alexey M; et al. (J Alzheimers Dis, 2018)
Activation of receptor for advanced glycation end products (RAGE) plays an essential role in the development of Alzheimer's disease (AD). It is known that the soluble isoform of the receptor binds to ligands and prevents negative effects of the receptor activation. We proposed that peptide fragments from RAGE prevent negative effects of the receptor activation during AD neurodegeneration. We have synthesized peptide fragments from surface-exposed regions of RAGE. Peptides were intranasally administrated into olfactory bulbectomized (OBX) mice, which developed some characteristics similar to AD neurodegeneration. We have found that only insertion of fragment (60-76) prevents the memory of OBX mice. Immunization of OBX mice with peptides showed that again only (60-76) peptide protected the memory of animals. Both intranasal insertion and immunization decreased the amyloid-β (Aβ) level in the brain. Activity of shortened fragments of (60-76) peptide was tested and showed only the (60-70) peptide is responsible for manifestation of activity. Intranasal administration of (60-76) peptide shows most protective effect on morpho-functional characteristics of neurons in the cortex and hippocampal areas. Using Flu-(60-76) peptide, we revealed its penetration in the brain of OBX mice as well as colocalization of Flu-labeled peptide with Aβ in the brain regions in transgenic mice. Flu-(60-76) peptide complex with trimer of Aβ was detected by SDS-PAGE. These data indicate that Aβ can be one of the molecular target of (60-70) peptide. These findings provide a new peptide molecule for design of anti-AD drug and for investigation of RAGE activation ways in progression of AD neurodegeneration.
Keywords: Administration, Intranasal; Animals; Behavior, Animal; Brain; Disease Models, Animal; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Neurons; Olfactory Bulb; Peptide Fragments; Receptor for Advanced Glycation End Products

A Systematic Review and Meta-Analysis on the Prevalence of Dementia in Europe: Estimates from the Highest-Quality Studies Adopting the DSM IV Diagnostic Criteria. - Bacigalupo, Ilaria; Mayer, Flavia; Lacorte, Eleonora; Di Pucchio, Alessandra; Marzolini, Fabrizio; Canevelli, Marco; Di Fiandra, Teresa; Vanacore, Nicola (J Alzheimers Dis, 2018)
BACKGROUND: Dementia, including Alzheimer's disease (AD), is one of the most burdensome medical conditions. Usually, the reviews that aim at calculating the prevalence of dementia include estimates from studies without assessing their methodological quality. Alzheimer's Disease International (ADI) proposed a score to assess the methodological quality of population-based studies aimed at estimating the prevalence of dementia. During the last three years, the European Commission has funded three projects (Eurodem, EuroCoDe, and ALCOVE) in order to estimate the prevalence of dementia in Europe. OBJECTIVE: The aim of this study was to perform a systematic review and meta-analysis of data on the prevalence of dementia in Europe derived from studies that included only subjects with a diagnosis of dementia according to the DSM IV criteria, and that had a high quality score according to ADI criteria. METHODS: We considered the studies selected by the two projects EuroCoDe (1993-2007) and Alcove (2008-2011), and we performed a new bibliographic search. For the systematic review, we only selected the subset of articles that included subjects with a diagnosis of dementia according to the DSM IV criteria. The studies were qualitatively assessed using the ADI tool. RESULTS: The meta-analysis considered 9 studies that were carried out in Europe between 1993 and 2018 including a total of 18,263 participants, of which 2,137 were diagnosed with dementia. The prevalence rate standardized for age and sex resulted 7.1%. DISCUSSION: This is the first systematic review on the prevalence of dementia in Europe considering only high-quality studies adopting the same diagnostic criteria (i.e., DSM IV).

Testamentary Capacity Assessment Tool (TCAT): A Brief Instrument for Patients with Dementia. - Papageorgiou, Sokratis G; Voskou, Panagiota; Economou, Alexandra; Beratis, Ion; Douzenis, Athanasios (J Alzheimers Dis, 2018)
BACKGROUND: In current practice, it is common for the medical practitioner to assess a person's testamentary capacity (TC) and give evidence to the Courts about a potential will contest. TC is an advanced cognitive activity that is both situation- and task-specific. OBJECTIVE: The aim of the present study was the development of a brief, specialized instrument for TC assessment in patients with dementia. METHOD: We developed a short tool consisting of four subtests, assessing the person's core functions which are required for TC: memory (orientation, autobiographical memory and realistic perception of beneficiaries), absence of serious psychopathology, knowledge of financial parameters (value of assets, everyday life products, bills), and intention (vignettes, theory of mind). For its validation, we examined 64 outpatients from the Cognitive Disorders/Dementia Unit, 2nd Department of Behavioral Neurology, University of Athens. The decision of the expert served as the gold standard for the evaluation of TC. RESULTS: Of the 64 participants, 39 were judged by the expert as capable of TC and the remaining 25 as incapable. For the total scale (maximum score of 48), the best combination of sensitivity (82.6%) and specificity (100%) was obtained for a cut-off score of 32/33. Cronbach's alpha showed high levels of internal reliability for the scale (α= 0.86) and the point-biserial correlation coefficients showed high levels of criterion-related validity (rbp = 0.797, p < 0.001). CONCLUSION: The new instrument appears to be a reliable screening tool for the evaluation of TC in dementia, which can be used by both the expert and the non-expert. Further research is needed to confirm these promising findings.
Keywords: Adult; Aged; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Mental Competency; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Sensitivity and Specificity; Wills

Three VCP Mutations in Patients with Frontotemporal Dementia. - Wong, Tsz Hang; Pottier, Cyril; Hondius, David C; Meeter, Lieke H H; van Rooij, Jeroen G J; Melhem, Shami; van Minkelen, Rick; van Duijn, Cornelia M; Rozemuller, Annemieke J M; Seelaar, Harro; Rademakers, Rosa; van Swieten, John C (J Alzheimers Dis, 2018)
Valosin-containing protein (VCP) is involved in multiple cellular activities. Mutations in VCP lead to heterogeneous clinical presentations including inclusion body myopathy with Paget's disease of the bone, frontotemporal dementia and amyotrophic lateral sclerosis, even in patients carrying the same mutation. We screened a cohort of 48 patients with familial frontotemporal dementia (FTD) negative for MAPT, GRN, and C9orf72 mutations for other known FTD genes by using whole exome sequencing. In addition, we carried out targeted sequencing of a cohort of 37 patients with frontotemporal lobar degeneration with Transactive response DNA-binding protein 43 (TDP-43) subtype from the Netherlands Brain bank. Two novel (p.Thr262Ser and p.Arg159Ser) and one reported (p.Met158Val) VCP mutations in three patients with a clinical diagnosis of FTD were identified, and were absence in population-match controls. All three patients presented with behavioral changes, with additional semantic deficits in one. No signs of Paget or muscle disease were observed. Pathological examination of the patient with VCP p.Arg159Ser mutation showed numerous TDP-43 immunoreactive (IR) neuronal intranuclear inclusions (NII) and dystrophic neurites (DN), while a lower number of NII and DN were observed in the patient with the VCP p.Thr262Ser mutation. Pathological findings of both patients were consistent with FTLD-TDP subtype D. Furthermore, only rare VCP-IR NII was observed in both cases. Our study expands the clinical heterogeneity of VCP mutations carriers, and indicates that other additional factors, such as genetic modifiers, may determine the clinical phenotype.

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

Ubisol-Q10 (a Nanomicellar Water-Soluble Formulation of CoQ10) Treatment Inhibits Alzheimer-Type Behavioral and Pathological Symptoms in a Double Transgenic Mouse (TgAPEswe, PSEN1dE9) Model of Alzheimer's Disease. - Muthukumaran, Krithika; Kanwar, Annie; Vegh, Caleb; Marginean, Alexandra; Elliott, Austin; Guilbeault, Nicholas; Badour, Alexander; Sikorska, Marianna; Cohen, Jerome; Pandey, Siyaram (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is one of the most common neurodegenerative pathologies for which there are no effective therapies to halt disease progression. Given the increase in the incidence of this disorder, there is an urgent need for pharmacological intervention. Unfortunately, recent clinical trials produced disappointing results. Molecular mechanisms of AD are converging on the notion that mitochondrial dysfunction, oxidative stress, and accumulation of dysfunctional proteins are involved in AD pathology. Previously, we have shown that a water-soluble formulation of Coenzyme Q10 (Ubisol-Q10), an integral part of the electron transport chain, stabilizes mitochondria and prevents neuronal cell death caused by neurotoxins or oxidative stress both in vitro and in vivo. In this study, we evaluated the neuroprotective effects of Ubisol-Q10 treatment in double transgenic AD mice. In the present study, we report that providing Ubisol-Q10 in drinking water (at a dose of ∼6 mg/kg/day) reduced circulating amyloid-β (Aβ) peptide, improved long term memory, preserved working spatial memory, and drastically inhibited Aβ plaque formation in 18-month-old transgenic mice compared to an untreated transgenic group. Thus Ubisol-Q10 supplementation has the potential to inhibit the progression of neurodegeneration, leading to a better quality of life for humans suffering with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Male; Maze Learning; Memory; Memory Disorders; Mice; Mice, Transgenic; Microglia; Mutation; Nerve Tissue Proteins; Peptide Fragments; Presenilin-1; Ubiquinone; Vitamins

The Unexpected Role of Aβ1-42 Monomers in the Pathogenesis of Alzheimer's Disease. - Tamagno, Elena; Guglielmotto, Michela; Monteleone, Debora; Manassero, Giusi; Vasciaveo, Valeria; Tabaton, Massimo (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) has been proposed as a biomarker and a drug target for the therapy of Alzheimer's disease (AD). The neurotoxic entity and relevance of each conformational form of Aβ to AD pathology is still under debate; Aβ oligomers are considered the major killer form of the peptide whereas monomers have been proposed to be involved in physiological process. Here we reviewed some different effects mediated by monomers and oligomers on mechanisms involved in AD pathogenesis such as autophagy and tau aggregation. Data reported in this review demonstrate that Aβ monomers could have a major role in sustaining the pathogenesis of AD and that AD therapy should be focused not only in the removal of oligomers but also of monomers.

The Uniform Data Set, Czech Version: Normative Data in Older Adults from an International Perspective. - Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Sulc, Zdenek; Vyhnálek, Martin; Bezdicek, Ondrej (J Alzheimers Dis, 2018)
BACKGROUND: Outside of the United States, international perspectives on normative data for neuropsychological test performance, within diverse populations, have been scarce. The neuropsychological test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the United States National Institute on Aging (NIA) is one of the most sensitive batteries for the evaluation of both normal cognitive aging and pathological cognitive decline. OBJECTIVE: This study aimed to determine the feasibility of the Czech Neuropsychological Test Battery from the Uniform Data Set (UDS-Cz 2.0), while also evaluating the results obtained from an international perspective. METHODS: This paper describes data from 520 cognitively normal participants. Regression analyses were used to describe the influence of demographic variables on UDS-Cz test performance. RESULTS: Cognitive performance on all measures declined with age, with patient education level serving as a protective factor. Therefore, the present study provides normative data for the UDS-Cz, adjusted for the demographic variables of age and education. CONCLUSION: The present study determines the psychometric properties of the UDS-Cz and establishes normative values in the aging Czech population, which can be used in clinical settings.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Czech Republic; Female; Humans; Internationality; Male; Middle Aged; National Institute on Aging (U.S.); Neuropsychological Tests; Psychometrics; Reference Values; Regression Analysis; United States

The Use of Mobile Games to Assess Cognitive Function of Elderly with and without Cognitive Impairment. - Bonnechère, Bruno; Van Vooren, Mélissa; Bier, Jean-Christophe; De Breucker, Sandra; Van Hove, Olivier; Van Sint Jan, Serge; Feipel, Véronique; Jansen, Bart (J Alzheimers Dis, 2018)
BACKGROUND: In the past few years numerous mobile games have been developed to train the brain. There is a lack of information about the relation between the scores obtained in these games and the cognitive abilities of the patients. OBJECTIVE: The aim of this study was to determine whether or not mobile games can be used to assess cognitive abilities of elderly. METHODS: Twenty healthy young adults, 29 old patients with cognitive impairments (Mini-Mental State Exam (MMSE) [20- 24]) and 27-aged controls participated in this study. Scores obtained in 7 mobile games were correlated with MMSE and the Addenbrooke's Cognitive Evaluation revised (ACE-R). RESULTS: Statistically significant differences were found for all games between patients with cognitive impairments and the aged controls. Correlations between the average scores of the games and the MMSE and ACE-R are significant (R = 0.72 [p < 0.001] and R = 0.81 [p < 0.001], respectively). CONCLUSION: Scores of cognitive mobile games could be used as an alternative to MMSE and ACE-R to evaluate cognitive function of aged people with and without cognitive impairment at least when MMSE is higher than 20/30.

Utility of Amyloid and FDG-PET in Clinical Practice: Differences Between Secondary and Tertiary Care Memory Units. - Lage, Carmen; Suarez, Andrea Gonzalez; Pozueta, Ana; Riancho, Javier; Kazimierczak, Martha; Bravo, María; Jimenez Bonilla, Julio; de Arcocha Torres, Marıa; Quirce, Remedios; Banzo, Ignacio; Vázquez-Higuera, José Luis; Rabinovici, Gil D; et al. (J Alzheimers Dis, 2018)
The clinical utility of amyloid positron emission tomography (PET) has not been fully established. Our aim was to evaluate the effect of amyloid imaging on clinical decision making in a secondary care unit and compare our results with a previous study in a tertiary center following the same methods. We reviewed retrospectively 151 cognitively impaired patients who underwent amyloid (Pittsburgh compound B [PiB]) PET and were evaluated clinically before and after the scan in a secondary care unit. One hundred and fifty concurrently underwent fluorodeoxyglucose (FDG)-PET. We assessed changes between the pre- and post-PET clinical diagnosis and Alzheimer's disease treatment plan. The association between PiB/FDG results and changes in management was evaluated using χ2 and multivariate logistic regression. Concordance between classification based on scan readings and baseline diagnosis was 66% for PiB and 47% for FDG. The primary diagnosis changed after PET in 17.2% of cases. When examined independently, discordant PiB and discordant FDG were both associated with diagnostic change (p < 0.0001). However, when examined together in a multivariate logistic regression, only discordant PiB remained significant (p = 0.0002). Changes in treatment were associated with concordant PiB (p = 0.009) while FDG had no effect on treatment decisions. Based on our regression model, patients with diagnostic dilemmas, a suspected non-amyloid syndrome, and Clinical Dementia Rating <1 were more likely to benefit from amyloid PET due to a higher likelihood of diagnostic change. We found that changes in diagnosis after PET in our secondary center almost doubled those of our previous analysis of a tertiary unit (9% versus 17.2%). Our results offer some clues about the rational use of amyloid PET in a secondary care memory unit stressing its utility in mild cognitive impairment patients.

Utility of an Alzheimer's Disease Risk-Weighted Polygenic Risk Score for Predicting Rates of Cognitive Decline in Preclinical Alzheimer's Disease: A Prospective Longitudinal Study. - Porter, Tenielle; Burnham, Samantha C; Milicic, Lidija; Savage, Greg; Maruff, Paul; Lim, Yen Ying; Li, Qiao-Xin; Ames, David; Masters, Colin L; Rainey-Smith, Stephanie; Rowe, Christopher C; Salvado, Olivier; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With the exception of APOE, genetic variants associated with increased Alzheimer's disease (AD) risk are characterized by small effect sizes. Polygenic risk scores (PRS) have shown utility in predicting AD risk; however, their utility for predicting decline in cognition at preclinical stages of AD is poorly understood. OBJECTIVE: To validate associations of a 22-variant AD-risk-weighted PRS with AD risk and related biomarkers and to assess its utility to predict cognitive decline. METHODS: The PRS was evaluated with respect to brain amyloid-β (Aβ) burden, cerebrospinal fluid (CSF) Aβ42, total-tau, and phospho-tau, and decline in cognition in 643 (570 cognitively normal (CN), 73 AD) PET-imaged participants from the longitudinal Australian Imaging, Biomarkers and Lifestyle (AIBL) Study of Ageing. Cognition was assessed using three composite measures; global cognition, verbal episodic memory, and a Pre-Alzheimer's Cognitive Composite (PACC). RESULTS: PRS, both with and without APOE, were positively correlated with brain Aβ burden, CSF total-tau, and phospho-tau in CN older adults. Further, in CN biomarker positive (Aβhigh) participants, significant associations were observed with baseline and longitudinal cognition. However, this association was not observed after the removal of APOE. Partitioning the PRS into quartiles revealed that the PRS associations with cognitive decline in Aβhigh CN older adults is due to a saturating effect of APOE genotype. CONCLUSIONS: An AD-risk-weighted PRS is associated with cognitive decline in CN older adults. However, this association is absent when APOE genotype is excluded from the PRS, suggesting that associations with cognitive decline in this model of polygenic risk are driven by APOE genotype alone. Further research is needed to define appropriate PRSs with greater utility for predicting preclinical AD cognitive decline.

Visit-To-Visit Blood Pressure Variability and the Risk of Dementia in Older People. - van Middelaar, Tessa; van Dalen, Jan W; van Gool, Willem A; van den Born, Bert-Jan H; van Vught, Lonneke A; Moll van Charante, Eric P; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: High visit-to-visit variability (VVV) in blood pressure (BP) is associated with cerebrovascular lesions on neuroimaging. OBJECTIVE: Our primary objective was to investigate whether VVV is associated with incident all-cause dementia. As a secondary objective, we studied the association of VVV with cognitive decline and cardiovascular disease (CVD). METHODS: We included community-dwelling people (age 70-78 year) from the 'Prevention of Dementia by Intensive Vascular Care' (preDIVA) trial with three to five 2-yearly BP measurements during 6-8 years follow-up. VVV was defined using coefficient of variation (CV; SD/mean×100). Cognitive decline was assessed using the Mini-Mental State Examination (MMSE). Incident CVD was defined as myocardial infarction or stroke. We used a Cox proportional hazard regression and mixed-effects model adjusted for sociodemographic factors and cardiovascular risk factors. RESULTS: In 2,305 participants (aged 74.2±2.5), mean systolic BP over all available visits was 150.1 mmHg (SD 13.6), yielding a CV of 9.0. After 6.4 years (SD 0.8) follow-up, 110 (4.8%) participants developed dementia and 140 (6.1%) CVD. Higher VVV was not associated with increased risk of dementia (hazard ratio [HR] 1.00 per point CV increase; 95% confidence interval [CI] 0.96-1.05), although the highest quartile of VVV was associated with stronger decline in MMSE (β -0.09, 95% CI -0.17 to -0.01). Higher VVV was associated with incident CVD (HR 1.07; 95% CI 1.04-1.11). CONCLUSION: In our study among older people, high VVV is not associated with incident all-cause dementia. It is associated with decline in MMSE and incident CVD.
Keywords: Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Dementia; Female; Humans; Hypertension; Incidence; Male; Netherlands; Proportional Hazards Models; Risk Factors

Visualization of Focal Thinning of the Ganglion Cell-Inner Plexiform Layer in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Shao, Yi; Jiang, Hong; Wei, Yantao; Shi, Yingying; Shi, Ce; Wright, Clinton B; Sun, Xiaoyan; Vanner, Elizabeth A; Rodriguez, Anny D; Lam, Byron L; Rundek, Tatjana; Baumel, Barry S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A detailed analysis of the tomographic thickness of intraretinal layers may provide more information on neurodegeneration in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD). OBJECTIVE: The goal was to analyze tomographic thickness patterns of intraretinal layers in patients with AD andMCI. METHOD: Forty-nine patients (25 AD and 24 MCI) and 21 cognitively normal (CN) controls were imaged using ultra-high-resolution optical coherence tomography to obtain volumetric data centered on the fovea. The segmented intraretinal layers were retinal nerve fiber layer (RNFL), ganglion cell- inner plexiform layer (GCIPL), inner nuclear layer (INL), outer nuclear layer (ONL), outer plexiform layer (OPL), and retinal photoreceptor (PR), in addition to the total retinal thickness(TRT). RESULTS: The thickness differences were negative (thinning) mainly in TRT, RNFL, and GCIPL in both AD and MCI groups in comparison to CN, while the thickness differences were positive (thickening) mainly in ONL and PR in AD. GCIPL of AD and MCI was thinner in superior, nasal superior, and temporal superior quadrants, compared to CN (p < 0.05). GCIPL of the inner superior, inner nasal superior, inner temporal superior, and outer nasal superior sectors was significantly thinner in AD than CN (p < 0.05). GCIPL of the outer superior, inner temporal superior, outer nasal, and temporal superior sectors was significantly thinner in MCI than CN (p < 0.05). CONCLUSION: Focal thinning of the GCIPL was visualized and quantified by detailed partitions in AD and MCI, which provides specific information about neurodegeneration in MCI and AD.

Volume and Connectivity of the Ventral Tegmental Area are Linked to Neurocognitive Signatures of Alzheimer's Disease in Humans. - De Marco, Matteo; Venneri, Annalena (J Alzheimers Dis, 2018)
BACKGROUND: There is an urgent need to identify the earliest biological changes within the neuropathological cascade of Alzheimer's disease (AD) processes. Recent findings in a murine model of AD showed significant preclinical loss of dopaminergic neurons in the ventral tegmental area (VTA), accompanied by reduced hippocampal innervation and declining memory. It is unknown if these observations can be translated in humans. OBJECTIVE: We tested the hypothesis that VTA volume is associated with the typical clinical markers of AD in a cohort of patients and healthy controls. METHODS: Structural and resting state functional MRI scans, and neuropsychological scores were acquired for 51 healthy adults, 30 patients with a diagnosis of mild cognitive impairment, and 29 patients with a diagnosis of AD dementia. VTA volume was quantified together with other control nuclei. The association between nuclei volume, hippocampal size, memory performance, and linguistic-executive skills was tested. The effect of VTA functional connectivity was also tested. RESULTS: VTA size, but not of control nuclei, yielded a strong association with both hippocampal size and memory competence (but not linguistic-executive performance), and this was particularly strong in healthy adults. In addition, functional connectivity between the VTA and hippocampus was significantly associated with both markers of AD. CONCLUSION: Diminished dopaminergic VTA activity may be crucial for the earliest pathological features of AD and might suggest new strategies for early treatment. Memory encoding processes may represent cognitive operations susceptible to VTA neurodegeneration.

White Matter Hyperintensities and Cognition in Mild Cognitive Impairment and Alzheimer's Disease: A Domain-Specific Meta-Analysis. - van den Berg, Esther; Geerlings, Mirjam I; Biessels, Geert Jan; Nederkoorn, Paul J; Kloppenborg, Raoul P (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMHs) are related to cognitive dysfunction in the general population. The clinical relevance of WMHs in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI) is, however, unclear. OBJECTIVE: This meta-analysis aimed to quantify the association of WMHs and specific cognitive domains in patients with MCI or AD. METHODS: PubMed (January 1990-January 2017) was searched for studies that used MRI to quantify WMHs, and measured cognitive functioning (≥1 predefined cognitive domain with ≥1 test) in a well-defined population of persons diagnosed with MCI or AD. Fischer's Z was used as the common metric for effect size. Modifying effects of demographics, MMSE, and WMH location were examined. RESULTS: Twelve cross-sectional studies on AD (total n = 1,370, median age 75 years) and 10 studies on MCI (9 cross-sectional, 1 longitudinal; total n = 2,286, median age 73 years) were included. The association between WMHs and overall cognition was significantly stronger for MCI (-0.25, -0.36 to -0.14) than for AD (-0.11, -0.14 to -0.08; QM = 10.7, p < 0.05). For both groups, largest effect sizes were found in attention and executive functions (-0.26, -0.36 to -0.15) and processing speed (-0.21, -0.35 to -0.12). No significant modifying effects of age and gender were found. CONCLUSION: WMHs have a medium-sized association with different cognitive functions in patients with MCI and a small, but statistically significant, association with cognition in AD. These result underscore the role of co-occurring vascular brain damage in MCI and AD.

Aberrant Co-localization of Synaptic Proteins Promoted by Alzheimer's Disease Amyloid-β Peptides: Protective Effect of Human Serum Albumin. - Domínguez-Prieto, Marta; Velasco, Ana; Vega, Lourdes; Tabernero, Arantxa; Medina, José M (J Alzheimers Dis, 2017)
Amyloid-β (Aβ), Aβ40, Aβ42, and, recently, Aβ25-35 have been directly implicated in the pathogenesis of Alzheimer's disease. We have studied the effects of Aβ on neuronal death, reactive oxygen species (ROS) production, and synaptic assembling in neurons in primary culture. Aβ25-35, Aβ40, and Aβ42 significantly decreased neuronal viability, although Aβ25-35 showed a higher effect. Aβ25-35 showed a more penetrating ability to reach mitochondria while Aβ40 did not enter the neuronal cytosol and Aβ42 was scarcely internalized. We did not observe a direct correlation between ROS production and cell death because both Aβ40 and Aβ42 decreased neuronal viability but Aβ40 did not change ROS production. Rather, ROS production seems to correlate with the penetrating ability of each Aβ. No significant differences were found between Aβ40 and Aβ42 regarding the extent of the deleterious effects of both peptides on neuronal viability or synaptophysin expression. However, Aβ40 elicited a clear delocalization of PSD-95 and synaptotagmin from prospective synapsis to the neuronal soma, suggesting the occurrence of a crucial effect of Aβ40 on synaptic disassembling. The formation of Aβ40- or Aβ42-serum albumin complexes avoided the effects of these peptides on neuronal viability, synaptophysin expression, and PSD-95/synaptotagmin disarrangement suggesting that sequestration of Aβ by albumin prevents deleterious effects of these peptides. We can conclude that Aβ borne by albumin can be safely transported through body fluids, a fact that may be compulsory for Aβ disposal by peripheral tissues.

Adherence to Clinical Practice Guidelines during Dementia Work-Up in a Real-World Setting: A Study from the Registry of Dementias of Girona. - Turró-Garriga, Oriol; Calvó-Perxas, Laia; Vilalta-Franch, Joan; Hernández-Ferrándiz, Marta; Flaqué, Margarita; Linares, Marta; Cullell, Marta; Gich, Jordi; Casas, Isabel; Perkal, Héctor; Garre-Olmo, Josep (J Alzheimers Dis, 2017)
BACKGROUND: There are several position statements and clinical practice guidelines (CPG) for diagnosing dementia. OBJECTIVE: Our aims were to evaluate the adherence to CPG among specialists in the 7 memory clinics included in the Registry of Dementias of Girona (ReDeGi), and to compare the results between 2007-2011 and 2012-2015. We also determined the time and number of visits required to achieve a diagnosis, the supplementary tests ordered, and the drugs prescribed according to dementia subtypes. METHODS: Medical charts of a stratified random sample of 475 ReDeGi cases were reviewed. Basic dementia work-up was evaluated using as a reference evidence-based CPG. An Index of Adherence (AI) was calculated using the following items in the medical chart: cognitive symptomatology; functional disability evaluation; physical examination; neurological examination; psychiatric examination; brief cognitive examination; activities of daily living performance examination; blood test; structural neuroimaging (CT-scan or MRI). RESULTS: The mean AI to CPG among specialists was of 8.2 points, and it improved from 7.9 points in 2007-2011 to 8.5 points in 2012-2015 (Cohen's d = 0.46). A lower adherence was detected in the most severe cases. A dementia diagnosis required 3.5 visits, regardless of the subtype of dementia, although milder cases required more time, more visits, and more supplementary tests than severe cases. CONCLUSION: The adherence to CPG in the catchment area of the ReDeGi is high, and an epidemiological surveillance system such as the ReDeGi may help in improving it. Dementia guidelines should establish procedures adapted to clinical practice, with simplified recommendations for most severe cases.

Alterations in the Peripheral Immune System in Dementia. - Busse, Mandy; Michler, Enrico; von Hoff, Franz; Dobrowolny, Henrik; Hartig, Roland; Frodl, Thomas; Busse, Stefan (J Alzheimers Dis, 2017)
Alterations in the immune response that result in inflammation might play a role in the pathology of dementias. In order to analyze changes of the peripheral immune system associated with different types of dementias, we determined several innate and adaptive cell populations in whole blood using flow cytometry. We included patients with Alzheimer's disease (AD; n = 60), vascular dementia (VaD; n = 20), and frontotemporal dementia (FTD; n = 12) at the time point of diagnosis and 24 age-matched neuropsychiatric healthy persons. Monocytes and NK cells were diminished in VaD, but not in AD and FTD. B cell and T cell numbers were decreased in all investigated forms of dementia. Changes in the contribution of naïve/memory T cells were only present in AD. Correlation and regression analyses revealed associations between altered immune cell populations and Q Albumin as marker for the integrity of the blood-cerebrospinal fluid-barrier, Mini-Mental State Examination values, and age. The peripheral immune system is altered in AD, VaD, and FTD. However, each disorder presents unique changes in the investigated cell types indicating different mechanisms underlying the pathology.

Alterations of Clock Gene RNA Expression in Brain Regions of a Triple Transgenic Model of Alzheimer's Disease. - Bellanti, Francesco; Iannelli, Giuseppina; Blonda, Maria; Tamborra, Rosanna; Villani, Rosanna; Romano, Adele; Calcagnini, Silvio; Mazzoccoli, Gianluigi; Vinciguerra, Manlio; Gaetani, Silvana; Giudetti, Anna Maria; Vendemiale, Gianluigi; et al. (J Alzheimers Dis, 2017)
A disruption to circadian rhythmicity and the sleep/wake cycle constitutes a major feature of Alzheimer's disease (AD). The maintenance of circadian rhythmicity is regulated by endogenous clock genes and a number of external Zeitgebers, including light. This study investigated the light induced changes in the expression of clock genes in a triple transgenic model of AD (3×Tg-AD) and their wild type littermates (Non-Tg). Changes in gene expression were evaluated in four brain areas¾suprachiasmatic nucleus (SCN), hippocampus, frontal cortex and brainstem¾of 6- and 18-month-old Non-Tg and 3×Tg-AD mice after 12 h exposure to light or darkness. Light exposure exerted significant effects on clock gene expression in the SCN, the site of the major circadian pacemaker. These patterns of expression were disrupted in 3×Tg-AD and in 18-month-old compared with 6-month-old Non-Tg mice. In other brain areas, age rather than genotype affected gene expression; the effect of genotype was observed on hippocampal Sirt1 expression, while it modified the expression of genes regulating the negative feedback loop as well as Rorα, Csnk1ɛ and Sirt1 in the brainstem. In conclusion, during the early development of AD, there is a disruption to the normal expression of genes regulating circadian function after exposure to light, particularly in the SCN but also in extra-hypothalamic brain areas supporting circadian regulation, suggesting a severe impairment of functioning of the clock gene pathway. Even though this study did not demonstrate a direct association between these alterations in clock gene expression among brain areas with the cognitive impairments and chrono-disruption that characterize the early onset of AD, our novel results encourage further investigation aimed at testing this hypothesis.

Alzheimer's Disease Genetics and ABCA7 Splicing. - Vasquez, Jared B; Simpson, James F; Harpole, Ryan; Estus, Steven (J Alzheimers Dis, 2017)
Both common and rare polymorphisms within ABCA7 have been associated with Alzheimer's disease (AD). In particular, the rare AD associated polymorphism rs200538373 was associated with altered ABCA7 exon 41 splicing and an AD risk odds ratio of ∼1.9. To probe the role of this polymorphism in ABCA7 splicing, we used minigene studies and qPCR of human brain RNA. We report aberrant ABCA7 exon 41 splicing in the brain of a carrier of the rs200538373 minor C allele. Moreover, minigene studies show that rs200538373 acts as a robust functional variant in vitro. Lastly, although the ABCA7 isoform with an extended exon 41 is predicted to undergo nonsense mediated RNA decay, this was not supported by qPCR analyses, which showed relatively normal ABCA7 mRNA levels in the carrier of the rs200538373 minor C allele. In summary, rs200538373 is a functional polymorphism that alters ABCA7 exon 41 splicing without grossly altering the level of ABCA7 mRNA.

Alzheimer's Disease in the Latino Community: Intersection of Genetics and Social Determinants of Health. - Vega, Irving E; Cabrera, Laura Y; Wygant, Cassandra M; Velez-Ortiz, Daniel; Counts, Scott E (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common type of dementia among individuals 65 or older. There are more than 5 million diagnosed cases in the US alone and this number is expected to triple by 2050. Therefore, AD has reached epidemic proportions with significant socioeconomic implications. While aging in general is the greatest risk factor for AD, several additional demographic factors that have contributed to the rise in AD in the US are under study. One such factor is associated with the relatively fast growth of the Latino population. Several reports indicate that AD is more prevalent among blacks and Latinos. However, the reason for AD disparity among different ethnic groups is still poorly understood and highly controversial. The Latino population is composed of different groups based on nationality, namely South and Central America, Mexico, and Caribbean Hispanics. This diversity among the Latino population represents an additional challenge since there are distinct characteristics associated with AD and comorbidities. In this review, we aim to bring attention to the intersection between social determinants of health and genetic factors associated with AD within the Latino community. We argue that understanding the interplay between identified social determinants of health, co-morbidities, and genetic factors could lead to community empowerment and inclusiveness in research and healthcare services, contributing to improved diagnosis and treatment of AD patients. Lastly, we propose that inserting a neuroethics perspective could help understand key challenges that influence healthcare disparities and contribute to increased risk of AD among Latinos.

Alzheimer's Disease: The Alternative Serotonergic Hypothesis of Cognitive Decline. - Vakalopoulos, Costa (J Alzheimers Dis, 2017)
The pathognomonic feature of Alzheimer's disease is a loss of declarative memory. This has generally been attributed to early involvement of medial temporal lobe structures with neurofibrillary tangles and loss of neurons in the entorhinal cortex. However, there has been a re-emerging emphasis on the causal role of brainstem monoaminergic nuclei as involvement of the cholinergic basal forebrain loses prominence. The rejection of this latter theory of cognitive decline is related to inconsistencies in time course and modest effects of treatment using cholinergic agents. The amyloid hypothesis of cortical dysfunction is also losing favor as current trials of plaque dissolution are proving again disappointing. Recent pre-clinical studies on APP/PS1 (familial Alzheimer's disease) transgenic mouse models using serotonergic receptor modulating agents, demonstrate clear neuroprotective effects. The involvement of midbrain raphe in the earliest stages of dementia requires a reassessment of relevant pathophysiology beyond behavioral and affective dimensions. Indeed, a theory of serotonergic modulation of explicit memory formation by direct enhancement of synaptic strength could change the view of the role of these nuclei in AD and lead to more effective treatments.

Alzheimer's Disease-Related Polymorphisms in Shunt-Responsive Idiopathic Normal Pressure Hydrocephalus. - Huovinen, Joel; Helisalmi, Seppo; Paananen, Jussi; Laiterä, Tiina; Kojoukhova, Maria; Sutela, Anna; Vanninen, Ritva; Laitinen, Marjo; Rauramaa, Tuomas; Koivisto, Anne M; Remes, Anne M; Soininen, Hilkka; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is a late onset, surgically treated progressive brain disease caused by impaired cerebrospinal fluid dynamics and subsequent ventriculomegaly. Comorbid Alzheimer's disease (AD) seems to be frequent in iNPH. OBJECTIVE: We aim to evaluate the role of AD-related polymorphisms in iNPH. METHODS: Overall 188 shunt-operated iNPH patients and 688 controls without diagnosed neurodegenerative disease were included into analysis. Twenty-three single-nucleotide polymorphisms (SNPs FRMD4A [rs7081208_A, rs2446581_A, rs17314229_T], CR1, BIN, CD2AP, CLU, MS4A6A, MS4A4E, PICALM, ABCA7, CD33, INPP5D, HLA_DRB5, EPHA1, PTK2B, CELF1, SORL1, FERMT2, SLC24A, DSG2, CASS4, and NME8) adjusted to APOE were analyzed between groups by using binary logistic regression analysis. Neuroradiological characteristics and AD-related changes in the right frontal cortical brain biopsies were available for further analysis. RESULTS: Logistic regression analysis adjusted to age, gender, and other SNPs indicated allelic variation of NME8 between iNPH patients and non-demented controls (p = 0.014). The allelic variation of NME8 was not related to the neuropathological changes in the brain biopsies of iNPH patients. However, periventricular white matter changes (p = 0.017) were more frequent in the iNPH patients with the AA-genotype, an identified risk factor of AD. CONCLUSIONS: Our findings increase the evidence that iNPH is characterized by genetic and pathophysiological mechanisms independent from AD. Considering that NME8 plays a role in the ciliary function and displays SNP-related diversity in white matter changes, the mechanisms of NME8 in iNPH and other neurodegenerative processes are worth further study.

Antibodies to Signaling Molecules and Receptors in Alzheimer's Disease are Associated with Psychomotor Slowing, Depression, and Poor Visuospatial Function. - Giil, Lasse M; Vedeler, Christian A; Kristoffersen, Einar K; Nordrehaug, Jan Erik; Heidecke, Harald; Dechend, Ralf; Schulze-Forster, Kai; Muller, Dominik N; von Goetze, Victoria S; Cabral-Marques, Otavio; Riemekasten, Gabriela; Vogelsang, Petra; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with several antibodies as well as signaling molecules and receptors. These may be detrimental in the presence of a disrupted blood-brain barrier (BBB). OBJECTIVE: To investigate whether the levels of antibodies toward 33 signaling molecules involved in neurotransmitter, vascular, and immune functions were associated with AD and, within the AD group; cognitive function and mood. METHODS: Antibodies in sera from patients with mild AD [(n = 91) defined as a Mini-Mental State Examination ≥ 20 or a Clinical Dementia Rating Scale≤1] and healthy controls (n = 102) were measured with enzyme-linked immunosorbent assays. Levels in AD and controls were compared by Mann-Whitney test. In the AD group, associations between antibodies and psychometric test scores were analyzed by robust regression. The false discovery threshold was set to 0.05. RESULTS: Antibodies to serotonin receptors [5-HT2AR (effect size (r) = 0.21, p = 0.004), 5-HT2CR (r = 0.25, p = 0.0005) and 5-HT7R (r = 0.21, p = 0.003)], vascular endothelial growth factor receptor 1 [VEGFR1 (r = 0.29, p < 0.001)] and immune-receptors (Stabilin-1 (r = 0.23, p = 0.001) and C5aR1 (r = 0.21, p = 0.004) were higher in AD. Psychomotor speed was associated with D1R-abs (β 0.49, p < 0.001), depression with ETAR-abs (β 0.31, p < 0.001), and visuospatial function with 5-HT1AR-abs (β 0.27, p = 0.004) despite similar antibody levels compared to controls. CONCLUSIONS: Antibody levels to VEGFR1, serotonergic receptors, and receptors in the immune system were increased in AD. Antibodies at similar levels as in controls were associated cognitive dysfunction and depression in AD.

Aortic Valve Calcification and the Risk of dementia: A Population-Based Study. - Wolters, Frank J; Bos, Daniel; Vernooij, Meike W; Franco, Oscar H; Hofman, Albert; Koudstaal, Peter J; van der Lugt, Aad; Ikram, M Arfan (J Alzheimers Dis, 2017)
The association of aortic valve calcification (AVC) with dementia remains unknown. In 2,428 non-demented participants from the population-based Rotterdam Study, we investigated the association of CT-assessed AVC with risk of dementia and cognitive decline. AVC was present in 33.1% of the population. During a median follow-up of 9.3 years, 160 participants developed dementia. We found no association between presence of AVC and risk of all-cause dementia [hazard ratio (HR): 0.89 (95% confidence interval (CI):0.63;1.26)]. Presence of AVC was not associated with cognitive decline on any of the cognitive tests, nor with a measure of global cognition.

APOEɛ4 Genotype, Amyloid, and Clinical Disease Progression in Cognitively Normal Older Adults. - Hollands, Simone; Lim, Yen Ying; Laws, Simon M; Villemagne, Victor L; Pietrzak, Robert H; Harrington, Karra; Porter, Tenielle; Snyder, Peter; Ames, David; Fowler, Christopher; Rainey-Smith, Stephanie R; Martins, Ralph N; et al. (J Alzheimers Dis, 2017)
BACKGROUND: In cognitively normal (CN) older adults, carriage of the apolipoprotein E (APOE) ɛ4 allele is associated with increased risk for dementia of the Alzheimer type (AD-dementia). It is unclear whether this occurs solely through APOEɛ4 increasing amyloid-β (Aβ) accumulation or through processes independent of Aβ. OBJECTIVE: To determine the extent and nature to which APOEɛ4 increases risk for clinical disease progression in CN older adults. METHODS: Data from the total (n = 765) and Aβ-imaged (n = 423) CN cohort in the Australian Imaging, Biomarker and Lifestyle (AIBL) Study of Ageing was analyzed using Cox proportional hazard models to estimate ɛ4 risk for clinical disease progression over a 72-month follow-up. RESULTS: With Aβ status unknown and risk from demographic characteristics controlled, ɛ4 carriage increased risk for clinical disease progression over 72 months by 2.66 times compared to risk of non-ɛ4 carriage. Re-analysis with Aβ status included showed that abnormally high Aβ increased risk for clinical disease progression over 72 months by 2.11 times compared to risk of low Aβ. However, with Aβ level known, ɛ4 carriage was no longer predictive of clinical disease progression. CONCLUSION: In CN older adults, the risk of ɛ4 for clinical disease progression occurs through the effect of ɛ4 increasing Aβ levels.

Apolipoprotein A1 in Cerebrospinal Fluid and Plasma and Progression to Alzheimer's Disease in Non-Demented Elderly. - Slot, Rosalinde E R; Van Harten, Argonde C; Kester, Maartje I; Jongbloed, Wesley; Bouwman, Femke H; Teunissen, Charlotte E; Scheltens, Philip; Veerhuis, Robert; van der Flier, Wiesje M (J Alzheimers Dis, 2017)
BACKGROUND: HDL-cholesterol transporter Apolipoprotein A1 (ApoA1) holds neuroprotective properties, such as inhibition of amyloid-β aggregation. Low plasma ApoA1 concentrations are associated with Alzheimer's disease (AD). Little is known about ApoA1 levels in the pre-dementia stages of AD. OBJECTIVE: To investigate associations between cerebrospinal fluid (CSF) and plasma ApoA1 levels and clinical progression toward AD in non-demented elderly. METHODS: From the Amsterdam Dementia Cohort, we included 429 non-demented elderly with subjective cognitive decline (SCD; n = 206, 61±9 years, Mini-Mental State Exam (MMSE) 28±2) and mild cognitive impairment (MCI; n = 223, 67±8 years, MMSE 27±2), with a mean follow-up of 2.5±1.6 years. We used Cox proportional hazard models to investigate relations between CSF and plasma ApoA1 concentrations and clinical progression, defined as progression to MCI or AD for SCD, and progression to AD for MCI. Analyses were adjusted for age, gender, MMSE, and plasma cholesterol levels. Analyses were stratified for diagnosis and APOEɛ4 carriership. RESULTS: 117 patients (27%) showed clinical progression. One standard deviation increase of CSF ApoA1 was associated with a 30% increased risk of clinical progression (hazard ratio (HR) (95% CI)  = 1.3(1.0-1.6)). The effect appeared to be attributable to the APOEɛ4 carriers with SCD (HR 3.3(1.0-10.9)). Lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD (HR 5.0(1.3-18.9)). CONCLUSION: Higher CSF and lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD; suggesting that ApoA1 may be involved in the earliest stages of AD.

Association between Cognitive Status before Surgery and Outcomes in Elderly Patients with Hip Fracture in a Dedicated Orthogeriatric Care Pathway. - Zerah, Lorene; Cohen-Bittan, Judith; Raux, Mathieu; Meziere, Anthony; Tourette, Cendrine; Neri, Christian; Verny, Marc; Riou, Bruno; Khiami, Frederic; Boddaert, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is associated with a worse prognosis of hip fracture, but the impact of a dedicated geriatric care pathway on the prognosis of these patients has not been evaluated. OBJECTIVE: According to the cognitive status before surgery, our main objective was to compare mortality rate at 6 months; secondary outcomes were to compare in-hospital complications, the risk of new institutionalization, and the ability to walk at 6 months. METHODS: Between 2009 and 2015, all patients (>70 years) admitted after hip fracture surgery into a dedicated unit of peri-operative geriatric care were included: patients with dementia (DP), without dementia (NDP), and with cognitive status not determined (CSND). Data are expressed as hazard ratio (HR) for multivariate cox analysis or odds ratio (OR) for multivariate logistic regression analysis and their 95% confidence interval (CI). RESULTS: We included 650 patients (86±6 years): 168 DP, 400 NDP, and 82 CSND. After adjustment for age, sex, comorbidities, polypharmacy, pre-fracture autonomy, time-to-surgery, and delirium, there were no significant differences for 6-month mortality (DP versus NDP: HR = 0.7[0.4-1.2], DP versus CSND: HR = 0.6[0.3-1.4], CSND versus NDP: HR = 0.8[0.4-1.7]); but DP and CSND were more likely to be newly institutionalized after 6 months compared to NDP (OR DP = 2.6[1.4-4.9], p = 0.003, OR CSND = 2.9[1.4-6.1], p = 0.004). 92% of population was walking after 6 months (63% with assistance): no difference was found between the three groups. CONCLUSION: In a dedicated geriatric care pathway, DP and CSND undergoing hip surgery have the same 6-month mortality and walking ability as NDP.

Association Between Later Life Lifestyle Factors and Alzheimer's Disease Biomarkers in Non-Demented Individuals: A Longitudinal Descriptive Cohort Study. - Reijs, Babette L R; Vos, Stephanie J B; Soininen, Hilkka; Lötjönen, Jyrki; Koikkalainen, Juha; Pikkarainen, Maria; Hall, Anette; Vanninen, Ritva; Liu, Yawu; Herukka, Sanna-Kaisa; Freund-Levi, Yvonne; Frisoni, Giovanni B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Lifestyle factors have been associated with the risk of dementia, but the association with Alzheimer's disease (AD) remains unclear. OBJECTIVE: To examine the association between later life lifestyle factors and AD biomarkers (i.e., amyloid-β 1-42 (Aβ42) and tau in cerebrospinal fluid (CSF), and hippocampal volume) in individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). In addition, to examine the effect of later life lifestyle factors on developing AD-type dementia in individuals with MCI. METHODS: We selected individuals with SCD (n = 111) and MCI (n = 353) from the DESCRIPA and Kuopio Longitudinal MCI studies. CSF Aβ42 and tau concentrations were assessed with ELISA assay and hippocampal volume with multi-atlas segmentation. Lifestyle was assessed by clinical interview at baseline for: social activity, physical activity, cognitive activity, smoking, alcohol consumption, and sleep. We performed logistic and Cox regression analyses adjusted for study site, age, gender, education, and diagnosis. Prediction for AD-type dementia was performed in individuals with MCI only. RESULTS: Later life lifestyle factors were not associated with AD biomarkers or with conversion to AD-type dementia. AD biomarkers were strongly associated with conversion to AD-type dementia, but these relations were not modulated by lifestyle factors. Apolipoprotein E (APOE) genotype did not influence the results. CONCLUSIONS: Later life lifestyle factors had no impact on key AD biomarkers in individuals with SCD and MCI or on conversion to AD-type dementia in MCI.

Association between Plasma Ceramides and Phosphatidylcholines and Hippocampal Brain Volume in Late Onset Alzheimer's Disease. - Kim, Min; Nevado-Holgado, Alejo; Whiley, Luke; Snowden, Stuart G; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Thambisetty, Madhav; Dobson, Richard J B; Powell, John F; et al. (J Alzheimers Dis, 2017)
Lipids such as ceramides and phosphatidylcholines (PC) have been found altered in the plasma of Alzheimer's disease (AD) patients in a number of discovery studies. For this reason, the levels of 6 ceramides and 3 PCs, with different fatty acid length and saturation levels, were measured in the plasma from 412 participants (AD n = 205, Control n = 207) using mass spectrometry coupled with ultra-performance liquid chromatography. After this, associations with AD status, brain atrophy, and age-related effects were studied. In the plasma of AD participants, cross-sectional analysis revealed elevated levels of three ceramides (Cer16:0 p < 0.01, Cer18:0 p < 0.01, Cer24:1 p < 0.05). In addition, two PCs in AD plasma (PC36:5 p < 0.05, PC38:6 p < 0.05) were found to be depleted compared to the control group, with PC36:5 also associating with hippocampal atrophy (p < 0.01). Age-specific analysis further revealed that levels of Cer16:0, Cer18:0, and Cer20:0 were associated with hippocampal atrophy only in younger participants (age < 75, p < 0.05), while all 3 PCs did so in the older participants (age > 75, p < 0.05). PC36:5 was associated with AD status in the younger group (p < 0.01), while PC38:6 and 40:6 did so in the older group (p < 0.05). In this study, elevated ceramides and depleted PCs were found in the plasma from 205 AD volunteers. Our findings also suggest that dysregulation in PC and ceramide metabolism could be occurring in different stages of AD progression.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

Associations of CAIDE Dementia Risk Score with MRI, PIB-PET measures, and cognition. - Stephen, Ruth; Liu, Yawu; Ngandu, Tiia; Rinne, Juha O; Kemppainen, Nina; Parkkola, Riitta; Laatikainen, Tiina; Paajanen, Teemu; Hänninen, Tuomo; Strandberg, Timo; Antikainen, Riitta; Tuomilehto, Jaakko; et al. (J Alzheimers Dis, 2017)
BACKGROUND: CAIDE Dementia Risk Score is the first validated tool for estimating dementia risk based on a midlife risk profile. OBJECTIVES: This observational study investigated longitudinal associations of CAIDE Dementia Risk Score with brain MRI, amyloid burden evaluated with PIB-PET, and detailed cognition measures. METHODS: FINGER participants were at-risk elderly without dementia. CAIDE Risk Score was calculated using data from previous national surveys (mean age 52.4 years). In connection to baseline FINGER visit (on average 17.6 years later, mean age 70.1 years), 132 participants underwent MRI scans, and 48 underwent PIB-PET scans. All 1,260 participants were cognitively assessed (Neuropsychological Test Battery, NTB). Neuroimaging assessments included brain cortical thickness and volumes (Freesurfer 5.0.3), visually rated medial temporal atrophy (MTA), white matter lesions (WML), and amyloid accumulation. RESULTS: Higher CAIDE Dementia Risk Score was related to more pronounced deep WML (OR 1.22, 95% CI 1.05-1.43), lower total gray matter (β-coefficient -0.29, p = 0.001) and hippocampal volume (β-coefficient -0.28, p = 0.003), lower cortical thickness (β-coefficient -0.19, p = 0.042), and poorer cognition (β-coefficients -0.31 for total NTB score, -0.25 for executive functioning, -0.33 for processing speed, and -0.20 for memory, all p < 0.001). Higher CAIDE Dementia Risk Score including APOE genotype was additionally related to more pronounced MTA (OR 1.15, 95% CI 1.00-1.30). No associations were found with periventricular WML or amyloid accumulation. CONCLUSIONS: The CAIDE Dementia Risk Score was related to indicators of cerebrovascular changes and neurodegeneration on MRI, and cognition. The lack of association with brain amyloid accumulation needs to be verified in studies with larger sample sizes.

Autonomic Nervous System Dysfunctions as a Basis for a Predictive Model of Risk of Neurological Disorders in Subjects with Prior History of Traumatic Brain Injury: Implications in Alzheimer's Disease. - Ho, Lap; Legere, Marc; Li, Tongbin; Levine, Samara; Hao, Ke; Valcarcel, Breanna; Pasinetti, Giulio M (J Alzheimers Dis, 2017)
Autonomic dysfunction is very common in patients with dementia, and its presence might also help in differential diagnosis among dementia subtypes. Various central nervous system structures affected in Alzheimer's disease (AD) are also implicated in the central autonomic nervous system (ANS) regulation. For example, deficits in central cholinergic function in AD could likely lead to autonomic dysfunction. We recently developed a simple, readily applicable evaluation for monitoring ANS disturbances in response to traumatic brain injury (TBI). This ability to monitor TBI allows for the possible detection and targeted prevention of long-term, detrimental brain responses caused by TBI that lead to neurodegenerative diseases such as AD. We randomly selected and extracted de-identified medical record information from subjects who have been assessed using the ANS evaluation protocol. Using machine learning strategies in the analysis of information from individual as well as a combination of ANS evaluation protocol components, we identified a novel prediction model that is effective in correctly segregating between cases with or without a documented history of TBI exposure. Results from our study support the hypothesis that trauma-induced ANS dysfunctions may contribute to clinical TBI features. Because autonomic dysfunction is very common in AD patients it is possible that TBI may also contribute to AD and/or other forms of dementia through these novel mechanisms. This study provides a novel prediction model to physiologically assess the likelihood of subjects with prior history of TBI to develop clinical TBI complications, such as AD.

BACE1 Dynamics Upon Inhibition with a BACE Inhibitor and Correlation to Downstream Alzheimer's Disease Markers in Elderly Healthy Participants. - Timmers, Maarten; Barão, Soraia; Van Broeck, Bianca; Tesseur, Ina; Slemmon, John; de Waepenaert, Katja; Bogert, Jennifer; Shaw, Leslie M; Engelborghs, Sebastiaan; Moechars, Dieder; Mercken, Marc; Van Nueten, Luc; et al. (J Alzheimers Dis, 2017)
The β-site amyloid-β protein precursor (AβPP) cleaving enzyme-1 (BACE1) is the rate limiting enzyme in the generation of amyloid-β peptide (Aβ) from AβPP, one of the major pathways in Alzheimer's disease (AD) pathology. Increased BACE1 levels and activity have been reported in the brain of patients with sporadic AD. Therefore, changes of BACE1 levels in the cerebrospinal fluid (CSF) have also been investigated as a possible biomarker of the disease. We analyzed BACE1 levels in CSF of elderly healthy participants before and after chronic treatment with a BACE inhibitor (BACEi) and evaluated the correlation between BACE1 levels and downstream AD markers. Overall, BACE1 CSF levels showed strong correlations to all downstream AD markers investigated. This is the first reported finding that shows BACE1 levels in CSF were well correlated to its end product Aβ1 - 42. As previously described, BACE1 levels were strongly correlated to total-tau and phosphorylated tau levels in CSF. Generally, chronic BACE inhibition did not influence BACE1 CSF protein levels. Follow-up studies including early-stage AD pathophysiology and prodromal AD patients will help to understand the importance of measuring BACE1 routinely in daily clinical practice and AD clinical trials.

Bilingualism and Cognitive Decline: A Story of Pride and Prejudice. - Woumans, Evy; Versijpt, Jan; Sieben, Anne; Santens, Patrick; Duyck, Wouter (J Alzheimers Dis, 2017)
In a recent review, Mukadam, Sommerlad, and Livingston (2017) argue that bilingualism offers no protection against cognitive decline. The authors examined the results of 13 studies (five prospective, eight retrospective) in which monolinguals and bilinguals were compared for cognitive decline and onset of dementia symptoms. Analysis of four of the five prospective studies resulted in the conclusion that there was no difference between monolinguals and bilinguals, whereas seven of the eight retrospective studies actually showed bilingualism to result in a four-to-five year delay of symptom onset. The authors decided to ignore the results from the retrospective studies in favor of those from the prospective studies, reasoning that the former may be confounded by participants' cultural background and education levels. In this commentary, we argue that most of these studies actually controlled for these two variables and still found a positive effect of bilingualism. Furthermore, we argue that the meta-analysis of the prospective studies is not complete, lacking the results of two crucial reports. We conclude that the literature offers substantial evidence for a bilingual effect on the development of cognitive decline and dementia.

Bipolar Disorder and Frontotemporal Dementia: An Intriguing Association. - Papazacharias, Apostolos; Lozupone, Madia; Barulli, Maria Rosaria; Capozzo, Rosa; Imbimbo, Bruno P; Veneziani, Federica; De Blasi, Roberto; Nardini, Marcello; Seripa, Davide; Panza, Francesco; Logroscino, Giancarlo (J Alzheimers Dis, 2017)
Bipolar disorder (BD) could represent a prodromal state of frontotemporal dementia (FTD). Two patients affected by lifelong BD with a progressive decline of cognitive functions, behavioral, and neurological signs, reached the early diagnosis of FTD before the age of 60. They were diagnosed as affected by primary progressive aphasia and FTD with parkinsonism, respectively. A diagnosis of FTD should therefore be taken into account, in case of unexpected cognitive and behavioral decline in patients with a long history of BD. Follow-up studies with genetic, neuropsychological, and neuroimaging markers of these BD/FTD patients could further explore some of the underlying association, opening new viable therapeutic options.

Brain Biomarkers in Familial Alzheimer's Disease Mouse Models. - Kuttner-Hirshler, Yafit; Venkatasubramanian, Palamadai N; Apolinario, Joan; Bonds, Jacqueline; Wyrwicz, Alice M; Lazarov, Orly (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by progressive loss of memory and cognitive deterioration. It is thought that the onset of the disease takes place several decades before memory deficits are apparent. Reliable biomarkers for the diagnosis or prognostication of the disease are highly desirable. Neural stem cells (NSC) exist in the adult brain throughout life and give rise to neural progenitor cells (NPC), which differentiate into neurons or glia. The level of NPC proliferation and new neuron formation is significantly compromised in mouse models of familial Alzheimer's disease (FAD). These deficits are readily detected in young adults, at 2-3 months of age, preceding amyloid deposition and cognitive impairments, which may indicate that impaired neurogenesis can be an early biomarker for cognitive deficits in AD. Recent studies suggest that NSC can be detected in live rodents, noninvasively, using proton magnetic resonance spectroscopy (1H-MRS) signal at 1.28 ppm. Here we examined the use of 1H-MRS for determining the extent of neurogenesis in the brains of FAD mice. We observed that the reduction in neurogenesis in the FAD mice as observed by immunohistochemistry, was not manifested by a reduction in the 1.28 ppm signal, suggesting that this marker is either not specific for neurogenesis or not sensitive enough for the detection of alterations in hippocampal neurogenesis in the brains of FAD mice.

Care Plan Improvement in Nursing Homes: An Integrative Review. - Mariani, Elena; Chattat, Rabih; Vernooij-Dassen, Myrra; Koopmans, Raymond; Engels, Yvonne (J Alzheimers Dis, 2017)
BACKGROUND: Care planning nowadays is a key activity in the provision of services to nursing home residents. A care plan describes the residents' needs and the actions to address them, providing both individualized and standardized interventions and should be updated as changes in the residents' conditions occur. OBJECTIVE: The aim of this review was to identify the core elements of the implementation of changes in nursing homes' care plans, by providing an overview of the type of stakeholders involved, describing the implementation strategies used, and exploring how care plans changed. METHODS: An integrative literature review was used to evaluate intervention studies taking place in nursing homes. Data were collected from PubMed, CINHAL-EBSCO, and PsycINFO. English language articles published between 1995 and April 2015 were included. Data analysis followed the strategy of Knafl and Whittemore. RESULTS: Twenty-six articles were included. The stakeholders involved were professionals, family caregivers, and patients. Only a few studies directly involved residents and family caregivers in the quality improvement process. The implementation strategies used were technology implementation, audit, training, feedback, and supervision. The majority of interventions changed the residents' care plans in terms of developing a more standardized care documentation that primarily focuses on its quality. Only some interventions developed more tailored care plans that focus on individualized needs. CONCLUSION: Care plans generally failed in providing both standardized and personalized interventions. Efforts should be made to directly involve residents in care planning and provide professionals with efficient tools to report care goals and actions in care plans.

Central Olfactory Dysfunction in Alzheimer's Disease and Mild Cognitive Impairment: A Functional MRI Study. - Vasavada, Megha M; Martinez, Brittany; Wang, Jianli; Eslinger, Paul J; Gill, David J; Sun, Xiaoyu; Karunanayaka, Prasanna; Yang, Qing X (J Alzheimers Dis, 2017)
BACKGROUND: Olfactory deficits are present in early Alzheimer's disease (AD) and mild cognitively impaired (MCI) patients. However, whether these deficits are due to dysfunction of the central or peripheral olfactory nervous system remains uncertain. This question is fundamentally important for developing imaging biomarkers for AD using olfactory testing. OBJECTIVE: This study sought to use olfactory functional magnetic resonance imaging (fMRI) to further demonstrate the involvement of the central olfactory system in olfactory deficits in MCI and AD. METHODS: We investigated the central olfactory system in 27 cognitively normal controls (CN), 21 MCI, and 15 AD subjects using olfactory fMRI with an odor-visual association paradigm during which a visual cue was paired with lavender odorant (odor condition) or odorless air (no-odor condition). RESULTS: The CN subjects had significantly greater activated volume in the primary olfactory cortex during both the odor and no-odor conditions compared to either the MCI or AD groups (p < 0.05). No significant differences were observed between the odor and no-odor conditions within each group. No-odor condition activation in AD and MCI correlated with the cognitive and olfactory assessments. CONCLUSION: The no-odor condition, allowing investigation of activation patterns when the peripheral olfactory system was not directly involved, elicited the same functional response as the odor condition for each of the three groups. Thus, the olfactory activation deficits present in AD and MCI patients are most likely caused by degeneration of the central olfactory nervous system.

The Cerebrospinal Fluid Aβ1-42/Aβ1-40 Ratio Improves Concordance with Amyloid-PET for Diagnosing Alzheimer's Disease in a Clinical Setting. - Niemantsverdriet, Ellis; Ottoy, Julie; Somers, Charisse; De Roeck, Ellen; Struyfs, Hanne; Soetewey, Femke; Verhaeghe, Jeroen; Van den Bossche, Tobi; Van Mossevelde, Sara; Goeman, Johan; De Deyn, Peter Paul; Mariën, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Evidence suggests that the concordance between amyloid-PET and cerebrospinal fluid (CSF) amyloid-β (Aβ) increases when the CSF Aβ1-42/Aβ1-40 ratio is used as compared to CSF Aβ1-42 levels alone. OBJECTIVE: In order to test this hypothesis, we set up a prospective longitudinal study comparing the concordance between different amyloid biomarkers for Alzheimer's disease (AD) in a clinical setting. METHODS: Seventy-eight subjects (AD dementia (n = 17), mild cognitive impairment (MCI, n = 48), and cognitively healthy controls (n = 13)) underwent a [18F]Florbetapir ([18F]AV45) PET scan, [18F]FDG PET scan, MRI scan, and an extensive neuropsychological examination. In a large subset (n = 67), a lumbar puncture was performed and AD biomarkers were analyzed (Aβ1-42, Aβ1-40, T-tau, P-tau181). RESULTS: We detected an increased concordance in the visual and quantitative (standardized uptake value ratio (SUVR) and total volume of distribution (VT)) [18F]AV45 PET measures when the CSF Aβ1-42/Aβ1-40 was applied compared to Aβ1-42 alone. CSF biomarkers were stronger associated to [18F]AV45 PET for SUVR values when considering the total brain white matter as reference region instead of cerebellar grey matterConclusions:The concordance between CSF Aβ and [18F]AV45 PET increases when the CSF Aβ1-42/Aβ1-40 ratio is applied. This finding is of most importance for the biomarker-based diagnosis of AD as well as for selection of subjects for clinical trials with potential disease-modifying therapies for AD.

Cerebrospinal Fluid Biomarkers for Alzheimer's Disease: A View of the Regulatory Science Qualification Landscape from the Coalition Against Major Diseases CSF Biomarker Team. - Arnerić, Stephen P; Batrla-Utermann, Richard; Beckett, Laurel; Bittner, Tobias; Blennow, Kaj; Carter, Leslie; Dean, Robert; Engelborghs, Sebastiaan; Genius, Just; Gordon, Mark Forrest; Hitchcock, Janice; Kaplow, June; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) drug development is burdened with the current requirement to conduct large, lengthy, and costly trials to overcome uncertainty in patient progression and effect size on treatment outcome measures. There is an urgent need for the discovery, development, and implementation of novel, objectively measured biomarkers for AD that would aid selection of the appropriate subpopulation of patients in clinical trials, and presumably, improve the likelihood of successfully evaluating innovative treatment options. Amyloid deposition and tau in the brain, which are most commonly assessed either in cerebrospinal fluid (CSF) or by molecular imaging, are consistently and widely accepted. Nonetheless, a clear gap still exists in the accurate identification of subjects that truly have the hallmarks of AD. The Coalition Against Major Diseases (CAMD), one of 12 consortia of the Critical Path Institute (C-Path), aims to streamline drug development for AD and related dementias by advancing regulatory approved drug development tools for clinical trials through precompetitive data sharing and adoption of consensus clinical data standards. This report focuses on the regulatory process for biomarker qualification, briefly comments on how it contrasts with approval or clearance of companion diagnostics, details the qualifications currently available to the field of AD, and highlights the current challenges facing the landscape of CSF biomarkers qualified as hallmarks of AD. Finally, it recommends actions to accelerate regulatory qualification of CSF biomarkers that would, in turn, improve the efficiency of AD therapeutic development.

Challenges and Considerations Related to Studying Dementia in Blacks/African Americans. - Ighodaro, Eseosa T; Nelson, Peter T; Kukull, Walter A; Schmitt, Frederick A; Abner, Erin L; Caban-Holt, Allison; Bardach, Shoshana H; Hord, Derrick C; Glover, Crystal M; Jicha, Gregory A; Van Eldik, Linda J; Byrd, Alexander X; et al. (J Alzheimers Dis, 2017)
Blacks/African Americans have been reported to be ∼2-4 times more likely to develop clinical Alzheimer's disease (AD) compared to Whites. Unfortunately, study design challenges (e.g., recruitment bias), racism, mistrust of healthcare providers and biomedical researchers, confounders related to socioeconomic status, and other sources of bias are often ignored when interpreting differences in human subjects categorized by race. Failure to account for these factors can lead to misinterpretation of results, reification of race as biology, discrimination, and missed or delayed diagnoses. Here we provide a selected historical background, discuss challenges, present opportunities, and suggest considerations for studying health outcomes among racial/ethnic groups. We encourage neuroscientists to consider shifting away from using biologic determination to interpret data, and work instead toward a paradigm of incorporating both biological and socio-environmental factors known to affect health outcomes with the goal of understanding and improving dementia treatments for Blacks/African Americans and other underserved populations.

Changes in Plasma β-NGF and Its Receptors Expression on Peripheral Blood Monocytes During Alzheimer's Disease Progression. - Crispoltoni, Lucia; Stabile, Anna Maria; Pistilli, Alessandra; Venturelli, Massimo; Cerulli, Giuliano; Fonte, Cristina; Smania, Nicola; Schena, Federico; Rende, Mario (J Alzheimers Dis, 2017)
Alzheimer's disease (AD), the most common cause of dementia, is characterized by the deposition of extracellular amyloid-β (Aβ) plaques and intracellular neurofibrillary tangles, and by neuroinflammation. During the pathogenesis of AD, monocyte-macrophage lineage cells become increasingly ineffective in clearing Aβ deposits, less able to differentiate, and shift toward pro-inflammatory processes. Beta-nerve growth factor (β-NGF) and its receptors, TrKA and p75NTR, produce several biological responses, including cell apoptosis and survival, and inflammation. In the central nervous system, the involvement of these receptors in several critical hallmarks of AD is well known, but their role in circulating monocytes during the progression of dementia is unclear. We investigated the relationship between plasma β-NGF concentration and TrkA/p75NTR receptor expression in monocytes of patients with mild cognitive impairment (MCI), mild AD, and severe AD. We observed that plasma β-NGF concentration was increased with a higher expression of TrKA, but not of p75NTR, in monocytes from patients with MCI and mild AD, whereas β-NGF concentration and TrKA expression were decreased and p75NTR expression was increased, associated with caspase 3-mediated apoptosis, in patients with severe AD. In our study, we show evidence of variation in plasmatic β-NGF and monocytic TrkA/p75NTR receptor expression during the progression of dementia. These novel findings add evidence to support the hypothesis for the involvement of β-NGF and its receptors on monocytes during AD progression.

Chromatin-Bound Oxidized α-Synuclein Causes Strand Breaks in Neuronal Genomes in in vitro Models of Parkinson's Disease. - Vasquez, Velmarini; Mitra, Joy; Hegde, Pavana M; Pandey, Arvind; Sengupta, Shiladitya; Mitra, Sankar; Rao, K S; Hegde, Muralidhar L (J Alzheimers Dis, 2017)
Alpha-synuclein (α-Syn) overexpression and misfolding/aggregation in degenerating dopaminergic neurons have long been implicated in Parkinson's disease (PD). The neurotoxicity of α-Syn is enhanced by iron (Fe) and other pro-oxidant metals, leading to generation of reactive oxygen species in PD brain. Although α-Syn is predominantly localized in presynaptic nerve terminals, a small fraction exists in neuronal nuclei. However, the functional and/or pathological role of nuclear α-Syn is unclear. Following up on our earlier report that α-Syn directly binds DNA in vitro, here we confirm the nuclear localization and chromatin association of α-Syn in neurons using proximity ligation and chromatin immunoprecipitation analysis. Moderate (∼2-fold) increase in α-Syn expression in neural lineage progenitor cells (NPC) derived from induced pluripotent human stem cells (iPSCs) or differentiated SHSY-5Y cells caused DNA strand breaks in the nuclear genome, which was further enhanced synergistically by Fe salts. Furthermore, α-Syn required nuclear localization for inducing genome damage as revealed by the effect of nucleus versus cytosol-specific mutants. Enhanced DNA damage by oxidized and misfolded/oligomeric α-Syn suggests that DNA nicking activity is mediated by the chemical nuclease activity of an oxidized peptide segment in the misfolded α-Syn. Consistent with this finding, a marked increase in Fe-dependent DNA breaks was observed in NPCs from a PD patient-derived iPSC line harboring triplication of the SNCA gene. Finally, α-Syn combined with Fe significantly promoted neuronal cell death. Together, these findings provide a novel molecular insight into the direct role of α-Syn in inducing neuronal genome damage, which could possibly contribute to neurodegeneration in PD.

Chronic Verubecestat Treatment Suppresses Amyloid Accumulation in Advanced Aged Tg2576-AβPPswe Mice Without Inducing Microhemorrhage. - Villarreal, Stephanie; Zhao, Fuqiang; Hyde, Lynn A; Holder, Daniel; Forest, Thomas; Sondey, Marie; Chen, Xia; Sur, Cyrille; Parker, Eric M; Kennedy, Matthew E (J Alzheimers Dis, 2017)
Verubecestat is a potent BACE1 enzyme inhibitor currently being investigated in Phase III trials for the treatment of mild-to-moderate and prodromal Alzheimer's disease. Multiple anti-amyloid immunotherapies have been dose-limited by adverse amyloid related imaging abnormalities such as vasogenic edema (ARIA-E) and microhemorrhage (ARIA-H) observed in human trials and mice. Verubecestat was tested in a 12-week nonclinical study for the potential to exacerbate microhemorrhage (ARIA-H) profiles in 18-22-month-old post-plaque Tg2576-AβPPswe mice. Animals were treated with verubecestat or controls including the anti-Aβ antibody analog of bapineuzumab (3D6) as a positive control for ARIA induction. ARIA-H was measured using in-life longitudinal T2*-MRI and Prussian blue histochemistry at study end. Verubecestat reduced plasma and cerebrospinal fluid Aβ40 and Aβ42 by >90% and 62% to 68%, respectively. The ARIA-H profile of verubecestat-treated mice was not significantly different than controls. Anti-Aβ treatment significantly increased ARIA-H detected by Prussian blue staining; however, anti-Aβ antibody treatment did not impact plaque status. Verubecestat treatment significantly suppressed the accumulation of total levels of brain Aβ40 and Aβ42 and Thioflavin S positive plaque load. Stereological analysis of cortex and hippocampus plaque load similarly revealed significantly reduced area of Aβ immunoreactivity and reduced plaque number in verubecestat-treated animals compared to controls. The absence of elevated ARIA events in verubecestat-treated mice was associated with a significant reduction in the level of accumulated CNS amyloid pathology and brain Aβ peptides; effects consistent with the desired therapeutic mechanism of verubecestat in AD patients. These data will be compared with longitudinal MRI profiles from ongoing clinical trials.

Cognitive Composites Domain Scores Related to Neuroimaging Biomarkers within Probable-Amnestic Mild Cognitive Impairment-Storage Subtype. - Espinosa, Ana; Alegret, Montserrat; Pesini, Pedro; Valero, Sergi; Lafuente, Asunción; Buendia, Mar; San José, Itziar; Ibarria, Marta; Tejero, Miguel A; Giménez, Joan; Ruiz, Susana; Hernandez, Isabel; et al. (J Alzheimers Dis, 2017)
The probable-amnestic (Pr-a) mild cognitive impairment (MCI)-storage subtype is a phenotype with 8.5 times more risk of conversion to dementia, mainly Alzheimer's disease (AD), than the possible non-amnestic (Pss-na) MCI. The aim of this study was to find the optimized cognitive composites (CCs) domain scores most related to neuroimaging biomarkers within Pr-aMCI-storage subtype patients. The Fundació ACE (ACE) study with 20 Pr-aMCI-storage subtype subjects (MCI) were analyzed. All subjects underwent a neuropsychological assessment, a structural MRI, FDG-PET, and PIB-PET. The adjusted hippocampal volume (aHV) on MRI, the standard uptake value ratio (SUVR) on FDG-PET and PIB-PET SUVR measures were analyzed. The construction of the CCs domain scores, and the aHV on MRI and FDG-PET SUVR measures, were replicated in the parental AB255 study database (n = 133 MCI). Partial correlations adjusted by age, gender, and education were calculated with the associated p-value among every CC domain score and the neuroimaging biomarkers. The results were replicated in the "MCI due to AD" with memory storage impairments from ADNI. Delayed Recall CC domain score was significantly correlated with PIB-PET SUVR (β= -0.61, p = 0.003) in the ACE study and also with aHV on MRI (β= 0.27, p = 0.01) and FDG-PET SUVR (β= 0.27, p = 0.01) in the AB255 study. After a median survival time of 20.6 months, 85% from the ACE MCI converted to AD. The replication of our results in the ADNI dataset also confirmed our findings. Delayed Recall is the CC domain score best correlated with neuroimaging biomarkers associated with prodromal AD diagnosis.

Cognitive Efficiency in Alzheimer's Disease is Associated with Increased Occipital Connectivity. - De Marco, Matteo; Duzzi, Davide; Meneghello, Francesca; Venneri, Annalena (J Alzheimers Dis, 2017)
There are cognitive domains which remain fully functional in a proportion of Alzheimer's disease (AD) patients. It is unknown, however, what distinctive mechanisms sustain such efficient processing. The concept of "cognitive efficiency" was investigated in these patients by operationalizing it as a function of the level of performance shown on the Letter Fluency test, on which, very often, patients in the early stages of AD show unimpaired performance. Forty-five individuals at the prodromal/early stage of AD (diagnosis supported by subsequent clinical follow-ups) and 45 healthy controls completed a battery of neuropsychological tests and an MRI protocol which included resting state acquisitions. The Letter Fluency test was the only task on which no between-group difference in performance was found. Participants were divided into "low-performing" and "high-performing" according to the global median. Dual-regression methods were implemented to compute six patterns of network connectivity. The diagnosis-by-level of performance interaction was inferred on each pattern to determine the network distinctiveness of efficient performance in AD. Significant interactions were found in the anterior default mode network, and in both left and right executive control networks. For all three circuits, high-performing patients showed increased connectivity within the ventral and dorsal part of BA19, as confirmed by post hoc t tests. Peristriate remapping is suggested to play a compensatory role. Since the occipital lobe is the neurophysiological source of long-range cortical connectivity, it is speculated that the physiological mechanisms of functional connectivity might sustain occipital functional remapping in early AD, particularly for those functions which are sustained by areas not excessively affected by the prodromal disease.

Cognitive Event-Related Potential, an Early Diagnosis Biomarker in Frail Elderly Subjects: The ERP-MAPT-PLUS Ancillary Study. - Bennys, Karim; Gabelle, Audrey; Berr, Claudine; De Verbizier, Delphine; Andrieu, Sandrine; Vellas, Bruno; Touchon, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: By analyzing brain synaptic function, cognitive event-related potentials (ERPs) could provide powerful and innovative tools for early Alzheimer's disease (AD) diagnosis. OBJECTIVE: We investigated the relevance of the ERP-P300 component as a potential diagnosis marker in elderly subjects at risk of developing AD. METHODS: ERP-P300 was analyzed on 85 subjects recruited from the Multidomain Alzheimer Preventive Trial (MAPT). PET-AV45 brain imaging was available from 36 subjects. RESULTS: Two ERP-P300 subgroups were identified according to their PET-AV45 status: PET-Aβ positive (n = 15) and PET-Aβ negative (n = 21). In the amyloid positive group, we observed a highly significant increase in P3b latency in parietal brain regions (p = 0.0052). P3b in parietal regions correctly categorized 69.4% elderly subjects from the P300-PET Aβ positive group. Combined analysis of parietal P3b latencies and category fluency correctly classified 75% subjects from the P300-PET Aβ positive group. CONCLUSIONS: The P300 ERP presents good predictive measure of brain amyloid load and has the potential to be used as a screening instrument for preclinical AD. The incorporation of P3b latency may be used as an adjunctive tool with neuropsychological assessment (i.e., verbal category fluency) as a specific and sensitive method for preclinical assessment of AD.

A Common Variant of IL-6R is Associated with Elevated IL-6 Pathway Activity in Alzheimer's Disease Brains. - Haddick, Patrick C G; Larson, Jessica L; Rathore, Nisha; Bhangale, Tushar R; Phung, Qui T; Srinivasan, Karpagam; Hansen, David V; Lill, Jennie R; Pericak-Vance, Margaret A; Haines, Jonathan; Farrer, Lindsay A; Kauwe, John S; et al. (J Alzheimers Dis, 2017)
The common p.D358A variant (rs2228145) in IL-6R is associated with risk for multiple diseases and with increased levels of soluble IL-6R in the periphery and central nervous system (CNS). Here, we show that the p.D358A allele leads to increased proteolysis of membrane bound IL-6R and demonstrate that IL-6R peptides with A358 are more susceptible to cleavage by ADAM10 and ADAM17. IL-6 responsive genes were identified in primary astrocytes and microglia and an IL-6 gene signature was increased in the CNS of late onset Alzheimer's disease subjects in an IL6R allele dependent manner. We conducted a screen to identify variants associated with the age of onset of Alzheimer's disease in APOE ɛ4 carriers. Across five datasets, p.D358A had a meta P = 3 ×10-4 and an odds ratio = 1.3, 95% confidence interval 1.12 -1.48. Our study suggests that a common coding region variant of the IL-6 receptor results in neuroinflammatory changes that may influence the age of onset of Alzheimer's disease in APOE ɛ4 carriers.

Cortical Cerebral Microinfarcts on 3 Tesla MRI in Patients with Vascular Cognitive Impairment. - Ferro, Doeschka A; van Veluw, Susanne J; Koek, Huiberdina L; Exalto, Lieza G; Biessels, Geert Jan (J Alzheimers Dis, 2017)
BACKGROUND: Cerebral microinfarcts (CMIs) are small ischemic lesions that are a common neuropathological finding in patients with stroke or dementia. CMIs in the cortex can now be detected in vivo on 3 Tesla MRI. OBJECTIVE: To determine the occurrence of CMIs and associated clinical features in patients with possible vascular cognitive impairment (VCI). METHOD: 182 memory-clinic patients (mean age 71.4±10.6, 55% male) with vascular injury on brain MRI (i.e., possible VCI) underwent a standardized work-up including 3 Tesla MRI and cognitive assessment. A control group consisted of 70 cognitively normal subjects (mean age 70.6±4.7, 60% male). Cortical CMIs and other neuroimaging markers of vascular brain injury were rated according to established criteria. RESULT: Occurrence of CMIs was higher (20%) in patients compared to controls (10%). Among patients, the presence of CMIs was associated with male sex, history of stroke, infarcts, and white matter hyperintensities. CMI presence was also associated with a diagnosis of vascular dementia and reduced performance in multiple cognitive domains. CONCLUSION: CMIs on 3 Tesla MRI are common in patients with possible VCI and co-occur with imaging markers of small and large vessel disease, likely reflecting a heterogeneous etiology. CMIs are associated with worse cognitive performance, independent of other markers of vascular brain injury.

Cortical Iron Reflects Severity of Alzheimer's Disease. - van Duijn, Sara; Bulk, Marjolein; van Duinen, Sjoerd G; Nabuurs, Rob J A; van Buchem, Mark A; van der Weerd, Louise; Natté, Remco (J Alzheimers Dis, 2017)
Abnormal iron distribution in the isocortex is increasingly recognized as an in vivo marker for Alzheimer's disease (AD). However, the contribution of iron accumulation to the AD pathology is still poorly understood. In this study, we investigated: 1) frontal cortical iron distribution in AD and normal aging and 2) the relation between iron distribution and degree of AD pathology. We used formalin fixed paraffin embedded frontal cortex from 10 AD patients, 10 elder, 10 middle aged, and 10 young controls and visualized iron with a modified Perl's histochemical procedure. AD and elderly subjects were not different with respect to age and sex distribution. Iron distribution in the frontal cortex was not affected by normal aging but was clearly different between AD and controls. AD showed accumulation of iron in plaques, activated microglia, and, in the most severe cases, in the mid-cortical layers along myelinated fibers. The degree of altered iron accumulations was correlated to the amount of amyloid-β plaques and tau pathology in the same block, as well as to Braak stage (p < 0.001). AD and normal aging show different iron and myelin distribution in frontal cortex. These changes appear to occur after the development of the AD pathological hallmarks. These findings may help the interpretation of high resolution in vivo MRI and suggest the potential of using changes in iron-based MRI contrast to indirectly determine the degree of AD pathology in the frontal cortex.

Cortical Metabolic and Cognitive Correlates of Disorientation in Alzheimer's Disease. - Weissberger, Gali H; Melrose, Rebecca J; Fanale, Candace M; Veliz, Joseph V; Sultzer, David L (J Alzheimers Dis, 2017)
Orientation to time, date, and place is commonly utilized in clinical settings to aid in diagnosis, staging, and monitoring of Alzheimer's disease (AD). This study aimed to identify the cerebral metabolic correlates of orientation in patients with AD, and the degree to which regions associated with orientation overlap with memory-related structures. Eighty-five patients with a diagnosis of probable AD underwent fluorodeoxyglucose positron emission tomography (FDG-PET) and neuropsychological testing. Orientation items from the Dementia Rating Scale and recognition performance from the Consortium to Establish a Registry for AD (CERAD) Word List Learning test were correlated with cerebral glucose metabolism. Post-hoc analyses examined neuropsychological predictors of orientation. Better orientation performance related to greater cerebral metabolism in the bilateral middle-inferior temporal lobes, bilateral middle-posterior cingulate, left angular gyrus, and left middle occipital gyrus. In comparison, higher CERAD recognition discriminability score was associated with greater metabolic activity in left medial temporal lobe regions including the hippocampal and parahippocampal gyri, and the left fusiform gyrus. Post-hoc behavioral analyses revealed multiple cognitive functions to be related to orientation, including list learning, recognition memory, visuospatial functioning, attention, and language. Findings from the present study suggest that disorientation in AD results from dysfunction of a network of structures and cognitive abilities commonly found to be implicated in AD. The study supports the notion that memory is necessary but not sufficient for successful orientation.

Cost-Utility of Using Alzheimer's Disease Biomarkers in Cerebrospinal Fluid to Predict Progression from Mild Cognitive Impairment to Dementia. - Handels, Ron L H; Wimo, Anders; Dodel, Richard; Kramberger, Milica G; Visser, Pieter Jelle; Molinuevo, José Luis; Verhey, Frans R J; Winblad, Bengt (J Alzheimers Dis, 2017)
BACKGROUND: Diagnostic research criteria for Alzheimer's disease support the use of biomarkers in the cerebrospinal fluid (CSF) to improve the accuracy of the prognosis regarding progression to dementia for people with mild cognitive impairment (MCI). OBJECTIVE: The aim of this study was to estimate the potential incremental cost-effectiveness ratio of adding CSF biomarker testing to the standard diagnostic workup to determine the prognosis for patients with MCI. METHODS: In an early technology assessment, a mathematical simulation model was built, using available evidence on added prognostic value as well as expert opinion to estimate the incremental costs and quality-adjusted life years (QALYs) of 20,000 virtual MCI patients with (intervention strategy) and without (control strategy) relying on CSF, from a health-care sector perspective and with a 5-year time horizon. RESULTS: Adding the CSF test improved the accuracy of prognosis by 11%. This resulted in an average QALY gain of 0.046 and € 432 additional costs per patient, representing an incremental cost-effectiveness ratio of € 9,416. CONCLUSION: The results show the potential of CSF biomarkers in current practice from a health-economics perspective. This result was, however, marked by a high degree of uncertainty, and empirical research is required into the impact of a prognosis on worrying, false-positive/negative prognosis, and stigmatization.

Cross-Sectional and Longitudinal Cognitive Correlates of FDDNP PET and CSF Amyloid-β and Tau in Parkinson's Disease1. - Buongiorno, Mariateresa; Antonelli, Francesca; Compta, Yaroslau; Fernandez, Yolanda; Pavía, Javier; Lomeña, Francisco; Ríos, José; Ramírez, Isabel; García, José Ramón; Soler, Marina; Cámara, Ana; Fernández, Manel; et al. (J Alzheimers Dis, 2017)
Tau and amyloid-β (Aβ) aggregates have been suggested to play a role in the development of dementia in Parkinson's disease (PD). Positron emission tomography (PET) with [18F]FDDNP and the determination of cerebrospinal fluid (CSF) levels of these proteins constitute a means to visualize in vivo Aβ and tau brain accumulation. Information about longitudinal changes of these CSF and PET biomarkers in PD with regard to progression to dementia is lacking. We assessed the cross-sectional and longitudinal associations of CSF and PET biomarkers of tau and Aβ with PD-related cognitive dysfunction in 6 healthy-controls (HC), 16 patients with PD without dementia (PDND), and 8 PD with dementia (PDD). All subjects underwent comprehensive neuropsychological testing, [18F]FDDNP PET, and CSF Aβ-tau determination. After 18 months, the PDND group was re-assessed clinically and by neuropsychological, PET, and CSF determinations. Cross-sectionally, PDD had higher [18F]FDDNP binding in lateral temporal regions and lower levels of CSF Aβ levels compared to PDND, with a congruent correlation between the [18F]FDDNP binding and CSF Aβ levels. Longitudinally, higher baseline lateral temporal [18F]FDDNP binding was associated to longitudinal worsening in cognitive performances and progression to dementia among subjects classified as PDND at baseline, who additionally disclosed at follow-up an increase in lateral-temporal FDDNP binding, as well as a reduction in CSF Aβ and an increase in CSF tau levels. These results confirm the relevance of these CSF and PET biomarkers to PDD, being specifically the first to show [18F]FDDNP PET as a dementia risk biomarker in PD, along with longitudinal CSF and PET changes over time.

Current Approaches and Clinician Attitudes to the Use of Cerebrospinal Fluid Biomarkers in Diagnostic Evaluation of Dementia in Europe. - Miller, Anne-Marie; Balasa, Mircea; Blennow, Kaj; Gardiner, Mary; Rutkowska, Aleksandra; Scheltens, Philip; Teunissen, Charlotte E; Visser, Pieter Jelle; Winblad, Bengt; Waldemar, Gunhild; Lawlor, Brian (J Alzheimers Dis, 2017)
BACKGROUND: BIOMARKAPD seeks to diminish the barriers associated with the clinical use of cerebrospinal fluid (CSF) biomarker analysis by reducing variation in CSF laboratory methodologies and generating consensus recommendations on their clinical interpretation and application for dementia diagnosis. OBJECTIVE: To examine the disparity in practitioner attitudes and clinical practice relating to the use of CSF biomarkers for dementia diagnosis across Europe. METHODS: Clinical dementia experts were surveyed on the prevalence of national consensus guidelines and analytical reimbursement across Europe, their biomarker platform preferences, lumbar puncture methodologies and application of reference values and cut-offs for CSF analysis. RESULTS: 74% of respondents (total n = 51) use CSF biomarkers in clinical practice and 69% perform lumbar punctures on an outpatient basis. Most use CSF biomarkers to diagnose atypical (84%) and early-onset cases of cognitive impairment (71%) and for the differential diagnosis of other dementias (69%). 82% state they are sufficiently informed about CSF biomarkers yet 61% report a lack of national consensus guidelines on their use for dementia diagnosis. 48% of countries represented do not reimburse clinical CSF analysis costs. 43% report using normal reference ranges derived from publications. CONCLUSION: Variations in attitude and practice relating to CSF biomarkers, widely recognised as barriers to their clinical acceptance, remain evident within and between countries across Europe, even in expert centres. These shortcomings must be addressed by developing consensus guidelines on CSF-related methodologies and their clinical application, to further their use for the diagnostic evaluation of dementia.

Daily Physical Activity Patterns During the Early Stage of Alzheimer's Disease. - Varma, Vijay R; Watts, Amber (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disease that results in severe disability. Very few studies have explored changes in daily physical activity patterns during early stages of AD when components of physical function and mobility may be preserved. OBJECTIVE: Our study explored differences in daily physical activity profiles, independent of the effects of non-cognitive factors including physical function and age, among individuals with mild AD compared to controls. METHODS: Patients with mild AD and controls (n = 92) recruited from the University of Kansas Alzheimer's Disease Center Registry, wore the Actigraph GT3X+ for seven days, and provided objective physical function (VO2 max) and mobility data. Using multivariate linear regression, we explored whether individuals with mild AD had different daily average and diurnal physical activity patterns compared to controls independent of non-cognitive factors that may affect physical activity, including physical function and mobility. RESULTS: We found that mild AD was associated with less moderate-intensity physical activity (p < 0.05), lower peak activity (p < 0.01), and lower physical activity complexity (p < 0.05) particularly during the morning. Mild AD was not associated with greater sedentary activity or less lower-intensity physical activity across the day after adjusting for non-cognitive covariates. CONCLUSIONS: These findings suggest that factors independent of physical capacity and mobility may drive declines in moderate-intensity physical activity, and not lower-intensity or sedentary activity, during the early stage of AD. This underscores the importance of a better mechanistic understanding of how cognitive decline and AD pathology impact physical activity. Findings emphasize the potential value of designing and testing time-of-day specific physical activity interventions targeting individuals in the early stages of AD, prior to significant declines in mobility and physical function.

Development of Nasal Lipid Nanocarriers Containing Curcumin for Brain Targeting. - Vaz, Gustavo Richter; Hädrich, Gabriela; Bidone, Juliana; Rodrigues, Jamile Lima; Falkembach, Mariana Corrêa; Putaux, Jean-Luc; Hort, Mariana Appel; Monserrat, José Maria; Varela Junior, Antônio Sergio; Teixeira, Helder Ferreira; Muccillo-Baisch, Ana Luiza; Horn, Ana Paula; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Curcumin (CUR) has properties that can be useful for the treatment of Alzheimer's disease. Such properties are the inhibition of amyloid-β-protein (Aβ) aggregation, Aβ-induced inflammation, and activities of β-secretase and acetylcholinesterase. However, previous studies have revealed that CUR exhibited low bioavailability and difficulties in reaching the brain. OBJECTIVE: To overcome such drawbacks, this study aims at developing nasal lipid nanocarriers loaded with CUR to effectively target the brain. METHODS: The lipid nanocarriers (NE) were prepared using the hot solvent diffusion associated with the phase inversion temperature methods. Physico-chemical and morphological characterizations and in vitro drug release of the nanocarriers were carried out. The CUR permeation/retention was analyzed in Franz-type diffusion cell using porcine nasal mucosa. Confocal laser scan and histopathological studies were also performed. RESULTS: The results showed that the NE sizes ranged between 18 nm and 44 nm with negative zeta potential. The CUR content ranged from 0.24 to 1.50 mg/mL with an encapsulation efficiency of 99%. The profiles of CUR release indicated a biphasic kinetics. CUR-NE permeation across the porcine nasal mucosa was higher when compared to free CUR. These results have also been validated through an analysis on a confocal microscopy. In addition, no toxicity on the nasal mucosa has been observed in a histopathological analysis. CONCLUSION: These results suggest that it is possible to develop NEs with a high content of CUR and small particle size. Such an encapsulation increases the potential of CUR permeation across the porcine nasal mucosa.

The Diagnostic and Prognostic Value of Neuropsychological Assessment in Memory Clinic Patients. - Jansen, Willemijn J; Handels, Ron L H; Visser, Pieter Jelle; Aalten, Pauline; Bouwman, Femke; Claassen, Jurgen; van Domburg, Peter; Hoff, Erik; Hoogmoed, Jan; Leentjens, Albert F G; Rikkert, Marcel Olde; Oleksik, Ania M; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Neuropsychological testing has long been embedded in daily clinical practice at memory clinics but the added value of a complete neuropsychological assessment (NPA) to standard clinical evaluation is unknown. OBJECTIVE: To evaluate the added diagnostic and prognostic value of NPA to clinical evaluation only in memory clinic patients. METHODS: In 221 memory clinic patients of a prospective cohort study, clinical experts diagnosed clinical syndrome (subjective cognitive impairment (SCI), mild cognitive impairment (MCI), or dementia) and etiology (Alzheimer's disease (AD) or no AD), and provided a prognosis of disease course (decline or no decline) before and after results of NPA were made available. The reference standard was a panel consensus based on all clinical information at baseline and up to 2 follow-up assessments. RESULTS: With NPA data available, clinicians changed their initial syndromal diagnosis in 22% of patients, and the etiological diagnosis as well as the prognosis in 15%. This led to an increase in correctly classified cases of 18% for syndromal diagnosis, 5% for etiological diagnosis, and 1% for prognosis. NPA data resulted in the largest improvement in patients initially classified as SCI (syndrome: 93.3% (n = 14) correctly reclassified, etiology: net reclassification improvement [NRI] = 0.61, prognosis: NRI = 0.13) or MCI (syndrome: 89.3% (n = 23) correctly reclassified, etiology: NRI = 0.17, prognosis: NRI = 0.14), while there was no improvement in patients with dementia (syndrome: 100% (n = 1) correctly reclassified, etiology: NRI = -0.05, prognosis: NRI = -0.06). Overall, inclusion of NPA in the diagnostic process increased confidence in all diagnoses with 6-7%. CONCLUSION: Administration of a complete NPA after standard clinical evaluation has added value for diagnosing cognitive syndrome and its underlying etiology in patients regarded as non-demented based on the first clinical impression.

Diagnostic and Prognostic Value of the Combination of Two Measures of Verbal Memory in Mild Cognitive Impairment due to Alzheimer's Disease. - Sala, Isabel; Illán-Gala, Ignacio; Alcolea, Daniel; Sánchez-Saudinós, Ma Belén; Salgado, Sergio Andrés; Morenas-Rodriguez, Estrella; Subirana, Andrea; Videla, Laura; Clarimón, Jordi; Carmona-Iragui, María; Ribosa-Nogué, Roser; Blesa, Rafael; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory impairment is the core feature of typical Alzheimer's disease. OBJECTIVE: To evaluate the performance of two commonly used verbal memory tests to detect mild cognitive impairment due to Alzheimer's disease (MCI-AD) and to predict progression to Alzheimer's disease dementia (AD-d). METHODS: Prospective study of MCI patients in a tertiary memory disorder unit. Patients underwent an extensive neuropsychological battery including two tests of declarative verbal memory: The Free and Cued Selective Reminding Test (FCSRT) and the word list learning task from the Consortium to Establish a Registry for Alzheimer's disease (CERAD-WL). Cerebrospinal fluid (CSF) was obtained from all patients and MCI-AD was defined by means of the t-Tau/Aβ1-42 ratio. Logistic regression analyses tested whether the combination of FCSRT and CERAD-WL measures significantly improved the prediction of MCI-AD. Progression to AD-d was analyzed in a Cox regression model. RESULTS: A total of 202 MCI patients with a mean follow-up of 34.2±24.2 months were included and 98 (48.5%) met the criteria for MCI-AD. The combination of FCSRT and CERAD-WL measures improved MCI-AD classification accuracy based on CSF biomarkers. Both tests yielded similar global predictive values (59.9-65.3% and 59.4-62.8% for FCSRT and CERAD-WL, respectively). MCI-AD patients with deficits in both FCSRT and CERAD-WL had a faster progression to AD-d than patients with deficits in only one test. CONCLUSIONS: The combination of FCSRT and CERAD-WL improves the classification of MCI-AD and defines different prognostic profiles. These findings have important implications for clinical practice and the design of clinical trials.

Differential Hemispheric Predilection of Microstructural White Matter and Functional Connectivity Abnormalities between Respectively Semantic and Behavioral Variant Frontotemporal Dementia. - Meijboom, Rozanna; Steketee, Rebecca M E; Ham, Leontine S; van der Lugt, Aad; van Swieten, John C; Smits, Marion (J Alzheimers Dis, 2017)
Semantic dementia (SD) and behavioral variant frontotemporal dementia (bvFTD), subtypes of frontotemporal dementia, are characterized by distinct clinical symptoms and neuroimaging features, with predominant left temporal grey matter (GM) atrophy in SD and bilateral or right frontal GM atrophy in bvFTD. Such differential hemispheric predilection may also be reflected by other neuroimaging features, such as brain connectivity. This study investigated white matter (WM) microstructure and functional connectivity differences between SD and bvFTD, focusing on the hemispheric predilection of these differences. Eight SD and 12 bvFTD patients, and 17 controls underwent diffusion tensor imaging and resting state functional MRI at 3T. Whole-brain WM microstructure was assessed to determine distinct WM tracts affected in SD and bvFTD. For these tracts, diffusivity measures and lateralization indices were calculated. Functional connectivity was established for GM regions affected in early stage SD or bvFTD. Results of a direct comparison between SD and bvFTD are reported. Whole-brain WM microstructure abnormalities were more pronounced in the left hemisphere in SD and bilaterally- with a slight predilection for the right- in bvFTD. Lateralization of tract-specific abnormalities was seen in SD only, toward the left hemisphere. Functional connectivity of disease-specific regions was mainly decreased bilaterally in SD and in the right hemisphere in bvFTD. SD and bvFTD show WM microstructure and functional connectivity abnormalities in different regions, that are respectively more pronounced in the left hemisphere in SD and in the right hemisphere in bvFTD. This indicates differential hemispheric predilection of brain connectivity abnormalities between SD and bvFTD.

Dual Mechanism of Toxicity for Extracellular Injection of Tau Oligomers versus Monomers in Human Tau Mice. - Manassero, Giusi; Guglielmotto, Michela; Monteleone, Debora; Vasciaveo, Valeria; Butenko, Olena; Tamagno, Elena; Arancio, Ottavio; Tabaton, Massimo (J Alzheimers Dis, 2017)
The mechanism of tau toxicity is still unclear. Here we report that recombinant tau oligomers and monomers, intraventricularly injected in mice with a pure human tau background, foster tau pathology through different mechanisms. Oligomeric forms of tau alter the conformation of tau in a paired helical filament-like manner. This effect occurs without tau hyperphosphorylation as well as activation of specific kinases, suggesting that oligomers of tau induce tau assembly through a nucleation effect. Monomers, in turn, induce neurodegeneration through a calpain-mediated tau cleavage that leads to accumulation of a 17 kDa neurotoxic peptide and induction of apoptotic cell death.

Early Detection of Learning Difficulties when Confronted with Novel Information in Preclinical Alzheimer's Disease Stage 1. - Tort-Merino, Adrià; Valech, Natalia; Peñaloza, Claudia; Grönholm-Nyman, Petra; León, María; Olives, Jaume; Estanga, Ainara; Ecay-Torres, Mirian; Fortea, Juan; Martínez-Lage, Pablo; Molinuevo, José L; Laine, Matti; et al. (J Alzheimers Dis, 2017)
We employed a highly demanding experimental associative learning test (the AFE-T) to explore memory functioning in Preclinical Alzheimer's Disease stage 1 (PreAD-1) and stage 2 (PreAD-2). The task consisted in the learning of unknown object/name pairs and our comprehensive setup allowed the analysis of learning curves, immediate recall, long-term forgetting rates at one week, three months, and six months, and relearning curves. Forty-nine cognitively healthy subjects were included and classified according to the presence or absence of abnormal CSF biomarkers (Control, n = 31; PreAD-1, n = 14; PreAD-2, n = 4). Control and PreAD-1 performances on the experimental test were compared by controlling for age and education. These analyses showed clear learning difficulties in PreAD-1 subjects (F = 6.98; p = 0.01). Between-group differences in long-term forgetting rates were less notable, reaching statistical significance only for the three-month cued forgetting rate (F = 4.83; p = 0.03). Similarly, relearning sessions showed only statistical trends between the groups (F = 3.22; p = 0.08). In the whole sample, significant correlations between CSF Aβ42/tau ratio and the AFE-T were found, both in the total learning score (r = 0.52; p < 0.001) and in the three-month cued forgetting rate (r = -0.38; p < 0.01). Descriptive subanalyses involving PreAD-2 suggested greater learning and recall difficulties in these subjects when compared with the PreAD-1 group. The present results suggest that explicit learning difficulties when binding information could be one of the earliest signs of the future emergence of episodic memory difficulties on the Alzheimer's disease continuum. Our findings indicate that the AFE-T is a sensitive test, capable of detecting subtle memory difficulties in PreAD-1.

EEG Dominant Frequency Peak Differentiates Between Alzheimer's Disease and Frontotemporal Lobar Degeneration. - Goossens, Joery; Laton, Jorne; Van Schependom, Jeroen; Gielen, Jeroen; Struyfs, Hanne; Van Mossevelde, Sara; Van den Bossche, Tobi; Goeman, Johan; De Deyn, Peter Paul; Sieben, Anne; Martin, Jean-Jacques; Van Broeckhoven, Christine; et al. (J Alzheimers Dis, 2017)
We investigated the power of EEG as biomarker in differential diagnosis of Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD). EEG was recorded from 106 patients with AD or FTLD, of which 37 had a definite diagnosis, and 40 controls. Dominant frequency peaks were extracted for all 19 channels, for each subject. The average frequency of the largest dominant frequency peaks (maxpeak) was significantly lower in AD than FTLD patients and controls. Based on ROC analysis, classification could be made with diagnostic accuracy of 78.9%. Our findings show that quantitative analysis of EEG maxpeak frequency is an easy and useful measure for differential dementia diagnosis.

Effect of APOE Genotype on Amyloid Deposition, Brain Volume, and Memory in Cognitively Normal Older Individuals. - Lim, Yen Ying; Williamson, Robert; Laws, Simon M; Villemagne, Victor L; Bourgeat, Pierrick; Fowler, Christopher; Rainey-Smith, Stephanie; Salvado, Olivier; Martins, Ralph N; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2017)
BACKGROUND: The association between the apolipoprotein E (APOE) ɛ4 allele and high risk of developing Alzheimer's disease (AD) dementia before the age of 80 has been recognized for over 30 years. However, the timing and mode of action of APOE is not understood, nor has there been a detailed analysis of the effect of APOE genotype on memory, hippocampal volume, and amyloid-β (Aβ) levels in cognitively normal adults. OBJECTIVE: Examine the effect of APOE allelic genotype on the relationship between Aβ levels, hippocampal volume, and memory in cognitively normal adults. METHODS: This is a cross-sectional study of 989 cognitively normal older adults enrolled in the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, all of whom underwent APOE genotyping and memory assessment. A subset of this group underwent PET neuroimaging for Aβ (n = 585) and MRI for hippocampal volume (n = 303). RESULTS: APOEɛ4 homozygotes (ɛ4/ɛ4) showed significantly worse episodic memory and higher Aβ levels than ɛ4 heterozygotes. The relationship between increasing Aβ levels and worse episodic memory was significant for ɛ3 homozygotes (ɛ3/ɛ3), ɛ4 heterozygotes, and strongest for ɛ4 homozygotes. There were no differences in hippocampal volume between APOE groups; the relationship between smaller hippocampal volume and worse episodic memory was significant only for ɛ4 homozygotes. CONCLUSION: APOE acts in a co-dominant fashion on Aβ levels, episodic memory, and hippocampal volume in cognitively normal older adults. APOEɛ4 is central to the events that lead to AD in cognitively normal older adults, likely through a quantitative role in the disruption of Aβ clearance.

Effect of APOE ε4 Genotype on Metabolic Biomarkers in Aging and Alzheimer's Disease. - Morris K, Jill; Uy, Roxanne Adeline Z; Vidoni, Eric D; Wilkins, Heather M; Archer, Ashley E; Thyfault, John P; Miles, John M; Burns, Jeffrey M (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) may have heterogeneous pathophysiological underpinnings, with risk factors including apolipoprotein rmvarep4 (APOE4) genotype and insulin resistance. We hypothesized that distinct phenotypes exist within AD. We examined APOE4 and metabolic biomarkers in 338 subjects (n = 213 nondemented (ND), n = 125 AD). We further characterized steady state free fatty acid (FFA) levels in a subset of 45 participants who had also participated in a hyperinsulinemic-euglycemic clamp. Insulin resistance (HOMA-IR) was elevated in AD versus ND (p = 0.04) and in APOE4 noncarriers versus carriers (p < 0.01). This was driven by increased fasting insulin in AD versus ND (p < 0.01) and in APOE4 non-carriers versus carriers (p = 0.01). Fasting glucose was not different. In subjects who underwent a clamp, there was a group x genotype interaction on FFA levels during hyperinsulinemia (p = 0.03). APOE4 non-carriers with AD had higher FFA levels, while APOE4 carriers with AD exhibited lower FFA levels. Metabolic dysfunction is overrepresented in individuals with AD dementia who do not carry the APOE4 allele. This suggests that important subsets of AD phenotypes may exist that diverge metabolically.

Effect of Attention Training in Mild Cognitive Impairment Patients with Subcortical Vascular Changes: The RehAtt Study. - Pantoni, Leonardo; Poggesi, Anna; Diciotti, Stefano; Valenti, Raffaella; Orsolini, Stefano; Della Rocca, Eleonora; Inzitari, Domenico; Mascalchi, Mario; Salvadori, Emilia (J Alzheimers Dis, 2017)
BACKGROUND AND OBJECTIVE: Mild cognitive impairment (MCI) patients with small vessel disease (SVD) are at high dementia risk. We tested the effects of cognitive rehabilitation in these patients using the Attention Process Training-II (APT-II) program in a single-blinded, randomized clinical trial. METHODS: Patients were randomized to APT-II or standard care and evaluated at baseline, 6, and 12 months with functional, quality of life, cognitive tests, and resting state functional MRI (rsfMRI). RESULTS: Forty-six patients were enrolled and 43 (mean±SD age 75.1±6.8) completed the study. No change was seen in functionality and quality of life between treated and non-treated patients. However, the Rey Auditory-Verbal Learning Test immediate recall showed a significant improvement in treated compared to non-treated group (change score 6 versus 12 months: 1.8±4.9 and -1.4±3.8, p = 0.021; baseline versus 12 months: 3.8±6.1 and 0.2±4.4, p = 0.032). A higher proportion of treated patients had stable/better evaluation compared to non-treated group on Visual search test (6 versus 12 months: 95% versus 71%, p = 0.038) and Rey-Osterrieth Complex Figure copy (6 versus 12 months: 95% versus 67%, p = 0.027). RsfMRI, performed in a subsample, showed that the difference between follow-up and baseline in synchronization of activity in cerebellar areas was significantly greater in treated than in non-treated patients. CONCLUSION: We were unable to show a significant effect in quality of life or functional status in treated patients with MCI and SVD. However, APT-II produces some beneficial effects in focused attention and working memory and seems to increase activity in brain circuits involved in cognitive processes.

Episodic Memory Dysfunction in Behavioral Variant Frontotemporal Dementia: A Clinical And FDG-PET Study. - Fernández-Matarrubia, Marta; Matías-Guiu, Jordi A; Cabrera-Martín, María Nieves; Moreno-Ramos, Teresa; Valles-Salgado, María; Carreras, José Luis; Matías-Guiu, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory disturbance is still considered as an exclusion criterion for behavioral variant frontotemporal dementia (bvFTD), but growing evidence suggests that memory can be impaired. OBJECTIVE: Our main purposes were to assess episodic memory in a group of bvFTD patients comparatively with Alzheimer's disease (AD) patients, and analyze the relationship between episodic memory and brain metabolism measured using positron emission tomography imaging with 18F-fluorodeoxyglucose (FDG-PET). METHODS: Twenty-six bvFTD, 29 AD, and 24 healthy controls were included. Episodic memory was assessed by the Free and Cued Selective Reminding Test (FCSRT), which controls for effective encoding and measures memory consolidation processing. All participants underwent FDG-PET brain scans to provide data for voxel-based brain mapping analysis. RESULTS: Half of bvFTD patients had a deficit of total, free delayed, and total free delayed recall as severe as AD patients (amnestic-FTD). The other half had FCSRT scores similar to controls (non-amnestic-FTD). Imaging analyses revealed that amnestic-FTD showed bilateral lower metabolism than non-amnestic-FTD in anterior parahippocampal and inferior temporal gyri. Additionally, FCSRT total and total delayed scores were inversely correlated with parahippocampal metabolism in both bvFTD and AD. Besides, bvFTD showed an inverse association among FCSRT and inferior temporal metabolism. CONCLUSIONS: Our findings support that bvFTD could present a genuine amnesia affecting storage and consolidation abilities, which involves structures implicated in the Papez circuit, as occurs in AD, and also inferior temporal regions. These results contribute to understanding the mechanisms underpinning memory dysfunction in bvFTD, and may be relevant to further revisions of the current diagnostic criteria.

Ethical Considerations for Deep Brain Stimulation Trials in Patients with Early-Onset Alzheimer's Disease. - Viaña, John Noel M; Bittlinger, Merlin; Gilbert, Frederic (J Alzheimers Dis, 2017)
Several studies of deep brain stimulation (DBS) of the fornix or the nucleus basalis of Meynert have been recently conducted in people with Alzheimer's disease, with several recruiting participants <65 and thus have early-onset Alzheimer's disease (EOAD). Although EOAD accounts for less than 5.5% of AD cases, ethical considerations must still be made when performing DBS trials including these participants since a portion of people with EOAD, especially those possessing autosomal-dominant mutations, have an atypical and more aggressive disease progression. These considerations include appropriate patient selection and signing of an informed consent for genetic testing; appropriate study design; potential outcomes that people with EOAD could expect; and accurate interpretation and balanced discussion of trial results. Finally, recommendations for future DBS for AD trials will be made to ensure that EOAD patients will not experience avoidable harms should they be enrolled in these experimental studies.

Ethnic Variations in Prognosis of Patients with Dementia: A Prospective Nationwide Registry Linkage Study in The Netherlands. - Agyemang, Charles; van de Vorst, Irene E; Koek, Huiberdina L; Bots, Michiel L; Seixas, Azizi; Norredam, Marie; Ikram, Umar; Stronks, Karien; Vaartjes, Ilonca (J Alzheimers Dis, 2017)
BACKGROUND: Data on dementia prognosis among ethnic minority groups are limited in Europe. OBJECTIVE: We assessed differences in short-term (1-year) and long-term (3-year) mortality and readmission risk after a first hospitalization or first ever referral to a day clinic for dementia between ethnic minority groups and the ethnic Dutch population in the NetherlandsMethods: Nationwide prospective cohorts of first hospitalized dementia patients (N = 55,827) from January 1, 2000 to December 31, 2010 were constructed. Differences in short-term and long-term mortality and readmission risk following hospitalization or referral to the day clinic between ethnic minority groups (Surinamese, Turkish, Antilleans, Indonesians) and the ethnic Dutch population were investigated using Cox proportional hazard regression models with adjustment for age, sex, and comorbidities. RESULTS: Age-sex-adjusted short-term and long-term risks of death following a first hospitalization with dementia were comparable between the ethnic minority groups and the ethnic Dutch. Age- and sex-adjusted risk of admission was higher only in Turkish compared with ethnic Dutch (HR 1.57, 95% CI,1.08-2.29). The difference between Turkish and the Dutch attenuated and was no longer statistically significant after further adjustment for comorbidities. There were no ethnic differences in short-term and long-term risk of death, and risk of readmission among day clinic patients. CONCLUSION: Compared with Dutch patients with a comparable comorbidity rate, ethnic minority patients with dementia did not have a worse prognosis. Given the poor prognosis of dementia, timely and targeted advance care planning is essential, particularly in ethnic minority groups who are mired by cultural barriers and where uptake of advance care planning is known to be low.

Evidence that the Human Innate Immune Peptide LL-37 may be a Binding Partner of Amyloid-β and Inhibitor of Fibril Assembly. - De Lorenzi, Ersilia; Chiari, Marcella; Colombo, Raffaella; Cretich, Marina; Sola, Laura; Vanna, Renzo; Gagni, Paola; Bisceglia, Federica; Morasso, Carlo; Lin, Jennifer S; Lee, Moonhee; McGeer, Patrick L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Identifying physiologically relevant binding partners of amyloid-β (Aβ) that modulate in vivo fibril formation may yield new insights into Alzheimer's disease (AD) etiology. Human cathelicidin peptide, LL-37, is an innate immune effector and modulator, ubiquitous in human tissues and expressed in myriad cell types. OBJECTIVE: We present in vitro experimental evidence and discuss findings supporting a novel hypothesis that LL-37 binds to Aβ42 and can modulate Aβ fibril formation. METHODS: Specific interactions between LL-37 and Aβ (with Aβ in different aggregation states, assessed by capillary electrophoresis) were demonstrated by surface plasmon resonance imaging (SPRi). Morphological and structural changes were investigated by transmission electron microscopy (TEM) and circular dichroism (CD) spectroscopy. Neuroinflammatory and cytotoxic effects of LL-37 alone, Aβ42 alone, and LL-37/Aβ complexes were evaluated in human microglia and neuroblastoma cell lines (SH-SY5Y). RESULTS: SPRi shows binding specificity between LL-37 and Aβ, while TEM shows that LL-37 inhibits Aβ42 fibril formation, particularly Aβ's ability to form long, straight fibrils characteristic of AD. CD reveals that LL-37 prevents Aβ42 from adopting its typical β-type secondary structure. Microglia-mediated toxicities of LL-37 and Aβ42 to neurons are greatly attenuated when the two peptides are co-incubated prior to addition. We discuss the complementary biophysical characteristics and AD-related biological activities of these two peptides. CONCLUSION: Based on this body of evidence, we propose that LL-37 and Aβ42 may be natural binding partners, which implies that balanced (or unbalanced) spatiotemporal expression of the two peptides could impact AD initiation and progression.

Failure to Recover from Proactive Semantic Interference and Abnormal Limbic Connectivity in Asymptomatic, Middle-Aged Offspring of Patients with Late-Onset Alzheimer's Disease. - Sánchez, Stella M; Abulafia, Carolina; Duarte-Abritta, Barbara; de Guevara, M Soledad Ladrón; Castro, Mariana N; Drucaroff, Lucas; Sevlever, Gustavo; Nemeroff, Charles B; Vigo, Daniel E; Loewenstein, David A; Villarreal, Mirta F; Guinjoan, Salvador M (J Alzheimers Dis, 2017)
BACKGROUND: We have obtained previous evidence of limbic dysfunction in middle-aged, asymptomatic offspring of late-onset Alzheimer's disease (LOAD) patients, and failure to recover from proactive semantic interference has been shown to be a sensitive cognitive test in other groups at risk for LOAD. OBJECTIVE: To assess the effects of specific proactive semantic interference deficits as they relate to functional magnetic resonance imaging (fMRI) neocortical and limbic functional connectivity in middle aged offspring of individuals with LOAD (O-LOAD) and age-equivalent controls. METHODS: We examined 21 O-LOAD and 20 controls without family history of neurodegenerative disorders (CS) on traditional measures of cognitive functioning and the LASSI-L, a novel semantic interference test uniquely sensitive to the failure to recover from proactive interference (frPSI). Cognitive tests then were correlated to fMRI connectivity of seeds located in entorhinal cortex and anterodorsal thalamic nuclei among O-LOAD and CS participants. RESULTS: Relative to CS, O-LOAD participants evidenced lower connectivity between entorhinal cortex and orbitofrontal, anterior cingulate, and anterior temporal cortex. In the offspring of LOAD patients, LASSI-L measures of frPSI were inversely associated with connectivity between anterodorsal thalamus and contralateral posterior cingulate. Intrusions on the task related to frPSI were inversely correlated with a widespread connectivity network involving hippocampal, insular, posterior cingulate, and dorsolateral prefrontal cortices, along with precunei and anterior thalamus in this group. Different patterns of connectivity associated with frPSI were observed among controls. CONCLUSION: The present results suggest that both semantic interference deficits and connectivity abnormalities might reflect limbic circuit dysfunction as a very early clinical signature of LOAD pathology, as previously demonstrated for other limbic phenotypes, such as sleep and circadian alterations.

Feasibility of Lumbar Puncture in the Study of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease in Subjects with Down Syndrome. - Carmona-Iragui, María; Santos, Telma; Videla, Sebastián; Fernández, Susana; Benejam, Bessy; Videla, Laura; Alcolea, Daniel; Blennow, Kaj; Blesa, Rafael; Lleo, Alberto; Fortea, Juan (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is the main medical problem in older adults with Down syndrome (DS). Studies of cerebrospinal fluid (CSF) AD biomarkers are limited and the feasibility of lumbar puncture (LP) is controversial in this population. OBJECTIVE: To analyze the frequency of complications after a LP in DS. METHODS: We collected data from 80 adults with DS that underwent a LP within the Down Alzheimer Barcelona Neuroimaging Initiative. Demographics, cognitive status, headache history, and presence of complications after the LP were recorded in every subject. In 53 of them (active group), this information was collected following a semi-structured and validated protocol that actively looks for complications. Other variables related to the LP procedure were also recorded. A telephone interview to the caregiver was performed 5-7 days after the procedure to ask about complications. Data from 27 subjects (clinical practice group), from whom the presence of complications was obtained in a medical follow-up visit within the three months after the LP, were also included. RESULTS: There were no adverse events in 90% of our participants. The most frequent complication was headache (6.25%); only one subject reported a typical post-lumbar puncture headache with moderate severity that required analgesic treatment. Dizziness (3.75%) and back pain (1.25%) were also reported. All the participants that reported complications belonged to the active group. CONCLUSION: LP can be safely performed to study CSF biomarkers in DS. The reported complications are qualitatively similar to the general population, but are less frequently reported, even when actively searched for.

Finger-to-Nose Test Findings in Alzheimer's Disease. - Bergeron, David; Vermette, Antoine; De La Sablonnière, Justine; Cayer, Anne-Marie; Laforce, Robert; Bouchard, Rémi W (J Alzheimers Dis, 2017)
The finger-to-nose test is routinely performed during the clinical assessment of patients with cognitive impairments. Although widely known to screen for cerebellar dysfunction by unmasking appendicular ataxia, we have found that this test could also be interpreted from a cognitive perspective. We describe two typical signs observed at the finger-to-nose test in Alzheimer's disease (AD) patients: the "second finger syndrome" and the "distal pressure sign". By retrospectively reviewing the medical records 461 patients followed at our academic memory clinic, we found that these signs are commonplace in AD, but not in vascular dementia or subjective cognitive impairment.

Framingham Risk Score and the Risk of Progression from Mild Cognitive Impairment to Dementia. - Viticchi, Giovanna; Falsetti, Lorenzo; Buratti, Laura; Sajeva, Giulia; Luzzi, Simona; Bartolini, Marco; Provinciali, Leandro; Silvestrini, Mauro (J Alzheimers Dis, 2017)
BACKGROUND: Mild cognitive impairment (MCI) often represents the clinical manifestation of cognitive deterioration preceding Alzheimer's disease (AD). Currently, there are no reliable approaches for an objective evaluation of the risk of developing AD in MCI patients. OBJECTIVE: The aim of this study was to verify whether the Framingham cardiovascular risk profile (FCRP) could be useful to identify patients at the highest risk of conversion from MCI to AD. METHODS: Patients with amnestic MCI (aMCI) were carefully investigated to assess their vascular risk profile. They were also submitted to a comprehensive neuropsychological evaluation. The FCRP was calculated for each patient and the apolipoprotein E (ApoE) genotype was determined from peripheral blood cells. The main outcome was defined as a conversion to AD within 24 months after inclusion. RESULTS: 385 consecutive aMCI subjects were included. Age, FCRP, and vascular age showed a fairly predictive value on conversion to AD. Selecting the subpopulation of ApoE ɛ4 carriers, we observed that FCRP had an increased performance in predicting the conversion. The rate of conversion increased from 12.5% in the FCRP low-risk group to 43.2% in the high-risk group (p < 0.0001). ApoE ɛ4 carriers had a 3.7-times increased probability of conversion with respect to the other subjects (p < 0.0001). CONCLUSIONS: FCRP assessment could be considered a reliable approach to predict conversion to AD in aMCI subjects. The presence of ApoE ɛ4 increases significantly the risk of conversion. These data confirm the narrow relationship between genetic and vascular risk factors in influencing the evolution of cognitive impairment.

Functional Disintegration of the Default Mode Network in Prodromal Alzheimer's Disease. - Dillen, Kim N H; Jacobs, Heidi I L; Kukolja, Juraj; Richter, Nils; von Reutern, Boris; Onur, Özgür A; Langen, Karl-Josef; Fink, Gereon R (J Alzheimers Dis, 2017)
Neurodegenerative brain changes can affect the functional connectivity strength between nodes of the default-mode network (DMN), which may underlie changes in cognitive performance. It remains unclear how the functional connectivity strength of DMN nodes differs from healthy to pathological aging and whether these changes are cognitively relevant. We used resting-state functional magnetic resonance imaging to investigate the functional connectivity strength across five DMN nodes in 25 healthy controls (HC), 28 subjective cognitive decline (SCD) participants, and 25 prodromal Alzheimer's disease (AD) patients. After identifying the ventral medial prefrontal cortex (vmPFC), posterior cingulate cortex (PCC), retrosplenial cortex (RSC), inferior parietal lobule, and the hippocampus we investigated the functional strength between DMN nodes using temporal network modeling. Functional coupling of the vmPFC and PCC in prodromal AD patients was disrupted. This vmPFC-PCC coupling correlated positively with memory performance in prodromal AD. Furthermore, the hippocampus de-coupled from posterior DMN nodes in SCD and prodromal AD patients. There was no coupling between the hippocampus and the anterior DMN. Additional mediation analyses indicated that the RSC enables communication between the hippocampus and DMN regions in HC but none of the other two groups. These results suggest an anterior-posterior disconnection and a hippocampal de-coupling from posterior DMN nodes with disease progression. Hippocampal de-coupling already occurring in SCD may provide valuable information for the development of a functional biomarker.

Gender-Specific Degeneration of Dementia-Related Subcortical Structures Throughout the Lifespan. - Nemeth, Viola Luca; Must, Anita; Horvath, Szatmar; Király, Andras; Kincses, Zsigmond Tamas; Vecsei, Laszlo (J Alzheimers Dis, 2017)
Age-related changes in brain structure are a question of interest to a broad field of research. Structural decline has been consistently, but not unambiguously, linked to functional consequences, including cognitive impairment and dementia. One of the areas considered of crucial importance throughout this process is the medial temporal lobe, and primarily the hippocampal region. Gender also has a considerable effect on volume deterioration of subcortical grey matter (GM) structures, such as the hippocampus. The influence of age×gender interaction on disproportionate GM volume changes might be mediated by hormonal effects on the brain. Hippocampal volume loss appears to become accelerated in the postmenopausal period. This decline might have significant influences on neuroplasticity in the CA1 region of the hippocampus highly vulnerable to pathological influences. Additionally, menopause has been associated with critical pathobiochemical changes involved in neurodegeneration. The micro- and macrostructural alterations and consequent functional deterioration of critical hippocampal regions might result in clinical cognitive impairment-especially if there already is a decline in the cognitive reserve capacity. Several lines of potential vulnerability factors appear to interact in the menopausal period eventually leading to cognitive decline, mild cognitive impairment, or Alzheimer's disease. This focused review aims to delineate the influence of unmodifiable risk factors of neurodegenerative processes, i.e., age and gender, on critical subcortical GM structures in the light of brain derived estrogen effects. The menopausal period appears to be of key importance for the risk of cognitive decline representing a time of special vulnerability for molecular, structural, and functional influences and offering only a narrow window for potential protective effects.

Genetic Risk as a Marker of Amyloid-β and Tau Burden in Cerebrospinal Fluid. - Voyle, Nicola; Patel, Hamel; Folarin, Amos; Newhouse, Stephen; Johnston, Caroline; Visser, Pieter Jelle; Dobson, Richard J B; Kiddle, Steven J (J Alzheimers Dis, 2017)
BACKGROUND: The search for a biomarker of Alzheimer's disease (AD) pathology (amyloid-β (Aβ) and tau) is ongoing, with the best markers currently being measurements of Aβ and tau in cerebrospinal fluid (CSF) and via positron emission tomography (PET) scanning. These methods are relatively invasive, costly, and often have high screening failure rates. Consequently, research is aiming to elucidate blood biomarkers of Aβ and tau. OBJECTIVE: This study aims to investigate a case/control polygenic risk score (PGRS) as a marker of tau and investigate blood markers of a combined Aβ and tau outcome for the first time. A sub-study also considers plasma tau as markers of Aβ and tau pathology in CSF. METHODS: We used data from the EDAR*, DESCRIPA**, and Alzheimer's Disease Neuroimaging Initiative (ADNI) cohorts in a logistic regression analysis to investigate blood markers of Aβ and tau in CSF. In particular, we investigated the extent to which a case/control PGRS is predictive of CSF tau, CSF amyloid, and a combined amyloid and tau outcome. The predictive ability of models was compared to that of age, gender, and APOE genotype ('basic model'). RESULTS: In EDAR and DESCRIPA test data, inclusion of a case/control PGRS was no more predictive of Aβ, and a combined Aβ and tau endpoint than the basic models (accuracies of 66.0%, and 73.3% respectively). The tau model saw a small increase in accuracy compared to basic models (59.6%). ADNI 2 test data also showed a slight increase in accuracy for the Aβ model when compared to the basic models (61.4%). CONCLUSION: We see some evidence that a case/control PGRS is marginally more predictive of Aβ and tau pathology than the basic models. The search for predictive factors of Aβ and tau pathologies, above and beyond demographic information, is still ongoing. Better understanding of AD risk alleles, development of more sensitive assays, and studies of larger sample size are three avenues that may provide such factors. However, the clinical utility of possible predictors of brain Aβ and tau pathologies must also be investigated.*'Beta amyloid oligomers in the early diagnosis of AD and as marker for treatment response'**'Development of screening guidelines and criteria for pre-dementia Alzheimer's disease'.

Genetic Stratification to Identify Risk Groups for Alzheimer's Disease. - Marioni, Riccardo E; Campbell, Archie; Hagenaars, Saskia P; Nagy, Reka; Amador, Carmen; Hayward, Caroline; Porteous, David J; Visscher, Peter M; Deary, Ian J (J Alzheimers Dis, 2017)
Stratification by genetic risk factors for Alzheimer's disease (AD) may help identify groups with the greatest disease risk. Biological changes that cause late-onset AD are likely to occur years, if not decades prior to diagnosis. Here, we select a subset of the Generation Scotland: Scottish Family Health Study cohort in a likely preclinical age-range of 60-70 years (subset n = 3,495 with cognitive and genetic data). We test for cognitive differences by polygenic risk scores for AD. The polygenic scores are constructed using all available SNPs, excluding those within a 500 kb distance of the APOE locus. Additive and multiplicative effects of APOE status on these associations are investigated. Small memory decrements were observed in those with high polygenic risk scores for AD (standardized beta -0.04, p = 0.020). These associations were independent of APOE status. There was no difference in AD polygenic scores across APOE haplotypes (p = 0.72). Individuals with high compared to low polygenic risk scores for AD (top and bottom 5% of the distribution) show cognitive decrements, albeit much smaller than for APOE ɛ4ɛ4 compared to ɛ3ɛ3 individuals (2.3 versus 3.5 fewer points on the processing speed test, and 1.8 versus 2.8 fewer points on the memory test). Polygenic risk scores for AD may help identify older individuals at greatest risk of cognitive decline and preclinical AD.

High Sensitivity Cardiac Troponin T and Cognitive Function in the Oldest Old: The Leiden 85-Plus Study. - Bertens, Anne Suzanne; Sabayan, Behnam; de Craen, Anton J M; Van der Mast, Roos C; Gussekloo, Jacobijn (J Alzheimers Dis, 2017)
BACKGROUND: Impaired cardiac function has been related to accelerated cognitive decline in late-life. OBJECTIVE: To investigate whether higher levels of high sensitivity cardiac troponin T (hs-cTnT), a sensitive marker for myocardial injury, are associated with worse cognitive function in the oldest old. METHODS: In 455 participants of the population-based Leiden 85-plus Study, hs-cTnT was measured at 86 years. Cognitive function was measured annually during four years with the Mini-Mental State Examination (MMSE). RESULTS: Participants in the highest gender-specific tertile of hs-cTnT had a 2.0-point lower baseline MMSE score than participants in the lowest tertile (95% confidence interval (CI) (95% CI 0.73-3.3), and had a 0.58-point steeper annual decline in MMSE during follow-up (95% CI 0.06-1.1). The associations remained after adjusting for sociodemographic and cardiovascular risk factors excluding those without a history of overt cardiac disease. CONCLUSION: In a population-based sample of the oldest old, higher levels of hs-cTnT were associated with worse cognitive function and faster cognitive decline, independently from cardiovascular risk factors and a history of overt cardiac disease.

Higher Peripheral TREM2 mRNA Levels Relate to Cognitive Deficits and Hippocampal Atrophy in Alzheimer's Disease and Amnestic Mild Cognitive Impairment. - Tan, Yi Jayne; Ng, Adeline S L; Vipin, Ashwati; Lim, Joseph K W; Chander, Russell J; Ji, Fang; Qiu, Yingwei; Ting, Simon K S; Hameed, Shahul; Lee, Tih-Shih; Zeng, Li; Kandiah, Nagaendran; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Variants in triggering receptor expressed on myeloid cells 2 (TREM2) are associated with increased Alzheimer's disease (AD) risk. Recent studies have reported inconsistent peripheral TREM2 mRNA expression levels and relationship with cognitive scores in AD and mild cognitive impairment (MCI). Additionally, no study has examined the association of peripheral TREM2 levels with neuroimaging measures in AD and MCI. OBJECTIVE: To determine peripheral TREM2 mRNA levels in AD, amnestic MCI (aMCI) and healthy controls, and the association with cognitive performance and brain structural changes. METHODS: We measured peripheral TREM2 mRNA levels in 80 AD, 30 aMCI, and 86 healthy controls using real time polymerase chain reaction. TREM2 levels were correlated with various cognitive performance and brain volumes, correcting for APOE4 status. RESULTS: TREM2 mRNA levels were significantly higher in AD compared to controls and aMCI. Levels did not differ between aMCI and controls. Corrected for APOE4, higher TREM2 levels correlated with lower Mini-Mental State Examination, Montreal Cognitive Assessment (MoCA) and episodic memory scores, and lower total grey matter and right hippocampal volumes. Whole-brain voxel-based morphometry analysis found negative association between TREM2 mRNA levels and grey matter volumes in temporal, parietal and frontal regions. AD subjects with MoCA scores ≤20 had higher TREM2 levels correlating with smaller total grey matter, left hippocampal and right hippocampal volumes. CONCLUSION: Peripheral TREM2 mRNA levels are higher in AD and are associated with AD-related cognitive deficits and hippocampal atrophy. Our findings suggest that TREM2 may be a potential non-invasive peripheral biomarker for AD diagnosis.

Homocysteine and Real-Space Navigation Performance among Non-Demented Older Adults. - Pařízková, Martina; Andel, Ross; Lerch, Ondřej; Marková, Hana; Gažová, Ivana; Vyhnálek, Martin; Hort, Jakub; Laczó, Jan (J Alzheimers Dis, 2017)
BACKGROUND: High plasma homocysteine (Hcy) level is related to higher risk of Alzheimer's disease (AD) and lower cognitive performance in older adults. OBJECTIVE: To assess the association between plasma Hcy level and real-space navigation performance and the role of vascular risk and protective factors, APOE status, and white matter lesions (WML) on this association. METHODS: Ninety-two non-demented older adults (29 with amnestic mild cognitive impairment, 46 with subjective cognitive decline, and 17 cognitively normal older adults) underwent spatial navigation testing of egocentric, allocentric, and mixed navigation in a real-space analogue of the Morris water maze, neuropsychological examination, blood collection, and MRI brain scan with evaluation of WML. RESULTS: In the regression analyses controlling for age, gender, education, and depressive symptoms, higher plasma Hcy level was related to worse mixed and egocentric (β= 0.31; p = 0.003 and β= 0.23; p = 0.017) but not allocentric (p > 0.05) navigation performance. Additional controlling for vascular risk and protective factors, WML, and APOE status did not modify the results. High total cholesterol and low vitamin B12 and folate levels increased the adverse effect of Hcy on egocentric and mixed navigation. WML did not explain the association between plasma Hcy level and navigation performance. CONCLUSION: Elevated plasma Hcy level may affect real-space navigation performance above and beyond vascular brain changes. This association may be magnified in the presence of high total cholesterol and low folate or vitamin B12 levels. Attention to the level of plasma Hcy may be a viable intervention strategy to prevent decline in spatial navigation in non-demented older adults.

Impact of Recruitment Methods in Subjective Cognitive Decline. - Abdelnour, Carla; Rodríguez-Gómez, Octavio; Alegret, Montserrat; Valero, Sergi; Moreno-Grau, Sonia; Sanabria, Ángela; Hernandez, Isabel; Rosende-Roca, Maitee; Vargas, Liliana; Mauleón, Ana; Sánchez, Domingo; Espinosa, Ana; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recruitment methods can determine sample characteristics in mild cognitive impairment and Alzheimer's disease dementia, but little is known about its influence in subjective cognitive decline (SCD). OBJECTIVE: To determine the influence of two types of recruitment methods in the characteristics of individuals with SCD. METHODS: We select and compare clinical and neuropsychological features, and frequency of APOE ɛ4 allele of 326 subjects with SCD from two cohorts: Open House Initiative (OHI) versus Memory Unit (MU). A logistic regression analysis (LRA), using gender and years of education as covariates, was used to examine the neuropsychological variables. RESULTS: The OHI sample were mostly women (75.9% versus 64.5%, p < 0.05), with higher educational level (12.15 [3.71] versus 10.70 [3.80] years, p = 0.001), and more family history of dementia (138 [62.7%] versus 44 [41.5%], p < 0.001) than the MU sample. Also, the OHI sample showed better overall neuropsychological performance than the MU sample, and after a LRA, this trend continued in automatic response inhibition capacity, abstract reasoning, and recognition memory. We did not find differences in age, depression history, and/or APOE ɛ4 allele frequency. CONCLUSION: SCD subjects showed different demographic and neuropsychological characteristics depending on the recruitment method, which should be taken into account in the design of research studies with this target population.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.

In vivo Patterns of Tau Pathology, Amyloid-β Burden, and Neuronal Dysfunction in Clinical Variants of Alzheimer's Disease. - Dronse, Julian; Fliessbach, Klaus; Bischof, Gérard N; von Reutern, Boris; Faber, Jennifer; Hammes, Jochen; Kuhnert, Georg; Neumaier, Bernd; Onur, Oezguer A; Kukolja, Juraj; van Eimeren, Thilo; Jessen, Frank; et al. (J Alzheimers Dis, 2017)
The clinical heterogeneity of Alzheimer's disease is not reflected in the rather diffuse cortical deposition of amyloid-β. We assessed the relationship between clinical symptoms, in vivo tau pathology, amyloid distribution, and hypometabolism in variants of Alzheimer's disease using novel multimodal PET imaging techniques. Tau pathology was primarily observed in brain regions related to clinical symptoms and overlapped with areas of hypometabolism. In contrast, amyloid-β deposition was diffusely distributed over the entire cortex. Tau PET imaging may thus serve as a valuable biomarker for the localization of neuronal injury in vivo and may help to validate atypical subtypes of Alzheimer's disease.

Incident Cerebral Microbleeds Detected by Susceptibility Weight-Imaging Help to Identify Patients with Mild Cognitive Impairment Progressing to Alzheimer's Disease. - Basselerie, Hubert; Bracoud, Luc; Zeestraten, Eva; Bouguen, Eva; Kiyasova, Vera; Pueyo, Maria; Cognard, Christophe; Dumas, Hervé; Gramada, Raluca; Ousset, Pierre Jean; Vellas, Bruno; Bonneville, Fabrice (J Alzheimers Dis, 2017)
BACKGROUND: The relationship between cerebral microbleeds (CMB) and Alzheimer's disease (AD) has not yet been clearly determined, particularly with susceptibility weight-imaging (SWI). OBJECTIVE: To evaluate the SWI sequence using 3T MRI for the detection of CMB, and its ability to differentiate elderly control subjects (CS), stable mild cognitive impairment patients (MCI-s), MCI patients progressing to AD (MCI-p), and AD patients. METHODS: It was a prospective, monocentric, observational study that took place in Toulouse, France. Participants were 65 years and older, enrolled in three groups: CS, MCI, and AD. Based on the longitudinal analysis of cognitive decline, MCI subjects were retrospectively classified as MCI-s or MCI-p. Each patient had a 4-year follow-up with MRI at baseline (MRI#1) and during the fourth year (MRI#3). CMB were counted on native SWI images juxtaposed to minIP reformatted images. RESULTS: 150 patients were enrolled: 48 CS, 25 MCI-s, 18 MCI-p, 59 AD. At MRI#1 and at MRI#3, there was no significant difference in the prevalence of CMB between groups (p = 0.75 and p = 0.87). In the MCI-p + AD group, significantly more subjects had≥4 incident CMB compared to the CS + MCI-s group (p = 0.016). In the MCI-p + AD group, the prevalence of patients with >4 CMB was significantly higher at MRI#3 than at MRI#1 (p = 0.008). CONCLUSION: Using SWI, AD and MCI-p patients had developed significantly more new CMB than CS and MCI-s patients during the follow-up. Incident CMB might be suggested as a potential imaging marker of AD progression.

Increased Carbohydrate Intake is Associated with Poorer Performance in Verbal Memory and Attention in an APOE Genotype-Dependent Manner. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Sohrabi, Hamid R; Weinborn, Michael; Verdile, Giuseppe; Fernando, W M A D Binosha; Lim, Yen Ying; Harrington, Karra; Burnham, Samantha; Taddei, Kevin; Masters, Colin L; Macaulay, Stuart L; et al. (J Alzheimers Dis, 2017)
Evidence suggests that a diet low in carbohydrates can impact on cognitive performance among those with Alzheimer's disease (AD). However, there is a lack of data assessing this relationship among cognitively normal (CN) older adults at increased future risk of developing AD due to carriage of the apolipoprotein E (APOE) ɛ4 allele. We assessed the cross-sectional association between carbohydrate intake, cognitive performance, and cerebral amyloid-β (Aβ) load in CN older adults, genotyped for APOEɛ4 allele carrier status. Greater carbohydrate intake was associated with poorer performance in verbal memory in APOEɛ4 allele non-carriers, and poorer performance in attention in APOEɛ4 allele carriers. There were no associations between carbohydrate intake and cerebral Aβ load. These results provide support to the idea that decreasing carbohydrate intake may offer neurocognitive benefits, with specific cognitive domains affected in an APOE genotype-dependent manner. These findings warrant further investigation utilizing a longitudinal study design.

Intensive 'Brain Training' Intervention Fails to Reduce Amyloid Pathologies or Cognitive Deficits in Transgenic Mouse Models of Alzheimer's Disease. - Anderson, Maria; Xu, Feng; Ou-Yang, Ming-Hsuan; Davis, Judianne; Van Nostrand, William E; Robinson, John K (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is the leading cause of dementia in the elderly. Amyloid-β protein (Aβ) depositions in both the brain parenchyma and the cerebral vasculature are recognized as important pathological components that contribute to the cognitive impairments found in individuals with AD. Because pharmacological options have been minimally effective in treating cognitive impairment to date, interest in the development of preventative lifestyle intervention strategies has increased in the field. One controversial strategy, cognitive-specific stimulation, has been studied previously in human participants and has been widely commercialized in the form of 'brain-training games.' In the present study, we developed a highly controlled, isolated cognitive training intervention program for mice. Two transgenic mouse lines, one that develops Aβ deposition largely in brain parenchyma, and another in the cerebral microvasculature, progressed through a series of domain-specific tasks for an average of 4 months. Despite the high intensity and duration of the intervention, we found little evidence of positive benefits for AD amyloid pathologies and post-training cognitive testing in these two models. Taken together, these results support the current evidence in human studies that cognitive-specific stimulation does not lead to a measurable reduction in AD pathology or an improvement in general brain health.

An Intracellular Amyloid-β/AβPP Epitope Correlates with Neurodegeneration in those Neuronal Populations Early Involved in Alzheimer's Disease. - Esquerda-Canals, Gisela; Martí-Clúa, Joaquim; Roda, Alejandro R; Villegas, Sandra (J Alzheimers Dis, 2017)
The main histopathological hallmarks of Alzheimer's disease (AD) are the extracellular deposition of neuritic amyloid plaques, composed of amyloid-β (Aβ) peptide, and the intracellular accumulation of neurofibrillary tangles, composed of hyperphosphorylated tau. Both traits are emulated in the 3xTg-AD mouse model. Because the relevance of this model in the bibliography and the main role of Aβ in neuronal impairment, here we have detailed the brain Aβ/AβPP distribution to subsequently quantify cellular density and intracellular burden for specific neuronal populations in the early stages of the disease. 6E10 immunoreactivity was evident in the deep layers of the cerebral cortex, in the pyramidal cell layer of the hippocampus, in the basolateral amygdala nucleus, and in the deep cerebellar nuclei macroneurons; whereas the specific neuronal populations with decreased cellular density were the large pyramidal neurons from the layers V-VI in the cerebral cortex, the pyramidal neurons from the CA2-3 region in the hippocampus, and the large neurons from the basolateral nucleus in the amygdala, apart from the already reported deep cerebellar nuclei. Interestingly, we found a strong correlation between intracellular Aβ/AβPP burden and cellular density in all these populations. In addition, behavioral testing showed the functional consequences of such a neuronal depletion. Concretely, anxious-like behavior is manifested in the corner and open-field tests, as well as cognitive functions shown to be impaired in the novel object recognition test and Morris water maze paradigm. To our knowledge, this is the first deep characterization of the specific neuronal populations affected in the 3xTg-AD mouse model.

Intracerebroventricular Streptozotocin Induces Obesity and Dementia in Lewis Rats. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Koroukhov, Nickolay; Taler, Michal; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2017)
BACKGROUND: Animal models of dementia associated with metabolic abnormalities play an important role in understanding the bidirectional relationships between these pathologies. Rodent strains develop cognitive dysfunctions without alteration of peripheral metabolism following intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to estimate the effect of icv-STZ on cognitive functions and peripheral metabolism in Lewis rats, which are rarely used for the induction of cognitive abnormalities. METHODS: Inbred adult Lewis rats were treated with single icv-STZ (3 mg/kg). Cognitive functions were assessed using Morris water maze (MWM) test and locomotion by the Open Field test. Metabolic alterations were studied using histological and biochemical analysis of brain and peripheral tissues. RESULTS: The icv-STZ induced rapid weight decline during the first two weeks. Thereafter, the rats showed an accelerated weight gain. Three months after the icv-STZ treatment, the rats were severely obese and revealed fatty liver, pancreatic islet hypertrophy, significantly elevated levels of blood insulin, leptin, and adiponectin, but intact peripheral glucose homeostasis. The icv-STZ rats expressed amyloid-β deposits in blood vessels of leptomeningeal area, microgliosis, astrogliosis, and spongiosis in fimbria-fornix area of hippocampus. Locomotor activities of icv-STZ treated and sham-operated rats were similar. In the MWM test, the icv-STZ treated rats demonstrated severely impaired spatial learning during both acquisition and reversal phases. CONCLUSIONS: Icv-STZ treated Lewis rats develop severe dementia associated with obesity and peripheral metabolic abnormalities. This animal model may be useful for exploring the pathophysiological relationship between obesity and dementia and provides a new tool for development of effective therapy.

Intrahippocampal Pathways Involved in Learning/Memory Mechanisms are Affected by Intracerebral Infusions of Amyloid-β25-35 Peptide and Hydrated Fullerene C60 in Rats. - Gordon, Rita; Podolski, Igor; Makarova, Ekaterina; Deev, Alexander; Mugantseva, Ekaterina; Khutsyan, Sergey; Sengpiel, Frank; Murashev, Arkady; Vorobyov, Vasily (J Alzheimers Dis, 2017)
Primary memory impairments associated with increased level of amyloid-β (Aβ) in the brain have been shown to be linked, partially, with early pathological changes in the entorhinal cortex (EC) which spread on the whole limbic system. While the hippocampus is known to play a key role in learning and memory mechanisms, it is as yet unclear how its structures are involved in the EC pathology. In this study, changes in memory and neuronal morphology in male Wistar rats intrahippocampally injected with Aβ25-35 were correlated on days 14 and 45 after the injection to reveal specific cognitive-structural associations. The main focus was on the dentate gyrus (DG) and hippocampal areas of CA1 and CA3 because of their involvement in afferent flows from EC to the hippocampus through tri-synaptic (EC → DG → CA3 → CA1) and/or mono-synaptic (EC → CA1) pathways. Evident memory impairments were observed at both time points after Aβ25-35 injection. However, on day 14, populations of morphological intact neurons were decreased in CA3 and, drastically, in CA1, and the DG supramedial bundle was significantly damaged. On day 45, this bundle largely and CA1 neurons partially recovered, whereas CA3 neurons remained damaged. We suggest that Aβ25-35 primarily affects the tri-synaptic pathway, destroying the granular cells in the DG supramedial area and neurons in CA3 and, through the Schaffer collaterals, in CA1. Intrahippocampal pretreatment with hydrated fullerene C60 allows the neurons and their connections to survive the amyloidosis, thus supporting the memory mechanisms.

Investigating Simulated Driving Errors in Amnestic Single- and Multiple-Domain Mild Cognitive Impairment. - Hird, Megan A; Vesely, Kristin A; Fischer, Corinne E; Graham, Simon J; Naglie, Gary; Schweizer, Tom A (J Alzheimers Dis, 2017)
The areas of driving impairment characteristic of mild cognitive impairment (MCI) remain unclear. This study compared the simulated driving performance of 24 individuals with MCI, including amnestic single-domain (sd-MCI, n = 11) and amnestic multiple-domain MCI (md-MCI, n = 13), and 20 age-matched controls. Individuals with MCI committed over twice as many driving errors (20.0 versus 9.9), demonstrated difficulty with lane maintenance, and committed more errors during left turns with traffic compared to healthy controls. Specifically, individuals with md-MCI demonstrated greater driving difficulty compared to healthy controls, relative to those with sd-MCI. Differentiating between different subtypes of MCI may be important when evaluating driving safety.

Iron Concentration in Deep Gray Matter Structures is Associated with Worse Visual Memory Performance in Healthy Young Adults. - Darnai, Gergely; Nagy, Szilvia Anett; Horváth, Réka; Ács, Péter; Perlaki, Gábor; Orsi, Gergely; Kovács, Norbert; Altbäcker, Anna; Plózer, Enikő; Tényi, Dalma; Weintraut, Rita; Schwarcz, Attila; et al. (J Alzheimers Dis, 2017)
Abnormally high deposition of iron can contribute to neurodegenerative disorders with cognitive impairment. Since previous studies investigating cognition-brain iron accumulation relationships focused on elderly people, our aim was to explore the association between iron concentration in subcortical nuclei and two types of memory performances in a healthy young population. Gender difference was found only in the globus pallidus. Our results showed that iron load characterized by R2* value on the MRI in the caudate and putamen was related to visual memory, while verbal memory was unrelated to iron concentration.

Left Ventricular Hypertrophy and Cognitive Decline in Old Age. - Mahinrad, Simin; Vriend, Annelotte E; Jukema, J Wouter; van Heemst, Diana; Sattar, Naveed; Blauw, Gerard Jan; Macfarlane, Peter W; Clark, Elaine N; de Craen, Anton J M; Sabayan, Behnam (J Alzheimers Dis, 2017)
BACKGROUND: Patients with advanced heart failure run a greater risk of dementia. Whether early cardiac structural changes also associate with cognitive decline is yet to be determined. OBJECTIVE: We tested whether left ventricular hypertrophy (LVH) derived from electrocardiogram associates with cognitive decline in older subjects at risk of cardiovascular disease. METHODS: We included 4,233 participants (mean age 75.2 years, 47.8% male) from PROSPER (PROspective Study of Pravastatin in the Elderly at Risk). LVH was assessed from baseline electrocardiograms by measuring the Sokolow-Lyon index. Higher levels of Sokolow-Lyon index indicate higher degrees of LVH. Cognitive domains involving selective attention, processing speed, and immediate and delayed memory were measured at baseline and repeated during a mean follow-up of 3.2 years. RESULTS: At baseline, LVH was not associated with worse cognitive function. During follow-up, participants with higher levels of LVH had a steeper decline in cognitive function including in selective attention (p = 0.009), processing speed (p = 0.010), immediate memory (p < 0.001), and delayed memory (p = 0.002). These associations were independent of cardiovascular risk factors, co-morbidities, and medications. CONCLUSION: LVH assessed by electrocardiogram associates with steeper decline in cognitive function of older subjects independent of cardiovascular risk factors and co-morbidities. This study provides further evidence on the link between subclinical cardiac structural changes and cognitive decline in older subjects.

The Link between Type 2 Diabetes and Neurodegeneration: Roles for Amyloid-β, Amylin, and Tau Proteins. - Bharadwaj, Prashant; Wijesekara, Nadeeja; Liyanapathirana, Milindu; Newsholme, Philip; Ittner, Lars; Fraser, Paul; Verdile, Giuseppe (J Alzheimers Dis, 2017)
A wealth of evidence indicates a strong link between type 2 diabetes (T2D) and neurodegenerative diseases such as Alzheimer's disease (AD). Although the precise mechanism remains unclear, T2D can exacerbate neurodegenerative processes. Brain atrophy, reduced cerebral glucose metabolism, and central nervous system insulin resistance are features of both AD and T2D. The T2D phenotype (glucose dyshomeostasis, insulin resistance, impaired insulin signaling) also promotes AD pathology, namely accumulation of amyloid-β (Aβ) and hyperphosphorylated tau and can induce other aspects of neuronal degeneration including inflammatory and oxidative processes. Aβ and hyperphosphorylated tau may also have roles in pancreatic β-cell dysfunction and in reducing insulin sensitivity and glucose uptake by peripheral tissues such as liver, skeletal muscle, and adipose tissue. This suggests a role for these AD-related proteins in promoting T2D. The accumulation of the islet amyloid polypeptide (IAPP, or amylin) within islet β-cells is a major pathological feature of the pancreas in patients with chronic T2D. Co-secreted with insulin, amylin accumulates over time and contributes to β-cell toxicity, ultimately leading to reduced insulin secretion and onset of overt (insulin dependent) diabetes. Recent evidence also suggests that this protein accumulates in the brain of AD patients and may interact with Aβ to exacerbate the neurodegenerative process. In this review, we highlight evidence indicating T2D in promoting Aβ and tau mediated neurodegeneration and the potential contributions of Aβ and tau in promoting a diabetic phenotype that could further exacerbate neurodegeneration. We also discuss underlying mechanisms by which amylin can contribute to the neurodegenerative processes.

A Lipidomics Approach to Assess the Association Between Plasma Sphingolipids and Verbal Memory Performance in Coronary Artery Disease Patients Undertaking Cardiac Rehabilitation: A C18:0 Signature for Cognitive Response to Exercise. - Saleem, Mahwesh; Herrmann, Nathan; Dinoff, Adam; Mielke, Michelle M; Oh, Paul I; Shammi, Prathiba; Cao, Xingshan; Venkata, Swarajya Lakshmi Vattem; Haughey, Norman J; Lanctôt, Krista L (J Alzheimers Dis, 2017)
BACKGROUND: Early subtle deficits in verbal memory, which may indicate early neural risk, are common in patients with coronary artery disease (CAD). While exercise can improve cognition, cognitive response to exercise is heterogeneous. Sphingolipids have been associated with the development and progression of CAD, and impairments in sphingolipid metabolism may play roles in neurodegeneration and in the neural adaptation response to exercise. OBJECTIVE: In this study, change in plasma concentrations of sphingolipids was assessed in relation to change in verbal memory performance and in other cognitive domains among CAD subjects undertaking a 6-month cardiac rehabilitation (CR) program. METHODS: Patients with CAD (n = 120, mean age = 64±6 y, 84% male, years of education = 16±3) underwent CR with neuropsychological assessments and blood collected at baseline, 3-, and 6-months. Z-scores based on age, gender, and education were combined for verbal memory, visuospatial memory, processing speed, executive function, and global cognition tasks to calculate cognitive domain Z-scores. Plasma sphingolipid concentrations were measured from fasting blood samples using high performance liquid chromatography coupled electrospray ionization tandem mass spectrometry (LC/MS/MS). Mixed models were used to identify sphingolipids significantly associated with performance in verbal memory and other cognitive domains, adjusting for potential confounders. RESULTS: A decrease in ceramide C18:0 concentration was significantly associated with improvement in verbal memory performance (b[SE] = -0.51 [0.25], p = 0.04), visuospatial memory (b[SE] = -0.44 [0.22], p = 0.05), processing speed (b[SE] = -0.89 [0.32], p = 0.007), and global cognition (b[SE] = -1.47 [0.59], p = 0.01) over 6 months of CR. CONCLUSIONS: Plasma ceramide C18:0 concentrations may be a sensitive marker of cognitive response to exercise in patients with CAD.

Longitudinal Characterization of [18F]-FDG and [18F]-AV45 Uptake in the Double Transgenic TASTPM Mouse Model. - Waldron, Ann-Marie; Wyffels, Leonie; Verhaeghe, Jeroen; Richardson, Jill C; Schmidt, Mark; Stroobants, Sigrid; Langlois, Xavier; Staelens, Steven (J Alzheimers Dis, 2017)
We aimed to monitor the timing of amyloid-β deposition in relation to changes in brain function using in vivo imaging with [18F]-AV45 and [18F]-FDG in a mouse model of Alzheimer's disease. TASTPM transgenic mice and wild-type controls were scanned longitudinally with [18F]-AV45 and [18F]-FDG before (3 months of age) and at multiple time points after the onset of amyloid deposition (6, 9, 12, and 15 months of age). As expected with increasing amyloidosis, TASTPM mice demonstrated progressive age-dependent increases in [18F]-AV45 uptake that were significantly higher than for WT from 9 months onwards and correlated to ex vivo measures of amyloid burden. The metabolism of [18F]-AV45 produces several brain penetrant radiometabolites and normalization to a reference region helps to negate this non-specific binding and improve the sensitivity of [18F]-AV45. The observed trajectory of [18F]-FDG alterations deviated from our proposed hypothesis of gradual decreases with worsening amyloidosis. While [18F]-FDG uptake in TASTPM mice was significantly lower than that of WT at 9 months, reduced [18F]-FDG was not associated with aging in TASTPM mice. Moreover, [18F]-FDG uptake did not correlate to measures of ex vivo amyloid burden. Our findings suggest that while amyloid-β is sufficient to induce hypometabolism, these pathologies are not linked in a dose-dependent manner in TASTPM mice.

A Longitudinal Study on Resting State Functional Connectivity in Behavioral Variant Frontotemporal Dementia and Alzheimer's Disease. - Hafkemeijer, Anne; Möller, Christiane; Dopper, Elise G P; Jiskoot, Lize C; van den Berg-Huysmans, Annette A; van Swieten, John C; van der Flier, Wiesje M; Vrenken, Hugo; Pijnenburg, Yolande A L; Barkhof, Frederik; Scheltens, Philip; van der Grond, Jeroen; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are the most common types of early-onset dementia. We applied longitudinal resting state functional magnetic resonance imaging (fMRI) to delineate functional brain connections relevant for disease progression and diagnostic accuracy. METHODS: We used two-center resting state fMRI data of 20 AD patients (65.1±8.0 years), 12 bvFTD patients (64.7±5.4 years), and 22 control subjects (63.8±5.0 years) at baseline and 1.8-year follow-up. We used whole-network and voxel-based network-to-region analyses to study group differences in functional connectivity at baseline and follow-up, and longitudinal changes in connectivity within and between groups. RESULTS: At baseline, connectivity between paracingulate gyrus and executive control network, between cuneal cortex and medial visual network, and between paracingulate gyrus and salience network was higher in AD compared with controls. These differences were also present after 1.8 years. At follow-up, connectivity between angular gyrus and right frontoparietal network, and between paracingulate gyrus and default mode network was lower in bvFTD compared with controls, and lower compared with AD between anterior cingulate gyrus and executive control network, and between lateral occipital cortex and medial visual network. Over time, connectivity decreased in AD between precuneus and right frontoparietal network and in bvFTD between inferior frontal gyrus and left frontoparietal network. Longitudinal changes in connectivity between supramarginal gyrus and right frontoparietal network differ between both patient groups and controls. CONCLUSION: We found disease-specific brain regions with longitudinal connectivity changes. This suggests the potential of longitudinal resting state fMRI to delineate regions relevant for disease progression and for diagnostic accuracy, although no group differences in longitudinal changes in the direct comparison of AD and bvFTD were found.

Low Erythrocyte Levels of Proteasome and Acyl-Peptide Hydrolase (APEH) Activities in Alzheimer's Disease: A Sign of Defective Proteostasis? - Palmieri, Gianna; Cocca, Ennio; Gogliettino, Marta; Valentino, Roberta; Ruvo, Menotti; Cristofano, Gloria; Angiolillo, Antonella; Balestrieri, Marco; Rossi, Mosè; Di Costanzo, Alfonso (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive, multifactorial neurodegenerative disorder that is the main cause of dementia. To date, there are no definitive diagnostic tests that can predict or assess onset and progression of the disease. Blood biomarkers for AD are being sought for many years but their identification remains a challenging task. In this study, we investigated the potential relationship between AD and levels of acyl-peptide hydrolase (APEH) and proteasome in erythrocyte samples of 52 participants (26 AD and 26 cognitively healthy controls). A statistically significant decrease in proteasome and exopeptidase/endopeptidase APEH activities was found in AD samples compared to those of healthy controls. Moreover, in contrast to what was observed for proteasome transcripts, APEH activities reduction in AD patients was unrelated to its gene expression levels, suggesting the occurrence of posttranslational modifications or the expression of endogenous inhibitors that might impair enzyme activity. These preliminary data further support a relationship between the APEH-proteasome system and AD molecular players, providing the first evidence of its potential use as a novel blood-based indicator for the routine detection of AD.

Memory Complaints and Cognitive Decline: Data from the GUIDAGE Study1. - Dardenne, Sophie; Delrieu, Julien; Sourdet, Sandrine; Cantet, Christelle; Andrieu, Sandrine; Mathiex-Fortunet, Hélène; Fougère, Bertrand; Vellas, Bruno (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive decline (SCD) may be a very early symptom of Alzheimer's disease (AD) and may be associated with a cognitive decline in a cognitively normal population. The McNair and Kahn Scale was used to assess memory complaints in the GuidAge study. OBJECTIVE: Our objectives were to examine if the McNair and Kahn Scale can predict cognitive decline and to screen which (if any) of the question(s) of this scale would better predict this cognitive decline. METHODS: The GuidAge study was a phase III, multicenter, randomized, double blind, placebo-controlled study. Individuals aged 70 years and older, without cognitive impairment (Clinical Dementia Rate (CDR = 0)) at baseline who had spontaneously reported SCD were included in this study. The 20-item version of the McNair and Kahn Scale was used to assess SCD and a standardized neuropsychological assessment was used to assess the cognitive status. RESULTS: 1,307 patients with SCD and with CDR = 0 at baseline were included. During the 5 years of follow-up, 519 patients showed cognitive decline. Incidence of aggravation score of CDR was 13.40% person years (95% CI [12.24-14.56]). Results showed a significant relationship between the McNair and Kahn Scale score and decline in cognitive performance (HR 1.012; 95% CI [1.002-1.021]; p = 0.0156). Among the 20 items, 5 were statistically significant to predict cognitive decline after adjustment. CONCLUSION: SCD is a promising indicator of memory impairment. Our study found that using the McNair and Kahn scale can predict cognitive decline. A 5-item version of this scale could be used to screen patients in clinical practice and in clinical research.

Memory Correlates of Alzheimer's Disease Cerebrospinal Fluid Markers: A Longitudinal Cohort Study. - Reijs, Babette L R; Ramakers, Inez H G B; Köhler, Sebastian; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Nathan, Pradeep J; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Vandenberghe, Rik; Johannsen, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Performance on episodic, semantic, and working memory tests is impaired in Alzheimer's disease (AD)-type dementia, but it is unclear which type of memory test is most strongly associated with early AD biomarkers in cerebrospinal fluid (CSF), and most useful for monitoring disease progression. OBJECTIVE: To examine the association between amyloid-β 1-42 (Aβ42) and tau in CSF with performance on different memory domains at baseline, and how these CSF markers are related with memory decline. METHODS: We included 263 individuals with normal cognition, mild cognitive impairment, AD-type dementia, and non-AD dementia from the European EDAR study. Assessment included CSF Aβ42 and t-tau analyses with INNO-BIA AlzBio3 Luminex assay, the CERAD wordlist learning and delayed recall, animal fluency test, and the CANTAB Paired Associates Learning (PAL) and Spatial Working Memory tasks. Follow-up assessments were performed within 3 years after baseline. RESULTS: At baseline, decreased CSF Aβ42 correlated most strongly with the PAL total errors adjusted and the wordlist delayed recall and increased CSF t-tau with the wordlist delayed recall. Over time, decreased CSF Aβ42 was associated with decline on the wordlist learning, whereas increased CSF t-tau were associated with decline in scores on the wordlist learning, wordlist delayed recall, and animal fluency. Associations were independent of baseline diagnosis. CONCLUSION: Tests assessing episodic verbal and visuospatial memory are most useful for detection of AD pathology. Tests for episodic verbal memory and semantic memory are most useful for tracking memory decline.

A Metal-Free Method for Producing MRI Contrast at Amyloid-β. - Hilt, Silvia; Tang, Tang; Walton, Jeffrey H; Budamagunta, Madhu; Maezawa, Izumi; Kálai, Tamás; Hideg, Kálmán; Singh, Vikrant; Wulff, Heike; Gong, Qizhi; Jin, Lee-Way; Louie, Angelique; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by depositions of the amyloid-β (Aβ) peptide in the brain. The disease process develops over decades, with substantial neurological loss occurring before a clinical diagnosis of dementia can be rendered. It is therefore imperative to develop methods that permit early detection and monitoring of disease progression. In addition, the multifactorial pathogenesis of AD has identified several potential avenues for AD intervention. Thus, evaluation of therapeutic candidates over lengthy trial periods also demands a practical, noninvasive method for measuring Aβ in the brain. Magnetic resonance imaging (MRI) is the obvious choice for such measurements, but contrast enhancement for Aβ has only been achieved using Gd(III)-based agents. There is great interest in gadolinium-free methods to image the brain. In this study, we provide the first demonstration that a nitroxide-based small-molecule produces MRI contrast in brain specimens with elevated levels of Aβ. The molecule is comprised of a  fluorene (a molecule with high affinity for Aβ) and a nitroxide spin label (a paramagnetic MRI contrast species). Labeling of brain specimens with the spin-labeled fluorene produces negative contrast in samples from AD model mice whereas no negative contrast is seen in specimens harvested from wild-type mice. Injection of spin-labeled fluorene into live mice resulted in good brain penetration, with the compound able to generate contrast 24-h post injection. These results provide a proof of concept method that can be used for early, noninvasive, gadolinium-free detection of amyloid plaques by MRI.

Methylene Blue (Tetramethylthionine Chloride) Influences the Mobility of Adult Neural Stem Cells: A Potentially Novel Therapeutic Mechanism of a Therapeutic Approach in the Treatment of Alzheimer's Disease. - van der Ven, Amelie T; Pape, Julius C; Hermann, Dirk; Schloesser, Robert; Genius, Just; Fischer, Nadine; Mößner, Rainald; Scherbaum, Norbert; Wiltfang, Jens; Rujescu, Dan; Benninghoff, Jens (J Alzheimers Dis, 2017)
An interest in neurogenesis in the adult human brain as a relevant and targetable process has emerged as a potential treatment option for Alzheimer's disease and other neurodegenerative conditions. The aim of this study was to investigate the effects of tetramethylthionine chloride (methylene blue, MB) on properties of adult murine neural stem cells. Based on recent clinical studies, MB has increasingly been discussed as a potential treatment for Alzheimer's disease. While no differences in the proliferative capacity were identified, a general potential of MB in modulating the migratory capacity of adult neural stem cells was indicated in a cell mobility assay. To our knowledge, this is the first time that MB could be associated with neural mobility. The results of this study add insight to the spectrum of features of MB within the central nervous system and may be helpful for understanding the molecular mechanisms underlying a potential therapeutic effect of MB.

MicroRNA Profile in Patients with Alzheimer's Disease: Analysis of miR-9-5p and miR-598 in Raw and Exosome Enriched Cerebrospinal Fluid Samples. - Riancho, Javier; Vázquez-Higuera, José Luis; Pozueta, Ana; Lage, Carmen; Kazimierczak, Martha; Bravo, María; Calero, Miguel; Gonalezález, Andrea; Rodríguez, Eloy; Lleo, Alberto; Sánchez-Juan, Pascual (J Alzheimers Dis, 2017)
BACKGROUND: MicroRNAs have been postulated as potential biomarkers for Alzheimer's disease (AD). Exosomes are nanovesicles which transport microRNAs, proteins, and other cargos. It has been hypothesized that the exosome traffic might be increased in neurodegenerative disorders. OBJECTIVE: i) To assess the cerebrospinal fluid (CSF) microRNA profile in a group of AD patients and control subjects and to validate a group of microRNAs previously reported by other authors. ii) To compare microRNA levels in whole CSF and in the exosome-enriched fraction in AD patients. METHODS: A panel of 760 microRNAs was analyzed in the CSF of 10 AD patients and 10 healthy subjects. Among microRNAs differently expressed, we selected those that had been previously reported by other authors. Candidates were validated in a larger group by individual qPCR assays. MicroRNA expression was also evaluated in exosome-enriched CSF samples of patients with AD and controls. RESULTS: Fifteen microRNAs were differently expressed in AD. MiR-9-5p, miR-134, and miR-598 were selected as candidates for further analysis. MiR-9-5p and miR-598 were detected in 50 and 75% of control CSF samples, respectively, while they were not detected in any AD CSF samples. We observed an opposite pattern when we evaluated the microRNA expression in the exosome-enriched CSF AD samples. No pattern variations were noted among healthy subjects. CONCLUSION: These data propose miR-9-5p and miR-598 as potential biomarkers for AD. Further studies in plasma and other body fluids will confirm their potential role as easily accessible biomarkers. In addition, our data suggest that exosome trafficking is different between AD and control subjects raising the need to take this phenomenon into consideration in future studies of AD biomarkers.

Modifiable Risk Factors for Prevention of Dementia in Midlife, Late Life and the Oldest-Old: Validation of the LIBRA Index. - Vos, Stephanie J B; van Boxtel, Martin P J; Schiepers, Olga J G; Deckers, Kay; de Vugt, Marjolein; Carrière, Isabelle; Dartigues, Jean-François; Pérès, Karine; Artero, Sylvaine; Ritchie, Karen; Galluzzo, Lucia; Scafato, Emanuele; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recently, the LIfestyle for BRAin health (LIBRA) index was developed to assess an individual's prevention potential for dementia. OBJECTIVE: We investigated the predictive validity of the LIBRA index for incident dementia in midlife, late life, and the oldest-old. METHODS: 9,387 non-demented individuals were recruited from the European population-based DESCRIPA study. An individual's LIBRA index was calculated solely based on modifiable risk factors: depression, diabetes, physical activity, hypertension, obesity, smoking, hypercholesterolemia, coronary heart disease, and mild/moderate alcohol use. Cox regression was used to test the predictive validity of LIBRA for dementia at follow-up (mean 7.2 y, range 1-16). RESULTS: In midlife (55-69 y, n = 3,256) and late life (70-79 y, n = 4,320), the risk for dementia increased with higher LIBRA scores. Individuals in the intermediate- and high-risk groups had a higher risk of dementia than those in the low-risk group. In the oldest-old (80-97 y, n = 1,811), higher LIBRA scores did not increase the risk for dementia. CONCLUSION: LIBRA might be a useful tool to identify individuals for primary prevention interventions of dementia in midlife, and maybe in late life, but not in the oldest-old.

Motoric Cognitive Risk Syndrome: Association with Incident Dementia and Disability. - Doi, Takehiko; Shimada, Hiroyuki; Makizako, Hyuma; Tsutsumimoto, Kota; Verghese, Joe; Suzuki, Takao (J Alzheimers Dis, 2017)
BACKGROUND: It is important to examine the etiology of motoric cognitive risk syndrome (MCR) and its association with dementia and disability to obtain biological insights and to develop preventive strategies. OBJECTIVE: This study aimed to examine the association of MCR with incidence of dementia and disability in a Japanese community-dwelling sample of older adults. METHODS: Participants were 4,235 older adults (50% women, mean age: 72.0 years). MCR was diagnosed at baseline using established criteria in non-demented seniors with self-reported cognitive complaints and slow gait. Incident cases of dementia were identified from insurance data monthly. Disability was regarded as certification by long-term care insurance. RESULTS: At baseline, 265 participants (6.3%) met criteria for MCR. During follow-up (mean duration: 29 months), there were 138 incident cases of dementia (3.3%) and 207 incident cases of disability (4.9%). Cox-proportional hazards models, adjusted for demographical data, lifestyle, and medical conditions, showed that presence of MCR at baseline was a major risk factor for developing dementia (HR 2.49, 95% CI 1.52-4.10, p < 0.001). MCR also predicted risk for disability (HR 1.69, 95% CI 1.08-2.02, p < 0.001). CONCLUSIONS: MCR is helpful in the short-term prediction of risk for dementia and disability in the elderly Japanese population. Identification of seniors with MCR is recommended for early detection and instituting preventive measures for reducing the risk of dementia and disability.

Mouse Models of Alzheimer's Disease. - Esquerda-Canals, Gisela; Montoliu-Gaya, Laia; Güell-Bosch, Jofre; Villegas, Sandra (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a neurodegenerative disorder that nowadays affects more than 40 million people worldwide and it is predicted to exponentially increase in the coming decades. Because no curative treatment exists, research on the pathophysiology of the disease, as well as the testing of new drugs, are mandatory. For these purposes, animal models constitute a valuable, although perfectible tool. This review takes a tour through several aspects of mouse models of AD, such as the generation of transgenic models, the relevance of the promoter driving the expression of the transgenes, and the concrete transgenes used to simulate AD pathophysiology. Then, transgenic mouse lines harboring mutated human genes at several loci such as APP, PSEN1, APOEɛ4, and ob (leptin) are reviewed. Therefore, not only the accumulation of the Aβ peptide is emulated but also cholesterol and insulin metabolism. Further novel information about the disease will allow for the development of more accurate animal models, which in turn will undoubtedly be helpful for bringing preclinical research closer to clinical trials in humans.

A Multi-Cohort Study of ApoE ɛ4 and Amyloid-β Effects on the Hippocampus in Alzheimer's Disease. - Khan, Wasim; Giampietro, Vincent; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun L W; Büchel, Christian; Conrod, Patricia; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Anreas; et al. (J Alzheimers Dis, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer's disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of APOE and amyloid-β (Aβ) on baseline hippocampal volumes in AD patients, mild cognitive impairment (MCI) subjects, and healthy controls. A large sample of healthy adolescents (n = 1,387) was also used to compared hippocampal volumes between APOE groups. Subjects had undergone a magnetic resonance imaging (MRI) scan and APOE genotyping. Hippocampal volumes were processed using FreeSurfer. In the AD and normal aging dataset, hippocampal comparisons were performed in each APOE group and in ɛ4 carriers with positron emission tomography Aβ who were dichotomized (Aβ+/Aβ-) using previous cut-offs. We found a linear reduction in hippocampal volumes with ɛ4 carriers possessing the smallest volumes, ɛ3 carriers possessing intermediate volumes, and ɛ2 carriers possessing the largest volumes. Moreover, AD and MCI ɛ4 carriers possessed the smallest hippocampal volumes and control ɛ2 carriers possessed the largest hippocampal volumes. Subjects with both APOE ɛ4 and Aβ+ had the lowest hippocampal volumes when compared to Aβ- ɛ4 carriers, suggesting a synergistic relationship between APOE ɛ4 and Aβ. However, we found no hippocampal volume differences between APOE groups in healthy 14-year-old adolescents. Our findings suggest that the strongest neuroanatomic effect of APOE ɛ4 on the hippocampus is observed in AD and groups most at risk of developing the disease, whereas hippocampi of old and young healthy individuals remain unaffected.

A Multifunctional Biocompatible Drug Candidate is Highly Effective in Delaying Pathological Signs of Alzheimer's Disease in 5XFAD Mice. - Segal-Gavish, Hadar; Danino, Ortal; Barhum, Yael; Ben-Zur, Tali; Shai, Ella; Varon, David; Offen, Daniel; Fischer, Bilha (J Alzheimers Dis, 2017)
BACKGROUND: Metal-ion-chelation was suggested to prevent zinc and copper ions-induced amyloid-β (Aβ) aggregation and oxidative stress, both implicated in the pathophysiology of Alzheimer's disease (AD). In a quest for biocompatible metal-ion chelators potentially useful for AD therapy, we previously tested a series of nucleoside 5'-phosphorothioate derivatives as agents for decomposition of Cu(I)/Cu(II)/Zn(II)-Aβ-aggregates, and as inhibitors of OH radicals formation in Cu(I) or Fe(II) /H2O2 solution. Specifically, in our recent study we have identified 2-SMe-ADP(α-S), designated as SAS, as a most promising neuroprotectant. OBJECTIVE: To further explore SAS ability to protect the brain from Aβ toxicity both in vitro and in vivo. METHODS: We evaluated SAS ability to decompose or inhibit the formation of Aβ42-M(II) aggregates, and rescue primary neurons and astrocytes from Aβ42 toxicity. Furthermore, we aimed at exploring the therapeutic effect of SAS on behavioral and cognitive deficits in the 5XFAD mouse model of AD. RESULTS: We found that SAS can rescue primary culture of neurons and astrocytes from Aβ42 toxicity and to inhibit the formation and dissolve Aβ42-Zn(II)/Cu(II) aggregates. Furthermore, we show that SAS treatment can prevent behavioral disinhibition and ameliorate spatial working memory deficits in 5XFAD mice. Notably, the mice were treated at the age of 2 months, before the onset of AD symptoms, for a duration of 2 months, while the effect was demonstrated at the age of 6 months. CONCLUSION: Our results indicate that SAS has the potential to delay progression of core pathological characteristics of AD in the 5XFAD mouse model.

Multiple Mechanisms Linking Type 2 Diabetes and Alzheimer's Disease: Testosterone as a Modifier. - Asih, Prita R; Tegg, Michelle L; Sohrabi, Hamid; Carruthers, Malcolm; Gandy, Samuel E; Saad, Farid; Verdile, Giuseppe; Ittner, Lars M; Martins, Ralph N (J Alzheimers Dis, 2017)
Evidence in support of links between type-2 diabetes mellitus (T2DM) and Alzheimer's disease (AD) has increased considerably in recent years. AD pathological hallmarks include the accumulation of extracellular amyloid-β (Aβ) and intracellular hyperphosphorylated tau in the brain, which are hypothesized to promote inflammation, oxidative stress, and neuronal loss. T2DM exhibits many AD pathological features, including reduced brain insulin uptake, lipid dysregulation, inflammation, oxidative stress, and depression; T2DM has also been shown to increase AD risk, and with increasing age, the prevalence of both conditions increases. In addition, amylin deposition in the pancreas is more common in AD than in normal aging, and although there is no significant increase in cerebral Aβ deposition in T2DM, the extent of Aβ accumulation in AD correlates with T2DM duration. Given these similarities and correlations, there may be common underlying mechanism(s) that predispose to both T2DM and AD. In other studies, an age-related gradual loss of testosterone and an increase in testosterone resistance has been shown in men; low testosterone levels can also occur in women. In this review, we focus on the evidence for low testosterone levels contributing to an increased risk of T2DM and AD, and the potential of testosterone treatment in reducing this risk in both men and women. However, such testosterone treatment may need to be long-term, and would need regular monitoring to maintain testosterone at physiological levels. It is possible that a combination of testosterone therapy together with a healthy lifestyle approach, including improved diet and exercise, may significantly reduce AD risk.

Neural Correlates of Self-Reference Effect in Early Alzheimer's Disease. - Gaubert, Malo; Villain, Nicolas; Landeau, Brigitte; Mézenge, Florence; Egret, Stéphanie; Perrotin, Audrey; Belliard, Serge; de la Sayette, Vincent; Eustache, Francis; Desgranges, Béatrice; Chételat, Gaël; Rauchs, Géraldine (J Alzheimers Dis, 2017)
Information that is processed with reference to the self (i.e., self-referential processing, SRP) is generally associated with better remembering than information processed in a semantic condition. This benefit of self on memory performance is called self-reference effect (SRE). In the present study, we assessed changes in the SRE and SRP-related brain activity in patients diagnosed with mild cognitive impairment or early Alzheimer's disease (MCI/AD). Fifteen patients with confirmed amyloid-β deposits (positive florbetapir-PET scan) and 28 healthy controls (negative florbetapir-PET scan) were included. Participants either had to judge personality trait adjectives with reference to themselves (self condition) or to a celebrity (other condition), or determine whether these adjectives were positive or not (semantic condition). These adjectives were then presented with distractors in a surprise recognition task. Functional MRI data were acquired during both the judgment and recognition tasks. The SRE was observed in controls, but reduced in patients. Both controls and patients activated cortical midline structures when judging items with reference to themselves, but patients exhibited reduced activity in the angular gyrus. In patients, activity at encoding in the angular gyrus positively correlated with subsequent recognition accuracy in the self condition (self accuracy). This region also exhibited significant hypometabolism and Aβ burden, both related to self accuracy. By contrast, there were no differences in brain activity during recognition, either between the self and semantic conditions, or between groups. These results highlight SRE impairment in patients with MCI/AD, despite intact activity in cortical midline structures, and suggest that dysfunction of the angular gyrus is related to this impairment.

Neurodegenerative Markers are Increased in Postmortem BA21 Tissue from African Americans with Alzheimer's Disease. - Ferguson, Sherry A; Panos, John J; Sloper, Daniel; Varma, Vijayalakshmi (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) presents with an earlier onset age and increased symptom severity in African Americans and Hispanics. OBJECTIVE: Although the prevalence of plaques and tangles may not exhibit ethnicity-related differences, levels of neurodegenerative proteins have not been described. METHODS: Here, levels of five proteins (i.e., S100B, sRAGE, GDNF, Aβ40, and Aβ42) and the Aβ42/Aβ40 ratio were measured in postmortem samples of the middle temporal gyrus (BA21) from age-matched African Americans and Caucasians with AD (n = 6/gender/ethnicity). RESULTS: S100B levels were increased 17% in African Americans (p < 0.003) while sRAGE was mildly decreased (p < 0.09). Aβ42 levels were increased 121% in African Americans (p < 0.02), leading to a 493% increase in the Aβ42/Aβ40 ratio (p < 0.002). Analysis of GDNF levels did not indicate any significant effects. There were no significant effects of gender and no significant ethnicity with gender interactions on any analyte. Effect size calculations indicated "medium" to "very large" effects. CONCLUSION: S100B is typically elevated in AD cases; however, the increased levels in African Americans here may be indicative of increased severity in specific populations. Increased Aβ42/Aβ40 ratios in the current study are compatible with increased disease severity and might indicate increased AD pathogenesis in African Americans. Overall, these results are compatible with a hypothesis of increased neuroinflammation in African Americans with AD.

Neuroimaging Feature Terminology: A Controlled Terminology for the Annotation of Brain Imaging Features. - Iyappan, Anandhi; Younesi, Erfan; Redolfi, Alberto; Vrooman, Henri; Khanna, Shashank; Frisoni, Giovanni B; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Ontologies and terminologies are used for interoperability of knowledge and data in a standard manner among interdisciplinary research groups. Existing imaging ontologies capture general aspects of the imaging domain as a whole such as methodological concepts or calibrations of imaging instruments. However, none of the existing ontologies covers the diagnostic features measured by imaging technologies in the context of neurodegenerative diseases. Therefore, the Neuro-Imaging Feature Terminology (NIFT) was developed to organize the knowledge domain of measured brain features in association with neurodegenerative diseases by imaging technologies. The purpose is to identify quantitative imaging biomarkers that can be extracted from multi-modal brain imaging data. This terminology attempts to cover measured features and parameters in brain scans relevant to disease progression. In this paper, we demonstrate the systematic retrieval of measured indices from literature and how the extracted knowledge can be further used for disease modeling that integrates neuroimaging features with molecular processes.

Neurons Derived from Induced Pluripotent Stem Cells of Patients with Down Syndrome Reproduce Early Stages of Alzheimer's Disease Type Pathology in vitro. - Dashinimaev, Erdem B; Artyuhov, Alexander S; Bolshakov, Alexey P; Vorotelyak, Ekaterina A; Vasiliev, Andrey V (J Alzheimers Dis, 2017)
People with Down syndrome (DS) are at high risk of developing pathology similar to Alzheimer's disease (AD). Modeling of this pathology in vitro may be useful for studying this phenomenon. In this study, we analyzed three different cultures of neural cells carrying trisomy of chromosome 21, which were generated by directed differentiation from induced pluripotent stem cells (iPS cells). We report here that in vitro generated DS neural cells have abnormal metabolism of amyloid-β (Aβ) manifested by increased secretion and accumulation of Aβ granules of Aβ42 pathological isoform with upregulated expression of the APP gene. Additionally, we found increased expression levels of genes that are considered to be associated with AD (BACE2, RCAN1, ETS2, TMED10), as compared to healthy controls. Thus, the neural cells generated from induced pluripotent stem cells with DS reproduce initial cellular signs of AD-type pathology and can be useful tools for modeling and studying this variant of AD in vitro.

Neuroprotective Effect of TREM-2 in Aging and Alzheimer's Disease Model. - Raha, Animesh Alexander; Henderson, James W; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Friedland, Robert P; Zaman, Shahid H; Raha-Chowdhury, Ruma (J Alzheimers Dis, 2017)
Neuroinflammation and activation of innate immunity are early events in neurodegenerative diseases including Alzheimer's disease (AD). Recently, a rare mutation in the gene Triggering receptor expressed on myeloid cells 2 (TREM2) has been associated with a substantial increase in the risk of developing late onset AD. To uncover the molecular mechanisms underlying this association, we investigated the RNA and protein expression of TREM2 in APP/PS1 transgenic mice. Our findings suggest that TREM2 not only plays a critical role in inflammation, but is also involved in neuronal cell survival and in neurogenesis. We have shown that TREM2 is a soluble protein transported by macrophages through ventricle walls and choroid plexus, and then enters the brain parenchyma via radial glial cells. TREM2 protein is essential for neuroplasticity and myelination. During the late stages of life, a lack of TREM2 protein may accelerate aging processes and neuronal cell loss and reduce microglial activity, ultimately leading to neuroinflammation. As inflammation plays a major role in neurodegenerative diseases, a lack of TREM2 could be a missing link between immunomodulation and neuroprotection.

Neuropsychological Symptoms in Sporadic Creutzfeldt-Jakob Disease Patients in Germany. - Krasnianski, Anna; Bohling, Geeske T; Heinemann, Uta; Varges, Daniela; Meissner, Bettina; Schulz-Schaeffer, Walter J; Reif, Andreas; Zerr, Inga (J Alzheimers Dis, 2017)
BACKGROUND: The polymorphism at codon 129 of the prion protein gene (PRNP) and the PrPSc types 1 and 2 belong to a molecular classification of sporadic Creutzfeldt-Jakob disease (sCJD) that correlates well with the clinical and neuropathological phenotype of sCJD. OBJECTIVE: The aim of the study was to perform the first detailed evaluation of neuropsychological deficits in a large group of definite sCJD patients with known molecular subtype. METHODS: We analyzed neuropsychological symptoms in a cohort of 248 sCJD patients with known M129 V polymorphism of PRNP and prion protein type. RESULTS: Neuropsychological symptoms were very frequent in our patients (96%) and occurred as early as in the first third of the disease course. Besides amnesia and impaired attention (89% each), frontal lobe syndrome (75%), aphasia (63%), and apraxia (57%) were the most common neuropsychological deficits. There was no statistically significant difference with regard to frequency of neuropsychological symptoms between the subtypes. In MV2 and VV2 patients, the onset of neuropsychological symptoms was significantly later than in all other subtypes. CONCLUSION: We provide the first detailed analysis of neuropsychological symptoms in a large group of sCJD patients with known M129 V genotype and prion protein type. We suggest that the rate of progression of neuropsychological symptoms is subtype-specific. These data may improve the diagnosis in atypical sCJD subtypes.

Neutrophil Gelatinase-Associated Lipocalin and its Receptors in Alzheimer's Disease (AD) Brain Regions: Differential Findings in AD with and without Depression. - Dekens, Doortje W; Naudé, Petrus J W; Engelborghs, Sebastiaan; Vermeiren, Yannick; Van Dam, Debby; Oude Voshaar, Richard C; Eisel, Ulrich L M; De Deyn, Peter P (J Alzheimers Dis, 2017)
Co-existing depression worsens Alzheimer's disease (AD) pathology. Neutrophil gelatinase-associated lipocalin (NGAL) is a newly identified (neuro)inflammatory mediator in the pathophysiologies of both AD and depression. This study aimed to compare NGAL levels in healthy controls, AD without depression (AD-D), and AD with co-existing depression (AD+D) patients. Protein levels of NGAL and its receptors, 24p3R and megalin, were assessed in nine brain regions from healthy controls (n = 19), AD-D (n = 19), and AD+D (n = 21) patients. NGAL levels in AD-D patients were significantly increased in brain regions commonly associated with AD. In the hippocampus, NGAL levels were even further increased in AD+D subjects. Unexpectedly, NGAL levels in the prefrontal cortex of AD+D patients were comparable to those in controls. Megalin levels were increased in BA11 and amygdala of AD+D patients, while no changes in 24p3R were detected. These findings indicate significant differences in neuroimmunological regulation between AD patients with and without co-existing depression. Considering its known effects, elevated NGAL levels might actively promote neuropathological processes in AD with and without depression.

No Genetic Overlap Between Circulating Iron Levels and Alzheimer's Disease. - Lupton, Michelle K; Benyamin, Beben; Proitsi, Petroula; Nyholt, Dale R; Ferreira, Manuel A; Montgomery, Grant W; Heath, Andrew C; Madden, Pamela A; Medland, Sarah E; Gordon, Scott D; Lovestone, Simon; Tsolaki, Magda; et al. (J Alzheimers Dis, 2017)
Iron deposition in the brain is a prominent feature of Alzheimer's disease (AD). Recently, peripheral iron measures have also been shown to be associated with AD status. However, it is not known whether these associations are causal: do elevated or depleted iron levels throughout life have an effect on AD risk? We evaluate the effects of peripheral iron on AD risk using a genetic profile score approach by testing whether variants affecting iron, transferrin, or ferritin levels selected from GWAS meta-analysis of approximately 24,000 individuals are also associated with AD risk in an independent case-control cohort (n∼10,000). Conversely, we test whether AD risk variants from a GWAS meta-analysis of approximately 54,000 account for any variance in iron measures (n∼9,000). We do not identify a genetic relationship, suggesting that peripheral iron is not causal in the initiation of AD pathology.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

Novel Phospho-Tau Monoclonal Antibody Generated Using a Liposomal Vaccine, with Enhanced Recognition of a Conformational Tauopathy Epitope. - Theunis, Clara; Adolfsson, Oskar; Crespo-Biel, Natalia; Piorkowska, Kasia; Pihlgren, Maria; Hickman, David T; Gafner, Valerie; Borghgraef, Peter; Devijver, Herman; Pfeifer, Andrea; Van Leuven, Fred; Muhs, Andreas (J Alzheimers Dis, 2017)
The microtubule-associated protein Tau is an intrinsically unfolded, very soluble neuronal protein. Under still unknown circumstances, Tau protein forms soluble oligomers and insoluble aggregates that are closely linked to the cause and progression of various brain pathologies, including Alzheimer's disease. Previously we reported the development of liposome-based vaccines and their efficacy and safety in preclinical mouse models for tauopathy. Here we report the use of a liposomal vaccine for the generation of a monoclonal antibody with particular characteristics that makes it a valuable tool for fundamental studies as well as a candidate antibody for diagnostic and therapeutic applications. The specificity and affinity of antibody ACI-5400 were characterized by a panel of methods: (i) measuring the selectivity for a specific phospho-Tau epitope known to be associated with tauopathy, (ii) performing a combination of peptide and protein binding assays, (iii) staining of brain sections from mouse preclinical tauopathy models and from human subjects representing six different tauopathies, and (iv) evaluating the selective binding to pathological epitopes on extracts from tauopathy brains in non-denaturing sandwich assays. We conclude that the ACI-5400 antibody binds to protein Tau phosphorylated at S396 and favors a conformation that is typically present in the brain of tauopathy patients, including Alzheimer's disease.

The Pitfall of Behavioral Variant Frontotemporal Dementia Mimics Despite Multidisciplinary Application of the FTDC Criteria. - Krudop, Welmoed A; Dols, Annemieke; Kerssens, Cora J; Eikelenboom, Piet; Prins, Niels D; Möller, Christiane; Schouws, Sigfried; Rhebergen, Didi; van Exel, Eric; van der Flier, Wiesje M; Sikkes, Sietske; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The behavioral variant of frontotemporal dementia (bvFTD) has a broad differential diagnosis including other neurological and psychiatric disorders. Psychiatric misdiagnoses occur in up to 50% of bvFTD patients. Numbers on misdiagnosis of bvFTD in psychiatric disorders are lacking. OBJECTIVE: The aim of our study was to investigate the frequency and characteristics of bvFTD misdiagnoses in psychiatric disorders and other neurologic disorders. METHODS: Thirty-five patients with a (possible or probable) bvFTD diagnosis made by specialized memory clinic neurologists were included. Change in diagnosis after consulting a psychiatrist at baseline was recorded as well as change in diagnosis after two years of multidisciplinary neuropsychiatric follow-up. Differences in cognitive and behavioral profiles were investigated per diagnostic group after follow-up (bvFTD, psychiatry, other neurologic disorders). Clinical profiles are described in detail. RESULTS: In 17 patients (48.5%), the bvFTD baseline diagnosis changed: Two at baseline after psychiatric consultation, and 15 after two years of multidisciplinary follow-up. Eleven (64.5%) of these 17 patients (31.5% of total) were reclassified with a psychiatric diagnosis. We found no differences for cognitive baseline profiles between patients with bvFTD versus psychiatric diagnoses. CONCLUSION: In almost half of cases, the initial bvFTD diagnosis was changed after follow-up, most often into a psychiatric disorder. A multidisciplinary neuropsychiatric approach in the diagnostic process of bvFTD results in the identification of treatable disorders. Our findings illustrate a limited specificity of the [18F]FDG-PET-scan and the bvFTD criteria in a neuropsychiatric cohort, especially combined with certain clinical symptoms, like disinhibition, apathy, or loss of empathy.

Plasma Amyloid-β Levels, Cerebral Small Vessel Disease, and Cognition: The Rotterdam Study. - Hilal, Saima; Akoudad, Saloua; van Duijn, Cornelia M; Niessen, Wiro J; Verbeek, Marcel M; Vanderstichele, Hugo; Stoops, Erik; Ikram, M Arfan; Vernooij, Meike W (J Alzheimers Dis, 2017)
BACKGROUND: Plasma amyloid-β (Aβ) levels are increasingly studied as a potential, accessible marker of cognitive impairment and dementia. The most common plasma Aβ isoforms, i.e., Aβ1-40 and Aβ1-42 have been linked with risk of Alzheimer's disease. However, it remains under-explored whether plasma Aβ levels including novel Aβ1-38 relate to vascular brain disease and cognition in a preclinical-phase of dementiaObjective:To examine the association of plasma Aβ levels (i.e., Aβ1-38, Aβ1-40, and Aβ1-42) with markers of cerebral small vessel disease (SVD) and cognition in a large population-based setting. METHODS: We analyzed plasma Aβ1 levels in 1201 subjects from two independent cohorts of the Rotterdam Study. Markers of SVD [lacunes, white matter hyperintensity (WMH) volume] were assessed on brain MRI (1.5T). Cognition was assessed by a detailed neuropsychological battery. In each cohort, the association of Aβ levels with SVD and cognition was performed using regression models. Estimates were then pooled across cohorts using inverse variance meta-analysis with fixed effects. RESULTS: Higher levels of plasma Aβ1-38, Aβ1-40, Aβ1-42, and Aβ1-40/ Aβ1-42 ratio were associated with increasing lacunar and microbleeds counts. Moreover, higher levels of Aβ1-40 and Aβ1-40/ Aβ1-42 were significantly associated with larger WMH volumes. With regard to cognition, a higher level of Aβ1-38 Aβ1-40 and Aβ1-40/ Aβ1-42 was related to worse performance on cognitive test specifically in memory domain. CONCLUSION: Higher plasma levels of Aβ levels are associated with subclinical markers of vascular disease and poorer memory. Plasma Aβ levels thus mark the presence of vascular brain pathology.

Pleiotropic Effect of Human ApoE4 on Cerebral Ceramide and Saturated Fatty Acid Levels. - den Hoedt, Sandra; Janssen, Carola I F; Astarita, Giuseppe; Piomelli, Daniele; Leijten, Frank P J; Crivelli, Simone M; Verhoeven, Adrie J M; De Vries, Helga E; Walter, Jochen; Martinez-Martinez, Pilar; Sijbrands, Eric J G; Kiliaan, Amanda J; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) is known for its role in lipid trafficking and the ɛ4 allele is a risk factor for late onset Alzheimer's disease (AD). Recently, aberrant ceramide and fatty acid (FA) levels have been implicated in AD. OBJECTIVE: To determine the specific effects of human ApoE4 (hE4) on cerebral ceramide and FA content during chow or a high fat/high cholesterol (HFHC) diet. METHODS: Cerebral ceramide and FA profiles were determined by LC-MSMS in 15-month-old female wild-type (WT), ApoE-knockout (E0), and hE4-knockin mice fed chow or a HFHC diet for 3 months. mRNA levels of genes involved in ceramide and FA metabolism were determined by qPCR. RESULTS: Similar to E0, hE4 mice displayed lower cerebral total ceramide, Cer16 : 0, and Cer24 : 1 levels than WT mice on both diets. Akin to WT mice, hE4 mice had lower total and saturated FA levels on chow than E0 mice. The HFHC diet significantly increased total and saturated FA levels in hE4 mice. Chow-fed hE4 mice showed lower mRNA levels of ceramide synthase (CerS) 6, acid sphingomyelinase, and of most ceramide and FA transporters than WT and E0 mice. The HFHC diet downregulated the expression of CerSs in hE4 and WT mice, and of ceramide and FA transporters in WT mice, but not in E0 mice. CONCLUSION: hE4 reduced cerebral ceramide levels to levels observed in E0 mice independent of diet. The HFHC diet increased cerebral FA levels in hE4 mice. This was associated with alterations in the expression of ceramide and FA transporters specifically in hE4 mice.

Predicting Development of Amyotrophic Lateral Sclerosis in Frontotemporal Dementia. - Van Langenhove, Tim; Piguet, Olivier; Burrell, James R; Leyton, Cristian; Foxe, David; Abela, Melissa; Bartley, Lauren; Kim, Woojin S; Jary, Eve; Huang, Yue; Dobson-Stone, Carol; Kwok, John B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: A proportion of patients with frontotemporal dementia (FTD) also develop amyotrophic lateral sclerosis (ALS). OBJECTIVE: We aimed to establish the risk of developing ALS in patients presenting with FTD and to identify the relevant clinical variables associated with progression from FTD to FTD-ALS. METHODS: Of 218 consecutive patients with FTD, 10.1% had a dual FTD-ALS diagnosis at presentation. The remaining 152 FTD patients with follow-up of at least 12 months were included in the present study. We calculated the rate of progression to FTD-ALS and compared the baseline characteristics of FTD patients who developed ALS to those who did not develop ALS. RESULTS: Five percent of FTD patients developed ALS. The incidence rate of ALS was 6.7/100 patient-years in patients with FTD symptoms since 1 year, which declined with duration of FTD symptoms. No FTD patients developed ALS after 5 years. Five out of 8 FTD patients who developed ALS had presented with a mixed behavioral variant FTD and progressive non-fluent aphasia (bvFTD+PNFA) phenotype, 2 with bvFTD, and 1 with PNFA. Progression to FTD-ALS was significantly more frequent in patients with bvFTD+PNFA compared to those without this phenotype (p < 0.0001, OR 38.3, 95% CI: 7.3 to 199.2), and in FTD patients who carried the C9orf72 repeat expansion compared to those without the repeat expansion (p = 0.02, OR 8.0, 95% CI: 1.7 to 38.6). CONCLUSIONS: FTD patients with a mixed bvFTD+PNFA phenotype and with a C9orf72 repeat expansion should be closely monitored for the possible development of ALS. The risk of developing ALS in FTD appears to decline with the duration of FTD symptoms.

A Preliminary Study on the Feasibility of Using a Virtual Reality Cognitive Training Application for Remote Detection of Mild Cognitive Impairment. - Zygouris, Stelios; Ntovas, Konstantinos; Giakoumis, Dimitrios; Votis, Konstantinos; Doumpoulakis, Stefanos; Segkouli, Sofia; Karagiannidis, Charalampos; Tzovaras, Dimitrios; Tsolaki, Magda (J Alzheimers Dis, 2017)
BACKGROUND: It has been demonstrated that virtual reality (VR) applications can be used for the detection of mild cognitive impairment (MCI). OBJECTIVE: The aim of this study is to provide a preliminary investigation on whether a VR cognitive training application can be used to detect MCI in persons using the application at home without the help of an examiner. METHODS: Two groups, one of healthy older adults (n = 6) and one of MCI patients (n = 6) were recruited from Thessaloniki day centers for cognitive disorders and provided with a tablet PC with custom software enabling the self-administration of the Virtual Super Market (VSM) cognitive training exercise. The average performance (from 20 administrations of the exercise) of the two groups was compared and was also correlated with performance in established neuropsychological tests. RESULTS: Average performance in terms of duration to complete the given exercise differed significantly between healthy(μ  = 247.41 s/ sd = 89.006) and MCI (μ= 454.52 s/ sd = 177.604) groups, yielding a correct classification rate of 91.8% with a sensitivity and specificity of 94% and 89% respectively for MCI detection. Average performance also correlated significantly with performance in Functional Cognitive Assessment Scale (FUCAS), Test of Everyday Attention (TEA), and Rey Osterrieth Complex Figure test (ROCFT). DISCUSSION: The VR application exhibited very high accuracy in detecting MCI while all participants were able to operate the tablet and application on their own. Diagnostic accuracy was improved compared to a previous study using data from only one administration of the exercise. The results of the present study suggest that remote MCI detection through VR applications can be feasible.

Quantitative Comparison of Dense-Core Amyloid Plaque Accumulation in Amyloid-β Protein Precursor Transgenic Mice. - Liu, Peng; Reichl, John H; Rao, Eshaan R; McNellis, Brittany M; Huang, Eric S; Hemmy, Laura S; Forster, Colleen L; Kuskowski, Michael A; Borchelt, David R; Vassar, Robert; Ashe, Karen H; Zahs, Kathleen R (J Alzheimers Dis, 2017)
There exist several dozen lines of transgenic mice that express human amyloid-β protein precursor (AβPP) with Alzheimer's disease (AD)-linked mutations. AβPP transgenic mouse lines differ in the types and amounts of Aβ that they generate and in their spatiotemporal patterns of expression of Aβ assemblies, providing a toolkit to study Aβ amyloidosis and the influence of Aβ aggregation on brain function. More complete quantitative descriptions of the types of Aβ assemblies present in transgenic mice and in humans during disease progression should add to our understanding of how Aβ toxicity in mice relates to the pathogenesis of AD. Here, we provide a direct quantitative comparison of amyloid plaque burdens and plaque sizes in four lines of AβPP transgenic mice. We measured the fraction of cortex and hippocampus occupied by dense-core plaques, visualized by staining with Thioflavin S, in mice from young adulthood through advanced age. We found that the plaque burdens among the transgenic lines varied by an order of magnitude: at 15 months of age, the oldest age studied, the median cortical plaque burden in 5XFAD mice was already ∼4.5 times that of 21-month-old Tg2576 mice and ∼15 times that of 21-24-month-old rTg9191 mice. Plaque-size distributions changed across the lifespan in a line- and region-dependent manner. We also compared the dense-core plaque burdens in the mice to those measured in a set of pathologically-confirmed AD cases from the Nun Study. Cortical plaque burdens in Tg2576, APPSwePS1ΔE9, and 5XFAD mice eventually far exceeded those measured in the human cohort.

Rare Genetic Variant in SORL1 May Increase Penetrance of Alzheimer's Disease in a Family with Several Generations of APOE-ɛ4 Homozygosity. - Louwersheimer, Eva; Cohn-Hokke, Petra E; Pijnenburg, Yolande A L; Weiss, Marjan M; Sistermans, Erik A; Rozemuller, Annemieke J; Hulsman, Marc; van Swieten, John C; van Duijn, Cock M; Barkhof, Frederik; Koene, Teddy; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The major genetic risk factor for late onset Alzheimer's disease (AD) is the APOE-ɛ4 allele. However, APOE-ɛ4 homozygosity is not fully penetrant, suggesting co-occurrence of additional genetic variants. OBJECTIVE: To identify genetic factors that, next to APOE-ɛ4 homozygosity, contribute to the development of AD. METHODS: We identified a family with nine AD patients spanning four generations, with an inheritance pattern suggestive of autosomal dominant AD, with no variants in PSEN1, PSEN2, or APP. We collected DNA from four affected and seven unaffected family members and performed exome sequencing on DNA from three affected and one unaffected family members. RESULTS: All affected family members were homozygous for the APOE-ɛ4 allele. Statistical analysis revealed that AD onset in this family was significantly earlier than could be expected based on APOE genotype and gender. Next to APOE-ɛ4 homozygosity, we found that all four affected family members carried a rare variant in the VPS10 domain of the SORL1 gene, associated with AβPP processing and AD risk. Furthermore, three of four affected family members carried a rare variant in the TSHZ3 gene, also associated with AβPP processing. Affected family members presented between 61 and 74 years, with variable presence of microbleeds/cerebral amyloid angiopathy and electroencephalographic abnormalities. CONCLUSION: We hypothesize that next to APOE-ɛ4 homozygosity, impaired SORL1 protein function, and possibly impaired TSHZ3 function, further disturbed Aβ processing. The convergence of these genetic factors over several generations might clarify the increased AD penetrance and the autosomal dominant-like inheritance pattern of AD as observed in this family.

Reduced Cerebral Blood Flow in Mild Cognitive Impairment Assessed Using Phase-Contrast MRI. - de Eulate, Reyes García; Goñi, Irene; Galiano, Alvaro; Vidorreta, Marta; Recio, Miriam; Riverol, Mario; Zubieta, José L; Fernández-Seara, María A (J Alzheimers Dis, 2017)
There is increasing evidence of a vascular contribution to Alzheimer's disease (AD). In some cases, prior work suggests that chronic brain hypoperfusion could play a prime pathogenic role contributing to the accumulation of amyloid-β,while other studies favor the hypothesis that vascular dysfunction and amyloid pathology are independent, although synergistic, mechanisms contributing to cognitive impairment. Vascular dysfunction can be evaluated by assessing cerebral blood flow impairment. Phase contrast velocity mapping by MRI offers a non-invasive means of quantifying the total inflow of blood to the brain. This quantitative parameter could be a sensitive indicator of vascular disease at early stages of AD. In this work, phase contrast MRI was used to evaluate cerebral hemodynamics in patients with subjective memory complaints, amnestic mild cognitive impairment, and mild to moderate AD, and compare them with control subjects. Results showed that blood flow and velocity were decreased in the patients with cognitive dysfunction and the decrease correlated with the degree of cognitive impairment as assessed by means of neuropsychological tests. Total cerebral blood flow measurements were clearly reduced in AD patients, but more importantly appeared to be sensitive enough to distinguish between healthy subjects and those with mild cognitive impairment. A quantitative measurement of total brain blood flow could potentially predict vascular dysfunction and compromised brain perfusion in early stages of AD.

Reduction of RPT6/S8 (a Proteasome Component) and Proteasome Activity in the Cortex is associated with Cognitive Impairment in Lewy Body Dementia. - Alghamdi, Amani; Vallortigara, Julie; Howlett, David R; Broadstock, Martin; Hortobágyi, Tibor; Ballard, Clive; Thomas, Alan J; O'Brien, John T; Aarsland, Dag; Attems, Johannes; Francis, Paul T; Whitfield, David R (J Alzheimers Dis, 2017)
Lewy body dementia is the second most common neurodegenerative dementia and is pathologically characterized by α-synuclein positive cytoplasmic inclusions, with varying amounts of amyloid-β (Aβ) and hyperphosphorylated tau (tau) aggregates in addition to synaptic loss. A dysfunctional ubiquitin proteasome system (UPS), the major proteolytic pathway responsible for the clearance of short lived proteins, may be a mediating factor of disease progression and of the development of α-synuclein aggregates. In the present study, protein expression of a key component of the UPS, the RPT6 subunit of the 19S regulatory complex was determined. Furthermore, the main proteolytic-like (chymotrypsin- and PGPH-) activities have also been analyzed. The middle frontal (Brodmann, BA9), inferior parietal (BA40), and anterior cingulate (BA24) gyrus' cortex were selected as regions of interest from Parkinson's disease dementia (PDD, n = 31), dementia with Lewy bodies (DLB, n = 44), Alzheimer's disease (AD, n = 16), and control (n = 24) brains. Clinical and pathological data available included the MMSE score. DLB, PDD, and AD were characterized by significant reductions of RPT6 (one-way ANOVA, p < 0.001; Bonferroni post hoc test) in prefrontal cortex and parietal cortex compared with controls. Strong associations were observed between RPT6 levels in prefrontal, parietal cortex, and anterior cingulate gyrus and cognitive impairment (p = 0.001, p = 0.001, and p = 0.008, respectively). These findings highlight the involvement of the UPS in Lewy body dementia and indicate that targeting the UPS may have the potential to slow down or reduce the progression of cognitive impairment in DLB and PDD.

Relation of Odor Identification with Alzheimer's Disease Markers in Cerebrospinal Fluid and Cognition. - Reijs, Babette L R; Ramakers, Inez H G B; Elias-Sonnenschein, Lyzel; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Johannsen, Peter; Vanderstichele, Hugo; Verhey, Frans; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Impaired olfactory function is an early characteristic of Alzheimer's disease (AD), but it remains unclear if odor identification also relates to early markers of AD in cerebrospinal fluid (CSF). OBJECTIVE: To investigate the association between odor identification and amyloid-β 1-42 (Aβ42) and total tau (t-tau) concentrations in CSF. In addition, to examine the relation between odor identification and cognitive function at baseline and at follow-up, and whether these associations are moderated by CSF Aβ42 and t-tau and apolipoprotein E (APOE) genotype. METHODS: We included 160 individuals (40 with normal cognition, 45 with mild cognitive impairment (MCI), 42 with AD-type dementia, and 26 individuals with non-AD dementia) from the EDAR study. Individuals were recruited from six memory clinics across Europe. Odor identification was tested with the brief University of Pennsylvania Smell Identification Test. CSF Aβ42 and t-tau were assessed with INNO-BIA AlzBio3 Luminex assay. Neuropsychological assessment included tests for verbal memory, verbal fluency, attention, executive function, and visuoconstruction. Follow-up was performed within 3 years after baseline. RESULTS: Lower odor identification scores correlated with increased CSF t-tau concentrations and with lower scores on all cognitive measures at baseline independent of diagnostic group. Lower odor identification scores predicted decline on the MMSE in the total group, and decline on wordlist learning and delayed recall in APOE ɛ4 carriers and in individuals with abnormal Aβ42. CONCLUSION: Odor identification impairment may be an indicator of neuronal injury rather than amyloid pathology.

Relationships of Dietary Patterns, Foods, and Micro- and Macronutrients with Alzheimer's Disease and Late-Life Cognitive Disorders: A Systematic Review. - Solfrizzi, Vincenzo; Custodero, Carlo; Lozupone, Madia; Imbimbo, Bruno P; Valiani, Vincenzo; Agosti, Pasquale; Schilardi, Andrea; D'Introno, Alessia; La Montagna, Maddalena; Calvani, Mariapaola; Guerra, Vito; Sardone, Rodolfo; et al. (J Alzheimers Dis, 2017)
In the last decade, the association between diet and cognitive function or dementia has been largely investigated. In the present article, we systematically reviewed observational studies published in the last three years (2014-2016) on the relationship among dietary factors and late-life cognitive disorders at different levels of investigation (i.e., dietary patterns, foods and food-groups, and dietary micro- and macronutrients), and possible underlying mechanisms of the proposed associations. From the reviewed evidence, the National Institute on Aging-Alzheimer's Association guidelines for Alzheimer's disease (AD) and cognitive decline due to AD pathology introduced some evidence suggesting a direct relation between diet and changes in the brain structure and activity. There was also accumulating evidence that combinations of foods and nutrients into certain patterns may act synergistically to provide stronger health effects than those conferred by their individual dietary components. In particular, higher adherence to a Mediterranean-type diet was associated with decreased cognitive decline. Moreover, also other emerging healthy dietary patterns such as the Dietary Approach to Stop Hypertension (DASH) and the Mediterranean-DASH diet Intervention for Neurodegenerative Delay (MIND) diets were associated with slower rates of cognitive decline and significant reduction of AD rate. Furthermore, some foods or food groups traditionally considered harmful such as eggs and red meat have been partially rehabilitated, while there is still a negative correlation of cognitive functions with saturated fatty acids and a protective effect against cognitive decline of elevated fish consumption, high intake of monounsaturated fatty acids and polyunsaturated fatty acids (PUFA), particularly n-3 PUFA.

Relative Incidence of Seizures and Myoclonus in Alzheimer's Disease, Dementia with Lewy Bodies, and Frontotemporal Dementia. - Beagle, Alexander J; Darwish, Sonja M; Ranasinghe, Kamalini G; La, Alice L; Karageorgiou, Elissaios; Vossel, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: Patients with Alzheimer's disease (AD) are more prone to seizures and myoclonus, but relative risk of these symptoms among other dementia types is unknown. OBJECTIVE: To determine incidence of seizures and myoclonus in the three most common neurodegenerative dementias: AD, dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD). METHODS: Our institution's medical records were reviewed for new-onset unprovoked seizures and myoclonus in patients meeting criteria for AD (n = 1,320), DLB (n = 178), and FTD (n = 348). Cumulative probabilities of developing seizures and myoclonus were compared between diagnostic groups, whereas age-stratified incidence rates were determined relative to control populations. RESULTS: The cumulative probability of developing seizures after disease onset was 11.5% overall, highest in AD (13.4%) and DLB (14.7%) and lowest in FTD (3.0%). The cumulative probability of developing myoclonus was 42.1% overall, highest in DLB (58.1%). The seizure incidence rates, relative to control populations, were nearly 10-fold in AD and DLB, and 6-fold in FTD. Relative seizure rates increased with earlier age-at-onset in AD (age <50, 127-fold; 50-69, 21-fold; 70+, 2-fold) and FTD (age <50, 53-fold; 50-69, 9-fold), and relative myoclonus rates increased with earlier age-at-onset in all groups. Seizures began an average of 3.9 years after the onset of cognitive or motor decline, and myoclonus began 5.4 years after onset. CONCLUSIONS: Seizures and myoclonus occur with greater incidence in patients with AD, DLB, and FTD than in the general population, but rates vary with diagnosis, suggesting varied pathomechanisms of network hyperexcitability. Patients often experience these symptoms early in disease, suggesting hyperexcitability could be an important target for interventions.

The Road Less Traveled: Alternative Pathways for Action-Verb Processing in Parkinson's Disease. - Abrevaya, Sofía; Sedeño, Lucas; Fitipaldi, Sol; Pineda, David; Lopera, Francisco; Buritica, Omar; Villegas, Andrés; Bustamante, Catalina; Gomez, Diana; Trujillo, Natalia; Pautassi, Ricardo; Ibáñez, Agustín; et al. (J Alzheimers Dis, 2017)
Action verbs are critically embodied in motor brain networks. In Parkinson's disease (PD), damage to the latter compromises access to such words. However, patients are not fully incapable of processing them, as their performance is far from floor level. Here we tested the hypothesis that action-verb processing in PD may rely on alternative disembodied semantic circuits. Seventeen PD patients and 15 healthy controls listened to action verbs and nouns during functional MRI scanning. Using cluster-mass analysis with a permutation test, we assessed task-related functional connectivity considering seeds differentially engaged by action and non-action words (namely, putamen and M1 versus posterior superior temporal lobe, respectively). The putamen seed showed reduced connectivity within the basal ganglia in patients for both lexical categories. However, only action verbs recruited different cortical networks in each group. Specifically, the M1 seed exhibited more anterior connectivity for controls and more posterior connectivity for patients, with no differences in the temporal seed. Moreover, the patients' level of basal ganglia atrophy positively correlated with their reliance on M1-posterior connectivity during action-verb processing. PD patients seem to have processed action verbs via non-motor cortical networks subserving amodal semantics. Such circuits may afford alternative pathways to process words when default embodied mechanisms are disturbed. Moreover, the greater the level of basal ganglia atrophy, the greater the patients' reliance on this alternative route. Our findings offer new insights into differential neurofunctional mechanisms recruited to process action semantics in PD.

Role of Niemann-Pick Type C Disease Mutations in Dementia. - Cupidi, Chiara; Frangipane, Francesca; Gallo, Maura; Clodomiro, Alessandra; Colao, Rosanna; Bernardi, Livia; Anfossi, Maria; Conidi, Maria Elena; Vasso, Franca; Curcio, Sabrina Anna Maria; Mirabelli, Maria; Smirne, Nicoletta; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Several neurological and systemic diseases can cause dementia, beyond Alzheimer's disease. Rare genetic causes are often responsible for dementia with atypical features. Recently, mutations causative for Niemann-Pick type C disease (NPC) have also been implicated in neurodegenerative diseases. NPC is an autosomal recessive lipid storage disorder caused by mutations in NPC1 and NPC2 genes. In adults, clinical presentation mimicking other neurodegenerative diseases makes diagnosis difficult. Recent evidence suggests that heterozygous mutations in NPC genes may take on etiological significance. OBJECTIVE: To investigate the presence of NPC1 and NPC2 mutations in adults affected by neurodegenerative dementia plus. METHODS: We performed a genetic screening on 50 patients using a wide clinical and biochemical approach to characterize the phenotype of mutated patients. RESULTS: Sequencing analysis revealed four different and known heterozygous mutations in NPC1 and NPC2 genes. Patient 1 carried the p. F284LfsX26 in NPC1 and was affected by progressive supranuclear palsy-like syndrome. The remaining three patients showed a corticobasal syndrome and harbored the c.441+1G>A variant of NPC2 (patient 2), the missense p.N222 S mutation associated with the c.1947+8G>C variant in the splice region of intron 12 in NPC1 (patient 3), and the p.V30M mutation in NPC2 (patient 4), respectively. Filipin staining was abnormal in patients 1 and 2. mRNA analysis revealed an altered splicing of the NPC2 gene in patient 2. CONCLUSIONS: Heterozygous mutations of NPC1 and NPC2 genes could contribute to dementia plus, at least in a subset of patients. We highlight the occurrence of NPC1 and NPC2 heterozygous variants in dementia-plus as pathological event.

Is Salivary Chromogranin A a Valid Psychological Stress Biomarker During Sensory Stimulation in People with Advanced Dementia? - Valdiglesias, Vanessa; Maseda, Ana; Lorenzo-López, Laura; Pásaro, Eduardo; Millán-Calenti, José C; Laffon, Blanca (J Alzheimers Dis, 2017)
Salivary chromogranin A (sCgA) is gaining attention as a biomarker of psychological stress. The objective of this work was to determine whether individualized music intervention and multisensory stimulation environment (MSSE) in a Snoezelen room produce changes in sCgA in severely demented older patients, and to assess the possible existence of differences in sCgA levels between the two types of interventions. Older adults with severe dementia (n = 22) were randomly assigned to two intervention groups. They participated in MSSE or individualized music interventions in 30-min weekly sessions for 16 weeks. Levels of sCgA were evaluated before and after a session, or 30-min interval, at four different time points: before starting the trial, in the middle and end of the intervention period, and two months later. Comparison of sCgA values obtained after each session with those obtained before (or at the same hour in before trial and follow-up samplings) showed no significant differences either in the individualized music or in the MSSE group at any sampling time. Comparison between the two types of interventions, both before and after each session, in the four sampling times, did not produce any significant difference either. Furthermore, no significant correlation was obtained between agitation, anxiety, cognitive function, and dementia severity with sCgA levels. In conclusion, despite beneficial effects of both individualized music and MSSE interventions being previously reported on neuropsychiatric outcomes for older patients with dementia, sCgA seems to not be a good indicator of these benefits.

Screening for Mild Cognitive Impairment and Dementia with Automated, Anonymous Online and Telephone Cognitive Self-Tests. - Van Mierlo, Lisa D; Wouters, Hans; Sikkes, Sietske A M; van der Flier, Wiesje M; Prins, Niels D; Bremer, Jonne A E; Koene, Teddy; Van Hout, Hein P J (J Alzheimers Dis, 2017)
BACKGROUND: Many older people worry about cognitive decline. Early cognitive screening in an anonymous and easily accessible manner may reassure older people who are unnecessarily worried about normal cognitive aging while it may also expedite help seeking in case of suspicious cognitive decline. OBJECTIVE: To develop and validate online and telephone-based automated self-tests of cognitive function. METHODS: We examined the feasibility and validity of the self-tests in a prospective study of 117 participants of whom 34 had subjective cognitive decline (SCD), 30 had mild cognitive impairment (MCI), and 53 had dementia. The ability of these self-tests to accurately distinguish MCI and dementia from SCD was examined with ROC curves. Convergent validity was examined by calculating rank correlations between the self-tests and neuropsychological tests. RESULTS: Both the online and telephone cognitive self-tests were feasible, because the majority of participants (86% and 80%, respectively) were able to complete them. The online self-test had adequate diagnostic accuracy in the screening for MCI and dementia versus SCD with an Area under the Curve (AUC) of 0.86 (95% CI: 0.78-0.93). The AUC of the MMSE was 0.82 (95% CI: 0.74-0.89). By contrast, the telephone self-test had lower diagnostic accuracy (AUC = 0.75, 95% CI: 0.64-0.86). Both self-tests had good convergent validity as demonstrated by moderate to strong rank correlations with neuropsychological tests. CONCLUSION: We demonstrated good diagnostic accuracy and convergent validity for the online self-test of cognitive function. It is therefore a promising tool in the screening for MCI and dementia.

Sensing of Alzheimer's Disease and Multiple Sclerosis Using Nano-Bio Interfaces. - Hajipour, Mohammad Javad; Ghasemi, Forough; Aghaverdi, Haniyeh; Raoufi, Mohammad; Linne, Uwe; Atyabi, Fatemeh; Nabipour, Iraj; Azhdarzadeh, Morteza; Derakhshankhah, Hossein; Lotfabadi, Alireza; Bargahi, Afshar; Alekhamis, Zahra; et al. (J Alzheimers Dis, 2017)
It is well understood that patients with different diseases may have a variety of specific proteins (e.g., type, amount, and configuration) in their plasmas. When nanoparticles (NPs) are exposed to these plasmas, the resulting coronas may incorporate some of the disease-specific proteins. Using gold (Au) NPs with different surface properties and corona composition, we have developed a colorimetric sensor array for the discrimination and detection of two neurodegenerative diseases, Alzheimer's disease (AD) and multiple sclerosis (MS). Applying a variety of techniques, including UV-visible spectra, array response analyses and liquid chromatography-tandem mass spectrometry, we found the corona-NP complexes, obtained from different human serums, had distinct protein composition, including some specific proteins that are known as AD and MS biomarkers. The array responses, analyzed by chemometrics and statistical methods, demonstrate promising capabilities of the sensor to unambiguously identify and discriminate AD and MS. The developed sensor array might enable a simple, inexpensive and rapid detection/discrimination of neurodegenerative diseases.

Sleep Apnea, Cognitive Profile, and Vascular Changes: An Intriguing Relationship. - Buratti, Laura; Viticchi, Giovanna; Baldinelli, Sara; Falsetti, Lorenzo; Luzzi, Simona; Pulcini, Alessandra; Petrelli, Cristina; Provinciali, Leandro; Silvestrini, Mauro (J Alzheimers Dis, 2017)
BACKGROUND: Sleep breathing disorders can affect cognitive performances through complex brain anatomical and functional changes. OBJECTIVE: Our aim was to evaluate the correlations between cognitive performances and obstructive sleep apnea syndrome (OSAS), as well as the possible influence of vascular factors. METHODS: Thirty-four non-demented OSAS patients and 34 controls were submitted to a neuropsychological evaluation and to a vascular screening including the study of cerebrovascular reactivity by means of the breath-holding index (BHI) calculation. After 6 months, polisomnographic, neuropsychologic, and hemodynamics assessment was repeated in patients. RESULTS: At baseline, some cognitive performances involved in executive and memory functions were significantly lower in patients with respect to controls. Significantly lower values in mean BHI were also detected in patients with respect to controls (p < 0.0001). At the 6-month evaluation, 18 patients had a reduction in OSAS severity (group 1) and 16 remained stable (group 2). Group 1 patients had a significant improvement in left and mean BHI (p < 0.001) and in short-term (p = 0.02) and long-term Rey Auditory Verbal Learning Test (p < 0.001). No change in cerebrovascular reactivity and cognitive profile was detected in group 2 patients. CONCLUSIONS: Patients with OSAS may experience a reduced cognitive efficiency. Improvement of OSAS was associated to favorable hemodynamic changes and increased level of performances in verbal memory tasks so suggesting an involvement of vascular underlying mechanisms in sustaining cognitive dysfunctions in OSAS. Our preliminary data suggest the need for further studies to deepen the knowledge about the relationships between OSAS, cerebral hemodynamic compromise, and cognitive impairment risk.

Social Cognition in the Frontal Variant of Alzheimer's Disease: A Case Study. - Duclos, Harmony; de la Sayette, Vincent; Bonnet, Anne-Laure; Viard, Armelle; Eustache, Francis; Desgranges, Béatrice; Laisney, Mickaël (J Alzheimers Dis, 2017)
Although frontal presentations of Alzheimer's disease (fv-AD) have already been described in the literature, we still know little about patients' social cognitive abilities, especially their theory of mind (ToM). We report the case of FT, a 61-year-old woman who was diagnosed with fv-AD. Two assessments of social cognition, using a false-belief task, the Reading the Mind in the Eyes test, and a task probing knowledge of social norms, were performed one year apart. FT exhibited cognitive ToM and social knowledge deficits from the onset. Affective ToM was initially preserved, but deteriorated as the disease progressed.

Social Representation of Dementia: An Analysis of 5,792 Consecutive Cases Evaluated in a Memory Clinic. - Cañabate, Pilar; Martínez, Gabriel; Rosende-Roca, Maitee; Moreno, Mariola; Preckler, Silvia; Valero, Sergi; Sotolongo, Oscar; Hernandez, Isabel; Alegret, Montserrat; Ortega, Gemma; Espinosa, Ana; Mauleón, Ana; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Different interpretations of cognitive impairment and dementia due to differences in health structures, such as cultural differences could affect the diagnosis and treatment of the condition. it is reasonable to expect that the social and family impact of the disease and coping strategies will differ among societies. OBJECTIVE: The general aim of this study is to understand the social representations of dementia, its associated practices, and the effects they imply. METHODS: People diagnosed with clinical dementia and their families were assessed from 2005 to 2015 in the memory clinic of the Fundació ACE, Institut Català de Neurociències Aplicades in Barcelona, Spain. RESULTS: 9,898 people were examined and 5,792 were diagnosed with dementia. For those with a caregiver (71%), the decision-making fell on the person with dementia in 16.2% of the cases; and for those without a caregiver, in 26.4% of the cases the family did not perceive the deficits as a disease, which led to multiple risk situations (74.6%). CONCLUSIONS: The recognition of dementia as part of aging is common among families. Consequently, risk situations may arise and diagnosis and access to treatment may be delayed. The incorporation of a social appraisal to the diagnostic process is a necessity to evaluate these situations.

Subjective Cognitive Complaints in Cognitively Healthy Older Adults and Their Relationship to Cognitive Performance and Depressive Symptoms. - Marková, Hana; Andel, Ross; Stepankova, Hana; Kopecek, Miloslav; Nikolai, Tomas; Hort, Jakub; Thomas-Antérion, Catherine; Vyhnálek, Martin (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive complaints (SCCs) may be an early marker of prodromal Alzheimer's disease. OBJECTIVES: Using a 10-item yes/no SCCs questionnaire (Le Questionnaire de Plainte Cognitive [QPC]), we evaluated the prevalence and distribution of SCCs in cognitively healthy Czech older adults and examined total score and specific QPC items in relation to depressive symptomology and cognitive performance. METHODS: A sample of 340 cognitively healthy older community-dwelling volunteers aged 60 or older from the third wave of the longitudinal project National Normative Study of Cognitive Determinants of Healthy Aging, who underwent a comprehensive neuropsychological assessment and completed the QPC and the 15-item Geriatric Depression Scale (GDS-15). Regression analysis was controlled for age when GDS-15 was the outcome and for age and GDS-15 with cognitive domains as the outcome. RESULTS: 71% reported 1 + SCCs, with prevalence of individual complaints ranging from 4% to 40%. The number of SCCs was associated with GDS-15 (p < 0.001). Personality change (p < 0.001) and Limitation in daily activities (p = 0.002) were significantly associated with higher GDS-15 score and Spatial orientation difficulties (p = 0.019) and Impression of worse memory in comparison to peers (p = 0.012) were significantly associated with lower memory performance. CONCLUSIONS: We identified some cognitive complaints that were very common in our sample. Overall, a higher number of SCCs in well cognitively functioning individuals was most closely related to depressive symptomatology, while some specific complaints reflected lower memory performance and should be considered when screening for people at risk of cognitive decline.

Synaptic Membrane Synthesis in Rats Depends on Dietary Sufficiency of Vitamin C, Vitamin E, and Selenium: Relevance for Alzheimer's Disease. - Cansev, Mehmet; Turkyilmaz, Mesut; Sijben, John W C; Sevinc, Cansu; Broersen, Laus M; van Wijk, Nick (J Alzheimers Dis, 2017)
Chronic consumption of a diet enriched with nutritional precursors of phospholipids, including uridine and the polyunsaturated fatty acids, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), was shown previously to enhance levels of brain phospholipids and synaptic proteins in rodents. Vitamin C, vitamin E, and selenium may directly affect the breakdown or synthesis of membrane phospholipids. The present study investigated the necessity of antioxidants for the effectiveness of supplementation with uridine plus DHA and EPA (as fish oil) in rats. Rats were randomized to four treatment groups and received, for 6 weeks, one of four experimental diets, i.e., a diet low in antioxidants, a diet high in antioxidants, a diet low in antioxidants supplemented with DHA+EPA+uridine, or a diet high in antioxidants supplemented with DHA+EPA+uridine. On completion of dietary treatment, rats were sacrificed, and brain levels of phospholipids, synaptic proteins, and two enzymes involved in phospholipid synthesis (choline-phosphate cytidylyltransferase, PCYT1A, and choline/ethanolamine phosphotransferase, CEPT1) were analyzed. Levels of phospholipids, the pre- and post-synaptic proteins Synapsin-1 and PSD95, and the enzymes PCYT1A and CEPT1 were significantly enhanced by combined supplementation of DHA+EPA+uridine and antioxidants and not enhanced by supplementation of DHA+EPA+uridine with insufficient antioxidant levels. Our data suggest that dietary vitamin C, vitamin E, and selenium are essential for the phospholipid precursors' effects on increasing levels of membrane phospholipids and synaptic proteins, the indirect indicators of synaptogenesis. Their concomitant supply may be relevant in Alzheimer's disease patients, because the disease is characterized by synapse loss and lower plasma and brain levels of phospholipid precursors and antioxidants.

A Systematic Review of Longitudinal Studies Which Measure Alzheimer's Disease Biomarkers. - Lawrence, Emma; Vegvari, Carolin; Ower, Alison; Hadjichrysanthou, Christoforos; De Wolf, Frank; Anderson, Roy M (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive and fatal neurodegenerative disease, with no effective treatment or cure. A gold standard therapy would be treatment to slow or halt disease progression; however, knowledge of causation in the early stages of AD is very limited. In order to determine effective endpoints for possible therapies, a number of quantitative surrogate markers of disease progression have been suggested, including biochemical and imaging biomarkers. The dynamics of these various surrogate markers over time, particularly in relation to disease development, are, however, not well characterized. We reviewed the literature for studies that measured cerebrospinal fluid or plasma amyloid-β and tau, or took magnetic resonance image or fluorodeoxyglucose/Pittsburgh compound B-positron electron tomography scans, in longitudinal cohort studies. We summarized the properties of the major cohort studies in various countries, commonly used diagnosis methods and study designs. We have concluded that additional studies with repeat measures over time in a representative population cohort are needed to address the gap in knowledge of AD progression. Based on our analysis, we suggest directions in which research could move in order to advance our understanding of this complex disease, including repeat biomarker measurements, standardization and increased sample sizes.

Tau Rather than TDP-43 Proteins are Potential Cerebrospinal Fluid Biomarkers for Frontotemporal Lobar Degeneration Subtypes: A Pilot Study. - Kuiperij, H Bea; Versleijen, Alexandra A M; Beenes, Marijke; Verwey, Nicolaas A; Benussi, Luisa; Paterlini, Anna; Binetti, Giuliano; Teunissen, Charlotte E; Raaphorst, Joost; Schelhaas, Helenius J; Küsters, Benno; Pijnenburg, Yolande A L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Frontotemporal dementia (FTD) is a heterogeneous disease both at the clinical, genetic, and pathobiological level. The underlying pathological spectrum (termed FTLD, frontotemporal lobar degeneration) is in most cases defined by accumulation of either tau (FTLD-tau) or TDP-43 proteins (FTLD-TDP). Biomarkers to differentiate these subtypes are not yet available, whereas these are essential requirements to study the natural course of disease and for homogeneous inclusion of patients in clinical studies. OBJECTIVE: To study if a combination of total (t-) and phosphorylated (p-)tau, and t-TDP-43 and p-TDP-43 proteins in cerebrospinal fluid (CSF) is suitable to discriminate FTLD-tau and FTLD-TDP subtypes. METHODS: We developed immunoassays for the quantification of t-TDP-43 and p-TDP-43 proteins and used commercially available assays for the quantification of t-tau and p-tau proteins. We quantified these proteins in ventricular CSF samples from neuropathologically defined FTLD-tau and FTLD-TDP cases to study the reflection of underlying brain pathology in CSF composition, and in lumbar CSF samples from FTLD-tau and FTLD-TDP patients to study the diagnostic potential of CSF biomarkers. RESULTS: In ventricular CSF, t-TDP-43 and t-tau levels, when combined into one model, were significantly different between neuropathologically-defined FTLD-tau and FTLD-TDP cases. In a pilot study using lumbar CSF, the p-tau/t-tau ratio, but not t-TDP-43 levels, were significantly different between FTLD-TDP and FTLD-tau patients. CONCLUSION: We conclude that with current available methods, CSF tau, rather than TDP-43 proteins, may have diagnostic value in the differentiation of FTLD patients with either tau or TDP-43 pathology.

Toward the Automation of Diagnostic Conversation Analysis in Patients with Memory Complaints. - Mirheidari, Bahman; Blackburn, Daniel; Harkness, Kirsty; Walker, Traci; Venneri, Annalena; Reuber, Markus; Christensen, Heidi (J Alzheimers Dis, 2017)
BACKGROUND: The early diagnosis of dementia is of great clinical and social importance. A recent study using the qualitative methodology of conversation analysis (CA) demonstrated that language and communication problems are evident during interactions between patients and neurologists, and that interactional observations can be used to differentiate between cognitive difficulties due to neurodegenerative disorders (ND) or functional memory disorders (FMD). OBJECTIVE: This study explores whether the differential diagnostic analysis of doctor-patient interactions in a memory clinic can be automated. METHODS: Verbatim transcripts of conversations between neurologists and patients initially presenting with memory problems to a specialist clinic were produced manually (15 with FMD, and 15 with ND). A range of automatically detectable features focusing on acoustic, lexical, semantic, and visual information contained in the transcripts were defined aiming to replicate the diagnostic qualitative observations. The features were used to train a set of five machine learning classifiers to distinguish between ND and FMD. RESULTS: The mean rate of correct classification between ND and FMD was 93% ranging from 97% by the Perceptron classifier to 90% by the Random Forest classifier.Using only the ten best features, the mean correct classification score increased to 95%. CONCLUSION: This pilot study provides proof-of-principle that a machine learning approach to analyzing transcripts of interactions between neurologists and patients describing memory problems can distinguish people with neurodegenerative dementia from people with FMD.

Two Novel Mutations in the First Transmembrane Domain of Presenilin1 Cause Young-Onset Alzheimer's Disease. - Liu, Collin Y; Ohki, Yu; Tomita, Taisuke; Osawa, Satoko; Reed, Bruce R; Jagust, William; Van Berlo, Victoria; Jin, Lee-Way; Chui, Helena C; Coppola, Giovanni; Ringman, John M (J Alzheimers Dis, 2017)
BACKGROUND: The presenilin-1 protein (PS1) is the catalytic unit of γ-secretase implicated in the production of abnormally long forms of amyloid-β (Aβ), including Aβ42, proteins thought critical in the pathogenesis of Alzheimer's disease (AD). In AD of autosomal dominant inheritance, the majority of pathogenic mutations have been found in the PSEN1 gene within which the location of the mutation can provide clues as to the mechanism of pathogenesis. OBJECTIVE: To describe clinical features of two novel mutations in the transmembrane portion 1 (TMD-1) of PSEN1 as well as biochemical features in one and neuropathological findings in the other. METHODS: Two index patients with young onset AD with an autosomal dominant pattern of inheritance underwent clinical and imaging assessments, as well as PSEN1 sequencing. Postmortem examination was completed in one patient. An artificial construct in which the P88L mutation was introduced was created to examine its effects on γ-secretase cleavage. RESULTS: Two novel variants in TMD-1 (P88L and V89L) were identified in affected probands. The neuropathological findings of AD were confirmed in the V89L mutation. Both patients presented around age 40 with early short-term memory deficits followed by seizures and corticospinal tract signs. The P88L mutation additionally featured early myoclonus followed by Parkinsonism. The causal role of the P88L mutation is supported by demonstration that this mutation dramatically increased Aβ42 and decreased APP and Notch intracellular domain production in vitro. CONCLUSION: Changes in a single amino acid in codons 88 and 89 of TMD-1 can result in young-onset AD. The TMD-1 of PS1 is a region important for the γ-secretase cleavage of Aβ.

Upregulated Expression of Heparanase and Heparanase 2 in the Brains of Alzheimer's Disease. - Garcia, Beatriz; Martin, Carla; Garcia-Suarez, Olivia; Muniz-Alonso, Barbara; Ordiales, Helena; Fernandez-Menendez, Santiago; Santos-Juanes, Jorge; Lorente-Gea, Laura; Castanon, Sonia; Vicente-Etxenausia, Ikerne; Pina Batista, Kelvin Manuel; Ruiz-Diaz, Irune; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Heparan sulfate proteoglycans (HSPGs) promote amyloid-β peptide and tau fibrillization in Alzheimer's disease (AD) and provide resistance against proteolytic breakdown. Heparanase (HPSE) is the only enzyme that cleaves heparan sulfate (HS). Heparanase 2 (HPSE2) lacks HS-degrading activity, although it is able to interact with HS with high affinity. OBJECTIVE: To analyze HPSE and HPSE2 expressions at different stages of AD. METHODS: RT-PCR was used to analyze transcription levels of both heparanases at different stages of AD, and immunohistochemistry was performed to localize each one in different parts of the brain. RESULTS: Both proteins appeared overexpressed at different stages of AD. Immunohistochemistry indicated that the presence of the heparanases was related to AD pathology, with intracellular deposits found in degenerated neurons. At the extracellular level, HPSE was observed only in neuritic plaques with a fragmented core, while HPSE2 appeared in those with compact cores as well. CONCLUSION: Given the involvement of HSPGs in AD pathology, there would seem to be a relationship between the regulation of heparanase expression, the features of the disease, and a possible therapeutic alternative.

Validation of a Latent Construct for Dementia in a Population-Wide Dataset from Singapore. - Peh, Chao Xu; Abdin, Edimansyah; Vaingankar, Janhavi A; Verma, Swapna; Chua, Boon Yiang; Sagayadevan, Vathsala; Seow, Esmond; Zhang, YunJue; Shahwan, Shazana; Ng, Li Ling; Prince, Martin; Chong, Siow Ann; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The latent variable δ has been proposed as a proxy for dementia. Previous validation studies have been conducted using convenience samples. It is currently unknown how δ performs in population-wide data. OBJECTIVE: To validate δ in Singapore using population-wide epidemiological study data on persons aged 60 and above. METHODS: δ was constructed using items from the Community Screening Instrument for Dementia (CSI'D) and World Health Organization Disability Assessment Schedule (WHODAS II). Confirmatory factor analysis (CFA) was conducted to examine δ model fit. Convergent validity was examined with the Clinical Dementia Rating scale (CDR) and GMS-AGECAT dementia. Divergent validity was examined with GMS-AGECAT depression. RESULTS: The δ model demonstrated fit to the data, χ2(df) = 249.71(55), p < 0.001, CFI = 0.990, TLI = 0.997, RMSEA = 0.037. Latent variable δ was significantly associated with CDR and GMS-AGECAT dementia (range: β= 0.32 to 0.63), and was not associated with GMS-AGECAT depression. Compared to unadjusted models, δ model fit was poor when adjusted for age, gender, ethnicity, and education. CONCLUSION: The study found some support for δ as a proxy for dementia in Singapore based on population data. Both convergent and divergent validity were established. In addition, the δ model structure appeared to be influenced by age, gender, ethnicity, and education covariates.

Validation of the Spanish Version of the LASSI-L for Diagnosing Mild Cognitive Impairment and Alzheimer's Disease. - Matías-Guiu, Jordi A; Curiel, Rosie E; Rognoni, Teresa; Valles-Salgado, María; Fernández-Matarrubia, Marta; Hariramani, Roshan; Fernández-Castro, Alejandro; Moreno-Ramos, Teresa; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: The Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L) is a novel cognitive test that measures recovery from proactive semantic interference, which may be an early cognitive marker of Alzheimer's disease (AD). OBJECTIVE: To generate normative data for a Spaniard population and to validate the LASSI-L for the diagnosis of amnestic mild cognitive impairment (aMCI) and mild AD. METHODS: We performed a cross-sectional study in which 97 healthy participants, 34 with aMCI, and 33 with mild AD were studied with LASSI-L and a comprehensive neuropsychological protocol. The overlapping strategy analysis was used to maximize the sample size and to provide age- and education-adjusted normative data using a logistic regression analysis. RESULTS: Internal consistency was 0.932. Convergent validity with the Free and Cued Selective Reminding Test was moderate. LASSI-L raw scores were correlated with age and years of education, but not gender. The area under the curve for discriminating between healthy controls and aMCI was 0.909, and between healthy controls and mild AD was 0.986. LASSI-L sub-scores representing maximum storage capacity, recovery from proactive interference, and delayed recall yielded the highest diagnostic accuracy. CONCLUSIONS: The LASSI-L is a reliable and valid test for the diagnosis of aMCI and mild AD. The age and education influences on the performance of the test and normative data are provided. LASSI-L merits further studies to evaluate its ability to detect preclinical AD and predict progression to aMCI and early dementia.

Visuospatial Functioning in Cerebral Amyloid Angiopathy: A Pilot Study. - Valenti, Raffaella; Charidimou, Andreas; Xiong, Li; Boulouis, Gregoire; Fotiadis, Panagiotis; Ayres, Alison; Riley, Grace; Kuijf, Hugo J; Reijmer, Yael D; Pantoni, Leonardo; Gurol, M Edip; Davidsdottir, Sigurros; et al. (J Alzheimers Dis, 2017)
Cerebral amyloid angiopathy (CAA) is a contributor to cognitive impairment in the elderly. We hypothesized that the posterior cortical predilection of CAA would cause visual-processing impairment. We systematically evaluated visuospatial abilities in 22 non-demented CAA patients. Neurocognitive evaluation demonstrated visuoperceptual impairment (23% on Benton Facial Recognition Test [BFRT] and 13.6% on Benton Judgment of Line Orientation Test [BJLO]). BFRT was inversely correlated with white matter hyperintensities volume and BJLO with parietal cerebral microbleeds. This pilot study highlights the presence of visual-processing deficits in CAA. The impairment could be related to global disease severity in addition to local brain injury.

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

White Matter Hyperintensities Potentiate Hippocampal Volume Reduction in Non-Demented Older Individuals with Abnormal Amyloid-β. - Freeze, Whitney M; Jacobs, Heidi I L; Gronenschild, Ed H; Jansen, Jacobus F A; Burgmans, Saartje; Aalten, Pauline; Clerx, Lies; Vos, Stephanie J; van Buchem, Mark A; Barkhof, Frederik; van der Flier, Wiesje M; Verbeek, Marcel M; et al. (J Alzheimers Dis, 2017)
Cerebral small vessel disease (cSVD) and amyloid-β (Aβ) deposition often co-exist in (prodromal) dementia, and both types of pathology have been associated with neurodegeneration. We examined whether cSVD and Aβ have independent or interactive effects on hippocampal volume (HV) in a memory clinic population. We included 87 individuals with clinical diagnoses of Alzheimer's disease (AD) (n = 24), mild cognitive impairment (MCI) (n = 26), and subjective cognitive complaints (SCC) (n = 37). cSVD magnetic resonance imaging markers included white matter hyperintensity (WMH) volume, lacunar infarct presence, and microbleed presence. Aβ pathology was assessed as cerebrospinal fluid-derived Aβ1 - 42 levels and dichotomized into normal or abnormal, and HV was determined by manual volumetric measurements. A linear hierarchical regression approach was applied for the detection of additive or interaction effects between cSVD and Aβ on HV in the total participant group (n = 87) and in the non-demented group (including SCC and MCI individuals only, n = 63). The results revealed that abnormal Aβ and lacunar infarct presence were independently associated with lower HV in the non-demented individuals. Interestingly, Aβ and WMH pathology interacted in the non-demented individuals, such that WMH had a negative effect on HV in individuals with abnormal CSF Aβ42 levels, but not in individuals with normal CSF Aβ42 levels. These associations were not present when individuals with AD were included in the analyses. Our observations suggest that relatively early on in the disease process older individuals with abnormal Aβ levels are at an increased risk of accelerated disease progression when concomitant cSVD is present.

Young to Middle-Aged Dogs with High Amyloid-β Levels in Cerebrospinal Fluid are Impaired on Learning in Standard Cognition tests. - Borghys, Herman; Van Broeck, Bianca; Dhuyvetter, Deborah; Jacobs, Tom; de Waepenaert, Katja; Erkens, Tim; Brooks, Melissa; Thevarkunnel, Sandy; Araujo, Joseph A (J Alzheimers Dis, 2017)
Understanding differences in Alzheimer's disease biomarkers before the pathology becomes evident can contribute to an improved understanding of disease pathogenesis and treatment. A decrease in amyloid-β (Aβ)42 in cerebrospinal fluid (CSF) is suggested to be a biomarker for Aβ deposition in brain. However, the relevance of CSF Aβ levels prior to deposition is not entirely known. Dogs are similar to man with respect to amyloid-β protein precursor (AβPP)-processing, age-related amyloid plaque deposition, and cognitive dysfunction. In the current study, we evaluated the relation between CSF Aβ42 levels and cognitive performance in young to middle-aged dogs (1.5-7 years old). Additionally, CSF sAβPPα and sAβPPβ were measured to evaluate AβPP processing, and CSF cytokines were measured to determine the immune status of the brain. We identified two groups of dogs showing consistently low or high CSF Aβ42 levels. Based on prior studies, it was assumed that at this age no cerebral amyloid plaques were likely to be present. The cognitive performance was evaluated in standard cognition tests. Low or high Aβ concentrations coincided with low or high sAβPPα, sAβPPβ, and CXCL-1 levels, respectively. Dogs with high Aβ concentrations showed significant learning impairments on delayed non-match to position (DNMP), object discrimination, and reversal learning compared to dogs with low Aβ concentrations. Our data support the hypothesis that high levels of CSF Aβ in dogs coincide with lower cognitive performance prior to amyloid deposition. Further experiments are needed to investigate this link, as well as the relevance with respect to Alzheimer's disease pathology progression.

Added Prognostic Value of Cerebrospinal Fluid Biomarkers in Predicting Decline in Memory Clinic Patients in a Prospective Cohort. - Handels, Ron L H; Joore, Manuela A; Vos, Stephanie J B; Aalten, Pauline; Ramakers, Inez H G B; Rikkert, Marcel Olde; Scheltens, Philip; Jansen, Willemijn J; Visser, Pieter-Jelle; van Berckel, Bart M N; van Domburg, Peter; Smid, Machiel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Limited information is available on short-term prognosis of Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF) in addition to routine diagnostic workup. OBJECTIVE: This study aims to investigate the added prognostic value of AD CSF biomarkers. METHODS: In a prospective cohort study, clinical experts predicted cognitive and functional symptoms in 114 memory clinic patients by assessing comprehensive routine diagnostic test information (patient history, and physical, neurological, psychiatric, neuropsychological, and MRI examinations), without and with CSF biomarkers. The reference standard was the 'observed clinically relevant decline' using baseline and 1- and 2-year follow-up information. RESULTS: Decline over a 2-year period was observed in 51% of all participants (3% in SMC, 48% in MCI, 90% in mild dementia). In the total sample, the accuracy of predicted decline did not differ significantly between routine assessment without (79% correctly predicted) and with (74% correctly predicted) CSF biomarkers. Subgroup analyses revealed 25 (83%) correct predictions in SMC, 30 (68%) in MCI, and 35 (88%) in dementia without the use of CSF; and 21 (70%), 27 (61%), and 36 (90%), respectively, with the use of CSF in addition to the routine assessment. CONCLUSION: AD CSF biomarkers did not increase accuracy of 2-year prognosis of cognitive and functional decline when added to routine diagnostic workup. This suggests that the standard diagnostic workup without CSF biomarkers allows fairly accurate predictions for the short-term course of symptoms. Routine AD biomarkers in CSF have limited prognostic value over 2 years in persons with a suspected cognitive disorder.

Aging Enables Ca2+ Overload and Apoptosis Induced by Amyloid-β Oligomers in Rat Hippocampal Neurons: Neuroprotection by Non-Steroidal Anti-Inflammatory Drugs and R-Flurbiprofen in Aging Neurons. - Calvo-Rodríguez, María; García-Durillo, Mónica; Villalobos, Carlos; Núñez, Lucía (J Alzheimers Dis, 2016)
The most important risk factor for Alzheimer's disease (AD) is aging. Neurotoxicity in AD has been linked to dyshomeostasis of intracellular Ca2+ induced by small aggregates of the amyloid-β peptide 1-42 (Aβ42 oligomers). However, how aging influences susceptibility to neurotoxicity induced by Aβ42 oligomers is unknown. In this study, we used long-term cultures of rat hippocampal neurons, a model of neuronal in vitro aging, to investigate the contribution of aging to Ca2+ dishomeostasis and neuron cell death induced by Aβ42 oligomers. In addition, we tested whether non-steroidal anti-inflammatory drugs (NSAIDs) and R-flurbiprofen prevent apoptosis acting on subcellular Ca2+ in aged neurons. We found that Aβ42 oligomers have no effect on young hippocampal neurons cultured for 2 days in vitro (2 DIV). However, they promoted apoptosis modestly in mature neurons (8 DIV) and these effects increased dramatically after 13 DIV, when neurons display many hallmarks of in vivo aging. Consistently, cytosolic and mitochondrial Ca2+ responses induced by Aβ42 oligomers increased dramatically with culture age. At low concentrations, NSAIDs and the enantiomer R-flurbiprofen lacking anti-inflammatory activity prevent Ca2+ overload and neuron cell death induced by Aβ42 oligomers in aged neurons. However, at high concentrations R-flurbiprofen induces apoptosis. Thus, Aβ42 oligomers promote Ca2+ overload and neuron cell death only in aged rat hippocampal neurons. These effects are prevented by low concentrations of NSAIDs and R-flurbiprofen acting on mitochondrial Ca2+ overload.

Altered Energy Metabolism Pathways in the Posterior Cingulate in Young Adult Apolipoprotein E ɛ4 Carriers. - Perkins, Michelle; Wolf, Andrew B; Chavira, Bernardo; Shonebarger, Daniel; Meckel, J P; Leung, Lana; Ballina, Lauren; Ly, Sarah; Saini, Aman; Jones, T Bucky; Vallejo, Johana; Jentarra, Garilyn; et al. (J Alzheimers Dis, 2016)
The APOE gene, encoding apolipoprotein E, is the primary genetic risk factor for late-onset Alzheimer's disease (AD). Apolipoprotein E ɛ4 allele (APOE4) carriers have alterations in brain structure and function (as measured by brain imaging) even as young adults. Examination of this population is valuable in further identifying details of these functional changes and their association with vulnerability to AD decades later. Previous work demonstrates functional declines in mitochondrial activity in the posterior cingulate cortex, a key region in the default mode network, which appears to be strongly associated with functional changes relevant to AD risk. Here, we demonstrate alterations in the pathways underlying glucose, ketone, and mitochondrial energy metabolism. Young adult APOE4 carriers displayed upregulation of specific glucose (GLUT1 & GLUT3) and monocarboxylate (MCT2) transporters, the glucose metabolism enzyme hexokinase, the SCOT & AACS enzymes involved in ketone metabolism, and complexes I, II, and IV of the mitochondrial electron transport chain. The monocarboxylate transporter (MCT4) was found to be downregulated in APOE4 carriers. These data suggest that widespread dysregulation of energy metabolism in this at-risk population, even decades before possible disease onset. Therefore, these findings support the idea that alterations in brain energy metabolism may contribute significantly to the risk that APOE4 confers for AD.

Analysis of Cerebrospinal Fluid and [11C]PIB PET Biomarkers for Alzheimer's Disease with Updated Protocols. - Wang, Min Jeong; Yi, SangHak; Han, Jee-Young; Park, So Young; Jang, Jae-Won; Chun, In Kook; Giau, Vo Van; Bagyinszky, Eva; Lim, Kun Taek; Kang, Sung Min; An, Seong Soo A; Park, Young Ho; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recently, a Korean research group suggested a consensus protocol, based on the Alzheimer's Disease Neuroimaging Initiative study protocol but with modifications for minimizing the confounding factors, for the evaluation of cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: Here, we analyzed fluid and imaging biomarkers of Alzheimer's disease (AD) in Korean population. We used the updated protocol to propose a more accurate CSF biomarker value for the diagnosis of AD. METHODS: Twenty-seven patients with AD and 30 cognitively normal controls (NC) were enrolled. CSF was collected from 55 subjects (patients with AD = 26, NC = 29) following the Korea consensus protocol. CSF biomarkers were measured using the INNO-BIA AlzBio3 immunoassay, and Pittsburgh compound B (PIB) positron emission tomography (PET) scans were also performed. RESULTS: The cutoff values of CSF amyloid beta 1-42 (Aβ42), total tau (t-Tau), and phosphorylated tau (p-Tau) proteins were 357.1 pg/ml, 83.35 pg/ml, and 38.00 pg/ml, respectively. The cutoff values of CSF t-Tau/Aβ42 and p-Tau/Aβ42 ratio- were 0.210 (sensitivity 100%, specificity 86.21%) and 0.1350 (sensitivity 88.46%, specificity of 92.86%). The concordance rate with PIB-PET was higher using the CSF t-Tau/Aβ42 ratio (κ= 0.849, CI 0.71-0.99) than CSF Aβ42 alone (κ= 0.703, CI 0.51-0.89). CONCLUSIONS: Here, we improved controversial factors associated with the previous CSF study protocol and suggested a new cutoff value for the diagnosis of AD. Our results showed good diagnostic performance for differentiation of AD. Thus, we expect our findings could be a cornerstone in the establishment and clinical application of biomarkers for AD diagnosis.

Apolipoprotein ɛ4 is Associated with Dementia and Cognitive Impairment Predominantly Due to Alzheimer's Disease and Not with Vascular Cognitive Impairment: A Singapore-Based Cohort. - Chai, Yuek Ling; Yeo, Hazel Kai-Hui; Wang, Jiehao; Hilal, Saima; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Wong, Boon-Seng; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: While the association for apolipoprotein ɛ4 allele (APOE4) with Alzheimer's disease (AD) has been consistently confirmed, the association with vascular cognitive impairment (VCI) is unclear. We therefore explored the relationship of APOE with both AD and cerebrovascular disease (CeVD) by examining the prevalence of APOE4 in AD, AD with CeVD and vascular dementia (VaD), as well as in cognitive impairment no dementia (CIND) with and without CeVD. METHODS: We performed a case-control study with subjects recruited from memory clinics and the community. All subjects underwent standardized brain neuroimaging, clinical and neuropsychological assessments, following which they were classified using research criteria. RESULTS: A total of 411 subjects; 92 controls with no cognitive impairment (NCI), 77 CIND without CeVD, 87 CIND with CeVD, 55 AD without CeVD, 68 AD with CeVD, and 32 VaD patients were recruited. Compared to NCI (16.3%), the prevalence of APOE4 carriers was significantly higher only in CIND (37.7%) and AD in the absence of CeVD (45.5%), but not in the three subgroups of VCI, namely CIND with CeVD (20.7%), AD with CeVD (27.9%) and VaD (25.0%). Logistic regression analyses also showed that APOE4 carriers were more likely to have CIND without CeVD (Odds Ratio [OR]: 3.34; 95% Confidence Interval [CI]: 1.59-7.03) and AD without CeVD (OR: 7.21; 95% CI: 2.74-18.98), but no such association was observed in the VCI subgroups. CONCLUSION: APOE4 is significantly associated with dementia and CIND due to AD pathology, but not with VCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apolipoprotein E4; Cognition Disorders; Cohort Studies; Dementia; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Psychiatric Status Rating Scales; Singapore; Vascular Diseases

Association Between Serum Ceruloplasmin Specific Activity and Risk of Alzheimer's Disease. - Siotto, Mariacristina; Simonelli, Ilaria; Pasqualetti, Patrizio; Mariani, Stefania; Caprara, Deborah; Bucossi, Serena; Ventriglia, Mariacarla; Molinario, Rossana; Antenucci, Mirca; Rongioletti, Mauro; Rossini, Paolo Maria; Squitti, Rosanna (J Alzheimers Dis, 2016)
Meta-analyses demonstrate copper involvement in Alzheimer's disease (AD), and the systemic ceruloplasmin status in relation to copper is an emerging issue. To deepen this matter, we evaluated levels of ceruloplasmin concentration, ceruloplasmin activity, ceruloplasmin specific activity (eCp/iCp), copper, non-ceruloplasmin copper iron, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype in a sample of 84 AD patients and 58 healthy volunteers. From the univariate logistic analyses we found that ceruloplasmin concentration, eCp/iCp, copper, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype were significantly associated with the probability of AD. In the multivariable logistic regression analysis, we selected the best subset of biological predictors by the forward stepwise procedure. The analysis showed a decrease of the risk of having AD for eCp/iCp (p = 0.001) and an increase of this risk for non-ceruloplasmin copper (p = 0.008), age (p = 0.001), and APOE-ɛ4 allele (p <  0.001). The estimated model showed a good power in discriminating AD patients from healthy controls (area under curve: 88% ; sensitivity: 66% ; specificity 93%). These data strength the breakdown of copper homeostasis and propose eCp/iCp as a reliable marker of ceruloplasmin status.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Area Under Curve; Biomarkers; Blood Chemical Analysis; Ceruloplasmin; Copper; Female; Genotype; Genotyping Techniques; Humans; Logistic Models; Male; Multivariate Analysis; Prognosis; Risk; ROC Curve; Sensitivity and Specificity; Transferrin

Association of Butyrylcholinesterase-K Allele and Apolipoprotein E ɛ4 Allele with Cognitive Decline in Dementia with Lewy Bodies and Alzheimer's Disease. - Vijayaraghavan, Swetha; Darreh-Shori, Taher; Rongve, Arvid; Berge, Guro; Sando, Sigrid B; White, Linda R; Auestad, Bjørn H; Witoelar, Aree; Andreassen, Ole A; Ulstein, Ingun D; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: A common polymorphism of the butyrylcholinesterase gene, the K-variant (BCHE-K) is associated with reduced butyrylcholinesterase (BuChE) activity. Insufficient studies exist regarding the frequency and role of BCHE-K in dementias. OBJECTIVE: To determine the association of BCHE-K and APOEɛ4 with diagnosis and rate of cognitive decline in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. METHODS: Genomic DNA from 368 subjects (108 AD, 174 DLB, and 86 controls) from two routine clinical cohort studies in Norway; DemVest and TrønderBrain, were genotyped for BCHE-K and APOEɛ4. The mild dementia DemVest subjects received annual Mini-Mental State Examination assessments for five years. RESULTS: BCHE-K frequency was lower in DLB (33.9% ; p <  0.01) than in control subjects (51.2%), and was numerically lower in AD as well (38.9% ; p = 0.11). More rapid cognitive decline was associated with the APOEɛ4 genotype, but not with the BCHE-K genotype. In an exploratory analysis of patients who completed all five follow-up visits, there was greater cognitive decline in BCHE-K carriers in the presence of the APOEɛ4 allele than in the absence of these polymorphisms. CONCLUSION: BCHE-K is associated with a reduced risk for AD and DLB whereas APOEɛ4 is associated with more rapid cognitive decline. The greater cognitive decline in individuals with both APOEɛ4 and BCHE-K alleles require prospective confirmation in well-controlled trials.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Butyrylcholinesterase; Cognition; Disease Progression; Female; Gene Frequency; Genotype; Humans; Lewy Body Disease; Male; Neuropsychological Tests

Association of Coffee Consumption with MRI Markers and Cognitive Function: A Population-Based Study. - Araújo, Larissa Fortunato; Mirza, Saira Saeed; Bos, Daniel; Niessen, Wiro J; Barreto, Sandhi Maria; van der Lugt, Aad; Vernooij, Meike W; Hofman, Albert; Tiemeier, Henning; Ikram, M Arfan (J Alzheimers Dis, 2016)
BACKGROUND: Coffee is one of the most widely consumed beverages worldwide and has been of considerable interest in research on cognition and dementia. OBJECTIVE: To investigate the effect of coffee on preclinical brain MRI markers of dementia and cognitive performance. METHODS: In 2,914 participants from the population-based Rotterdam Study (mean age: 59.3±7.2 years, 55% females), we assessed coffee consumption, performed brain MRI, and assessed cognition at baseline. To study cognitive change, cognitive assessment was repeated after 5 years of follow-up. Coffee consumption was analyzed continuously (per cup increase) and in categories (0-1, >1-3, >3 cups/day). Using logistic and linear regression, associations of coffee consumption with lacunar infarcts and brain tissue volumes on MRI, and cognitive performance (cross-sectional and longitudinal) were investigated, adjusting for relevant confounders. RESULTS: We found that higher coffee consumption was associated with a lower prevalence of lacunar infarcts [odds ratio per cup increase: 0.88 (95% CI:0.79;0.98)], and smaller hippocampal volume [difference: -0.01 (95% CI:-0.02;0.00)]. Also, we found that the highest category of coffee consumption was associated with better performance on the Letter Digit Substitution Task [difference: 1.13(95% CI:0.39;1.88)], Word Fluency test [0.74(95% CI:0.04,1.45)], Stroop interference task [1.82(95% CI:0.23;3.41)], and worse performance on the 15-Word Learning test delayed recall [-0.38(95% CI:-0.74;-0.02)]. These associations were not found when cognition was analyzed longitudinally. CONCLUSION: We found complex associations between coffee consumption, brain structure, and cognition. Higher coffee consumption was cross-sectionally associated with a lower occurrence of lacunar infarcts and better executive function, but also with smaller hippocampal volume and worse memory function.

Association of Plasma Aβ40 Peptides, But Not Aβ42, with Coronary Artery Disease and Diabetes Mellitus. - Roeben, Benjamin; Maetzler, Walter; Vanmechelen, Eugeen; Schulte, Claudia; Heinzel, Sebastian; Stellos, Konstantinos; Godau, Jana; Huber, Heiko; Brockmann, Kathrin; Wurster, Isabel; Gaenslen, Alexandra; Grüner, Eva; et al. (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: Plasma levels of amyloid-beta (Aβ) 1-40 peptide have been proposed to be associated with cardiovascular mortality in patients with coronary artery disease (CAD). Therefore, we aimed to investigate the association of plasma Aβ levels with CAD, cardiovascular risk factors (CVRF), and APOE genotype in non-demented elderly individuals. METHODS: Plasma Aβ1 - 40 and Aβ1 - 42 levels of 526 individuals (mean age of 63.0±7.3 years) were quantified with the INNO-BIA plasma Aβ forms assay based on multiplextrademark technique. APOE genotype was determined with an established protocol. Presence of CAD and CVRFs were ascertained using a questionnaire and/or medical records. RESULTS: Plasma Aβ1 - 40 levels were significantly higher in individuals with CAD (p = 0.043) and, independently, in individuals with diabetes mellitus (DM) type 2 (p = 0.001) while accounting for age- and gender-effects. Plasma Aβ1 - 42 levels were higher in APOEɛ4 carriers (p = 0.004), but were neither relevantly associated with CAD nor with any CVRF. Plasma Aβ1 - 40 showed no association with APOE genotype. DISCUSSION: Our findings argue for an association of circulating plasma Aβ1 - 40 peptides with incident CAD and DM. Further investigations are needed to entangle the role of Aβ1 - 40 role in the pathophysiology of cardiovascular disease independent of its known role in Alzheimer's disease.

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Blockade of the Interaction of Calcineurin with FOXO in Astrocytes Protects Against Amyloid-β-Induced Neuronal Death. - Fernandez, Ana M; Hervas, Ruben; Dominguez-Fraile, Manuel; Garrido, Victoria Navarro; Gomez-Gutierrez, Patricia; Vega, Miguel; Vitorica, Javier; Perez, Juan J; Torres Aleman, Ignacio (J Alzheimers Dis, 2016)
Astrocytes actively participate in neuro-inflammatory processes associated to Alzheimer's disease (AD), and other brain pathologies. We recently showed that an astrocyte-specific intracellular signaling pathway involving an interaction of the phosphatase calcineurin with the transcription factor FOXO3 is a major driver in AD-associated pathological inflammation, suggesting a potential new druggable target for this devastating disease. We have now developed decoy molecules to interfere with calcineurin/FOXO3 interactions, and tested them in astrocytes and neuronal co-cultures exposed to amyloid-β (Aβ) toxicity. We observed that interference of calcineurin/FOXO3 interactions exerts a protective action against Aβ-induced neuronal death and favors the production of a set of growth factors that we hypothesize form part of a cytoprotective pathway to resolve inflammation. Furthermore, interference of the Aβ-induced interaction of calcineurin with FOXO3 by decoy compounds significantly decreased amyloid-β protein precursor (AβPP) synthesis, reduced the AβPP amyloidogenic pathway, resulting in lower Aβ levels, and blocked the expression of pro-inflammatory cytokines TNFα and IL-6 in astrocytes. Collectively, these data indicate that interrupting pro-inflammatory calcineurin/FOXO3 interactions in astrocytes triggered by Aβ accumulation in brain may constitute an effective new therapeutic approach in AD. Future studies with intranasal delivery, or brain barrier permeable decoy compounds, are warranted.

Brain Serotonergic and Noradrenergic Deficiencies in Behavioral Variant Frontotemporal Dementia Compared to Early-Onset Alzheimer's Disease. - Vermeiren, Yannick; Janssens, Jana; Aerts, Tony; Martin, Jean-Jacques; Sieben, Anne; Van Dam, Debby; De Deyn, Peter P (J Alzheimers Dis, 2016)
Routinely prescribed psychoactive drugs in behavioral variant frontotemporal dementia (FTD) for improvement of (non)cognitive symptoms are primarily based on monoamine replacement or augmentation strategies. These were, however, initially intended to symptomatically treat other degenerative, behavioral, or personality disorders, and thus lack disease specificity. Moreover, current knowledge on brain monoaminergic neurotransmitter deficiencies in this presenile disorder is scarce, particularly with reference to changes in Alzheimer's disease (AD). The latter hence favors neurochemical comparison studies in order to elucidate the monoaminergic underpinnings of FTD compared to early-onset AD, which may contribute to better pharmacotherapy. Therefore, frozen brain samples, i.e., Brodmann area (BA) 6/8/9/10/11/12/22/24/46, amygdala, and hippocampus, of 10 neuropathologically confirmed FTD, AD, and control subjects were analyzed by means of reversed-phase high-performance liquid chromatography. Levels of serotonergic, dopaminergic, and noradrenergic compounds were measured. In nine brain areas, serotonin (5-HT) concentrations were significantly increased in FTD compared to AD patients, while 5-hydroxyindoleacetic acid/5-HT ratios were decreased in eight regions, also compared to controls. Furthermore, in all regions, noradrenaline (NA) levels were significantly higher, and 3-methoxy-4-hydroxyphenylglycol/NA ratios were significantly lower in FTD than in AD and controls. Contrarily, significantly higher dopamine (DA) levels and reduced homovanillic acid/DA ratios were only found in BA12 and BA46. Results indicate that FTD is defined by distinct serotonergic and noradrenergic deficiencies. Additional research regarding the interactions between both monoaminergic networks is required. Similarly, clinical trials investigating the effects of 5-HT1A receptor antagonists or NA-modulating agents, such as α1/2/β1-blockers, seem to have a rationale and should be considered.

Cerebral Glucose Metabolism is Associated with Verbal but not Visual Memory Performance in Community-Dwelling Older Adults. - Gardener, Samantha L; Sohrabi, Hamid R; Shen, Kai-Kai; Rainey-Smith, Stephanie R; Weinborn, Michael; Bates, Kristyn A; Shah, Tejal; Foster, Jonathan K; Lenzo, Nat; Salvado, Olivier; Laske, Christoph; Laws, Simon M; et al. (J Alzheimers Dis, 2016)
Increasing evidence suggests that Alzheimer's disease (AD) sufferers show region-specific reductions in cerebral glucose metabolism, as measured by [18F]-fluoro-2-deoxyglucose positron emission tomography (18F-FDG PET). We investigated preclinical disease stage by cross-sectionally examining the association between global cognition, verbal and visual memory, and 18F-FDG PET standardized uptake value ratio (SUVR) in 43 healthy control individuals, subsequently focusing on differences between subjective memory complainers and non-memory complainers. The 18F-FDG PET regions of interest investigated include the hippocampus, amygdala, posterior cingulate, superior parietal, entorhinal cortices, frontal cortex, temporal cortex, and inferior parietal region. In the cohort as a whole, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in both the left hippocampus and right amygdala. There were no associations observed between global cognition, delayed recall in logical memory, or visual reproduction and 18F-FDG PET SUVR. Following stratification of the cohort into subjective memory complainers and non-complainers, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in the right amygdala in those with subjective memory complaints. There were no significant associations observed in non-memory complainers between 18F-FDG PET SUVR in regions of interest and cognitive performance. We observed subjective memory complaint-specific associations between 18F-FDG PET SUVR and immediate verbal memory performance in our cohort, however found no associations between delayed recall of verbal memory performance or visual memory performance. It is here argued that the neural mechanisms underlying verbal and visual memory performance may in fact differ in their pathways, and the characteristic reduction of 18F-FDG PET SUVR observed in this and previous studies likely reflects the pathophysiological changes in specific brain regions that occur in preclinical AD.

Cerebral Microbleeds and Cerebrovascular Reactivity in the General Population: The EDAN Study. - Akoudad, Saloua; Gurol, M Edip; Fotiadis, Panagiotis; Koudstaal, Peter J; Hofman, Albert; Ikram, M Arfan; Greenberg, Steven M; Vernooij, Meike W (J Alzheimers Dis, 2016)
BACKGROUND: In patients with symptomatic cerebral amyloid angiopathy (CAA), cerebrovascular reactivity to visual stimuli is reduced. Lobar microbleeds are a diagnostic hallmark of CAA, but are also highly prevalent in asymptomatic individuals. Recent data suggest that the latter group might have CAA. OBJECTIVE: We investigated whether cerebrovascular reactivity is impaired in asymptomatic individuals with lobar microbleeds. METHODS: From the population-based Rotterdam Study, we invited 35 participants with lobar microbleeds and 15 age-matched controls (all≥55 years) for functional MRI (fMRI) as part of the Early Detection of Angiopathy Network (EDAN) Study. Cerebrovascular reactivity parameters (i.e., amplitude and time to peak responses) were assessed in response to visual stimulation using fMRI. Student's t-test and linear regression were used to compare fMRI parameters in participants with and without microbleeds. RESULTS: Amplitude and time to peak responses did not differ between participants with and without microbleeds (respectively, p = 0.179 and p = 0.555). Participants with microbleeds had slightly higher amplitude responses compared to participants without microbleeds. After excluding individuals with mixed microbleeds (i.e., lobar and non-lobar microbleeds), we found no significant difference in cerebrovascular reactivity for persons with a single microbleed or multiple microbleeds compared to persons without microbleeds. CONCLUSIONS: In the general population, lobar microbleeds may not relate to impaired cerebrovascular reactivity. In asymptomatic individuals, lobar microbleeds may either reflect less advanced CAA pathology insufficient to cause functional vascular impairment, or reflect vascular pathology other than CAA.

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study. - Wang, Nan; Allali, Gilles; Kesavadas, Chandrasekharan; Noone, Mohan L; Pradeep, Vayyattu G; Blumen, Helena M; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. OBJECTIVE: We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. METHODS: 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence of cerebral small vessel disease (lacunar infarcts and cerebral microbleeds (CMB)) and white matter hyperintensities on MRI was ascertained by raters blinded to clinical information. MCR was defined by the presence of cognitive complaints and slow gait in older adults without dementia or mobility disability. RESULTS: Thirty-eight (27.3%) participants met MCR criteria. The overall prevalence of lacunar infarcts and CMB was 49.6% and 9.4% , respectively. Lacunar infarcts in the frontal lobe, but no other brain regions, were associated with MCR even after adjusting for vascular risk factors and presence of white matter hyperintensities (adjusted Odds Ratio (aOR): 4.67, 95% CI: 1.69-12.94). Frontal lacunar infarcts were associated with slow gait (aOR: 3.98, 95% CI: 1.46-10.79) and poor performance on memory test (β: -1.24, 95% CI: -2.42 to -0.05), but not with cognitive complaints or non-memory tests. No association of CMB was found with MCR, individual MCR criterion or cognitive tests. CONCLUSIONS: Frontal lacunar infarcts are associated with MCR in Indian seniors, perhaps, by contributing to slow gait and poor memory function.
Keywords: Aged; Brain; Cerebral Small Vessel Diseases; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; India; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Risk Factors; Stroke, Lacunar; White Matter

Cerebrospinal Fluid Alzheimer's Disease Biomarkers Across the Spectrum of Lewy Body Diseases: Results from a Large Multicenter Cohort. - van Steenoven, Inger; Aarsland, Dag; Weintraub, Daniel; Londos, Elisabet; Blanc, Frédéric; van der Flier, Wiesje M; Teunissen, Charlotte E; Mollenhauer, Brit; Fladby, Tormod; Kramberger, Milica G; Bonanni, Laura; Lemstra, Afina W (J Alzheimers Dis, 2016)
BACKGROUND: Concomitant Alzheimer's disease (AD) pathology is observed in Lewy body diseases (LBD), but the clinical impact is unknown. Only a few biomarker studies in LBD exist and have included small cohorts from single centers. OBJECTIVE: We aimed to evaluate the prevalence of abnormal cerebrospinal fluid (CSF) AD biomarkers across the spectrum of LBD in a large multicenter cohort and to assess whether an AD biomarker profile was associated with demographic and clinical differences in dementia with Lewy bodies (DLB). METHODS: We included 375 DLB patients, 164 Parkinson's disease (PD) patients without dementia, and 55 PD patients with dementia (PDD) from 10 centers. CSF amyloid-beta42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) values were dichotomized as abnormal or normal according to locally available cut-off values. A CSF AD profile was defined as abnormal Aβ42 combined with abnormal t-tau and/or p-tau. RESULTS: A substantial proportion of DLB patients had abnormal values for CSF Aβ42, t-tau, and p-tau, while abnormal values were uncommon in PD without dementia. Patients with PDD had values in between. A CSF AD profile was observed in 25% of DLB patients, compared with only 9% of PDD and 3% of PD without dementia. Within DLB, patients with a CSF AD profile were older, more often female, performed worse on the Mini-Mental State Examination, and had shorter disease duration compared with patients with normal CSF. CONCLUSION: A CSF AD profile is more common in DLB compared with PDD and PD, and is associated with more severe cognitive impairment in DLB.

The Cerebrospinal Fluid Neurogranin/BACE1 Ratio is a Potential Correlate of Cognitive Decline in Alzheimer's Disease. - De Vos, Ann; Struyfs, Hanne; Jacobs, Dirk; Fransen, Erik; Klewansky, Tom; De Roeck, Ellen; Robberecht, Caroline; Van Broeckhoven, Christine; Duyckaerts, Charles; Engelborghs, Sebastiaan; Vanmechelen, Eugeen (J Alzheimers Dis, 2016)
BACKGROUND: In diagnosing Alzheimer's disease (AD), ratios of cerebrospinal fluid (CSF) biomarkers, such as CSF Aβ1-42/tau, have an improved diagnostic performance compared to the single analytes, yet, still a limited value to predict cognitive decline. Since synaptic dysfunction/loss is closely linked to cognitive impairment, synaptic proteins are investigated as candidate CSF AD progression markers. OBJECTIVE: We studied CSF levels of the postsynaptic protein neurogranin and protein BACE1, predominantly localized presynaptically, and their relation to CSF total-tau, Aβ1-42, Aβ1-40, and Aβ1-38. All six analytes were considered as single parameters as well as ratios. METHODS: Every ELISA involved was based on monoclonal antibodies, including the BACE1 and neurogranin immunoassay. The latter specifically targets neurogranin C-terminally truncated at P75, a more abundant species of the protein in CSF. We studied patients with MCI due to AD (n = 38) and 50 dementia due to AD patients, as well as age-matched cognitively healthy elderly (n = 20). A significant subset of the patients was followed up by clinical and neuropsychological (MMSE) examinations for at least one year. RESULTS: The single analytes showed statistically significant differences between the clinical groups, but the ratios of analytes indeed had a higher diagnostic performance. Furthermore, only the ratio of CSF neurogranin trunc P75/BACE1 was significantly correlated with the yearly decline in MMSE scores in patients with MCI and dementia due to AD, pointing toward the prognostic value of the ratio. CONCLUSION: This is the first study demonstrating that the CSF neurogranin trunc P75/BACE1 ratio, reflecting postsynaptic/presynaptic integrity, is related to cognitive decline.

Changes in Neural Connectivity and Memory Following a Yoga Intervention for Older Adults: A Pilot Study. - Eyre, Harris A; Acevedo, Bianca; Yang, Hongyu; Siddarth, Prabha; Van Dyk, Kathleen; Ercoli, Linda; Leaver, Amber M; Cyr, Natalie St; Narr, Katherine; Baune, Bernhard T; Khalsa, Dharma S; Lavretsky, Helen (J Alzheimers Dis, 2016)
BACKGROUND: No study has explored the effect of yoga on cognitive decline and resting-state functional connectivity. OBJECTIVES: This study explored the relationship between performance on memory tests and resting-state functional connectivity before and after a yoga intervention versus active control for subjects with mild cognitive impairment (MCI). METHODS: Participants ( ≥ 55 y) with MCI were randomized to receive a yoga intervention or active "gold-standard" control (i.e., memory enhancement training (MET)) for 12 weeks. Resting-state functional magnetic resonance imaging was used to map correlations between brain networks and memory performance changes over time. Default mode networks (DMN), language and superior parietal networks were chosen as networks of interest to analyze the association with changes in verbal and visuospatial memory performance. RESULTS: Fourteen yoga and 11 MET participants completed the study. The yoga group demonstrated a statistically significant improvement in depression and visuospatial memory. We observed improved verbal memory performance correlated with increased connectivity between the DMN and frontal medial cortex, pregenual anterior cingulate cortex, right middle frontal cortex, posterior cingulate cortex, and left lateral occipital cortex. Improved verbal memory performance positively correlated with increased connectivity between the language processing network and the left inferior frontal gyrus. Improved visuospatial memory performance correlated inversely with connectivity between the superior parietal network and the medial parietal cortex. CONCLUSION: Yoga may be as effective as MET in improving functional connectivity in relation to verbal memory performance. These findings should be confirmed in larger prospective studies.

Characteristics of Alzheimer's Disease Patients with Severe Executive Disorders. - Godefroy, Olivier; Bakchine, Serge; Verny, Marc; Delabrousse-Mayoux, Jean-Philippe; Roussel, Martine; Pere, Jean-Jacques (J Alzheimers Dis, 2016)
BACKGROUND: Executive dysfunctions in Alzheimer's disease (AD) have been assessed using variable batteries and/or in selected populations. OBJECTIVE: The primary objective of this observational study was to determine the prevalence and severity of executive dysfunction in AD patients using a previously validated battery. The secondary objective was to determine the characteristics including treatment outcomes of AD patients with severe executive dysfunction. METHODS: The study included AD patients with mild-to-moderate dementia aged 60 or over, consulting in various clinical settings including memory clinics and requiring the introduction of an antidementia drug. Executive dysfunction was examined using a validated, shortened executive battery. RESULTS: 381 patients were included. Executive dysfunctions were observed in 88.2% of the patients (95% CI: 84.9-91.4) and were severe (defined as ≥2/3 impaired scores) in 80.4% (95% CI: 76.9-84.8). Global hypoactivity with apathy was more frequent (p = 0.0001) than impairment in executive function tests. The 308 patients with severe executive dysfunction were older (p = 0.003) and had more severe dementia (p = 0.0001). Similarly, in the subset of 257 patients with mild dementia, individuals with severe executive dysfunction were older (p = 0.003) and had more severe dementia. Global hypoactivity was independently associated with difficulties in IADL and a higher caregiver burden (p = 0.0001 for both). The severity of executive dysfunction did not significantly influence the patients' outcomes at 6 months. CONCLUSIONS: Executive dysfunction is a very common disorder in a representative population of patients with mild-to-moderate AD. It was independently correlated with impaired autonomy and increased caregiver burden but did not significantly influence treatment outcomes.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Caregivers; Cost of Illness; Executive Function; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Severity of Illness Index; Treatment Outcome

Characterization of Alzheimer's Disease and Mild Cognitive Impairment in Older Adults in Panama. - Villarreal, Alcibiades E; Grajales, Shantal; O'Bryant, Sid E; Edwards, Melissa; López, Lineth; Montalván, Astevia; Britton, Gabrielle B (J Alzheimers Dis, 2016)
Research on age-related cognitive impairment is scarce in Central America. We report factors associated with cognitive impairment among a sample of older adults in Panama diagnosed with Alzheimer's disease (AD, n = 31), mild cognitive impairment (MCI, n = 43), or no cognitive impairment (controls, n = 185). Apolipoprotein E (ApoE) genotype was assessed in a subset of cases (n = 135). Age (OR = 2.53, 95% CI = 1.03-6.17) and ApoE ɛ4 (OR = 5.14, 95% CI = 2.11-12.52) were significantly related to cognitive impairment (AD/MCI combined). Results underscore the potential of genetic screening in Panama for identifying those at risk of dementia.

Clearing Amyloid-β through PPARγ/ApoE Activation by Genistein is a Treatment of Experimental Alzheimer's Disease. - Bonet-Costa, Vicent; Herranz-Pérez, Vicente; Blanco-Gandía, MariCarmen; Mas-Bargues, Cristina; Inglés, Marta; Garcia-Tarraga, Patricia; Rodriguez-Arias, Marta; Miñarro, Jose; Borras, Consuelo; Garcia-Verdugo, Jose Manuel; Viña, Jose (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) clearance from brain, which is decreased in Alzheimer's disease, is facilitated by apolipoprotein E (ApoE). ApoE is upregulated by activation of the retinoid X receptor moiety of the RXR/PPARγ dimeric receptor. Genistein, a non-toxic, well-tested, and inexpensive drug activates the other moiety of the receptor PPARγ. Treatment of an Alzheimer's disease mouse model with genistein results in a remarkable and rapid improvement in various parameters of cognition, such as hippocampal learning, recognition memory, implicit memory, and odor discrimination. This is associated with a lowering of Aβ levels in brain, in the number and the area of amyloid plaques (confirmed in vivo by positron emission tomography) as well as in microglial reactivity. Finally, incubation of primary astrocytes with genistein results in a PPARγ-mediated increased release of ApoE. Our results strongly suggest that controlled clinical trials should be performed to test the effect of genistein as treatment of human Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Avoidance Learning; Brain; Cells, Cultured; Disease Models, Animal; Female; Genistein; Habituation, Psychophysiologic; Maze Learning; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Nootropic Agents; Olfactory Perception; Plaque, Amyloid; PPAR gamma; Recognition (Psychology); Tetrahydronaphthalenes

Clinical Impact of a Second FDG-PET in Atypical/Unclear Dementia Syndromes. - Bergeron, David; Beauregard, Jean-Mathieu; Guimond, Jean; Fortin, Marie-Pierre; Houde, Michèle; Poulin, Stéphane; Verret, Louis; Bouchard, Rémi W; Laforce, Robert (J Alzheimers Dis, 2016)
Diagnosis of atypical/unclear dementia is often difficult and this delays treatment initiation. Several authors have shown that beyond standard dementia workup, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) reduces the number of unclear diagnoses, leads to earlier treatment, and has a beneficial impact on families. However, it is not uncommon that the FDG-PET findings are equivocal in this setting. For those cases, a repeat FDG-PET may clarify the diagnosis and prevent treatment delay. We retrospectively assessed the clinical impact of a repeat FDG-PET in 59 patients with atypical/unclear dementia syndromes and inconclusive initial FDG-PET. Changes in primary diagnosis, diagnostic confidence, and management following the second FDG-PET were examined. Conducting a second FDG-PET reduced the number of unclear diagnoses from 80% to 34% , led to diagnostic change in 24% of cases, and treatment modification in 22% of patients. Overall, the clinical impact was higher when initial diagnostic confidence was low and the second FDG-PET repeated ≥12 months after the first one. In tertiary care memory clinic settings, when diagnostic incertitude persists despite extensive evaluation and an equivocal FDG-PET, repeating the FDG-PET 12 months later can greatly clarify the diagnosis and improve management.
Keywords: Adult; Brain; Dementia; Diagnosis, Differential; Female; Fluorodeoxyglucose F18; Humans; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; Retrospective Studies

Clinical Utility of Amyloid PET Imaging in the Differential Diagnosis of Atypical Dementias and Its Impact on Caregivers. - Bensaïdane, Mohamed Reda; Beauregard, Jean-Mathieu; Poulin, Stéphane; Buteau, François-Alexandre; Guimond, Jean; Bergeron, David; Verret, Louis; Fortin, Marie-Pierre; Houde, Michèle; Bouchard, Rémi W; Soucy, Jean-Paul; Laforce, Robert (J Alzheimers Dis, 2016)
Recent studies have supported a role for amyloid positron emission tomography (PET) imaging in distinguishing Alzheimer's disease (AD) pathology from other pathological protein accumulations leading to dementia. We investigated the clinical utility of amyloid PET in the differential diagnosis of atypical dementia cases and its impact on caregivers. Using the amyloid tracer 18F-NAV4694, we prospectively scanned 28 patients (mean age 59.3 y, s.d. 5.8; mean MMSE 21.4, s.d. 6.0) with an atypical dementia syndrome. Following a comprehensive diagnostic workup (i.e., history taking, neurological examination, blood tests, neuropsychological evaluation, MRI, and FDG-PET), no certain diagnosis could be arrived at. Amyloid PET was then conducted and classified as positive or negative. Attending physicians were asked to evaluate whether this result led to a change in diagnosis or altered management. They also reported their degree of confidence in the diagnosis. Caregivers were met after disclosure of amyloid PET results and completed a questionnaire/interview to assess the impact of the scan. Our cohort was evenly divided between positive (14/28) and negative (14/28) 18F-NAV4694 cases. Amyloid PET resulted in a diagnostic change in 9/28 cases (32.1%: 17.8% changed from AD to non-AD, 14.3% from non-AD to AD). There was a 44% increase in diagnostic confidence. Altered management occurred in 71.4% (20/28) of cases. Knowledge of amyloid status improved caregivers' outcomes in all domains (anxiety, depression, disease perception, future anticipation, and quality of life). This study suggests a useful additive role for amyloid PET in atypical cases with an unclear diagnosis beyond the extensive workup of a tertiary memory clinic. Amyloid PET increased diagnostic confidence and led to clinically significant alterations in management. The information gained from that test was well received by caregivers and encouraged spending quality time with their loved ones.

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit. - Xiong, Li; Davidsdottir, Sigurros; Reijmer, Yael D; Shoamanesh, Ashkan; Roongpiboonsopit, Duangnapa; Thanprasertsuk, Sekh; Martinez-Ramirez, Sergi; Charidimou, Andreas; Ayres, Alison M; Fotiadis, Panagiotis; Gurol, Edip; Blacker, Deborah L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is increasingly recognized as a cause of cognitive impairment in the elderly, but the cognitive profile in patients with the disease has not been well characterized. OBJECTIVE: To characterize the neuropsychological profile of CAA patients without dementia and to determine the association between cognitive performance in different domains and neuroimaging lesions characteristic of CAA. METHODS: Fifty-eight non-demented CAA patients were compared to 138 cognitively normal subjects using a standard neuropsychological test battery. Total brain volume (TBV), white matter hyperintensities, number of lobar cerebral microbleeds, hippocampal volume, and cortical superficial siderosis in all CAA patients were assessed. The association between these neuroimaging markers and neuropsychological performance in different cognitive domains in the CAA group were analyzed. RESULTS: Patients with CAA had significantly worse performance on all individual neuropsychological domains tested, when compared to the cognitive normal group. The cognitive decline of CAA patients was most noticeable in tests for processing speed with a Z score of -1.92±1.56 (mean±SD), then followed by executive function (-0.93±1.01), episodic memory (-0.87±1.29), semantic fluency (-0.73±1.06), and attention (-0.42±0.98). TBV of the CAA patients was correlated with processing speed (β= 0.335, p = 0.03) and executive function (β= 0.394, p = 0.01). CONCLUSIONS: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.
Keywords: Aged; Atrophy; Brain; Cerebral Amyloid Angiopathy; Cognition; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke

Cognitive Reserve in Alzheimer's Dementia: Diagnostic Accuracy of a Testing-the-Limits Paradigm. - Küster, Olivia C; Kösel, Jonas; Spohn, Stephanie; Schurig, Niklas; Tumani, Hayrettin; von Arnim, Christine A F; Uttner, Ingo (J Alzheimers Dis, 2016)
Individuals with higher cognitive reserve are more able to cope with pathological brain alterations, potentially due to the application of more efficient cognitive strategies. The extent to which an individual's cognitive performance can be increased by advantageous conditions differs substantially between patients with Alzheimer's dementia (AD) and healthy older adults and can be assessed with the Testing-the-Limits (TtL) approach. Thus, TtL has been proposed as a tool for the early diagnosis of AD. Here, we report the diagnostic accuracy of a memory TtL paradigm to discriminate between AD patients and controls. The TtL paradigm was administered to 57 patients with clinically diagnosed AD and 94 controls. It consisted of a pre-test condition, representing baseline cognitive performance, the presentation of an encoding strategy, and two subsequent post-test conditions, representing learning potential. Receiver operating characteristic (ROC) curves were analyzed for each condition in order to receive optimal cutoff points along with their sensitivity and specificity and to compare the diagnostic accuracy of the conditions. Differentiation between AD patients and controls, indicated by the area under the ROC curve, increased significantly for the TtL post-test and total error scores compared to the pre-test score. The combined error score in the two post-tests could differentiate between AD patients and controls with a sensitivity of 0.93 and a specificity of 0.80. The presented approach can be carried out in 25 minutes and thus constitutes a time- and cost-effective way to diagnose AD with high accuracy.

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Comparing Longitudinal Behavior Changes in the Primary Progressive Aphasias. - Van Langenhove, Tim; Leyton, Cristian E; Piguet, Olivier; Hodges, John R (J Alzheimers Dis, 2016)
BACKGROUND: Differentiating between primary progressive aphasia (PPA) variants based on the profile of language deficits can be difficult in a proportion of patients. Further, little is presently know about the pattern of longitudinal changes in behavior in PPA variants. OBJECTIVE: To determine the presence of behavioral changes in the main variants of PPA: semantic (sv-PPA), nonfluent/agrammatic (nfv-PPA), and logopenic (lv-PPA), and establish the course of these changes over time. METHODS: We measured behavioral changes in 73 prospectively recruited PPA (30 sv-PPA, 22 nfv-PPA, and 21 lv-PPA), as well as 33 behavioral variant frontotemporal dementia (bv-FTD) and 31 Alzheimer's disease (AD) patients, at baseline and after 1 year, using the Cambridge Behavioural Inventory Revised. All included patients had mild dementia severity at baseline. RESULTS: Both at baseline and follow-up, sv-PPA exhibited significantly more behavioral disturbances of the type characteristic of bv-FTD compared with other PPA variants. 74% of sv-PPA patients with mild dementia severity exhibited at least one behavior disturbance at baseline, which increased to 84% during follow-up. Behavioral symptoms did not differ between nfv-PPA and lv-PPA groups at baseline. At follow-up, however, empathy loss was significantly more pronounced in nfv-PPA. The prevalence and course of behavioral symptoms in lv-PPA was similar to that found in AD. CONCLUSIONS: sv-PPA show more prominent FTD-like behavioral disturbances compared with other PPA variants which typically emerge already early in the disease course. Empathy loss may be an important factor that helps differentiating nfv-PPA from lv-PPA. Our results may allow improved prediction of likely progression in behavioral symptoms across the PPA variants.

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

The Cytome Assay as a Tool to Investigate the Possible Association Between Exposure to Extremely Low Frequency Magnetic Fields and an Increased Risk for Alzheimer's Disease. - Maes, Annemarie; Anthonissen, Roel; Wambacq, Sheleen; Simons, Koen; Verschaeve, Luc (J Alzheimers Dis, 2016)
Exposure to extremely low frequency magnetic fields (ELF-MF) has been identified as one of the potential environmental risk factors for Alzheimer's disease (AD). However, this is far from being established. So far there is no experimental evidence supporting this alleged association. We have performed an in vitro cytogenetic laboratory investigation to explore the plausibility of such association. Our investigation was based on possible similarities found in cells from AD patients and in cells exposed to ELF-MF. We especially found that 50  Hz ELF-MF increase the frequency of cells with (large) micronuclei and nuclear buds indicating that fields above 50 μT may induce chromosome instabilities as those found in AD patients. It should be stressed yet that results from the few published experimental studies on ELF-MF and AD are rather reassuring. Thus, our findings certainly do not prove anything. They only suggest that further investigations might be necessary.
Keywords: Apoptosis; Carcinoma; Cell Line, Tumor; Chromosome Aberrations; Cytokinesis; Dose-Response Relationship, Radiation; Humans; Magnetic Fields; Risk Factors

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

A Depressive Endophenotype for Predicting Cognitive Decline among Mexican American Adults and Elders. - Johnson, Leigh A; Gamboa, Adriana; Vintimilla, Raul; Edwards, Melissa; Hall, James; Weiser, Brent; Yadav, Menaka; Dickensheets, Tony; O'Bryant, Sid E (J Alzheimers Dis, 2016)
BACKGROUND: Late life depression is a prodromal feature and a risk factor for Alzheimer's disease (AD) and mild cognitive impairment (MCI). We identified five items in the Geriatric Depression scale (DepE) that are important as a risk for MCI and AD: memory problems, feeling blue, crying, feeling worthless, and trouble concentrating. OBJECTIVE: Our goal was to examine the relationship between DepE and cognition in a cohort of Mexican Americans. METHODS: Data from 317 Mexican Americans from the HABLE study were analyzed. DepE scores were dichotomized into two groups: endorsement of 1 item or less, and endorsement of 2 or more items. Cognition was assessed via neuropsychological tests, and diagnosis was based on consensus review. We utilized linear regression to examine the association between DepE and cognitive performance, and logistic regression to examine the utility of DepE in predicting MCI. To examine the impact of DepE on memory over 12 months, we performed ANOVA analysis. RESULTS: Elevated DepE scores were associated with poorer performance on various measures of memory and cognition, but not executive or visual spatial skills. Over 12 months, we found a decline in immediate memory among women but not men. Those with high scores were 4 times more likely to have MCI. ANOVA of total scores revealed differences between groups on immediate memory (p < 0.05) in women, with no significant differences on delay recall in either gender. CONCLUSION: DepE can be utilized in Mexican Americans to identify those at risk of memory related cognitive decline.

Diagnostic Accuracy of MRI and Additional [18F]FDG-PET for Behavioral Variant Frontotemporal Dementia in Patients with Late Onset Behavioral Changes. - Vijverberg, Everard G B; Wattjes, Mike P; Dols, Annemiek; Krudop, Welmoed A; Möller, Christiane; Peters, Anne; Kerssens, Cora J; Gossink, Flora; Prins, Niels D; Stek, Max L; Scheltens, Philip; van Berckel, Bart N M; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Neuroimaging has a reasonable accuracy to differentiate behavioral variant frontotemporal dementia (bvFTD) from other neurodegenerative disorders, its value for the differentiation of bvFTD among subjects with acquired behavioral disturbances is unknown. OBJECTIVE: To determine the diagnostic accuracy of MRI, additional [18F]FDG-PET, and their combination for bvFTD among subjects with late onset behavioral changes. METHODS: Patients with late onset behavioral changes referred to a memory clinic or psychiatric services were included. At baseline, 111 patients had a brain MRI scan and 74 patients received an additional [18F]FDG-PET when the MRI was inconclusive. The consensus diagnosis after two-year-follow-up was used as the gold standard to calculate sensitivity and specificity for baseline neuroimaging. RESULTS: 27 patients had probable/definite bvFTD and 84 patients had a non-bvFTD diagnosis (primary psychiatric diagnosis or other neurological disorders). MRI had a sensitivity of 70% (95% CI 52-85%) with a specificity of 93% (95% CI 86-97%). Additional [18F]FDG-PET had a sensitivity of 90% (95% CI 66-100%) with a specificity of 68% (95% CI 56-79%). The sensitivity of combined neuroimaging was 96% (95% CI 85-100%) with a specificity of 73% (95% CI 63-81%). In 66% of the genetic FTD cases, MRI lacked typical frontotemporal atrophy. 40% of cases with a false positive [18F]FDG-PET scan had a primary psychiatric diagnosis. CONCLUSION: A good diagnostic accuracy was found for MRI and additional [18F]FDG-PET for bvFTD in patients with late onset behavioral changes. Caution with the interpretation of neuroimaging results should especially be taken in cases with a genetic background and in cases with a primary psychiatric differential diagnosis where [18F]FDG-PET is the only abnormal investigation.

Diagnostic Distortions: A Case Report of Progressive Apraxia of Speech. - Brodtmann, Amy; Pemberton, Hugh; Darby, David; Vogel, Adam P (J Alzheimers Dis, 2016)
Apraxia of speech (AOS) can be the presenting symptom of neurodegenerative disease. The position of primary progressive AOS in the nosology of the dementias is still controversial. Despite seeing many specialists, patients are often misdiagnosed, in part due to a lack of quantitative measures of speech dysfunction. We present a single case report of a patient presenting with AOS, including acoustic analysis, language assessment, and brain imaging. A 52-year-old woman presenting with AOS had remained undiagnosed for 6 years despite seeing 8 specialists. Results of her MRI scans, genetic testing, and computerized speech analysis are provided. AOS is an underdiagnosed clinical syndrome causing great distress to patients and families. Using acoustic analysis of speech may lead to improved diagnostic accuracy. AOS is a complex entity with an expanding phenotype, and quantitative clinical measures will be critical for detection and to assess progression.

Diagnostic Impact of Cerebrospinal Fluid Biomarker (Pre-)Analytical Variability in Alzheimer's Disease. - Niemantsverdriet, Ellis; Goossens, Joery; Struyfs, Hanne; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Vanderstichele, Hugo; Engelborghs, Sebastiaan (J Alzheimers Dis, 2016)
Intra- and inter-laboratory variability of cerebrospinal fluid (CSF) biomarker analyses remains an important issue. We investigated the clinical-diagnostic impact of CSF biomarker concentration shifts in mild cognitive impairment (MCI) and autopsy-confirmed Alzheimer's disease (AD) dementia patients. MCI patients (n = 85), autopsy-confirmed AD dementia patients (n = 72), and cognitively healthy controls (n = 100) were included in this prospective, longitudinal study. AD dementia patients were followed up until death, and controls were included from 1992 until 2003. In-house validated cutoff values of biomarkers were applied: Aβ1-42 <638.5 pg/mL, T-tau>296.5 pg/mL, P-tau(181P) >56.5 pg/mL. Both increments and decrements (from ± 5% to ± 40% ) were added to the true (=observed) CSF biomarker values, imitating the anticipated differences in biomarker concentrations. Within certain limits, the clinical diagnostic performance of AD CSF biomarkers remains largely unchanged and clinical diagnostic accuracy deviated less than 8.2% from the reference when concentration shifts ranging between -20% and +20% were added to one of the three CSF biomarkers in MCI and autopsy-confirmed AD patients. Notwithstanding the fact that (pre- and post-)analytical parameters can affect the clinical classification, the present exploratory study provides evidence that for a specific context of use, the impact on clinical accuracy of biomarker concentration shifts might be lower than originally expected. In conclusion, induced shifts of ±20% in only one of the three biomarkers has limited impact on the clinical accuracy of AD CSF biomarkers in MCI and autopsy-confirmed AD patients when using the IWG-2 criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Autopsy; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Exercise; Female; Follow-Up Studies; Humans; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Differential Mass Spectrometry Profiles of Tau Protein in the Cerebrospinal Fluid of Patients with Alzheimer's Disease, Progressive Supranuclear Palsy, and Dementia with Lewy Bodies. - Barthélemy, Nicolas R; Gabelle, Audrey; Hirtz, Christophe; Fenaille, François; Sergeant, Nicolas; Schraen-Maschke, Susanna; Vialaret, Jérôme; Buée, Luc; Junot, Christophe; Becher, François; Lehmann, Sylvain (J Alzheimers Dis, 2016)
Microtubule-associated Tau proteins are major actors in neurological disorders, the so-called tauopathies. In some of them, and specifically in Alzheimer's disease (AD), hyperphosphorylated forms of Tau aggregate into neurofibrillary tangles. Following and understanding the complexity of Tau's molecular profile with its multiple isoforms and post-translational modifications represent an important issue, and a major analytical challenge. Immunodetection methods are, in fact, limited by the number, specificity, sensitivity, and capturing property of the available antibodies. Mass spectrometry (MS) has recently allowed protein quantification in complex biological fluids using isotope-labeled recombinant standard for absolute quantification (PSAQ). To study Tau proteins, which are found at very low concentrations within the cerebrospinal fluid (CSF), we relied on an innovative two-step pre-fractionation strategy, which was not dependent on immuno-enrichment. We then developed a sensitive multiplex peptide detection capability using targeted high-resolution MS to quantify Tau-specific peptides covering its entire sequence. This approach was used on a clinical cohort of patients with AD, progressive supranuclear palsy (PSP), and dementia with Lewy body (DLB) and with control non-neurodegenerative disorders. We uncovered a common CSF Tau molecular profile characterized by a predominance of central core expression and 1N/3R isoform detection. While PSP and DLB tau profiles showed minimal changes, AD was characterized by a unique pattern with specific modifications of peptide distribution. Taken together these results provide important information on Tau biology for future therapeutic interventions, and improved molecular diagnosis of tauopathies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analysis of Variance; Chromatography, Liquid; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Peptide Fragments; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Statistics as Topic; Supranuclear Palsy, Progressive; tau Proteins

Dihydropyridine Derivatives Modulate Heat Shock Responses and have a Neuroprotective Effect in a Transgenic Mouse Model of Alzheimer's Disease. - Kasza, Ágnes; Hunya, Ákos; Frank, Zsuzsa; Fülöp, Ferenc; Török, Zsolt; Balogh, Gábor; Sántha, Miklós; Bálind, Árpád; Bernáth, Sándor; Blundell, Katie L I M; Prodromou, Chrisostomos; Horváth, Ibolya; et al. (J Alzheimers Dis, 2016)
Heat shock proteins (Hsps) have chaperone activity and play a pivotal role in the homeostasis of proteins by preventing misfolding, by clearing aggregated and damaged proteins from cells, and by maintaining proteins in an active state. Alzheimer's disease (AD) is thought to be caused by amyloid-β peptide that triggers tau hyperphosphorylation, which is neurotoxic. Although proteostasis capacity declines with age and facilitates the manifestation of neurodegenerative diseases such as AD, the upregulation of chaperones improves prognosis. Our research goal is to identify potent Hsp co-inducers that enhance protein homeostasis for the treatment of AD, especially 1,4-dihydropyridine derivatives optimized for their ability to modulate cellular stress responses. Based on favorable toxicological data and Hsp co-inducing activity, LA1011 was selected for the in vivo analysis of its neuroprotective effect in the APPxPS1 mouse model of AD. Here, we report that 6 months of LA1011 administration effectively improved the spatial learning and memory functions in wild type mice and eliminated neurodegeneration in double mutant mice. Furthermore, Hsp co-inducer therapy preserves the number of neurons, increases dendritic spine density, and reduces tau pathology and amyloid plaque formation in transgenic AD mice. In conclusion, the Hsp co-inducer LA1011 is neuroprotective and therefore is a potential pharmaceutical candidate for the therapy of neurodegenerative diseases, particularly AD.

Do Microglia Default on Network Maintenance in Alzheimer's Disease? - Southam, Katherine A; Vincent, Adele J; Small, David H (J Alzheimers Dis, 2016)
Although the cause of Alzheimer's disease (AD) remains unknown, a number of new findings suggest that the immune system may play a critical role in the early stages of the disease. Genome-wide association studies have identified a wide array of risk-associated genes for AD, many of which are associated with abnormal functioning of immune cells. Microglia are the brain's immune cells. They play an important role in maintaining the brain's extracellular environment, including clearance of aggregated proteins such as amyloid-β (Aβ). Recent studies suggest that microglia play a more active role in the brain than initially considered. Specifically, microglia provide trophic support to neurons and also regulate synapses. Microglial regulation of neuronal activity may have important consequences for AD. In this article we review the function of microglia in AD and examine the possible relationship between microglial dysfunction and network abnormalities, which occur very early in disease pathogenesis.
Keywords: Alzheimer Disease; Animals; Humans; Microglia; Synapses

Effectiveness of Exercise- and Cognitive-Based Treatments on Salivary Cortisol Levels and Sundowning Syndrome Symptoms in Patients with Alzheimer's Disease. - Venturelli, Massimo; Sollima, Alessio; Cè, Emiliano; Limonta, Eloisa; Bisconti, Angela V; Brasioli, Anna; Muti, Ettore; Esposito, Fabio (J Alzheimers Dis, 2016)
Sundowning syndrome (SDS) in patients with Alzheimer's disease (AD) is characterized by the intensification of behavioral disorders at sunset. Despite SDS etiology being unclear, a strong relationship between high cortisol levels and SDS has been reported. Aerobic exercise (AE) and cognitive training (CT) can reduce cortisol levels. However, whether SDS would benefit from AE and CT is still unknown. Therefore, the aim of this study was to investigate whether AE and CT treatments are effective in reducing SDS via downregulation of cortisol levels. The possible additive effects of combined AE+CT were also assessed. Eighty AD patients were randomly assigned to AE (n = 20), CT (n = 20), AE+CT (n = 20), and standard therapy (no treatment, NT; n = 20). Treatments were administered for 3 months, 5 days/week, 1 hour before sunset. Before and after treatments, salivary cortisol levels were sampled at 7, 11, 15, at sunset, and 20 (time of day). Blind assessment of behavioral disorders (neuropsychiatric inventory, NPI) and agitation (agitated behavior scale, ABS) were also performed. After interventions, cortisol levels were reduced in AE and AE+CT by ∼26%. In the same groups, NPI and ABS decreased by ∼50%. By contrast, cortisol and behavioral disorders were similar to baseline in CT and NT. Changes in NPI and ABS were significantly correlated with the reduction in cortisol levels. AE or AE+CT effects on SDS and cortisol levels and the lack of effect of CT alone indicate the effectiveness of an exercise-based treatment on SDS, suggesting a possible hypothalamic-pituitary-adrenal axis dysregulation underpinning SDS.

Effectiveness of Supporting Informal Caregivers of People with Dementia: A Systematic Review of Randomized and Non-Randomized Controlled Trials. - Vandepitte, Sophie; Van Den Noortgate, Nele; Putman, Koen; Verhaeghe, Sofie; Faes, Kristof; Annemans, Lieven (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is known as a major public health problem affecting both patients and caregivers, and placing a high financial strain upon society. In community-dwelling patients, it is important to support informal caregivers in order to help them sustain their demanding role. Previous reviews about effectiveness of such supporting strategies often included a small number of studies, focused only on particular supportive types, particular outcomes, or solely on caregivers. OBJECTIVE: A general systematic review was conducted investigating effectiveness of different supportive strategies on at least the well-being of the caregiver or the care-recipient. METHODS: A systematic literature search was conducted in Web of Science and PubMed. An adapted version of the Downs and Black (1998) checklist was used to assess methodological quality. A new classification was developed to group different types of caregiver support. RESULTS: Fifty-three papers met the inclusion criteria. Although 87% of the interventions were to some extent effective, methods and findings were rather inconsistent. Psychoeducational interventions generally lead to positive outcomes for caregivers, and delay permanent institutionalization of care-recipients. Cognitive behavioral therapy decreases dysfunctional thoughts among caregivers. Occupational therapy decreases behavioral problems among patients and improves self-efficacy of caregivers. In general, those interventions tailored on individual level generate better outcomes. Comparative research on respite care was very rare. CONCLUSIONS: Despite methodological inconsistency, supporting caregivers appears to be an effective strategy often improving well-being of caregiver or care-recipient and resulting in additional benefits for society. However, there is a need for more research on the (cost)-effectiveness of respite care.

The Effects of Latrepirdine on Amyloid-β Aggregation and Toxicity. - Porter, Tenielle; Bharadwaj, Prashant; Groth, David; Paxman, Adrian; Laws, Simon M; Martins, Ralph N; Verdile, Giuseppe (J Alzheimers Dis, 2016)
Latrepirdine (Dimebon) has been demonstrated to be a neuroprotective and cognition improving agent in neurodegenerative diseases that feature protein aggregation and deposition, such as Alzheimer's disease (AD). The accumulation of amyloid-β (Aβ) protein aggregates is a key event in the neurodegenerative process in AD. This study explores if latrepirdine modulation of protein aggregation contributes to its neuroprotective mechanism of action. Assessment of neuronal cell death showed that there was a significant reduction in lactate dehydrogenase release at an equimolar ratio of Aβ:latrepirdine and with lower concentrations of latrepirdine. The ability of latrepirdine to alter the formation of Aβ42 aggregates was assessed by thioflavin-T fluorescence, western immunoblotting and atomic force microscopy (AFM). Despite showing a reduction in thioflavin-T fluorescence with latrepirdine treatment, indicating a decrease in aggregation, immunoblotting and AFM showed a modest increase in both the formation and size of Aβ aggregates. The discrepancies between thioflavin-T and the other assays are consistent with previous evidence that cyclic molecules can interfere with thioflavin-T binding of amyloid protein preparations. The ability of latrepirdine to modulate Aβ aggregation appears to be independent of its neuroprotective effects, and is unlikely to be a mechanism by which latrepirdine offers protection. This study investigates the effect of latrepirdine on Aβ aggregation, and presents evidence suggesting that caution should be applied in the use of thioflavin-T fluorescence based assays as a method for screening compounds for protein aggregation altering properties.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Antipsychotic Agents; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Interactions; Humans; Indoles; L-Lactate Dehydrogenase; Microscopy, Atomic Force; Neuroblastoma; Peptide Fragments; Protein Aggregates

Efficacy and Safety of Crocus sativus L. in Patients with Mild Cognitive Impairment: One Year Single-Blind Randomized, with Parallel Groups, Clinical Trial. - Tsolaki, Magda; Karathanasi, Elina; Lazarou, Ioulietta; Dovas, Kostas; Verykouki, Eleni; Karacostas, Anastasios; Georgiadis, Kostas; Tsolaki, Anthoula; Adam, Katerina; Kompatsiaris, Ioannis; Sinakos, Zacharias (J Alzheimers Dis, 2016)
There is evidence to suggest the efficacy of Crocus (saffron) in the management of cognitive decline. This study examined the efficacy of Crocus in patients with amnesic and multi domain MCI (aMCImd). The participants included 17 patients on Crocus and 18 on a waiting list, who were examined with a short neuropsychological battery, MRI 3T, while some patients were examined via 256-channel electroencephalogram (HD-EEG) at baseline and after 12 months. The results showed that patients on Crocus had improved Mini-Mental State Examination scores (p = 0.015), while the control group deteriorated. Also, MRI, EEG, and ERP showed improvement in specific domains. This led us to conclude that Crocus is a good choice for management of aMCImd.

Evaluation of a Genetic Risk Score to Improve Risk Prediction for Alzheimer's Disease. - Chouraki, Vincent; Reitz, Christiane; Maury, Fleur; Bis, Joshua C; Bellenguez, Celine; Yu, Lei; Jakobsdottir, Johanna; Mukherjee, Shubhabrata; Adams, Hieab H; Choi, Seung Hoan; Larson, Eric B; Fitzpatrick, Annette; et al. (J Alzheimers Dis, 2016)
Effective prevention of Alzheimer's disease (AD) requires the development of risk prediction tools permitting preclinical intervention. We constructed a genetic risk score (GRS) comprising common genetic variants associated with AD, evaluated its association with incident AD and assessed its capacity to improve risk prediction over traditional models based on age, sex, education, and APOEɛ4. In eight prospective cohorts included in the International Genomics of Alzheimer's Project (IGAP), we derived weighted sum of risk alleles from the 19 top SNPs reported by the IGAP GWAS in participants aged 65 and older without prevalent dementia. Hazard ratios (HR) of incident AD were estimated in Cox models. Improvement in risk prediction was measured by the difference in C-index (Δ-C), the integrated discrimination improvement (IDI) and continuous net reclassification improvement (NRI>0). Overall, 19,687 participants at risk were included, of whom 2,782 developed AD. The GRS was associated with a 17% increase in AD risk (pooled HR = 1.17; 95% CI =   [1.13-1.21] per standard deviation increase in GRS; p-value =  2.86×10-16). This association was stronger among persons with at least one APOEɛ4 allele (HRGRS = 1.24; 95% CI =   [1.15-1.34]) than in others (HRGRS = 1.13; 95% CI =   [1.08-1.18]; pinteraction = 3.45×10-2). Risk prediction after seven years of follow-up showed a small improvement when adding the GRS to age, sex, APOEɛ4, and education (Δ-Cindex =  0.0043 [0.0019-0.0067]). Similar patterns were observed for IDI and NRI>0. In conclusion, a risk score incorporating common genetic variation outside the APOEɛ4 locus improved AD risk prediction and may facilitate risk stratification for prevention trials.

Evaluation of Underlying Causes of Death in Patients with Dementia to Support Targeted Advance Care Planning. - van de Vorst, Irene E; Koek, Huiberdina L; Bots, Michiel L; Vaartjes, Ilonca (J Alzheimers Dis, 2016)
BACKGROUND: Insight in causes of death in demented patients may help physicians in end-of-life care. OBJECTIVES: To investigate underlying causes of death (UCD) in demented patients stratified by age, sex, dementia subtype [Alzheimer's disease (AD), vascular dementia (VaD)] and to compare them with UCD in the general population (GP). METHODS: A nationwide cohort of 59,201 patients with dementia (admitted to a hospital or visiting a day clinic) was constructed [38.7% men, 81.4 years (SD 7.0)] from 2000 through 2010. UCDs were reported and compared to the GP by calculating relative risks (RRs). RESULTS: During follow up [median follow up time 1.3 years (IQR 0.3- 3.0)], 64.2% of women and 69.3% of men died. Leading UCDs were dementia (17.5% in men and 23.7% in women) and cardiovascular disease (CVD) (18.7% and 19.2%, respectively). When compared to the GP, dementia was a more common UCD (RR in men 4.65, 95% CI 4.43-4.88), while CVD (RR in men 0.67, 95% CI 0.65-0.68) and cancer (RR 0.40, 95% CI 0.39-0.41) were less common. These differences were more pronounced in patients aged between 60-69 as compared to those aged≥90 years. Patients with AD died less often of cerebrovascular diseases as compared to VaD (RR in men 0.53, 95% CI 0.47-0.59). CONCLUSION: UCDs in patients with dementia differs from that of the GP, as dementia is more often and cancer less often an UCD. Although less frequent compared to the GP, CVD also is one of the leading UCDs in patients with dementia. This information is valuable for targeted advance care planning.

Evidence For and Against a Pathogenic Role of Reduced γ-Secretase Activity in Familial Alzheimer's Disease. - Jayne, Tanya; Newman, Morgan; Verdile, Giuseppe; Sutherland, Greg; Münch, Gerald; Musgrave, Ian; Moussavi Nik, Seyyed Hani; Lardelli, Michael (J Alzheimers Dis, 2016)
The majority of mutations causing familial Alzheimer's disease (fAD) have been found in the gene PRESENILIN1 (PSEN1) with additional mutations in the related gene PRESENILIN2 (PSEN2). The best characterized function of PRESENILIN (PSEN) proteins is in γ-secretase enzyme activity. One substrate of γ-secretase is encoded by the gene AMYLOID BETA A4 PRECURSOR PROTEIN (AβPP/APP) that is a fAD mutation locus. AβPP is the source of the amyloid-β (Aβ) peptide enriched in the brains of people with fAD or the more common, late onset, sporadic form of AD, sAD. These observations have resulted in a focus on γ-secretase activity and Aβ as we attempt to understand the molecular basis of AD pathology. In this paper we briefly review some of the history of research on γ-secretase in AD. We then discuss the main ideas regarding the role of γ-secretase and the PSEN genes in this disease. We examine the significance of the "fAD mutation reading frame preservation rule" that applies to PSEN1 and PSEN2 (and AβPP) and look at alternative roles for AβPP and Aβ in fAD. We present a case for an alternative interpretation of published data on the role of γ-secretase activity and fAD-associated mutations in AD pathology. Evidence supports a "PSEN holoprotein multimer hypothesis" where PSEN fAD mutations generate mutant PSEN holoproteins that multimerize with wild type holoprotein and dominantly interfere with an AD-critical function(s) such as autophagy or secretion of Aβ. Holoprotein multimerization may be required for the endoproteolysis that activates PSENs' γ-secretase activity.

Exercise Prevents Amyloid-β-Induced Hippocampal Network Disruption by Inhibiting GSK3β Activation. - Isla, Arturo G; Vázquez-Cuevas, Francisco Gabriel; Peña-Ortega, Fernando (J Alzheimers Dis, 2016)
Exercise is becoming a promising therapeutic approach to prevent alterations both in Alzheimer's disease (AD) patients and in transgenic models of AD. This neuroprotection has been associated with changes in hippocampal structure and function, as well as with the reduction of amyloid-β (Aβ) production and accumulation. However, whether exercise produces lasting changes in hippocampal population activity and renders it resistant to Aβ-induced network dysfunction is still unknown. Thus, we tested whether voluntary exercise changes hippocampal population activity and prevents its alteration in the presence of Aβ, which has been associated to glycogen synthase kinase-3β (GSK3β) activation. We found that the hippocampal population activity recorded in slices obtained from mice that exercised voluntarily (with free access to a running wheel for 21 days) exhibits higher power and faster frequency composition than slices obtained from sedentary animals. Moreover, the hippocampal network of mice that exercised becomes insensitive to Aβ-induced inhibition of spontaneous population activity. This protective effect correlates with the inability of Aβ to activate GSK3β, is mimicked by GSK3β inhibition with SB126763 (in slices obtained from sedentary mice), and is abolished by the inhibition of PI3K with LY294002 (in slices obtained from mice that exercised). We conclude that voluntary exercise produces a lasting protective state in the hippocampus, maintained in hippocampal slices by a PI3K-dependent mechanism that precludes its functional disruption in the presence of Aβ by avoiding GSK3β activation.

Expression Pattern of Scavenger Receptors and Amyloid-β Phagocytosis of Astrocytes and Microglia in Culture are Modified by Acidosis: Implications for Alzheimer's Disease. - Eugenín, Jaime; Vecchiola, Andrea; Murgas, Paola; Arroyo, Pablo; Cornejo, Francisca; von Bernhardi, Rommy (J Alzheimers Dis, 2016)
The pathological hallmarks of Alzheimer's disease (AD) are amyloid-β (Aβ) plaques, neurofibrillary tangles, and glia activation. The pathology also includes vascular amyloidosis and cerebrovascular disease. Vascular compromise can result in hypoperfusion, local tissue hypoxia, and acidosis. Activated microglia and astrocytes can phagocytose Aβ through membrane receptors that include scavenger receptors. Changes in glial cells induced by extracellular acidosis could play a role in the development of AD. Here, we assess whether extracellular acidosis changes glial cell properties relevant for Aβ clearance capacity. Incubation of glial cells on acidified culture medium (pH 6.9 or 6.5) for 24-48 h resulted in decreased cell diameter, with thinner branches in astrocytes, slight reduction in cell body size in microglia, a transient decrease in astrocyte adhesion to substrates, and a persistent decrease in microglia adhesion compared with control media (pH 7.4). Astrocyte Aβ phagocytosis decreased at pH 6.9 and 6.5, whereas microglia phagocytosis only transiently decreased in acidified media. Scavenger receptors class B member I (SR-BI) increased and scavenger receptors-macrophage receptors with collagenous structures (SR-MARCO) decreased in astrocytes cultured at pH 6.5. In contrast, in microglia exposed to pH 6.5, expression of SR-BI and SR-MARCO increased and fatty acid translocase (CD-36) decreased. In conclusion, the acidic environment changed the adhesiveness and morphology of both microglia and astrocytes, but only astrocytes showed a persistent decrease in Aβ clearance activity. Expression of scavenger receptors was affected differentially in microglia and astrocytes by acidosis. These changes in scavenger receptor patterns can affect the activation of glia and their contribution to neurodegeneration.

Extracellular Tau Paired Helical Filaments Differentially Affect Tau Pathogenic Mechanisms in Mitotic and Post-Mitotic Cells: Implications for Mechanisms of Tau Propagation in the Brain. - Varghese, Merina; Santa-Maria, Ismael; Ho, Lap; Ward, Libby; Yemul, Shrishailam; Dubner, Lauren; Księżak-Reding, Hanna; Pasinetti, Giulio Maria (J Alzheimers Dis, 2016)
The release of paired helical filaments (PHFs) from neurons into the extracellular space may contribute to the propagation of tau pathology across brain regions in Alzheimer's disease (AD) and other tauopathies. The majority of available mechanistic studies exploring the pathologic role of extracellular PHFs are conducted in proliferating cell lines. Here, we compare how extracellular PHFs induce tauopathy in mitotic cells and in post-mitotic brain neurons. In a mitotic cell line (HEK 293T), extracellular exposure to AD PHFs leads to an intracellular "aggresomal" type deposition of tau, coincidental with redistribution of dynein, a retrograde motor protein. We also observed that PHFs impaired proteasome degradation, but not autophagy. Exposure of cells to proteasome inhibitors was sufficient to induce intracellular tau aggregate formation as well as reorganization of dynein and the intermediate filament protein, vimentin. Thus, in mitotic cells, extracellular PHFs promote cellular tau aggregation, in part, by interfering with cellular proteasome degradation processes. In contrast with our observations with proliferating cells, exposure of post-mitotic primary neuronal cultures to AD PHFs did not promote "aggresomal" tau deposition, but instead resulted in a widespread accumulation of phosphorylated tau-immunoreactive swellings in neuritic processes, characterized by disturbed cytoskeletal organization of dynein and vimentin. Collectively, our observations suggest that extracellular PHFs may contribute to the propagation of tau pathology by independent mechanisms in post-mitotic and mitotic brain cells. These outcomes indicate that in addition to post-mitotic brain neurons, mitotic brain cells should also be considered as targets for therapeutic interventions to attenuate propagation of tauopathy.

Feasibility of a Memory Clinic-Based Physical Activity Prescription Program. - Vidoni, Eric D; Watts, Amber S; Burns, Jeffrey M; Greer, Colby S; Graves, Rasinio S; Van Sciver, Angela; Black, Jessica R; Cooper, Sarah K; Nagely, Allison C; Uphoff, Elaine; Volmer, Jennifer M; Bieberle, Natalie A (J Alzheimers Dis, 2016)
BACKGROUND: Effective programs for promoting physical activity are needed for those with cognitive impairment. OBJECTIVE: To test the feasibility of mobile Health (mHealth) technology-supported physical activity prescription from a tertiary care memory clinic. METHODS: This feasibility study was designed as a 16-week randomized, crossover trial of a physical activity prescription: 8 weeks of intervention, 8 weeks of baseline or maintenance phase data collection. We recruited 2 cohorts: 21 individuals with Alzheimer-related cognitive impairment (mean age 72.3 (5.2), 9 females), and 9 individuals with normal cognition (mean age 69.6 (5.8), 8 females). We gave each cohort an mHealth accelerometer-based physical activity prescription to double number of steps taken. Our primary outcomes were feasibility and safety. Our secondary outcomes were change in weekly steps taken, Dementia Quality of Life Scale, Self-efficacy Scale, 6-minute Walk, and mini-Physical Performance Test. RESULTS: Set-up and use of the device was not a barrier to participation. However, only 62% of participants with cognitive impairment completed the intervention. The cohort with cognitive impairment did not change their weekly step count above Week 1. All participants in the cohort with normal cognition were able to set up and use their device and increased their weekly step count above Week 1. There were no differences between Week 1 and Week 8 for any secondary measures in either cohort. CONCLUSIONS: Setup and daily use of mHealth technology appears to be feasible for a person with cognitive impairment with the help of a partner, but increasing daily step counts over 8 weeks was not achieved. Future work needs to assess alternative activity prescription goals or additional support for patients and their partners.

Fine Particulate Matter, Residential Proximity to Major Roads, and Markers of Small Vessel Disease in a Memory Study Population. - Wilker, Elissa H; Martinez-Ramirez, Sergi; Kloog, Itai; Schwartz, Joel; Mostofsky, Elizabeth; Koutrakis, Petros; Mittleman, Murray A; Viswanathan, Anand (J Alzheimers Dis, 2016)
BACKGROUND: Long-term exposure to ambient air pollution has been associated with impaired cognitive function and vascular disease in older adults, but little is known about these associations among people with concerns about memory loss. OBJECTIVE: To examine associations between exposures to fine particulate matter and residential proximity to major roads and markers of small vessel disease. METHODS: From 2004-2010, 236 participants in the Massachusetts Alzheimer's Disease Research Center Longitudinal Cohort participated in neuroimaging studies. Residential proximity to major roads and estimated 2003 residential annual average of fine particulate air pollution (PM2.5) were linked to measures of brain parenchymal fraction (BPF), white matter hyperintensities (WMH), and cerebral microbleeds. Associations were modeled using linear and logistic regression and adjusted for clinical and lifestyle factors. RESULTS: In this population (median age [interquartile range] = 74 [12], 57% female) living in a region with median 2003 PM2.5 annual average below the current Environmental Protection Agency (EPA) standard, there were no associations between living closer to a major roadway or for a 2μg/m3 increment in PM2.5 and smaller BPF, greater WMH volume, or a higher odds of microbleeds. However, a 2μg/m3 increment in PM2.5 was associated with -0.19 (95% Confidence Interval (CI): -0.37, -0.005) lower natural log-transformed WMH volume. Other associations had wide confidence intervals. CONCLUSIONS: In this population, where median 2003 estimated PM2.5 levels were below the current EPA standard, we observed no pattern of association between residential proximity to major roads or 2003 average PM2.5 and greater burden of small vessel disease or neurodegeneration.

Fluoxetine Treatment Induces Seizure Behavior and Premature Death in APPswe/PS1dE9 Mice. - Sierksma, Annerieke S R; de Nijs, Laurence; Hoogland, Govert; Vanmierlo, Tim; van Leeuwen, Fred W; Rutten, Bart P F; Steinbusch, Harry W M; Prickaerts, Jos; van den Hove, Daniel L A (J Alzheimers Dis, 2016)
Treatment of Alzheimer's disease (AD) patients with the antidepressant fluoxetine is known to improve memory and cognitive function. However, the mechanisms underlying these effects are largely unknown. To unravel these mechanisms, we aimed to treat APPswe/PS1dE9 mice with fluoxetine. Unexpectedly, with time, an increased number of animals displayed seizure behavior and died. Although spontaneous behavioral seizures have been reported previously in this mouse model, the observation of seizures and death consequential to fluoxetine treatment is new. Our results warrant further research on the underlying mechanisms as this may refine the treatment of AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anticonvulsants; Body Weight; Disease Models, Animal; Fluoxetine; Humans; Logistic Models; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Presenilin-1; Seizures

Formulaic Language in People with Probable Alzheimer's Disease: A Frequency-Based Approach. - Zimmerer, Vitor C; Wibrow, Mark; Varley, Rosemary A (J Alzheimers Dis, 2016)
BACKGROUND: Language change can be a valuable biological marker of overall cognitive change in Alzheimer's disease (AD) and other forms of dementia. Previous reports have described increased use of language formulas in AD, i.e., combinations likely processed in a holistic manner. Words that commonly occur together are more likely to become a formula. OBJECTIVE: To determine if frequency of co-occurrence as one indicator for formulaic language can distinguish people with probable AD from controls and if variables are sensitive to time post-symptom onset. METHODS: We developed the Frequency in Language Analysis Tool (FLAT), which indicates degrees of formulaicity in an individual language sample. The FLAT accomplishes this by comparing individual language samples to co-occurrence data from the British National Corpus (BNC). Our analysis also contained more conventional language variables in order to assess novel contributions of the FLAT. We analyzed data from the Pitt Corpus, which is part of DementiaBank. RESULTS: Both conventional and co-occurrence variables were able to distinguish AD and control groups. According to co-occurrence data, people with probable AD produced more formulaic language than controls. Only co-occurrence variables correlated with disease progression. DISCUSSION: Frequency of word co-occurrences is one indicator for formulaicity and a valuable contribution to characterizing language change in AD.

Heterogeneous Language Profiles in Patients with Primary Progressive Aphasia due to Alzheimer's Disease. - Louwersheimer, Eva; Keulen, M Antoinette; Steenwijk, Martijn D; Wattjes, Mike P; Jiskoot, Lize C; Vrenken, Hugo; Teunissen, Charlotte E; van Berckel, Bart N M; van der Flier, Wiesje M; Scheltens, Philip; van Swieten, John C; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
BACKGROUND: The logopenic variant of Primary Progressive Aphasia (lvPPA) is associated with underlying Alzheimer's disease (AD) pathology and characterized by impaired single word retrieval and repetition of phrases and sentences. OBJECTIVE: We set out to study whether logopenic aphasia is indeed the prototypic language profile in PPA patients with biomarker evidence of underlying AD pathology and to correlate language profiles with cortical atrophy patterns on MRI. METHODS: Inclusion criteria: (I) clinical diagnosis of PPA; (II) CSF profile and/or PiB-PET scan indicative for amyloid pathology; (III) availability of expert language evaluation. Based on language evaluation, patients were classified as lvPPA (fulfilling lvPPA core criteria), lvPPA extended (fulfilling core criteria plus other language disturbances), or PPA unclassifiable (not fulfilling lvPPA core criteria). Cortical atrophy patterns on MRI were visually rated and quantitative measurements of cortical thickness were performed using FreeSurfer. RESULTS: We included 22 patients (age 67±7 years, 50% female, MMSE 21±6). 41% were classified as lvPPA, 36% as lvPPA extended with additional deficits in language comprehension and/or confrontation naming, and 23% as PPA unclassifiable. By both qualitative and quantitative measurements, patients with lvPPA showed mild global cortical atrophy on MRI, whereas patients with lvPPA extended showed more focal cortical atrophy, predominantly at the left tempo-parietal side. For PPA unclassifiable, qualitative measurements revealed a heterogeneous atrophy pattern. CONCLUSION: Although most patients fulfilled the lvPPA criteria, we found that their language profiles were heterogeneous. The clinical and radiological spectrum of PPA due to underlying AD pathology is broader than pure lvPPA.
Keywords: Aged; Alzheimer Disease; Aphasia, Primary Progressive; Atrophy; Biomarkers; Brain; Female; Humans; Language; Language Tests; Magnetic Resonance Imaging; Male; Mental Status Schedule; Organ Size; Positron-Emission Tomography; Retrospective Studies

High Risk of Dementia in Ventricular Enlargement with Normal Pressure Hydrocephalus Related Symptoms1. - Koivisto, Anne M; Kurki, Mitja I; Alafuzoff, Irina; Sutela, Anna; Rummukainen, Jaana; Savolainen, Sakari; Vanninen, Ritva; Jääskeläinen, Juha E; Soininen, Hilkka; Leinonen, Ville (J Alzheimers Dis, 2016)
BACKGROUND: Differential diagnosis of ventricular enlargement with normal pressure hydrocephalus (NPH) related symptoms is challenging. Patients with enlarged ventricles often manifest cognitive deterioration but their long-term outcome is not well known. OBJECTIVES: We aim to evaluate long-term cognitive outcome in patients with enlarged ventricles and clinically suspected NPH. METHODS: A neurologist and a neurosurgeon clinically evaluated 468 patients with enlarged ventricles and suspected NPH using radiological methods, intraventricular pressure monitoring, and frontal cortical brain biopsy. The neurologist confirmed final diagnoses after a median follow-up interval of 4.8 years. RESULTS: Altogether, 232 patients (50%) with enlarged ventricles did not fulfill the criteria for shunt surgery. The incidence of dementia among patients with enlarged ventricles, and at least one NPH-related symptom with adequate follow-up data (n = 446) was high, varying from 77 (iNPH, shunt responders) to 141/1000 person-years (non-shunted patients with enlarged ventricles). At the end of the follow-up, 59% of all these patients were demented. The demented population comprised 73% of non-shunted patients with enlarged ventricles, 63% of shunted iNPH patients that did not respond to treatment, and 46% of iNPH patients that were initially responsive to shunting. The most common cause of dementia was Alzheimer's disease (n = 94, 36%), followed by vascular dementia (n = 68, 26%). CONCLUSIONS: One-half of patients with enlarged ventricles and clinically suspected NPH were not shunted after intraventricular pressure monitoring. Dementia caused by various neurodegenerative diseases was frequently seen in patients with ventricular enlargement. Thus, careful diagnostic evaluation in collaboration with neurologists and neurosurgeons is emphasized.

Human Truncated Tau Induces Mature Neurofibrillary Pathology in a Mouse Model of Human Tauopathy. - Zimova, Ivana; Brezovakova, Veronika; Hromadka, Tomas; Weisova, Petronela; Cubinkova, Veronika; Valachova, Bernadeta; Filipcik, Peter; Jadhav, Santosh; Smolek, Tomas; Novak, Michal; Zilka, Norbert (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) represents the most common neurodegenerative disorder. Several animal models have been developed in order to test pathophysiological mechanisms of the disease and to predict effects of pharmacological interventions. Here we examine the molecular and behavioral features of R3m/4 transgenic mice expressing human non-mutated truncated tau protein (3R tau, aa151-391) that were previously used for efficacy testing of passive tau vaccine. The mouse model reliably recapitulated crucial histopathological features of human AD, such as pre-tangles, neurofibrillary tangles, and neuropil threads. The pathology was predominantly located in the brain stem. Transgenic mice developed mature sarkosyl insoluble tau complexes consisting of mouse endogenous and human truncated and hyperphosphorylated forms of tau protein. The histopathological and biochemical features were accompanied by significant sensorimotor impairment and reduced lifespan. The sensorimotor impairment was monitored by a highly sensitive, fully-automated tool that allowed us to assess early deficit in gait and locomotion. We suggest that the novel transgenic mouse model can serve as a valuable tool for analysis of the therapeutic efficacy of tau vaccines for AD therapy.

Hyperactivity with Agitative-Like Behavior in a Mouse Tauopathy Model. - Jul, Pia; Volbracht, Christiane; de Jong, Inge E M; Helboe, Lone; Elvang, Anders Brandt; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), are characterized by formation of neurofibrillary tangles consisting of hyperphosphorylated tau. In addition to memory loss, patients experience behavioral symptoms such as agitation, aggression, depression, and insomnia. We explored the behavioral phenotype of a mouse model (rTg4510) carrying the human tau P301L mutation found in a familial form of FTD. We tested these mice in locomotor activity assays as well as in the Morris water maze to access spatial memory. In addition to cognitive impairments, rTg4510 mice exhibited a hyperactivity phenotype which correlated with progression of tau pathology and was dependent on P301L tau transgene expression. The hyperactive phenotype was characterized by significantly increased locomotor activity in a novel and in a simulated home cage environment together with a disturbed day/night cycle. The P301L-tau-dependent hyperactivity and agitative-like phenotype suggests that these mice may form a correlate to some of the behavioral disturbances observed in advanced AD and FTD.
Keywords: Age Factors; Analysis of Variance; Animals; Brain; Cognition Disorders; Disease Models, Animal; Doxycycline; Exploratory Behavior; Humans; Hyperkinesis; Male; Maze Learning; Mice; Mice, Transgenic; Motor Activity; Mutation; Psychomotor Agitation; tau Proteins; Tauopathies; Time Factors

Immunization Against Specific Fragments of Neurotrophin p75 Receptor Protects Forebrain Cholinergic Neurons in the Olfactory Bulbectomized Mice. - Bobkova, Natalia; Vorobyov, Vasily; Medvinskaya, Natalia; Nesterova, Inna; Tatarnikova, Olga; Nekrasov, Pavel; Samokhin, Alexander; Deev, Alexander; Sengpiel, Frank; Koroev, Dmitry; Volpina, Olga (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by progressive cognitive impairment associated with marked cholinergic neuron loss and amyloid-β (Aβ) peptide accumulation in the brain. The cytotoxicity in AD is mediated, at least in part, by Aβ binding with the extracellular domain of the p75 neurotrophin receptor (p75NTR), localized predominantly in the membranes of acetylcholine-producing neurons in the basal forebrain. Hypothesizing that an open unstructured loop of p75NTR might be the effective site for Aβ binding, we have immunized both olfactory bulbectomized (OBX) and sham-operated (SO) mice (n = 82 and 49, respectively) with synthetic peptides, structurally similar to different parts of the loops, aiming to block them by specific antibodies. OBX-mice have been shown in previous studies, and confirmed in the present one, to be characterized by typical behavioral, morphological, and biochemical AD hallmarks, including cholinergic deficits in forebrain neurons. Immunization of OBX- or SO-mice with KLH conjugated fragments of p75NTR induced high titers of specific serum antibodies for each of nine chosen fragments. However, maximal protective effects on spatial memory, evaluated in a Morris water maze, and on activity of choline acetyltransferase in forebrain neurons, detected by immunoreactivity to specific antibodies, were revealed only for peptides with amino acid residue sequences of 155-164 and 167-176. We conclude that the approach based on immunological blockade of specific p75NTR sites, linked with the cytotoxicity, is a useful and effective tool for study of AD-associated mechanisms and for development of highly selective therapy of cholinergic malfunctioning in AD patients.

Immunization with Small Amyloid-β-derived Cyclopeptide Conjugates Diminishes Amyloid-β-Induced Neurodegeneration in Mice. - Mulder, Cornelis K; Dong, Yun; Brugghe, Humphrey F; Timmermans, Hans A M; Tilstra, Wichard; Westdijk, Janny; van Riet, Elly; van Steeg, Harry; Hoogerhout, Peter; Eisel, Ulrich L M (J Alzheimers Dis, 2016)
BACKGROUND: Soluble oligomeric (misfolded) species of amyloid-β (Aβ) are the main mediators of toxicity in Alzheimer's disease (AD). These oligomers subsequently form aggregates of insoluble fibrils that precipitate as extracellular and perivascular plaques in the brain. Active immunization against Aβ is a promising disease modifying strategy. However, eliciting an immune response against Aβ in general may interfere with its biological function and was shown to cause unwanted side-effects. Therefore, we have developed a novel experimental vaccine based on conformational neo-epitopes that are exposed in the misfolded oligomeric Aβ, inducing a specific antibody response. OBJECTIVE: Here we investigate the protective effects of the experimental vaccine against oligomeric Aβ1-42-induced neuronal fiber loss in vivo. METHODS: C57BL/6 mice were immunized or mock-immunized. Antibody responses were measured by enzyme-linked immunosorbent assay. Next, mice received a stereotactic injection of oligomeric Aβ1-42 into the nucleus basalis of Meynert (NBM) on one side of the brain (lesion side), and scrambled Aβ1-42 peptide in the contralateral NBM (control side). The densities of choline acetyltransferase-stained cholinergic fibers origination from the NBM were measured in the parietal neocortex postmortem. The percentage of fiber loss in the lesion side was determined relative to the control side of the brain. RESULTS: Immunized responders (79%) showed 23% less cholinergic fiber loss (p = 0.01) relative to mock-immunized mice. Moreover, fiber loss in immunized responders correlated negatively with the measured antibody responses (R2 = 0.29, p = 0.02). CONCLUSION: These results may provide a lead towards a (prophylactic) vaccine to prevent or at least attenuate (early onset) AD symptoms.

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

Intraneuronal Amylin Deposition, Peroxidative Membrane Injury and Increased IL-1β Synthesis in Brains of Alzheimer's Disease Patients with Type-2 Diabetes and in Diabetic HIP Rats. - Verma, Nirmal; Ly, Han; Liu, Miao; Chen, Jing; Zhu, Haining; Chow, Martin; Hersh, Louis B; Despa, Florin (J Alzheimers Dis, 2016)
Amylin is a hormone synthesized and co-secreted with insulin by pancreatic β-cells that crosses the blood-brain barrier and regulates satiety. Amylin from humans (but not rodents) has an increased propensity to aggregate into pancreatic islet amyloid deposits that contribute to β-cell mass depletion and development of type-2 diabetes by inducing oxidative stress and inflammation. Recent studies demonstrated that aggregated amylin also accumulates in brains of Alzheimer's disease (AD) patients, preponderantly those with type-2 diabetes. Here, we report that, in addition to amylin plaques and mixed amylin-Aβ deposits, brains of diabetic patients with AD show amylin immunoreactive deposits inside the neurons. Neuronal amylin formed adducts with 4-hydroxynonenal (4-HNE), a marker of peroxidative membrane injury, and increased synthesis of the proinflammatory cytokine interleukin (IL)-1β. These pathological changes were mirrored in rats expressing human amylin in pancreatic islets (HIP rats) and mice intravenously injected with aggregated human amylin, but not in hyperglycemic rats secreting wild-type non-amyloidogenic rat amylin. In cultured primary hippocampal rat neurons, aggregated amylin increased IL-1β synthesis via membrane destabilization and subsequent generation of 4-HNE. These effects were blocked by membrane stabilizers and lipid peroxidation inhibitors. Thus, elevated circulating levels of aggregated amylin negatively affect the neurons causing peroxidative membrane injury and aberrant inflammatory responses independent of other confounding factors of diabetes. The present results are consistent with the pathological role of aggregated amylin in the pancreas, demonstrate a novel contributing mechanism to neurodegeneration, and suggest a direct, potentially treatable link of type-2 diabetes with AD.

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

A Late Life Risk Index for Severe Cognitive Impairment in Mexico. - Downer, Brian; Veeranki, Sreenivas P; Wong, Rebeca (J Alzheimers Dis, 2016)
BACKGROUND: Several dementia risk indices have been developed for older adults in high-income countries. However, no index has been developed for populations in low- or middle-income countries. OBJECTIVE: To create a risk index for predicting severe cognitive impairment among adults aged ≥60 in Mexico and to compare the accuracy of this index to the Dementia Screening Indicator (DSI). METHODS: This study included 3,002 participants from the Mexican Health and Aging Study (MHAS) interviewed in 2001 and 2012. The MHAS risk index included sociodemographic, health, and functional characteristics collected in 2001. A point value based on the beta coefficients from a multivariable logistic regression model was assigned to each risk factor and the total score was calculated. RESULTS: The MHAS risk index (AUC = 0.74 95% CI = 0.70-0.77) and DSI (AUC = 0.72 95% CI = 0.69-0.77) had similar accuracy for discriminating between participants who developed severe cognitive impairment from those who did not. A score of ≥16 on the MHAS risk index had a sensitivity of 0.69 (95% CI = 0.64-0.70) and specificity of 0.67 (95% CI = 0.66-0.69). A score of ≥23 on the DSI had a sensitivity of 0.56 (95% CI = 0.50-0.63) and specificity of 0.78 (95% CI = 0.76-0.79). DISCUSSION: The MHAS risk index and DSI have moderate accuracy for predicting severe cognitive impairment among older adults in Mexico. This provides evidence that existing dementia risk indices may be applicable in low- and middle-income countries such as Mexico. Future research should seek to identify additional risk factors that can improve the accuracy of the MHAS risk index.
Keywords: Age Factors; Aged; Cognitive Dysfunction; Female; Humans; Life Style; Logistic Models; Longitudinal Studies; Male; Mexico; Middle Aged; Multivariate Analysis; Risk Factors; Social Behavior; Socioeconomic Factors

Longitudinal Changes in Functional Brain Connectivity Predicts Conversion to Alzheimer's Disease. - Serra, Laura; Cercignani, Mara; Mastropasqua, Chiara; Torso, Mario; Spanò, Barbara; Makovac, Elena; Viola, Vanda; Giulietti, Giovanni; Marra, Camillo; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
This longitudinal study investigates the modifications in structure and function occurring to typical Alzheimer's disease (AD) brains over a 2-year follow-up, from pre-dementia stages of disease, with the aim of identifying biomarkers of prognostic value. Thirty-one patients with amnestic mild cognitive impairment were recruited and followed-up with clinical, neuropsychological, and MRI assessments. Patients were retrospectively classified as AD Converters or Non-Converters, and the data compared between groups. Cross-sectional MRI data at baseline, assessing volume and functional connectivity abnormalities, confirmed previous findings, showing a more severe pattern of regional grey matter atrophy and default-mode network disconnection in Converters than in Non-Converters. Longitudinally, Converters showed more grey matter atrophy in the frontotemporal areas, accompanied by increased connectivity in the precuneus. Discriminant analysis revealed that functional connectivity of the precuneus within the default mode network at baseline is the parameter able to correctly classify patients in Converters and Non-Converters with high sensitivity, specificity, and accuracy.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Cognitive Dysfunction; Cross-Sectional Studies; Discriminant Analysis; Disease Progression; Female; Follow-Up Studies; Gray Matter; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neural Pathways; Neuropsychological Tests; Prognosis; Rest

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

Low Serum Insulin-Like Growth Factor-I Predicts Cognitive Decline in Alzheimer's Disease. - Vidal, Jean-Sébastien; Hanon, Olivier; Funalot, Benoît; Brunel, Nadège; Viollet, Cécile; Rigaud, Anne-Sophie; Seux, Marie-Laure; le-Bouc, Yves; Epelbaum, Jacques; Duron, Emmanuelle (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between the insulin-like growth factor-I (IGF-I) system and Alzheimer's disease (AD) is mostly based on transversal studies. It remains, however, to demonstrate whether IGF-I is associated with cognitive decline over time in AD. OBJECTIVE: The objective of the study was to analyze the course of cognitive decline of AD subjects over a 24-month period in relation to serum IGF-I and insulin-like growth factor binding protein-3 (IGFBP-3) measured at baseline. METHODS: Data are from the SIGAL follow-up study. IGF-I and IGFBP-3 were measured in AD subjects who performed a Mini-Mental State Examination (MMSE) every 6 months for 2 years. MMSE course was analyzed using a mixed model with random intercept and slope function. RESULTS: Among the 200 AD participants, 146 (mean age = 81.1 (standard deviation (SD) = 5.9) years, 62.6% of women) had at least one follow-up visit. Mean IGF-I at baseline was 147.8 (74.2) ng/mL. Hundred forty-six participants (62.6%) had at least one follow-up visit. Mean MMSE was 21.7 (4.7)/30 and dropped on average by 2.28 points per year. MMSE decline was steeper among participants with lower IGF-I. For each decrease of 1 SD of IGF-I, subjects lost an additional 0.63 points per year in MMSE, e.g., participants with IGF-I level of 74 ng/mL lost 2.91 MMSE points per year whereas participants with IGF-I of 222 ng/mL lost 1.65 MMSE points per year. There was no association between IGFBP-3 and cognitive decline. CONCLUSION: Lower baseline serum IGF-I was associated with faster cognitive decline in AD over a 2-year period.

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

Metallothioneins in Prion- and Amyloid-Related Diseases. - Adam, Pavlína; Křížková, Soňa; Heger, Zbyněk; Babula, Petr; Pekařík, Vladimír; Vaculovičoá, Markéta; Gomes, Cláudio M; Kizek, René; Adam, Vojtěch (J Alzheimers Dis, 2016)
Prion and other amyloid-forming diseases represent a group of neurodegenerative disorders that affect both animals and humans. The role of metal ions, especially copper and zinc is studied intensively in connection with these diseases. Their involvement in protein misfolding and aggregation and their role in creation of reactive oxygen species have been shown. Recent data also show that metal ions not only bind the proteins with high affinity, but also modify their biochemical properties, making them important players in prion-related diseases. In particular, the level of zinc ions is tightly regulated by several mechanisms, including transporter proteins and the low molecular mass thiol-rich metallothioneins. From four metallothionein isoforms, metallothionein-3, a unique brain-specific metalloprotein, plays a crucial role only in this regulation. This review critically evaluates the involvement of metallothioneins in prion- and amyloid-related diseases in connection with the relationship between metallothionein isoforms and metal ion regulation of their homeostasis.
Keywords: Amyloidosis; Animals; Brain Diseases; Humans; Metallothionein; Prion Diseases

Midlife Physical Activity and Cognition Later in Life: A Prospective Twin Study. - Iso-Markku, Paula; Waller, Katja; Vuoksimaa, Eero; Heikkilä, Kauko; Rinne, Juha; Kaprio, Jaakko; Kujala, Urho M (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity has been associated with a reduced risk of cognitive decline but the nature of this association remains obscure. OBJECTIVE: To study associations between midlife physical activity and cognition in old age for a prospective cohort of Finnish twins. METHODS: Physical activity in the Finnish Twin Cohort was assessed using questionnaire responses collected in 1975 and 1981. After a mean follow-up of 25.1 years, the subjects' (n = 3050; mean age 74.2; range 66-97) cognition was evaluated with a validated telephone interview. Both participation in vigorous physical activity, and the volume of physical activity, divided into quintiles, were used as predictors of cognitive impairment. Metrics collected by TELE were used to categorize participants as: cognitively impaired, suffering mild cognitive impairment, or cognitively healthy. RESULTS: Participation in vigorous physical activity compared to non-participation for both 1975 and 1981 was associated with a lower risk of cognitive impairment in individual-based analyses (fully adjusted OR 0.50, 95% CI 0.35-0.73). Pairwise analyses yielded similar but statistically non-significant associations. In terms of the volume of physical activity, the most active quintile of individuals (OR 0.69, 95% CI 0.46-1.04) had a reduced risk of cognitive decline compared with the most sedentary quintile in the fully adjusted model although no clear dose-response was found. CONCLUSION: Vigorous midlife physical activity was associated with less cognitive impairment but without a clear dose-response association between the volume of physical activity and cognition.

Moderate-to-High Intensity Physical Exercise in Patients with Alzheimer's Disease: A Randomized Controlled Trial. - Hoffmann, Kristine; Sobol, Nanna A; Frederiksen, Kristian S; Beyer, Nina; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jacobsen, Søren; Laugesen, Lars P; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Studies of physical exercise in patients with Alzheimer's disease (AD) are few and results have been inconsistent. OBJECTIVE: To assess the effects of a moderate-to-high intensity aerobic exercise program in patients with mild AD. METHODS: In a randomized controlled trial, we recruited 200 patients with mild AD to a supervised exercise group (60-min sessions three times a week for 16 weeks) or to a control group. Primary outcome was changed from baseline in cognitive performance estimated by Symbol Digit Modalities Test (SDMT) in the intention-to-treat (ITT) group. Secondary outcomes included changes in quality of life, ability to perform activities of daily living, and in neuropsychiatric and depressive symptoms. RESULTS: The ITT analysis showed no significant differences between intervention and control groups in change from baseline of SDMT, other cognitive tests, quality of life, or activities of daily living. The change from baseline in Neuropsychiatric Inventory differed significantly in favor of the intervention group (mean: -3.5, 95% confidence interval (CI) -5.8 to -1.3, p = 0.002). In subjects who adhered to the protocol, we found a significant effect on change from baseline in SDMT as compared with the control group (mean: 4.2, 95% CI 0.5 to 7.9, p = 0.028), suggesting a dose-response relationship between exercise and cognition. CONCLUSIONS: This is the first randomized controlled trial with supervised moderate-to-high intensity exercise in patients with mild AD. Exercise reduced neuropsychiatric symptoms in patients with mild AD, with possible additional benefits of preserved cognition in a subgroup of patients exercising with high attendance and intensity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Depression; Exercise; Exercise Therapy; Female; Humans; Male; Middle Aged; Quality of Life; Treatment Outcome

Monitoring Blood-Brain Barrier Integrity Following Amyloid-β Immunotherapy Using Gadolinium-Enhanced MRI in a PDAPP Mouse Model. - Blockx, Ines; Einstein, Steve; Guns, Pieter-Jan; Van Audekerke, Johan; Guglielmetti, Caroline; Zago, Wagner; Roose, Dimitri; Verhoye, Marleen; Van der Linden, Annemie; Bard, Frederique (J Alzheimers Dis, 2016)
BACKGROUND: Amyloid-related imaging abnormalities (ARIA) have been reported with some anti-amyloid-β (Aβ) immunotherapy trials. They are detected with magnetic resonance imaging (MRI) and thought to represent transient accumulation of fluid/edema (ARIA-E) or microhemorrhages (ARIA-H). Although the clinical significance and pathophysiology are unknown, it has been proposed that anti-Aβimmunotherapy may affect blood-brain barrier (BBB) integrity. OBJECTIVE: To examine vascular integrity in aged (12-16 months) PDAPP and wild type mice (WT), we performed a series of longitudinal in vivo MRI studies. METHODS: Mice were treated on a weekly basis using anti-Aβimmunotherapy (3D6) and follow up was done longitudinally from 1-12 weeks after treatment. BBB-integrity was assessed using both visual assessment of T1-weighted scans and repeated T1 mapping in combination with gadolinium (Gd-DOTA). RESULTS: A subset of 3D6 treated PDAPP mice displayed numerous BBB disruptions, whereas WT and saline-treated PDAPP mice showed intact BBB integrity under the conditions tested. In addition, the contrast induced decrease in T1 value was observed in the meningeal and midline area. BBB disruption events occurred early during treatment (between 1 and 5 weeks), were transient, and resolved quickly. Finally, BBB-leakages associated with microhemorrhages were confirmed by Perls'Prussian blue histopathological analysis. CONCLUSION: Our preclinical findings support the hypothesis that 3D6 leads to transient leakage from amyloid-positive vessels. The current study has provided valuable insights on the time course of vascular alterations during immunization treatment and supports further research in relation to the nature of ARIA and the utility of in vivo repeated T1 MRI as a translational tool.

Monophosphoryl Lipid-A: A Promising Tool for Alzheimer's Disease Toll. - Rego, Ângela; Viana, Sofia D; Ribeiro, Carlos A Fontes; Rodrigues-Santos, Paulo; Pereira, Frederico C (J Alzheimers Dis, 2016)
Neuroinflammation is a two-edged sword in Alzheimer's disease (AD). A certain degree of neuroinflammation is instrumental in the clearance of amyloid-β (Aβ) peptides by activated microglia, although a sustained neuroinflammation might accelerate Aβ deposition, thus fostering the neurodegenerative process and functional decline in AD. There is an increasing body of evidence suggesting that the innate immune system via Toll-like receptor 4 (TLR4) finely orchestrates the highly regulated inflammatory cascade that takes place in AD pathology. Herein we critically review pre-clinical (in vitro and in vivo approaches) and clinical studies showing that monophosphoryl lipid A (MPL), a partial TLR4 agonist, may have beneficial effect on AD physiopathology. The in vivo data elegantly showed that MPL enhanced Aβ plaque phagocytosis thus decreasing the number and the size of Aβ deposits and soluble Aβ in brain from APPswe/PS1 mice. Furthermore, MPL also improved their cognition. The mechanism underlying this MPL effect was proposed to be microglial activation by recruiting TLR4. Additionally, it was demonstrated that MPL increased the Aβ antibody titer and showed a safe profile in mice and primates, when used as a vaccine adjuvant. Clinical studies using MPL as an adjuvant in Aβ immunotherapy are currently ongoing. Overall, we argue that the TLR4 partial agonist MPL is a potentially safe and effective new pharmacological tool in AD.

Motoric Cognitive Risk Syndrome and Falls Risk: A Multi-Center Study. - Callisaya, Michele L; Ayers, Emmeline; Barzilai, Nir; Ferrucci, Luigi; Guralnik, Jack M; Lipton, Richard B; Otahal, Petr; Srikanth, Velandai K; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The Motoric Cognitive Risk Syndrome (MCR) is characterized by slow gait speed and cognitive complaints. OBJECTIVES: The objective of this study was to determine if the presence of MCR increases the risk of falls in older people. METHODS: Individual participant data (n = 6,204) from five longitudinal studies from three countries were used for this analysis. MCR diagnosis was defined as both the presence of objectively measured slow gait speed and subjective cognitive complaints in those without dementia or mobility disability. Falls were prospectively ascertained using phone calls or questionnaires. Log binomial regression was performed to determine if MCR increased the risk of falls separately in each cohort. Random effects meta-analysis was used to pool results from all cohorts. RESULTS: The mean age of participants was 74.9 (SD 6.8) years and 44% (n = 2728) were male. Overall 33.9% (n = 2104) reported a fall over follow-up. Pooled relative risk of MCR with any falls was RR 1.44 95% CI 1.16, 1.79. The components of MCR, slow gait (RR 1.30 95% CI 1.14, 1.47) and cognitive complaint (RR 1.25, 95% CI 1.07, 1.46) were also associated with an increased risk of any falls. In sub-analyses MCR was associated with any fall independent of previous falls (RR 1.29 95% CI 1.09, 1.53) and with multiple falls (RR 1.77, 95% CI 1.25, 2.51). CONCLUSION: MCR is associated with an increased risk of falls. The increase in risk was higher than for its individual components. The simplicity of the MCR makes it an attractive falls risk screening tool for the clinic.

Netrin-1 Interrupts Amyloid-β Amplification, Increases sAβPPα in vitro and in vivo, and Improves Cognition in a Mouse Model of Alzheimer's Disease. - Spilman, Patricia R; Corset, Veronique; Gorostiza, Olivia; Poksay, Karen S; Galvan, Veronica; Zhang, Junli; Rao, Rammohan; Peters-Libeu, Clare; Vincelette, Jon; McGeehan, Andrew; Dvorak-Ewell, Melita; Beyer, Janine; et al. (J Alzheimers Dis, 2016)
Recent studies have shown that inoculation of susceptible mice with amyloid-β (Aβ) peptides accelerates Aβ deposition in the brain, supporting the idea that Aβ may be self-amplifying; however, the exact mechanism is not understood. Here we provide evidence that Aβ may self-amplify, in part, by inhibiting α-secretase ADAM10 (a disintegrin and metalloprotease) cleavage of full-length Aβ precursor protein (FL AβPP) and therefore allow greater β-secretase processing, and that Aβ itself is a substrate for ADAM10. Exposure of primary neuronal cultures from PDAβPP mice to exogenous rat Aβ1- 40 resulted in increased de novo human Aβ1-42 production and exposure of cells to Aβ decreased production of ADAM10 cleavage product soluble AβPPα (sAβPPα). In a cell-free assay, Aβ decreased ADAM10 cleavage of the chimeric substrate MBP-AβPPC125 and Aβ itself was apparently cleaved by the enzyme. The axonal guidance and trophic factor netrin-1, however, reduced the Aβ1- 40-induced Aβ1-42 increase, increased sAβPPα, and reversed the Aβ-induced sAβPPα decrease in vitro. In vivo, induction of netrin-1 expression in PDAβPPSwe/Ind transgenic mice resulted in reductions in both Aβ1-42 and Aβ1- 40, and ICV delivery of netrin-1 to PDAβPPSwe/Ind mice increased sAβPPα, decreased Aβ, and improved working memory. Finally, to support further study of netrin-1's potential as a therapeutic for Alzheimer's disease, pilot gene therapy studies were performed and a netrin mimetic peptide synthesized and tested that, like netrin, can increase sAβPPα and decrease Aβ1-42in vitro. Taken together, these data provide mechanistic insights into Aβ self-amplification and the ability of netrin-1 to disrupt it.

Neuroimaging Correlates of Frontotemporal Dementia Associated with SQSTM1 Mutations. - Luis, Elkin; Ortiz, Alexandra; Eudave, Luis; Ortega-Cubero, Sara; Borroni, Barbara; van der Zee, Julie; Gazzina, Stefano; Caroppo, Paola; Rubino, Elisa; D'Agata, Federico; Le Ber, Isabelle; Santana, Isabel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Frontotemporal lobar degeneration (FTLD) is a progressive dementia characterized by focal atrophy of frontal and/or temporal lobes caused by mutations in the gene coding for sequestosome 1 (SQSTM1), among other genes. Rare SQSTM1 gene mutations have been associated with Paget's disease of bone, amyotrophic lateral sclerosis, and, more recently, frontotemporal lobar degeneration (FTLD). OBJECTIVE: The aim of the study was to determine whether a characteristic pattern of grey and white matter loss is associated with SQSTM1 dysfunction. METHODS: We performed a voxel-based morphometry (VBM) study in FTD subjects carrying SQSTM1 pathogenic variants (FTD/SQSTM1 mutation carriers; n = 10), compared with FTD subjects not carrying SQSTM1 mutations (Sporadic FTD; n = 20) and healthy controls with no SQSTM1 mutations (HC/SQSTM1 noncarriers; n = 20). The groups were matched according to current age, disease duration, and gender. RESULTS: After comparing FTD/SQSTM1 carriers with Sporadic FTD, a predominantly right cortical atrophy pattern was localized in the inferior frontal, medial orbitofrontal, precentral gyri, and the anterior insula. White matter atrophy was found in both medial and inferior frontal gyri, pallidum, and putamen. FTD/SQSTM1 carriers compared with HC/SQSTM1 noncarriers showed atrophy at frontal, temporal, and parietal lobes of both hemispheres whereas the MRI pattern found in Sporadic FTD compared with controls was frontal and left temporal lobe atrophy, extending toward parietal and occipital lobes of both hemispheres. CONCLUSIONS: These results suggest that fronto-orbito-insular regions including corticospinal projections as described in ALS are probably more susceptible to the damaging effect of SQSTM1 mutations delineatinga specific gene-linked atrophy pattern.

Non-Fibrillar Oligomeric Amyloid-β within Synapses. - Pickett, Eleanor K; Koffie, Robert M; Wegmann, Susanne; Henstridge, Christopher M; Herrmann, Abigail G; Colom-Cadena, Marti; Lleo, Alberto; Kay, Kevin R; Vaught, Melissa; Soberman, Roy; Walsh, Dominic M; Hyman, Bradley T; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by memory loss, insidious cognitive decline, profound neurodegeneration, and the extracellular accumulation of amyloid-β (Aβ) peptide in senile plaques and intracellular accumulation of tau in neurofibrillary tangles. Loss and dysfunction of synapses are believed to underlie the devastating cognitive decline in AD. A large amount of evidence suggests that oligomeric forms of Aβ associated with senile plaques are toxic to synapses, but the precise sub-synaptic localization of Aβ and which forms are synaptotoxic remain unknown. Here, we characterize the sub-synaptic localization of Aβ oligomers using three high-resolution imaging techniques, stochastic optical reconstruction microscopy, immunogold electron microscopy, and Förster resonance energy transfer in a plaque-bearing mouse model of AD. With all three techniques, we observe oligomeric Aβ inside synaptic terminals. Further, we tested a panel of Aβ antibodies using the relatively high-throughput array tomography technique to determine which forms are present in synapses. Our results show that different oligomeric Aβ species are present in synapses and highlight the potential of array tomography for rapid testing of aggregation state specific Aβ antibodies in brain tissue.

Non-Verbal Episodic Memory Deficits in Primary Progressive Aphasias are Highly Predictive of Underlying Amyloid Pathology. - Ramanan, Siddharth; Flanagan, Emma; Leyton, Cristian E; Villemagne, Victor L; Rowe, Christopher C; Hodges, John R; Hornberger, Michael (J Alzheimers Dis, 2016)
Diagnostic distinction of primary progressive aphasias (PPA) remains challenging, in particular for the logopenic (lvPPA) and nonfluent/agrammatic (naPPA) variants. Recent findings highlight that episodic memory deficits appear to discriminate these PPA variants from each other, as only lvPPA perform poorly on these tasks while having underlying amyloid pathology similar to that seen in amnestic dementias like Alzheimer's disease (AD). Most memory tests are, however, language based and thus potentially confounded by the prevalent language deficits in PPA. The current study investigated this issue across PPA variants by contrasting verbal and non-verbal episodic memory measures while controlling for their performance on a language subtest of a general cognitive screen. A total of 203 participants were included (25 lvPPA; 29 naPPA; 59 AD; 90 controls) and underwent extensive verbal and non-verbal episodic memory testing, with a subset of patients (n = 45) with confirmed amyloid profiles as assessed by Pittsburgh Compound B and PET. The most powerful discriminator between naPPA and lvPPA patients was a non-verbal recall measure (Rey Complex Figure delayed recall), with 81% of PPA patients classified correctly at presentation. Importantly, AD and lvPPA patients performed comparably on this measure, further highlighting the importance of underlying amyloid pathology in episodic memory profiles. The findings demonstrate that non-verbal recall emerges as the best discriminator of lvPPA and naPPA when controlling for language deficits in high load amyloid PPA cases.
Keywords: Aged; Alzheimer Disease; Amyloid; Aniline Compounds; Aphasia, Primary Progressive; Brain; Diagnosis, Differential; Female; Humans; Logistic Models; Male; Memory, Episodic; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Speech Perception; Thiazoles

A Novel Liposomal Nanoparticle for the Imaging of Amyloid Plaque by Magnetic Resonance Imaging. - Tanifum, Eric A; Ghaghada, Ketan; Vollert, Craig; Head, Elizabeth; Eriksen, Jason L; Annapragada, Ananth (J Alzheimers Dis, 2016)
Amyloid binding molecules with greater hydrophilicity than existing ligands were synthesized. The lead candidate ET6-21 bound amyloid fibrils, and amyloid deposits in dog brain and human brain tissue ex vivo. The ligand was used to prepare novel amyloid-targeted liposomal nanoparticles. The preparation was tested in the Tg2576 and TetO/APP mouse models of amyloid deposition. Gd chelates and Indocyanine green were included in the particles for visualization by MRI and near-infrared microscopy. Upon intravenous injection, the particles successfully traversed the blood-brain barrier in these mice, and bound to the plaques. Magnetic resonance imaging (T1-MRI) conducted 4 days after injection demonstrated elevated signal in the brains of mice with amyloid plaques present. No signal was observed in amyloid-negative mice, or in amyloid-positive mice injected with an untargeted version of the same agent. The MRI results were confirmed by immunohistochemical and fluorescent microscopic examination of mouse brain sections, showing colocalization of the fluorescent tags and amyloid deposits.

Novel Mutation (Gly212Val) in the PS2 Gene Associated with Early-Onset Familial Alzheimer's Disease. - Marín-Muñoz, Juan; Noguera-Perea, Ma Fuensanta; Gómez-Tortosa, Estrella; López-Motos, David; Antequera-Torres, Martirio; Martínez-Herrada, Begoña; Manzanares-Sánchez, Salvadora; Vivancos-Moreau, Laura; Legaz-García, Agustina; Rábano-Gutiérrez Del Arroyo, Alberto; Antúnez-Almagro, Carmen (J Alzheimers Dis, 2016)
Mutations in the presenilin 2 gene (PS2) are an extremely rare cause of early-onset autosomal dominant Alzheimer's disease (AD), accounting for only 5% of these families. These cases represent a particular model of AD, and the scarcity of reports on their clinical phenotypes makes them of great interest. We report a family with early-onset autosomal dominant AD in four members, where the two living siblings were found to carry the novel PS2 mutation Gly212Val (exon 7, transmembrane domain IV) with highly predicted pathogenicity. Age at onset ranged from 60 to 65 years and three of the cases died between ages 74 and 76 years. Clinical phenotype was quite homogeneous among affected members of the family, and overall features, including cognitive decline, tau/p-tau and amyloid-β cerebrospinal fluid markers, neuroimaging, and neuropathology were consistent with typical AD. Lewy bodies were present but restricted to the amygdala.

Optimized Standard Operating Procedures for the Analysis of Cerebrospinal Fluid Aβ42 and the Ratios of Aβ Isoforms Using Low Protein Binding Tubes. - Vanderstichele, Hugo Marcel Johan; Janelidze, Shorena; Demeyer, Leentje; Coart, Els; Stoops, Erik; Herbst, Victor; Mauroo, Kimberley; Brix, Britta; Hansson, Oskar (J Alzheimers Dis, 2016)
BACKGROUND: Reduced cerebrospinal fluid (CSF) concentration of amyloid-β1-42 (Aβ1-42) reflects the presence of amyloidopathy in brains of subjects with Alzheimer's disease (AD). OBJECTIVE: To qualify the use of Aβ1-42/Aβ1-40 for improvement of standard operating procedures (SOP) for measurement of CSF Aβ with a focus on CSF collection, storage, and analysis. METHODS: Euroimmun ELISAs for CSF Aβ isoforms were used to set up a SOP with respect to recipient properties (low binding, polypropylene), volume of tubes, freeze/thaw cycles, addition of detergents (Triton X-100, Tween-20) in collection or storage tubes or during CSF analysis. Data were analyzed with linear repeated measures and mixed effects models. RESULTS: Optimization of CSF analysis included a pre-wash of recipients (e.g., tubes, 96-well plates) before sample analysis. Using the Aβ1-42/Aβ1-40 ratio, in contrast to Aβ1-42, eliminated effects of tube type, additional freeze/thaw cycles, or effect of CSF volumes for polypropylene storage tubes. 'Low binding' tubes reduced the loss of Aβ when aliquoting CSF or in function of additional freeze/thaw cycles. Addition of detergent in CSF collection tubes resulted in an almost complete absence of variation in function of collection procedures, but affected the concentration of Aβ isoforms in the immunoassay. CONCLUSION: The ratio of Aβ1-42/Aβ1-40 is a more robust biomarker than Aβ1-42 toward (pre-) analytical interfering factors. Further, 'low binding' recipients and addition of detergent in collection tubes are able to remove effects of SOP-related confounding factors. Integration of the Aβ1-42/Aβ1-40 ratio and 'low-binding tubes' into guidance criteria may speed up worldwide standardization of CSF biomarker analysis.

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Performance Evaluation of an Automated ELISA System for Alzheimer's Disease Detection in Clinical Routine. - Chiasserini, Davide; Biscetti, Leonardo; Farotti, Lucia; Eusebi, Paolo; Salvadori, Nicola; Lisetti, Viviana; Baschieri, Francesca; Chipi, Elena; Frattini, Giulia; Stoops, Erik; Vanderstichele, Hugo; Calabresi, Paolo; et al. (J Alzheimers Dis, 2016)
The variability of Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers undermines their full-fledged introduction into routine diagnostics and clinical trials. Automation may help to increase precision and decrease operator errors, eventually improving the diagnostic performance. Here we evaluated three new CSF immunoassays, EUROIMMUNtrademark amyloid-β 1-40 (Aβ1-40), amyloid-β 1-42 (Aβ1-42), and total tau (t-tau), in combination with automated analysis of the samples. The CSF biomarkers were measured in a cohort consisting of AD patients (n = 28), mild cognitive impairment (MCI, n = 77), and neurological controls (OND, n = 35). MCI patients were evaluated yearly and cognitive functions were assessed by Mini-Mental State Examination. The patients clinically diagnosed with AD and MCI were classified according to the CSF biomarkers profile following NIA-AA criteria and the Erlangen score. Technical evaluation of the immunoassays was performed together with the calculation of their diagnostic performance. Furthermore, the results for EUROIMMUN Aβ1-42 and t-tau were compared to standard immunoassay methods (INNOTESTtrademark). EUROIMMUN assays for Aβ1-42 and t-tau correlated with INNOTEST (r = 0.83, p < 0.001 for both) and allowed a similar interpretation of the CSF profiles. The Aβ1-42/Aβ1-40 ratio measured with EUROIMMUN was the best parameter for AD detection and improved the diagnostic accuracy of Aβ1-42 (area under the curve = 0.93). In MCI patients, the Aβ1-42/Aβ1-40 ratio was associated with cognitive decline and clinical progression to AD.The diagnostic performance of the EUROIMMUN assays with automation is comparable to other currently used methods. The variability of the method and the value of the Aβ1-42/Aβ1-40 ratio in AD diagnosis need to be validated in large multi-center studies.

Pharmacological Modulations of the Serotonergic System in a Cell-Model of Familial Alzheimer's Disease. - Tajeddinn, Walid; Persson, Torbjörn; Calvo-Garrido, Javier; Seed Ahmed, Mohammed; Maioli, Silvia; Vijayaraghavan, Swetha; Kazokoglu, Mehmet Selim; Parrado-Fernández, Cristina; Yoshitake, Takashi; Kehr, Jan; Francis, Paul; Winblad, Bengt; et al. (J Alzheimers Dis, 2016)
Serotonin (5-HT) plays a central role in the integrity of different brain functions. The 5-HT homeostasis is regulated by many factors, including serotonin transporter (SERT), monoamine oxidase enzyme (MAO), and several 5-HT receptors, including the 5-HT1B. There is little knowledge how the dynamics of this system is affected by the amyloid-β (Aβ) burden of Alzheimer's disease (AD) pathology. SH-SY5Y neuroblastoma cells transfected with the amyloid precursor protein (APP) gene containing the Swedish mutations causing familial AD (APPswe), were used as a model to explore the effect of Aβ pathology on 5-HT1B and related molecules including the receptor adaptor protein (p11), SERT and MAOA gene expression, and MAOA activity after treatment with selective serotonin reuptake inhibitor (SSRI) (sertraline), and a 5-HT1B receptor antagonist. Sertraline led more than 70 fold increase of 5-HT1B gene expression (p < 0.001), an increased serotonin turnover in both APPswe and control cells and reduced intracellular serotonin levels by 75% in APPswe cells but not in controls (p > 0.05). Treatment with the 5-HT1B receptor antagonist increased SERT gene-expression in control cells but not in the APPswe cells. 5-HT and 5-HT1B antagonist treatment resulted in different p11 expression patterns in APPswe cells compared to controls. Although MAOA gene expression was not changed by APPswe overexpression, adding 5-HT lead to a significant increase in MAOA gene expression in APPswe but not control cells. These findings suggest that the sensitivity of the 5-HT1B receptor and related systems is affected by APPswe overexpression, with potential relevance for pharmacologic intervention in AD. This may at least partly explain the lack of effect of SSRIs in patients with AD and depression.

A Phase IIa Randomized Control Trial of VEL015 (Sodium Selenate) in Mild-Moderate Alzheimer's Disease. - Malpas, Charles B; Vivash, Lucy; Genc, Sila; Saling, Michael M; Desmond, Patricia; Steward, Christopher; Hicks, Rodney J; Callahan, Jason; Brodtmann, Amy; Collins, Steven; Macfarlane, Stephen; Corcoran, Niall M; et al. (J Alzheimers Dis, 2016)
BACKGROUND: There is increasing interest in targeting hyperphosphorylated tau (h-tau) as a disease modifying approach for Alzheimer's disease (AD). Sodium selenate directly stimulates the activity of PP2A, the main enzyme responsible for h-tau dephosphorylation in the brain. OBJECTIVE: This study assessed the safety and tolerability of 24-week treatment with VEL015 (sodium selenate) in AD. Investigating the effects of VEL015 on cognitive, CSF, and neuroimaging biomarkers of AD were secondary, exploratory objectives. Data were used to identify biomarkers showing most promise for use in subsequent efficacy trials. METHODS: A 24-week, multicenter, Phase IIa, double-blinded randomized controlled trial. Forty patients aged ≥55 y with mild-moderate AD (MMSE 14-26) were randomized to supranutritional (VEL015 10 mg tds [n = 20]) and control (VEL015 320μg tds [n = 10] or placebo [n = 10]) groups. Patients were regularly monitored for safety, adverse events (AEs), and protocol compliance. Exploratory biomarkers included cognitive tests, neuroimaging (diffusion MR), and CSF (p-tau, t-tau, and Aβ1-42). RESULTS: Thirty-six (90%; [supranutritional n = 18, control/placebo n = 18]) patients completed the trial. There were no differences in the incidence of specific AEs between groups. Only one secondary biomarker, diffusion MR measures, showed group differences, with less deterioration in the supranutritional group (p < 0.05). CONCLUSION: Treatment with VEL015 at doses up to 30 mg per day for 24 weeks was safe and well-tolerated in patients with AD. Diffusion MR measures appear to be the most sensitive biomarkers to assess disease progression over 24 weeks.

Primary Progressive Aphasia in the Network of French Alzheimer Plan Memory Centers. - Magnin, Eloi; Démonet, Jean-François; Wallon, David; Dumurgier, Julien; Troussière, Anne-Cécile; Jager, Alain; Duron, Emmanuelle; Gabelle, Audrey; de la Sayette, Vincent; Volpe-Gillot, Lisette; Tio, Gregory; Evain, Sarah; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Few demographical data about primary progressive aphasia (PPA) are available, and most knowledge regarding PPA is based on tertiary centers' results. OBJECTIVE: Our aims were to describe demographical characteristics of the PPA population in a large sample of PPA patients from the network of French Alzheimer plan memory centers (Sample 1), and to describe the stratification of cerebrospinal fluid (CSF) biomarkers in two different samples of PPA patients (Samples 2 and 3). METHODS: All registered PPA patients in the French Alzheimer's disease (AD) databank (Sample 1: n = 2,035) and a subsample (Sample 2: n = 65) derived from a multicentric prospective cohort with CSF biomarker analysis were analyzed. A multicentric retrospective cohort from language expert tertiary centers (Sample 3: n = 97) with CSF biomarker analysis was added. Sample 3 was added to replicate the CSF results of the Sample 2 and to evaluate repartition of AD pathology in the three variant of PPA according to the latest classification. RESULTS: Non-Fluent/Agrammatic, Logopenic, and Unclassifiable PPA patients (NF/A-Logo-Unclass PPA) were older and more frequent than Semantic PPA patients (2.2 versus 0.8/100,000 inhabitants; p < 0.00001). Male predominance occurred after the age of 80 (p < 0.00001). A higher level of education was observed in the PPA population compared to a typical amnesic AD group. No demographical significant difference between PPA due to AD and not due to AD was observed. The Logopenic variant was most frequent with 85% of AD CSF biomarker profiles (35% in NF/A PPA; 20% in Semantic PPA). CONCLUSION: PPA occurs also in an elderly population, especially in male patients over 80. CSF biomarkers are useful to stratify PPA. The epidemiology of PPA should be further investigated to confirm gender and cognitive reserve role in PPA to better understand the factors and mechanisms leading to this language-predominant deficit during neurodegenerative diseases.

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins

Protein Kinase Activity Decreases with Higher Braak Stages of Alzheimer's Disease Pathology. - Rosenberger, Andrea F N; Hilhorst, Riet; Coart, Elisabeth; García Barrado, Leandro; Naji, Faris; Rozemuller, Annemieke J M; van der Flier, Wiesje M; Scheltens, Philip; Hoozemans, Jeroen J M; van der Vies, Saskia M (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by a long pre-clinical phase (20-30 years), during which significant brain pathology manifests itself. Disease mechanisms associated with pathological hallmarks remain elusive. Most processes associated with AD pathogenesis, such as inflammation, synaptic dysfunction, and hyper-phosphorylation of tau are dependent on protein kinase activity. The objective of this study was to determine the involvement of protein kinases in AD pathogenesis. Protein kinase activity was determined in postmortem hippocampal brain tissue of 60 patients at various stages of AD and 40 non-demented controls (Braak stages 0-VI) using a peptide-based microarray platform. We observed an overall decrease of protein kinase activity that correlated with disease progression. The phosphorylation of 96.7% of the serine/threonine peptides and 37.5% of the tyrosine peptides on the microarray decreased significantly with increased Braak stage (p-value <0.01). Decreased activity was evident at pre-clinical stages of AD pathology (Braak I-II). Increased phosphorylation was not observed for any peptide. STRING analysis in combination with pathway analysis and identification of kinases responsible for peptide phosphorylation showed the interactions between well-known proteins in AD pathology, including the Ephrin-receptor A1 (EphA1), a risk gene for AD, and sarcoma tyrosine kinase (Src), which is involved in memory formation. Additionally, kinases that have not previously been associated with AD were identified, e.g., protein tyrosine kinase 6 (PTK6/BRK), feline sarcoma oncogene kinase (FES), and fyn-associated tyrosine kinase (FRK). The identified protein kinases are new biomarkers and potential drug targets for early (pre-clinical) intervention.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Female; Hippocampus; Humans; Male; Middle Aged; Phosphorylation; Protein Kinases; Protein-Serine-Threonine Kinases; Severity of Illness Index

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

A Qualitative Impairment in Face Perception in Alzheimer's Disease: Evidence from a Reduced Face Inversion Effect. - Lavallée, Marie Maxime; Gandini, Delphine; Rouleau, Isabelle; Vallet, Guillaume T; Joannette, Maude; Kergoat, Marie-Jeanne; Busigny, Thomas; Rossion, Bruno; Joubert, Sven (J Alzheimers Dis, 2016)
Prevalent face recognition difficulties in Alzheimer's disease (AD) have typically been attributed to the underlying episodic and semantic memory impairment. The aim of the current study was to determine if AD patients are also impaired at the perceptual level for faces, more specifically at extracting a visual representation of an individual face. To address this question, we investigated the matching of simultaneously presented individual faces and of other nonface familiar shapes (cars), at both upright and inverted orientation, in a group of mild AD patients and in a group of healthy older controls matched for age and education. AD patients showed a reduced inversion effect (i.e., larger performance for upright than inverted stimuli) for faces, but not for cars, both in terms of error rates and response times. While healthy participants showed a much larger decrease in performance for faces than for cars with inversion, the inversion effect did not differ significantly for faces and cars in AD. This abnormal inversion effect for faces was observed in a large subset of individual patients with AD. These results suggest that AD patients have deficits in higher-level visual processes, more specifically at perceiving individual faces, a function that relies on holistic representations specific to upright face stimuli. These deficits, combined with their memory impairment, may contribute to the difficulties in recognizing familiar people that are often reported in patients suffering from the disease and by their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Face; Facial Recognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Orientation; Pattern Recognition, Visual; Perceptual Disorders; Photic Stimulation; Psychiatric Status Rating Scales; Reaction Time; Statistics as Topic

Reduction of Blood Amyloid-β Oligomers in Alzheimer's Disease Transgenic Mice by c-Abl Kinase Inhibition. - Estrada, Lisbell D; Chamorro, David; Yañez, María José; Gonzalez, Marcelo; Leal, Nancy; von Bernhardi, Rommy; Dulcey, Andrés E; Marugan, Juan; Ferrer, Marc; Soto, Claudio; Zanlungo, Silvana; Inestrosa, Nibaldo C; et al. (J Alzheimers Dis, 2016)
One of the pathological hallmarks of Alzheimer's disease (AD) is the presence of amyloid plaques, which are deposits of misfolded and aggregated amyloid-beta peptide (Aβ). The role of the c-Abl tyrosine kinase in Aβ-mediated neurodegeneration has been previously reported. Here, we investigated the therapeutic potential of inhibiting c-Abl using imatinib. We developed a novel method, based on a technique used to detect prions (PMCA), to measure minute amounts of misfolded-Aβ in the blood of AD transgenic mice. We found that imatinib reduces Aβ-oligomers in plasma, which correlates with a reduction of AD brain features such as plaques and oligomers accumulation, neuroinflammation, and cognitive deficits. Cells exposed to imatinib and c-Abl KO mice display decreased levels of β-CTF fragments, suggesting that an altered processing of the amyloid-beta protein precursor is the most probable mechanism behind imatinib effects. Our findings support the role of c-Abl in Aβ accumulation and AD, and propose AD-PMCA as a new tool to evaluate AD progression and screening for drug candidates.

Regular Benzodiazepine and Z-Substance Use and Risk of Dementia: An Analysis of German Claims Data. - Gomm, Willy; von Holt, Klaus; Thomé, Friederike; Broich, Karl; Maier, Wolfgang; Weckbecker, Klaus; Fink, Anne; Doblhammer, Gabriele; Haenisch, Britta (J Alzheimers Dis, 2016)
BACKGROUND: While acute detrimental effects of benzodiazepine (BDZ), and BDZ and related z-substance (BDZR) use on cognition and memory are known, the association of BDZR use and risk of dementia in the elderly is controversially discussed. Previous studies on cohort or claims data mostly show an increased risk for dementia with the use of BDZs or BDZRs. For Germany, analyses on large population-based data sets are missing. OBJECTIVE: To evaluate the association between regular BDZR use and incident any dementia in a large German claims data set. METHODS: Using longitudinal German public health insurance data from 2004 to 2011 we analyzed the association between regular BDZR use (versus no BDZR use) and incident dementia in a case-control design. We examined patient samples aged≥60 years that were free of dementia at baseline. To address potential protopathic bias we introduced a lag time between BDZR prescription and dementia diagnosis. Odds ratios were calculated applying conditional logistic regression, adjusted for potential confounding factors such as comorbidities and polypharmacy. RESULTS: The regular use of BDZRs was associated with a significant increased risk of incident dementia for patients aged≥60 years (adjusted odds ratio [OR] 1.21, 95% confidence interval [CI] 1.13-1.29). The association was slightly stronger for long-acting substances than for short-acting ones. A trend for increased risk for dementia with higher exposure was observed. CONCLUSION: The restricted use of BDZRs may contribute to dementia prevention in the elderly.

Relative Alterations in Blood-Based Levels of Sestrin in Alzheimer's Disease and Mild Cognitive Impairment Patients. - Rai, Nitish; Kumar, Rahul; Desai, Gaurav Rajesh; Venugopalan, G; Shekhar, Shashank; Chatterjee, Prasun; Tripathi, Manjari; Upadhyay, Ashish Datt; Dwivedi, Sadanand; Dey, Aparajit B; Dey, Sharmistha (J Alzheimers Dis, 2016)
Sestrins (sesn) are highly conserved proteins that play an important neuroprotective role, in part as a consequence of their antioxidative capacity, which prevents reactive oxygen species formation. In this study, we evaluated the concentrations of sesn1 and sesn2 in the serum of 41 Alzheimer's disease (AD) patients, 27 mild cognitive impairment (MCI), and 60 elderly controls, by surface plasmon resonance, which was validated by using western blot. Moreover, the mRNA level of sestrins in all the study groups was determined by real time polymerase chain reaction. The results showed significant overexpression of serum sesn2 protein and mRNA levels in the AD group compared to MCI and elderly control groups. A difference in serum sesn2 concentration between MCI and the control group was also evident. ROC analysis showed highly sensitive, selective cutoff values for sens2 in the differentiation of AD, MCI, and controls. No significant difference in sesn1 level was observed among the study groups. This study highlights the important role of sesn2 in the progression of the AD, indicating its potential utility as a protein marker in this devastating disease.

Reversible Mild Cognitive Impairment: The Role of Comorbidities at Baseline Evaluation. - Grande, Giulia; Cucumo, Valentina; Cova, Ilaria; Ghiretti, Roberta; Maggiore, Laura; Lacorte, Eleonora; Galimberti, Daniela; Scarpini, Elio; Clerici, Francesca; Pomati, Simone; Vanacore, Nicola; Mariani, Claudio (J Alzheimers Dis, 2016)
The prognostic value of mild cognitive impairment (MCI) is being questioned, with some MCI subjects reverting to normal cognition (NC). The reversion rate varies mostly depending on the study design, the setting, and both MCI and NC definitions. Previous studies have focused on the profile of subjects who revert to NC, but the role of comorbidities has not been entirely investigated. We aimed to evaluate the proportion of MCI subjects who revert to NC in a memory clinic context, focusing on the role of comorbidities. Between 2004 and 2013, 374 MCI subjects were recruited. During a mean time of 32 ± 25.5 months, 21 subjects (5.6%) reverted to NC. Subjects who reverted to NC were younger (p = 0.0001), more educated (p = 0.0001), had a better global cognition (p = 0.0001), as assessed by the Mini-Mental State Examination (MMSE) and suffered from more comorbidities (p = 0.002), as assessed by Cumulative Illness Rating Scale (CIRS) than those who developed dementia. The Cox Regression Model, constructed to adjust for the confounders, showed that the higher were the MMSE (HR = 1.83, CI 95%: 1.07-3.11) and the CIRS score (HR = 1.3, CI 95% 0.88-1.92) at baseline, the higher was the probability of returning to NC than developing dementia, though the last association was not significant. Subjects who reverted to NC were more frequently affected by respiratory (p = 0.002), urologic (p = 0.012), and psychiatric (p = 0.012) diseases. The cognitive performance of subjects with medical comorbidities could benefit from preventive strategies aimed at treating the underlying diseases.
Keywords: Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Comorbidity; Female; Humans; Male; Memory; Mental Status Schedule; Neuropsychological Tests; Reference Values; Verbal Learning

The Role of Cerebrospinal Fluid Biomarkers in the Evolution of Diagnostic Criteria in Alzheimer's Disease: Shortcomings in Prodromal Diagnosis. - Szalárdy, Levente; Zádori, Dénes; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2016)
The available evidence indicates a high performance of core cerebrospinal fluid (CSF) biomarkers in differentiating between Alzheimer's disease (AD) and other dementias, and suggests that their characteristic alterations can be detected even at the prodromal stage of AD. On this basis, the ability of core CSF biomarkers to identify prodromal AD patients from pre-dementia of all causes can be postulated, a concept that is reflected in recent revisions of AD research criteria and a consensus statement. Following an overview on the role of biomarkers in the evolution of diagnostic criteria of AD in recent decades, this paper provides a critical review of the widely applied CSF biomarker study designs and evaluating approaches that address the ability of core CSF biomarkers to diagnose prodromal AD, with special focus on their potential limitations in terms of clinical interpretation and utility. The findings together raise the question of whether we are indeed able to establish a CSF biomarker-based diagnosis of AD at the prodromal stage.

The Savvy Caregiver Program: A Probe Multicenter Randomized Controlled Pilot Trial in Caregivers of Patients Affected by Alzheimer's Disease. - Sepe-Monti, Micaela; Vanacore, Nicola; Bartorelli, Luisa; Tognetti, Alessandra; Giubilei, Franco (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a major cause of disability in the elderly, leading to a considerable burden on caregivers and high costs to society. Psycho-education programs such as the Savvy Caregiver Program (SCP) are reported to be a successful means of reducing caregivers' distress through various intervention strategies. The aim of the present study was to assess the efficacy of the SCP in reducing the burden and psychological symptoms in caregivers of AD patients and to analyze the coping strategies adopted by the caregivers. The study was designed as a multicenter, randomized, controlled, pilot clinical trial. One hundred and sixty-four caregivers of patients with probable AD were randomized. The SCP was structured in six, weekly, two-hour sessions. All the clinical scales were administered before treatment, two weeks and six months after treatment. Caregivers in the SCP group displayed better coping strategies adopted to positive attitudes, and they tended to be less anxious and less depressed than those in the control group. However, caregiver burden levels were not reduced in SCP caregivers. The patients of SCP caregivers received a lower number of new prescriptions of neuroleptics during the 6 months of follow-up than the patients of control caregivers and apathy was the neuropsychiatric symptom that improved most as a result of the SCP. The results of this study suggest that the SCP may improve coping strategies of caregivers of people affected by AD, influencing their psychological symptoms and those of their patients.

Self-Perceived Quality of Life Among Patients with Alzheimer's Disease: Two Longitudinal Models of Analysis. - Conde-Sala, Josep L; Turró-Garriga, Oriol; Portellano-Ortiz, Cristina; Viñas-Diez, Vanesa; Gascón-Bayarri, Jordi; Reñé-Ramírez, Ramón (J Alzheimers Dis, 2016)
The objective was to analyze the factors that influence self-perceived quality of life (QoL) in patients with Alzheimer's disease (AD), contrasting two different longitudinal models. A total of 127 patients were followed up over 24 months. The instruments applied were: Quality of Life in Alzheimer's Disease scale (QoL-AD), Geriatric Depression Scale-15, Anosognosia Questionnaire-Dementia, Disability Assessment in Dementia, Neuropsychiatric Inventory, and the Mini-Mental State Examination. Two models for grouping patients were tested: 1) Baseline score on the QoL-AD (QoL-Baseline), and 2) Difference in QoL-AD score between baseline and follow-up (QoL-Change). Generalized estimating equations were used to analyze longitudinal data, and multinomial regression analyses were performed. Over the follow-up period the QoL-Baseline model showed greater variability between groups (Wald χ2 = 172.3, p < 0.001) than did the QoL-Change model (Wald χ2  = 1.7, p = 0.427). In the QoL-Baseline model the predictive factors were greater depression (odds ratio [OR] = 1.20; 95% CI: 1.00- 1.45) and lower functional ability (OR = 0.92; 95% CI: 0.85- 0.99) for the Low QoL group (< 33 QoL-AD), and less depression (OR = 0.68; 95% CI: 0.52- 0.88), more anosognosia (OR = 1.07; 95% CI: 1.01- 1.13), and fewer neuropsychiatric symptoms (OR = 0.95; 95% CI: 0.91- 0.99) for the High-QoL group (>37 QoL-AD). The model based on baseline scores (QoL-Baseline) was better than the QoL-Change model in terms of identifying trajectories and predictors of QoL in AD.

Self-Reported Change in Quality of Life with Retirement and Later Cognitive Decline: Prospective Data from the Nurses' Health Study. - Vercambre, Marie-Noël; Okereke, Olivia I; Kawachi, Ichiro; Grodstein, Francine; Kang, Jae H (J Alzheimers Dis, 2016)
To investigate whether a positive transition into retirement may be associated with later cognitive aging, we included a subset of 4,926 Nurses' Health Study participants who retired from work at ages 60-69, then provided a subjective assessment of the change in overall quality of life (QOL) with retirement. Subsequently (range: 1 month to 4.7 years later), when all were aged 70+ years, they completed a baseline telephone cognitive battery evaluating global cognition, episodic memory, and executive function. They had up to three follow-up cognitive assessments. Controlling for various occupational factors before retirement and socioeconomic, lifestyle, and health-related factors as of the baseline cognitive assessment, we used generalized linear models for repeated measures to estimate mean differences in rates of cognitive decline across categories of QOL transition at retirement: "worse", "same", or "better". Over a median 6 years of follow-up, the global cognitive score change was -0.123 on average. Compared with women who reported no change in QOL at retirement (31%), women who reported improvement (61%) showed a significantly slower rate of cognitive decline (difference = +0.011 95% CI = 0.004, 0.019). This mean difference was equivalent to that observed between women who were 2 years apart in age. No significant differences in cognitive decline rates were observed for the women who reported worsened QOL (8%). Secondary analyses to address possible reverse causation showed robust associations. A positive transition into retirement was associated with better maintenance of cognitive function over time in aging women. These findings need to be replicated in other populations.

The Societal Cost of Dementia in Singapore: Results from the WiSE Study. - Abdin, Edimansyah; Subramaniam, Mythily; Achilla, Evanthia; Chong, Siow Ann; Vaingankar, Janhavi Ajit; Picco, Louisa; Sambasivam, Rajeswari; Pang, Shirlene; Chua, Boon Yiang; Ng, Li Ling; Chua, Hong Choon; Heng, Derrick; et al. (J Alzheimers Dis, 2016)
BACKGROUND: There is currently limited evidence on the economic burden that dementia exerts on multi-ethnic Asian populations. OBJECTIVE: The present study aimed to estimate the economic cost of dementia in Singapore. METHODS: We used data from the Well-being of the Singapore Elderly study, a nationally representative survey of the older Singapore Resident population aged 60 years and above. Generalized linear modeling was used to estimate factors associated with costs. RESULTS: The total cost of dementia in 2013 was estimated at S$532 million (95% CI, S$361 million to S$701 million) while the annual cost per person was estimated at S$10,245 per year (95% CI, S$6,954 to S$12,495). Apart from dementia, higher total societal cost were also significantly associated with older age, Indian ethnicity, and those who were diagnosed with heart problems, stroke, diabetes or depression, whereas being divorced/separated, lower education, and those who were diagnosed with hypertension were significantly associated with lower total societal cost. CONCLUSION: The study provides a rich body of information on healthcare utilization and cost of dementia, which is essential for future planning of services for the elderly population.
Keywords: Adult; Aged, 80 and over; Cost of Illness; Dementia; Female; Humans; Linear Models; Male; Middle Aged; Singapore

Spatial Memory Impairment is Associated with Intraneural Amyloid-β Immunoreactivity and Dysfunctional Arc Expression in the Hippocampal-CA3 Region of a Transgenic Mouse Model of Alzheimer's Disease. - Morin, Jean-Pascal; Cerón-Solano, Giovanni; Velázquez-Campos, Giovanna; Pacheco-López, Gustavo; Bermúdez-Rattoni, Federico; Díaz-Cintra, Sofía (J Alzheimers Dis, 2016)
Dysfunction of synaptic communication in cortical and hippocampal networks has been suggested as one of the neuropathological hallmarks of the early stages of Alzheimer's disease (AD). Also, several lines of evidence have linked disrupted levels of activity-regulated cytoskeletal associated protein (Arc), an immediate early gene product that plays a central role in synaptic plasticity, with AD "synaptopathy". The mapping of Arc expression patterns in brain networks has been extensively used as a marker of memory-relevant neuronal activity history. Here we evaluated basal and behavior-induced Arc expression in hippocampal networks of the 3xTg-AD mouse model of AD. The basal percentage of Arc-expressing cells in 10-month-old 3xTg-AD mice was higher than wild type in CA3 (4.88% versus 1.77% , respectively) but similar in CA1 (1.75% versus 2.75% ). Noteworthy, this difference was not observed at 3 months of age. Furthermore, although a Morris water maze test probe induced a steep (∼4-fold) increment in the percentage of Arc+ cells in the CA3 region of the 10-month-old wild-type group, no such increment was observed in age-matched 3xTg-AD, whereas the amount of Arc+ cells in CA1 increased in both groups. Further, we detected that CA3 neurons with amyloid-β were much more likely to express Arc protein under basal conditions. We propose that in 3xTg-AD mice, intraneuronal amyloid-β expression in CA3 could increase unspecific neuronal activation and subsequent Arc protein expression, which might impair further memory-stabilizing processes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Benzeneacetamides; CA3 Region, Hippocampal; Cytoskeletal Proteins; Disease Models, Animal; Gene Expression Regulation; Humans; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurons; Presenilin-1; Pyridines; tau Proteins

Specific Triazine Herbicides Induce Amyloid-β42 Production. - Portelius, Erik; Durieu, Emilie; Bodin, Marion; Cam, Morgane; Pannee, Josef; Leuxe, Charlotte; Mabondzo, Aloϊse; Oumata, Nassima; Galons, Hervé; Lee, Jung Yeol; Chang, Young-Tae; Stϋber, Kathrin; et al. (J Alzheimers Dis, 2016)
Proteolytic cleavage of the amyloid-β protein precursor (AβPP) by secretases leads to extracellular release of amyloid-β (Aβ) peptides. Increased production of Aβ42 over Aβ40 and aggregation into oligomers and plaques constitute an Alzheimer's disease (AD) hallmark. Identifying products of the 'human chemical exposome' (HCE) able to induce Aβ42 production may be a key to understanding some of the initiating causes of AD and to generate non-genetic, chemically-induced AD animal models. A cell model was used to screen HCE libraries for Aβ42 inducers. Out of 3500+ compounds, six triazine herbicides were found that induced a β- and γ-secretases-dependent, 2-10 fold increase in the production of extracellular Aβ42 in various cell lines, primary neuronal cells, and neurons differentiated from human-induced pluripotent stem cells (iPSCs). Immunoprecipitation/mass spectrometry analyses show enhanced production of Aβ peptides cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and lower, a characteristic of AD. Neurons derived from iPSCs obtained from a familial AD (FAD) patient (AβPP K724N) produced more Aβ42 versus Aβ40 than neurons derived from healthy controls iPSCs (AβPP WT). Triazines enhanced Aβ42 production in both control and AD iPSCs-derived neurons. Triazines also shifted the cleavage pattern of alcadeinα, another γ-secretase substrate, suggesting a direct effect of triazines on γ-secretase activity. In conclusion, several widely used triazines enhance the production of toxic, aggregation prone Aβ42/Aβ43 amyloids, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in late-onset AD.

Stability of Progranulin Under Pre-Analytical Conditions in Serum and Cerebrospinal Fluid. - Willemse, Eline A J; Durieux-Lu, Sisi; van der Flier, Wiesje M; Pijnenburg, Yolande A L; de Jonge, Robert; Teunissen, Charlotte E (J Alzheimers Dis, 2016)
Progranulin (PGRN) levels in blood and cerebrospinal fluid (CSF) are increasingly studied as potential markers for neurodegenerative disorders. We aimed to 1) characterize two commercially available PGRN ELISAs on several assay validation parameters, 2) assess the stability of PGRN in serum and CSF under pre-analytical conditions, and 3) compare stability in the two assays. Intra- and inter-assay variation, inter-lot variation, linearity, lower limit of detection, and kit correlations were assessed for the Adipogen and R&D PGRN ELISA kits. Blood and serum samples were experimentally exposed to ≤9 freeze/thaw cycles, delayed processing for ≤24 h at room temperature and 4°C, and to temperature stability tests for ≤3 weeks at -20°C, 4°C, room temperature, and 37°C. Both commercial PGRN ELISA kits showed acceptable ranges for intra- and inter-assay variation, where the R&D kit performed more accurate than the Adipogen kit, especially for inter-assay variation (intra-assay serum: 6.7 and 8.3%, respectively; inter-assay serum: 9.2 and 21.0%; intra-assay CSF: 3.6 and 12.0%; inter-assay CSF: 16.0 and 44.5%). Absolute serum PGRN concentrations were 1.9-fold higher in Adipogen than R&D (p < 0.001) and strongly correlated between both kits (ρ= 0.86, p < 0.0001) and CSF PGRN levels were on the borderline of detection in both kits. PGRN was typically stable under all pre-analytical conditions addressed, although two weeks at 37°C resulted in decreased PGRN concentrations in CSF, only when using the Adipogen kit. These results support further examination of PGRN as a potential marker in neurodegenerative diseases, since PGRN is stable in serum and CSF and can be measured using ELISA kits from several providers.

Stroke, Vascular Dementia, and Alzheimer's Disease: Molecular Links. - Vijayan, Murali; Reddy, P Hemachandra (J Alzheimers Dis, 2016)
Stroke is a brain disease that occurs when blood flow stops, resulting in reduced oxygen supply to neurons. Stroke occurs at any time and at any age, but increases after the age of 55. It is the second leading cause of death and the third leading cause of disability-adjusted, life-years. The pathophysiology of ischemic stroke is complex and recent molecular, cellular, and animal models and postmortem brain studies have revealed that multiple cellular changes have been implicated, including oxidative stress/mitochondrial dysfunction, inflammatory responses, micro RNA alterations, and marked changes in brain proteins. These cellular changes provide new information for developing therapeutic strategies for ischemic stroke treatment. Research also revealed that stroke increases with a number of modifiable factors and most strokes can be prevented and/or controlled through pharmacological or surgical interventions and lifestyle changes. Ischemic stroke is the major risk factor for vascular dementia and Alzheimer's disease. This review summarizes the latest research findings on stroke, including causal factors and molecular links between stroke and vascular disease/Alzheimer's disease.

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

Transcriptional Analysis of Blood Lymphocytes and Skin Fibroblasts, Keratinocytes, and Endothelial Cells as a Potential Biomarker for Alzheimer's Disease. - Mukhamedyarov, Marat A; Rizvanov, Albert A; Yakupov, Eduard Z; Zefirov, Andrey L; Kiyasov, Andrey P; Reis, Helton J; Teixeira, Antônio L; Vieira, Luciene B; Lima, Luciana M; Salafutdinov, Ilnur I; Petukhova, Elena O; Khaiboullina, Svetlana F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating and progressive form of dementia that is typically associated with a build-up of amyloid-β plaques and hyperphosphorylated and misfolded tau protein in the brain. Presently, there is no single test that confirms AD; therefore, a definitive diagnosis is only made after a comprehensive medical evaluation, which includes medical history, cognitive tests, and a neurological examination and/or brain imaging. Additionally, the protracted prodromal phase of the disease makes selection of control subjects for clinical trials challenging. In this study we have utilized a gene-expression array to screen blood and skin punch biopsy (fibroblasts, keratinocytes, and endothelial cells) for transcriptional differences that may lead to a greater understanding of AD as well as identify potential biomarkers. Our analysis identified 129 differentially expressed genes from blood of dementia cases when compared to healthy individuals, and four differentially expressed punch biopsy genes between AD subjects and controls. Additionally, we identified a set of genes in both tissue compartments that showed transcriptional variation in AD but were largely stable in controls. The translational products of these variable genes are involved in the maintenance of the Golgi structure, regulation of lipid metabolism, DNA repair, and chromatin remodeling. Our analysis potentially identifies specific genes in both tissue compartments that may ultimately lead to useful biomarkers and may provide new insight into the pathophysiology of AD.

Transferring cut-off values between assays for cerebrospinal fluid Alzheimer's disease biomarkers. - García Barrado, Leandro; Coart, Els; Vanderstichele, Hugo M J; Burzykowski, Tomasz (J Alzheimers Dis, 2016)
Current technologies quantifying cerebrospinal fluid biomarkers to identify subjects with Alzheimer's disease pathology report different concentrations in function of technology and suffer from between-laboratory variability. Hence, lab- and technology-specific cut-off values are required. It is common practice to establish cut-off values on small datasets and, in the absence of well-characterized samples, to transfer the cut-offs to another assay format using 'side-by-side' testing of samples with both assays. We evaluated the uncertainty in cut-off estimation and the performance of two methods of cut-off transfer by using two clinical datasets and simulated data. The cut-off for the new assay was transferred by applying the commonly-used linear regression approach and a new Bayesian method, which consists of using prior information about the current assay for estimation of the biomarker's distributions for the new assay. Simulations show that cut-offs established with current sample sizes are insufficiently precise and also show the effect of increasing sample sizes on the cut-offs' precision. The Bayesian method results in unbiased and less variable cut-offs with substantially narrower 95% confidence intervals compared to the linear-regression transfer. For the BIODEM datasets, the transferred cut-offs for INNO-BIA Aβ1-42 are 167.5 pg/mL (95% credible interval [156.1, 178.0] and 172.8 pg/mL (95% CI [147.6, 179.6]) with Bayesian and linear regression methods, respectively. For the EUROIMMUN assay, the estimated cut-offs are 402.8 pg/mL (95% credible interval [348.0, 473.9]) and 364.4 pg/mL (95% CI [269.7, 426.8]). Sample sizes and statistical methods used to establish and transfer cut-off values have to be carefully considered to guarantee optimal diagnostic performance of biomarkers.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Bayes Theorem; Biomarkers; Cognitive Dysfunction; Datasets as Topic; Humans; Linear Models; Multivariate Analysis; Peptide Fragments; tau Proteins

Validation of microRNAs in Cerebrospinal Fluid as Biomarkers for Different Forms of Dementia in a Multicenter Study. - Müller, Mareike; Kuiperij, H Bea; Versleijen, Alexandra A M; Chiasserini, Davide; Farotti, Lucia; Baschieri, Francesca; Parnetti, Lucilla; Struyfs, Hanne; De Roeck, Naomi; Luyckx, Jill; Engelborghs, Sebastiaan; Claassen, Jurgen A; et al. (J Alzheimers Dis, 2016)
MicroRNAs (miRNAs) regulate translational inhibition of proteins, but are also detected in body fluids, including cerebrospinal fluid (CSF), where they may serve as disease-specific biomarkers. Previously, we showed differential expression of miR-146a, miR-29a, and miR-125b in the CSF of Alzheimer's disease (AD) patients versus controls. In this study, we aim to confirm these findings by using larger, independent sample cohorts of AD patients and controls from three different centers. Furthermore, we aim to identify confounding factors that possibly arise using such a multicenter approach. The study was extended by including patients diagnosed with mild cognitive impairment due to AD, frontotemporal dementia and dementia with Lewy bodies. Previous results of decreased miR-146a levels in AD patients compared to controls were confirmed in one center. When samples from all three centers were combined, several confounding factors were identified. After controlling for these factors, we did not identify differences in miRNA levels between the different groups. However, we provide suggestions to circumvent various pitfalls when measuring miRNAs in CSF to improve future studies.

Validation of the Total Cerebrovascular Disease Burden Scale in a Community Sample. - Xu, Xin; Hilal, Saima; Collinson, Simon L; Chan, Qun Lin; Yi Chong, Eddie Jun; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Cheng, Ching-Yu; Wong, Tien Yin; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND: A total cerebrovascular disease (CeVD) burden scale was previously constructed and an inverse association of CeVD burden and cognition was found. However, the generalizability of the CeVD scale has not been examined. OBJECTIVE: The objective was to validate the previously constructed total CeVD burden scale by establishing its association with cognitive function and dementia diagnosis in a community sample. METHODS: Eligible participants were assessed on an extensive neuropsychological battery and underwent MRI scans. The total CeVD scale, comprising markers of both small- and large-vessel diseases, was derived according to previously described criteria. Association of total CeVD burden with global and domain-based cognitive performance and dementia diagnostic utility of the scale was established. RESULTS: A total of 863 participants were included in the analysis. A stepwise association of CeVD burden score with global and domain-specific cognitive function was found. Per score increase on the total CeVD burden scale was associated with 3.6 (95% CI = 2.1-6.4) times higher odds of dementia compared to dementia-free. DISCUSSION: The total CeVD burden scale is associated with cognition and dementia in a community sample. Longitudinal studies are required to establish the predictive ability of this scale.

Vitamin D and Memory Decline: Two Population-Based Prospective Studies. - Kuźma, Elżbieta; Soni, Maya; Littlejohns, Thomas J; Ranson, Janice M; van Schoor, Natasja M; Deeg, Dorly J H; Comijs, Hannie; Chaves, Paulo H M; Kestenbaum, Bryan R; Kuller, Lewis H; Lopez, Oscar L; Becker, James T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vitamin D deficiency has been linked with dementia risk, cognitive decline, and executive dysfunction. However, the association with memory remains largely unknown. OBJECTIVE: To investigate whether low serum 25-hydroxyvitamin D (25(OH)D) concentrations are associated with memory decline. METHODS: We used data on 1,291 participants from the US Cardiovascular Health Study (CHS) and 915 participants from the Dutch Longitudinal Aging Study Amsterdam (LASA) who were dementia-free at baseline, had valid vitamin D measurements, and follow-up memory assessments. The Benton Visual Retention Test (in the CHS) and Rey's Auditory Verbal Learning Test (in the LASA) were used to assess visual and verbal memory, respectively. RESULTS: In the CHS, those moderately and severely deficient in serum 25(OH)D changed -0.03 SD (95% CI: -0.06 to 0.01) and -0.10 SD (95% CI: -0.19 to -0.02) per year respectively in visual memory compared to those sufficient (p = 0.02). In the LASA, moderate and severe deficiency in serum 25(OH)D was associated with a mean change of 0.01 SD (95% CI: -0.01 to 0.02) and -0.01 SD (95% CI: -0.04 to 0.02) per year respectively in verbal memory compared to sufficiency (p = 0.34). CONCLUSIONS: Our findings suggest an association between severe vitamin D deficiency and visual memory decline but no association with verbal memory decline. They warrant further investigation in prospective studies assessing different memory subtypes.
Keywords: Humans; Memory Disorders; Netherlands; Prospective Studies; United States; Vitamin D; Vitamin D Deficiency

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

The Zebrafish Equivalent of Alzheimer's Disease-Associated PRESENILIN Isoform PS2V Regulates Inflammatory and Other Responses to Hypoxic Stress. - Ebrahimie, Esmaeil; Moussavi Nik, Seyyed Hani; Newman, Morgan; Van Der Hoek, Mark; Lardelli, Michael (J Alzheimers Dis, 2016)
Dominant mutations in the PRESENILIN genes PSEN1 and PSEN2 cause familial Alzheimer's disease (fAD) that usually shows onset before 65 years of age. In contrast, genetic variation at the PSEN1 and PSEN2 loci does not appear to contribute to risk for the sporadic, late onset form of the disease (sAD), leading to doubts that these genes play a role in the majority of AD cases. However, a truncated isoform of PSEN2, PS2V, is upregulated in sAD brains and is induced by hypoxia and high cholesterol intake. PS2V can increase γ-secretase activity and suppress the unfolded protein response (UPR), but detailed analysis of its function has been hindered by lack of a suitable, genetically manipulable animal model since mice and rats lack this PRESENILIN isoform. We recently showed that zebrafish possess an isoform, PS1IV, that is cognate to human PS2V. Using an antisense morpholino oligonucleotide, we can block specifically the induction of PS1IV that normally occurs under hypoxia. Here, we exploit this ability to identify gene regulatory networks that are modulated by PS1IV. When PS1IV is absent under hypoxia-like conditions, we observe changes in expression of genes controlling inflammation (particularly sAD-associated IL1B and CCR5), vascular development, the UPR, protein synthesis, calcium homeostasis, catecholamine biosynthesis, TOR signaling, and cell proliferation. Our results imply an important role for PS2V in sAD as a component of a pathological mechanism that includes hypoxia/oxidative stress and support investigation of the role of PS2V in other diseases, including schizophrenia, when these are implicated in the pathology.

Adipose Tissue Distribution in Patients with Alzheimer's Disease: A Whole Body MRI Case-Control Study. - Diehl-Wiesenecker, Eva; von Armin, Christine A F; Dupuis, Luc; Müller, Hans-Peter; Ludolph, Albert C; Kassubek, Jan (J Alzheimers Dis, 2015)
BACKGROUND: Total and central adiposity have been associated with increased risk of Alzheimer's disease (AD). Visceral and subcutaneous adipose tissues have different metabolic characteristics and could therefore be differentially associated with AD. OBJECTIVE: To compare regional fat distribution determined by magnetic resonance imaging (MRI) in AD patients and healthy controls and investigate associations with stage of the disease and chemical markers. The investigation was performed in a prospective case-control study. METHODS: We examined thirty patients with mild to moderate AD by whole-body MRI (1.5 T) and clinical questionnaires in comparison to thirty cognitively healthy age- and gender-matched study participants. Volumes of total, subcutaneous, and visceral body fat tissue were determined by an unbiased automatic analysis algorithm. Levels of leptin, ghrelin, and adiponectin were determined in serum, amyloid-β (Aβ)1-42 and tau protein levels in cerebrospinal fluid (CSF). RESULTS: Male AD patients displayed significantly more total fat tissue than male controls. This difference was not observed in women. We observed a trend toward higher volume of visceral fat tissue in all patients (p = 0.13). Severity of disease was not associated with fat distribution in our study. Increased leptin levels correlated with lower CSF Aβ 1-42 in female, but not in male, AD patients. CONCLUSIONS: Fat volume is increased in male, but not in female AD patients. Negative correlation of leptin levels and CSF Aβ 1-42 in females might be one co-factor for the increased AD risk of females. Further studies are required to confirm this gender difference in fat volume during AD and evaluate its pathophysiological importance.

Alzheimer's Disease Normative Cerebrospinal Fluid Biomarkers Validated in PET Amyloid-β Characterized Subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. - Li, Qiao-Xin; Villemagne, Victor L; Doecke, James D; Rembach, Alan; Sarros, Shannon; Varghese, Shiji; McGlade, Amelia; Laughton, Katrina M; Pertile, Kelly K; Fowler, Christopher J; Rumble, Rebecca L; Trounson, Brett O; et al. (J Alzheimers Dis, 2015)
BACKGROUND: The cerebrospinal fluid (CSF) amyloid-β (Aβ)1-42, total-tau (T-tau), and phosphorylated-tau (P-tau181P) profile has been established as a valuable biomarker for Alzheimer's disease (AD). OBJECTIVE: The current study aimed to determine CSF biomarker cut-points using positron emission tomography (PET) Aβ imaging screened subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging, as well as correlate CSF analyte cut-points across a range of PET Aβ amyloid ligands. METHODS: Aβ pathology was determined by PET imaging, utilizing 11C-Pittsburgh Compound B, 18F-flutemetamol, or 18F-florbetapir, in 157 AIBL participants who also underwent CSF collection. Using an INNOTEST assay, cut-points were established (Aβ1-42 >544 ng/L, T-tau <407 ng/L, and P-tau181P <78 ng/L) employing a rank based method to define a "positive" CSF in the sub-cohort of amyloid-PET negative healthy participants (n = 97), and compared with the presence of PET demonstrated AD pathology. RESULTS: CSF Aβ1-42 was the strongest individual biomarker, detecting cognitively impaired PET positive mild cognitive impairment (MCI)/AD with 85% sensitivity and 91% specificity. The ratio of P-tau181P or T-tau to Aβ1-42 provided greater accuracy, predicting MCI/AD with Aβ pathology with ≥92% sensitivity and specificity. Cross-validated accuracy, using all three biomarkers or the ratio of P-tau or T-tau to Aβ1-42 to predict MCI/AD, reached ≥92% sensitivity and specificity. CONCLUSIONS: CSF Aβ1-42 levels and analyte combination ratios demonstrated very high correlation with PET Aβ imaging. Our study offers additional support for CSF biomarkers in the early and accurate detection of AD pathology, including enrichment of patient cohorts for treatment trials even at the pre-symptomatic stage.

Blood Protein Markers of Neocortical Amyloid-β Burden: A Candidate Study Using SOMAscan Technology. - Voyle, Nicola; Baker, David; Burnham, Samantha C; Covin, Antonia; Zhang, Zhanpan; Sangurdekar, Dipen P; Tan Hehir, Cristina A; Bazenet, Chantal; Lovestone, Simon; Kiddle, Steven; Dobson, Richard J B (J Alzheimers Dis, 2015)
BACKGROUND: Four previously reported studies have tested for association of blood proteins with neocortical amyloid-β burden (NAB). If shown to be robust, these proteins could have utility as a blood test for enrichment in clinical trials of Alzheimer's disease (AD) therapeutics. OBJECTIVE: This study aimed to investigate whether previously identified blood proteins also show evidence for association with NAB in serum samples from the Australian Imaging, Biomarker and Lifestyle Flagship Study of Ageing (AIBL). The study considers candidate proteins seen in cohorts other than AIBL and candidates previously discovered in the AIBL cohort. METHODS: Our study used the SOMAscan platform for protein quantification in blood serum. Linear and logistic regressions were used to model continuous NAB and dichotomized NAB respectively using single proteins as a predictor. Multiple protein models were built using stepwise regression techniques and support vectors machines. Age and APOE ε4 carriage were used as covariates for all analysis. RESULTS: Of the 41 proteins previously reported, 15 AIBL candidates and 20 non-AIBL candidates were available for testing. Of these candidates, pancreatic polypeptide (PPY) and IgM showed a significant association with NAB. Notably, IgM was found to associate with continuous NAB across cognitively normal control subjects. CONCLUSIONS: We have further demonstrated the association of PPY and IgM with NAB, despite technical differences between studies. There are several reasons for a lack of significance for the other candidates including platform differences and the use of serum rather than plasma samples. To investigate the possibility of technical differences causing lack of further replication, further studies are required.

A Blood-Based, 7-Metabolite Signature for the Early Diagnosis of Alzheimer's Disease. - Olazarán, Javier; Gil-de-Gómez, Luis; Rodríguez-Martín, Andrés; Valentí-Soler, Meritxell; Frades-Payo, Belén; Marín-Muñoz, Juan; Antúnez, Carmen; Frank-García, Ana; Jiménez, Carmen Acedo; Gracia, Lorenzo Morlén; Torregrossa, Roberto Petidier; Guisasola, María Concepción; et al. (J Alzheimers Dis, 2015)
Accurate blood-based biomarkers of Alzheimer's disease (AD) could constitute simple, inexpensive, and non-invasive tools for the early diagnosis and treatment of this devastating neurodegenerative disease. We sought to develop a robust AD biomarker panel by identifying alterations in plasma metabolites that persist throughout the continuum of AD pathophysiology. Using a multicenter, cross-sectional study design, we based our analysis on metabolites whose levels were altered both in AD patients and in patients with amnestic mild cognitive impairment (aMCI), the earliest identifiable stage of AD. UPLC coupled to mass spectrometry was used to independently compare the levels of 495 plasma metabolites in aMCI (n = 58) and AD (n = 100) patients with those of normal cognition controls (NC, n = 93). Metabolite alterations common to both aMCI and AD patients were used to generate a logistic regression model that accurately distinguished AD from NC patients. The final panel consisted of seven metabolites: three amino acids (glutamic acid, alanine, and aspartic acid), one non-esterified fatty acid (22:6n-3, DHA), one bile acid (deoxycholic acid), one phosphatidylethanolamine [PE(36:4)], and one sphingomyelin [SM(39:1)]. Detailed analysis ruled out the influence of potential confounding variables, including comorbidities and treatments, on each of the seven biomarkers. The final model accurately distinguished AD from NC patients (AUC, 0.918). Importantly, the model also distinguished aMCI from NC patients (AUC, 0.826), indicating its potential diagnostic utility in early disease stages. These findings describe a sensitive biomarker panel that may facilitate the specific detection of early-stage AD through the analysis of plasma samples.

Comorbid Depression and Diabetes as a Risk for Mild Cognitive Impairment and Alzheimer's Disease in Elderly Mexican Americans. - Johnson, Leigh A; Gamboa, Adriana; Vintimilla, Raul; Cheatwood, Austin J; Grant, Alyann; Trivedi, Ashesh; Edwards, Melissa; Hall, James R; O'Bryant, Sid E (J Alzheimers Dis, 2015)
BACKGROUND: The links between diabetes, depression, and Alzheimer's disease (AD) has been established, but they are still poorly understood. However, little research has examined the effect that comorbidity of depression and diabetes has on cognitive impairment in an ethnically diverse sample. OBJECTIVE: The purpose of this study was to investigate the relationship between comorbid diabetes and depression on cognitive dysfunction; and examine the relationship in an ethnically diverse population. METHODS AND RESULTS: Analyses of data from 2,436 participants (914 men and 1,522 women) of three separate cohorts: HABLE, FRONTIER, and TARCC. In the HABLE cohort, comorbidity (odds ratio [OR] = 3.008; 95% CI = 1.358-6.667), age (OR = 1.138; 95% CI = 1.093-1.185), and education (OR = 0.915; 95% CI = 0.852-0.982) increased the risk of mild cognitive impairment (MCI) diagnosis among elderly Mexican American. In the TARCC cohort, results showed an increase risk of MCI in both non-Hispanic whites (OR = 18.795; 95% CI = 2.229-158.485) and Mexican Americans (OR = 8.417; 95% CI = 2.967-23.878). Finally, results in the FRONTIER cohort showed that in elderly Mexican Americans, comorbidity (OR = 2.754; 95% CI = 1.084-6.995) and age (OR = 1.069; 95% CI = 1.023-1.118) significantly increased risk of MCI. In non-Hispanic whites, comorbidity did not significantly increase risk of MCI. CONCLUSIONS: Among elderly Mexican Americans, comorbid depression and diabetes significantly increased risk for MCI and AD across cohorts. Effects of comorbid diabetes and depression on MCI were inconclusive. Our results support the link between comorbid diabetes and depression and risk for cognitive decline among Mexican Americans. This finding is of critical importance as the Hispanic population is at higher risk of developing AD.

Correcting for the Absence of a Gold Standard Improves Diagnostic Accuracy of Biomarkers in Alzheimer's Disease. - Coart, Els; Barrado, Leandro García; Duits, Flora H; Scheltens, Philip; van der Flier, Wiesje M; Teunissen, Charlotte E; van der Vies, Saskia M; Burzykowski, Tomasz (J Alzheimers Dis, 2015)
BACKGROUND: Studies investigating the diagnostic accuracy of biomarkers for Alzheimer's disease (AD) are typically performed using the clinical diagnosis or amyloid-β positron emission tomography as the reference test. However, neither can be considered a gold standard or a perfect reference test for AD. Not accounting for errors in the reference test is known to cause bias in the diagnostic accuracy of biomarkers. OBJECTIVE: To determine the diagnostic accuracy of AD biomarkers while taking the imperfectness of the reference test into account. METHODS: To determine the diagnostic accuracy of AD biomarkers and taking the imperfectness of the reference test into account, we have developed a Bayesian method. This method establishes the biomarkers' true value in predicting the AD-pathology status by combining the reference test and the biomarker data with available information on the reliability of the reference test. The new methodology was applied to two clinical datasets to establish the joint accuracy of three cerebrospinal fluid biomarkers (amyloid-β1-42, Total tau, and P-tau181) by including the clinical diagnosis as imperfect reference test into the analysis. RESULTS: The area under the receiver-operating-characteristics curve to discriminate between AD and controls, increases from 0.949 (with 95% credible interval [0.935,0.960]) to 0.990 ([0.985,0.995]) and from 0.870 ([0.817,0.912]) to 0.975 ([0.943,0.990]) for the cohorts, respectively. CONCLUSIONS: Use of the Bayesian methodology enables an improved estimate of the exact diagnostic value of AD biomarkers and overcomes the lack of a gold standard for AD. Using the new method will increase the diagnostic confidence for early stages of AD.

Differential Effects of Meal Challenges on Cognition, Metabolism, and Biomarkers for Apolipoprotein E ɛ4 Carriers and Adults with Mild Cognitive Impairment. - Hanson, Angela J; Bayer, Jennifer L; Baker, Laura D; Cholerton, Brenna; VanFossen, Brian; Trittschuh, Emily; Rissman, Robert A; Donohue, Michael C; Moghadam, Setareh H; Plymate, Stephen R; Craft, Suzanne (J Alzheimers Dis, 2015)
BACKGROUND: High intake of saturated fat (SF) and glycemic index (GI) foods is a risk factor for sporadic Alzheimer's disease. Meal challenges may elucidate mechanisms that contribute to this risk, enabling development of targeted interventions. OBJECTIVE: To assess cognitive and metabolic changes after a meal high in SF and GI calories (HIGH) versus a meal low in these macronutrients (LOW) in older adults with and without cognitive impairment, and with and without the apolipoprotein E4 risk factor. METHODS: 46 adults with either cognitive impairment (CI) or normal cognition (NC) ingested a LOW (25% total fat, 7% SF, GI <55) and a HIGH meal (50% total fat, 25% SF, GI >70) in a blinded random fashion. Participants then underwent cognitive testing and blood sampling for metabolic and Alzheimer's disease biomarkers. Data were analyzed using repeated measures ANOVA and Spearman correlations. RESULTS: E4-adults with NC demonstrated lower delayed memory scores after the HIGH compared to the LOW meal, whereas normal E4+ and CI E4- groups had higher scores after the HIGH meal (ANOVA p = 0.03). These findings were associated with meal-induced changes in glucose (p = 0.05), insulin (p = 0.004), triglycerides (p <  0.01), and plasma Aβ42 (p = 0.05). CONCLUSIONS: These preliminary data suggest that cognitive performance of adults without CI may worsen following high SF and sugar meals, whereas adults with CI or those at risk for CI due to E4 status may benefit acutely from such meals. Furthermore, plasma Aβ was affected by meal type, suggesting a relationship between metabolic response and amyloid regulation.

The GLP-1 Receptor Agonist Liraglutide Improves Memory Function and Increases Hippocampal CA1 Neuronal Numbers in a Senescence-Accelerated Mouse Model of Alzheimer's Disease. - Hansen, Henrik H; Fabricius, Katrine; Barkholt, Pernille; Niehoff, Michael L; Morley, John E; Jelsing, Jacob; Pyke, Charles; Bjerre Knudsen, Lotte; Farr, Susan A; Vrang, Niels (J Alzheimers Dis, 2015)
Recent studies indicate that glucagon-like peptide 1 (GLP-1) receptor agonists, currently used in the management of type 2 diabetes, exhibit neurotrophic and neuroprotective effects in amyloid-β (Aβ) toxicity models of Alzheimer's disease (AD). We investigated the potential pro-cognitive and neuroprotective effects of the once-daily GLP-1 receptor agonist liraglutide in senescence-accelerated mouse prone 8 (SAMP8) mice, a model of age-related sporadic AD not dominated by Aβ plaques. Six-month-old SAMP8 mice received liraglutide (100 or 500 μg/kg/day, s.c.) or vehicle once daily for 4 months. Vehicle-dosed age-matched 50% back-crossed as well as untreated young (4-month-old) SAMP8 mice were used as control groups for normal memory function. Vehicle-dosed 10-month-old SAMP8 mice showed significant learning and memory retention deficits in an active-avoidance T-maze, as compared to both control groups. Also, 10-month-old SAMP8 mice displayed no immunohistological signatures of Aβ plaques or hyperphosphorylated tau, indicating the onset of cognitive deficits prior to deposition of amyloid plaques and neurofibrillary tangles in this AD model. Liraglutide significantly increased memory retention and total hippocampal CA1 pyramidal neuron numbers in SAMP8 mice, as compared to age-matched vehicle-dosed SAMP8 mice. In conclusion, liraglutide delayed or partially halted the progressive decline in memory function associated with hippocampal neuronal loss in a mouse model of pathological aging with characteristics of neurobehavioral and neuropathological impairments observed in early-stage sporadic AD.

Tau and Amyloid-β Cerebrospinal Fluid Biomarkers have Differential Relationships with Cognition in Mild Cognitive Impairment. - Malpas, Charles B; Saling, Michael M; Velakoulis, Dennis; Desmond, Patricia; O'Brien, Terence J (J Alzheimers Dis, 2015)
Alzheimer's disease (AD) is characterized by two primary pathologies: tau-related neurofibrillary tangles and the extracellular accumulation of amyloid-β (Aβ). The development of these pathologies is topologically distinct early in the disease, with Aβ beginning to accumulate as a diffuse, neocortical pathology, while tau-related pathology begins to form in mesial temporal regions. This study investigated the hypothesis that, by virtue of this distinction, there exist preferential associations between the primary pathologies and aspects of the cognitive phenotype. We investigated the relationship between cerebrospinal fluid (CSF) biomarkers for tau and Aβ pathologies with neurocognitive measures in 191 patients with mild cognitive impairment (MCI). Participants completed cognitive tests of new learning, information processing speed, and working memory. Separate regression models were computed and then followed up with mediation analyses to examine the predictive status of CSF biomarkers. The effect of Aβ on learning was mediated by phospho-tau (p = 0.008). In contrast, Aβ had a direct effect on information processing speed that was not mediated by phospho-tau (p = 0.59). No predictors were significant for working memory. This study provided evidence for a differential relationship of Aβ and phospho-tau pathologies on the neurocognitive phenotype of MCI. This supports the proposition that these primary AD pathologies maximally affect different aspects of cognition, and has potential implications for cognitive assessments and the use of biomarkers in disease-modifyingtherapeutic trials.

Advancing research diagnostic criteria for Alzheimer's disease: the IWG-2 criteria. - Dubois, Bruno; Feldman, Howard H; Jacova, Claudia; Hampel, Harald; Molinuevo, José Luis; Blennow, Kaj; DeKosky, Steven T; Gauthier, Serge; Selkoe, Dennis; Bateman, Randall; Cappa, Stefano; Crutch, Sebastian; et al. (Lancet Neurol, 2014)
In the past 8 years, both the International Working Group (IWG) and the US National Institute on Aging-Alzheimer's Association have contributed criteria for the diagnosis of Alzheimer's disease (AD) that better define clinical phenotypes and integrate biomarkers into the diagnostic process, covering the full staging of the disease. This Position Paper considers the strengths and limitations of the IWG research diagnostic criteria and proposes advances to improve the diagnostic framework. On the basis of these refinements, the diagnosis of AD can be simplified, requiring the presence of an appropriate clinical AD phenotype (typical or atypical) and a pathophysiological biomarker consistent with the presence of Alzheimer's pathology. We propose that downstream topographical biomarkers of the disease, such as volumetric MRI and fluorodeoxyglucose PET, might better serve in the measurement and monitoring of the course of disease. This paper also elaborates on the specific diagnostic criteria for atypical forms of AD, for mixed AD, and for the preclinical states of AD.
Keywords: Alzheimer Disease; Biomarkers; Humans; International Cooperation; Phenotype; Practice Guidelines as Topic; Societies, Medical

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Young blood reverses age-related impairments in cognitive function and synaptic plasticity in mice. - Villeda, Saul A; Plambeck, Kristopher E; Middeldorp, Jinte; Castellano, Joseph M; Mosher, Kira I; Luo, Jian; Smith, Lucas K; Bieri, Gregor; Lin, Karin; Berdnik, Daniela; Wabl, Rafael; Udeochu, Joe; et al. (Nat Med, 2014)
As human lifespan increases, a greater fraction of the population is suffering from age-related cognitive impairments, making it important to elucidate a means to combat the effects of aging. Here we report that exposure of an aged animal to young blood can counteract and reverse pre-existing effects of brain aging at the molecular, structural, functional and cognitive level. Genome-wide microarray analysis of heterochronic parabionts--in which circulatory systems of young and aged animals are connected--identified synaptic plasticity-related transcriptional changes in the hippocampus of aged mice. Dendritic spine density of mature neurons increased and synaptic plasticity improved in the hippocampus of aged heterochronic parabionts. At the cognitive level, systemic administration of young blood plasma into aged mice improved age-related cognitive impairments in both contextual fear conditioning and spatial learning and memory. Structural and cognitive enhancements elicited by exposure to young blood are mediated, in part, by activation of the cyclic AMP response element binding protein (Creb) in the aged hippocampus. Our data indicate that exposure of aged mice to young blood late in life is capable of rejuvenating synaptic plasticity and improving cognitive function.
Keywords: Age Factors; Aging; Animals; Blood Transfusion; Blotting, Western; Cell Line; Cognition Disorders; Cyclic AMP Response Element-Binding Protein; DNA Primers; Hippocampus; Immunohistochemistry; Mice; Mice, Inbred C57BL; Microarray Analysis; Neuronal Plasticity; Parabiosis; Polymerase Chain Reaction

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Tracking pathophysiological processes in Alzheimer's disease: an updated hypothetical model of dynamic biomarkers. - Jack, Clifford R; Knopman, David S; Jagust, William J; Petersen, Ronald C; Weiner, Michael W; Aisen, Paul S; Shaw, Leslie M; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Lesnick, Timothy G; Pankratz, Vernon S; et al. (Lancet Neurol, 2013)
In 2010, we put forward a hypothetical model of the major biomarkers of Alzheimer's disease (AD). The model was received with interest because we described the temporal evolution of AD biomarkers in relation to each other and to the onset and progression of clinical symptoms. Since then, evidence has accumulated that supports the major assumptions of this model. Evidence has also appeared that challenges some of our assumptions, which has allowed us to modify our original model. Refinements to our model include indexing of individuals by time rather than clinical symptom severity; incorporation of interindividual variability in cognitive impairment associated with progression of AD pathophysiology; modifications of the specific temporal ordering of some biomarkers; and recognition that the two major proteinopathies underlying AD biomarker changes, amyloid β (Aβ) and tau, might be initiated independently in sporadic AD, in which we hypothesise that an incident Aβ pathophysiology can accelerate antecedent limbic and brainstem tauopathy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Humans; Models, Biological; Nonlinear Dynamics; tau Proteins

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

A paravascular pathway facilitates CSF flow through the brain parenchyma and the clearance of interstitial solutes, including amyloid β. - Iliff, Jeffrey J; Wang, Minghuan; Liao, Yonghong; Plogg, Benjamin A; Peng, Weiguo; Gundersen, Georg A; Benveniste, Helene; Vates, G Edward; Deane, Rashid; Goldman, Steven A; Nagelhus, Erlend A; Nedergaard, Maiken (Sci Transl Med, 2012)
Because it lacks a lymphatic circulation, the brain must clear extracellular proteins by an alternative mechanism. The cerebrospinal fluid (CSF) functions as a sink for brain extracellular solutes, but it is not clear how solutes from the brain interstitium move from the parenchyma to the CSF. We demonstrate that a substantial portion of subarachnoid CSF cycles through the brain interstitial space. On the basis of in vivo two-photon imaging of small fluorescent tracers, we showed that CSF enters the parenchyma along paravascular spaces that surround penetrating arteries and that brain interstitial fluid is cleared along paravenous drainage pathways. Animals lacking the water channel aquaporin-4 (AQP4) in astrocytes exhibit slowed CSF influx through this system and a ~70% reduction in interstitial solute clearance, suggesting that the bulk fluid flow between these anatomical influx and efflux routes is supported by astrocytic water transport. Fluorescent-tagged amyloid β, a peptide thought to be pathogenic in Alzheimer's disease, was transported along this route, and deletion of the Aqp4 gene suppressed the clearance of soluble amyloid β, suggesting that this pathway may remove amyloid β from the central nervous system. Clearance through paravenous flow may also regulate extracellular levels of proteins involved with neurodegenerative conditions, its impairment perhaps contributing to the mis-accumulation of soluble proteins.
Keywords: Amyloid beta-Peptides; Animals; Aquaporin 4; Astrocytes; Biological Transport; Brain; Cerebral Ventricles; Cerebrospinal Fluid; Extracellular Fluid; Imaging, Three-Dimensional; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence, Multiphoton; Water

18F-THK523: a novel in vivo tau imaging ligand for Alzheimer's disease. - Fodero-Tavoletti, Michelle T; Okamura, Nobuyuki; Furumoto, Shozo; Mulligan, Rachel S; Connor, Andrea R; McLean, Catriona A; Cao, Diana; Rigopoulos, Angela; Cartwright, Glenn A; O'Keefe, Graeme; Gong, Sylvia; Adlard, Paul A; et al. (Brain, 2011)
While considerable effort has focused on developing positron emission tomography β-amyloid imaging radiotracers for the early diagnosis of Alzheimer's disease, no radiotracer is available for the non-invasive quantification of tau. In this study, we detail the characterization of (18)F-THK523 as a novel tau imaging radiotracer. In vitro binding studies demonstrated that (18)F-THK523 binds with higher affinity to a greater number of binding sites on recombinant tau (K18Δ280K) compared with β-amyloid(1-42) fibrils. Autoradiographic and histofluorescence analysis of human hippocampal serial sections with Alzheimer's disease exhibited positive THK523 binding that co-localized with immunoreactive tau pathology, but failed to highlight β-amyloid plaques. Micro-positron emission tomography analysis demonstrated significantly higher retention of (18)F-THK523 (48%; P < 0.007) in tau transgenic mice brains compared with their wild-type littermates or APP/PS1 mice. The preclinical examination of THK523 has demonstrated its high affinity and selectivity for tau pathology both in vitro and in vivo, indicating that (18)F-THK523 fulfils ligand criteria for human imaging trials.
Keywords: Alzheimer Disease; Analysis of Variance; Aniline Compounds; Animals; Autoradiography; Binding Sites; Brain; Female; Fluorodeoxyglucose F18; Humans; Immunohistochemistry; Male; Mice; Quinolines; Radiopharmaceuticals; tau Proteins

Caspase signalling controls microglia activation and neurotoxicity. - Burguillos, Miguel A; Deierborg, Tomas; Kavanagh, Edel; Persson, Annette; Hajji, Nabil; Garcia-Quintanilla, Albert; Cano, Josefina; Brundin, Patrik; Englund, Elisabet; Venero, Jose L; Joseph, Bertrand (Nature, 2011)
Activation of microglia and inflammation-mediated neurotoxicity are suggested to play a decisive role in the pathogenesis of several neurodegenerative disorders. Activated microglia release pro-inflammatory factors that may be neurotoxic. Here we show that the orderly activation of caspase-8 and caspase-3/7, known executioners of apoptotic cell death, regulate microglia activation through a protein kinase C (PKC)-δ-dependent pathway. We find that stimulation of microglia with various inflammogens activates caspase-8 and caspase-3/7 in microglia without triggering cell death in vitro and in vivo. Knockdown or chemical inhibition of each of these caspases hindered microglia activation and consequently reduced neurotoxicity. We observe that these caspases are activated in microglia in the ventral mesencephalon of Parkinson's disease (PD) and the frontal cortex of individuals with Alzheimer's disease (AD). Taken together, we show that caspase-8 and caspase-3/7 are involved in regulating microglia activation. We conclude that inhibition of these caspases could be neuroprotective by targeting the microglia rather than the neurons themselves.
Keywords: Alzheimer Disease; Animals; Caspase 3; Caspase 7; Caspase 8; Caspase Inhibitors; Caspases; Cell Death; Cells, Cultured; Dopamine; Enzyme Activation; Frontal Lobe; Gene Knockdown Techniques; Humans; Lipopolysaccharides; Mice; Microglia; Neostriatum; Neurotoxicity Syndromes; Parkinson Disease; Protein Kinase C-delta; Rats; Signal Transduction; Substantia Nigra; Toll-Like Receptor 4

Directed conversion of Alzheimer's disease patient skin fibroblasts into functional neurons. - Qiang, Liang; Fujita, Ryousuke; Yamashita, Toru; Angulo, Sergio; Rhinn, Herve; Rhee, David; Doege, Claudia; Chau, Lily; Aubry, Laetitia; Vanti, William B; Moreno, Herman; Abeliovich, Asa (Cell, 2011)
Directed conversion of mature human cells, as from fibroblasts to neurons, is of potential clinical utility for neurological disease modeling as well as cell therapeutics. Here, we describe the efficient generation of human-induced neuronal (hiN) cells from adult skin fibroblasts of unaffected individuals and Alzheimer's patients, using virally transduced transcription regulators and extrinsic support factors. hiN cells from unaffected individuals display morphological, electrophysiological, and gene expression profiles that typify glutamatergic forebrain neurons and are competent to integrate functionally into the rodent CNS. hiN cells from familial Alzheimer disease (FAD) patients with presenilin-1 or -2 mutations exhibit altered processing and localization of amyloid precursor protein (APP) and increased production of Aβ, relative to the source patient fibroblasts or hiN cells from unaffected individuals. Together, our findings demonstrate directed conversion of human fibroblasts to a neuronal phenotype and reveal cell type-selective pathology in hiN cells derived from FAD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Cell Transdifferentiation; Cells, Cultured; Fibroblasts; Humans; Neurons; Presenilin-1; Presenilin-2; Regenerative Medicine; Skin

Evidence for ordering of Alzheimer disease biomarkers. - Jack, Clifford R; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Aisen, Paul S; Trojanowski, John Q; Shaw, Leslie M; Bernstein, Matthew A; Petersen, Ronald C; Weiner, Michael W; Knopman, David S (Arch Neurol, 2011)
OBJECTIVE: To empirically assess the concept that Alzheimer disease (AD) biomarkers significantly depart from normality in a temporally ordered manner. DESIGN: Validation sample. SETTING: Multisite, referral centers. PARTICIPANTS: A total of 401 elderly participants in the Alzheimer's Disease Neuroimaging Initiative who were cognitively normal, who had mild cognitive impairment, or who had AD dementia. We compared the proportions of 3 AD biomarker values (the Aβ42 level in cerebrospinal fluid [CSF], the total tau level in CSF, and the hippocampal volume adjusted for intracranial volume [hereafter referred to as the adjusted hippocampal volume]) that were abnormal as cognitive impairment worsened. Cut points demarcating normal vs abnormal for each biomarker were established by maximizing diagnostic accuracy in independent autopsy samples. MAIN OUTCOME MEASURES: Three AD biomarkers (ie, the CSF Aβ42 level, the CSF total tau level, and the adjusted hippocampal volume). RESULTS: Within each clinical group of the entire sample (n = 401), the CSF Aβ42 level was abnormal more often than was the CSF total tau level or the adjusted hippocampal volume. Among the 298 participants with both baseline and 12-month data, the proportion of participants with an abnormal Aβ42 level did not change from baseline to 12 months in any group. The proportion of participants with an abnormal total tau level increased from baseline to 12 months in cognitively normal participants (P = .05) but not in participants with mild cognitive impairment or AD dementia. For 209 participants with an abnormal CSF Aβ42 level at baseline, the percentage with an abnormal adjusted hippocampal volume but normal CSF total tau level increased from baseline to 12 months in participants with mild cognitive impairment. No change in the percentage of MCI participants with an abnormal total tau level was seen between baseline and 12 months. CONCLUSIONS: A reduction in the CSF Aβ42 level denotes a pathophysiological process that significantly departs from normality (ie, becomes dynamic) early, whereas the CSF total tau level and the adjusted hippocampal volume are biomarkers of downstream pathophysiological processes. The CSF total tau level becomes dynamic before the adjusted hippocampal volume, but the hippocampal volume is more dynamic in the clinically symptomatic mild cognitive impairment and AD dementia phases of the disease than is the CSF total tau level.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Hippocampus; Humans; Longitudinal Studies; Male; Mild Cognitive Impairment; tau Proteins

Exercise training increases size of hippocampus and improves memory. - Erickson, Kirk I; Voss, Michelle W; Prakash, Ruchika Shaurya; Basak, Chandramallika; Szabo, Amanda; Chaddock, Laura; Kim, Jennifer S; Heo, Susie; Alves, Heloisa; White, Siobhan M; Wojcicki, Thomas R; Mailey, Emily; et al. (Proc Natl Acad Sci U S A, 2011)
The hippocampus shrinks in late adulthood, leading to impaired memory and increased risk for dementia. Hippocampal and medial temporal lobe volumes are larger in higher-fit adults, and physical activity training increases hippocampal perfusion, but the extent to which aerobic exercise training can modify hippocampal volume in late adulthood remains unknown. Here we show, in a randomized controlled trial with 120 older adults, that aerobic exercise training increases the size of the anterior hippocampus, leading to improvements in spatial memory. Exercise training increased hippocampal volume by 2%, effectively reversing age-related loss in volume by 1 to 2 y. We also demonstrate that increased hippocampal volume is associated with greater serum levels of BDNF, a mediator of neurogenesis in the dentate gyrus. Hippocampal volume declined in the control group, but higher preintervention fitness partially attenuated the decline, suggesting that fitness protects against volume loss. Caudate nucleus and thalamus volumes were unaffected by the intervention. These theoretically important findings indicate that aerobic exercise training is effective at reversing hippocampal volume loss in late adulthood, which is accompanied by improved memory function.
Keywords: Aged; Aging; Brain-Derived Neurotrophic Factor; Enzyme-Linked Immunosorbent Assay; Exercise; Hippocampus; Humans; Magnetic Resonance Imaging; Memory; Middle Aged; Organ Size; Space Perception

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide